The Cardiovascular Health Study: design and rationale. - Fried, L P; Borhani, N O; Enright, P; Furberg, C D; Gardin, J M; Kronmal, R A; Kuller, L H; Manolio, T A; Mittelmark, M B; Newman, A (Ann Epidemiol, 1991)
The Cardiovascular Health Study (CHS) is a population-based, longitudinal study of coronary heart disease and stroke in adults aged 65 years and older. The main objective of the study is to identify factors related to the onset and course of coronary heart disease and stroke. CHS is designed to determine the importance of conventional cardiovascular disease (CVD) risk factors in older adults, and to identify new risk factors in this age group, especially those that may be protective and modifiable. The study design called for enrollment of 1250 men and women in each of four communities: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Pittsburgh, Pennsylvania. Eligible participants were sampled from Medicare eligibility lists in each area. Extensive physical and laboratory evaluations were performed at baseline to identify the presence and severity of CVD risk factors such as hypertension, hypercholesterolemia and glucose intolerance; subclinical disease such as carotid artery atherosclerosis, left ventricular enlargement, and transient ischemia; and clinically overt CVD. These examinations in CHS permit evaluation of CVD risk factors in older adults, particularly in groups previously under-represented in epidemiologic studies, such as women and the very old. The first of two examination cycles began in June 1989. A second comprehensive examination will be repeated three years later. Periodic interim contacts are scheduled to ascertain and verify the incidence of CVD events, the frequency of recurrent events, and the sequellae of CVD.
Keywords: Aged; Cerebrovascular Disorders; Coronary Disease; Epidemiologic Methods; Female; Health Status; Humans; Longitudinal Studies; Male; Physical Examination; Research Design; Risk Factors; United States

Assessing the use of medications in the elderly: methods and initial experience in the Cardiovascular Health Study. The Cardiovascular Health Study Collaborative Research Group. - Psaty, B M; Lee, M; Savage, P J; Rutan, G H; German, P S; Lyles, M (J Clin Epidemiol, 1992)
The Cardiovascular Health Study (CHS), a cohort study of risk factors for coronary heart disease and stroke, recruited 5201 community-dwelling adults aged 65 years or older. To assess the prevalence of medication use at baseline, we used the method of medication inventory and transcribed information about drug names and doses from prescription bottles. Using a specially-written computer program, persons without a knowledge of drug nomenclature coded 10,511 (89%) of the 11,846 medicines entered. We compared the results of the medication inventory and answers to questions on specific medications for reliability and validity. The use of beta-blockers and beta-agonists assessed by the method of medication inventory, but not by the method of directed recall, was associated with a significant effect on mean heart rate. Among 5197 participants with medication data, 76.1% were taking at least one medicine, and the mean number of drugs per person was 2.28. Among those with a reported history of high blood pressure, participants with cardiovascular disease (CVD) were more likely to be treated, and they were more likely to be taking beta-blockers and calcium-channel blockers than those without CVD. Daily aspirin use was also more common among those with CVD (30.5% of women and 43.2% of men) than among those without CVD (14.0% of women and 14.0% of men). The prevalence of post-menopausal estrogen use differed significantly among the four clinical centers (range = 5.5%-22.5% of women). We conclude that this method of assessing medications was easy to use and provided estimates of exposure to drugs that may affect risk of cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Cerebrovascular Disorders; Coronary Disease; Data Collection; Drug Utilization; Female; Humans; Male; Prospective Studies; Risk Factors; United States

Distribution and correlates of sonographically detected carotid artery disease in the Cardiovascular Health Study. The CHS Collaborative Research Group. - O'Leary, D H; Polak, J F; Kronmal, R A; Kittner, S J; Bond, M G; Wolfson, S K; Bommer, W; Price, T R; Gardin, J M; Savage, P J (Stroke, 1992)
BACKGROUND AND PURPOSE: This article describes the prevalence of extracranial carotid atherosclerosis assessed by ultrasonography, its association with risk factors, and its relation to symptomatic coronary disease and stroke in men and women aged > or = 65 years. METHODS: Maximum percent stenosis, maximum common carotid artery wall thickness, and maximum internal carotid artery wall thickness were assessed using duplex ultrasound in 5,201 men and women aged > or = 65 years in the Cardiovascular Health Study, a study of the risk factors and natural history of cardiovascular disease in the elderly. Existing coronary disease and stroke were assessed by physical examination and participant history. RESULTS: Detectable carotid stenosis was present in 75% of men and 62% of women, although the prevalence of > or = 50% stenosis was low, 7% in men and 5% in women. Maximum stenosis and maximum wall thickness measurements increased with age and were uniformly greater at all ages in men than in women (p < 0.00001). Established risk factors for atherosclerosis (hypertension, smoking, diabetes) and indications of vascular disease (left ventricular hypertrophy, major electrocardiographic abnormality, bruits, and history of heart disease or stroke) related to all three carotid artery measures in the elderly. Of the three ultrasound measures, the best correlate for a history of coronary disease was maximum internal carotid artery wall thickness. For stroke the best correlate was common carotid artery wall thickness. Multiple logistic regression models of prevalent coronary heart disease and stroke that included the ultrasound findings indicated, after adjustment for age and sex, that maximum internal wall thickness and maximum common carotid wall thickness were significant correlates of both. Maximum stenosis did not add significantly to the correlation. CONCLUSIONS: In the elderly the incidence of carotid atherosclerosis was high, although the frequency of severe disease was low. The prevalence and severity of carotid atherosclerosis continued to increase with age even in the late decades of life, and more disease was found in men than in women at all ages. Known risk factors for atherosclerosis continued to relate to carotid abnormalities in the later decades of life, both in symptomatic and asymptomatic subjects.
Keywords: Aged; Arteriosclerosis; Cardiomegaly; Carotid Artery Diseases; Cerebrovascular Disorders; Coronary Disease; Female; Humans; Male; Medical Records; Prevalence; Regression Analysis; Risk Factors; Ultrasonography

The distribution of coagulation factors VII and VIII and fibrinogen in adults over 65 years. Results from the Cardiovascular Health Study. - Tracy, R P; Bovill, E G; Fried, L P; Heiss, G; Lee, M H; Polak, J F; Psaty, B M; Savage, P J (Ann Epidemiol, 1992)
The Cardiovascular Health Study (CHS) was designed to examine cardiovascular disease and its risk factors in older adults. We report here the distributions of the coagulation factors fibrinogen, factor VII, and factor VIII in a population-based cohort of men and women 65 years or older. In other studies of middle-aged individuals, these factors were shown to be associated with cardiovascular risk. In the CHS cohort, all three factors were elevated, compared to levels reported in middle-aged individuals, and fibrinogen and factor VIII values were higher in each successive age group; factor VII values, in contrast, declined slightly with age in the CHS cohort. Compared to white subjects, blacks had higher values for fibrinogen and factor VIII and lower values for factor VII. While women had markedly higher values for factor VII and factor VIII than men at all ages in the CHS, mean fibrinogen values were not different between men and women.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Cardiovascular Diseases; Cohort Studies; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Male; Middle Aged; Risk Factors

Echocardiographic design of a multicenter investigation of free-living elderly subjects: the Cardiovascular Health Study. - Gardin, J M; Wong, N D; Bommer, W; Klopfenstein, H S; Smith, V E; Tabatznik, B; Siscovick, D; Lobodzinski, S; Anton-Culver, H; Manolio, T A (J Am Soc Echocardiogr, 1992)
The Framingham study has shown by M-mode echocardiography that left ventricular hypertrophy is a powerful, independent predictor for the development of coronary heart disease and that increased left atrial dimension has been associated with an increased risk of stroke. No previous population-based study has evaluated the risk factor correlates and predictive value for coronary heart disease and stroke of two-dimensional and Doppler, as well as M-mode, echocardiography. The Cardiovascular Health Study is a multi-year prospective epidemiologic study of 5201 men and women older than 65 recruited from four geographic sites in the United States. The main objectives of incorporating echocardiography were to determine whether echocardiographic indices, or changes in these indices, are (1) correlated with traditional risk factors for coronary heart disease and stroke; and (2) independent predictors of morbidity and mortality for coronary heart disease and stroke. Echocardiographic measurements of interest include those related to global and segmental left ventricular systolic and diastolic structure and function and left atrial size. For each subject, a baseline echocardiogram was recorded in super-VHS tape using a standard protocol and equipment. All studies were sent to a reading center where images were digitized and measurements were made using customized computer algorithms. Calculated data and images were stored on optical disks to facilitate retrieval and future comparisons in longitudinal studies. A second echocardiogram is scheduled in year 7, with a goal of determining whether changes in cardiac anatomy or function over a 5-year period are important predictors of morbidity or mortality from coronary heart disease and stroke. Quality control measures included standardized training of echocardiography technicians and readers, technician observation by a trained echocardiographer, periodic blind duplicate readings with reader review sessions, phantom studies, and quality control adults.
Keywords: Allied Health Personnel; Cerebrovascular Disorders; Coronary Disease; Echocardiography; Echocardiography, Doppler; Humans; Prospective Studies; Quality Control; Risk Factors; United States

Eligibility for cholesterol referral in community-dwelling older adults. The Cardiovascular Health Study. - Manolio, T A; Furberg, C D; Wahl, P W; Tracy, R P; Borhani, N O; Gardin, J M; Fried, L P; O'Leary, D H; Kuller, L H (Ann Intern Med, 1992)
OBJECTIVES: To assess the proportion of community-dwelling adults aged 65 years or older who are eligible for referral for lipoprotein analysis and intervention according to the National Cholesterol Education Program (NCEP) guidelines. DESIGN: Cross-sectional study based on examinations and questionnaires collected in 1989 and 1990. SETTING: Four communities in the U.S. in the Cardiovascular Health Study (CHS), a study of risk factors for heart disease and stroke in older adults. PARTICIPANTS: A sample of 4810 men and women ages 65 to 100 randomly selected and recruited from Health Care Financing Administration Medicare eligibility lists for the four communities; not institutionalized, not wheelchair-bound, not currently receiving therapy for cancer, not currently taking lipid-lowering medications, and not having eaten in the preceding 9 hours. MEASUREMENTS: Total cholesterol and lipoprotein analysis measured in all participants. RESULTS: Total cholesterol levels were less than 5.17 mmol/L (200 mg/dL) in 37% of participants, 5.17 to 6.19 mmol/L (200 to 239 mg/dL) in 39%, and 6.20 mmol/L (240 mg/dL) or greater in 24%. Compared with their counterparts, older participants, especially those over 80 years of age, were more likely to have levels below 5.17 mmol/L, as were men, nonwhites, and those with coronary heart disease or two or more coronary heart disease risk factors (P less than 0.008 for all values). Based on this screening measurement, 2174 participants were eligible for lipoprotein analysis, 80% were eligible for dietary or drug therapy using NCEP guidelines. Overall, 46% of CHS participants were eligible for lipoprotein analysis and 36% for intervention by NCEP guidelines, based on a single cholesterol measurement. CONCLUSION: A substantial proportion of older adults in this community sample were eligible for lipoprotein analysis and intervention. Prospective studies of elderly persons are needed to determine the risk for incident coronary heart disease according to NCEP classifications and the benefits of lipid-lowering treatments in persons in this age group so that intervention strategies may best be targeted to an appropriately high-risk group.
Keywords: Age Factors; Aged; Aged, 80 and over; Cerebrovascular Disorders; Cholesterol, LDL; Coronary Disease; Eligibility Determination; Female; Humans; Hypercholesterolemia; Longitudinal Studies; Male; Primary Prevention; Referral and Consultation; Risk Factors; United States

Isolated systolic hypertension and subclinical cardiovascular disease in the elderly. Initial findings from the Cardiovascular Health Study. - Psaty, B M; Furberg, C D; Kuller, L H; Borhani, N O; Rautaharju, P M; O'Leary, D H; Bild, D E; Robbins, J; Fried, L P; Reid, C (JAMA, 1992)
OBJECTIVE: To assess the association between isolated systolic hypertension (ISH) and subclinical disease in adults aged 65 years and above. DESIGN: Medicare eligibility lists were used to obtain a representative sample of 5201 community-dwelling elderly persons for the Cardiovascular Health Study, a National Heart, Lung, and Blood Institute--sponsored cohort study of risk factors for coronary heart disease and stroke. In this cross-sectional analysis of baseline data, we excluded 3012 participants who were receiving antihypertensive medications, had clinical cardiovascular disease, or had a diastolic blood pressure of at least 90 mm Hg. MAIN OUTCOME MEASURES: For electrocardiogram: myocardial infarction, left ventricular hypertrophy, and left ventricular mass as measures of myocardial damage and strain; for echocardiography: left ventricular mass, fractional shortening, and Doppler flow velocities as measures of cardiac systolic and diastolic function; and for carotid sonography: carotid arterial intima-media thickness as a measure of atherosclerosis. RESULTS: Among the 2189 men and women in this analysis, 195 (9%) had ISH (systolic blood pressure, greater than or equal to 160 mm Hg) and 596 (23%) had borderline ISH (systolic blood pressure, 140 to 159 mm Hg). Systolic blood pressure was associated with myocardial infarction by electrocardiogram (P = .02). Borderline and definite ISH were strongly associated with left ventricular mass (P less than .001). While there was little association with cardiac systolic function, borderline and definite ISH were associated with cardiac diastolic function (P less than .001). Isolated systolic hypertension was also strongly associated with increased intima-media thickness of the carotid artery (P less than .001). CONCLUSIONS: While cohort analyses of future repeated measures will provide a better assessment of risk, both borderline and definite ISH were strongly related to a variety of measures of subclinical disease in elderly men and women.
Keywords: Aged; Aged, 80 and over; Cardiomegaly; Cardiovascular Diseases; Carotid Artery Diseases; Cerebrovascular Disorders; Coronary Disease; Cross-Sectional Studies; Echocardiography; Electrocardiography; Female; Humans; Hypertension; Male; Myocardial Infarction; Prospective Studies; Risk Factors; Systole

Major electrocardiographic abnormalities in persons aged 65 years and older (the Cardiovascular Health Study). Cardiovascular Health Study Collaborative Research Group. - Furberg, C D; Manolio, T A; Psaty, B M; Bild, D E; Borhani, N O; Newman, A; Tabatznik, B; Rautaharju, P M (Am J Cardiol, 1992)
Electrocardiographic abnormalities are often found in older patients, but their prevalence in free-living elderly populations is not well-defined. In addition, the clinical significance of many of these abnormalities is uncertain. The prevalence of major electrocardiographic abnormalities was determined in 5,150 adults aged greater than or equal to 65 years from the Cardiovascular Health Study--a study of risk factors for stroke and coronary heart disease in the elderly. Ventricular conduction defects, major Q/QS waves, left ventricular hypertrophy, isolated major ST-T-wave abnormalities, atrial fibrillation and first-degree atrioventricular block were collectively categorized as major electrocardiographic abnormalities. Prevalence of any major electrocardiographic abnormality was 29% in the entire cohort, 19% among 2,413 participants who reported no history of coronary artery disease or systemic hypertension, and 37% among 2,737 participants with a history of coronary artery disease or hypertension. Prevalence of major electrocardiographic abnormalities was higher in men than in women regardless of history, and tended to increase with age. Major Q/QS waves were found in 5.2%, and more than half were in those who did not report a previous myocardial infarction. Major electrocardiographic abnormalities are common in elderly men and women irrespective of the history of heart disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Arrhythmias, Cardiac; Chi-Square Distribution; Electrocardiography; Female; Heart Diseases; Humans; Logistic Models; Male; Prevalence; Risk Factors; Sex Factors; United States

Orthostatic hypotension in older adults. The Cardiovascular Health Study. CHS Collaborative Research Group. - Rutan, G H; Hermanson, B; Bild, D E; Kittner, S J; LaBaw, F; Tell, G S (Hypertension, 1992)
The purpose of the present study was to assess the prevalence of orthostatic hypotension and its associations with demographic characteristics, cardiovascular risk factors and symptomatology, prevalent cardiovascular disease, and selected clinical measurements in the Cardiovascular Health Study, a multicenter, observational, longitudinal study enrolling 5,201 men and women aged 65 years and older at initial examination. Blood pressure measurements were obtained with the subjects in a supine position and after they had been standing for 3 minutes. The prevalence of asymptomatic orthostatic hypotension, defined as 20 mm Hg or greater decrease in systolic or 10 mm Hg or greater decrease in diastolic blood pressure, was 16.2%. This prevalence increased to 18.2% when the definition also included those in whom the procedure was aborted due to dizziness upon standing. The prevalence was higher at successive ages. Orthostatic hypotension was associated significantly with difficulty walking (odds ratio, 1.23; 95% confidence interval, 1.02, 1.46), frequent falls (odds ratio, 1.52; confidence interval, 1.04, 2.22), and histories of myocardial infarction (odds ratio, 1.24; confidence interval, 1.02, 1.50) and transient ischemic attacks (odds ratio, 1.68; confidence interval, 1.12, 2.51). History of stroke, angina pectoris, and diabetes mellitus were not associated significantly with orthostatic hypotension. In addition, orthostatic hypotension was associated with isolated systolic hypertension (odds ratio, 1.35; confidence interval, 1.09, 1.68), major electrocardiographic abnormalities (odds ratio, 1.21; confidence interval, 1.03, 1.42), and the presence of carotid artery stenosis based on ultrasonography (odds ratio, 1.67; confidence interval, 1.23, 2.26). Orthostatic hypotension was negatively associated with weight. We conclude that orthostatic hypotension is common in the elderly and increases with advancing age. It is associated with cardiovascular disease, particularly those manifestations measured objectively, such as carotid stenosis. It is associated also with general neurological symptoms, but this link may not be causal. Differences in prevalence of and associations with orthostatic hypotension in the present study compared with others are largely attributed to differences in population characteristics and methodology.
Keywords: Aged; Aging; Dementia; Demography; Female; Health Status; Humans; Hypotension, Orthostatic; Male; Multivariate Analysis; Nervous System Diseases; Prevalence; Risk Factors

Ankle-arm index as a marker of atherosclerosis in the Cardiovascular Health Study. Cardiovascular Heart Study (CHS) Collaborative Research Group. - Newman, A B; Siscovick, D S; Manolio, T A; Polak, J; Fried, L P; Borhani, N O; Wolfson, S K (Circulation, 1993)
BACKGROUND: Peripheral arterial disease measured noninvasively by the ankle-arm index (AAI) is common in older adults, largely asymptomatic, and associated with clinically manifest cardiovascular disease (CVD). The criteria for an abnormal AAI have varied in previous studies. To determine whether there is an inverse dose-response relation between the AAI and clinical CVD, subclinical disease, and risk factors, we examined the relation of the AAI to cardiovascular risk factors, other noninvasive measures of subclinical atherosclerosis using carotid ultrasound, echocardiography and electrocardiography, and clinical CVD. METHODS AND RESULTS: The AAI was measured in 5084 participants > or = 65 years old at the baseline examination of the Cardiovascular Health Study. All subjects had detailed assessment of prevalent CVD, measures of cardiovascular risk factors, and noninvasive measures of disease. Participants were stratified by baseline clinical CVD status and AAI (< 0.8, > or = 0.8 to < 0.9, > or = 0.9 to < 1.0, > or = 1.0 to < 1.5). Analyses tested for a dose-response relation of the AAI with clinical CVD, risk factors, and subclinical disease. The cumulative frequency of a low AAI was 7.4% of participants < 0.8, 12.4% < 0.9, and 23.6% < 1.0. participants with an AAI < 0.8 were more than twice as likely as those with an AAI of 1.0 to 1.5 to have a history of myocardial infarction, angina, congestive heart failure, stroke, or transient ischemic attack (all P < .01). In participants free of clinical CVD at baseline, the AAI was inversely related to history of hypertension, history of diabetes, and smoking, as well as systolic blood pressure, serum creatinine, fasting glucose, fasting insulin, measures of pulmonary function, and fibrinogen level (all P < .01). Risk factor associations with the AAI were similar in men and women free of CVD except for serum total and low-density lipoprotein cholesterol, which were inversely associated with AAI level only in women. Risk factors associated with an AAI of < 1.0 in multivariate analysis included smoking (odds ratio [OR], 2.55), history of diabetes (OR, 3.84), increasing age (OR, 1.54), and nonwhite race (OR, 2.36). In the 3372 participants free of clinical CVD, other noninvasive measures of subclinical CVD, including carotid stenosis by duplex scanning, segmental wall motion abnormalities by echocardiogram, and major ECG abnormalities were inversely related to the AAI (all P < .01). CONCLUSIONS: There was an inverse dose-response relation of the AAI with CVD risk factors and subclinical and clinical CVD among older adults. The lower the AAI, the greater the increase in CVD risk; however, even those with modest, asymptomatic reductions in the AAI (0.8 to 1.0) appear to be at increased risk of CVD.
Keywords: Aged; Ankle; Arm; Arteriosclerosis; Blood Pressure Determination; Cardiovascular Diseases; Female; Humans; Male; Multivariate Analysis; Peripheral Vascular Diseases; Population Surveillance; Predictive Value of Tests; Risk Factors

Associations of postmenopausal estrogen use with cardiovascular disease and its risk factors in older women. The CHS Collaborative Research Group. - Manolio, T A; Furberg, C D; Shemanski, L; Psaty, B M; O'Leary, D H; Tracy, R P; Bush, T L (Circulation, 1993)
BACKGROUND: Postmenopausal estrogen replacement therapy has been associated with favorable levels of cardiovascular disease risk factors, but these associations and the relations between estrogen use and subclinical disease have not been examined in large samples of older women. METHODS AND RESULTS: Present and past estrogen use was ascertained in 2955 women > or = 65 years old in the Cardiovascular Health Study, a study of risk factors for coronary heart disease and stroke in the elderly. Present estrogen use was reported by 12% of these women and past use by an additional 26.5%. Estrogen use (past or present) was strongly associated with lower low-density lipoprotein cholesterol, fibrinogen, glucose, insulin, obesity, and age and higher high-density lipoprotein cholesterol and socioeconomic status (all P < .0001). Estrogen users also had lower levels of subclinical disease as measured by carotid intimal-medial thickness, carotid stenosis grade, ECG left ventricular mass, and Doppler mitral peak flow velocities (each P < .02). Relations were similar in younger and older women (65 to 74 versus > or = 75 years) and smokers and nonsmokers and were unchanged after women with poor medication compliance were excluded. After adjustment for other factors, estrogen use was associated with decreased carotid wall thickness, although this association was of borderline significance after further adjustment for lipids. CONCLUSIONS: Postmenopausal estrogen use in this sample of older women was associated with favorable cardiovascular disease risk factor profiles and with lower measures of subclinical disease. These findings suggest that postmenopausal estrogen use may be associated with lower risk of cardiovascular disease in women well into the eighth decade of life.
Keywords: Aged; Aging; Cardiovascular Diseases; Carotid Arteries; Carotid Stenosis; Electrocardiography; Estrogen Replacement Therapy; Female; Heart; Heart Ventricles; Humans; Patient Compliance; Risk Factors; Smoking; Ultrasonography

Epidemiology of low cholesterol levels in older adults. The Cardiovascular Health Study. - Manolio, T A; Ettinger, W H; Tracy, R P; Kuller, L H; Borhani, N O; Lynch, J C; Fried, L P (Circulation, 1993)
BACKGROUND: Low cholesterol levels have been associated with increased mortality from stroke, cancer, and other noncardiovascular diseases, but the reasons for this association remain unclear. One explanation is that persons with low cholesterol levels have early or occult disease that eventually leads to their deaths. METHODS AND RESULTS: This possibility was explored in 2,091 men and 2,714 women 65-100 years old in the Cardiovascular Health Study, a multicenter observational study of risk factors for heart disease and stroke in older adults. Cholesterol levels < or = 160 mg/dL were present in 11.6% of men and 3.7% of women and increased in prevalence with age. After adjustment for age, total cholesterol levels in this range were associated with a twofold increased prevalence of treated diabetes in men and women and with a twofold increased prevalence of cancer diagnosed in the preceding 5 years in women only. Low cholesterol was also associated with lower levels of hemoglobin, albumin, and factor VII, suggesting a link with hepatic synthetic function. On multivariate analysis, factors most strongly associated with low cholesterol levels in men and women were decreased factor VII levels, decreased albumin, and diabetes. CONCLUSIONS: Cross-sectional associations with low cholesterol levels differ by sex and suggest poorer health by some measures. The observed relations with treated diabetes and impaired hepatic synthetic function should be examined for risk of mortality in longitudinal data from this and other observational studies.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Cardiovascular Physiological Phenomena; Cholesterol; Female; Health Status; Humans; Longitudinal Studies; Male; Prevalence; Probability; Regression Analysis; Risk Factors

Smoking and lung function in elderly men and women. The Cardiovascular Health Study. - Higgins, M W; Enright, P L; Kronmal, R A; Schenker, M B; Anton-Culver, H; Lyles, M (JAMA, 1993)
OBJECTIVE: To investigate relationships between cigarette smoking and pulmonary function in elderly men and women. DESIGN: Cross-sectional analysis of baseline data from a prospective, population-based study of risk factors, preclinical, and overt cardiovascular and pulmonary disease. SETTING: Defined communities in Forsyth County, North Carolina; Pittsburgh, Pa; Sacramento County, California; and Washington County, Maryland. POPULATION: A total of 5201 noninstitutionalized men and women 65 years of age and older. MAIN OUTCOME MEASURES: Pulmonary function; means of forced expiratory volume in 1 second (FEV1) and forced vital capacity and prevalence of low FEV1 levels. RESULTS: Prevalence of cigarette smoking was 10% to 20% and higher in women than men and in blacks than whites. Forced vital capacity and FEV1 levels were related positively to height and white race and negatively to age and waist girth. Age- and height-adjusted FEV1 means were 23% and 18% lower in male and female current smokers, respectively, than in never smokers but not reduced in never smokers currently living with a smoker. Smokers who quit before age 40 years had FEV1 levels similar to never smokers, but FEV1 levels were lower by 7% and 14% in smokers who quit at ages 40 to 60 years and older than 60 years, respectively. Lung function was related inversely to pack-years of cigarette use. Prevalence rates of impaired lung function were highest in current smokers and lowest in never smokers. Regression coefficients for the smoking variables were smaller in persons without cardiovascular or respiratory conditions than in the total cohort. CONCLUSIONS: Cigarette smoking is associated with reduced pulmonary function in elderly men and women. However, smokers who quit, even after age 60 years, have better pulmonary function than continuing smokers.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Anthropometry; Cardiovascular Diseases; Cross-Sectional Studies; European Continental Ancestry Group; Female; Forced Expiratory Volume; Humans; Lung Diseases; Male; Prevalence; Prospective Studies; Reference Values; Respiratory Function Tests; Risk Factors; Smoking; United States; Vital Capacity

Cardiac arrhythmias on 24-h ambulatory electrocardiography in older women and men: the Cardiovascular Health Study. - Manolio, T A; Furberg, C D; Rautaharju, P M; Siscovick, D; Newman, A B; Borhani, N O; Gardin, J M; Tabatznik, B (J Am Coll Cardiol, 1994)
OBJECTIVES: This study describes the prevalence and correlates of cardiac arrhythmias in older persons. BACKGROUND: Cardiac arrhythmias are frequent in selected samples of elderly persons, but their prevalence and association with cardiovascular disease and its risk factors have not been examined in a large population-based sample. METHODS: In 1,372 participants in the Cardiovascular Health Study, a population-based study of cardiovascular disease risk factors, 24-h ambulatory electrocardiography was performed. RESULTS: Serious arrhythmias, such as sustained ventricular tachycardia and complete atrioventricular block, were uncommon, but brief episodes of ventricular tachycardia (> or = 3 consecutive ventricular depolarizations) were detected in 4.3% of women and 10.3% of men. Ventricular arrhythmias as a group (excluding ectopic beats < 15/h) were more common in men than in women but were not significantly associated with age. The same patterns were true for bradycardia/conduction blocks. Supraventricular arrhythmias as a group (excluding ectopic beats < 15/h), in contrast, did not differ by gender but were strongly associated with increased age. Multivariate analyses showed associations with arrhythmias to differ by gender, with only one association (increased age and supraventricular arrhythmias) present in both women and men. Ventricular arrhythmias, particularly in men, were associated with a higher prevalence of cardiovascular disease and its risk factors and with subclinical disease, as measured by increased left ventricular mass and impaired left ventricular function. CONCLUSIONS: Arrhythmias are common in the elderly, and their association with cardiovascular disease differs by gender. Although risk related to arrhythmias can only be determined by prospective study, such studies should have adequate power to examine potential gender differences in associations.
Keywords: Aged; Aged, 80 and over; Arrhythmias, Cardiac; Cardiovascular Diseases; Circadian Rhythm; Electrocardiography, Ambulatory; Female; Humans; Logistic Models; Longitudinal Studies; Male; Prevalence; Risk Factors; Sex Factors

Eating patterns of community-dwelling older adults: the Cardiovascular Health Study. - Kumanyika, S; Tell, G S; Shemanski, L; Polak, J; Savage, P J (Ann Epidemiol, 1994)
We analyzed eating patterns of 4643 adults (1988 men and 2655 women) aged 65 years and older at the time of their enrollment in the Cardiovascular Health Study. Diet was assessed with a qualitative, picture-sort food frequency questionnaire along with supplemental questions on other eating pattern variables. Consumption of high fat foods and low fiber foods was more frequent in older participants, men, minorities, and persons with body mass index > or = 30 kg/m2 and less common among persons who reported following self-prescribed or medically prescribed special diets. Few associations of consumption of specific food groups with disease status were identified. Participants with coronary heart disease, diabetes, hypertension, and cardiovascular disease were significantly more likely to report following a special diet and using low-calorie or low-sodium food products, however. Although the percentage of participants with prevalent disease who reported following special diets was relatively low from a clinical perspective, it was sufficiently high to suggest that controlling for dietary modifications may be important when attempting to identify associations of diet with prevalent disease in older populations.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cardiovascular Diseases; Cerebrovascular Disorders; Demography; Diet; Diet Surveys; Diet, Sodium-Restricted; Female; Humans; Male; Minority Groups; Prospective Studies; Risk Factors; Sex Factors

Magnetic resonance abnormalities and cardiovascular disease in older adults. The Cardiovascular Health Study. - Manolio, T A; Kronmal, R A; Burke, G L; Poirier, V; O'Leary, D H; Gardin, J M; Fried, L P; Steinberg, E P; Bryan, R N (Stroke, 1994)
BACKGROUND AND PURPOSE: Cerebral magnetic resonance imaging often detects abnormalities whose significance is unknown. The prevalence and correlates of findings such as ventricular enlargement, sulcal widening, and increased white matter signal intensity were examined in 303 men and women aged 65 to 95 years participating in a multicenter study of cardiovascular disease. METHODS: Cerebral magnetic resonance imaging was performed and interpreted according to a standard protocol, and findings were correlated with measures of cardiovascular disease and its risk factors. RESULTS: Measures of cerebral atrophy increased with age and were greater in men than in women (each P < .01). Ventricular enlargement and sulcal widening were associated with prior stroke, hypertension, diabetes, and white race (each P < .03). Extent of white matter hyperintensity was associated with age, prior stroke, hypertension, and use of diuretics (each P < .004). On multivariate analysis, age, male gender, white race, and prior stroke retained strong associations with increased ventricular and sulcal scores. After adjustment for age, prior stroke, and other risk factors, white matter hyperintensity was associated with atherosclerosis as measured by increased internal carotid artery thickness on ultrasound. CONCLUSIONS: Cerebral atrophy and white matter hyperintensity are common in the elderly and are associated with age, prior stroke, and known cardiovascular risk factors. Though these findings have been suggested to represent normal aging, their wide variability and associations with cardiovascular disease argue against their inevitability with advancing age and support the need to identify modifiable risk factors for these abnormalities.
Keywords: Age Factors; Aged; Aged, 80 and over; Analysis of Variance; Atrophy; Brain; Cerebral Ventricles; Cerebrovascular Disorders; Female; Humans; Magnetic Resonance Imaging; Male; Regression Analysis; Risk Factors; Sex Factors

A method for using MR to evaluate the effects of cardiovascular disease on the brain: the cardiovascular health study. - Bryan, R N; Manolio, T A; Schertz, L D; Jungreis, C; Poirier, V C; Elster, A D; Kronmal, R A (AJNR Am J Neuroradiol, 1994)
PURPOSE: To do a pilot study for the Cardiovascular Health Study (a population-based, longitudinal study of coronary heart disease and stroke in adults 65 years of age and older designed to identify risk factors related to cerebrovascular disease, particularly stroke): (a) to determine the feasibility of adding brain MR to the full-scale study; (b) to evaluate the reliability of standardized MR image interpretation in a multicenter study; and (c) to compare the prevalence of stroke determined by MR with that by clinical history. METHODS: Protocol-defined MR studies were performed in 100 subjects with clinical histories of stroke and 203 subjects without reported histories of stroke. MR scans were independently evaluated by two trained neuroradiologists for the presence of small (< or = 3 mm) and large (> 3 mm) "infarctlike" lesions. The sizes of the cerebral sulci and lateral ventricles and the extent of white matter disease were graded on a scale of 0 to 9. RESULTS: Eighty percent of the Cardiovascular Health Study participants who were invited to undergo MR studies agreed to do so; 95% of those agreeing to the procedure successfully completed the exams. Intrareader and interreader reliability of infarctlike lesion identification was high for large lesions (kappa, 0.71 and 0.78, respectively) but not for small lesions (kappa, 0.71 and 0.32, respectively). Relaxed intrareader and interreader kappa scores for sulcal and ventricular sizes and extent of white matter disease were greater than 0.8 MR evidence of infarctlike lesions was present in 77% of the participants with histories of stroke but was also present in 23% of the participants without clinical histories of stroke. Seventy-nine percent of the infarctlike lesions were larger than 3 mm. CONCLUSIONS: This preliminary study indicates that a large, prospective, epidemiologic study of elderly subjects using MR scans of the brain for identification of cerebrovascular disease is feasible and that the interpretative results are reproducible, and suggests that MR evidence of stroke is more prevalent than reported clinical history of stroke.
Keywords: Aged; Brain; Cerebral Infarction; Cerebral Ventricles; Cerebrovascular Disorders; Cohort Studies; Coronary Disease; Cross-Sectional Studies; Diagnosis, Differential; Feasibility Studies; Female; Humans; Image Interpretation, Computer-Assisted; Incidence; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mass Screening; Observer Variation; Pilot Projects; Prospective Studies; Risk Factors; United States

Physical disability in older adults: a physiological approach. Cardiovascular Health Study Research Group. - Fried, L P; Ettinger, W H; Lind, B; Newman, A B; Gardin, J (J Clin Epidemiol, 1994)
Measures of physical function have been developed primarily to assess health status, prognosis, and service needs. They are now, increasingly, being used as outcome measures in studies seeking to determine the causes of disability. However, the extent to which these standardized measures, as they currently are constituted, are meaningful for the evaluation of underlying pathophysiology is not defined. To assess evidence for an etiologic rationale for these measures, we evaluated self-report of difficulty in physical function in the Cardiovascular Health Study, a study of 5201 men and women 65 years and older in four U.S. communities. We determined (by factor analysis) that self-reported difficulty with each of 17 tasks of daily life aggregates in four groups; i.e. difficulty in one task is associated with having difficulty in the other tasks in the group. These groups include (1) activities primarily dependent on mobility and exercise tolerance; (2) complex activities heavily dependent on cognition and sensory input; (3) selected basic self-care activities; and (4) upper extremity activities. Groups 2 and 3 are similar, but not identical, to Instrumental Activities of Daily Living (IADL) and Activities of Daily Living (ADL), respectively. We then tested whether these groupings were associated with different underlying impairments. Multiple logistic regression analyses indicate that there are constellations of physiologic and disease characteristics significantly (p < 0.01) associated with difficulty in each of these four groups of activities, among 15 chronic diseases and conditions ascertained. Some diseases are uniquely associated with difficulty in one group of tasks; some overlap, and are associated with 2, 3 or 4 groups of tasks. The associations found with difficulty in performing tasks in groups 2 and 3 were frequently stronger than those with the larger groups of ADL or IADL tasks, suggesting increased specificity of associations found with these new groupings. These results suggest that re-grouping of tasks of daily life may provide a more refined physiologically-based outcome measure for use in evaluating causes of disability. The ability to define risk factors for disability may be enhanced by choosing outcome measures with a demonstrated physiologic rationale.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic Disease; Disabled Persons; Factor Analysis, Statistical; Female; Geriatric Assessment; Humans; Logistic Models; Male; Outcome Assessment (Health Care); Risk Factors; Sex Factors; Socioeconomic Factors; United States

Prevalence of subclinical atherosclerosis and cardiovascular disease and association with risk factors in the Cardiovascular Health Study. - Kuller, L; Borhani, N; Furberg, C; Gardin, J; Manolio, T; O'Leary, D; Psaty, B; Robbins, J (Am J Epidemiol, 1994)
The prevalence of subclinical atherosclerosis and cardiovascular disease was evaluated among the 5,201 adults aged > or = 65 years in four communities participating in the Cardiovascular Health Study from June 1989 through May 1990. A combined index based on electrocardiogram and echocardiogram abnormalities, carotid artery wall thickness and stenosis based on carotid ultrasound, decreased ankle-brachial blood pressure, and positive response to a Rose Questionnaire for angina or intermittent claudication defined subclinical disease. The prevalence of subclinical disease was 36% in women and 38.7% in men and increased with age. Among women, low-density lipoprotein cholesterol, systolic blood pressure, blood glucose, and cigarette smoking were positively associated, and high-density lipoprotein cholesterol negatively associated, with subclinical disease. In men, systolic blood pressure, blood glucose, and cigarette smoking were independent risk factors in multiple logistic regression analyses. The risk factors for subclinical disease are, therefore, similar to those for clinical disease at younger ages, especially among women. It is possible that older individuals with subclinical disease are at very high risk of developing clinical disease and that more aggressive interventions to prevent clinical disease should be oriented to individuals with subclinical disease.
Keywords: Aged; Aged, 80 and over; Arteriosclerosis; Cardiovascular Diseases; Female; Humans; Logistic Models; Longitudinal Studies; Male; Prevalence; Risk Factors; United States

Respiratory muscle strength in the elderly. Correlates and reference values. Cardiovascular Health Study Research Group. - Enright, P L; Kronmal, R A; Manolio, T A; Schenker, M B; Hyatt, R E (Am J Respir Crit Care Med, 1994)
Maximal inspiratory pressure (MIP) was assessed in 4,443 ambulatory participants of the Cardiovascular Health Study, 65 yr of age and older, sampled from four communities. Maximal expiratory pressure (MEP) was also measured in 790 participants from a single clinic. Positive predictors of MIP included male sex, FVC, handgrip strength, and higher levels of lean body mass (or low bioelectric resistance). Negative predictors were age, current smoking, self-reported fair to poor general health, and waist size. Both participant and technician learning effects were noted, but there was no independent effect of race, hypertension, cardiovascular disease, or diabetes. A healthy subgroup was identified by excluding current smokers, those with fair to poor general health, or an FEV1 less than 65% of predicted. Mean values determined from the healthy group were 57/116 cm H2O (MIP/MEP) for women, and 83/174 for men. Lower limits of the normal range (fifth percentiles) were 45 to 60% of the mean predicted values. The reference equations derived from this group of healthy 65 to 85-yr-olds may be used by pulmonary function laboratories and respiratory therapists who evaluate the respiratory muscle strength of elderly patients.
Keywords: Aged; Aged, 80 and over; Aging; Body Constitution; Cardiovascular Diseases; Female; Humans; Male; Prospective Studies; Reference Values; Respiratory Function Tests; Respiratory Muscles; Risk Factors; Sex Characteristics; Smoking

Self-reported causes of physical disability in older people: the Cardiovascular Health Study. CHS Collaborative Research Group. - Ettinger, W H; Fried, L P; Harris, T; Shemanski, L; Schulz, R; Robbins, J (J Am Geriatr Soc, 1994)
OBJECTIVE: To determine the major conditions and symptoms reported to cause difficulty in 17 physical tasks of daily life and the criterion validity of self-report of diseases given as the causes of the difficulty in functioning, in community-dwelling older people. DESIGN: Cross sectional analyses of data obtained in an observational cohort study. SETTING: Research clinics in four US communities: Winston-Salem, NC, Hagerstown, MD, Pittsburgh, PA, and Sacramento, CA. PARTICIPANTS: 5201 community-dwelling people > or = 65 years old. RESULTS: Arthritis and other musculoskeletal diseases were given as the primary causes of difficulty in performing physical tasks by 49.0% of the participants reporting difficulty in any task, followed by heart disease (13.7%), injury (12.0%), old age (11.7%), lung disease (6.0%), and stroke (2.9%). The self-reports of diseases that caused disability varied by task. Whereas arthritis was given as a cause of difficulty in most of the 17 different tasks, heart and lung disease were more likely to be reported as causing difficulty with activities requiring high aerobic work capacity such as walking one-half mile or doing heavy housework. Stroke was more likely to be reported as causing difficulty with use of the upper extremities and in performing basic activities of daily living. There was a high degree of consistency (91%) between the diseases and symptoms reported to cause disabilities. The percentage of people who reported a disease as the cause of their difficulty performing a task and had independent confirmation of the diagnosis was 85% in men and 71% in women, and varied according to type of disease and the individual's cognitive status and health status. CONCLUSION: These data suggest that age-related chronic diseases are important causes of disability in older people but that the type of disability is dependent on the underlying disease that causes the disability. Also, self-report of the cause of disability appears to be generally accurate but is influenced by gender, health status, and type of disease.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Arthritis; Cardiovascular Diseases; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Disabled Persons; Female; Health Status; Health Surveys; Heart Diseases; Humans; Lung Diseases; Male; Observer Variation; Reproducibility of Results; Risk Factors; Sex Factors; United States

Black-white differences in subclinical cardiovascular disease among older adults: the Cardiovascular Health Study. CHS Collaborative Research Group. - Manolio, T A; Burke, G L; Psaty, B M; Newman, A B; Haan, M; Powe, N; Tracy, R P; O'Leary, D H (J Clin Epidemiol, 1995)
Cardiovascular and all-cause mortality are higher in black than white Americans, but racial differences in clinical and subclinical cardiovascular disease (CVD) have not been examined in older adults. Clinical and subclinical CVD and its risk factors were compared in 4926 white and 244 black men and women aged 65 years and older. Black participants had lower socioeconomic status and generally higher prevalences of CVD and its risk factors, except for adverse lipid profiles. Common carotid wall thickness was greater in black than white women, and ankle-arm blood pressure ratios were lower in black women and men (p < 0.01). After adjustment for CVD risk factors, common carotid walls were significantly thicker and ankle-arm ratios were lower in blacks than whites of both sexes, while internal carotid walls were significantly thinner in black women. Racial differences in clinical and subclinical CVD in older adults are similar to those reported in younger populations and do not appear to be explained by CVD risk factors.
Keywords: African Continental Ancestry Group; Aged; Cardiovascular Diseases; Carotid Arteries; European Continental Ancestry Group; Female; Geriatric Assessment; Humans; Male; Multivariate Analysis; Prevalence; Regression Analysis; Risk Factors; Sex Factors

Fibrinogen and factor VIII, but not factor VII, are associated with measures of subclinical cardiovascular disease in the elderly. Results from The Cardiovascular Health Study. - Tracy, R P; Bovill, E G; Yanez, D; Psaty, B M; Fried, L P; Heiss, G; Lee, M; Polak, J F; Savage, P J (Arterioscler Thromb Vasc Biol, 1995)
No studies have examined the associations of coagulation factor levels with measures of subclinical cardiovascular disease (CVD) in the elderly. The Cardiovascular Health Study (CHS) is a prospective, population-based cohort study of CVD in persons older than 65 years. At the baseline examination, we measured fibrinogen, factor VII, and factor VIII levels in 5024 of the 5201 participants of the CHS and examined the associations of these coagulation factors with measures of subclinical CVD in a cross-sectional analysis. Subclinical CVD measures were based on electrocardiography, carotid ultrasonography, echocardiography, and ankle-arm blood pressure measurements (AAI). For analyses, we used the full cohort as well as two mutually exclusive subgroups: those with prevalent clinical CVD at baseline and those without. Fibrinogen and to a lesser extent factor VIII showed positive associations with a variety of subclinical CVD measures. In age-adjusted analyses, fibrinogen and factor VIII were significantly associated with 8 of 10 measures. In multivariate analyses, fibrinogen was significantly associated with carotid artery stenosis, internal (but not common) carotid artery wall thickness, and AAI. Factor VIII was associated with abnormal wall motion and AAI in the full cohort only. Factor VII was not consistently associated with subclinical disease measures. In bivariate analyses that included data from all three groups, there were 5 positive subclinical disease associations and 5 negative associations for factor VII. In multivariate analyses, there were no significant associations between factor VII and subclinical CVD in the full cohort or in either subgroup. We conclude that in these cross-sectional analyses, fibrinogen and to a lesser extent factor VIII are associated with subclinical CVD in the elderly, even in those without symptoms or a history of clinical CVD. Factor VII, however, was not associated with subclinical CVD in the elderly.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Carotid Stenosis; Cohort Studies; Factor VII; Factor VIII; Fibrinogen; Humans; Multivariate Analysis; Prospective Studies; Regression Analysis; Risk Factors

Hematological and biochemical laboratory values in older Cardiovascular Health Study participants. - Robbins, J; Wahl, P; Savage, P; Enright, P; Powe, N; Lyles, M (J Am Geriatr Soc, 1995)
OBJECTIVE: To define reference hematologic and biochemical lab values in older individuals. DESIGN: Randomly selected, age- and gender-stratified participants. SETTING: Visits by participants to four research clinics. PATIENTS: A total of 5201 participants in the Cardiovascular Health Study, an observational study of older Medicare-eligible individuals living at home. MEASUREMENT: Information about health status, previous illness, and medication use was obtained from participants and/or their MDs. This information was used to define a healthy subset of the population. Blood samples were obtained for Cholesterol, HDL and LDL cholesterol, fasting and 2-hour postload glucose and insulin, fibrinogen, factors VII and VIII, potassium, creatinine, albumin, uric acid, white blood count, hematocrit, hemoglobin, and platelet count. RESULTS: Significant differences were found for age group and/or gender for all mean values. Many tests were significantly different from the generally accepted reference ranges used in clinical laboratories. CONCLUSIONS: In some situations accepted laboratory norms for the general population can not be extrapolated to older adults. There are implications for both research and clinical practice.
Keywords: Age Factors; Aged; Analysis of Variance; California; Cardiovascular Diseases; Cohort Studies; Female; Health Status; Humans; Male; Maryland; Middle Aged; North Carolina; Pennsylvania; Reference Values; Risk Factors; Sex Characteristics

High density lipoprotein cholesterol is associated with serum cortisol in older people. - Varma, V K; Rushing, J T; Ettinger, W H (J Am Geriatr Soc, 1995)
OBJECTIVE: To determine the associations between serum cortisol and HDL cholesterol, other lipoprotein lipids and cardiovascular risk factors, carotid atherosclerosis, and clinical heart disease in older people. DESIGN: A cross-sectional, observational, ancillary study of the Cardiovascular Health Study (CHS). POPULATION: A total of 245 community-dwelling people, 65 to 89 years old, were recruited consecutively for a 2-month period from the CHS cohort in Forsyth County, North Carolina. METHODS: Cortisol was measured by radioimmunoassay in serum collected between 7:00 and 10:00 AM after an overnight fast. Cortisol levels were correlated with lipoprotein lipids, insulin, glucose, body mass index, waist-hip ratio, prevalent coronary heart disease, hypertension, diabetes, and carotid atherosclerosis by B-mode ultrasound. RESULTS: Serum cortisol was correlated negatively (r = -.24) with body mass index and waist-hip ratio (r = -.16) but was not related significantly to fasting insulin or glucose. Cortisol was not associated significantly with triglyceride and low density lipoprotein cholesterol but showed a positive correlation (r = .21) with high density lipoprotein cholesterol. The relationship between cortisol and high density lipoprotein cholesterol persisted after adjustment for gender, body mass index, waist-hip ratio, cigarette and alcohol use, triglyceride level, and diabetes. There was a trend toward a negative correlation between cortisol and measures of carotid atherosclerosis, but no significant relationship was indicated between cortisol and prevalent coronary heart disease, hypertension, or diabetes. CONCLUSION: Endogenous glucocorticoid levels correlated with HDL cholesterol levels and may play a role in the physiologic regulation of high density lipoprotein levels in older people.
Keywords: Aged; Body Constitution; Body Mass Index; Cardiovascular Diseases; Carotid Stenosis; Cholesterol, HDL; Coronary Disease; Cross-Sectional Studies; Diabetes Mellitus; Female; Humans; Hydrocortisone; Hypertension; Male; Prevalence; Risk Factors

Ischemic episodes in 24-h ambulatory electrocardiograms of elderly persons: the Cardiovascular Health Study. - Rautaharju, P M; Manolio, T A; Furberg, C D; Siscovick, D; Newman, A B; Borhani, N O; Gardin, J M (Int J Cardiol, 1995)
We examined correlates of ischemic episodes in 24-h ambulatory electrocardiograms (ECG) in a sample of 1511 men and women 65 years old and older. Ischemic episodes had a high prevalence period during early afternoon and also during morning hours after awakening, and the overall prevalence was 13% in men and 9% in women (P < 0.001 for gender difference). The prevalence was 9.6% in participants with no history of myocardial infarction and no major or minor resting ECG abnormalities. In multivariate analysis by logistic regression, being on digitalis medication was associated with over a three-fold risk of ischemic episodes, with an odds ratio (95% confidence limits) of 3.21 (1.80 to 5.74). Left ventricular hypertrophy by ECG and atrial fibrillation had almost a three-fold excess risk of ischemic episodes, with odds ratios 2.81 (1.37 to 5.74) and 2.63 (1.17 to 5.91), respectively. Isolated ST-T abnormalities had almost a two-fold excess of ischemic episodes, with an odds ratio of 1.89 (1.01 to 3.54). Being overweight was associated with a 33% reduced likelihood of ischemic episodes after adjustment for other factors, with an odds ratio of 0.67 (0.46 to 0.98). It is concluded that the prevalence of silent ischemic episodes is high in older men and women.
Keywords: Age Factors; Aged; Arrhythmias, Cardiac; Atrial Fibrillation; California; Circadian Rhythm; Digitalis Glycosides; Electrocardiography; Electrocardiography, Ambulatory; Female; Health Surveys; Humans; Hypertrophy, Left Ventricular; Logistic Models; Male; Maryland; Multivariate Analysis; Myocardial Infarction; Myocardial Ischemia; North Carolina; Obesity; Odds Ratio; Pennsylvania; Prevalence; Risk Factors; Sex Characteristics

Methods of assessing prevalent cardiovascular disease in the Cardiovascular Health Study. - Psaty, B M; Kuller, L H; Bild, D; Burke, G L; Kittner, S J; Mittelmark, M; Price, T R; Rautaharju, P M; Robbins, J (Ann Epidemiol, 1995)
The objective of this article is to describe the methods of assessing cardiovascular conditions among older adults recruited to the Cardiovascular Health Study (CHS), a cohort study of risk factors for coronary disease and stroke. Medicare eligibility lists from four US communities were used to obtain a representative sample of 5201 community-dwelling elderly, who answered standardized questionnaires and underwent an extensive clinic examination at baseline. For each cardiovascular condition, self-reports were confirmed by components of the baseline examination or, if necessary, by a validation protocol that included either the review of medical records or surveys of treating physicians. Potential underreporting of a condition was detected either by the review of medical records at baseline for other self-reported conditions or, during prospective follow-up, by the investigation of potential incident events. For myocardial infarction, 75.5% of the self-reports in men and 60.6% in women were confirmed. Self-reported congestive heart failure was confirmed in 73.3% of men and 76.6% of women; stroke, in 59.6% of men and 53.8% of women; and transient ischemic attack, in 41.5% of men and 37.0% of women. Underreporting was also common. During prospective follow-up of an average of about 3 years per person, approximately 50% of men and 38% of women were hospitalized or investigated for at least one potential incident event; for each cardiovascular condition, about 1 to 4% of those investigated during prospective follow-up were found to have had the cardiovascular condition prior to entry into the cohort.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Aged; Cerebrovascular Disorders; Cohort Studies; Coronary Disease; Electrocardiography; Epidemiologic Methods; False Negative Reactions; Female; Humans; Male; Population Surveillance; Prevalence; Prospective Studies; Reproducibility of Results; Risk Factors; Self Disclosure; United States

Subclinical disease as an independent risk factor for cardiovascular disease. - Kuller, L H; Shemanski, L; Psaty, B M; Borhani, N O; Gardin, J; Haan, M N; O'Leary, D H; Savage, P J; Tell, G S; Tracy, R (Circulation, 1995)
BACKGROUND: The primary aim of the present study was to determine the relation between measures of subclinical cardiovascular disease and the incidence of clinical cardiovascular disease among 5201 adults 65 years of age or older who were participating in the Cardiovascular Health Study. METHODS AND RESULTS: A new method of classifying subclinical disease at baseline examination in the Cardiovascular Health Study included measures of ankle-brachial blood pressure, carotid artery stenosis and wall thickness, ECG and echocardiographic abnormalities, and positive response to the Rose Angina and Claudication Questionnaire. Participants were followed for an average of 2.39 years (maximum, 3 years). For participants without evidence of clinical cardiovascular disease at baseline, the presence of subclinical disease compared with no subclinical disease was associated with a significant increased risk of incident total coronary heart disease including CHD deaths and nonfatal MI and angina pectoris for both men and women. For individuals with subclinical disease, the increased risk of total coronary heart disease was 2.0 for men and 2.5 for women, and the increased risk of total mortality was 2.9 for men and 1.7 for women. The increased risk changed little after adjustment for other risk factors, including lipoprotein levels, blood pressure, smoking, and diabetes. CONCLUSIONS: The measurement of subclinical disease provides an approach for identifying high-risk older individuals who may be candidates for more active intervention to prevent clinical disease.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Female; Humans; Incidence; Longitudinal Studies; Male; Myocardial Infarction; Odds Ratio; Reference Values; Risk Factors

Association of fibrinogen and coagulation factors VII and VIII with cardiovascular risk factors in the elderly: the Cardiovascular Health Study. Cardiovascular Health Study Investigators. - Cushman, M; Yanez, D; Psaty, B M; Fried, L P; Heiss, G; Lee, M; Polak, J F; Savage, P J; Tracy, R P (Am J Epidemiol, 1996)
The cross-sectional correlates of three hemostatic factors--fibrinogen, factor VII, and factor VIII--were examined in the Cardiovascular Health Study, a population-based cohort study of 5,201 subjects over age 65 years. Subjects were recruited in 1989-1990 in Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Pittsburgh, Pennsylvania. In multivariate linear regression models, cardiac risk factors significantly associated with fibrinogen were current smoking, race, lipids, and white blood count. In women, alcohol use, obesity, physical activity, and insulin level were also significant, while in men hypertension was correlated. The significant correlates of factor VII were lipids and white blood count in men and estrogen use, alcohol use, race, lipids, insulin level, white blood count, and obesity in women. The independent correlates of factor VIII were insulin, glucose, and race in both sexes; low density lipoprotein cholesterol, white blood count, and diuretic use in men; and alcohol use in women. In multivariate models, factors known to be modifiable risk factors for cardiovascular disease accounted for more of the population variance of these hemostatic factors in women than in men, especially for factor VII. The hemostatic factors may mediate some effects of risk factors on disease, and this should be considered in longitudinal studies.
Keywords: Age Distribution; Aged; Aged, 80 and over; Analysis of Variance; Cardiovascular Diseases; Cohort Studies; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Linear Models; Logistic Models; Male; Prevalence; Risk Factors; Sex Distribution; United States

Asthma and its association with cardiovascular disease in the elderly. The Cardiovascular Health Study Research Group. - Enright, P L; Ward, B J; Tracy, R P; Lasser, E C (J Asthma, 1996)
Cardiovascular disease (CVD) is more prevalent in elderly than in middle-aged patients. Symptoms such as intermittent wheezing with dyspnea may then be due to either CVD or asthma. The objective of this study was to determine the prevalence and correlates of asthma in the elderly and their associations with CVD and CVD risk factors. A community sample of 5201 elderly persons from the Cardiovascular Health Study was asked if they had a physician diagnosis of asthma, and multiple cardiovascular risk and disease variables were measured. Six percent of the participants (309) recalled a history of asthma, and half of these were never smokers. Thirty percent of those with asthma were currently taking a bronchodilator, 14% inhaled steroids, and 10% oral prednisone. Men and women with asthma who were cigarette smokers were more likely to report a concurrent diagnosis of congestive heart failure than smokers without asthma (p = .04). However, when we determined the independent CVD correlates of asthma in this cohort, controlling for smoking status, age, gender, and diagnoses of chronic bronchitis and emphysema, only higher levels of high-density lipoprotein cholesterol (HDL-C) and higher plasma fibrinogen levels were significantly associated with asthma. It was concluded that asthma is as prevalent in the elderly as in middle-aged persons and is associated with higher HDL-C and higher fibrinogen levels, but not with prevalent cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Asthma; Cardiovascular Diseases; Cohort Studies; Female; Humans; Lung; Male; Multivariate Analysis; Prevalence; Risk Factors; Sex Distribution; Smoking

Carotid artery measures are strongly associated with left ventricular mass in older adults (a report from the Cardiovascular Health Study). - Kronmal, R A; Smith, V E; O'Leary, D H; Polak, J F; Gardin, J M; Manolio, T A (Am J Cardiol, 1996)
Associations of carotid artery diameter and intimal-medial thickness by ultrasound with echocardiographic left ventricular (LV) structure were examined in 3,409 participants in the Cardiovascular Health Study, a population-based study of risk factors for coronary heart disease and stroke in men and women aged > or = 65 years. At baseline, sector-guided M-mode echocardiography and B-mode ultrasound were used to evaluate the left ventricle and carotid arteries, respectively. Common carotid artery diameter and intimal-medial thickness were significantly related to LV mass in correlational analysis (r=0.40 and 0.20, respectively, p<0.01), and each was independently associated with LV mass after adjustment for age, gender, weight, systolic and diastolic blood pressure, antihypertensive medication use, prior coronary heart disease, electrocardiographic abnormalities, high-density lipoprotein, and factor VII. We speculate that changes in the arterial wall affect impedance to LV ejection leading to increases in LV mass. Further follow-up of this cohort is in progress and will help to determine whether such carotid artery measures could, by exacerbating LV hypertrophy, constitute another important risk factor for adverse cardiovascular outcomes.
Keywords: Aged; Carotid Arteries; Cohort Studies; Female; Heart Ventricles; Humans; Hypertrophy, Left Ventricular; Male; Regression Analysis; Risk Factors; Ultrasonography

Clinical correlates of white matter findings on cranial magnetic resonance imaging of 3301 elderly people. The Cardiovascular Health Study. - Longstreth, W T; Manolio, T A; Arnold, A; Burke, G L; Bryan, N; Jungreis, C A; Enright, P L; O'Leary, D; Fried, L (Stroke, 1996)
BACKGROUND AND PURPOSE: Our aim was to identify potential risk factors for and clinical manifestations of white matter findings on cranial MRI in elderly people. METHODS: Medicare eligibility lists were used to obtain a representative sample of 5888 community-dwelling people aged 65 years or older. Correlates of white matter findings were sought among 3301 participants who underwent MRI scanning and denied a history of stroke or transient ischemic attack. Participants underwent extensive standardized evaluations at baseline and on follow-up, including standard questionnaires, physical examination, multiple blood tests, electrocardiogram, pulmonary function tests, carotid sonography, and M-mode echocardiography. Neuroradiologists graded white matter findings from 0 (none) to 9 (maximal) without clinical information. RESULTS: Many potential risk factors were related to the white matter grade, but in the multivariate model the factors significantly (all P < .01) and independently associated with increased grade were greater age, clinically silent stroke on MRI, higher systolic blood pressure, lower forced expiratory volume in 1 second (FEV1), and income less than $50,000 per year. If excluded, FEV1 was replaced in the model by female sex, history of smoking, and history of physician-diagnosed hypertension at the baseline examination. Many clinical features were correlated with the white matter grade, especially those indicating impaired cognitive and lower extremity function. CONCLUSIONS: White matter findings were significantly associated with age, silent stroke, hypertension, FEV1, and income. The white matter findings may not be considered benign because they are associated with impaired cognitive and lower extremity function.
Keywords: Age Factors; Aged; Aging; Blood Pressure; Brain; Cardiovascular Diseases; Cerebrovascular Disorders; Cohort Studies; Female; Humans; Ischemic Attack, Transient; Magnetic Resonance Imaging; Male; Multivariate Analysis; Risk Factors; Sex Factors

Correlates of thrombin markers in an elderly cohort free of clinical cardiovascular disease. - Cushman, M; Psaty, B M; Macy, E; Bovill, E G; Cornell, E S; Kuller, L H; Tracy, R P (Arterioscler Thromb Vasc Biol, 1996)
Studies suggest that thrombosis is important in the progression of atherosclerotic lesions. The biochemical markers prothrombin fragment 1-2 and fibrinopeptide A reflect in vivo thrombin generation and activity, respectively. As such, they are markers that might be associated with cardiovascular risk. From the Cardiovascular Health Study, a cohort study of 5201 persons over 65 years of age, 399 persons free of clinical cardiovascular disease (CVD) at the baseline examination were selected for study of specialized markers of hemostasis. We report the cross-sectional relationships of the thrombin markers to CVD risk factors and measures of subclinical CVD. The range of fragment 1-2 2 was 0.12 to 0.85 nmol/L. The range of fibrinopeptide A was 0.9 to 44.1 micrograms/L. High levels of fragment 1-2 and fibrinopeptide A were associated with age, with levels higher in women than men. Fragment 1-2 was associated with smoking; high levels of triglyceride, creatinine, and C-reactive protein; and low levels of glucose. Fibrinopeptide A was associated with high C-reactive protein and apolipoprotein(a) and lower ankle-brachial index. There were no significant associations of the thrombin markers with race, fibrinogen, alcohol consumption, diabetes, or most measures of subclinical CVD. Study findings support a hypothesis that there are physiological interrelationships between cardiac risk factors, hemostasis, inflammation, and progression of atherosclerosis.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Cohort Studies; Female; Hemostasis; Humans; Male; Risk Factors; Thrombin

Lipoprotein levels in elderly patients with asthma. Cardiovascular Health Study Research Group. - Enright, P L; Lasser, E C; Ward, B J; Tracy, R P (J Allergy Clin Immunol, 1996)
Keywords: Aged; Aging; Arteriosclerosis; Asthma; Female; Humans; Lipoproteins; Male; Prospective Studies; Risk Factors; Sex Factors

Risk factors for abdominal aortic aneurysms in older adults enrolled in The Cardiovascular Health Study. - Alcorn, H G; Wolfson, S K; Sutton-Tyrrell, K; Kuller, L H; O'Leary, D (Arterioscler Thromb Vasc Biol, 1996)
B-mode ultrasound examinations of the abdominal aorta were performed from 1990 to 1992 to evaluate the prevalence of abdominal aortic aneurysm (AAA) in a subgroup of the Pittsburgh cohort (656 participants, aged 65 to 90 years) of the Cardiovascular Health Study (CHS). In this pilot study, we evaluated various definitions of aneurysm and the reproducibility of the measurements. In year 5 (1992 to 1993) of the CHS, the entire cohort (4741 participants) was examined. AAA was defined as an infrarenal aortic diameter of > or= 3.0 cm, or a ratio of infrarenal to suprarenal diameter of > or= 1.2, or a history of AAA repair. For the entire CHS cohort, prevalence of aneurysms was 9.5% (451/4741) overall, with a prevalence among men of 14.2% (278/1956) and prevalence among women of 6.2% (173/2785). Variables significantly related to AAA were older age; male sex; history of angina, coronary heart disease, and myocardial infarction; lower ankle-arm blood pressure ratio; higher maximum carotid stenosis; greater intima-media thickness of the internal carotid artery; higher creatinine; lower HDL levels and higher LDL levels; and cigarette smoking. The study has documented the strong association of cardiovascular risk factors and measures of clinical and subclinical atherosclerosis and cardiovascular disease and prevalence of aneurysms. We used a definition that is more sensitive than previously reported (diameter or ratio), which allowed the detection of smaller aneurysms and possibly those at an earlier stage of development. Follow-up of this cohort may lead to new criteria for determining the risk factors for progression of aneurysms.
Keywords: Aged; Anthropometry; Aortic Aneurysm, Abdominal; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Comorbidity; Female; Humans; Male; Middle Aged; Pilot Projects; Prevalence; Reproducibility of Results; Risk Factors; Smoking; Ultrasonography; United States

Short-term predictors of incident stroke in older adults. The Cardiovascular Health Study. - Manolio, T A; Kronmal, R A; Burke, G L; O'Leary, D H; Price, T R (Stroke, 1996)
BACKGROUND AND PURPOSE: Risk factors for incident stroke have been examined in middle-aged persons, but less is known about stroke precursors in the elderly, who suffer the highest rates of stroke. Short-term risk factors for incident stroke were examined in a longitudinal, population-based study including extensive measures of subclinical disease. METHODS: Prospective study of 5201 women and men aged 65 years and older was undertaken in the multicenter Cardiovascular Health Study. RESULTS: During an average 3.31-year follow-up, 188 incident strokes occurred. Stroke incidence increased significantly with age and was similar in women and men. Factors associated with increased stroke risk in multivariate analysis included age, aspirin use, diabetes, impaired glucose tolerance, higher systolic blood pressure, increased time needed to walk 15 ft. frequent falls, elevated creatinine level, abnormal left ventricular (LV) wall motion and increased LV mass on echocardiography, ultrasound-defined carotid stenosis, and atrial fibrillation. Increased LV mass and carotid stenosis were associated with twofold and threefold increases in incidences of stroke, respectively (P < .001). Aspirin users had a 52% higher risk of stroke (relative risk, 1.52; 95% confidence interval, 1.1 to 2.0; P < .007) after adjustment for other factors. This association was present only among aspirin users without prior coronary disease, atrial fibrillation, claudication, or transient ischemic attack, who had an 84% higher risk (relative risk, 1.84; 95% confidence interval, 1.2 to 2.8). CONCLUSIONS: Short-term risk of stroke has a complex relationship with aspirin use and is strongly related to subclinical disease in this sample of older adults. These relationships should be considered in assessing stroke risk in the elderly, in whom recognized and subclinical cardiovascular disease is highly prevalent.
Keywords: Age Factors; Aged; Cardiovascular Physiological Phenomena; Cerebrovascular Disorders; Cohort Studies; Female; Health Status; Humans; Incidence; Longitudinal Studies; Male; Multivariate Analysis; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors; Time Factors

Thickening of the carotid wall. A marker for atherosclerosis in the elderly? Cardiovascular Health Study Collaborative Research Group. - O'Leary, D H; Polak, J F; Kronmal, R A; Savage, P J; Borhani, N O; Kittner, S J; Tracy, R; Gardin, J M; Price, T R; Furberg, C D (Stroke, 1996)
BACKGROUND AND PURPOSE: We investigated the relationships between prevalent coronary heart disease (CHD), clinically manifest atherosclerotic disease (ASD), and major established risk factors for atherosclerosis and intima-media thickness (IMT) in the common carotid arteries (CCA) and internal carotid arteries (ICA) separately and in combination in older adults. We wished to determine whether a noninvasive measurement can serve as an indicator of clinically manifest atherosclerotic disease and to determine which of the two variables, CCA IMT or ICA IMT, is a better correlate. METHODS: IMT of the CCA and ICA was measured with duplex ultrasound in 5117 of 5201 individuals enrolled in the Cardiovascular Health Study, a study of the risk factors and the natural history of cardiovascular disease in adults aged 65 years or more. Histories of CHD, peripheral arterial disease, and cerebrovascular disease were obtained during baseline examination. Risk factors included cholesterol levels, cigarette smoking, elevated blood pressure, diabetes, age, and sex. Relationships between risk factors and IMT were studied by multiple regression analysis and canonical variate analysis. Prediction of prevalent CHD and ASD by IMT measurements in CCAs and ICAs were made by logistic regression, adjusting for age and sex. RESULTS: IMT measurements of the CCAs and ICAs were greater in persons with CHD and ASD than those without, even after controlling for sex (P < .001). IMT measurements in the ICA were greater than those in the CCA. Risk factors for ASD accounted for 17% and 18% of the variability in IMT in the CCA and ICA, respectively. These same risk factors accounted for 25% of the variability of a composite measurement consisting of the sum of the ICA IMT and CCA IMT. The ability to predict CHD and ASD was greater for ICA IMT (odds ratio [confidence interval]: 1.36 [1.31 to 1.41] and 1.35 [1.25 to 1.44], respectively) than for CCA IMT (1.09 [1.05 to 1.13] and 1.17 [1.09 to 1.25]). CONCLUSIONS: Whereas CCA IMT is associated with major risk factors for atherosclerosis and existing CHD and ASD in older adults, this association is not as strong as that for ICA IMT. The combination of these measures relates more strongly to existing CHD and ASD and cerebrovascular disease risk factors than either taken alone.
Keywords: Adult; Aged; Arteriosclerosis; Blood Pressure; Carotid Artery, Common; Carotid Artery, Internal; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; Diabetes Mellitus; Diabetic Angiopathies; Electrocardiography; Female; Humans; Male; Medical History Taking; Physical Examination; Prospective Studies; Regression Analysis; Risk Factors; Sex Characteristics; Smoking; Tunica Intima; Tunica Media; Ultrasonography

Utility of new electrocardiographic models for left ventricular mass in older adults. The Cardiovascular Health Study Collaborative Research Group. - Rautaharju, P M; Manolio, T A; Siscovick, D; Zhou, S H; Gardin, J M; Kronmal, R; Furberg, C D; Borhani, N O; Newman, A (Hypertension, 1996)
Several multivariate statistical models have recently been introduced for estimation of left ventricular mass from standard 12-lead electrocardiographic measurements. The validity of these algorithms has not been adequately evaluated. The objective of this investigation was to compare the associations between echocardiographic and electrocardiographic left ventricular mass values with clinical and subclinical indexes of coronary heart disease. The evaluation was performed with participants of the Cardiovascular Health Study, a population-based sample of 5201 men and women aged 65 years and older. Echocardiographic M-mode measurements of left ventricular mass were performed from videotape recordings with the use of a strictly standardized protocol. Electrocardiographic algorithms of the Novacode program and new algorithms derived from the Cardiovascular Health Study population were used for left ventricular mass prediction. Echocardiographic and electrocardiographic determinations of left ventricular mass were technically successful in 3410 (65.6%) and 5013 (96.4%) participants, respectively. The Novacode model overestimated echocardiographic left ventricular mass. Compared with the Novacode model, the new Cardiovascular Health Study electrocardiographic model, which includes adjustment for body weight, eliminated left ventricular mass prediction bias and improved the correlation between echocardiographic and electrocardiographic left ventricular mass from .33 to .54 in women and from .46 to .51 in men. Echocardiographic and electrocardiographic models both demonstrated similar and about equally strong associations with overt and subclinical disease and with risk factors for left ventricular hypertrophy. These observations demonstrate the potential utility of electrocardiographic models for left ventricular mass estimation.
Keywords: Age Factors; Aged; Echocardiography; Electrocardiography; Female; Humans; Hypertrophy, Left Ventricular; Linear Models; Male; Models, Cardiovascular; Obesity; Odds Ratio; Prognosis; Risk Factors; Sex Factors; Videotape Recording

White blood cell counts in persons aged 65 years or more from the Cardiovascular Health Study. Correlations with baseline clinical and demographic characteristics. - Bovill, E G; Bild, D E; Heiss, G; Kuller, L H; Lee, M H; Rock, R; Wahl, P W (Am J Epidemiol, 1996)
A higher white blood cell (WBC) count has been shown to be a risk factor for myocardial infarction and stroke in middle-aged populations. This study evaluated the relation between baseline WBC count and other risk factors, as well as subclinical and prevalent disease, in the Cardiovascular Health Study, an epidemiologic study of coronary heart disease and stroke in 5,201 persons aged 65 years or older. Baseline data were collected over a 12-month period in 1989-1990. WBC counts were statistically significantly higher in people with prevalent and subclinical atherosclerotic cardiovascular disease than in those who were free of disease. WBC counts correlated (p < 0.01) positively with coagulation factors, measures of glucose metabolism, creatinine, smoking, and triglycerides. In contrast, WBC counts correlated negatively with high density lipoprotein cholesterol, forced expiratory volume, forced vital capacity, and height. The correlations between WBC counts and risk factors were similar in both the entire cohort and the subgroup of persons who had never smoked. The authors conclude that WBC counts in the elderly are associated with prevalent and subclinical atherosclerotic cardiovascular disease, as well as its risk factors.
Keywords: Age Distribution; Aged; Aged, 80 and over; Cerebrovascular Disorders; Female; Humans; Leukocyte Count; Leukocytosis; Longitudinal Studies; Male; Myocardial Infarction; Prevalence; Reference Values; Risk Factors; United States

The association of antihypertensive agents with MRI white matter findings and with Modified Mini-Mental State Examination in older adults. - Heckbert, S R; Longstreth, W T; Psaty, B M; Murros, K E; Smith, N L; Newman, A B; Williamson, J D; Bernick, C; Furberg, C D (J Am Geriatr Soc, 1997)
OBJECTIVES: To examine the association of antihypertensive regimen with magnetic resonance imaging (MRI) white matter hyperintensity and with cognitive impairment in older adults. DESIGN: Cross-sectional study. SETTING: The Cardiovascular Health study, an observational prospective cohort study of risk factors for coronary heart disease and stroke in men and women 65 years of age and older. PARTICIPANTS: 1268 men and women with pharmacologically treated hypertension. MEASUREMENTS: Information on medication use, medical history, and health habits was collected at clinic examinations. Participants completed the Modified Mini-Mental State Examination (3MS) and underwent MRI examination. Without clinical information, study neuroradiologists assigned an overall grade of white matter signal intensity on MRI on a scale from 0 (no findings) to 9 (extensive findings). RESULTS: Adjusted mean white matter grade was higher for users of calcium channel blockers (2.59, P = .007) and users of loop diuretics (2.60, P = .015) than for users of beta blockers (2.12). The association was present for both dihydropyridine and non-dihydropyridine calcium channel blockers. Adjusted mean 3MS scores were lower for users of calcium channel blockers (89.6, P < .002), especially dihydropyridines, and users of loop diuretics (89.7, P < .006) than for users of beta blockers (92.3). No statistically significant association could be shown for users of other drug regimens, including thiazides and ACE inhibitors. CONCLUSION: In this study, users of antihypertensive regimens which included calcium channel blockers or loop diuretics had more severe white matter hyperintensity on MRI and worse performance on 3MS than users of beta blockers.
Keywords: Adrenergic beta-Antagonists; Aged; Aged, 80 and over; Antihypertensive Agents; Brain; Calcium Channel Blockers; Cognition; Cohort Studies; Cross-Sectional Studies; Diuretics; Female; Geriatric Assessment; Humans; Magnetic Resonance Imaging; Male; Risk Factors

Carrying the burden of cardiovascular risk in old age: associations of weight and weight change with prevalent cardiovascular disease, risk factors, and health status in the Cardiovascular Health Study. - Harris, T B; Savage, P J; Tell, G S; Haan, M; Kumanyika, S; Lynch, J C (Am J Clin Nutr, 1997)
Measured weight in old age, reported weight at age 50 y, and weight change from age 50 y to old age were studied in association with prevalent cardiovascular disease (CVD), CVD risk factors, and health status in a population of 4954 men and women aged > or = 65 y in the Cardiovascular Health Study (CHS). Heavier weight (i.e., generally weight in the fourth quartile for the cohort) at age 50 y was more closely associated with prevalent CVD than was current weight, with these associations stronger in women than in men. Heavier current weight and heavier weight at age 50 y were associated with cardiovascular risk factors, including higher blood pressure, lower high-density-lipoprotein cholesterol, and higher fasting insulin. Heavier weight at both time points was related to mobility problems in both men and women and to lower current physical activity levels; among women, strong associations were also seen with lower education and current income. Remaining within 10% of reported weight at age 50 y was associated with better health status as measured by reported health, mobility difficulty, number of medications, and prevalent CVD in men. Paradoxically, most cardiovascular risk factors were lowest for weight losers despite an association of weight loss with poorer health. In this cohort of persons aged > or = 65 y, heavier weight was associated with CVD and CVD risk factors, suggesting that prevention of overweight may prove beneficial in improving cardiovascular risk in older persons. Weight stability from age 50 y to old age was associated with better health status than was weight gain or loss.
Keywords: Aged; Blood Pressure; Body Constitution; Body Weight; Cardiovascular Diseases; Cholesterol, LDL; Female; Health Status; Humans; Insulin; Longitudinal Studies; Male; Middle Aged; Odds Ratio; Prevalence; Risk Factors; Sex Characteristics

Clinical factors associated with calcific aortic valve disease. Cardiovascular Health Study. - Stewart, B F; Siscovick, D; Lind, B K; Gardin, J M; Gottdiener, J S; Smith, V E; Kitzman, D W; Otto, C M (J Am Coll Cardiol, 1997)
OBJECTIVES: The aim of this study was to determine the prevalence of aortic sclerosis and stenosis in the elderly and to identify clinical factors associated with degenerative aortic valve disease. BACKGROUND: Several lines of evidence suggest that degenerative aortic valve disease is not an inevitable consequence of aging and may be associated with specific clinical factors. METHODS: In 5,201 subjects > or = 65 years of age enrolled in the Cardiovascular Health Study, the relation between aortic sclerosis or stenosis identified on echocardiography and clinical risk factors for atherosclerosis was evaluated by using stepwise logistic regression analysis. RESULTS: Aortic valve sclerosis was present in 26% and aortic valve stenosis in 2% of the entire study cohort; in subjects > or = 75 years of age, sclerosis was present in 37% and stenosis in 2.6%. Independent clinical factors associated with degenerative aortic valve disease included age (twofold increased risk for each 10-year increase in age), male gender (twofold excess risk), present smoking (35% increase in risk) and a history of hypertension (20% increase in risk). Other significant factors included height and high lipoprotein(a) and low density lipoprotein cholesterol levels. CONCLUSIONS: Clinical factors associated with aortic sclerosis and stenosis can be identified and are similar to risk factors for atherosclerosis.
Keywords: Aged; Aged, 80 and over; Aortic Valve; Aortic Valve Stenosis; Calcinosis; Female; Heart Valve Diseases; Humans; Male; Prospective Studies; Risk Factors; Sclerosis

Does the association of risk factors and atherosclerosis change with age? An analysis of the combined ARIC and CHS cohorts. The Atherosclerosis Risk in Communities (ARIC) and Cardiovascular Health Study (CHS) investigators. - Howard, G; Manolio, T A; Burke, G L; Wolfson, S K; O'Leary, D H (Stroke, 1997)
INTRODUCTION: A decrease in the estimated relative risk of cerebrovascular and cardiovascular diseases associated with known disease risk factors has been observed among elderly cohorts, perhaps suggesting that continued risk factor management in the elderly may not be as efficacious as with younger age groups. In this paper, the differential magnitude of the association of risk factors with atherosclerosis across the age spectrum from 45 years to older than 75 years is presented. METHODS: Subclinical atherosclerosis as measured by carotid ultrasonography and risk factor prevalence were assessed using similar methods among participants aged 45 to 64 years in the Atherosclerosis Risk in Communities (ARIC) study and among participants 65 years and older in the Cardiovascular Health Study (CHS). Pooling these two cohorts provided data on the relationship of risk factors and atherosclerosis on nearly 19,000 participants over a broad age range. Regression analyses were used to assess the consistency of the magnitude of the association of risk factors with atherosclerosis across the age spectrum separately for black and white participants in cross-sectional analyses. RESULTS: As expected, each of the risk factors was globally (across all ages) associated with increased atherosclerosis. However, the magnitude of the association did not differ across the age spectrum for hypertension, low density lipoprotein cholesterol (LDL-c), fibrinogen, or body mass index (BMI). For whites, there was a significantly greater impact of smoking and HDL-C among older age strata but a smaller impact of diabetes. For black women, the impact of HDL-C decreased among the older age strata. CONCLUSIONS: These data suggest that most risk factors continue to be associated with increased atherosclerosis at older ages, possibly suggesting a continued value in investigation of strategies to reduce atherosclerosis by controlling risk factors at older ages.
Keywords: African Americans; African Continental Ancestry Group; Aged; Aging; Arteriosclerosis; Body Mass Index; Cardiovascular Physiological Phenomena; Cardiovascular System; Carotid Arteries; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Health Status; Humans; Hypertension; Male; Middle Aged; Regression Analysis; Risk Factors; Sex Factors; Smoking; Tunica Intima; Tunica Media; Ultrasonography

Exercise intensity and subclinical cardiovascular disease in the elderly. The Cardiovascular Health Study. - Siscovick, D S; Fried, L; Mittelmark, M; Rutan, G; Bild, D; O'Leary, D H (Am J Epidemiol, 1997)
The authors assessed the cross-sectional association between intensity of exercise in later life and coronary heart disease risk factors and subclinical disease among 2,274 men and women, 65 years of age and older, who were participants in the Cardiovascular Health Study (CHS) during 1989-1990. Subjects were free of prior clinical cardiovascular disease or impairment of physical function. Exercise intensity was characterized as low, moderate, or high, based on highest intensity exercise reported over the 2 weeks prior to the CHS baseline examination. After adjustment for age, education, and postmenopausal hormone therapy (among women), there was an inverse dose-response relationship of exercise intensity with selected risk factors. By low, moderate, and high exercise intensity, respectively: fasting insulin-men, 15.6 microU/ml, 14.1 microU/ml, and 12.6 microU/ml, p for trend <0.001; women, 14.8 microU/ml, 13.8 microU/ml, and 12.0 microU/ml, p for trend = 0.01; serum fibrinogen-men, 316.2 mg/dl, 315.4 mg/dl, and 300.0 mg/dl, p for trend = 0.01; women, 327.3 mg/dl, 317.0 mg/dl, and 310.7 mg/dl, p for trend = 0.01; lower extremity arterial disease by percent with ankle-arm index <0.9-men, 18.3, 5.5, and 3.7, p for trend = 0.01; women, 10.0, 5.7, and 2.8, p for trend = 0.02; evidence of myocardial injury by cardiac infarction/injury score (CIIS)-men, 8.0, 6.0, 3.9, p for trend <0.001; women, 4.6, 3.9, and 3.6, p for trend = 0.03. Adjustment for smoking, alcohol consumption, and total kilocalories expended in exercise altered the findings only slightly. The authors conclude that intensity of exercise in later life is associated with favorable coronary disease risk factor levels and a reduced prevalence of several markers of subclinical disease.
Keywords: Aged; Cardiovascular Diseases; Cross-Sectional Studies; Energy Metabolism; Exercise; Female; Fibrinogen; Humans; Insulin; Life Style; Longitudinal Studies; Male; Prevalence; Risk Factors

Health effects of caregiving: the caregiver health effects study: an ancillary study of the Cardiovascular Health Study. - Schulz, R; Newsom, J; Mittelmark, M; Burton, L; Hirsch, C; Jackson, S (Ann Behav Med, 1997)
We propose that two related sources of variability in studies of caregiving health effects contribute to an inconsistent pattern of findings: the sampling strategy used and the definition of what constitutes caregiving. Samples are often recruited through self-referral and are typically comprised of caregivers experiencing considerable distress. In this study, we examine the health effects of caregiving in large population-based samples of spousal caregivers and controls using a wide array of objective and self-report physical and mental health outcome measures. By applying different definitions of caregiving, we show that the magnitude of health effects attributable to caregiving can vary substantially, with the largest negative health effects observed among caregivers who characterize themselves as being strained. From an epidemiological perspective, our data show that approximately 80% of persons living with a spouse with a disability provide care to their spouse, but only half of care providers report mental or physical strain associated with caregiving.
Keywords: Activities of Daily Living; Aged; Arousal; Cardiovascular Diseases; Caregivers; Cerebrovascular Disorders; Coronary Disease; Cost of Illness; Female; Geriatric Assessment; Health Behavior; Health Status; Humans; Male; Psychophysiologic Disorders; Risk Factors; Spouses; Stress, Psychological

Incidence of and risk factors for atrial fibrillation in older adults. - Psaty, B M; Manolio, T A; Kuller, L H; Kronmal, R A; Cushman, M; Fried, L P; White, R; Furberg, C D; Rautaharju, P M (Circulation, 1997)
BACKGROUND: This study aimed to describe the incidence of atrial fibrillation (AF) among older adults during 3 years of follow-up. METHODS AND RESULTS: In this cohort study, 5201 adults > or = 65 years old were examined annually on four occasions between June 1989 and May 1993. At baseline, participants answered questionnaires and underwent a detailed examination that included carotid ultrasound, pulmonary function tests, ECG, and echocardiography. Subjects with a pacemaker or AF at baseline (n=357) were excluded. New cases of AF were identified from three sources: (1) annual self-reports, (2) annual ECGs, and (3) hospital discharge diagnoses. Cox proportional-hazards models were used to assess baseline risk factors as predictors of incident AF. Among 4844 participants, 304 developed a first episode of AF during an average follow-up of 3.28 years, for an incidence of 19.2 per 1000 person-years. The onset was strongly associated with age, male sex, and the presence of clinical cardiovascular disease. For men 65 to 74 and 75 to 84 years old, the incidences were 17.6 and 42.7, respectively, and for women, 10.1 and 21.6 events per 1000 person-years. In stepwise models, the use of diuretics, a history of valvular heart disease, coronary disease, advancing age, higher levels of systolic blood pressure, height, glucose, and left atrial size were all associated with an increased risk of AF. The use of beta-blockers and high levels of alcohol use, cholesterol, and forced expiratory volume in 1 second were associated with a reduced risk of AF. CONCLUSIONS: The incidence of AF in older adults may be higher than estimated by previous population studies. Left atrial size appears to be an important risk factor, and the control of blood pressure and glucose may be important in preventing the development of AF.
Keywords: Adult; Aged; Atrial Fibrillation; Blood Glucose; Blood Pressure; Cerebrovascular Disorders; Cohort Studies; Coronary Disease; Electrocardiography; Female; Follow-Up Studies; Hospital Records; Humans; Incidence; Male; Prospective Studies; Risk Factors; United States

Knowledge of risk among patients at increased risk for stroke. - Samsa, G P; Cohen, S J; Goldstein, L B; Bonito, A J; Duncan, P W; Enarson, C; DeFriese, G H; Horner, R D; Matchar, D B (Stroke, 1997)
BACKGROUND AND PURPOSE: Patients who recognize their increased risk for stroke are more likely to engage in (and comply with) stroke prevention practices than those who do not. We describe perceived risk of stroke among a nationally diverse sample of patients at increased risk for stroke and determine whether patients' knowledge of their stroke risk varied according to patients' demographic and clinical characteristics. METHODS: Respondents were recruited from the Academic Medical Center Consortium (n = 621, five academic medical centers, inpatients of varying age); the Cardiovascular Health Study (n = 321, population-based sample of persons aged 65+ years); and United HealthCare (n = 319, five health plans, inpatients and outpatients typically younger than 65 years). The primary outcome was awareness of being at risk for stroke. RESULTS: Only 41% of respondents were aware of their increased risk for stroke (including less than one half of patients with previous minor stroke). Approximately 74% of patients who recalled being told of their increased stroke risk by a physician acknowledged this risk in comparison with 28% of patients who did not recall being informed by a physician. Younger patients, depressed patients, those in poor current health, and those with a history of TIA were most likely to be aware of their stroke risk. CONCLUSIONS: Over one half of patients at increased risk of stroke are unaware of their risk. Healthcare providers play a crucial role in communicating information about risk, and successful communication encourages adoption of stroke prevention practices. Educational messages should be targeted toward patients least likely to be aware of their risk.
Keywords: Adult; Aged; Aged, 80 and over; Awareness; Cerebrovascular Disorders; Female; Humans; Knowledge; Male; Middle Aged; Multivariate Analysis; Risk Factors

Left ventricular mass in the elderly. The Cardiovascular Health Study. - Gardin, J M; Arnold, A; Gottdiener, J S; Wong, N D; Fried, L P; Klopfenstein, H S; O'Leary, D H; Tracy, R; Kronmal, R (Hypertension, 1997)
Left ventricular (LV) mass, as estimated from M-mode echocardiography (echo), has previously been shown to be an independent predictor of incident cardiovascular disease morbidity and mortality. We evaluated the relationship at baseline of echo LV mass to relevant cardiovascular disease risk factors and other potential covariates in the Cardiovascular Health Study, multicenter study sponsored by the National Heart, Lung, and Blood Institute of 5201 men and women aged 65 years or older (mean, 73). Two-dimensionally directed M-mode echo LV mass measurements could be obtained in 1357 men and 2053 women (66% of this elderly cohort). Stepwise linear regression analyses of the relationship of echo LV mass to demographic and risk factor, physical activity, electrocardiographic, and prevalent disease variables resulted in a model that explained 37% of the variance for the entire cohort. In order of decreasing importance, factors positively associated with echo LV mass were body weight, male sex, systolic pressure, presence of congestive heart failure, present smoking, major and minor electrocardiographic abnormalities, treatment for hypertension, valvular heart disease, aortic regurgitation by color Doppler, and mitral regurgitation by color Doppler (in men) whereas diastolic pressure, bioresistance (a measure of adiposity), and high-density lipoprotein cholesterol were inversely related to echo LV mass. Although height and weight were both related to LV mass, height added nothing once weight was entered in multiple linear regression analyses. Furthermore, in the multiple regression models, diastolic pressure was inversely and systolic BP positively related to LV mass, with similar magnitudes for their coefficients. In consonance with these findings, pulse pressure was positively related to LV mass in bivariate analyses. Multiple linear regression analyses explained less of the variance for ventricular septal thickness (R2 = .13) and LV posterior wall thickness (R2 = .14) than for LV mass (R2 = .37) and LV diastolic dimension (R2 = .27). Intriguing findings in the elderly Cardiovascular Health Study cohort included the presence of pulse pressure as a positive correlate, and high-density lipoprotein cholesterol as an inverse correlate, of LV mass. Longitudinal studies in the Cardiovascular Health Study cohort will help to clarify the importance of demographic, risk factor, and other variables, and changes in these variables, in predicting changes in echo LV mass and its components as well as the prognostic significance of LV mass in the elderly.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Body Weight; Cardiovascular Diseases; Cohort Studies; Echocardiography; Female; Humans; Hypertrophy, Left Ventricular; Male; Prospective Studies; Risk Factors; Ventricular Function, Left

Lifetime smoking exposure affects the association of C-reactive protein with cardiovascular disease risk factors and subclinical disease in healthy elderly subjects. - Tracy, R P; Psaty, B M; Macy, E; Bovill, E G; Cushman, M; Cornell, E S; Kuller, L H (Arterioscler Thromb Vasc Biol, 1997)
Blood levels of C-reactive protein (CRP), a marker of inflammation, are related to cardiovascular disease risk. To determine cross-sectional correlates in the elderly, we measured CRP in 400 men and women older than 65 years and free of clinical cardiovascular disease at baseline as part of the Cardiovascular Health Study. Only 2% of the values were greater than 10 mg/L, the cut-point usually used to identify inflammation. CRP levels appeared tightly regulated, since there were strong bivariate correlations between CRP and the following: inflammation-sensitive proteins such as fibrinogen (r = .52); measures of fibrinolysis such as plasmin-antiplasmin complex (r = .23); pack-years of smoking (r = .30); and body mass index (r = .24; all P values < or = .001). The association with pack-years was independent of the length of time since cessation of smoking. CRP levels were also associated with coagulation factors VIIc, IXc, and Xc; HDL cholesterol (negative) and triglyceride; diabetes status; diuretic use; ECG abnormalities; and level of exercise. Because of effect modification, two multiple linear regression prediction models were developed for CRP, one each for never smokers and ever smokers. An a priori physiologic model was used to guide these analyses, which disallowed the use of other inflammation-sensitive variables such as fibrinogen. In never smokers, the independent predictors were body mass index (+), diabetes status (+), plasmin-antiplasmin complex (+), and the presence of ECG abnormalities (+); this model predicted 15% of the CRP population variance. In ever smokers, the predictors were body mass index (+), plasmin-antiplasmin complex (+), pack-years of smoking (+), HDL cholesterol (-), and ankle-arm blood pressure index (-); this model predicted 42% of the population variance. We conclude that levels of CRP in the healthy elderly are tightly regulated and reflect lifetime exposure to smoking as well as level of obesity, ongoing level of fibrinolysis, diabetes status, and level of subclinical atherothrombotic disease. Moreover, exposure to smoking affects the relation of CRP to these other factors.
Keywords: Aged; Body Mass Index; C-Reactive Protein; Cardiovascular Diseases; Female; Humans; Male; Multivariate Analysis; Risk Factors; Smoking

Sleep disturbance, psychosocial correlates, and cardiovascular disease in 5201 older adults: the Cardiovascular Health Study. - Newman, A B; Enright, P L; Manolio, T A; Haponik, E F; Wahl, P W (J Am Geriatr Soc, 1997)
OBJECTIVES: To describe the prevalence of self reported sleep disturbances in older men and women and to describe their relationships with health status and cardiovascular disease (CVD). DESIGN: Cross-sectional study of sleep disturbance, CVD, general health, psychosocial factors, physical function, and use of psychotropic medications. SETTING: Participants of the Cardiovascular Health Study, 5201 adults aged 65 and older recruited from a random sample of noninstitutionalized Medicare enrollees in four US communities. MEASURES: Self-reported sleep disturbances and standardized questionnaires for cardiopulmonary symptoms and diseases, depression, social support, activities of daily living, physical activity, cognitive function, and current medications, spirometry, ECG, echocardiography, and carotid ultrasound. RESULTS: Women were twice as likely as men to report difficulty falling asleep (30% vs 14%). Daytime sleepiness, difficulty falling asleep, and frequent awakenings increased in prevalence with age. All symptoms were related strongly to depression. Symptoms of daytime sleepiness were also related strongly to poor health and limitations in activities of daily living in men and women. In multivariate analysis, men taking benzodiazepines were likely to report difficulty falling asleep and daytime sleepiness, whereas women taking benzodiazepines reported difficulty falling asleep and waking up too early. After accounting for these factors, the only cardiovascular disease independently associated with sleep disturbances was angina. Men and women with confirmed angina were 1.6 times more likely to report trouble falling asleep. Independent relationships between sleep disturbances and cardiovascular risk factors such as obesity, hypertension, smoking, and diabetes were relatively weak and inconsistent, though smokers were less likely to report frequent awakenings. CONCLUSIONS: Sleep disturbances are relatively common in older men and women and are associated with poor health, depression, angina, limitations in activities of daily living, and the use of benzodiazepines.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cross-Sectional Studies; Depression; Female; Geriatric Assessment; Health Surveys; Humans; Male; Prevalence; Psychotropic Drugs; Random Allocation; Risk Factors; Sex Factors; Sleep Wake Disorders; Social Support; Surveys and Questionnaires; United States

Use of calcium channel blockers and breast carcinoma risk in postmenopausal women. - Fitzpatrick, A L; Daling, J R; Furberg, C D; Kronmal, R A; Weissfeld, J L (Cancer, 1997)
BACKGROUND: The use of calcium channel blockers in an elderly population recently was reported to be associated with the incidence of cancer. The Cardiovascular Health Study, a multisite observational cohort study, provided the opportunity to investigate the epidemiologic association between the use of calcium channel blockers and breast carcinoma risk in 3198 women age > or = 65 years. METHODS: Standard questionnaires and clinical procedures were administered at four study sites annually from 1989-1990 to 1993-1994. Drug usage was assessed by a medication inventory and hospitalizations for 75 incident invasive breast carcinoma cases were identified using International Classification of Diseases-9 Clinical Modification codes. Time-dependent Cox proportional hazards regression models were used to assess associations between incident breast carcinoma and the use of specific antihypertensive medication including calcium channel blockers. RESULTS: In adjusted Cox proportional hazards models, an elevated risk of breast carcinoma was associated with use of calcium channel blockers (hazard ratio [HR]: 2.57; 95% confidence interval [CI], 1.47-4.49). This association persisted when the comparison group was users of other antihypertensive medication. No associations between the use of other antihypertensive medication with incident breast carcinoma were found. Associations were enhanced by assessment of high dose at baseline (HR: 4.42; 95% CI, 1.37-14.27) and when calcium channel blockers were combined with estrogen use (HR: 4.48; 95% CI, 1.58-12.75). The association was found to be strongest for the use of estrogens with immediate release calcium channel blockers (HR: 8.48; 95% CI, 2.99-24.08). CONCLUSIONS: Although the number of cases was limited in this observational study, associations found between the use of calcium channel blockers and incident invasive breast carcinoma warrant further investigation. Site specific carcinomas should be included as an outcome of ongoing and planned long term clinical trials using calcium channel blockers.
Keywords: Age Factors; Aged; Breast Neoplasms; Calcium Channel Blockers; Cohort Studies; Estrogens; Female; Humans; Postmenopause; Proportional Hazards Models; Risk Factors

Aspirin use and incident stroke in the cardiovascular health study. CHS Collaborative Research Group. - Kronmal, R A; Hart, R G; Manolio, T A; Talbert, R L; Beauchamp, N J; Newman, A (Stroke, 1998)
BACKGROUND AND PURPOSE: Randomized clinical trials testing aspirin in relatively low-risk, middle-aged people have consistently shown small increases in stroke associated with aspirin use. We analyzed the relationship between the regular use of aspirin and incident ischemic and hemorrhagic stroke among people aged 65 years or older participating in the Cardiovascular Health Study. METHODS: We conducted a multivariate analysis of incident stroke rates in a prospectively assessed, observational cohort of 5011 elderly people followed for a mean of 4.2 years. RESULTS: Participants had a mean age of 72 years, and 58% were women. Twenty-three percent used aspirin frequently, and 17% used aspirin infrequently at study entry. Frequent aspirin use was associated with an increased rate of ischemic stroke compared with nonusers (relative risk= 1.6; 95% confidence interval [CI], 1.2 to 2.2; P=0.001). After adjustment for other stroke risk factors, women who used aspirin frequently or infrequently at study entry had a 1.8-fold (95% CI, 1.2 to 2.8) and 1.6-fold (95% CI, 0.9 to 3.0) increased risk of ischemic stroke, respectively (P<0.01, test for trend), compared with nonusers. In men, aspirin use was not statistically significantly associated with stroke risk. Findings were similar when aspirin use in the years before the incident stroke was used in the modeling. Aspirin use at entry was also associated with a 4-fold (95% CI, 1.6 to 10.0) increase in risk of hemorrhagic stroke for both infrequent and frequent users of aspirin (P=0.003). CONCLUSIONS: Aspirin use was associated with increased risks of ischemic stroke in women and hemorrhagic stroke overall in this elderly cohort, after adjustment for other stroke predictors. The possibility exists of confounding by reasons for aspirin use rather than cause and effect. Whether regular aspirin use increases stroke risk for elderly people without cardiovascular disease can only be determined by randomized clinical trials.
Keywords: Aged; Aspirin; Brain Ischemia; Cardiovascular Diseases; Cerebral Hemorrhage; Cerebrovascular Disorders; Cohort Studies; Cyclooxygenase Inhibitors; Dose-Response Relationship, Drug; Female; Follow-Up Studies; Humans; Incidence; Male; Regression Analysis; Risk Factors; Sex Factors; Time Factors

Asymptomatic internal carotid artery stenosis defined by ultrasound and the risk of subsequent stroke in the elderly. The Cardiovascular Health Study. - Longstreth, W T; Shemanski, L; Lefkowitz, D; O'Leary, D H; Polak, J F; Wolfson, S K (Stroke, 1998)
BACKGROUND AND PURPOSE: We sought in this study to relate carotid ultrasound findings in asymptomatic older adults to the 5-year risk of various cerebrovascular outcomes used in the Asymptomatic Carotid Atherosclerosis Study (ACAS). METHODS: The Cardiovascular Health Study (CHS) is a longitudinal study of people 65 years and older. Analyses of internal carotid artery stenosis defined by multiple different cutoffs of peak systolic velocity, rather than one particular cutoff, were performed in the 5441 participants who underwent carotid ultrasound and lacked a history of transient ischemic attack or stroke. The 5-year risks of 7 cerebrovascular disease outcomes used in ACAS were estimated for each cutoff. RESULTS: Associations with the 5-year risk of outcomes were substantially elevated only at cutoffs with high peak systolic velocities. In this population, the number of people with such high velocities was small. For example, with a cutoff of approximately 2.5 m/s, suggesting a stenosis of >70%, the 5-year risk of an ipsilateral fatal or nonfatal stroke was 5%, and only 0.5% of the group had velocities at least this high. CONCLUSIONS: In a group of older adults likely to participate in a screening program, as evidenced by willingness to participate in CHS, high peak systolic velocities consistent with high-grade carotid stenosis were uncommon and risk of subsequent cerebrovascular disease outcomes was relatively low. These findings do not suggest that similar populations of older adults would benefit from a program using ultrasound to screen for asymptomatic carotid stenosis.
Keywords: Aged; Blood Flow Velocity; Carotid Artery, Internal; Carotid Stenosis; Cerebrovascular Disorders; Cohort Studies; Female; Humans; Male; Prevalence; Risk Factors; Systole; Ultrasonography, Doppler

Body mass index and mortality in nonsmoking older adults: the Cardiovascular Health Study. - Diehr, P; Bild, D E; Harris, T B; Duxbury, A; Siscovick, D; Rossi, M (Am J Public Health, 1998)
OBJECTIVES: This study assesses the relationship of body mass index to 5-year mortality in a cohort of 4317 nonsmoking men and women aged 65 to 100 years. METHODS: Logistic regression analyses were conducted to predict mortality as a function of baseline body mass index, adjusting for demographic, clinical, and laboratory covariates. RESULTS: There was an inverse relationship between body mass index and mortality; death rates were higher for those who weighed the least. Inclusion of covariates had trivial effects on these results. People who had lost 10% or more of their body weight since age 50 had a relatively high death rate. When that group was excluded, there was no remaining relationship between body mass index and mortality. CONCLUSIONS: The association between higher body mass index and mortality often found in middle-aged populations was not observed in this large cohort of older adults. Over-weight does not seem to be a risk factor for 5-year mortality in this age group. Rather, the risks associated with significant weight loss should be the primary concern.
Keywords: Age Distribution; Aged; Body Mass Index; Cardiovascular Diseases; Cause of Death; Cohort Studies; Female; Humans; Logistic Models; Male; Mortality; Predictive Value of Tests; Risk Factors; Sex Distribution; Smoking; Survival Analysis; United States; Weight Loss

Correlates of antithrombin, protein C, protein S, and TFPI in a healthy elderly cohort. - Sakkinen, P A; Cushman, M; Psaty, B M; Kuller, L H; Bajaj, S P; Sabharwal, A K; Boineau, R; Macy, E; Tracy, R P (Thromb Haemost, 1998)
The majority of fatal acute myocardial infarctions occur in the elderly. Since these events are predominantly thrombotic, we studied the cross-sectional associations of the anticoagulant proteins Antithrombin, Protein C, Protein S. and Tissue Factor Pathway Inhibitor (TFPI) in a subgroup (n = 400) of the Cardiovascular Health Study (a study of healthy men and women > or = 65 years) free of clinical cardiovascular disease (CVD). We did not observe any strong age-associated trends, although Protein C was lower in older women (p < or = 0.001), and TFPI was higher in older men (p < or = 0.01). The inhibitors were highly intercorrelated, and were associated with increased levels of inflammation-sensitive proteins (e.g., fibrinogen. plasminogen), lipids (especially total and LDL-cholesterol), and coagulation factors, such as Factors VIIc, IXc, and Xc. None was associated with the procoagulant markers Prothrombin Fragment F1-2 or Fibrinopeptide A. Only TFPI was associated with subclinical atherosclerosis: ankle-arm index and internal carotid artery stenosis, p trend < or = 0.01; and carotid wall thickness, p trend < or = 0.05. In multivariate analysis the independent predictors of TFPI were levels of fibrinogen; the fibrinolytic marker plasmin-antiplasmin complex; LDL-cholesterol; and carotid wall thickness (R2 for the model = 0.35). In summary, the inhibitors did not appear to increase with age, and were predominantly associated with inflammation markers and lipids. Since markers of thrombin production do increase with age, we hypothesize that an age-related hemostatic imbalance may ensue, with associated increased thrombotic risk. Only TFPI was associated with subclinical CVD, suggesting that it may more closely reflect endothelial damage.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Anticoagulants; Antithrombin III; Biomarkers; Cross-Sectional Studies; Disease Susceptibility; Female; Humans; Lipoproteins; Male; Prevalence; Protein C; Protein S; Reference Values; Risk Factors; Thrombosis

Differences in prevalence of and risk factors for subclinical vascular disease among black and white participants in the Cardiovascular Health Study. - Kuller, L; Fisher, L; McClelland, R; Fried, L; Cushman, M; Jackson, S; Manolio, T (Arterioscler Thromb Vasc Biol, 1998)
A composite measure of subclinical vascular disease has been developed in the Cardiovascular Health Study (CHS). In previous reports, we measured the prevalence of subclinical disease among the original 5201 participants in the CHS, the relationship of risk factors to subclinical disease, and the association of subclinical disease to clinical coronary heart disease. In 1992 to 1993 (year 4 of the study), a larger cohort of 424 black women and 248 black men was added to the study. In this study, we have compared the prevalence of subclinical disease among blacks and whites in the CHS and the association with cardiovascular risk factors. The prevalence of subclinical disease for all participants (aged > or =65 years) was 41.3% for white women, 39.7% for black women, 41.9% for white men, and 43.7% for black men. The prevalence increased with age. The risk factor associations for subclinical disease were similar among blacks and whites. In multivariate analysis, age, systolic blood pressure, LDL cholesterol, smoking, and family history of myocardial infarction were independently associated with subclinical disease among both black and white women, while for white men, systolic blood pressure, use of antihypertensive medication, smoking, body mass index, and diastolic blood pressure (inverse) were related to subclinical disease. In black men, blood triglyceride level, use of antihypertensive medications, and family history of myocardial infarction (inverse) were associated with subclinical disease.
Keywords: African Americans; Aged; Cardiovascular Physiological Phenomena; Cohort Studies; European Continental Ancestry Group; Female; Health Status; Humans; Male; Multivariate Analysis; Prevalence; Regression Analysis; Risk Factors; Vascular Diseases

Factor V Leiden is not a risk factor for arterial vascular disease in the elderly: results from the Cardiovascular Health Study. - Cushman, M; Rosendaal, F R; Psaty, B M; Cook, E F; Valliere, J; Kuller, L H; Tracy, R P (Thromb Haemost, 1998)
Coagulation factor V Leiden is a risk marker for venous thrombosis. For arterial thrombosis no large study to date has included population-based elderly patients. The Cardiovascular Health Study is a longitudinal study of 5,201 men and women over age 65. With 3.4-year follow-up, we studied 373 incident cases of myocardial infarction (MI), angina, stroke. or transient ischemic attack (TIA), and 482 controls. The odds ratios for each event with heterozygous factor V Leiden were: MI, 0.46 (95% CI 0.17 to 1.25); angina, 1.0 (95% CI 0.45 to 2.23); stroke, 0.77 (95% CI 0.35 to 1.70): TIA, 1.33 (95% CI 0.5 to 3.55); any outcome, 0.83 (95% CI 0.48 to 1.44). Adjustment for cardiovascular risk factors did not change relationships. In older adults factor V Leiden is not a risk factor for future arterial thrombosis.
Keywords: Adult; Age Factors; Aged; Arteries; Factor V; Female; Humans; Male; Middle Aged; Mutation; Risk Factors; Thrombosis

Lacunar infarcts defined by magnetic resonance imaging of 3660 elderly people: the Cardiovascular Health Study. - Longstreth, W T; Bernick, C; Manolio, T A; Bryan, N; Jungreis, C A; Price, T R (Arch Neurol, 1998)
OBJECTIVE: To identify risk factors for and functional consequences of lacunar infarct in elderly people. METHODS: The Cardiovascular Health Study (CHS) is a longitudinal study of people 65 years or older, in which 3660 participants underwent cranial magnetic resonance imaging (MRI). Neuroradiologists read scans in a standard fashion without any clinical information. Lacunes were defined as subcortical areas consistent with infarcts measuring 3 to 20 mm. In cross-sectional analyses, clinical correlates were contrasted among groups defined by MRI findings. RESULTS: Of the 3660 subjects who underwent MRI, 2529 (69%) were free of infarcts of any kind and 841 (23%) had 1 or more lacunes without other types present, totaling 1270 lacunes. For most of these 841 subjects, their lacunes were single (66%) and silent (89%), namely without a history of transient ischemic attack or stroke. In multivariate analyses, factors independently associated with lacunes were increased age, diastolic blood pressure, creatinine, and pack-years of smoking (listed in descending order of strength of association; for all, P < .005), as well as maximum internal carotid artery stenosis of more than 50% (odds ratio [OR], 1.81; P < .005), male sex (OR, 0.74; P < .005), and history of diabetes at entrance into the study (OR, 1.33; P < .05). Models for subgroups of single, multiple, silent, and symptomatic lacunes differed only minimally. Those with silent lacunes had more cognitive, upper extremity, and lower extremity dysfunction not recognized as stroke than those whose MRIs were free of infarcts. CONCLUSIONS: In this group of older adults, lacunes defined by MRI are common and associated with factors that likely promote or reflect small-vessel disease. Silent lacunes are also associated with neurologic dysfunction.
Keywords: Aged; Cerebral Infarction; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Multivariate Analysis; Risk Factors

Relationship between ApoE, MRI findings, and cognitive function in the Cardiovascular Health Study. - Kuller, L H; Shemanski, L; Manolio, T; Haan, M; Fried, L; Bryan, N; Burke, G L; Tracy, R; Bhadelia, R (Stroke, 1998)
BACKGROUND AND PURPOSE: We determined the relationship between apolipoprotein (Apo)E, MRI, and low cognitive scores. METHODS: The relationship between age, education, ApoE genotype, MRI examination of the brain, subclinical and clinical cardiovascular disease, and low (<80) score on the Modified Mini-Mental State Examination (3MSE, as modified by Teng and Chui) was evaluated for 3469 black and white participants in the Cardiovascular Health Study (CHS) in years 5 and 6 of the study. The participants were followed for up to 3 years. RESULTS: The prevalence of scores <80 in years 5 and 6 of the CHS was 8.2% for participants without and 20.4% for those with prior history of stroke. Age, race, and education were important determinants of low 3MSE scores. The prevalence of ApoE-4 (odds ratio [OR], 1.6 [1.1 to 2.1]) was directly related to scores <80, as was high ventricular volume (OR, 1.6 [1.2 to 2.3]), high white matter grade (OR, 1.4 [1.1 to 1.9]), and infarctlike lesions (OR, 1.6 [1.2 to 2.1]) on the MRI in the multivariate analysis. A five-point or greater decline in scores over up to 3 years was more often observed for participants with low 3MSE scores at year 5, at older ages, with lower education, and experiencing incident stroke (OR, 3.6 [1.2 to 10.6]), ApoE-4 genotype (OR, 1.8 [1.4 to 2.3]), and with MRI findings of high ventricular volume (OR, 2.0 [1.5 to 2.7]), and infarctlike lesions (OR, 1.2 [0.9 to 1.5]). CONCLUSIONS: These results demonstrate that vascular changes on MRI, measures of brain atrophy, ApoE-4, and age, education, and race are associated with low cognitive scores among older individuals. The MRI of the brain provides valuable information related to cognitive tests and decline over time. The potential exists for using MRI measurements to identify high-risk individuals for dementia and to test potential interventions to reduce the risk of dementia.
Keywords: African Continental Ancestry Group; Aged; Apolipoproteins E; Brain; Cardiovascular Diseases; Cerebral Infarction; Cognition; Cognition Disorders; European Continental Ancestry Group; Female; Genotype; Health Status; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Polymerase Chain Reaction; Risk Factors; Sex Factors; United States

Relationship between balance and abnormalities in cerebral magnetic resonance imaging in older adults. - Tell, G S; Lefkowitz, D S; Diehr, P; Elster, A D (Arch Neurol, 1998)
BACKGROUND: Falling is a major cause of disability and morbidity among older adults. Because poor balance is a major reason for frequent falls, assessment of balance and its risk factors are important. In this study, we postulated that cerebral changes identified on magnetic resonance (MR) imaging are related to balance, and that older adults with balance problems would have significantly greater prevalence of such brain abnormalities than older adults without balance problems. DESIGN AND MEASUREMENTS: Several measures of balance were examined in more than 700 community-dwelling older men and women, blacks and whites. Balance measures included dynamic posturography, functional reach, Romberg and 1-foot stand tests, tandem stand, and 1-foot stand. Cerebral MR imaging assessments included ventricular size, sulcal widening, white matter disease, and ischemic infarctions. Cardiovascular disease and hypertension were determined and controlled for in the analyses. RESULTS: A summary of the balance measures was significantly related to each of the 4 MR imaging measures, with those with poorer balance having more disease. The strongest associations with balance were seen for white matter disease and ventricular size. All but the ischemic infarction variable remained significantly associated with balance after adjustments for sex, race, age, cardiovascular disease, and hypertension. CONCLUSION: Cerebral changes identified by MR imaging are associated with poorer balance among older adults.
Keywords: Accidental Falls; Aged; Aging; Cerebral Cortex; Female; Humans; Magnetic Resonance Imaging; Male; Postural Balance; Risk Factors

Risk factors for 5-year mortality in older adults: the Cardiovascular Health Study. - Fried, L P; Kronmal, R A; Newman, A B; Bild, D E; Mittelmark, M B; Polak, J F; Robbins, J A; Gardin, J M (JAMA, 1998)
CONTEXT: Multiple factors contribute to mortality in older adults, but the extent to which subclinical disease and other factors contribute independently to mortality risk is not known. OBJECTIVE: To determine the disease, functional, and personal characteristics that jointly predict mortality in community-dwelling men and women aged 65 years or older. DESIGN: Prospective population-based cohort study with 5 years of follow-up and a validation cohort of African Americans with 4.25-year follow-up. SETTING: Four US communities. PARTICIPANTS: A total of 5201 and 685 men and women aged 65 years or older in the original and African American cohorts, respectively. MAIN OUTCOME MEASURES: Five-year mortality. RESULTS: In the main cohort, 646 deaths (12%) occurred within 5 years. Using Cox proportional hazards models, 20 characteristics (of 78 assessed) were each significantly (P<.05) and independently associated with mortality: increasing age, male sex, income less than $50000 per year, low weight, lack of moderate or vigorous exercise, smoking for more than 50 pack-years, high brachial (>169 mm Hg) and low tibial (< or = 127 mm Hg) systolic blood pressure, diuretic use by those without hypertension or congestive heart failure, elevated fasting glucose level (>7.2 mmol/L [130 mg/dL]), low albumin level (< or = 37 g/L), elevated creatinine level (> or = 106 micromol/L [1.2 mg/dL]), low forced vital capacity (< or = 2.06 mL), aortic stenosis (moderate or severe) and abnormal left ventricular ejection fraction (by echocardiography), major electrocardiographic abnormality, stenosis of internal carotid artery (by ultrasound), congestive heart failure, difficulty in any instrumental activity of daily living, and low cognitive function by Digit Symbol Substitution test score. Neither high-density lipoprotein cholesterol nor low-density lipoprotein cholesterol was associated with mortality. After adjustment for other factors, the association between age and mortality diminished, but the reduction in mortality with female sex persisted. Finally, the risk of mortality was validated in the second cohort; quintiles of risk ranged from 2% to 39% and 0% to 26% for the 2 cohorts. CONCLUSIONS: Objective measures of subclinical disease and disease severity were independent and joint predictors of 5-year mortality in older adults, along with male sex, relative poverty, physical activity, smoking, indicators of frailty, and disability. Except for history of congestive heart failure, objective, quantitative measures of disease were better predictors of mortality than was clinical history of disease.
Keywords: African Americans; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Female; Follow-Up Studies; Health Surveys; Humans; Male; Mortality; Proportional Hazards Models; Prospective Studies; Risk Factors; United States

Time trends in the use of cholesterol-lowering agents in older adults: the Cardiovascular Health Study. - Lemaitre, R N; Furberg, C D; Newman, A B; Hulley, S B; Gordon, D J; Gottdiener, J S; McDonald, R H; Psaty, B M (Arch Intern Med, 1998)
OBJECTIVES: To describe recent temporal patterns of cholesterol-lowering medication use and the characteristics that may have influenced the initiation of cholesterol-lowering therapy among those aged 65 years or older. SUBJECTS AND METHODS: A cohort of 5201 adults 65 years or older were examined annually between June 1989 and May 1996. We added 687 African American adults to the cohort in 1992-1993. We measured blood lipid levels at baseline and for the original cohort in the third year of follow-up. We assessed the use of cholesterol-lowering drugs at each visit. RESULTS: The prevalence of cholesterol-lowering drug use in 1989-1990 was 4.5% among the men and 5.9% among the women; these figures increased over the next 6 years to 8.1% and 10.0%, respectively, in 1995-1996. There was a 4-fold increase in the use of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors during the 6 years of follow-up, from 1.9% of all participants in 1989-1990 to 7.5% in 1995-1996. The use of bile acid sequestrants, nicotinic acid, and probucol declined from initial levels of less than 1% each. Among the participants who were untreated in 1989-1990, but eligible for cholesterol-lowering therapy after a trial of dietary therapy according to the 1993 guidelines of the National Cholesterol Education Panel, less than 20% initiated drug therapy in the 6 years of follow-up, even among subjects with a history of coronary heart disease. Among participants untreated at baseline but eligible for either cholesterol-lowering therapy or dietary therapy, initiation of cholesterol-lowering drug therapy was directly associated with total cholesterol levels, hypertension, and a history of coronary heart disease, and was inversely related to age, high-density lipoprotein cholesterol levels, and difficulties with activities of daily living. Other characteristics that form the basis of the 1993 National Cholesterol Education Panel guidelines-diabetes, smoking, family history of premature coronary heart disease, and total number of risk factors-were not associated with the initiation of cholesterol-lowering drug therapy. CONCLUSIONS: Given the clinical trial evidence for benefit, those aged 65 to 75 years and with prior coronary heart disease appeared undertreated with cholesterol-lowering drug therapy.
Keywords: Aged; Anticholesteremic Agents; Cholesterol, LDL; Cohort Studies; Female; Humans; Hypercholesterolemia; Male; Prevalence; Risk Factors; United States

Analytical and biologic variability in measures of hemostasis, fibrinolysis, and inflammation: assessment and implications for epidemiology. - Sakkinen, P A; Macy, E M; Callas, P W; Cornell, E S; Hayes, T E; Kuller, L H; Tracy, R P (Am J Epidemiol, 1999)
An increasing number of cardiovascular epidemiologic studies are measuring non-traditional risk markers of disease, most of which do not have established biovariability characteristics. When biovariability data have been reported, they usually represent a short time period, and, in any case, there is little consensus on how the information should be used. The authors performed a long-term (6-month) repeated measures study on 26 healthy individuals, and, using a nested analysis of variance (ANOVA) approach, report on the analytical (CVA), intraindividual (CVI), and between individual (CVG) variability of 12 procoagulant, fibrinolysis, and inflammation assays, including total cholesterol for comparison. The results suggest acceptable analytical variability (CVA < or = 1/2 CVI) for all assays. However, there was a large range of intraindividual variation as a proportion of total variance (2-78%), and adjusting for intraindividual and between individual variation in bivariate correlations increased the observed correlation by more than 30 percent for three of these assays. Overall, the assays showed a significant increase in intraindividual variation over 6 months (p < 0.05). While these findings suggest that most of these assays have biovariability characteristics similar to cholesterol, there is variation among assays. Some assays may be better suited to epidemiologic studies, and knowledge of an assay's biovariability data may be useful in interpreting simple statistics, and in designing multivariate models.
Keywords: Adult; Aged; Analysis of Variance; Cardiovascular Diseases; Cholesterol; Epidemiology; Female; Fibrinolysis; Hemostasis; Humans; Inflammation; Male; Middle Aged; Models, Statistical; Multivariate Analysis; Risk Factors

Ankle-arm index as a predictor of cardiovascular disease and mortality in the Cardiovascular Health Study. The Cardiovascular Health Study Group. - Newman, A B; Shemanski, L; Manolio, T A; Cushman, M; Mittelmark, M; Polak, J F; Powe, N R; Siscovick, D (Arterioscler Thromb Vasc Biol, 1999)
Peripheral arterial disease (PAD) in the legs, measured noninvasively by the ankle-arm index (AAI) is associated with clinically manifest cardiovascular disease (CVD) and its risk factors. To determine risk of total mortality, coronary heart disease, or stroke mortality and incident versus recurrent CVD associated with a low AAI, we examined the relationship of the AAI to subsequent CVD events in 5888 older adults with and without CVD. The AAI was measured in 5888 participants >/=65 years old at the baseline examination of the Cardiovascular Health Study. All participants had a detailed assessment of prevalent CVD and were contacted every 6 months for total mortality and CVD events (including CVD mortality, fatal and nonfatal myocardial infarction, congestive heart failure, angina, stroke, and hospitalized PAD). The crude mortality rate at 6 years was highest (32.3%) in those participants with prevalent CVD and a low AAI (P<0.9), and it was lowest in those with neither of these findings (8.7%, P<0.01). Similar patterns emerged from analysis of recurrent CVD and incident CVD. The risk for incident congestive heart failure (relative risk [RR]=1.61) and for total mortality (RR=1.62) in those without CVD at baseline but with a low AAI remained significantly elevated after adjustment for cardiovascular risk factors. Hospitalized PAD events occurred months to years after the AAI was measured, with an adjusted RR of 5.55 (95% CI, 3.08 to 9.98) in those at risk for incident events. A statistically significant decline in survival was seen at each 0.1 decrement in the AAI. An AAI of <0.9 is an independent risk factor for incident CVD, recurrent CVD, and mortality in this group of older adults in the Cardiovascular Health Study.
Keywords: Age Distribution; Aged; Aged, 80 and over; Ankle; Arm; Blood Pressure Determination; Cardiovascular Diseases; Cohort Studies; Female; Humans; Hypertension; Male; Predictive Value of Tests; Risk Factors; Sex Distribution; Survival Analysis

Antidiabetic treatment trends in a cohort of elderly people with diabetes. The cardiovascular health study, 1989-1997. - Smith, N L; Heckbert, S R; Bittner, V A; Savage, P J; Barzilay, J I; Dobs, A S; Psaty, B M (Diabetes Care, 1999)
OBJECTIVE: This study characterizes the pharmaceutical treatment of type 2 diabetes from 1989-1990 to 1996-1997 in an elderly cohort. RESEARCH DESIGN AND METHODS: A total of 5,888 adults aged > or = 65 years were recruited and attended a baseline clinic visit in 1989-1990 (n = 5,201, original cohort) or 1992-1993 (n = 687. African-American [new] cohort) as participants of the Cardiovascular Health Study. Fasting serum glucose (FSG) was measured at baseline. Medication use was ascertained by drug inventory at all annual clinic visits. Diabetes was defined at baseline as insulin or oral hypoglycemic agent (OHA) use or as having an FSG > or = 7.0 mmol/l (126 mg/dl), the current consensus definition of diabetes. RESULTS: A total of 387 (7%) original (FSG = 9.8 mmol/l [177 mg/dl]) and 115 (17%) new (FSG = 10.6 mmol/l [191 mg/dl]) cohort members had pharmacologically treated diabetes at baseline. Among those in the original and in the new cohorts who survived follow-up, respectively, OHA use decreased from 80 to 48% (P < 0.001) and from 67 to 50% (P < 0.003) and insulin use increased from 20 to 33% (P = 0.001) and from 33 to 37% (P = 0.603). There were 396 (8%) original (FSG = 8.8 mmol/l [159 mg/dl]) and 45 (7%) new (FSG = 10.0 mmol/l [181 mg/dl]) cohort members with diabetes untreated at baseline. Among them, respectively, OHA use reached 38 and 30% and insulin use reached 6 and 16% in 1996-1997. CONCLUSIONS: Diabetes was common in this elderly cohort, and > 80% of treated patients with diabetes at baseline were not achieving fasting glucose goals of < or = 6.7 mmol/l (120 mg/dl). Many untreated at baseline remained untreated after 7 years of follow-up.
Keywords: Aged; Blood Glucose; Cardiovascular Diseases; Cohort Studies; Diabetes Mellitus; Drug Therapy; Female; Follow-Up Studies; Humans; Hypoglycemic Agents; Insulin; Male; Prospective Studies; Risk Factors; Time Factors; United States

Association of aortic-valve sclerosis with cardiovascular mortality and morbidity in the elderly. - Otto, C M; Lind, B K; Kitzman, D W; Gersh, B J; Siscovick, D S (N Engl J Med, 1999)
BACKGROUND: Although aortic-valve stenosis is clearly associated with adverse cardiovascular outcomes, it is unclear whether valve sclerosis increases the risk of cardiovascular events. METHODS: We assessed echocardiograms obtained at base line from 5621 men and women 65 years of age or older who were enrolled in a population-based prospective study. On echocardiography, the aortic valve was normal in 70 percent (3919 subjects), sclerotic without outflow obstruction in 29 percent (1610), and stenotic in 2 percent (92). The subjects were followed for a mean of 5.0 years to assess the risk of death from any cause and of death from cardiovascular causes. Cardiovascular morbidity was defined as new episodes of myocardial infarction, angina pectoris, congestive heart failure, or stroke. RESULTS: There was a stepwise increase in deaths from any cause (P for trend, <0.001) and deaths from cardiovascular causes (P for trend, <0.001) with increasing aortic-valve abnormality; the respective rates were 14.9 and 6.1 percent in the group with normal aortic valves, 21.9 and 10.1 percent in the group with aortic sclerosis, and 41.3 and 19.6 percent in the group with aortic stenosis. The relative risk of death from cardiovascular causes among subjects without coronary heart disease at base line was 1.66 (95 percent confidence interval, 1.23 to 2.23) for those with sclerotic valves as compared with those with normal valves, after adjustment for age and sex. The relative risk remained elevated after further adjustment for clinical factors associated with sclerosis (relative risk, 1.52; 95 percent confidence interval, 1.12 to 2.05). The relative risk of myocardial infarction was 1.40 (95 percent confidence interval, 1.07 to 1.83) among subjects with aortic sclerosis, as compared with those with normal aortic valves. CONCLUSIONS: Aortic sclerosis is common in the elderly and is associated with an increase of approximately 50 percent in the risk of death from cardiovascular causes and the risk of myocardial infarction, even in the absence of hemodynamically significant obstruction of left ventricular outflow.
Keywords: Aged; Angina Pectoris; Aortic Valve; Calcinosis; Cardiovascular Diseases; Cerebrovascular Disorders; Female; Heart Failure; Heart Valve Diseases; Humans; Male; Mortality; Myocardial Infarction; Prospective Studies; Risk; Risk Factors; Ultrasonography; United States; Ventricular Outflow Obstruction

Cardiovascular disease in older adults with glucose disorders: comparison of American Diabetes Association criteria for diabetes mellitus with WHO criteria. - Barzilay, J I; Spiekerman, C F; Wahl, P W; Kuller, L H; Cushman, M; Furberg, C D; Dobs, A; Polak, J F; Savage, P J (Lancet, 1999)
BACKGROUND: The new fasting American Diabetes Association (ADA) criteria for the diagnosis of diabetes mellitus rely mainly on fasting blood glucose concentrations and use a lower cut-off value for diagnosis than the WHO criteria. We aimed to assess the sensitivity of these criteria for the detection of cardiovascular disease, the main complication of diabetes mellitus in the elderly. METHODS: We did a cross-sectional and prospective analysis of 4515 participants of the Cardiovascular Health Study, an 8 year longitudinal study designed to identify factors related to the onset and course of cardiovascular disease in adults aged at least 65 years. We calculated the prevalence and incidence of cardiovascular disease for the ADA and WHO criteria. FINDINGS: There was a higher prevalence of cardiovascular disease among individuals with impaired glucose or newly diagnosed diabetes by both criteria than among those with normal glucose concentrations. However, because fewer individuals had abnormal glucose states by the fasting ADA criteria (22.3%) than by the WHO criteria (46.8%), the number of cases of cardiovascular disease attributable to abnormal glucose states was a third of that attributable by the WHO criteria (53 vs 159 cases per 10,000). For the two sets of criteria, the relative risk for incident cardiovascular disease (mean follow-up 5.9 years) was higher in individuals with impaired glucose and newly diagnosed diabetes than in those with normal glucose. Individuals classified as normal by the fasting ADA criteria had a higher absolute number of incident events (455 of 581 events) than those classified as normal by the WHO criteria (269 of 581 events). Fasting ADA criteria were therefore less sensitive than the WHO criteria for predicting cardiovascular disease among individuals with abnormal glucose (sensitivity, 28% vs 54%). INTERPRETATION: The new fasting ADA criteria seem to be less predictive than the WHO criteria for the burden of cardiovascular disease associated with abnormal glucose in the elderly.
Keywords: Age Factors; Aged; Blood Glucose; Cardiovascular Diseases; Cross-Sectional Studies; Diabetes Complications; Diabetes Mellitus; Fasting; Female; Glucose Intolerance; Humans; Longitudinal Studies; Male; Prospective Studies; Risk Factors; Sensitivity and Specificity; Societies, Medical; United States; World Health Organization

Caregiving as a risk factor for mortality: the Caregiver Health Effects Study. - Schulz, R; Beach, S R (JAMA, 1999)
CONTEXT: There is strong consensus that caring for an elderly individual with disability is burdensome and stressful to many family members and contributes to psychiatric morbidity. Researchers have also suggested that the combination of loss, prolonged distress, the physical demands of caregiving, and biological vulnerabilities of older caregivers may compromise their physiological functioning and increase their risk for physical health problems, leading to increased mortality. OBJECTIVE: To examine the relationship between caregiving demands among older spousal caregivers and 4-year all-cause mortality, controlling for sociodemographic factors, prevalent clinical disease, and subclinical disease at baseline. DESIGN: Prospective population-based cohort study, from 1993 through 1998 with an average of 4.5 years of follow-up. SETTING: Four US communities. PARTICIPANTS: A total of 392 caregivers and 427 noncaregivers aged 66 to 96 years who were living with their spouses. MAIN OUTCOME MEASURE: Four-year mortality, based on level of caregiving: (1) spouse not disabled; (2) spouse disabled and not helping; (3) spouse disabled and helping with no strain reported; or(4) spouse disabled and helping with mental or emotional strain reported. RESULTS: After 4 years of follow-up, 103 participants (12.6%) died. After adjusting for sociodemographic factors, prevalent disease, and subclinical cardiovascular disease, participants who were providing care and experiencing caregiver strain had mortality risks that were 63% higher than noncaregiving controls (relative risk [RR], 1.63; 95% confidence interval [CI], 1.00-2.65). Participants who were providing care but not experiencing strain (RR, 1.08; 95 % CI, 0.61-1.90) and those with a disabled spouse who were not providing care (RR, 1.37; 95% CI, 0.73-2.58) did not have elevated adjusted mortality rates relative to the noncaregiving controls. CONCLUSIONS: Our study suggests that being a caregiver who is experiencing mental or emotional strain is an independent risk factor for mortality among elderly spousal caregivers. Caregivers who report strain associated with caregiving are more likely to die than noncaregiving controls.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Disabled Persons; Female; Health Status; Home Nursing; Humans; Male; Mortality; Proportional Hazards Models; Prospective Studies; Risk Factors; Socioeconomic Factors; Spouses; Stress, Psychological; United States

Carotid-artery intima and media thickness as a risk factor for myocardial infarction and stroke in older adults. Cardiovascular Health Study Collaborative Research Group. - O'Leary, D H; Polak, J F; Kronmal, R A; Manolio, T A; Burke, G L; Wolfson, S K (N Engl J Med, 1999)
BACKGROUND: The combined thickness of the intima and media of the carotid artery is associated with the prevalence of cardiovascular disease. We studied the associations between the thickness of the carotid-artery intima and media and the incidence of new myocardial infarction or stroke in persons without clinical cardiovascular disease. METHODS: Noninvasive measurements of the intima and media of the common and internal carotid artery were made with high-resolution ultrasonography in 5858 subjects 65 years of age or older. Cardiovascular events (new myocardial infarction or stroke) served as outcome variables in subjects without clinical cardiovascular disease (4476 subjects) over a median follow-up period of 6.2 years. RESULTS: The incidence of cardiovascular events correlated with measurements of carotid-artery intima-media thickness. The relative risk of myocardial infarction or stroke increased with intima-media thickness (P<0.001). The relative risk of myocardial infarction or stroke (adjusted for age and sex) for the quintile with the highest thickness as compared with the lowest quintile was 3.87 (95 percent confidence interval, 2.72 to 5.51). The association between cardiovascular events and intima-media thickness remained significant after adjustment for traditional risk factors, showing increasing risks for each quintile of combined intima-media thickness, from the second quintile (relative risk, 1.54; 95 percent confidence interval, 1.04 to 2.28), to the third (relative risk, 1.84; 95 percent confidence interval, 1.26 to 2.67), fourth (relative risk, 2.01; 95 percent confidence interval, 1.38 to 2.91), and fifth (relative risk, 3.15; 95 percent confidence interval, 2.19 to 4.52). The results of separate analyses of myocardial infarction and stroke paralleled those for the combined end point. CONCLUSIONS: Increases in the thickness of the intima and media of the carotid artery, as measured noninvasively by ultrasonography, are directly associated with an increased risk of myocardial infarction and stroke in older adults without a history of cardiovascular disease.
Keywords: Aged; Carotid Arteries; Cerebrovascular Disorders; Disease-Free Survival; Female; Humans; Incidence; Male; Myocardial Infarction; Proportional Hazards Models; Prospective Studies; Risk Factors; Tunica Intima; Tunica Media; Ultrasonography

Cerebrovascular disease and depression symptoms in the cardiovascular health study. - Steffens, D C; Helms, M J; Krishnan, K R; Burke, G L (Stroke, 1999)
BACKGROUND AND PURPOSE: Evidence is mounting linking cerebrovascular disease with depressive symptoms in the elderly. Lesions in both white and gray matter have been associated with depressive symptoms and major depression. We sought to investigate the relationship between depressive symptoms and white and gray matter lesions in subjects participating in the Cardiovascular Health Study. METHODS: In a sample of 3660 men and women who underwent a standardized interview, physical examination, and MRI scan, we examined the association between number of white and gray matter lesions and white matter grade (a measure of severity) and reported depressive symptoms using a modified version of the Centers for Epidemiologic Studies Depression (CES-D) scale. We controlled for a variety of demographic and medical variables as well as functional status and Modified Mini-Mental State Examination score. RESULTS: The number of small (<3 mm) basal ganglia lesions was significantly associated with reported depressive symptoms, but white matter grade was not. In subsequent logistic regression models, number of basal ganglia lesions remained a significant predictor after controlling for non-MRI variables and severity of white matter lesions. CONCLUSIONS: Our findings extend previous reports that linked cerebrovascular changes to depressive symptoms in clinical populations to a large community-based population. This report provides further evidence of the importance of basal ganglia lesions in geriatric depression.
Keywords: Activities of Daily Living; Aged; Brain; Cardiovascular Diseases; Cerebrovascular Disorders; Cross-Sectional Studies; Depression; Female; Humans; Logistic Models; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Risk Factors

Fibrinolytic activation markers predict myocardial infarction in the elderly. The Cardiovascular Health Study. - Cushman, M; Lemaitre, R N; Kuller, L H; Psaty, B M; Macy, E M; Sharrett, A R; Tracy, R P (Arterioscler Thromb Vasc Biol, 1999)
Coagulation factor levels predict arterial thrombosis in epidemiological studies, but studies of older persons are needed. We studied 3 plasma antigenic markers of fibrinolysis, viz, plasminogen activator inhibitor-1 (PAI-1), fibrin fragment D-dimer, and plasmin-antiplasmin complex (PAP) for the prediction of arterial thrombosis in healthy elderly persons over age 65. The study was a nested case-control study in the Cardiovascular Health Study cohort of 5201 men and women >/=65 years of age who were enrolled from 1989 to 1990. Cases were 146 participants without baseline clinical vascular disease who developed myocardial infarction, angina, or coronary death during a follow-up of 2.4 years. Controls remained free of cardiovascular events and were matched 1:1 to cases with respect to sex, duration of follow-up, and baseline subclinical vascular disease status. With increasing quartile of D-dimer and PAP levels but not of PAI-1, there was an independent increased risk of myocardial infarction or coronary death, but not of angina. The relative risk for D-dimer above versus below the median value (>/=120 microg/L) was 2.5 (95% confidence interval, 1.1 to 5.9) and for PAP above the median (>/=5.25 nmol/L), 3.1 (1.3 to 7.7). Risks were independent of C-reactive protein and fibrinogen concentrations. There were no differences in risk by sex or presence of baseline subclinical disease. D-dimer and PAP, but not PAI-1, predicted future myocardial infarction in men and women over age 65. Relationships were independent of other risk factors, including inflammation markers. Results indicate a major role for these markers in identifying a high risk of arterial disease in this age group.
Keywords: Age Factors; Aged; Angina Pectoris; Biomarkers; Female; Fibrin Fibrinogen Degradation Products; Fibrinolysin; Fibrinolysis; Follow-Up Studies; Heart Arrest; Humans; Male; Myocardial Infarction; Plasminogen Activator Inhibitor 1; Risk Factors

Neuroanatomic and functional correlates of depressed mood: the Cardiovascular Health Study. - Sato, R; Bryan, R N; Fried, L P (Am J Epidemiol, 1999)
Although a number of studies suggest an association between stroke and depression, few have examined the relation between magnetic resonance imaging (MRI)-identified lesions and depression among community-dwelling older adults. This cross-sectional study sought to assess the association between MRI infarcts in the basal ganglia and non-basal-ganglia areas, potential functional consequences of these lesions, and depressive symptomatology in 3,371 US men and women aged 65 years or older who participated in the Cardiovascular Health Study between 1992 and 1994. By using multiple linear regression models, the authors found that after adjustment for age, gender, and stroke history, Center for Epidemiologic Studies Depression Scale scores were independently associated with non-basal-ganglia lesions (p = 0.04) but were not independently associated with basal ganglia lesions (p = 0.11). When measures of physical disability and cognitive impairment were added to the models, these measures displaced MRI-identified infarcts in their association with depressive symptoms. In additional models, hemispheric location and size of the basal ganglia lesion were found to have no relation to depression levels. These results suggest that the functional consequences of cerebrovascular disease may be the causal pathway by which basal ganglia and non-basal-ganglia lesions are associated with depressive symptomatology.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Basal Ganglia; Cerebral Infarction; Cognition; Cross-Sectional Studies; Depression; Female; Geriatric Assessment; Humans; Linear Models; Magnetic Resonance Imaging; Male; Psychiatric Status Rating Scales; Risk Factors; United States

Oral anticoagulation in patients with atrial fibrillation: adherence with guidelines in an elderly cohort. - White, R H; McBurnie, M A; Manolio, T; Furberg, C D; Gardin, J M; Kittner, S J; Bovill, E; Knepper, L (Am J Med, 1999)
PURPOSE: To determine adherence with practice guidelines in a population-based cohort of elderly persons aged 70 years or older with atrial fibrillation. SUBJECTS AND METHODS: This was a cross-sectional analysis of a subgroup of participants in the Cardiovascular Health Study, a prospective observational study involving four communities in the United States. Subjects were participants with atrial fibrillation on electrocardiogram at one or more yearly examinations from 1993 to 1995. The outcome measure was self-reported use of warfarin in 1995. RESULTS: In 1995, 172 (4.1%) participants had atrial fibrillation together with information regarding warfarin use and no preexisting indication for its use. Warfarin was used by 63 (37%) of these participants. Of the 109 participants not reporting warfarin use, 92 (84%) had at least one of the clinical risk factors (aside from age) associated with stroke in patients with atrial fibrillation. Among participants not taking warfarin, 47% were taking aspirin. Several characteristics were independently associated with warfarin use, including age [odds ratio (OR) = 0.6 per 5-year increment, 95% CI 0.5-0.9], a modified mini-mental examination score <85 points [OR = 0.3, 95% confidence interval (CI) 0.1-0.9], and among patients without prior stroke, female sex (OR = 0.5, 95% CI 0.2-1.0). CONCLUSIONS: Despite widely publicized practice guidelines to treat patients who have atrial fibrillation with warfarin, most participants who had atrial fibrillation were at high risk for stroke but were not treated with warfarin. More studies are needed to determine why elderly patients with atrial fibrillation are not being treated with warfarin.
Keywords: Administration, Oral; Aged; Anticoagulants; Atrial Fibrillation; Cerebrovascular Disorders; Cross-Sectional Studies; Female; Humans; Logistic Models; Male; Odds Ratio; Practice Guidelines as Topic; Prospective Studies; Risk; Risk Factors; Warfarin

Prevalence and associations of MRI-demonstrated brain infarcts in elderly subjects with a history of transient ischemic attack. The Cardiovascular Health Study. - Bhadelia, R A; Anderson, M; Polak, J F; Manolio, T A; Beauchamp, N; Knepper, L; O'Leary, D H (Stroke, 1999)
BACKGROUND AND PURPOSE: MRI is more sensitive than CT, but the significance of brain abnormalities seen on MR images obtained in older subjects with transient ischemic attack (TIA) is not clear. We studied the prevalence and risk factors associated with MRI-demonstrated infarcts in elderly subjects with a history of TIA. METHODS: Participants of the Cardiovascular Health Study, aged 65 years or more and without prior stroke, were studied with brain MRI (n=3456). The prevalence of brain infarcts (>/=3 mm) on MRI was determined in subjects with and without TIA. The cardiovascular risk factors and clinical and subclinical cardiovascular disease associated with MRI infarcts were studied in subjects with TIA. RESULTS: Subjects with TIA (n=100) had a higher prevalence of MRI infarcts than subjects without TIA (46% versus 28%; P<0.001). The unadjusted odds ratio for having MRI infarcts in subjects with TIA was 2.20 (95% CI, 1.47 to 3.30) and remained significantly elevated after adjustments for risk factors and cerebrovascular disease (odds ratio, 1.86; 95% CI, 1.23 to 2.83). In subjects with TIA, diastolic blood pressure (P=0.01) and internal carotid artery intima-media thickness (P=0.01) were the only factors predictive of the presence of MRI infarcts by stepwise logistic regression analysis. CONCLUSIONS: MRI infarcts are imaging manifestations of clinically important cerebrovascular disease in subjects with a history of TIA, given their increased prevalence and positive association with increased diastolic blood pressure and internal carotid artery intima-media thickness.
Keywords: Aged; Brain; Cardiovascular Diseases; Cerebral Infarction; Cross-Sectional Studies; Female; Humans; Ischemic Attack, Transient; Magnetic Resonance Imaging; Male; Odds Ratio; Population Surveillance; Predictive Value of Tests; Prevalence; Prospective Studies; Risk Factors; United States

The relationship of fibrinogen and factors VII and VIII to incident cardiovascular disease and death in the elderly: results from the cardiovascular health study. - Tracy, R P; Arnold, A M; Ettinger, W; Fried, L; Meilahn, E; Savage, P (Arterioscler Thromb Vasc Biol, 1999)
Little is known about the prospective associations of fibrinogen, factor VII, or factor VIII with cardiovascular disease (CVD) and mortality in the elderly. At baseline in the Cardiovascular Health Study (5888 white and African American men and women; aged >/=65 years), we measured fibrinogen, factor VIII, and factor VII. We used sex-stratified stepwise Cox survival analysis to determine relative risks (RRs) for CVD events and all-cause mortality (up to 5 years of follow-up), both unadjusted and adjusted for CVD risk factors and subclinical CVD. After adjustment, comparing the fifth quintile to the first, fibrinogen was significantly associated in men with coronary heart disease events (RR=2.1) and stroke or transient ischemic attack (RR=1.3), and also with mortality within 2.5 years of follow-up (RR=5.8) and later (RR=1.7). Factor VIII was significantly associated in men with coronary heart disease events (RR=1.5) and mortality (RR=1.8), and in women with stroke/transient ischemic attack (RR=1.4). For both factors, values were higher in those who died, whether causes were CVD-related or non-CVD-related, but highest in CVD death. Factor VII exhibited associations with incident angina (RR=1.44) in men and with death in women (RR, middle quintile compared with first=0.66). However, in general, factor VII was not consistently associated with CVD events in this population. We conclude that, if confirmed in other studies, the measurement of fibrinogen and/or factor VIII may help identify older individuals at higher risk for CVD events and mortality.
Keywords: Aged; Cardiovascular Diseases; Factor VII; Factor VIII; Female; Fibrinogen; Humans; Male; Multivariate Analysis; Risk Factors

Relationship of plasmin generation to cardiovascular disease risk factors in elderly men and women. - Sakkinen, P A; Cushman, M; Psaty, B M; Rodriguez, B; Boineau, R; Kuller, L H; Tracy, R P (Arterioscler Thromb Vasc Biol, 1999)
Plasmin-alpha2-antiplasmin complex (PAP) marks plasmin generation and fibrinolytic balance. We recently observed that elevated levels of PAP predict acute myocardial infarction in the elderly, yet little is known about the correlates of PAP. We measured PAP in 800 elderly subjects who were free of clinical cardiovascular disease in 2 cohort studies: the Cardiovascular Health Study and the Honolulu Heart Program. Median PAP levels did not differ between the Cardiovascular Health Study (6.05+/-1.46 nmol/L) and the Honolulu Heart Program (6.11+/-1.44 nmol/L), and correlates of PAP were similar in both cohorts. In CHS, PAP levels increased with age (r=0. 30), procoagulant factors (eg, factor VIIc, r=0.15), thrombin activity (prothrombin fragment F1+2, r=0.29), and inflammation-sensitive proteins (eg, fibrinogen, r=0.44; factor VIIIc, r=0.37). PAP was associated with increased atherosclerosis as measured by the ankle-arm index (AAI) (P for trend, </=0.001). PAP was negatively related to factors associated with the insulin resistance syndrome (IRS) (eg, fasting insulin, r=-0.26; body mass index, r=-0.26), possibly reflecting an association with plasminogen activator inhibitor-1 (r=-0.29). Although our study did not have sufficient power to detect a significant interaction, PAP and AAI appeared to be more weakly associated in subjects with more manifestations of the IRS: PAP appeared more strongly associated with AAI in the subgroup with 0 or 1 metabolic disorders (P</=0.001; slope estimate, -0.14) compared with the subgroup with 2 or more metabolic disorders (P=0.10; slope estimate, -0.08) and in those with non-insulin-dependent diabetes mellitus (P=0.46; slope estimate, -0.04). Although PAP reflects reactive fibrinolysis and is associated with subclinical atherosclerosis, this relationship may be weaker in populations with characteristics of the IRS, possibly reflecting the inhibitory effects of plasminogen activator inhibitor-1 on PAP. Decreased fibrinolysis in the presence of subclinical disease in subjects with hyperinsulinemia or glucose intolerance is consistent with the premise that depressed plasmin generation may enhance the progression of atherosclerosis in these people.
Keywords: Aged; Aged, 80 and over; alpha-2-Antiplasmin; Antifibrinolytic Agents; Asian Continental Ancestry Group; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Fibrinolysin; Fibrinolysis; Humans; Insulin Resistance; Male; Multivariate Analysis; Myocardial Infarction; Plasminogen Activator Inhibitor 1; Risk Factors

The role of APOE epsilon4 in modulating effects of other risk factors for cognitive decline in elderly persons. - Haan, M N; Shemanski, L; Jagust, W J; Manolio, T A; Kuller, L (JAMA, 1999)
CONTEXT: Cognitive decline in elderly persons is often an early predictor of dementia. Subclinical cardiovascular disease (CVD) and diabetes mellitus may contribute to substantial decline in cognitive function in the elderly. These risks may be modified by gene-environment interactions between apolipoprotein E (APOE) genotype and CVD risk factors or subclinical CVD. OBJECTIVES: To examine the association between subclinical CVD and decline in cognitive functioning in the elderly and to examine effect modification by the APOE genotype of the association between subclinical disease and cognitive decline. DESIGN: The Cardiovascular Health Study, a population-based, prospective cohort study. SETTING AND POPULATION: A total of 5888 randomly selected Medicare-eligible participants from Sacramento County, California; Forsyth County, North Carolina; Washington County, Maryland; and Pittsburgh, Pa, aged 65 years or older, who were recruited in 1989-1990 (n = 5201) and in 1992-1993 (n = 687) and who were followed up for 7 and 5 years, respectively. MAIN OUTCOME MEASURES: Change over time in scores on the Modified Mini-Mental State Examination and the Digit Symbol Substitution Test as a function of APOE genotype, subclinical CVD, and diabetes mellitus. RESULTS: Seventy percent of participants had no significant decline on the Modified Mini-Mental State Examination. Systolic blood pressure, the ankle-arm brachial index, atherosclerosis of the internal carotid artery, diabetes mellitus, and several diagnoses of prevalent CVD were significantly associated with declines in scores on the Modified Mini-Mental State Examination and the Digit Symbol Substitution Test. The rate of cognitive decline associated with peripheral vascular disease, atherosclerosis of the common and internal carotid arteries, or diabetes mellitus was increased by the presence of any APOE epsilon4 allele. CONCLUSIONS: Most healthy elderly people did not experience cognitive decline. Measures of subclinical CVD were modest predictors of cognitive decline. Those with any APOE epsilon4 allele in combination with atherosclerosis, peripheral vascular disease, or diabetes mellitus were at substantially higher risk of cognitive decline than those without the APOE epsilon4 allele or subclinical CVD. High levels of atherosclerosis increased cognitive decline independently of APOE genotype.
Keywords: Aged; Aging; Alleles; Apolipoproteins E; Cardiovascular Diseases; Cognition Disorders; Cohort Studies; Diabetes Mellitus; Genotype; Humans; Mental Status Schedule; Prospective Studies; Risk Factors

Stroke risk in an elderly population with atrial fibrillation. - Feinberg, W M; Kronmal, R A; Newman, A B; Kraut, M A; Bovill, E G; Cooper, L; Hart, R G (J Gen Intern Med, 1999)
Patients with nonvalvular atrial fibrillation (AF) have an increased risk of stroke, but the absolute rate of stroke varies widely depending on coexistent vascular disease. We assessed the stroke rate and predictive value of two published schemes for stroke risk stratification in a population-derived cohort of 259 elderly people with nonvalvular AF followed for a median of 5.3 years. The rate of ischemic stroke was 2.8% per year (95% confidence interval [CI] 1.9, 3.9). Thirty-one percent were predicted to be at low risk, and their stroke rate was 1.7% per year (95% CI 0.6, 3.8). Many people with AF in this population-derived cohort had relatively low rates of stroke. Further studies to reliably stratify stroke risk in patients with AF are needed.
Keywords: Aged; Atrial Fibrillation; Cerebrovascular Disorders; Cohort Studies; Humans; Male; Poisson Distribution; Proportional Hazards Models; Risk Factors

Traditional risk factors and subclinical disease measures as predictors of first myocardial infarction in older adults: the Cardiovascular Health Study. - Psaty, B M; Furberg, C D; Kuller, L H; Bild, D E; Rautaharju, P M; Polak, J F; Bovill, E; Gottdiener, J S (Arch Intern Med, 1999)
BACKGROUND: Risk factors for myocardial infarction (MI) have not been well characterized in older adults, and in estimating risk, we sought to assess the individual and joint contributions made by both traditional risk factors and measures of subclinical disease. METHODS: In the Cardiovascular Health Study, we recruited 5888 adults aged 65 years and older from 4 US centers. At baseline in 1989-1990, participants underwent an extensive examination that included traditional risk factors such as blood pressure and fasting glucose level and measures of subclinical disease as assessed by electrocardiography, carotid ultrasonography, echocardiography, pulmonary function, and ankle-arm index. Participants were followed up with semiannual contacts, and all cardiovascular events were classified by the Morbidity and Mortality Committee. The main analytic technique was the Cox proportional hazards model. RESULTS: At baseline, 1967 men and 2979 women had no history of an MI. After follow-up for an average of 4.8 years, there were 302 coronary events, which included 263 patients with MI and 39 with definite fatal coronary disease. The incidence was higher in men (20.7 per 1000 person-years) than women (7.9 per 1000 person-years). In all subjects, the incidence was strongly associated with age, increasing from 7.8 per 1000 person-years in subjects aged 65 to 69 years to 25.6 per 1000 person-years in subjects aged 85 years and older. Glucose level and systolic blood pressure were associated with the incidence of MI, but smoking and lipid measures were not. After adjustment for age and sex, the significant subclinical disease predictors of MI were borderline or abnormal ejection fraction by echocardiography, high levels of intimal-medial thickness of the internal carotid artery, and a low ankle-arm index. Forced vital capacity and electrocardiographic left ventricular mass did not enter the stepwise model. Excluding subjects with clinical cardiovascular diseases such as prior angina or congestive heart failure at baseline had little effect on these results. Risk factors were generally similar in men and women. CONCLUSIONS: After follow-up of 4.8 years, systolic blood pressure, fasting glucose level, and selected subclinical disease measures were important predictors of the incidence of MI in older adults. Uncontrolled high blood pressure may explain about one quarter of the coronary events in this population.
Keywords: Age Distribution; Aged; Female; Follow-Up Studies; Humans; Incidence; Male; Multivariate Analysis; Myocardial Infarction; Predictive Value of Tests; Proportional Hazards Models; Risk; Risk Factors; Sex Distribution

Underdiagnosis and undertreatment of asthma in the elderly. Cardiovascular Health Study Research Group. - Enright, P L; McClelland, R L; Newman, A B; Gottlieb, D J; Lebowitz, M D (Chest, 1999)
OBJECTIVE: To describe the clinical correlates of asthma in a community-based sample of elderly persons. PARTICIPANTS: A community sample of 4,581 persons > or = 65 years old from the Cardiovascular Health Study. MEASUREMENTS: Standardized respiratory, sleep, and quality-of-life (QOL) questions, a medication inventory, spirometry, and ambulatory peak flow. RESULTS: Four percent of the participants reported a current diagnosis of asthma (definite asthma), while another 4% reported at least one attack of wheezing accompanied by chest tightness or dyspnea during the previous 12 months (probable asthma). Smokers and those with congestive heart failure were excluded from the subsequent analyses, leaving 2,527 participants. Of those who had definite asthma, 40% were taking a sympathomimetic bronchodilator, 30% inhaled corticosteroids, 21% theophylline, and 18% oral corticosteroids; 39% were taking no asthma medications. The participants with definite or probable asthma were much more likely than the others to have a family history of asthma, childhood respiratory problems, a history of workplace exposures, dyspnea on exertion, hay fever, chronic bronchitis, nocturnal symptoms, and daytime sleepiness. They were also more likely to report poor general health, symptoms of depression, and limitation of activities of daily living. There was little difference in the morbidity and QOL of participants with recent asthma-like symptoms who had received the diagnosis of asthma versus those who had not. CONCLUSIONS: Asthma in elderly persons is associated with a lower QOL and considerable morbidity when compared with those who do not have asthma symptoms. Asthma is underdiagnosed in this group and is often associated with allergic triggers; inhaled corticosteroids are underutilized.
Keywords: Age Factors; Aged; Aged, 80 and over; Asthma; Female; Humans; Male; Peak Expiratory Flow Rate; Quality of Life; Risk Factors; Spirometry; Vital Capacity

Association between depression and mortality in older adults: the Cardiovascular Health Study. - Schulz, R; Beach, S R; Ives, D G; Martire, L M; Ariyo, A A; Kop, W J (Arch Intern Med, 2000)
BACKGROUND: Studies of the association between depressive symptoms and mortality in elderly populations have yielded contradictory findings. To address these discrepancies, we test this association using the most extensive array of sociodemographic and physical health control variables ever studied, to our knowledge, in a large population-based sample of elderly individuals. OBJECTIVE: To examine the relation between baseline depressive symptoms and 6-year all-cause mortality in older persons, systematically controlling for sociodemographic factors, clinical disease, subclinical disease, and health risk factors. METHODS: A total of 5201 men and women aged 65 years and older from 4 US communities participated in the study. Depressive symptoms and 4 categories of covariates were assessed at baseline. The primary outcome measure was 6-year mortality. RESULTS: Of the 5201 participants, 984 (18.9%) died within 6 years. High baseline depressive symptoms were associated with a higher mortality rate (23.9%) than low baseline depression scores (17.7%) (unadjusted relative risk [RR], 1.41; 95% confidence interval [CI], 1.22-1.63). Depression was also an independent predictor of mortality when controlling for sociodemographic factors (RR, 1.43; 95% CI, 1.23-1.66), prevalent clinical disease (RR, 1.25; 95% CI, 1.07-1.45), subclinical disease indicators (RR, 1.35; 95% CI, 1.15-1.58), or biological or behavioral risk factors (RR, 1.42; 95% CI, 1.22-1.65). When the best predictors from all 4 classes of variables were included as covariates, high depressive symptoms remained an independent predictor of mortality (RR, 1.24; 95% CI, 1.06-1.46). CONCLUSIONS: High levels of depressive symptoms are an independent risk factor for mortality in community-residing older adults. Motivational depletion may be a key underlying mechanism for the depression-mortality effect.
Keywords: Aged; Alcohol Drinking; Depression; Depressive Disorder; Female; Health Status Indicators; Humans; Male; Motivation; Prevalence; Risk Factors; Smoking; Socioeconomic Factors; United States

Chlamydia pneumoniae, herpes simplex virus type 1, and cytomegalovirus and incident myocardial infarction and coronary heart disease death in older adults : the Cardiovascular Health Study. - Siscovick, D S; Schwartz, S M; Corey, L; Grayston, J T; Ashley, R; Wang, S P; Psaty, B M; Tracy, R P; Kuller, L H; Kronmal, R A (Circulation, 2000)
BACKGROUND: Whether serological evidence of prior infection with Chlamydia pneumoniae, herpes simplex virus type 1 (HSV-1), and cytomegalovirus (CMV) is associated with myocardial infarction (MI) and coronary heart disease (CHD) death remains a source of controversy. METHODS AND RESULTS: We conducted a nested case-control study among participants in the Cardiovascular Health Study, a cohort study of persons aged >/=65 years. Cases experienced an incident MI and CHD death (n=213). Control subjects were matched to cases by age, sex, clinic, year of enrollment, and month of blood draw (n=405). Serum was analyzed for IgG antibodies to C pneumoniae, HSV-1, and CMV. After adjustment for other risk factors, the risk of MI and CHD death was associated with the presence of IgG antibodies to HSV-1 (odds ratio [OR] 2.0, 95% CI 1.1 to 3.6) but was not associated with the presence of IgG antibodies to either C pneumoniae (OR 1.1, 95% CI 0.7 to 1.8) or CMV (OR 1.2, 95% CI 0.7 to 1.9). Although there was little association with low to moderate C pneumoniae antibody titers (</=1:512), high-titer (1:1024) C pneumoniae antibody was associated with an increased risk (OR 2.2, 95% CI 1.1 to 4.4). CONCLUSIONS: Among older adults, the presence of IgG antibodies to HSV-1 was associated with a 2-fold increase in the risk of incident MI and CHD death. For C pneumoniae, only high-titer IgG antibodies were associated with an increased risk of MI and CHD death. The presence of IgG antibodies to CMV was not associated with risk among the elderly.
Keywords: Adult; Age Factors; Aged; Antibodies, Bacterial; Antibodies, Viral; Case-Control Studies; Chlamydophila pneumoniae; Coronary Disease; Cytomegalovirus; Female; Herpesvirus 1, Human; HIV Antibodies; Humans; Immunoglobulin G; Male; Myocardial Infarction; Risk Factors

Clinical correlates of ventricular and sulcal size on cranial magnetic resonance imaging of 3,301 elderly people. The Cardiovascular Health Study. Collaborative Research Group. - Longstreth, W T; Arnold, A M; Manolio, T A; Burke, G L; Bryan, N; Jungreis, C A; O'Leary, D; Enright, P L; Fried, L (Neuroepidemiology, 2000)
To identify potential risk factors for and clinical manifestations of ventricular and sulcal enlargement on cranial magnetic resonance imaging (MRI), 3,301 community-dwelling people 65 years or older without a history of stroke or transient ischemic attack underwent extensive standardized evaluations and MRI. In the multivariate model, increased age and white matter grade on MRI were the dominant risk factors for ventricular and sulcal grade. For ventricular grade, other than race, for which non-Blacks had higher grades, models for men and women shared no other factors. For sulcal grades, models for men and women shared variables reflecting cigarette smoking and diabetes. Clinical features were correlated more strongly with ventricular than sulcal grade and more strongly for women than men. Significant age-adjusted correlations between ventricular grade and the Digit-Symbol Substitution Test were found for men and women. Prospective studies will be needed to extend findings of this cross-sectional analysis.
Keywords: Age Distribution; Age Factors; Aged; Aging; Cerebral Ventricles; Continental Population Groups; Cross-Sectional Studies; Diabetes Complications; Female; Humans; Hypertrophy; Linear Models; Magnetic Resonance Imaging; Male; Multivariate Analysis; Risk Factors; Severity of Illness Index; Sex Distribution; Sex Factors; Smoking; Stroke

Clustering of procoagulation, inflammation, and fibrinolysis variables with metabolic factors in insulin resistance syndrome. - Sakkinen, P A; Wahl, P; Cushman, M; Lewis, M R; Tracy, R P (Am J Epidemiol, 2000)
The known metabolic cardiovascular disease risk factors associated with insulin resistance syndrome (IRS) do not adequately explain the excess cardiovascular disease risk attributed to this syndrome, and abnormalities in hemostatic variables may contribute to this excess risk. Using data from 322 nondiabetic elderly men and women (aged 65-100 years) participating in the Cardiovascular Health Study during 1989-1990, the authors performed factor analysis on 10 metabolic risk factors associated with IRS and 11 procoagulation, inflammation, and fibrinolysis variables to examine the clustering of the metabolic and hemostatic risk markers. Factor analysis of the metabolic variables confirmed four uncorrelated factors: body mass, insulin/glucose, lipids, and blood pressure. Adding the hemostatic variables yielded three new factors interpreted as inflammation, vitamin K-dependent proteins, and procoagulant activity. Plasminogen activator inhibitor-1 clustered with the body mass factor, supporting the hypothesis that obesity is related to impaired fibrinolysis. Fibrinogen clustered with the inflammation summary factor rather than procoagulant activity, supporting the position that fibrinogen principally reflects underlying inflammation rather than procoagulant potential. The authors conclude that should hemostatic variables be shown to contribute to IRS-related cardiovascular disease, apart from plasminogen activator inhibitor-1, they may do so independently of the established metabolic abnormalities.
Keywords: Aged; Aged, 80 and over; Antigens; Blood Coagulation; Cardiovascular Diseases; Cluster Analysis; Factor Analysis, Statistical; Factor VII; Female; Fibrinogen; Fibrinolysis; Humans; Inflammation; Insulin Resistance; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Risk Factors

Coronary artery calcification in older adults with minimal clinical or subclinical cardiovascular disease. - Newman, A B; Naydeck, B; Sutton-Tyrrell, K; Edmundowicz, D; Gottdiener, J; Kuller, L H (J Am Geriatr Soc, 2000)
BACKGROUND: Coronary artery calcification (CAC) reflects the extent of coronary artery atherosclerosis. The extent of coronary artery calcification is not well described in older adults. OBJECTIVE: To determine the extent of CAC in older adults participating in a large population study of cardiovascular disease (CVD), especially those characterized as having minimal clinical or subclinical cardiovascular disease. DESIGN: An observational epidemiologic study. POPULATION: Participants in the Cardiovascular Health Study Cohort, mean age 78 years, who had electron beam computed tomography (EBT) scan of the heart (n = 133); included were 106 persons with no prior evidence of clinical or subclinical CVD. MEASUREMENTS: Total CAC score was measured using cardiac EBT. Cardiovascular disease and risk factors, as well as carotid ultrasound, electrocardiogram, echocardiogram, and ankle-arm index, had been measured previously to define subclinical disease. Previous cerebral magnetic resonance imaging was also evaluated. RESULTS: Overall, the CAC scores were higher in those with clinical cardiovascular disease or evidence of subclinical cardiovascular disease than in those with no evidence of disease. For the 106 participants without evidence of clinical or subclinical disease, the median score was 176, compared with 367 in those with subclinical disease and 923 in those with clinical CVD. Seventeen persons had scores of zero. There was little difference in risk factors across quartiles of CAC in the subgroup of 106 with prior characterization of minimal CVD despite the broad range of CAC scores. There was a higher proportion of those with white matter grade > or = 2 by magnetic resonance imaging among those with higher CAC scores (P = .025). Infarct-like lesions prevalence ranged from 12.5% in the lowest group to 47.1% in the highest CAC group (P = .019). CONCLUSIONS: Older adults with evidence of clinical or subclinical CVD have higher total CAC scores. Though the extent of coronary artery calcification was lower in those with minimal evidence of CVD, the range was broad and not explained by CVD risk factors.
Keywords: Aged; Aging; Analysis of Variance; Calcinosis; Cardiovascular Diseases; Chi-Square Distribution; Coronary Artery Disease; Coronary Disease; Female; Humans; Male; Risk Factors; Statistics, Nonparametric; Tomography, X-Ray Computed

Daytime sleepiness predicts mortality and cardiovascular disease in older adults. The Cardiovascular Health Study Research Group. - Newman, A B; Spiekerman, C F; Enright, P; Lefkowitz, D; Manolio, T; Reynolds, C F; Robbins, J (J Am Geriatr Soc, 2000)
INTRODUCTION: As part of the baseline examination in the Cardiovascular Health Study, sleep disturbance symptoms including snoring and daytime sleepiness, were assessed as potential risk factors or precipitants of cardiovascular disease (CVD). Because of the association of sleep disturbance with poorer health and the possible associations of sleep apnea with CVD, we hypothesized that those with poorer sleep or daytime sleepiness may be at increased risk of mortality or incident CVD. SETTING: Participants (n = 5888) were recruited in 1989, with an additional minority cohort recruited in 1993, in four US communities for a cohort study designed to evaluate risk factors for cardiovascular disease. METHODS: An interview-administered questionnaire regarding health and sleep habits with ongoing ascertainment of total mortality and cardiovascular disease morbidity and mortality, including total CVD morbidity and mortality, incident myocardial infarction, and congestive heart failure. RESULTS: Daytime sleepiness was the only sleep symptom that was significantly associated with mortality in both men and women. The unadjusted hazard ratio was 2.12 (1.66, 2.72) in women and 1.40 (1.12, 1.73) in men. Men who reported difficulty falling asleep also had an increased mortality rate (HR = 1.43 (1.14, 1.80)) which was not seen in women. The risks were attenuated with adjustment for age but remained significant for daytime sleepiness in women (HR = 1.82 (1.42, 2.34)) and for difficulty falling asleep in men. (HR = 1.29 (1.03, 1.63)). Frequent awakenings, early morning awakening, and snoring were not associated with a significantly increased risk of mortality in these older men and women. Crude event rates were evaluated for total incident cardiovascular morbidity and mortality, incident myocardial infarction, and incident congestive heart failure (CHF). Incident CVD rates were higher in both men and women with daytime sleepiness. The aged adjusted HR was 1.35 (95% CI = 1.03, 1.76) in men and was 1.66 (95% CI = 1.28, 2.16) in women. Incident CVD was not higher in those with any other sleep disturbance including snoring. The risk of CVD events associated with daytime sleepiness was attenuated but remained significant in women after adjustment for age. Incident myocardial infarction (MI) rates were also higher in women with daytime sleepiness but were not significantly higher in men. Incident CHF rates were increased in both men and women with daytime sleepiness. In men, the age adjusted HR was 1.49 (95% CI, 1.12- 1.98) and in women, was 2.21 (95% CI, 1.64-2.98). Women reporting both daytime sleepiness and frequent awakening had a hazard ratio of 2.34 (95% CI, 1.66-3.29) for incident CHF compared with those with daytime sleepiness but without frequent awakening. This interaction was not found in men. CONCLUSIONS: In this study, daytime sleepiness was the only sleep disturbance symptom that was associated with mortality, incident CVD morbidity and mortality, MI, and CHF. These findings were stronger in women than men, i.e., the associations persisted for mortality, CVD, and CHF in women after adjustment for age and other factors. Thus, a report of daytime sleepiness identifies older adults at increased risk for total and cardiovascular mortality, and is an independent risk factor in women.
Keywords: Age Factors; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Female; Health Status; Heart Failure; Humans; Incidence; Male; Multivariate Analysis; Myocardial Infarction; Odds Ratio; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Sleep Stages; Sleep Wake Disorders; Snoring; Surveys and Questionnaires; United States

Depressive symptoms and risks of coronary heart disease and mortality in elderly Americans. Cardiovascular Health Study Collaborative Research Group. - Ariyo, A A; Haan, M; Tangen, C M; Rutledge, J C; Cushman, M; Dobs, A; Furberg, C D (Circulation, 2000)
BACKGROUND: Several epidemiological studies have associated depressive symptoms with cardiovascular disease. We investigated whether depressive symptoms constituted a risk for coronary heart disease (CHD) and total mortality among an apparently healthy elderly cohort. METHODS AND RESULTS: In a prospective cohort of 5888 elderly Americans (>/=65 years) who were enrolled in the Cardiovascular Health Study, 4493 participants who were free of cardiovascular disease at baseline provided annual information on their depressive status, which was assessed using the Depression Scale of the Center for Epidemiological Studies. These 4493 subjects were followed for 6 years for the development of CHD and mortality. The cumulative mean depression score was assessed for each participant up to the time of event (maximum 6-year follow-up). Using time-dependent, proportional-hazards models, the unadjusted hazard ratio associated with every 5-unit increase in mean depression score for the development of CHD was 1.15 (P:=0.006); the ratio for all-cause mortality was 1.29 (P:<0.0001). In multivariate analyses adjusted for age, race, sex, education, diabetes, hypertension, cigarette smoking, total cholesterol, triglyceride level, congestive heart failure, and physical inactivity, the hazard ratio for CHD was 1.15 (P:=0.006) and that for all-cause mortality was 1.16 (P:=0.006). Among participants with the highest cumulative mean depression scores, the risk of CHD increased by 40% and risk of death by 60% compared with those who had the lowest mean scores. CONCLUSIONS: Among elderly Americans, depressive symptoms constitute an independent risk factor for the development of CHD and total mortality.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Coronary Disease; Depression; Female; Humans; Male; Prospective Studies; Risk Factors; United States

Diabetes mellitus: subclinical cardiovascular disease and risk of incident cardiovascular disease and all-cause mortality. - Kuller, L H; Velentgas, P; Barzilay, J; Beauchamp, N J; O'Leary, D H; Savage, P J (Arterioscler Thromb Vasc Biol, 2000)
Previously diagnosed diabetes mellitus, newly diagnosed diabetes mellitus, and impaired glucose tolerance are important determinants of the risk of clinical cardiovascular disease (CVD). We have evaluated the relation of patients with subclinical CVD, diabetes, and impaired glucose tolerance and "normal" subjects and the risk of clinical CVD in the Cardiovascular Health Study. Diabetes (1343), impaired glucose tolerance (1433), and normal (2421) were defined by World Health Organization criteria at baseline in 1989 to 1990. The average follow-up was 6.4 years (mean age 73 years). Diabetics had a higher prevalence of clinical and subclinical CVD at baseline. Compared with diabetes in the absence of subclinical disease, the presence of subclinical CVD and diabetes was associated with significant increased adjusted relative risk of death (1.5, CI 0.93 to 2.41), relative risk of incident coronary heart disease (1.99, CI 1.25 to 3.19), and incident myocardial infarction (1.93, CI 0.96 to 3.91). The risk of clinical events was greater for participants with a history of diabetes compared with newly diagnosed diabetics at baseline. Compared with nondiabetic nonhypertensive subjects without subclinical disease, patients with a combination of diabetes, hypertension, and subclinical disease had a 12-fold increased risk of stroke. Fasting blood glucose levels were a weak predictor of incident coronary heart disease as were most other risk factors. Subclinical CVD was the primary determinant of clinical CVD among diabetics in the Cardiovascular Health Study.
Keywords: Aged; Arteriosclerosis; Coronary Disease; Diabetes Mellitus, Type 1; Diabetes Mellitus, Type 2; Diabetic Angiopathies; Female; Humans; Incidence; Male; Multivariate Analysis; Myocardial Infarction; Prevalence; Proportional Hazards Models; Risk Factors; Sex Distribution; Stroke

Does snoring predict sleepiness independently of apnea and hypopnea frequency? - Gottlieb, D J; Yao, Q; Redline, S; Ali, T; Mahowald, M W (Am J Respir Crit Care Med, 2000)
Obstructive apneas and hypopneas during sleep are a well recognized cause of excessive daytime sleepiness. Snoring is also associated with excess sleepiness, although it is not known whether this reflects an independent effect of snoring or whether snoring is simply a marker for obstructive sleep apnea. To further explore the relation of snoring to sleepiness, we conducted a cross-sectional cohort study of community-dwelling adults participating in the Sleep Heart Health Study. The study sample comprises 2,737 men and 3,040 women with a mean age of 64 (SD 11) yr. Sleepiness was quantified using the Epworth Sleepiness Scale (ESS). Snoring history was obtained via a self-completion questionnaire. The respiratory disturbance index (RDI), defined as the number of apneas plus hypopneas per hour of sleep, was measured during in-home polysomnography. The ESS score increased progressively with increasing RDI, from a mean of 7.1 (4.2) in subjects with RDI < 1.5 to 8.8 (4.8) in subjects with RDI >/= 15 (p < 0.001). A progressive increase in ESS score was also seen across five categories of snoring frequency, from 6.4 (4.2) in current nonsnorers to 9.3 (4.8) in subjects who snored six to seven nights per week (p < 0.001). The prevalence of excessive daytime sleepiness, defined as an ESS score >/= 11, increased from 15% in never-snorers to 39% in those who snored six to seven nights per week. The relation of snoring to sleepiness was seen at all levels of RDI, with no significant change in the relation of snoring to ESS score after adjustment for RDI in multivariate models. The effects of snoring and RDI on sleepiness were little affected by adjustment for age, sex, race, body mass index, or questionnaire evidence of insufficient sleep time or nocturnal leg jerks or cramps. We conclude that both snoring and RDI are independently associated with excess sleepiness in community-dwelling, middle-aged and older adults.
Keywords: Adult; Aged; Arousal; Cohort Studies; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Polysomnography; Risk Factors; Sleep Apnea, Obstructive; Snoring; Wakefulness

Effects of varying approaches for identifying respiratory disturbances on sleep apnea assessment. - Redline, S; Kapur, V K; Sanders, M H; Quan, S F; Gottlieb, D J; Rapoport, D M; Bonekat, W H; Smith, P L; Kiley, J P; Iber, C (Am J Respir Crit Care Med, 2000)
Varying approaches to measuring the respiratory disturbance index (RDI) may lead to discrepant estimates of the severity of sleep-disordered breathing (SDB). In this study, we assessed the impact of varying the use of corroborative data (presence and degree of desaturation and/or arousal) to identify hypopneas and apneas. The relationships among 10 RDIs defined by various definitions of apneas and hypopneas were assessed in 5,046 participants in the Sleep Heart Health Study (SHHS) who underwent overnight unattended 12-channel polysomnography (PSG). The magnitude of the median RDI varied 10-fold (i.e., 29.3 when the RDI was based on events identified on the basis of flow or volume amplitude criteria alone to 2.0 for an RDI that required an associated 5% desaturation with events). The correlation between RDIs based on different definitions ranged from 0.99 to 0.68. The highest correlations were among RDIs that required apneas and hypopneas to be associated with some level of desaturation. Lower correlations were observed between RDIs that required desaturation as compared with RDIs defined on the basis of amplitude criteria alone or associated arousal. These data suggest that different approaches for measuring the RDI may contribute to substantial variability in identification and classification of the disorder.
Keywords: Adult; Aged; Aged, 80 and over; Arousal; Diagnosis, Differential; Female; Humans; Lung Volume Measurements; Male; Middle Aged; Observer Variation; Oxygen; Oxyhemoglobins; Polysomnography; Risk Factors; Sleep Apnea Syndromes

Estrogen use, APOE, and cognitive decline: evidence of gene-environment interaction. - Yaffe, K; Haan, M; Byers, A; Tangen, C; Kuller, L (Neurology, 2000)
OBJECTIVE: APOE-epsilon4 increases the risk of cognitive decline, while elderly women who take estrogen may have less risk of cognitive decline. The authors sought to determine whether estrogen use modifies the association between APOE-epsilon4 and cognitive decline. METHOD: - As part of the Cardiovascular Health Study, 3,393 Medicare-eligible women (> or =65 years) were randomly selected and recruited from Sacramento County, CA; Washington County, MD; Forsyth County, NC; and Pittsburgh, PA. Cognitive testing was administered annually; the authors studied the 2,716 women with cognitive testing on > or =2 visits. They analyzed change in score on the Modified Mini-Mental State Examination (3MS) as a function of estrogen use, APOE genotype, and baseline common and internal carotid artery wall thickening. RESULTS: A total of 297 (11%) women were current estrogen users and 336 (12%) were past estrogen users. Over the 6-year average follow-up, baseline current users declined 1.5 points on the 3MS whereas never users declined 2.7 points (p = 0.023). Compared with epsilon4-negative women, epsilon4-positive women had a greater adjusted hazard ratio of cognitive impairment (3MS < 80), hazard risk [HR] = 1.47; 95% CI, 1.13 to 1.90. There was an interaction between estrogen use and epsilon4 presence (p = 0.037). Among epsilon4-negative women, current estrogen use reduced the risk of adjusted cognitive impairment compared with never users by almost half (HR = 0.59; 95% CI, 0.36 to 0.99), whereas, it did not reduce the risk among epsilon4-positive women (current use, HR = 1.33; 95% CI, 0.74 to 2.42). Compared with never use, current estrogen use was associated with less internal and common carotid wall thickening in epsilon4-negative women but not in epsilon4-positive women (p for interaction < 0.05 for both). Differences remained after adjusting for age, education, race, and stroke. CONCLUSIONS: Estrogen use was associated with less cognitive decline among epsilon4-negative women but not epsilon4-positive women. Potential mechanisms, including carotid atherosclerosis, by which epsilon4 may interact with estrogen and cognition warrant further investigation.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Apolipoproteins E; Carotid Stenosis; Estrogen Replacement Therapy; Female; Genotype; Humans; Mental Status Schedule; Neuropsychological Tests; Risk Factors

Predictors of congestive heart failure in the elderly: the Cardiovascular Health Study. - Gottdiener, J S; Arnold, A M; Aurigemma, G P; Polak, J F; Tracy, R P; Kitzman, D W; Gardin, J M; Rutledge, J E; Boineau, R C (J Am Coll Cardiol, 2000)
OBJECTIVES: We sought to characterize the predictors of incident congestive heart failure (CHF), as determined by central adjudication, in a community-based elderly population. BACKGROUND: The elderly constitute a growing proportion of patients admitted to the hospital with CHF, and CHF is a leading source of morbidity and mortality in this group. Elderly patients differ from younger individuals diagnosed with CHF in terms of biologic characteristics. METHODS: We analyzed data from the Cardiovascular Health Study, a prospective population-based study of 5,888 elderly people >65 years old (average 73 +/- 5, range 65 to 100) at four locations. Multiple laboratory measures of cardiovascular structure and function, blood chemistries and functional assessments were obtained. RESULTS: During an average follow-up of 5.5 years (median 6.3), 597 participants developed incident CHF (rate 19.3/1,000 person-years). The incidence of CHF increased progressively across age groups and was greater in men than in women. On multivariate analysis, other independent predictors included prevalent coronary heart disease, stroke or transient ischemic attack at baseline, diabetes, systolic blood pressure (BP), forced expiratory volume 1 s, creatinine >1.4 mg/dl, C-reactive protein, ankle-arm index <0.9, atrial fibrillation, electrocardiographic (ECG) left ventricular (LV) mass, ECG ST-T segment abnormality, internal carotid artery wall thickness and decreased LV systolic function. Population-attributable risk, determined from predictors of risk and prevalence, was relatively high for prevalent coronary heart disease (13.1%), systolic BP > or =140 mm Hg (12.8%) and a high level of C-reactive protein (9.7%), but was low for subnormal LV function (4.1%) and atrial fibrillation (2.2%). CONCLUSIONS: The incidence of CHF is high in the elderly and is related mainly to age, gender, clinical and subclinical coronary heart disease, systolic BP and inflammation. Despite the high relative risk of subnormal systolic LV function and atrial fibrillation, the actual population risk of these for CHF is small because of their relatively low prevalence in community-dwelling elderly people.
Keywords: Aged; Aged, 80 and over; Coronary Disease; Female; Geriatric Assessment; Heart Failure; Humans; Ischemic Attack, Transient; Male; Prospective Studies; Risk Factors; Survival Rate

Prevalence, predisposing factors, and prognosis of clinically unrecognized myocardial infarction in the elderly. - Sheifer, S E; Gersh, B J; Yanez, N D; Ades, P A; Burke, G L; Manolio, T A (J Am Coll Cardiol, 2000)
OBJECTIVES: This study was designed to determine the prevalence of unrecognized myocardial infarction (UMI), as well as risk factors, and to compare prognosis after detection of previously UMI to that after recognized myocardial infarction (RMI). BACKGROUND: Past studies revealed that a significant proportion of MIs escape recognition, and that prognosis after such events is poor, but the epidemiology of UMI has not been reassessed in the contemporary era. METHODS: The Cardiovascular Health Study (CHS) database, composed of individuals > or =65, was queried for participants who, at entry, demonstrated electrocardiographic evidence of a prior Q-wave MI, but who lacked a history of this diagnosis. The features and outcomes of this group were compared to those of individuals with prevalent RMI. RESULTS: Of 5,888 participants, 901 evidenced a past MI, and 201 (22.3%) were previously unrecognized. The independent predictors of UMI were the absence of angina and the absence of congestive heart failure (CHF). Six-year mortality did not significantly differ between the two groups. CONCLUSIONS: 1) In the elderly, UMI continues to represent a significant proportion of all MIs; 2) associations with angina and CHF may reflect complex neurological issues, but they also may represent diagnosis bias; 3) these individuals can otherwise not be distinguished from those with recognized infarctions; and 4) mortality rates after UMI and RMI are similar. Future studies should address screening for UMI, risk stratification after detection of previously UMI, and the role of standard post-MI therapies.
Keywords: Aged; Cause of Death; Coronary Disease; Cross-Sectional Studies; Databases, Factual; Electrocardiography; Female; Follow-Up Studies; Humans; Male; Myocardial Infarction; Prognosis; Risk Factors; Stroke; Survival Rate

Tobacco, hypertension, and vascular disease: risk factors for renal functional decline in an older population. - Bleyer, A J; Shemanski, L R; Burke, G L; Hansen, K J; Appel, R G (Kidney Int, 2000)
BACKGROUND: A decline in renal function with age has been noted in some but not all individuals. The purpose of this study was to identify risk factors associated with a clinically significant increase in serum creatinine (of at least 0.3 mg/dL) in an older nondiabetic population. METHODS: A retrospective case-control study was performed analyzing data obtained from 4142 nondiabetic participants of the Cardiovascular Health Study Cohort, all at least 65 years of age, who had two measurements of serum creatinine performed at least three years apart. Cases were identified as participants who developed an increase in serum creatinine of at least 0.3 mg/dL, with controls including participants who did not sustain such an increase. RESULTS: There was an increase in the serum creatinine of at least 0.3 mg/dL in 2.8% of the population. In a multivariate "best-fit" model adjusted for gender, weight, black race, baseline serum creatinine, and age, the following factors were associated with an increase in serum creatinine: number of cigarettes smoked per day, systolic blood pressure, and maximum internal carotid artery intimal thickness. CONCLUSIONS: These data suggest that three very preventable or treatable conditions-hypertension, smoking, and prevalent vascular disease, which are associated with large and small vessel disease-are highly associated with clinically important changes in renal function in an older population.
Keywords: African Continental Ancestry Group; Aged; Aging; Cohort Studies; Creatinine; European Continental Ancestry Group; Female; Humans; Hypertension; Kidney; Male; Regression Analysis; Retrospective Studies; Risk Factors; Smoking; Vascular Diseases

Area characteristics and individual-level socioeconomic position indicators in three population-based epidemiologic studies. - Diez-Roux, A V; Kiefe, C I; Jacobs, D R; Haan, M; Jackson, S A; Nieto, F J; Paton, C C; Schulz, R (Ann Epidemiol, 2001)
PURPOSE: There is growing interest in incorporating area indicators into epidemiologic analyses. Using data from the 1990 U.S. Census linked to individual-level data from three epidemiologic studies, we investigated how different area indicators are interrelated, how measures for different sized areas compare, and the relation between area and individual-level social position indicators. METHODS: The interrelations between 13 area indicators of wealth/income, education, occupation, and other socioenvironmental characteristics were investigated using correlation coefficients and factor analyses. The extent to which block-group measures provide information distinct from census tract measures was investigated using intraclass correlation coefficients. Loglinear models were used to investigate associations between area and individual-level indicators. RESULTS: Correlations between area measures were generally in the 0.5--0.8 range. In factor analyses, six indicators of income/wealth, education, and occupation loaded on one factor in most geographic sites. Correlations between block-group and census tract measures were high (correlation coefficients 0.85--0.96). Most of the variability in block-group indicators was between census tracts (intraclass correlation coefficients 0.72--0.92). Although individual-level and area indicators were associated, there was evidence of important heterogeneity in area of residence within individual-level income or education categories. The strength of the association between individual and area measures was similar in the three studies and in whites and blacks, but blacks were much more likely to live in more disadvantaged areas than whites. CONCLUSIONS: Area measures of wealth/income, education, and occupation are moderately to highly correlated. Differences between using census tract or block-group measures in contextual investigations are likely to be relatively small. Area and individual-level indicators are far from perfectly correlated and provide complementary information on living circumstances. Differences in the residential environments of blacks and whites may need to be taken into account in interpreting race differences in epidemiologic studies.
Keywords: Adult; Black or African American; Cardiovascular Diseases; Demography; Educational Status; Factor Analysis, Statistical; Humans; Income; Linear Models; Occupations; Risk Factors; Social Class; Social Environment; Socioeconomic Factors; Statistics, Nonparametric; United States; White People

Association between blood pressure level and the risk of myocardial infarction, stroke, and total mortality: the cardiovascular health study. - Psaty, B M; Furberg, C D; Kuller, L H; Cushman, M; Savage, P J; Levine, D; O'Leary, D H; Bryan, R N; Anderson, M; Lumley, T (Arch Intern Med, 2001)
BACKGROUND: Recent reports have drawn attention to the importance of pulse pressure as a predictor of cardiovascular events. Pulse pressure is used neither by clinicians nor by guidelines to define treatable levels of blood pressure. METHODS: In the Cardiovascular Health Study, 5888 adults 65 years and older were recruited from 4 US centers. At baseline in 1989-1990, participants underwent an extensive examination, and all subsequent cardiovascular events were ascertained and classified. RESULTS: At baseline, 1961 men and 2941 women were at risk for an incident myocardial infarction or stroke. During follow-up that averaged 6.7 years, 572 subjects had a coronary event, 385 had a stroke, and 896 died. After adjustment for potential confounders, systolic blood pressure (SBP), diastolic blood pressure (DBP), and pulse pressure were directly associated with the risk of incident myocardial infarction and stroke. Only SBP was associated with total mortality. Importantly, SBP was a better predictor of cardiovascular events than DBP or pulse pressure. In the adjusted model for myocardial infarction, a 1-SD change in SBP, DBP, and pulse pressure was associated with hazard ratios (95% confidence intervals) of 1.24 (1.15-1.35), 1.13 (1.04-1.22), and 1.21 (1.12-1.31), respectively; and adding pulse pressure or DBP to the model did not improve the fit. For stroke, the hazard ratios (95% confidence intervals) were 1.34 (1.21-1.47) with SBP, 1.29 (1.17-1.42) with DBP, and 1.21 (1.10-1.34) with pulse pressure. The association between blood pressure level and cardiovascular disease risk was generally linear; specifically, there was no evidence of a J-shaped relationship. In those with treated hypertension, the hazard ratios for the association of SBP with the risks for myocardial infarction and stroke were less pronounced than in those without treated hypertension. CONCLUSION: In this population-based study of older adults, although all measures of blood pressure were strongly and directly related to the risk of coronary and cerebrovascular events, SBP was the best single predictor of cardiovascular events.
Keywords: Aged; Blood Pressure; Female; Humans; Male; Myocardial Infarction; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; Survival Rate; United States

The association of bone mineral density and depression in an older population. - Robbins, J; Hirsch, C; Whitmer, R; Cauley, J; Harris, T (J Am Geriatr Soc, 2001)
OBJECTIVE: To evaluate the association between bone mineral density (BMD) and measurements of depression in an older population. DESIGN: Population-based, cross-sectional study. SETTING: Study subjects were participants in the Cardiovascular Health Study (CHS), a longitudinal, long-term, follow-up study, at the University of California Davis (Sacramento, California) and the University of Pittsburgh (Pittsburgh, Pennsylvania) clinical centers. PARTICIPANTS: A random sample of 1,566 Medicare enrollees age 65 and older enrolled in the CHS. MEASUREMENTS: Total hip BMD, measured using dual energy x-ray absorptiometry (DEXA), after adjustment for multiple covariates, was compared with depression evaluated with the Center for Epidemiological Studies 10-item Depression Scale (CES-Dm). Risk factors for osteoporosis were compared in depressed and nondepressed participants. Potential correlates were entered into a regression model. Depression scores were compared in normal, osteopenic, and osteoporotic individuals. RESULTS: Sixteen percent of participants were clinically depressed; 9% had BMDs in the osteoporotic range. Mean BMD was 40 mg/cm2 lower in those with clinical depression. High CES-Dm scores were associated with lower BMD (P < .001) when adjusted for body mass index (BMI), age, kilocalories of activity, estrogen use, gender, race, smoking and drinking. When stratified by race, this remained true for all Caucasians (P < .01), all African Americans (P < .05), and when stratified by race and gender the association remained only for all Caucasian women (P < .001). In women and Caucasian men there was an increase in depression scores among individuals with osteoporotic-range BMDs. CONCLUSIONS: A significant association was found between BMD and depressive symptoms after adjustment for osteoporosis risk factors. In Caucasians, depressive symptoms were associated with both osteoporotic and osteopenic levels of BMD. Causality cannot be ascribed, with only one measurement of BMD. We postulate that there may be an unmeasured third factor, such as an endogenous steroid, that is responsible for both low BMD and depression.
Keywords: Absorptiometry, Photon; Aged; Analysis of Variance; Black People; Body Mass Index; Bone Density; Bone Diseases, Metabolic; California; Cross-Sectional Studies; Depression; Energy Metabolism; Exercise; Female; Follow-Up Studies; Fractures, Bone; Humans; Linear Models; Male; Osteoporosis; Pennsylvania; Population Surveillance; Psychiatric Status Rating Scales; Radionuclide Imaging; Risk Factors; Sex Distribution; Single-Blind Method; White People

The association of sleep-disordered breathing and sleep symptoms with quality of life in the Sleep Heart Health Study. - Baldwin, C M; Griffith, K A; Nieto, F J; O'Connor, G T; Walsleben, J A; Redline, S (Sleep, 2001)
This study assessed the extent to which sleep-disordered breathing (SDB), difficulty initiating and maintaining sleep (DIMS), and excessive daytime sleepiness (EDS) were associated with impairment of quality of life (QoL) using the SF-36. Participants (n=5,816; mean age=63 years; 52.5% women) were enrolled in the nation-wide population-based Sleep Heart Health Study (SHHS) implemented to investigate sleep-disordered breathing as a risk factor in the development of cardiovascular disease. Each transformed SF-36 scale was analyzed independently using multiple logistic regression analysis with sleep and other potential confounding variables (e.g., age, ethnicity) included as independent variables. Men (11.6%) were significantly more likely to have SDB compared to women (5.6%), while women (42.4%) were significantly more likely to report DIMS than men (32.5%). Vitality was the sole SF-36 scale to have a linear association with the clinical categories of SDB (mild, moderate, severe SDB). However, individuals with severe SDB indicated significantly poorer QoL on several SF-36 scales. Both DIMS and EDS were strongly associated with reduced QoL even after adjusting for confounding variables for both sexes. Findings suggest 1) mild to moderate SDB is associated with reduced vitality, while severe SDB is more broadly associated with poorer QoL, 2) subjective sleep symptoms are comprehensively associated with poorer QoL, and 3) SF-36 mean score profiles for SDB and sleep symptoms are equivalent to other chronic diseases in the U.S. general population.
Keywords: Adult; Cardiovascular Diseases; Chronic Disease; Circadian Rhythm; Disorders of Excessive Somnolence; Female; Health Status; Humans; Male; Middle Aged; Polysomnography; Population Surveillance; Prevalence; Quality of Life; Risk Factors; Severity of Illness Index; Sleep Apnea Syndromes; United States

Cardiovascular disease and mortality in older adults with small abdominal aortic aneurysms detected by ultrasonography: the cardiovascular health study. - Newman, A B; Arnold, A M; Burke, G L; O'Leary, D H; Manolio, T A (Ann Intern Med, 2001)
BACKGROUND: Persons with abdominal aortic aneurysm are more likely to have a higher prevalence of risk factors for and clinical manifestations of cardiovascular disease. It is unknown whether these factors explain the high mortality rate associated with abdominal aortic aneurysm. OBJECTIVE: To describe the risk for mortality, cardiovascular mortality, and cardiovascular morbidity in persons screened for abdominal aortic aneurysm. DESIGN: Longitudinal cohort study. SETTING: Four communities in the United States. PARTICIPANTS: 4734 men and women older than 65 years of age recruited from Medicare eligibility lists. MEASUREMENTS: Abdominal ultrasonography was used to measure the aortic diameter and the ratio of infrarenal to suprarenal measurement of aortic diameter in 1992-1993. Abdominal aortic aneurysm was defined as aortic diameter of 3 cm or greater or infrarenal-to-suprarenal ratio of 1.2 or greater. Mortality, cardiovascular disease mortality, incident cardiovascular disease, and repair or rupture were assessed after 4.5 years. RESULTS: The prevalence of aneurysm was 8.8%, and 87.7% of aneurysms were 3.5 cm or less in diameter. Rates of total mortality (65.1 vs. 32.8 per 1000 person-years), cardiovascular mortality (34.3 vs. 13.8 per 1000 person-years), and incident cardiovascular disease (47.3 vs. 31.0 per 1000 person-years) were higher in participants with aneurysm than in those without aneurysm; after adjustment for age, risk factors, and presence of other cardiovascular disease, the respective relative risks were 1.32, 1.36, and 1.57. Rates of repair and rupture were low. CONCLUSIONS: Rates of total mortality, cardiovascular disease mortality, and incident cardiovascular disease were higher in participants with abdominal aortic aneurysm than in those without aneurysm, independent of age, sex, other clinical cardiovascular disease, and extent of atherosclerosis detected by noninvasive testing. Persons with smaller aneurysms detected by ultrasonography should be advised to modify risk factors for cardiovascular disease while under surveillance for increase in the size of the aneurysm.
Keywords: Aged; Aged, 80 and over; Aortic Aneurysm, Abdominal; Aortic Rupture; Cardiovascular Diseases; Disease Progression; Female; Humans; Incidence; Longitudinal Studies; Male; Mortality; Proportional Hazards Models; Risk Factors; Ultrasonography; United States

Cluster analysis and patterns of findings on cranial magnetic resonance imaging of the elderly: the Cardiovascular Health Study. - Longstreth, W T; Diehr, P; Manolio, T A; Beauchamp, N J; Jungreis, C A; Lefkowitz, D (Arch Neurol, 2001)
OBJECTIVE: To characterize patterns of findings on cranial magnetic resonance imaging (MRI) of the elderly using a statistical technique called cluster analysis. SUBJECTS AND METHODS: The Cardiovascular Health Study is a population-based, longitudinal study of 5888 people 65 years and older. Of these, 3230 underwent cranial MRI scans, which were coded for presence of infarcts and grades for white matter, ventricles, and sulci. Cluster analysis separated participants into 5 clusters based solely on patterns of MRI findings. Participants comprising each cluster were contrasted with respect to cardiovascular risk factors and clinical manifestations. RESULTS: One cluster was low on all the MRI findings (normal) and another was high on all of them (complex infarcts). Another cluster had evidence for infarcts alone (simple infarcts), whereas the last 2 clusters lacked infarcts, one having enlarged ventricles and sulci (atrophy) and the other having prominent white matter changes and enlarged ventricles (leukoaraiosis). Factors that distinguished these clusters in a discriminant analysis were age, sex, several measures of hypertension, internal carotid artery wall thickness, smoking, and prevalent claudication before the MRI. The atrophy group had the highest percentage of men and the normal group had the lowest. Cognitive and motor performance also differed across clusters, with the atrophy cluster performing better than may have been expected. CONCLUSIONS: These MRI patterns identified participants with different vascular disease risk factors and clinical manifestations. Results of these exploratory analyses warrant consideration in other populations of elderly people. Such patterns may provide clues about the pathophysiology of structural brain changes in the elderly.
Keywords: Aged; Brain; Cerebral Infarction; Cerebrovascular Disorders; Cluster Analysis; Cohort Studies; Discriminant Analysis; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Risk Factors

Coronary artery calcification in older adults to age 99: prevalence and risk factors. - Newman, A B; Naydeck, B L; Sutton-Tyrrell, K; Feldman, A; Edmundowicz, D; Kuller, L H (Circulation, 2001)
BACKGROUND: Coronary artery calcification has been proposed as a noninvasive method to assess cardiovascular disease (CVD) risk. However, the prevalence and risk factors for coronary artery calcification in populations >65 years have not been well studied. METHODS AND RESULTS: Electron beam tomography was performed to assess coronary artery calcium (CAC) in 614 older adults aged, on average, 80 years (range, 67 to 99 years); 367 (60%) were women, and 143 (23%) were black. Calcium scores ranged from 0 to 5459. Median scores were 622 for men and 205 for women. Scores increased by age and were lower in blacks than in whites. Nine percent of subjects (n=57) had no CAC, and 31% (n=190) had a score lower than 100. A history of CVD was associated with calcium score. Age, male sex, white race, CVD, triglyceride level, pack-years of smoking, and asthma, emphysema, or bronchitis (chronic obstructive pulmonary disease) were independently associated with CAC score in the fourth quartile. CONCLUSIONS: A wide range of CAC scores was observed, suggesting adaptation with aging. CAC may have potential to predict CVD in older adults, but this remains to be determined.
Keywords: Age Distribution; Age Factors; Aged; Aged, 80 and over; Black People; Calcinosis; Calcium; Cohort Studies; Comorbidity; Coronary Angiography; Coronary Artery Disease; Coronary Vessels; Demography; Female; Humans; Logistic Models; Male; Predictive Value of Tests; Prevalence; Risk Factors; Sex Distribution; Sex Factors; Tomography, X-Ray Computed; White People

Correlates of peak expiratory flow lability in elderly persons. - Enright, P L; McClelland, R L; Buist, A S; Lebowitz, M D (Chest, 2001)
OBJECTIVE: To determine the correlates of the lability of peak expiratory flow (PEF) in the elderly. METHODS: A community sample of 4,581 persons > or = 65 years old from the Cardiovascular Health Study completed an asthma questionnaire and underwent spirometry. During a follow-up examination of the cohort, 1,836 persons agreed to measure PEF at home twice daily for 2 weeks, and 90% successfully obtained at least 4 days of valid measurements. PEF lability was calculated as the highest daily (PEF maximum - PEF minimum)/mean PEF. RESULTS: Mean PEF measured at home was accurate when compared to PEF determined by spirometry in the clinic. Mean PEF lability was 18% in those with current asthma (n = 165) vs 12% in healthy nonsmokers (upper limit of normal, 29%). Approximately 26% of those with asthma and 14% of the other participants had abnormally high PEF lability (> 29%). After excluding participants with asthma, other independent predictors of high PEF lability included black race, current and former smoking, airway obstruction on spirometry, daytime sleepiness, recent wheezing, chronic cough, emphysema, and wheezing from lying in a supine position. Despite having a lower mean PEF, those reporting congestive heart failure (n = 82) did not have significantly higher PEF lability. CONCLUSIONS: Measurement of PEF lability at home is highly successful in elderly persons. PEF lability > or = 30% is abnormal in the elderly and is associated with asthma.
Keywords: Aged; Aged, 80 and over; Aging; Asthma; Female; Heart Failure; Humans; Male; Monitoring, Ambulatory; Peak Expiratory Flow Rate; Predictive Value of Tests; Pulmonary Disease, Chronic Obstructive; Reference Values; Rhinitis, Allergic, Seasonal; Risk Factors; Signal Processing, Computer-Assisted; Spirometry

Estrogen replacement and brachial artery flow-mediated vasodilation in older women. - Herrington, D M; Espeland, M A; Crouse, J R; Robertson, J; Riley, W A; McBurnie, M A; Burke, G L (Arterioscler Thromb Vasc Biol, 2001)
It remains unclear whether estrogen therapy (with or without progestin) improves endothelial function in older postmenopausal women with or at risk for coronary heart disease. To address this issue, we analyzed brachial artery flow-mediated vasodilation in the Cardiovascular Health Study, a longitudinal study of cardiovascular risk factors in subjects over 65 years of age. At the tenth annual Cardiovascular Health Study examination, 1662 women returned for follow-up. Eighteen percent (n=291) were current users of estrogen replacement, most of whom (75.9%, n=221) took unopposed estrogen. Brachial artery ultrasound examinations measuring vasodilation in response to a flow stimulus (hyperemia) were performed on 1636 women. There were no statistical differences in brachial flow-mediated vasodilator responses between users and nonusers, even after adjustment for potential confounders. Absence of an effect was most notable in women over 80 years old and in those with established cardiovascular disease. However, among women without clinical or subclinical cardiovascular disease or its risk factors, there was a significant association between hormone replacement therapy use and flow-mediated vasodilator responses (P=0.01). Among older postmenopausal women, favorable vascular effects of estrogen may be limited to those who have not yet developed atherosclerotic vascular disease. These data emphasize the importance of ongoing efforts to determine the role of hormone replacement therapy for primary prevention of cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Brachial Artery; Cardiovascular Diseases; Drug Therapy, Combination; Estrogen Replacement Therapy; Estrogens; Female; Humans; Longitudinal Studies; Progestins; Risk Factors; Ultrasonography; Vasodilation

Factors associated with healthy aging: the cardiovascular health study. - Burke, G L; Arnold, A M; Bild, D E; Cushman, M; Fried, L P; Newman, A; Nunn, C; Robbins, J (J Am Geriatr Soc, 2001)
OBJECTIVES: To identify factors associated with remaining healthy in older adults. DESIGN: Longitudinal cohort study. SETTING: Data were collected at the four Cardiovascular Health Study field centers. PARTICIPANTS: 5,888 participants age 65 years and older in the Cardiovascular Health Study. MEASUREMENTS: Presence of chronic disease was assessed at baseline and over a maximum 7-year follow-up period. Participants who were free of chronic disease (no cardiovascular disease (CVD), chronic obstructive pulmonary disease, or self-reported cancer, except nonmelanoma skin cancer) at the baseline examination were then monitored for the onset of incident cancer, cardiovascular disease, and fatal outcomes. RESULTS: A high proportion of these older adults was healthy at the initial examination and remained healthy over the follow-up period. Numerous behavioral factors were associated with continued health, including physical activity, refraining from cigarette smoking, wine consumption (women), higher educational status, and lower waist circumference. A number of CVD risk factors and subclinical disease measures were associated with continued health, including higher high-density lipoprotein (HDL) cholesterol, lack of diabetes, thinner common carotid intimal nmedial thickness, lower blood pressure, lower C-reactive protein, and higher ankle-arm blood pressure ratio. Among the behavioral factors, exercise, not smoking, and not taking aspirin remained significant predictors of health even after controlling for CVD risk factors and subclinical disease in older adults. CONCLUSIONS: These data suggest that a number of modifiable behavioral factors (physical activity, smoking, and obesity) and cardiovascular risk factors (diabetes, HDL cholesterol, and blood pressure) are associated with maintenance of good health in older adults.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Cohort Studies; Diet; Exercise; Female; Health Status; Humans; Incidence; Life Style; Longitudinal Studies; Lung Diseases, Obstructive; Male; Neoplasms; Probability; Reference Values; Risk Factors; Sex Distribution; Socioeconomic Factors; Survival Rate; United States

Gait variability in community-dwelling older adults. - Brach, J S; Berthold, R; Craik, R; VanSwearingen, J M; Newman, A B (J Am Geriatr Soc, 2001)
OBJECTIVES: To describe gait variability at usual and fast walking speeds in community-dwelling older adults and to describe the effects of increasing gait speed on gait variability. DESIGN: Cross-sectional, descriptive study. SETTING: The Cardiovascular Health Study at the University of Pittsburgh. PARTICIPANTS: Ninety-five community-living older adults, 54 women and 41 men, age 65 and older (mean age +/- standard deviation 79.4 +/- 3.37). MEASUREMENTS: Gait measured at participant's usual and fast walking speed collected using an instrumented walkway. Step-length and step-width variability were determined using the coefficient of variation. RESULTS: Step-length variability was greatest in those who walked the slowest (r = -0.66, P < .001); step-width variability was smallest in those who walked the slowest (r -0.37, P < .001). Individuals who could not increase their walking speed (<0.10 m/second) on command had an increase in step-length variability and a decrease in step-width variability, whereas those who could increase their speed (>0.10 m/second) had an increase in step-width variability when walking at a faster speed. CONCLUSIONS: Step-length and step-width variability have opposite associations with gait speed in older adults. Improvement in step-length and step-width variability with attempted acceleration might be a key factor to examine in future studies of disability risk and therapeutic interventions.
Keywords: Aged; Aged, 80 and over; Aging; Body Height; Body Weight; Cross-Sectional Studies; Disability Evaluation; Female; Gait; Humans; Male; Residence Characteristics; Risk Factors; Time Factors; Walking

Importance of heart failure with preserved systolic function in patients > or = 65 years of age. CHS Research Group. Cardiovascular Health Study. - Kitzman, D W; Gardin, J M; Gottdiener, J S; Arnold, A; Boineau, R; Aurigemma, G; Marino, E K; Lyles, M; Cushman, M; Enright, P L (Am J Cardiol, 2001)
Although congestive heart failure (CHF) is a common syndrome among the elderly, there is a relative paucity of population-based data, particularly regarding CHF with normal systolic left ventricular function. A total of 4,842 independent living, community-dwelling subjects aged 66 to 103 years received questionnaires on medical history, family history, personal habits, physical activity, and socioeconomic status, confirmation of pre-existing cardiovascular and cerebrovascular disease, anthropometric measurements, casual seated random-zero blood pressure, forced vital capacity and expiratory volume in 1 second, 12-lead supine electrocardiogram, fasting glucose, creatinine, plasma lipids, carotid artery wall thickness by ultrasonography, and echocardiography-Doppler examinations. Participants with at least 1 confirmed episode of CHF by Cardiovascular Health Study criteria were considered prevalent for CHF. The prevalence of CHF was 8.8% and was associated with increased age, particularly for women, in whom it increased more than twofold from age 65 to 69 years (6.6%) to age > or = 85 years (14%). In multivariate analysis, subjects with CHF were more likely to be older (odds ratio [OR] 1.2 for 5-year difference, men OR 1.1), and more often had a history of myocardial infarction (OR 7.3), atrial fibrillation (OR 3.0), diabetes mellitus (OR 2.1), renal dysfunction (OR 2.0 for creatinine < or = 1.5 mg/ dl), and chronic pulmonary disease (OR 1.8; women only). The echocardiographic correlates of CHF were increased left atrial and ventricular dimensions. Importantly, 55% of subjects with CHF had normal left ventricular systolic function and 80% had either normal or only mildly reduced systolic function. Among subjects with CHF, women had normal systolic function more frequently than men (67% vs 42%; p < 0.001). Thus, CHF is common among community-dwelling elderly. It increases with age and is usually associated with normal systolic LV function, particularly among women. The finding that a large proportion of elderly with CHF have preserved LV systolic function is important because there is a paucity of data to guide management in this dominant subset.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Chi-Square Distribution; Echocardiography, Doppler; Female; Health Status; Heart Failure; Humans; Logistic Models; Longitudinal Studies; Male; Prevalence; Risk Factors; Surveys and Questionnaires; United States; Ventricular Function, Left

M-mode echocardiographic predictors of six- to seven-year incidence of coronary heart disease, stroke, congestive heart failure, and mortality in an elderly cohort (the Cardiovascular Health Study). - Gardin, J M; McClelland, R; Kitzman, D; Lima, J A; Bommer, W; Klopfenstein, H S; Wong, N D; Smith, V E; Gottdiener, J (Am J Cardiol, 2001)
Previous studies have identified a number of echocardiographic variables that predict cardiovascular disease (CVD) events and mortality, but have not focused on a large elderly cohort. The purpose of this study was to determine whether M-mode echocardiographic variables predicted all-cause mortality, incident coronary heart disease (CHD), congestive heart failure (CHF), and stroke in a large prospective, multicenter, population-based study. In the Cardiovascular Health Study, a biracial cohort of 5,888 men and women (mean age 73 years) underwent 2-dimensional M-mode echocardiographic measurements of left ventricular (LV) internal dimensions, wall thickness, mass and geometry, as well as measurement of left atrial dimension and assessment for mitral annular calcium. Participants were followed for 6 to 7 years for incident events; analyses excluded subjects with prevalent disease. One or more echocardiographic measurements were independent predictors of all-cause mortality and incident CHD, CHF, and stroke. After adjustment for anthropometric and traditional CVD risk factors, LV mass was significantly related to incident CHD, CHF, and stroke. The highest quartile of LV mass conferred a hazards ratio of 3.36, compared with the lowest quartile, for incident CHF. Furthermore, incident CHF-free survival was significantly lower for participants with LV mass in the highest versus the 2 lowest quartiles (86% vs 97%, respectively, at 2,500 days). Eccentric and concentric LV hypertrophy, respectively, conferred adjusted hazards ratios, compared with normal LV geometry, of 2.05 and 1.61 for incident CHD, and 2.95 and 3.32 for incident CHF. Thus, in an elderly biracial population, selected 2-dimensional M-mode echocardiographic measurements were important markers of subclinical disease and conferred independent prognostic information for incident CVD events, especially CHF and CHD.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Coronary Disease; Echocardiography, Doppler; Female; Heart Failure; Humans; Incidence; Male; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke

Post-menopausal hormone therapy and concentrations of protein C and antithrombin in elderly women. - Cushman, M; Psaty, B M; Meilahn, E N; Dobs, A S; Kuller, L H (Br J Haematol, 2001)
The effects of post-menopausal hormone therapy (HRT) on blood coagulation in elderly women are not well defined. We studied associations of HRT use with levels of natural anticoagulant proteins in a cross-sectional study of 3393 women > or = 65 years of age participating in the Cardiovascular Health Study. Protein C antigen and antithrombin were measured in all users (n = 230 unopposed oestrogen; 60 oestrogen/progestin) and a comparison group of 196 age- and race-matched non-users. Compared with non-users, oestrogen use was associated with higher protein C (4.80 vs. 4.30 microg/ml, P < 0.01). Results were similar for oestrogen/progestin (P > 0.05). In both user groups, antithrombin was lower than in non-users (109% for each vs. 115% in non-users, P < 0.001). Adjustment for factors related to prescription of HRT and to anticoagulant protein levels had little impact on the results. For antithrombin, associations with HRT were larger for thinner Caucasian women and black women. Venous thrombosis from HRT may be mediated partly by alterations in antithrombin, but not protein C concentrations. This study extends previous observations to older women, the group at highest risk of venous thromboembolism. Studies of HRT-induced alterations in anticoagulant function in relation to the occurrence of thrombosis with HRT are required.
Keywords: Aged; Antithrombins; Black People; Body Mass Index; Cross-Sectional Studies; Estrogen Replacement Therapy; Female; Humans; Logistic Models; Postmenopause; Progestins; Protein C; Risk Factors; Venous Thrombosis; White People

Predictive value of systolic and diastolic function for incident congestive heart failure in the elderly: the cardiovascular health study. - Aurigemma, G P; Gottdiener, J S; Shemanski, L; Gardin, J; Kitzman, D (J Am Coll Cardiol, 2001)
OBJECTIVES: We sought to assess the ability of echocardiographic indices of systolic and diastolic function to predict incident congestive heart failure (CHF). BACKGROUND: Noninvasive indices of subclinical systolic and/or diastolic dysfunction that can be used to identify patients in a transition phase between normal cardiac function and clinical CHF would be valuable. Though midwall shortening and Doppler mitral inflow patterns are seemingly well suited to predict subsequent CHF, the predictive value of these indices has not been investigated. METHODS: We studied 2,671 participants in the Cardiovascular Health Study who were free of coronary heart disease, CHF or atrial fibrillation. Clinical and quantitative echocardiographic data were obtained in all participants. RESULTS: At a mean follow-up of 5.2 years (range 0 to 6 years), 170 participants (6.4% of the cohort) developed CHF. Although 96% of these participants had normal or borderline ejection fraction (EF) at baseline, only 57% had normal or borderline EF at the time of hospitalization. In multivariate modeling, fractional shortening at the endocardium (relative risk [RR] 1.85 per 10-unit decrease, confidence interval [CI] 1.27 to 2.39), fractional shortening at the midwall (RR 1.29 per five-unit decrease, 95% CI 1.11-1.51) and peak Doppler peak E (RR 1.15 for each 0.1 M/s increment; CI 1.02 to 1.21) independently predicted incident CHF. Both high and low Doppler E/A ratios were predictive of incident CHF. CONCLUSIONS: Roughly half the occurrences of CHF in this population are associated with normal or borderline EF. Echocardiographic findings suggestive of subclinical contractile dysfunction and diastolic filling abnormalities are both predictive of subsequent CHF. The standard (FSendo) and refined (FSmw) parameters of systolic function performed similarly in this regard, though subjects with left ventricular hypertrophy and depressed FSmw are at particularly high risk for subsequent CHF.
Keywords: Age Factors; Aged; Aged, 80 and over; Diastole; Echocardiography; Female; Follow-Up Studies; Heart Failure; Humans; Male; Multivariate Analysis; Myocardial Contraction; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Factors; Systole

Relation of hemodynamics and risk factors to ventricular-vascular interactions in the elderly: the Cardiovascular Health Study. - de Simone, G; McClelland, R; Gottdiener, J S; Celentano, A; Kronmal, R A; Gardin, J M (J Hypertens, 2001)
OBJECTIVE: To investigate the interaction between left ventricular (LV) geometry, carotid structure and arterial compliance in relation to hemodynamic stimuli and risk factors (plasma cholesterol, body mass index, insulin resistance, smoking habit, age, sex and race). DESIGN: Cross-sectional. METHODS: Echocardiography and carotid ultrasound were performed in 2375 elderly subjects without signs or history of prevalent cardiovascular disease, diabetes or renal disease (795 men; 298 non-whites; 1215 hypertensive), from the cohort of the Cardiovascular Health Study. Arterial compliance was estimated by the prognostically validated ratio of stroke volume to pulse pressure (SV/PP) as the percent deviation (Delta%) from the value predicted by individual age, heart rate and body weight. RESULTS: Intima-medial thickness (IMT) was higher in the presence of LV hypertrophy (LVH) in normotensive and hypertensive subjects and was greatest in the presence of concentric LVH. Maximum carotid lumen diameter (CLD) was also higher in the presence of LVH (and was greatest with eccentric LVH, in association with relatively high values for stroke volume). After adjusting for blood pressure, maximum carotid lumen diameter was directly correlated with stroke volume, and IMT to LV mass (all P < 0.001). Similarly, IMT was also related to maximum carotid lumen diameter, independently of prevalent risk factors (P < 0.001). SV/PP-Delta% was reduced in both groups with concentric LV remodeling (both P < 0.0001) or concentric LVH (both P < 0.05). Adjusting for risk factors did not affect these associations in normotensives, but made them insignificant in hypertensives. In normotensives, IMT was inversely related to SV/PP-Delta% (P < 0.001), independently of risk factors, whereas no significant relation was found in hypertensives. CONCLUSIONS: The magnitudes of carotid intima-medial thickness and lumen diameter parallel levels of LV mass and geometry, and are directly related to stroke volume and arterial stiffness; this interaction is most evident in the presence of normal blood pressure, whereas it is affected by other cardiovascular risk factors when arterial hypertension is present.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Carotid Arteries; Compliance; Cross-Sectional Studies; Echocardiography; Female; Hemodynamics; Humans; Hypertension; Hypertrophy, Left Ventricular; Male; Reference Values; Risk Factors; Stroke Volume; Tunica Intima; Tunica Media; Ventricular Function, Left

The relation of markers of inflammation to the development of glucose disorders in the elderly: the Cardiovascular Health Study. - Barzilay, J I; Abraham, L; Heckbert, S R; Cushman, M; Kuller, L H; Resnick, H E; Tracy, R P (Diabetes, 2001)
Several studies suggest that inflammation plays a role in the pathogenesis of some glucose disorders in adults. We tested this hypothesis in a longitudinal cohort study of older individuals who had normal fasting glucose (FG) values at baseline. We compared the baseline levels of six inflammatory markers in participants who had developed glucose disorders at follow-up with those of participants whose FG remained normal at follow-up. Participants were members of the Cardiovascular Health Study, a prospective study of risk factors for cardiovascular disease in adults > or =65 years. All 5,888 participants had baseline testing, including FG and markers of inflammation: white blood cell and platelet counts and albumin, fibrinogen, C-reactive protein (CRP), and factor VIIIc levels. At 3-4 years of follow-up, 4,481 (84.5%) of those who were alive had FG levels retested. Participants who developed diabetes (n = 45) had higher median levels of CRP at baseline than those who remained normoglycemic. On multivariate analysis, those with elevated CRP levels (75th percentile [2.86 mg/l] vs. 25th percentile [0.82 mg/l]) were 2.03 times (95% confidence intervals, 1.44-2.86) more likely to have diabetes on follow-up. Adjustment for confounders and other inflammatory markers did not appreciably change this finding. There was no relationship between the development of diabetes and other markers of inflammation. Inflammation, as measured by CRP levels, is associated with the development of diabetes in the elderly. Understanding the role of inflammation in the pathogenesis of glucose disorders in this age-group may lead to better classification and treatment of glucose disorders among them.
Keywords: Aged; Biomarkers; Blood Glucose; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Diabetes Mellitus; Female; Humans; Hypoglycemia; Inflammation; Longitudinal Studies; Male; Reference Values; Risk Factors

Relation of sleep-disordered breathing to cardiovascular disease risk factors: the Sleep Heart Health Study. - Newman, A B; Nieto, F J; Guidry, U; Lind, B K; Redline, S; Pickering, T G; Quan, S F (Am J Epidemiol, 2001)
Associations between sleep-disordered breathing and cardiovascular disease (CVD) may be mediated by higher cardiovascular risk factor levels in those with sleep-disordered breathing. The authors examined these relations in the Sleep Heart Health Study, a multiethnic cohort of 6,440 men and women over age 40 years conducted from October 1995 to February 1998 and characterized by home polysomnography. In 4,991 participants who were free of self-reported CVD at the time of the sleep study, moderate levels of sleep-disordered breathing were common, with a median Respiratory Disturbance Index (RDI) of 4.0 (interquartile range, 1.25-10.7). The level of RDI was associated cross-sectionally with age, body mass index, waist-to-hip ratio, hypertension, diabetes, and lipid levels. These relations were more pronounced in those under age 65 years than in those over age 65. Women under age 65 years with RDI in the higher quartiles were more obese than men with similar RDI. Although the pattern of associations was consistent with greater obesity in those with higher RDI, higher body mass index did not explain all of these associations. If sleep-disordered breathing is shown in future follow-up to increase the risk for incident CVD events, part of the risk is likely to be due to the higher cardiovascular risk factors in those with higher RDI.
Keywords: Adult; Aged; Analysis of Variance; Cardiovascular Diseases; Chi-Square Distribution; Cross-Sectional Studies; Female; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Polysomnography; Risk Factors; Sleep Apnea Syndromes; United States

Risk factors for hospitalized gastrointestinal bleeding among older persons. Cardiovascular Health Study Investigators. - Kaplan, R C; Heckbert, S R; Koepsell, T D; Furberg, C D; Polak, J F; Schoen, R E; Psaty, B M (J Am Geriatr Soc, 2001)
OBJECTIVES: We sought to estimate the incidence of hospitalization for upper and lower gastrointestinal bleeding among older persons and to identify independent risk factors. DESIGN: Prospective cohort study. SETTING: The Cardiovascular Health Study (CHS). PARTICIPANTS: 5,888 noninstitutionalized men and women age 65 years or older in four U.S. communities enrolled in the CHS. MEASUREMENTS: Gastrointestinal bleeding events during the period 1989 through 1998 were identified using hospital discharge diagnosis codes and confirmed by medical records review. Risk-factor information was collected in a standardized fashion at study baseline and annually during follow-up. RESULTS: Among CHS participants (mean baseline age 73.3 years, 42% male), the incidence of hospitalized gastrointestinal bleeding was 6.8/1,000 person-years. In multivariate analyses, advanced age, male sex, unmarried status, cardiovascular disease, difficulty with daily activities, use of multiple medications, and use of oral anticoagulants were independent risk factors. Compared with nonsmokers, subjects who smoked more than half a pack per day had a multivariate-adjusted hazard ratio (HR) of 2.14 (95% confidence interval [CI] = 1.22-3.75) for upper gastrointestinal bleeding and a multivariate-adjusted HR of 0.21 (95% CI = 0.03-1.54) for lower gastrointestinal bleeding. Aspirin users did not have an elevated risk of upper gastrointestinal bleeding (HR = 0.76, 95% CI = 0.52-1.11), and users of other nonsteroidal anti-inflammatory drugs had a HR of 1.54 (95 % CI = 0.99-2.36). Low ankle-arm systolic blood pressure index was associated with higher risk of gastrointestinal bleeding among subjects with clinical cardiovascular disease but not among those without clinical cardiovascular disease. CONCLUSION: This study identifies risk factors for gastrointestinal bleeding, such as disability, that may be amenable to modification. The findings will help clinicians to identify older persons who are at high risk for gastrointestinal bleeding.
Keywords: Activities of Daily Living; Age Distribution; Aged; Aged, 80 and over; Anti-Inflammatory Agents, Non-Steroidal; Anticoagulants; Aspirin; Cardiovascular Diseases; Female; Gastrointestinal Hemorrhage; Hospitalization; Humans; Incidence; Male; Multivariate Analysis; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; Smoking; United States

Silent MRI infarcts and the risk of future stroke: the cardiovascular health study. - Bernick, C; Kuller, L; Dulberg, C; Longstreth, W T; Manolio, T; Beauchamp, N; Price, T (Neurology, 2001)
BACKGROUND: Silent infarcts are commonly discovered on cranial MRI in the elderly. OBJECTIVE: To examine the association between risk of stroke and presence of silent infarcts, alone and in combination with other stroke risk factors. METHODS: Participants (3,324) in the Cardiovascular Health Study (CHS) without a history of stroke underwent cranial MRI scans between 1992 and 1994. Silent infarcts were defined as focal lesions greater than 3 mm that were hyperintense on T2 images and, if subcortical, hypointense on T1 images. Incident strokes were identified and classified over an average follow-up of 4 years. The authors evaluated the risk of subsequent symptomatic stroke and how it was modified by other potential stroke risk factors among those with silent infarcts. RESULTS: Approximately 28% of CHS participants had evidence of silent infarcts (n = 923). The incidence of stroke was 18.7 per 1,000 person-years in those with silent infarcts (n = 67) compared with 9.5 per 1,000 person-years in the absence of silent infarcts. The adjusted relative risk of incident stroke increased with multiple (more than one) silent infarcts (hazard ratio 1.9 [1.2 to 2.8]). Higher values of diastolic and systolic blood pressure, common and internal carotid wall thickness, and the presence of atrial fibrillation were associated with an increased risk of strokes in those with silent infarcts (n = 53 strokes). CONCLUSION: The presence of silent cerebral infarcts on MRI is an independent predictor of the risk of symptomatic stroke over a 4-year follow- up in older individuals without a clinical history of stroke.
Keywords: Aged; Cerebral Infarction; Cohort Studies; Female; Follow-Up Studies; Humans; Incidence; Magnetic Resonance Imaging; Male; Predictive Value of Tests; Risk Factors; Stroke

Usefulness of T-axis deviation as an independent risk indicator for incident cardiac events in older men and women free from coronary heart disease (the Cardiovascular Health Study). - Rautaharju, P M; Nelson, J C; Kronmal, R A; Zhang, Z M; Robbins, J; Gottdiener, J S; Furberg, C D; Manolio, T; Fried, L (Am J Cardiol, 2001)
T-axis shift has been reported to be an indicator of increased mortality risk. We evaluated the association of spatial T-axis deviation with incident coronary heart disease (CHD) events in older men and women free from clinically overt CHD. Spatial T-axis deviation was measured from the standard 12-lead electrocardiogram of a subgroup of 4,173 subjects considered free of CHD at baseline in the Cardiovascular Health Study, a prospective cohort study of risk factors for CHD and stroke in older men and women. Cox regression analysis was used to evaluate the association of altered repolarization with the risk of incident CHD events. The prevalence of marked T-axis deviation (> or =45 degrees ) was 12%. During the median follow-up of 7.4 years, there were 161 CHD deaths, 743 deaths from all causes, and 679 incident CHD events. Adjusting for demographic and clinical risk factors, including other electrocardiographic abnormalities, there was a nearly twofold excess risk of CHD death, and approximately a 50% excess risk of incident CHD and all-cause mortality for those with marked T-axis deviation. From other electrocardiographic abnormalities, only QT prolongation was associated with excess risk for incident CHD comparable to that for abnormal T-axis deviation. These results suggest that T-axis deviation is an easily quantified marker for subclinical disease and an independent indicator for the risk of incident CHD events in older men and women free of CHD.
Keywords: Aged; Algorithms; Cohort Studies; Coronary Disease; Electrocardiography; Female; Follow-Up Studies; Humans; Male; Prevalence; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; Survival Analysis

Weight change in old age and its association with mortality. - Newman, A B; Yanez, D; Harris, T; Duxbury, A; Enright, P L; Fried, L P (J Am Geriatr Soc, 2001)
OBJECTIVES: Previous studies of weight change and mortality in older adults have relied on self-reported weight loss, have not evaluated weight gain, or have had limited information on health status. Our objective was to determine whether 5% weight gain or loss in 3 years was predictive of mortality in a large sample of older adults. DESIGN: Longitudinal observational cohort study. SETTING: Four U.S. communities. PARTICIPANTS: Four thousand seven hundred fourteen community-dwelling older adults, age 65 and older. MEASUREMENTS: Weight gain or loss of 5% in a 3-year period was examined in relationship to baseline health status and interim health events. Risk for subsequent mortality was estimated in those with weight loss or weight gain compared with the group whose weight was stable. RESULTS: Weight changes occurred in 34.6% of women and 27.3% of men, with weight loss being more frequent than gain. Weight loss was associated with older age, black race, higher weight, lower waist circumference, current smoking, stroke, any hospitalization, death of a spouse, activities of daily living disability, lower grip strength, and slower gait speed. Weight loss but not weight gain of 5% or more was associated with an increased risk of mortality that persisted after multivariate adjustment (Hazard ratio (HR) = 1.67, 95% CI = 1.29-2.15) and was similar in those with no serious illness in the period of weight change. Those with weight loss and low baseline weight had the highest crude mortality rate, although the HR for weight loss was similar for all tertiles of baseline weight and for those with or without a special diet, compared with those whose weight was stable. CONCLUSIONS: This study confirms that even modest decline in body weight is an important and independent marker of risk of mortality in older adults.
Keywords: Aged; Analysis of Variance; Body Weight; Chi-Square Distribution; Female; Health Status; Humans; Longitudinal Studies; Male; Mortality; Proportional Hazards Models; Risk Factors; United States; Weight Gain; Weight Loss

Anticardiolipin antibodies as a risk factor for venous thromboembolism in a population-based prospective study. - Runchey, Shauna S; Folsom, Aaron R; Tsai, Michael Y; Cushman, Mary; McGovern, Paul D (Br J Haematol, 2002)
Anticardiolipin antibodies, one of the family of 'antiphospholipid' antibodies, increase the risk of venous thromboembolism in the presence of autoimmune disease. Our objective was to determine prospectively whether there is a positive association between anticardiolipin antibodies and venous thromboembolism in ostensibly healthy adults. We conducted a nested case-control study (n = 317 patients and n = 655 control subjects) in a longitudinal study of over 20 000 participants. Baseline (prediagnosis) anticardiolipin IgG and IgM antibodies were assessed by enzyme-linked immunoassays. Venous thromboembolism was validated using standardized criteria for venous thrombosis and pulmonary embolism. There was no association between anticardiolipin antibodies and subsequent venous thromboembolism occurrence, overall or in any subgroup. For example, the multivariate-adjusted relative risk was 0.88 (95% confidence interval, 0.43, 1.78) for greater than versus less than the 95th percentile of anticardiolipin IgG. In conclusion, in this general population sample, an elevated anticardiolipin antibody level was not a risk factor for venous thromboembolism.
Keywords: Aged; Aged, 80 and over; Antibodies, Anticardiolipin; Case-Control Studies; Female; Humans; Immunoglobulin G; Immunoglobulin M; Longitudinal Studies; Male; Middle Aged; Odds Ratio; Prospective Studies; Reference Values; Risk Factors; Thromboembolism; Venous Thrombosis

Calcium channel blocker use and gastrointestinal tract bleeding among older adults. - Kaplan, Robert C; Heckbert, Susan R; Koepsell, Thomas D; Rosendaal, Frits R; Furberg, Curt D; Cooper, Lawton S; Psaty, Bruce M (Age Ageing, 2002)
Keywords: Aged; Antihypertensive Agents; Calcium Channel Blockers; Gastrointestinal Hemorrhage; Geriatric Assessment; Health Services for the Aged; Humans; Hypertension; Prospective Studies; Risk Factors

Cardiovascular disease risk status in elderly persons with renal insufficiency. - Shlipak, Michael G; Fried, Linda F; Crump, Casey; Bleyer, Anthony J; Manolio, Teri A; Tracy, Russell P; Furberg, Curt D; Psaty, Bruce M (Kidney Int, 2002)
BACKGROUND: Renal insufficiency has been independently associated with incident cardiovascular disease events in some, but not all, prospective studies. We determined the prevalence of elevated cardiovascular disease risk status among elderly persons with renal insufficiency. METHODS: This study is a cross-sectional analysis using data collected at the baseline visit of the Cardiovascular Health Study, which enrolled 5888 community dwelling adults aged 65 years or older from four clinical centers in the United States. Renal insufficiency was defined as a serum creatinine level > or =1.3 mg/dL in women and > or =1.5 mg/dL in men. The outcomes of this study included prevalent cardiovascular disease [prior coronary heart disease (CHD) or stroke], subclinical cardiovascular disease (abnormal values of ankle-arm index, carotid ultrasound, and echocardiography) and elevated cardiovascular risk based upon a diagnosis of diabetes and the Framingham equations. The association between renal insufficiency and cardiovascular risk status was estimated with and without adjustment for other cardiovascular predictors. RESULTS: Among the 5808 participants with creatinine levels measured at entry, 15.9% of men (N = 394), and 7.6% of women (N = 254) had renal insufficiency. The prevalence of either clinical or subclinical cardiovascular disease was 64% in persons with renal insufficiency compared with 43% in those without it [odds ratio (OR) 2.34; 95% confidence interval (95% CI), 1.96, 2.80]. After adjustment for other cardiovascular risk factors, renal insufficiency remained significantly associated with clinical and subclinical cardiovascular disease (adjusted OR 1.43; 95% CI, 1.18, 1.75), but the magnitude of association was substantially reduced. After combining clinical and subclinical cardiovascular disease, diabetes, and an estimated risk>20% by the Framingham equations, 78% of men and 61% of women with renal insufficiency had elevated cardiovascular risk status. CONCLUSIONS: Renal insufficiency is a marker for elevated cardiovascular disease risk in community dwelling elderly adults.
Keywords: Age Distribution; Aged; Cholesterol, HDL; Cholesterol, LDL; Coronary Disease; Creatinine; Cross-Sectional Studies; Female; Humans; Kidney Failure, Chronic; Male; Prevalence; Prospective Studies; Risk Factors

Cardiovascular risk factors and venous thromboembolism incidence: the longitudinal investigation of thromboembolism etiology. - Tsai, Albert W; Cushman, Mary; Rosamond, Wayne D; Heckbert, Susan R; Polak, Joseph F; Folsom, Aaron R (Arch Intern Med, 2002)
BACKGROUND: The association between traditional cardiovascular risk factors and risk of venous thromboembolism (VTE) has not been extensively examined in prospective studies. METHODS: To determine whether atherosclerotic risk factors are also associated with increased incidence of VTE, we conducted a prospective study of 19 293 men and women without previous VTE in 6 US communities between 1987 and 1998. RESULTS: There were 215 validated VTE events (1.45 per 1000 person-years) during a median of 8 years of follow-up. The age-adjusted hazard ratio was 1.4 (95% confidence interval [CI], 1.1-1.9) for men vs women, 1.6 (95% CI, 1.2-2.2) for blacks vs whites, and 1.7 (95% CI, 1.5-2.0) per decade of age. Cigarette smoking, hypertension, dyslipidemia, physical inactivity, and alcohol consumption were not associated with risk of VTE. Age-, race-, and sex-adjusted hazard ratios for body mass index categories (calculated as the weight in kilograms divided by the height in meters squared) of less than 25, 25 to less than 30, 30 to less than 35, 35 to less than 40, and 40 or more were 1.0, 1.5, 2.2, 1.5, and 2.7, respectively (P<.001 for the trend). Diabetes was also associated with an increased risk of VTE (adjusted hazard ratio, 1.5 [95% CI, 1.0-2.1]). CONCLUSIONS: Our data showing no relationship of some arterial risk factors with VTE corroborate the view that the etiology of VTE differs from atherosclerotic cardiovascular disease. In addition, the findings suggest a hypothesis that avoidance of obesity and diabetes or vigilance in prophylaxis in patients with those conditions may prevent some venous thromboses.
Keywords: Aged; Arteriosclerosis; Female; Humans; Incidence; Male; Middle Aged; Multivariate Analysis; Proportional Hazards Models; Prospective Studies; Pulmonary Embolism; Risk Factors; United States; Venous Thrombosis

Coagulation factors, inflammation markers, and venous thromboembolism: the longitudinal investigation of thromboembolism etiology (LITE). - Tsai, Albert W; Cushman, Mary; Rosamond, Wayne D; Heckbert, Susan R; Tracy, Russell P; Aleksic, Nena; Folsom, Aaron R (Am J Med, 2002)
PURPOSE: We sought to assess prospectively whether higher levels of blood coagulation factors and inflammation markers are risk factors for venous thromboembolism. SUBJECTS AND METHODS: In two pooled population-based cohort studies, we measured levels of factor VII, factor VIII, von Willebrand factor, fibrinogen, and C-reactive protein, and white blood cell count, in samples obtained from 19,237 adults with no baseline history of venous thromboembolism, cancer, or warfarin use. The endpoint was validated venous thromboembolism during follow-up (median, 7.8 years). RESULTS: A total of 159 venous thromboembolism events occurred. Factor VIII and von Willebrand factor were linearly associated with increased risk of venous thromboembolism (P for trend <0.0001). As compared with those in the lowest quartile, the multivariate-adjusted hazard ratio (HR) of venous thromboembolism was 2.6 (95% confidence interval [CI]: 1.6 to 4.3) for factor VIII levels in the highest quartile and 3.8 (95% CI: 2.0 to 7.2) for the highest fifth percentile. For von Willebrand factor, the hazard ratios in middle-aged subjects were 4.6 (95% CI: 2.2 to 9.2) for the highest quartile and 7.6 (95% CI: 3.1 to 18) for the highest fifth percentile. Factor VII levels above the 95th percentile, as compared with the lowest quartile, also conveyed a higher risk of venous thromboembolism (HR = 2.4; 95% CI: 1.2 to 4.8). In contrast, there was no association of venous thromboembolism with fibrinogen or C-reactive protein levels, or white cell count. CONCLUSIONS: In this prospective study, elevated factor VIII and von Willebrand factor levels were common, independent, and dose-dependent risk factors for venous thromboembolism, and an elevated factor VII level was a possible risk factor. Venous thromboembolism, unlike arterial disease, was not related to inflammatory markers.
Keywords: Aged; Biomarkers; Blood Coagulation Factors; C-Reactive Protein; Cohort Studies; Confidence Intervals; Factor VII; Female; Fibrinogen; Humans; Inflammation Mediators; Longitudinal Studies; Male; Middle Aged; Multivariate Analysis; Prospective Studies; Risk Assessment; Risk Factors; Sensitivity and Specificity; Thromboembolism; Venous Thrombosis; von Willebrand Factor

Correlates of aortic stiffness in elderly individuals: a subgroup of the Cardiovascular Health Study. - Mackey, Rachel H; Sutton-Tyrrell, Kim; Vaitkevicius, Peter V; Sakkinen, Pamela A; Lyles, Mary F; Spurgeon, Harold A; Lakatta, Edward G; Kuller, Lewis H (Am J Hypertens, 2002)
BACKGROUND: Arterial stiffness has been associated with aging, hypertension, and diabetes; however, little data has been published examining risk factors associated with arterial stiffness in elderly individuals. METHODS: Longitudinal associations were made between aortic stiffness and risk factors measured approximately 4 years earlier. Aortic pulse wave velocity (PWV), an established index of arterial stiffness, was measured in 356 participants (53.4% women, 25.3% African American), aged 70 to 96 years, from the Pittsburgh site of the Cardiovascular Health Study during 1996 to 1998. RESULTS: Mean aortic pulse wave velocity (850 cm/sec, range 365 to 1863) did not differ by ethnicity or sex. Increased aortic stiffness was positively associated with higher systolic blood pressure (SBP), age, fasting and 2-h postload glucose, fasting and 2-h insulin, triglycerides, waist circumference, body mass index, truncal fat, decreased physical activity, heart rate, and common carotid artery wall thickness (P < .05). After controlling for age and SBP, the strongest predictors of aortic stiffness in men were heart rate (P = .001) and 2-h glucose (P = .063). In women, PWV was positively associated with heart rate (P = .018), use of antihypertensive medication (P = .035), waist circumference (P = .030), and triglycerides (P = .081), and was negatively associated with physical activity (P = .111). Results were similar when the analysis was repeated in nondiabetic individuals and in those free of clinical or subclinical cardiovascular disease in 1992 to 1993. CONCLUSIONS: In these elderly participants, aortic stiffness was positively associated with risk factors associated with the insulin resistance syndrome, increased common carotid intima-media thickness, heart rate, and decreased physical activity measured several years earlier.
Keywords: Aged; Aged, 80 and over; Aging; Aorta; Female; Heart Rate; Humans; Hypertension; Insulin Resistance; Longitudinal Studies; Male; Pulsatile Flow; Risk Factors; Sex Distribution

Glucose, blood pressure, and lipid control in older people with and without diabetes mellitus: the Cardiovascular Health Study. - Smith, Nicholas L; Savage, Peter J; Heckbert, Susan R; Barzilay, Joshua I; Bittner, Vera A; Kuller, Lewis H; Psaty, Bruce M (J Am Geriatr Soc, 2002)
OBJECTIVES: To determine the prevalence of cardiovascular risk-factor treatment and control in older adults with normal fasting glucose, impaired fasting glucose, and diabetes mellitus and whether those with diabetes mellitus had better risk factor control than older adults with normal fasting glucose. DESIGN: Secondary analysis of data from population-based, prospective cohort study of risk factors for cardio-vascular and cerebrovascular disease in older people (Cardiovascular Health Study). SETTING: Community-based. PARTICIPANTS: Community-dwelling adults aged 65 and older. MEASUREMENTS: Fasting plasma glucose, serum cholesterol and its subfractions, systolic and diastolic blood pressures, and body mass index. RESULTS: There were 579 (18%) cohort members with diabetes mellitus (77% receiving antidiabetic medication, 23% with fasting glucose > or =126 mg/dL and no treatment), 213 (6%) with impaired fasting glucose, and 2,582 (77%)with normal fasting glucose. Of diabetic participants, 12% had recommended fasting glucose levels of less than 110 mg/dL. Of participants with hypertension, a larger proportion of diabetic participants than nondiabetic participants (89% versus 75%, P < .01) was treated with antihypertensive agents, but a smaller proportion of diabetic participants had recommended blood pressure levels of 129/85 mmHg or lower than nondiabetic participants had recommended blood pressure levels of 139/89 mmHg or lower (27% vs 48%, P < .01). Diabetic dyslipidemic participants were treated less often with lipid-lowering therapy (26% versus 55%, P < .01) and achieved recommended low-density lipoprotein goals less often (8%versus 54%, P < .01) than nondiabetic dyslipidemic participants. CONCLUSIONS: Overall, treatment and control of cardiovascular risk factors were suboptimal in this older population, especially among those with diabetes mellitus. Optimizing risk-factor control can improve health outcomes in older adults with and without diabetes mellitus.
Keywords: Age Factors; Aged; Blood Glucose; Blood Pressure; Cardiovascular Diseases; Cholesterol, LDL; Cross-Sectional Studies; Diabetes Complications; Diabetes Mellitus; Female; Humans; Male; Prevalence; Prospective Studies; Risk Factors

Incidence, manifestations, and predictors of brain infarcts defined by serial cranial magnetic resonance imaging in the elderly: the Cardiovascular Health Study. - Longstreth, W T; Dulberg, Corinne; Manolio, Teri A; Lewis, Michael R; Beauchamp, Norman J; O'Leary, Daniel; Carr, Jeff; Furberg, Curt D (Stroke, 2002)
BACKGROUND AND PURPOSE: MRI-defined infarcts are common in the elderly. We sought to explore incidence, manifestations, and predictors of such infarcts. METHODS: The Cardiovascular Health Study (CHS) is a population-based, longitudinal study of 5888 people aged > or =65 years. Participants have had extensive baseline and follow-up evaluations; 1433 participants underwent 2 MRI scans separated by 5 years and had no infarcts on initial MRI. RESULTS: On follow-up MRI, 254 participants (17.7%) had 1 or more infarcts. Most were single (75.6%), subcortical (79.9%), and small (3 to 20 mm in 87.0%). Only 11.4% of those with infarcts experienced a documented transient ischemic attack or stroke between the scans. Although participants were similar at initial MRI, those with MRI-defined infarcts on follow-up experienced greater decline than those without infarcts on the Modified Mini-Mental State Examination and Digit-Symbol Substitution test (both P<0.01). Severity of white matter changes on initial MRI was the strongest predictor of incident infarcts. When it was excluded from stepwise multivariable models, predictors were serum creatinine, age, and ankle-arm index. CONCLUSIONS: Incident MRI-defined infarcts commonly affect the elderly. Most are small, subcortical, and not associated with acute symptoms recognized as a transient ischemic attack or stroke. Nonetheless, they cannot be considered silent because of their association with subtle cognitive deficits. These covert infarcts are associated with white matter changes, which may share a common pathophysiology. Whether control of vascular risk factors, such as blood pressure, would reduce the risk of developing these infarcts and associated cognitive decline deserves further investigation.
Keywords: Aged; Brain Infarction; California; Cohort Studies; Creatinine; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Magnetic Resonance Imaging; Maryland; Multivariate Analysis; Neuropsychological Tests; North Carolina; Odds Ratio; Pennsylvania; Predictive Value of Tests; Risk Factors

Inflammation and coagulation factors in persons > 65 years of age with symptoms of depression but without evidence of myocardial ischemia. - Kop, Willem J; Gottdiener, John S; Tangen, Catherine M; Fried, Linda P; McBurnie, Mary Ann; Walston, Jeremy; Newman, Anne; Hirsch, Calvin; Tracy, Russell P (Am J Cardiol, 2002)
Depression is associated with increased cardiovascular disease, but the underlying mechanisms are not well understood. This study examines associations of depressive symptoms with inflammation and coagulation factors in persons aged > 65 years. Blood samples were obtained from 4,268 subjects free of cardiovascular disease (age 72.4 +/- 5.5 years, 2,623 women). Inflammation markers were C-reactive protein (CRP), white blood cell (WBC) count, total platelet count, and albumin; coagulation factors included factors VIIc and VIIIc and fibrinogen. Depression was assessed with the Center for Epidemiologic Studies Depression scale, and states of energy depletion with a validated exhaustion index. Statistical adjustments were made for risk factors (age, sex, race, systolic blood pressure, smoking status, diabetes mellitus) and physical measures of frailty (isometric handgrip, timed 15-feet walk test, activity level). Depression was associated with elevated CRP (3.31 +/- 0.10 vs 3.51 +/- 0.21 mg/L), WBC (6.14 +/- 0.03 vs 6.43 +/- 0.11 10(6)/L), fibrinogen (319 +/- 1 vs 326 +/- 3 mg/dl), and factor VIIc (124.6 +/- 0.6% vs 127.2 +/- 1.3%; all p <0.05). Exhaustion also was related to elevated inflammation and coagulation markers (p < 0.05). Exhausted men had markedly elevated CRP levels (6.82 +/- 2.10 mg/L) versus nonexhausted men (3.05 +/- 0.16: p = 0.007). After adjustment for control variables, exhaustion remained associated with albumin (p = 0.033), fibrinogen (p = 0.017), CRP (p = 0.066), and WBC (p = 0.060), whereas associations of depressive symptoms with biochemistry measures lost statistical significance. Thus, depression and exhaustion are associated with low-grade inflammation and elevated coagulation factors in persons aged > 65 years.
Keywords: Aged; Blood Chemical Analysis; Blood Coagulation Factors; Cardiovascular Diseases; Depression; Female; Humans; Inflammation; Male; Risk Factors

Left atrial dimensions determined by M-mode echocardiography in black and white older (> or =65 years) adults (The Cardiovascular Health Study). - Manolio, Teri A; Gottdiener, John S; Tsang, Teresa S M; Gardin, Julius M (Am J Cardiol, 2002)
Stroke and atrial fibrillation are common and serious illnesses in the elderly, the risks of which are substantially increased by left atrial (LA) enlargement. Despite growing recognition of the importance of LA enlargement, the distribution and correlates of LA dimension in the elderly have not been well defined. A total of 3,882 women and men aged >65 years were studied. Increased LA dimension was independently associated with increased weight, mitral annular calcium, regional wall motion abnormalities, mitral early peak inflow velocity, and left ventricular (LV) fractional shortening. Increased LA dimension was negatively associated with aortic leaflet thickening. The relation with LV fractional shortening was curvilinear with a nadir at 35% to 40%. LA dimension in black men was approximately 1.9 mm less than in white men in multivariate analyses. Adjustment for spirometric lung volumes and chest dimensions appeared to diminish the race-LA dimension relation. Thus, LA dimension is strongly associated with weight and with several echocardiographic valvular abnormalities; its relation with LV fractional shortening is U-shaped with a nadir at the borderline of LV functional impairment.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Blood Flow Velocity; Body Weight; Cardiovascular Diseases; Echocardiography; Electrocardiography; European Continental Ancestry Group; Evidence-Based Medicine; Female; Heart Atria; Heart Ventricles; Humans; Male; Multivariate Analysis; Prospective Studies; Risk Factors; Statistics as Topic; Ventricular Function, Left

No association of plasma prothrombin concentration or the G20210A mutation with incident cardiovascular disease: results from the Cardiovascular Health Study. - Smiles, Adam M; Jenny, Nancy S; Tang, Zhonghua; Arnold, Alice; Cushman, Mary; Tracy, Russell P (Thromb Haemost, 2002)
Prothrombin is a key factor in blood clotting, a process intimately involved in thrombotic disease. We assessed prothrombin levels and G20210A genotype in a case-control study within the Cardiovascular Health Study. Cases included angina, myocardial infarction, stroke, and the presence of MRI-detectable infarcts (n approximately 250 each). Population-based controls free of clinical cardiovascular disease (CVD) (n approximately 500) and a subset free of clinical and subclinical CVD (n approximately 250) were used for comparison. The 20210 A allele, frequency 2.9%, was associated with higher mean prothrombin levels: 166.3 vs. 139.5 microg/ml (P <0.001). Significant correlates of prothrombin included gender, plasma lipids, other vitamin K-dependent proteins, and inflammatory markers, but not race, smoking, hypertension, diabetes, measures of subclinical CVD, or markers of procoagulant activity. Compared to controls, neither genotype nor prothrombin level was associated with any CVD case group. We conclude that, in the elderly, neither prothrombin level nor 20210 genotype were associated with either CVD risk factors or events. This is consistent with the lack of association of prothrombin levels with measures of underlying CVD or procoagulant markers.
Keywords: 3' Untranslated Regions; Aged; Aged, 80 and over; Alleles; Angina Pectoris; Blood Proteins; Cardiovascular Diseases; Case-Control Studies; Comorbidity; Diabetes Mellitus; Female; Genetic Predisposition to Disease; Humans; Hyperlipidemias; Hypertension; Male; Mutation; Myocardial Infarction; Obesity; Promoter Regions, Genetic; Prothrombin; Risk Factors; Smoking; Stroke; Vermont

Nuclear magnetic resonance spectroscopy of lipoproteins and risk of coronary heart disease in the cardiovascular health study. - Kuller, Lewis; Arnold, Alice; Tracy, Russell; Otvos, James; Burke, Greg; Psaty, Bruce; Siscovick, David; Freedman, David S; Kronmal, Richard (Arterioscler Thromb Vasc Biol, 2002)
OBJECTIVES: Relationships between incident cardiovascular disease and lipoprotein subclass measurements by nuclear magnetic resonance spectroscopy were evaluated in the Cardiovascular Health Study (CHS) in a nested case-cohort analysis. METHODS AND RESULTS: The case group consisted of 434 participants with incident myocardial infarction (MI) and angina diagnosed after entry to the study (1990 to 1995) and the comparison group, 249 "healthy" participants with no prevalent clinical or subclinical disease. By univariate analysis, the median levels for healthy participants versus participants with incident MI and angina were 0 versus 7 mg% for small low density lipoprotein (LDL), 1501 versus 1680 nmol/L for the number of LDL particles, and 21.6 versus 21.3 for LDL size, and these values were significantly different between "healthy" participants and those with incident MI and angina for women but not men. The levels of less dense LDL, which is most of the total LDL cholesterol among women, was not related to incident MI and angina. For women, large high density lipoprotein cholesterol (HDLc), but not small HDLc, levels were significantly higher for healthy participants compared with levels for participants with MI and angina. For men and women, levels of total and very low density lipoprotein triglycerides were higher for the case group than for the healthy group. In multivariate models for women that included triglycerides and HDLc, the number of LDL particles (but not LDL size) remained significantly related to MI and angina. CONCLUSIONS: Small LDL, the size of LDL particles, and the greater number of LDL particles are related to incident coronary heart disease among older women.
Keywords: Aged; Aging; Cardiovascular System; Case-Control Studies; Cohort Studies; Coronary Disease; Female; Health Status; Humans; Lipoproteins, HDL; Lipoproteins, LDL; Lipoproteins, VLDL; Magnetic Resonance Spectroscopy; Male; Nuclear Magnetic Resonance, Biomolecular; Risk Factors; Sex Factors

Outcome of congestive heart failure in elderly persons: influence of left ventricular systolic function. The Cardiovascular Health Study. - Gottdiener, John S; McClelland, Robyn L; Marshall, Robert; Shemanski, Lynn; Furberg, Curt D; Kitzman, Dalane W; Cushman, Mary; Polak, Joseph; Gardin, Julius M; Gersh, Bernard J; Aurigemma, Gerard P; Manolio, Teri A (Ann Intern Med, 2002)
BACKGROUND: Most persons with congestive heart failure are elderly, and many elderly persons with congestive heart failure have normal left ventricular systolic function. OBJECTIVE: To evaluate the relationship between left ventricular systolic function and outcome of congestive heart failure in elderly persons. DESIGN: Population-based longitudinal study of coronary heart disease and stroke. SETTING: Four U.S. sites: Forsyth County, North Carolina; Sacramento County, California; Allegheny County, Pennsylvania; and Washington County, Maryland. PARTICIPANTS: 5888 persons who were at least 65 years of age and were recruited from the community. MEASUREMENTS: Total mortality and cardiovascular morbidity and mortality. RESULTS: Of 5532 participants, 269 (4.9%) had congestive heart failure. Among these, left ventricular function was normal in 63%, borderline decreased in 15%, and overtly impaired in 22%. The mortality rate was 25 deaths per 1000 person-years in the reference group (no congestive heart failure and normal left ventricular function at baseline); 154 deaths per 1000 person-years in participants with congestive heart failure and impaired left ventricular systolic function; 87 and 115 deaths per 1000 person-years in participants with congestive heart failure and normal or borderline systolic function, respectively; and 89 deaths per 1000 person-years in persons with impaired left ventricular function but no congestive heart failure. Although the risk for death from congestive heart failure was lower in persons with normal systolic function than in those with impaired function, more deaths were associated with normal systolic function because more persons with heart failure fall into this category. CONCLUSIONS: Community-dwelling elderly persons, especially those with impaired left ventricular function, have a substantial risk for death from congestive heart failure. However, more deaths occur from heart failure in persons with normal systolic function because left ventricular function is more often normal than impaired in elderly persons with heart failure.
Keywords: Aged; Cause of Death; Echocardiography; Female; Heart Failure; Humans; Longitudinal Studies; Male; Myocardial Infarction; Prevalence; Prognosis; Risk Factors; Stroke; Ventricular Dysfunction, Right; Ventricular Function, Left

Predictors of sleep-disordered breathing in community-dwelling adults: the Sleep Heart Health Study. - Young, Terry; Shahar, Eyal; Nieto, F Javier; Redline, Susan; Newman, Anne B; Gottlieb, Daniel J; Walsleben, Joyce A; Finn, Laurel; Enright, Paul; Samet, Jonathan M (Arch Intern Med, 2002)
BACKGROUND: Sleep-disordered breathing (SDB) is common, but largely undiagnosed in the general population. Information on demographic patterns of SDB occurrence and its predictive factors in the general population is needed to target high-risk groups that may benefit from diagnosis. METHODS: The sample comprised 5615 community-dwelling men and women aged between 40 and 98 years who were enrolled in the Sleep Heart Health Study. Data were collected by questionnaire, clinical examinations, and in-home polysomnography. Sleep-disordered breathing status was based on the average number of apnea and hypopnea episodes per hour of sleep (apnea-hypopnea index [AHI]). We used multiple logistic regression modeling to estimate cross-sectional associations of selected participant characteristics with SDB defined by an AHI of 15 or greater. RESULTS: Male sex, age, body mass index, neck girth, snoring, and repeated breathing pause frequency were independent, significant correlates of an AHI of 15 or greater. People reporting habitual snoring, loud snoring, and frequent breathing pauses were 3 to 4 times more likely to have an AHI of 15 or greater vs an AHI less than 15, but there were weaker associations for other factors with an AHI of 15 or greater. The odds ratios (95% confidence interval) for an AHI of 15 or greater vs an AHI less than 15 were 1.6 and 1.5, respectively, for 1-SD increments in body mass index and neck girth. As age increased, the magnitude of associations for SDB and body habitus, snoring, and breathing pauses decreased. CONCLUSIONS: A significant proportion of occult SDB in the general population would be missed if screening or case finding were based solely on increased body habitus or male sex. Breathing pauses and obesity may be particularly insensitive for identifying SDB in older people. A better understanding of predictive factors for SDB, particularly in older adults, is needed.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Cohort Studies; Continental Population Groups; Female; Humans; Male; Middle Aged; Obesity; Predictive Value of Tests; Residence Characteristics; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Snoring

Prevalence of renovascular disease in the elderly: a population-based study. - Hansen, Kimberley J; Edwards, Matthew S; Craven, Timothy E; Cherr, Gregory S; Jackson, Sharon A; Appel, Richard G; Burke, Gregory L; Dean, Richard H (J Vasc Surg, 2002)
PURPOSE: The purpose of this investigation was to estimate the population-based prevalence of renovascular disease (RVD), defined as > or = 60% diameter-reducing renal artery stenosis or occlusion, and to define its associations with age, gender, race, and other potential risk factors among participants in the Cardiovascular Health Study (CHS). METHODS: The CHS is a multicenter, longitudinal cohort study of cardiovascular disease risk factors, morbidity, and mortality among free-living adults of more than 65 years of age. As part of an ancillary investigation, participants in the Forsyth County cohort of the CHS were invited to undergo renal duplex sonography (RDS) to define the presence or absence of RVD. RVD was defined as stenosis with a focal renal artery peak systolic velocity exceeding 1.8 m/s in the main renal artery and defined as occlusion when an imaged renal artery lacked a Doppler signal. Demographic and atherosclerotic risk factor data were gathered as part of the baseline CHS examination. Univariable tests of association were performed with chi(2) and Student t tests and logistic regression analysis. Multivariate associations were examined with logistic regression analysis. RESULTS: Eight hundred seventy CHS participants underwent RDS. Of these examinations, 834 (96%) were technically adequate to define the presence or absence of RVD. The RDS study cohort had a mean age of 77.2 +/- 4.9 years and consisted of 63% women and 37% men. Participant race was 76% white and 23% African American. The overall prevalence rate of RVD was 6.8%. Among the 57 patients with RVD, 50 (88%) had unilateral disease and seven (12%) had bilateral disease. Seven cases were seen of renal artery occlusion, including one case with contralateral renal artery stenosis. The mean ages of patients with and without RVD were 78.7 +/- 5.7 years and 77.1 +/- 4.9 years (P =.018). RVD was present in 5.5% of women and 9.1% of men (P =.053). RVD was present in 6.9% of white participants and 6.7% of African American participants (P =.933). Multivariate analysis revealed increasing participant age (P =.028; odds ratio, 1.34; 95% CI, 1.03, 1.73), high-density lipoprotein cholesterol levels of less than 40 mg/dL (P =.003; odds ratio, 2.63; 95% CI, 1.40, 4.93), and increasing systolic blood pressure (P =.007; odds ratio, 1.44; 95% CI, 1.10, 1.87) to be significantly and independently associated with the presence of RVD. CONCLUSION: This investigation provides the first population-based estimate of the prevalence of RVD among free-living, elderly black and white Americans. RVD was present in 6.8% of the study cohort. RVD showed no association with ethnicity. However, its presence was significantly and independently associated with increasing age, low high-density lipoprotein cholesterol levels, and increasing systolic blood pressure.
Keywords: Age Factors; Aged; Aged, 80 and over; Cohort Studies; Ethnic Groups; Female; Humans; Longitudinal Studies; Male; Prevalence; Prospective Studies; Renal Artery; Renal Artery Obstruction; Risk Factors; Sex Factors; Ultrasonography, Doppler, Duplex

Prospective study of the G20210A polymorphism in the prothrombin gene, plasma prothrombin concentration, and incidence of venous thromboembolism. - Folsom, Aaron R; Cushman, Mary; Tsai, Michael Y; Heckbert, Susan R; Aleksic, Nena (Am J Hematol, 2002)
Case-control studies have indicated increased risk of venous thrombosis associated with the prothrombin gene G20210A polymorphism and with elevated plasma prothrombin levels. We sought to confirm these results in a prospective population-based study of 21,690 persons. We measured G20210A and prothrombin antigen on pre-event blood samples of 302 participants who developed venous thromboembolism (VTE) and 626 participants who remained free of VTE. Approximately 4.0% of cases and 2.4% of controls carried the G20210A polymorphism, but only one of 137 African Americans did. The odds ratio in whites was 1.87 (95% CI = 0.85, 4.11)--higher for those who reported a prior history of VTE (OR = 5.44) than those reporting no VTE history (OR = 1.41) and in those with idiopathic VTE (OR = 2.51) than those with secondary VTE (OR = 1.38). There was no association between venous thromboembolism and plasma prothrombin antigen level. We estimated that the G20210A polymorphism may account for approximately 2.5% of venous thromboembolism events in United States whites.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Case-Control Studies; European Continental Ancestry Group; Genotype; Humans; Incidence; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Prospective Studies; Prothrombin; Recurrence; Research Design; Risk Factors; Thromboembolism; United States

A prospective study of venous thromboembolism in relation to factor V Leiden and related factors. - Folsom, Aaron R; Cushman, Mary; Tsai, Michael Y; Aleksic, Nena; Heckbert, Susan R; Boland, Lori L; Tsai, Albert W; Yanez, N David; Rosamond, Wayne D (Blood, 2002)
The aim of this study was to examine the occurrence of venous thromboembolism (VTE) in relation to factor V-related risk factors. Using a nested case-control design combining 2 population-based prospective studies, we measured factor V Leiden, HR2 haplotype, activated protein C (APC) resistance, and plasma factor V antigen in 335 participants who developed VTE during 8 years of follow-up and 688 controls. The overall odds ratio (OR) of VTE was 3.67 (95% CI, 2.20-6.12) in participants carrying factor V Leiden compared with noncarriers. APC resistance measured after predilution with factor V-deficient plasma conferred an OR of 2.58 (95% CI, 1.62-4.10). All 3 participants homozygous for the HR2 haplotype had a VTE, and the OR of VTE for homozygosity was estimated to be 5.5 (95% CI, 2.45-12.5). Carriers of the HR2 haplotype otherwise were not at increased risk of VTE overall (OR = 1.05; 95% CI, 0.64-1.72), but double heterozygotes for HR2 and factor V Leiden carried an OR of idiopathic VTE of 16.3 (95% CI, 1.7-159) compared with noncarriers. Factor V antigen also was not associated with VTE overall, but for participants with the combination of high factor V antigen plus factor V Leiden the OR of idiopathic VTE was 11.5 (95% CI, 4.2-31.4). In the general population, APC resistance and factor V Leiden were important VTE risk factors; homozygosity for the HR2 haplotype may be a risk factor but was rare; otherwise, HR2 haplotype and factor V antigen were not risk factors except in carriers of factor V Leiden.
Keywords: Activated Protein C Resistance; Aged; Cohort Studies; Continental Population Groups; Factor V; Genotype; Haplotypes; Humans; Incidence; Longitudinal Studies; Middle Aged; Odds Ratio; Prospective Studies; Risk Factors; Thromboembolism; Venous Thrombosis

Racial differences in coronary artery calcification in older adults. - Newman, Anne B; Naydeck, Barbara L; Whittle, Jeff; Sutton-Tyrrell, Kim; Edmundowicz, Daniel; Kuller, Lewis H (Arterioscler Thromb Vasc Biol, 2002)
Reports on race-related differences in coronary artery calcium (CAC) are just beginning to emerge and have not been well studied in the elderly. This study was undertaken to assess whether such differences exist and the relationship between CAC and cardiovascular risk factors in a cohort of elderly community-dwelling adults. CAC was measured by using electron-beam tomography in 614 adults (aged 67 to 99 years), of whom 59% were women and 23% were black. The median CAC score was lower in blacks than in whites for men (159 versus 787, respectively; P<0.001) and for women (134 versus 233, respectively; P=0.02) after adjustment for age, cardiovascular disease, and risk factors for cardiovascular disease, although this difference was stronger and remained significant among men only. Lower CAC scores were also observed in the subgroup of blacks with a history of myocardial infarction. The lower CAC scores in blacks compared with whites observed in this study is consistent with either a lower prevalence of coronary artery disease or a lower extent of calcification of coronary artery disease.
Keywords: Age Factors; Aged; Calcinosis; Cohort Studies; Coronary Artery Disease; Female; Humans; Logistic Models; Male; Risk Factors; Sex Factors; Tomography, X-Ray Computed

A regression model for longitudinal change in the presence of measurement error. - Yanez, N David; Kronmal, Richard A; Shemanski, Lynn R; Psaty, Bruce M (Ann Epidemiol, 2002)
PURPOSE: The analysis of change in measured variables has become quite popular in studies where data are collected repeatedly over time. The authors describe some of the potential pitfalls in the analysis of change when the variable for change is measured with error. They show that regression analysis is often biased, possibly leading to erroneous results. METHODS: A simple method to correct for measurement error bias in regression models that model change is presented. RESULTS AND CONCLUSIONS: The two examples illustrate how measurement error can adversely affect an analysis. The bias-corrected approach yields valid results.
Keywords: Aged; Bias; Coronary Disease; Humans; Lipoproteins; Models, Statistical; Regression Analysis; Risk Factors

The relation of atherosclerotic cardiovascular disease to retinopathy in people with diabetes in the Cardiovascular Health Study. - Klein, Ronald; Marino, Emily K; Kuller, Lewis H; Polak, Joseph F; Tracy, Russell P; Gottdiener, John S; Burke, Gregory L; Hubbard, Larry D; Boineau, Robin (Br J Ophthalmol, 2002)
AIMS: To describe the association of retinopathy with atherosclerosis and atherosclerotic risk factors in people with diabetes. METHODS: 296 of the 558 people classified as having diabetes by the American Diabetes Association criteria, from a population based cohort of adults (ranging in age from 69 to 102 years) living in four United States communities (Allegheny County, Pennsylvania; Forsyth County, North Carolina; Sacramento County, California; and Washington County, Maryland) were studied from 1997 to 1998. Lesions typical of diabetic retinopathy were determined by grading a 45 degrees colour fundus photograph of one eye of each participant, using a modification of the Airlie House classification system. RESULTS: Retinopathy was present in 20% of the diabetic cohort, with the lowest prevalence (16%), in those 80 years of age or older. Retinopathy was detected in 20.3% of the 296 people with diabetes; 2.7% of the 296 had signs of proliferative retinopathy and 2.1% had signs of macular oedema. The prevalence of diabetic retinopathy was higher in black people (35.4%) than white (16.0%). Controlling for age, sex, and blood glucose, retinopathy was more frequent in black people than white (odds ratio (OR) 2.26, 95% confidence interval (CI) 1.01, 5.05), in those with longer duration of diabetes (OR (per 5 years of diabetes) 1.42, 95% CI 1.18, 1.70), in those with subclinical cardiovascular disease (OR 1.49, 95% CI 0.51, 4.31), or coronary heart disease or stroke (OR 3.23, 95% CI 1.09, 9.56) than those without those diseases, in those with higher plasma low density lipoprotein (LDL) cholesterol (OR (per 10 mg/dl of LDL cholesterol) 1.12, 95% CI 1.02, 1.23), and in those with gross proteinuria (OR 4.76, 95% CI 1.53, 14.86). CONCLUSION: Data from this population based study suggest a higher prevalence of retinopathy in black people than white people with diabetes and the association of cardiovascular disease, elevated plasma LDL cholesterol, and gross proteinuria with diabetic retinopathy. However, any conclusions or explanations regarding associations described here must be made with caution because only about one half of those with diabetes mellitus were evaluated.
Keywords: Age of Onset; Aged; Aged, 80 and over; Arteriosclerosis; Black People; Blood Pressure; Cohort Studies; Diabetes Mellitus, Type 2; Diabetic Retinopathy; Female; Humans; Longitudinal Studies; Male; Odds Ratio; Prospective Studies; Regression Analysis; Risk Factors; Time Factors; White People

Relationship between coronary artery calcification and other measures of subclinical cardiovascular disease in older adults. - Newman, Anne B; Naydeck, Barbara L; Sutton-Tyrrell, Kim; Edmundowicz, Daniel; O'Leary, Daniel; Kronmal, Richard; Burke, Gregory L; Kuller, Lewis H (Arterioscler Thromb Vasc Biol, 2002)
BACKGROUND: In the Cardiovascular Health Study, subclinical cardiovascular disease (CVD) predicted CVD events in older adults. The extent to which this measure or its components reflect calcified coronary disease is unknown. METHODS AND RESULTS: Coronary artery calcium (CAC) was assessed with electron beam tomography in 414 participants without clinical CVD and examined using cut points (CAC> or =400 and CAC> or =800) and the log(CAC); 274 had subclinical CVD by ankle-arm index, ECG, or carotid ultrasound. Cut points for subclinical disease as previously defined in the Cardiovascular Health Study were examined as well as continuous measures to produce receiver operating characteristic curve curves. A low ankle-arm index was highly specific for a high CAC score. The internal carotid artery intima-media thickness was most strongly correlated with CAC (r=0.30) and was significantly related to both CAC cut points and to the log(CAC) score independently of all other measures. CONCLUSIONS: In these community-dwelling older adults without clinical CVD, internal carotid artery intima-media thickness was most closely related to CAC. However, 17.5% of those with a CAC> or =400 would be missed in the ascertainment of subclinical atherosclerosis using the previously published composite of subclinical atherosclerosis. Prospective follow-up will determine whether the CAC score improves prediction of CVD events over other noninvasive measures.
Keywords: Aged; Aged, 80 and over; Calcinosis; Cardiovascular Diseases; Carotid Stenosis; Cohort Studies; Coronary Artery Disease; Demography; Female; Humans; Male; Prevalence; Risk Factors; Sensitivity and Specificity; Sex Factors; Tomography, X-Ray Computed; Tunica Intima; Tunica Media

Serum potassium level and dietary potassium intake as risk factors for stroke. - Green, D M; Ropper, A H; Kronmal, R A; Psaty, B M; Burke, G L (Neurology, 2002)
BACKGROUND: Numerous studies have found that low potassium intake and low serum potassium are associated with increased stroke mortality, but data regarding stroke incidence have been limited. Serum potassium levels, dietary potassium intake, and diuretic use in relation to risk for stroke in a prospectively studied cohort were investigated. METHODS: The study comprised 5,600 men and women older than 65 years who were free of stroke at enrollment. Baseline data included serum potassium level, dietary potassium intake, and diuretic use. Participants were followed for 4 to 8 years, and the incidence and types of strokes were recorded. Low serum potassium was defined as less than 4.1 mEq/L, and low potassium intake as less than 2.4 g/d. RESULTS: Among diuretic users, there was an increased risk for stroke associated with lower serum potassium (relative risk [RR]: 2.5, p < 0.0001). Among individuals not taking diuretics, there was an increased risk for stroke associated with low dietary potassium intake (RR: 1.5, p < 0.005). The small number of diuretic users with lower serum potassium and atrial fibrillation had a 10-fold greater risk for stroke compared with those with higher serum potassium and normal sinus rhythm. CONCLUSIONS: A lower serum potassium level in diuretic users, and low potassium intake in those not taking diuretics were associated with increased stroke incidence among older individuals. Lower serum potassium was associated with a particularly high risk for stroke in the small number of diuretic users with atrial fibrillation. Further study is required to determine if modification of these factors would prevent strokes.
Keywords: Aged; Cohort Studies; Confidence Intervals; Diuretics; Humans; Linear Models; Male; Potassium; Potassium, Dietary; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke

A stroke prediction score in the elderly: validation and Web-based application. - Lumley, Thomas; Kronmal, Richard A; Cushman, Mary; Manolio, Teri A; Goldstein, Steven (J Clin Epidemiol, 2002)
The objective of this study was to construct a prediction model for predicting stroke in an elderly U.S. population, and to assess the accuracy in this population of other previously published prediction models. The subjects were participants in the Cardiovascular Health Study: 2,495 men and 3,393 women age 65 years and older at baseline, and followed for 6.3 years. Among 5,711 participants free of baseline stroke, 399 strokes occurred. Sex-specific prediction equations were constructed using study variables that were most importantly related to incident stroke: age, systolic blood pressure, diabetes, ECG diagnosis of atrial fibrillation or left ventricular hypertrophy, confirmed history of cardiovascular disease, diabetes, time to walk 15 ft, and serum creatinine. The prediction rule was implemented as a risk score and in a Web-based interactive Java applet. Overall, the model predicted 5-year stroke risks ranging from less than 1 to 59%. The 20% of subjects in the highest predicted risk group had a 5-year actual stroke incidence rate of 15%, while the 20% lowest risk group had a 1% incidence. Risk scores from two other studies performed well in these study participants. Effective discrimination between low and high stroke risk in the elderly was possible in this cohort with data that are easy to obtain. Evaluation of the generalizability and clinical usefulness of this prediction model requires further research.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Female; Follow-Up Studies; Humans; Incidence; Male; Models, Cardiovascular; Predictive Value of Tests; Risk Factors; ROC Curve; Stroke; United States

Therapy with hydroxymethylglutaryl coenzyme a reductase inhibitors (statins) and associated risk of incident cardiovascular events in older adults: evidence from the Cardiovascular Health Study. - Lemaitre, Rozenn N; Psaty, Bruce M; Heckbert, Susan R; Kronmal, Richard A; Newman, Anne B; Burke, Gregory L (Arch Intern Med, 2002)
BACKGROUND: Recommendations to treat older adults with hydroxymethylglutaryl coenzyme A reductase inhibitors (statins) for the primary prevention of coronary heart disease events are supported by a single clinical trial restricted to adults 73 years or younger with low levels of high-density lipoprotein cholesterol. METHODS: We investigated the association of statin use with incident cardiovascular disease and all-cause mortality during up to 7.3 years' follow-up of 1250 women and 664 men from the Cardiovascular Health Study. Study participants were 65 years and older and free of cardiovascular disease at baseline. They received drug therapy to lower cholesterol levels at baseline or no treatment with a recommendation for therapy according to the National Cholesterol Education Program guidelines. Use of these drugs was assessed annually. We used proportional-hazards models to calculate hazard ratios (HRs) and 95% confidence intervals (CIs), adjusted for confounding variables. RESULTS: We found 382 incident cardiovascular events (159 myocardial infarctions, 159 strokes, and 64 deaths due to coronary heart disease) and 362 total deaths from June 1, 1989, to May 31, 1997. Compared with no use of drugs to lower cholesterol levels, statin use was associated with decreased risk of cardiovascular events (multivariate HR, 0.44; 95% CI, 0.27-0.71) and all-cause mortality (HR, 0.56; 95% CI, 0.36-0.88). Similar associations were observed among participants 74 years or older at baseline. CONCLUSIONS: Use of statins was associated with decreased risk of incident cardiovascular events among elderly adults. These findings lend support to the National Cholesterol Education Program guidelines, which recommend therapy for the lowering of cholesterol levels for older adults with hypercholesterolemia.
Keywords: Aged; Cholesterol, LDL; Coronary Disease; Female; Follow-Up Studies; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Hypercholesterolemia; Hypolipidemic Agents; Incidence; Male; Multivariate Analysis; Proportional Hazards Models; Risk Factors; United States

The association between the length of the QT interval and mortality in the Cardiovascular Health Study. - Robbins, John; Nelson, Jennifer Clark; Rautaharju, Pentti M; Gottdiener, John S (Am J Med, 2003)
PURPOSE: A long QT interval is a risk factor for arrhythmic events and sudden death. Whether moderate QT prolongation is associated with clinical events in community-dwelling elderly patients is uncertain. METHODS: We measured the QT interval in a population-based sample of 5888 men and women at least 65 years of age who were participants in the Cardiovascular Health Study. The association between Bazett's rate-corrected QT (QTc, in ms) and mortality during the subsequent 10 years was evaluated. We stratified participants by the presence or absence of coronary heart disease status at baseline, and adjusted for coronary heart disease risk factors. RESULTS: The rates of all-cause and coronary heart disease mortality were greater in participants with longer QTc intervals. Among participants without known coronary heart disease, those whose QTc interval was >450 ms were at increased risk of all-cause mortality (relative risk [RR] = 1.34; 95% confidence interval [CI]: 1.07 to 1.67) and coronary heart disease mortality (RR = 1.6; 95% CI: 1.0 to 2.5) when compared with participants whose QTc interval was <410 ms. The associations were stronger among those with known coronary heart disease (RR for all-cause mortality = 2.3; 95% CI: 1.6 to 3.3; and RR for coronary heart disease mortality = 2.0; 95% CI: 1.1 to 3.7). CONCLUSIONS: The QT interval from the standard electrocardiograms is of value for identification of elderly persons at increased risk of coronary heart disease and total mortality. A QTc interval >450 ms should prompt clinical evaluation and possible interventions to reduce the risk of coronary events.
Keywords: Aged; Arrhythmias, Cardiac; Cause of Death; Coronary Disease; Electrocardiography; Female; Follow-Up Studies; Heart Rate; Humans; Male; Randomized Controlled Trials as Topic; Risk Factors; Statistics as Topic; Survival Analysis; United States

The association between time since last meal and blood pressure in older adults: the cardiovascular health study. - Smith, Nicholas L; Psaty, Bruce M; Rutan, Gale H; Lumley, Thomas; Yanez, David; Chaves, Paulo H M; Kronmal, Richard A (J Am Geriatr Soc, 2003)
OBJECTIVES: To demonstrate a postprandial hypotensive (PPH) phenomenon in older adults. DESIGN: Observational, prospective cohort study composed of baseline and nine follow-up visits. SETTING: Cardiovascular Health Study, an epidemiological study of risk factors for cardiovascular disease in older adults. PARTICIPANTS: Five thousand eight hundred eighty-eight community-dwelling adults aged 65 and older. MEASUREMENTS: Blood pressure and time since last meal were recorded synchronously at baseline and at follow-up clinic visits. Generalized estimating equations were used to estimate associations between time since last meal and blood pressure and to adjust variance estimates to account for repeated blood pressure measures within subjects across fasting times. RESULTS: Mean systolic and diastolic blood pressures were lower in the first hour after the last meal and were progressively higher through the fourth hour after the last meal than blood pressures measured immediately after the last meal (0 hour: 133.7/68.8 mmHg; 1st hour: 130.1/66.6 mmHg; 4th hour: 136.5/71.1 mmHg). Changes were significant for systolic and diastolic measures (P <.001 for both). Exploratory analyses suggested that the systolic PPH association was more pronounced in women. Little evidence was found that the degree of systolic or diastolic PPH varied by age, race, prevalent cardiovascular disease, heart rate, ejection fraction, treated hypertension or diabetes mellitus, or body mass index. CONCLUSION: These data support previous observations that there is a significant drop in blood pressure within 1 hour after a meal in older adults. Time since last meal may be an important factor to consider when measuring blood pressure in older adults, and perhaps national standards need to be set.
Keywords: Aged; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Eating; Female; Humans; Hypotension; Male; Postprandial Period; Prospective Studies; Risk Factors; Time Factors

C-reactive protein, carotid intima-media thickness, and incidence of ischemic stroke in the elderly: the Cardiovascular Health Study. - Cao, Jie J; Thach, Chau; Manolio, Teri A; Psaty, Bruce M; Kuller, Lewis H; Chaves, Paulo H M; Polak, Joseph F; Sutton-Tyrrell, Kim; Herrington, David M; Price, Thomas R; Cushman, Mary (Circulation, 2003)
BACKGROUND: Increased carotid artery intima-media thickness (IMT) and elevated C-reactive protein (CRP) are both associated with the occurrence of stroke. We investigated whether elevated CRP is a risk factor for ischemic stroke independent of carotid IMT and studied the interaction between CRP and IMT. METHODS AND RESULTS: We studied 5417 participants aged 65 years or older without preexisting stroke or chronic atrial fibrillation who were participants in the Cardiovascular Health Study. The hazard ratio of incident ischemic stroke was estimated by Cox proportional hazards regression. During 10.2 years of follow-up, 469 incident ischemic strokes occurred. The adjusted hazard ratios for ischemic stroke in the 2nd to 4th quartiles of baseline CRP, relative to the 1st quartile, were 1.19 (95% CI 0.92 to 1.53), 1.05 (95% CI 0.81 to 1.37), and 1.60 (95% CI 1.23 to 2.08), respectively. With additional adjustment for carotid IMT, there was little confounding. The association of CRP with stroke was significantly different depending on IMT (P<0.02), with no association of CRP with stroke among those in the lowest IMT tertile and a significant association among those with higher levels of IMT. CONCLUSIONS: We conclude that elevated CRP is a risk factor for ischemic stroke, independent of atherosclerosis severity as measured by carotid IMT. The association of CRP with stroke is more apparent in the presence of a higher carotid IMT. CRP and carotid IMT may each be independent integrals in determining the risk of ischemic stroke.
Keywords: Aged; Brain Ischemia; C-Reactive Protein; California; Carotid Arteries; Cohort Studies; Comorbidity; Female; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Maryland; North Carolina; Odds Ratio; Pennsylvania; Proportional Hazards Models; Risk Assessment; Risk Factors; Stroke; Tunica Intima; Tunica Media; Ultrasonography

Diabetes and sleep disturbances: findings from the Sleep Heart Health Study. - Resnick, Helaine E; Redline, Susan; Shahar, Eyal; Gilpin, Adele; Newman, Anne; Walter, Robert; Ewy, Gordon A; Howard, Barbara V; Punjabi, Naresh M (Diabetes Care, 2003)
OBJECTIVE: To test the hypothesis that diabetes is independently associated with sleep-disordered breathing (SDB), and in particular that diabetes is associated with sleep abnormalities of a central, rather than obstructive, nature. RESEARCH DESIGN AND METHODS: Using baseline data from the Sleep Heart Health Study (SHHS), we related diabetes to 1). the respiratory disturbance index (RDI; number of apneas plus hypopneas per h of sleep); 2). obstructive apnea index (OAI; >or=3 apneas/h of sleep associated with obstruction of the upper airway); 3). percent of sleep time < 90% O(2) saturation; 4). central apnea index (CAI; >or=3 apneas [without respiratory effort]/h sleep); 5). occurrence of a periodic breathing (Cheyne Stokes) pattern; and 6) sleep stages. Initial analyses excluding persons with prevalent cardiovascular disease (CVD) were repeated including these participants. RESULTS: Of the 5874 participants included in this report, 692 (11.8%) reported diabetes or were taking oral hypoglycemic medications or insulin and 1002 had prevalent CVD. Among the 4872 persons without CVD, 470 (9.6%) had diabetes. Diabetic participants had worse CVD risk factor profiles than their nondiabetic counterparts, including higher BMI, waist and neck circumferences, triglycerides, higher prevalence of hypertension, and lower HDL cholesterol (P < 0.001, all). Descriptive analyses indicated differences between diabetic and nondiabetic participants in RDI, sleep stages, sleep time <90% O(2) saturation, CAI, and periodic breathing (P < 0.05, all). However, multivariable regression analyses that adjusted for age, sex, BMI, race, and neck circumference eliminated these differences for all sleep measures except percent time in rapid eye movement (REM) sleep (19.0% among diabetic vs. 20.1% among nondiabetic subjects, P < 0.001) and prevalence of periodic breathing (odds ratio [OR] for diabetic subjects versus nondiabetic subjects 1.80, 95% CI 1.02-3.15). Additionally, adjusted analyses showed diabetes was associated with nonstatistically significant elevations in the odds of an increased central breathing index (OR 1.42, 95% CI 0.80-2.55). Addition to the analysis of the 1002 persons with prevalent CVD (including 222 people with diabetes) did not materially change these results. CONCLUSIONS: These data suggest that diabetes is associated with periodic breathing, a respiratory abnormality associated with abnormalities in the central control of ventilation. Some sleep disturbances may result from diabetes through the deleterious effects of diabetes on central control of respiration. The high prevalence of SDB in diabetes, although largely explained by obesity and other confounders, suggests the presence of a potentially treatable risk factor for CVD in the diabetic population.
Keywords: Aged; Diabetes Mellitus; Female; Humans; Logistic Models; Male; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Sleep Apnea Syndromes; Sleep Apnea, Obstructive

Early age-related maculopathy in the cardiovascular health study. - Klein, Ronald; Klein, Barbara E K; Marino, Emily K; Kuller, Lewis H; Furberg, Curt; Burke, Gregory L; Hubbard, Larry D (Ophthalmology, 2003)
OBJECTIVE: To describe the prevalence of early age-related maculopathy (ARM) and its relation to atherosclerosis, lipids, hypertension, and inflammatory factors in a population studied for cardiovascular disease risk factors and outcomes. DESIGN: Population-based cohort study. PARTICIPANTS: A biracial population of 2361 adults (ranging from 69-97 years of age; 1998 whites and 363 blacks) living in four US counties (Allegheny County, Pennsylvania; Forsyth County, North Carolina; Sacramento County, California; and Washington County, Maryland) were examined during the interval from 1997 to 1998. METHODS: Drusen and other lesions typical of ARM were identified by examining a 45 degrees color fundus photograph of one eye of each participant and classified by means of a modification of the Wisconsin Age-Related Maculopathy Grading System. MAIN OUTCOME MEASURES: Early ARM. RESULTS: Early ARM was present in 15.5% and late ARM in 1.3% of the cohort. The overall prevalence of any ARM was lower in blacks (9.1%) compared with whites (18.2%). While controlling for age, race, gender, and total calories consumed in the diet, factors associated with ARM were cerebral white matter disease as detected by magnetic resonance imaging (odds ratio [OR], 1.50; 95% confidence interval [CI], 1.05, 2.16, P = 0.027), and lower serum total cholesterol (OR, per 10 mg/dl increase 0.95; 95% CI, 0.91, 0.98, P = 0.02). There were no associations between hypertension, blood pressure, common carotid artery plaque, or any systemic inflammatory factors studied and early ARM. CONCLUSIONS: This population-based study documents the higher prevalence of ARM in whites compared with blacks. Although an association was found between signs of white matter disease and early ARM, there was no evidence of an association of ARM with either hypertension or inflammatory factors.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Arteriosclerosis; Blood Pressure; C-Reactive Protein; California; Cohort Studies; Diet; European Continental Ancestry Group; Female; Humans; Hypertension; Leukocyte Count; Longitudinal Studies; Macular Degeneration; Male; Mid-Atlantic Region; North Carolina; Prevalence; Prospective Studies; Risk Factors; Serum Albumin

Elevations of inflammatory and procoagulant biomarkers in elderly persons with renal insufficiency. - Shlipak, Michael G; Fried, Linda F; Crump, Casey; Bleyer, Anthony J; Manolio, Teri A; Tracy, Russell P; Furberg, Curt D; Psaty, Bruce M (Circulation, 2003)
BACKGROUND: Renal insufficiency has been associated with cardiovascular disease events and mortality in several prospective studies, but the mechanisms for the elevated risk are not clear. Little is known about the association of renal insufficiency with inflammatory and procoagulant markers, which are potential mediators for the cardiovascular risk of kidney disease. METHODS AND RESULTS: The cross-sectional association of renal insufficiency with 8 inflammatory and procoagulant factors was evaluated using baseline data from the Cardiovascular Health Study, a population-based cohort study of 5888 subjects aged > or =65 years. C-reactive protein, fibrinogen, factor VIIc, and factor VIIIc levels were measured in nearly all participants; interleukin-6, intercellular adhesion molecule-1, plasmin-antiplasmin complex, and D-dimer levels were measured in nearly half of participants. Renal insufficiency was defined as a serum creatinine level > or =1.3 mg/dL in women and > or =1.5 mg/dL in men. Multivariate linear regression was used to compare adjusted mean levels of each biomarker in persons with and without renal insufficiency after adjustment for other baseline characteristics. Renal insufficiency was present in 647 (11%) of Cardiovascular Health Study participants. After adjustment for baseline differences, levels of C-reactive protein, fibrinogen, interleukin-6, factor VIIc, factor VIIIc, plasmin-antiplasmin complex, and D-dimer were significantly greater among persons with renal insufficiency (P<0.001). In participants with clinical, subclinical, and no cardiovascular disease at baseline, the positive associations of renal insufficiency with these inflammatory and procoagulant markers were similar. CONCLUSION: Renal insufficiency was independently associated with elevations in inflammatory and procoagulant biomarkers. These pathways may be important mediators leading to the increased cardiovascular risk of persons with kidney disease.
Keywords: Aged; alpha-2-Antiplasmin; Biomarkers; Blood Coagulation Factors; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Creatinine; Cross-Sectional Studies; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Fibrinolysin; Humans; Inflammation; Interleukin-6; Male; Prospective Studies; Renal Insufficiency; Risk Factors

Evaluation of dementia in the cardiovascular health cognition study. - Lopez, Oscar L; Kuller, Lewis H; Fitzpatrick, Annette; Ives, Diane; Becker, James T; Beauchamp, Norman (Neuroepidemiology, 2003)
OBJECTIVE: To describe a methodology to evaluate dementia and frequency of different types of dementia and prevalence of the Cardiovascular Health Study (CHS). METHODS: The CHS is a longitudinal study of cardiovascular disease among community-dwelling individuals over the age of 65. Of the 5,888 participants in the original study, 3,608 had a magnetic resonance imaging (MRI) of the brain in 1991, and formed the cohort for the dementia study. The CHS included yearly measures of cognitive function and, from 1998 to 2000, participants were evaluated for dementia by detailed neurological, and neuropsychological examinations. The possible cases of dementia and mild cognitive impairment (MCI) were adjudicated by a review committee of neurologists and psychiatrists. RESULTS: There were 480 cases of (13.3%) incident dementia in the total sample, 227 (6.3%) prevalent dementia, 577 (16.0%) MCI, and 2,318 (64.4%) normal. The adjudication committee classified 69% of the incident dementia as Alzheimer's disease (AD), 11% as vascular dementia (VaD), 16% as both, and 4% as other types. There was a substantial agreement between pre- and postMRI diagnosis of types of dementia. The frequency of dementia within the CHS cohort which survived to the end of the study in 1998-1999, was 13.5% for white men, 14.5% for white women, 22.2% for black men and 23.4% for black women. CONCLUSION: The CHS has developed a methodology for longitudinal studies of dementia in large cohorts and represents the largest study of dementia including cognitive testing, MRI and genetic markers.
Keywords: Age Distribution; Aged; Aged, 80 and over; Cardiovascular Diseases; Cognition Disorders; Cohort Studies; Cross-Sectional Studies; Dementia; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Prevalence; Risk Factors; Sex Distribution

Fibrin fragment D-dimer and the risk of future venous thrombosis. - Cushman, Mary; Folsom, Aaron R; Wang, Lu; Aleksic, Nena; Rosamond, Wayne D; Tracy, Russell P; Heckbert, Susan R (Blood, 2003)
Plasma D-dimer concentration rises more than 100-fold during acute deep vein thrombosis, but there are no prospective data concerning D-dimer as a risk factor for incident venous thrombosis in a general population. Incident venous thrombosis was ascertained in 2 prospective observational studies, the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. Of 21 690 participants enrolled between 1987 and 1993, after 8 years of follow-up, D-dimer was measured using baseline stored plasma of 307 participants who developed venous thrombosis and 616 who did not. Relative to the first quintile of the distribution of D-dimer, the age-adjusted odds ratios for future venous thrombosis for the second to fifth quintiles of D-dimer were 1.6, 2.3, 2.3, and 4.2, respectively (P for trend <.0001). Following added adjustment for sex, race, body mass index, factor V Leiden, prothrombin 20210A, and elevated factor VIII coagulant activity (factor VIII:c), these odds ratios were 1.5, 2.1, 1.9, and 3.0, respectively (P for trend <.0001). Among those with idiopathic thrombosis or secondary thrombosis unrelated to cancer, the adjusted fifth quintile odds ratios were 3.5 and 4.8, respectively. By contrast, D-dimer in the fifth versus first quintile was not related to occurrence of cancer-associated thrombosis (odds ratio, 1.1). Odds ratios for elevated D-dimer were consistently elevated in subgroups defined by age, sex, race, duration of follow-up, and thrombosis type (deep vein thrombosis or pulmonary embolus). D-dimer is strongly and positively related to the occurrence of future venous thrombosis.
Keywords: Aged; Body Mass Index; Cohort Studies; Continental Population Groups; Factor V; Factor VIII; Female; Fibrin Fibrinogen Degradation Products; Humans; Longitudinal Studies; Male; Middle Aged; Odds Ratio; Prospective Studies; Prothrombin; Risk Factors; Venous Thrombosis

Hormone replacement therapy and the risk of incident congestive heart failure: the Cardiovascular Health Study. - Rea, Thomas D; Psaty, Bruce M; Heckbert, Susan R; Cushman, Mary; Meilahn, Elaine; Olson, Jean L; Lemaitre, Rozenn N; Smith, Nicholas L; Sotoodehnia, Nona; Chaves, Paulo H M (J Womens Health (Larchmt), 2003)
BACKGROUND: The development of congestive heart failure (CHF) in older persons is related to a variety of mechanisms. Hormone replacement therapy (HRT) affects several of the pathways that may be important in the development of CHF. We hypothesized that HRT would be associated with a decreased risk of incident CHF. METHODS: Using Cox proportional-hazards regression, we assessed the risk of incident CHF (n = 304) associated with time-dependent past and current use of HRT compared to never use. The Cardiovascular Health Study is a prospective cohort study of community-dwelling adults aged 65 years and older. This analysis included female participants without a history of CHF at baseline (n = 3223). RESULTS: At baseline, 62% were never users, 26% were past users, and 12% were current users of HRT. Compared with never users, the multivariable relative risk (RR) of CHF was 1.01 (95% confidence interval [95% CI] 0.76,1.34) for past users and 1.34 (0.93,1.94) for current users. Results were similar among most treatment and clinical subgroups, except that the association of current HRT with CHF appeared to depend on body mass index (BMI) or osteoporosis status. The RR was 0.82 (0.43,1.60) for normal weight women, 1.65 (0.95,2.88) for overweight women, and 2.22 (1.06,4.67) for obese women (p = 0.01 for interaction). Similarly, the RR was 0.15 (0.04,0.65) for women with osteoporosis and 1.82 (1.25,2.65) for women without osteoporosis (p = 0.001 for interaction). CONCLUSIONS: Overall, HRT was not associated with the risk of incident CHF, although BMI and osteoporosis appeared to modify the association of HRT with CHF. The risk of CHF was lower in patients with lower BMI or osteoporosis.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Estrogen Replacement Therapy; Female; Heart Failure; Humans; Incidence; Life Style; Middle Aged; Multivariate Analysis; Obesity; Osteoporosis, Postmenopausal; Proportional Hazards Models; Prospective Studies; Risk; Risk Factors; United States; Women's Health

Imputation of missing longitudinal data: a comparison of methods. - Engels, Jean Mundahl; Diehr, Paula (J Clin Epidemiol, 2003)
BACKGROUND AND OBJECTIVES: Missing information is inevitable in longitudinal studies, and can result in biased estimates and a loss of power. One approach to this problem is to impute the missing data to yield a more complete data set. Our goal was to compare the performance of 14 methods of imputing missing data on depression, weight, cognitive functioning, and self-rated health in a longitudinal cohort of older adults. METHODS: We identified situations where a person had a known value following one or more missing values, and treated the known value as a "missing value." This "missing value" was imputed using each method and compared to the observed value. Methods were compared on the root mean square error, mean absolute deviation, bias, and relative variance of the estimates. RESULTS: Most imputation methods were biased toward estimating the "missing value" as too healthy, and most estimates had a variance that was too low. Imputed values based on a person's values before and after the "missing value" were superior to other methods, followed by imputations based on a person's values before the "missing value." Imputations that used no information specific to the person, such as using the sample mean, had the worst performance. CONCLUSIONS: We conclude that, in longitudinal studies where the overall trend is for worse health over time and where missing data can be assumed to be primarily related to worse health, missing data in a longitudinal sequence should be imputed from the available longitudinal data for that person.
Keywords: Aged; Analysis of Variance; Bias; Coronary Disease; Data Interpretation, Statistical; Depression; Female; Health Status; Humans; Longitudinal Studies; Male; Research Design; Risk Factors; Stroke; United States

Inflammation as a risk factor for atrial fibrillation. - Aviles, Ronnier J; Martin, David O; Apperson-Hansen, Carolyn; Houghtaling, Penny L; Rautaharju, Pentti; Kronmal, Richard A; Tracy, Russell P; Van Wagoner, David R; Psaty, Bruce M; Lauer, Michael S; Chung, Mina K (Circulation, 2003)
BACKGROUND: The presence of systemic inflammation determined by elevations in C-reactive protein (CRP) has been associated with persistence of atrial fibrillation (AF). The relationship between CRP and prediction of AF has not been studied in a large population-based cohort. METHODS AND RESULTS: CRP measurement and cardiovascular assessment were performed at baseline in 5806 subjects enrolled in the Cardiovascular Health Study. Patients were followed up for a mean of 6.9+/-1.6 (median 7.8) years. AF was identified by self-reported history and ECGs at baseline and by ECGs and hospital discharge diagnoses at follow-up. Univariate and multivariate analyses were used to assess CRP as a predictor of baseline and future development of AF. At baseline, 315 subjects (5%) had AF. Compared with subjects in the first CRP quartile (<0.97 mg/L), subjects in the fourth quartile (>3.41 mg/L) had more AF (7.4% versus 3.7%, adjusted OR 1.8, 95% CI 1.2 to 2.5; P=0.002). Of 5491 subjects without AF at baseline, 897 (16%) developed AF during follow-up. Baseline CRP predicted higher risk for developing future AF (fourth versus first quartile adjusted hazard ratio 1.31, 95% CI 1.08 to 1.58; P=0.005). When treated as a continuous variable, elevated CRP predicted increased risk for developing future AF (adjusted hazard ratio for 1-SD increase, 1.24; 95% CI 1.11 to 1.40; P<0.001). CONCLUSIONS: CRP is not only associated with the presence of AF but may also predict patients at increased risk for future development of AF.
Keywords: Aged; Atrial Fibrillation; C-Reactive Protein; Cross-Sectional Studies; Female; Humans; Inflammation; Longitudinal Studies; Male; Risk Factors

Lp(a) lipoprotein, vascular disease, and mortality in the elderly. - Ariyo, Abraham A; Thach, Chau; Tracy, Russell (N Engl J Med, 2003)
BACKGROUND: As compared with what is known about predictors of vascular events in middle-aged persons, less is known about these events in the elderly. Lp(a) lipoprotein, which plays an important part in atherothrombogenesis, has been associated with an increased risk of vascular disease. We investigated this relation among older U.S. adults. METHODS: In a prospective study of 5888 community-dwelling older adults (65 years of age or older) in the United States, 2375 women and 1597 men who were free of vascular disease provided base-line serum samples for analysis for levels of Lp(a) lipoprotein. These 3972 subjects were followed for a median of 7.4 years to evaluate the development of stroke and to track deaths from vascular causes and all causes. The men and women were divided into quintile groups according to the Lp(a) lipoprotein level at base line. RESULTS: Using Cox proportional-hazards models, we determined the risk associated with each quintile level of Lp(a) lipoprotein, with the lowest quintile serving as the reference group. As compared with those in the lowest quintile, men in the highest quintile had three times the unadjusted risk of stroke (relative risk, 3.00; 95 percent confidence interval, 1.59 to 5.65), almost three times the risk of death associated with vascular events (relative risk, 2.54; 95 percent confidence interval, 1.59 to 4.08), and nearly twice the risk of death from all causes (relative risk, 1.76; 95 percent confidence interval, 1.31 to 2.36). Adjustment for age; sex; the levels of total cholesterol, low-density lipoprotein cholesterol, and triglycerides; carotid-wall thickness; smoking status; the presence or absence of diabetes and systolic and diastolic hypertension; body-mass index; and other traditional risk factors had little effect on the final assessments. Similar analyses for women, which also included adjustment for estrogen use or nonuse, revealed no such relation. CONCLUSIONS: Among older adults in the United States, an elevated level of Lp(a) lipoprotein is an independent predictor of stroke, death from vascular disease, and death from any cause in men but not in women. These data support the use of Lp(a) lipoprotein levels in predicting the risk of these events in older men.
Keywords: Aged; Coronary Disease; Female; Humans; Incidence; Lipoprotein(a); Male; Mortality; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors; Stroke; Survival Analysis; United States; Vascular Diseases

Multiple imputation of baseline data in the cardiovascular health study. - Arnold, Alice M; Kronmal, Richard A (Am J Epidemiol, 2003)
Most epidemiologic studies will encounter missing covariate data. Software packages typically used for analyzing data delete any cases with a missing covariate to perform a complete case analysis. The deletion of cases complicates variable selection when different variables are missing on different cases, reduces power, and creates the potential for bias in the resulting estimates. Recently, software has become available for producing multiple imputations of missing data that account for the between-imputation variability. The implementation of the software to impute missing baseline data in the setting of the Cardiovascular Health Study, a large, observational study, is described. Results of exploratory analyses using the imputed data were largely consistent with results using only complete cases, even in a situation where one third of the cases were excluded from the complete case analysis. There were few differences in the exploratory results across three imputations, and the combined results from the multiple imputations were very similar to results from a single imputation. An increase in power was evident and variable selection simplified when using the imputed data sets.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Analysis of Variance; Cardiovascular Diseases; Cause of Death; Cohort Studies; Data Collection; Data Interpretation, Statistical; Epidemiologic Studies; Female; Humans; Linear Models; Male; Mathematical Computing; Models, Statistical; Predictive Value of Tests; Proportional Hazards Models; Risk Factors; Software; Survival Analysis; United States; Ventricular Remodeling

n-3 Polyunsaturated fatty acids, fatal ischemic heart disease, and nonfatal myocardial infarction in older adults: the Cardiovascular Health Study. - Lemaitre, Rozenn N; King, Irena B; Mozaffarian, Dariush; Kuller, Lewis H; Tracy, Russell P; Siscovick, David S (Am J Clin Nutr, 2003)
BACKGROUND: Little is known about the relation of the dietary intake of n-3 polyunsaturated fatty acids, ie, docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) from fatty fish and alpha-linolenic acid from vegetable oils, with ischemic heart disease among older adults. OBJECTIVE: We investigated the associations of plasma phospholipid concentrations of DHA, EPA, and alpha-linolenic acid as biomarkers of intake with the risk of incident fatal ischemic heart disease and incident nonfatal myocardial infarction in older adults. DESIGN: We conducted a case-control study nested in the Cardiovascular Health Study, a cohort study of adults aged > or = 65 y. Cases experienced incident fatal myocardial infarction and other ischemic heart disease death (n = 54) and incident nonfatal myocardial infarction (n = 125). Matched controls were randomly selected (n = 179). We measured plasma phospholipid concentrations of n-3 polyunsaturated fatty acids in blood samples drawn approximately 2 y before the event. RESULTS: A higher concentration of combined DHA and EPA was associated with a lower risk of fatal ischemic heart disease, and a higher concentration of alpha-linolenic acid with a tendency to lower risk, after adjustment for risk factors [odds ratio: 0.32 (95% CI: 0.13, 0.78; P = 0.01) and 0.52 (0.24, 1.15; P = 0.1), respectively]. In contrast, n-3 polyunsaturated fatty acids were not associated with nonfatal myocardial infarction. CONCLUSIONS: Higher combined dietary intake of DHA and EPA, and possibly alpha-linolenic acid, may lower the risk of fatal ischemic heart disease in older adults. The association of n-3 polyunsaturated fatty acids with fatal ischemic heart disease, but not with nonfatal myocardial infarction, is consistent with possible antiarrhythmic effects of these fatty acids.
Keywords: Aged; alpha-Linolenic Acid; Biomarkers; Case-Control Studies; Cohort Studies; Coronary Disease; Dietary Supplements; Docosahexaenoic Acids; Eicosapentaenoic Acid; Fatty Acids, Omega-3; Female; Fish Oils; Humans; Incidence; Male; Myocardial Infarction; Odds Ratio; Phospholipids; Prevalence; Prospective Studies; Risk Factors

The prevalence and risk factors of retinal microvascular abnormalities in older persons: The Cardiovascular Health Study. - Wong, Tien Yin; Klein, Ronald; Sharrett, A Richey; Manolio, Teri A; Hubbard, Larry D; Marino, Emily K; Kuller, Lewis; Burke, Gregory; Tracy, Russell P; Polak, Joseph F; Gottdiener, John S; Siscovick, David S (Ophthalmology, 2003)
PURPOSE: To describe the prevalence of retinal microvascular characteristics and their associations with atherosclerosis in elderly, nondiabetic persons. DESIGN AND PARTICIPANTS: Population-based, cross-sectional study comprising 2050 men and women aged 69 to 97 years without diabetes, living in four communities. METHODS: Participants underwent retinal photography and standardized grading of retinal microvascular characteristics, including retinopathy (e.g., microaneurysms, retinal hemorrhages), focal arteriolar narrowing, and arteriovenous nicking. In addition, calibers of retinal arterioles and venules were measured on digitized photographs to obtain an estimate of generalized arteriolar narrowing. Atherosclerosis and its risk factors were obtained from clinical examination and laboratory investigations. MAIN OUTCOME MEASURES: Prevalence of retinal microvascular abnormalities and their associations with measures of atherosclerosis. RESULTS: The prevalence of retinal microvascular abnormalities was 8.3% for retinopathy, 9.6% for focal arteriolar narrowing, and 7.7% for arteriovenous nicking. All retinal lesions were associated with hypertension (odds ratios [OR] were 1.8 for retinopathy, 2.1 for focal arteriolar narrowing, 1.5 for arteriovenous nicking, and 1.7 for generalized arteriolar narrowing). After controlling for age, gender, race, mean arterial blood pressure, and antihypertensive medication use, retinopathy was associated with prevalent coronary heart disease (OR, 1.7), prevalent myocardial infarction (OR, 1.7), prevalent stroke (OR, 2.0), presence of carotid artery plaque (OR, 1.9), and increased intima-media thickness of the common carotid (OR, 2.3; fourth vs. first quartile) and internal carotid (OR, 1.8; fourth vs. first quartile) arteries. In contrast, focal arteriolar narrowing, arteriovenous nicking, and generalized arteriolar narrowing were not associated with any measures of atherosclerosis. CONCLUSIONS: Retinal microvascular abnormalities are common in older persons without diabetes and are related to hypertension. Retinopathy is associated with prevalent coronary heart disease, stroke, and carotid artery thickening, but focal and generalized arteriolar narrowing and arteriovenous nicking are not related to most measures of atherosclerosis. These data suggest that retinal microvascular abnormalities reflect processes associated with hypertension but distinct from atherosclerosis.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Coronary Artery Disease; Cross-Sectional Studies; Female; Humans; Hypertension; Male; Prevalence; Retinal Diseases; Retinal Vessels; Risk Factors; United States

A prospective analysis of risk factors for white matter disease in the brain stem: the Cardiovascular Health Study. - Ding, Jingzhong; Nieto, F Javier; Beauchamp, Norman J; Longstreth, W T; Manolio, Teri A; Hetmanski, Jacqueline B; Fried, Linda P (Neuroepidemiology, 2003)
BACKGROUND AND PURPOSE: White matter disease (WMD) in the brain stem may be a predictor of poor clinical outcome, independent of WMD in the periventricular and subcortical areas of the brain. Many cardiovascular risk factors such as older age, hypertension, and smoking have been suggested as risk factors for WMD in the periventricular and subcortical areas of the brain. However, no epidemiologic study has examined the associations between cardiovascular risk factors and WMD in the brain stem. METHODS: A total of 789 participants, aged 65 years or older, from the Cardiovascular Health Study constituted the present study population. WMD, defined as hyperintensive lesions on magnetic resonance imaging (MRI), in the brain stem was measured in 1992/1993 and 1997/1998. RESULTS: Of the 789 participants, 212 (26.9%) had WMD in the brain stem in 1997/1998. In multivariate logistic regression analysis, the presence of WMD in the brain stem in 1997/1998 was significantly associated with several variables measured in 1992/1993: an increase by 5 years of age (OR = 1.51, 95% CI: 1.25-1.83), a 10-pack-years increase in smoking (OR = 1.12, 95% CI: 1.04-1.21), a 0.1-liter increase in first-second forced expiratory volume (OR = 0.95, 95% CI: 0.92-0.99), a 1 micromol/l increase in fibrinogen level (OR = 1.13, 95% CI: 1.03-1.23), and MRI infarction (OR = 2.58, 95% CI: 1.78-3.74). Excluding those (n = 167) with WMD in the brain stem in 1992/1993, the pattern remained. Hypertension was not associated with WMD in the brain stem. CONCLUSIONS: Increased age, smoking, lower forced expiratory volume, increased fibrinogen level, and MRI infarction, but not hypertension, may be independent risk factors for WMD in the brain stem in older adults.
Keywords: Age Factors; Aged; Brain Diseases; Brain Infarction; Brain Stem; Cardiovascular Diseases; Female; Fibrinogen; Forced Expiratory Volume; Humans; Magnetic Resonance Imaging; Male; Prospective Studies; Regression Analysis; Risk Factors; Smoking

Prospective study of fibrinolytic markers and venous thromboembolism. - Folsom, Aaron R; Cushman, Mary; Heckbert, Susan R; Rosamond, Wayne D; Aleksic, Nena (J Clin Epidemiol, 2003)
Prior research has conflicted on whether increased levels of plasma fibrinolytic factors may identify patients at risk of venous thromboembolism (VTE). We therefore performed a nested case-control study of VTE within two prospective population-based studies. In 308 participants who developed VTE and 640 controls, we measured PAI-1 antigen, tPA/PAI-1 complex, plasmin-alpha 2-antiplasmin (PAP), and the PAI-1 -675 4G/5G promoter polymorphism on pre-event blood samples. There was no overall association between any of these fibrinolytic variables and VTE, after adjustment for age or for multiple VTE risk factors. There was weak evidence for an interaction of PAP with elevated factor VIIIc and elevated D-dimer in augmenting VTE risk. We conclude that, for the most part, these fibrinolytic markers do not identify healthy subjects at risk for VTE.
Keywords: Aged; alpha-2-Antiplasmin; Antifibrinolytic Agents; Biomarkers; Caenorhabditis elegans Proteins; Case-Control Studies; Female; Fibrinolysin; Fibrinolysis; Humans; Male; Middle Aged; Odds Ratio; Plasminogen Activator Inhibitor 1; Prognosis; Prospective Studies; Protein-Tyrosine Kinases; Risk Factors; Thromboembolism; Venous Thrombosis

Prospective study of the A455V polymorphism in the thrombomodulin gene, plasma thrombomodulin, and incidence of venous thromboembolism: the LITE Study. - Aleksic, N; Folsom, A R; Cushman, M; Heckbert, S R; Tsai, M Y; Wu, K K (J Thromb Haemost, 2003)
Plasma thrombomodulin (soluble TM; sTM) is considered to be a marker of endothelial injury, but a recent report indicated that the relationship of sTM with thrombosis is complex. Venous thromboembolic events were identified in adults in two longitudinal cohort studies, the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study, totaling 21 690 participants. After 8 years of follow-up, sTM was measured in baseline plasma of 305 participants who developed venous thrombosis and 607 who did not. Thrombomodulin A455V genotype was determined in 302 cases and 626 controls. There was no difference in the prevalence of the three TM genotypes between cases and controls and no difference in age-adjusted mean values of sTM by genotype. There were no associations of age-adjusted sTM or TMA455V genotype with overall venous thromboembolism or with thrombosis in any subtype of venous thromboembolism.
Keywords: Age Factors; Aged; Amino Acid Substitution; Case-Control Studies; Female; Genotype; Humans; Incidence; Male; Polymorphism, Genetic; Prevalence; Prospective Studies; Risk Factors; Thromboembolism; Thrombomodulin; Venous Thrombosis

Risk factors for dementia in the cardiovascular health cognition study. - Kuller, Lewis H; Lopez, Oscar L; Newman, Anne; Beauchamp, Norman J; Burke, Greg; Dulberg, Corinne; Fitzpatrick, Annette; Fried, Linda; Haan, Mary N (Neuroepidemiology, 2003)
BACKGROUND: The Cardiovascular Health Cognition Study has evaluated the determinants of dementia among 3,608 participants that had a magnetic resonance imaging (MRI) of the brain in 1991 and were followed to 1998-1999. METHODS: There were 480 incident dementia cases, 330 (69%) were classified as Alzheimer's disease (AD). RESULTS: In univariate analysis, low scores on the Modified Mini-Mental State Examination (3MSE) and on the Digit Symbol Substitution Test as well as declines in scores over time prior to the development of dementia were significant predictors of dementia. A high ventricular grade on the MRI (atrophy) as well as high white matter grade, a number of brain infarcts on the MRI were all determinants of dementia. Apolipoprotein E epsilon4 (Apo(E-4)) was also a powerful predictor of dementia. In a multivariate Cox proportional hazards model controlling for race, gender and grade, the hazard ratios for age (1.1), 3MSE score (0.9), ventricular size (1.4), white matter grade (1.8), presence of large infarcts >3 mm (1.3) and Apo(E-4) (2.1) were significant predictors of dementia. The combination of an Apo(E-4) genotype, 3MSE score <90, > or =5 ventricular grade, > or =3 white matter grade at the time of the MRI were associated with a 17-fold increased risk (95% CI: 8.6-34.9) of dementia as compared to individuals with none of the above attributes. CONCLUSIONS: Measures of cognition, Apo(E-4) and MRI of the brain are strong predictors of both dementia and of AD.
Keywords: Aged; Aged, 80 and over; Apolipoproteins E; Cardiovascular Diseases; Cognition Disorders; Dementia; Female; Genotype; Humans; Magnetic Resonance Imaging; Male; Odds Ratio; Predictive Value of Tests; Proportional Hazards Models; Risk Factors

Risk factors for mild cognitive impairment in the Cardiovascular Health Study Cognition Study: part 2. - Lopez, Oscar L; Jagust, William J; Dulberg, Corinne; Becker, James T; DeKosky, Steven T; Fitzpatrick, Annette; Breitner, John; Lyketsos, Constantine; Jones, Beverly; Kawas, Claudia; Carlson, Michelle; Kuller, Lewis H (Arch Neurol, 2003)
OBJECTIVE: To examine the risk factors for mild cognitive impairment (MCI) in a longitudinal population study-the Cardiovascular Health Study Cognition Study. DESIGN: We examined the factors that in the period 1991 through 1994 predicted the development of MCI in all participants of the Cardiovascular Health Study Cognition Study. Further examination was conducted in the Pittsburgh, Pa, cohort (n = 927), where participants with MCI were classified as having either the MCI amnestic-type or the MCI multiple cognitive deficits-type. SETTING: Multicenter population study. PATIENTS: This study includes all participants of the Cardiovascular Health Study Cognition Study (n = 3608) who had a magnetic resonance imaging (MRI) scan of the brain between 1991 and 1994, and detailed neuropsychological, neurological, and medical evaluations to identify the presence of MCI or dementia in the period 1998 to 1999. The mean time between the closest clinical examination to the MRI and the diagnostic evaluation for cognitive disorders was 5.8 years for the Cardiovascular Health Study Cognition Study cohort and 6.0 years for the Pittsburgh cohort. MAIN OUTCOME MEASURES: Risk factors for MCI at the time of the MRI were identified using logistic regression, controlling for age, race, educational level, baseline Modified Mini-Mental State Examination and Digit Symbol Test scores, measurements of depression, MRI findings (atrophy, ventricular volume, white matter lesions, and infarcts), the presence of the apolipoprotein E (APOE) epsilon4 allele, hypertension, diabetes mellitus, and heart disease. RESULTS: Mild cognitive impairment (n = 577) was associated with race (African American), low educational level, low Modified Mini-Mental State Examination and Digit Symbol Test scores, cortical atrophy, MRI-identified infarcts, and measurements of depression. The MCI amnestic-type was associated with MRI-identified infarcts, the presence of the APOE epsilon4 allele, and low Modified Mini-Mental State Examination scores. The MCI multiple cognitive deficits-type was associated with low Modified Mini-Mental State Examination and Digit Symbol Test scores. CONCLUSIONS: The development of MCI is associated with measurements of cognition and depression, racial and constitutional factors, and cerebrovascular disease. Early cognitive deficits seem to be a common denominator for the 2 forms of MCI; the presence of cerebrovascular disease and the APOE epsilon4 allele is associated with the amnestic type of MCI.
Keywords: Aged; Apolipoprotein E4; Apolipoproteins E; Brain; Cardiovascular Diseases; Cognition Disorders; Cohort Studies; Depressive Disorder; Female; Humans; Logistic Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mood Disorders; Pennsylvania; Population; Risk Factors

Serum homocysteine, thermolabile variant of methylene tetrahydrofolate reductase (MTHFR), and venous thromboembolism: Longitudinal Investigation of Thromboembolism Etiology (LITE). - Tsai, Albert W; Cushman, Mary; Tsai, Michael Y; Heckbert, Susan R; Rosamond, Wayne D; Aleksic, Nena; Yanez, N David; Psaty, Bruce M; Folsom, Aaron R (Am J Hematol, 2003)
We sought to examine prospectively the association of serum homocysteine and the methylene tetrahydrofolate reductase (MTHFR) C677T gene polymorphism with risk of venous thromboembolism (VTE). We studied these relationships in a nested case-control study of 303 VTE cases and 635 matched controls from a population-based cohort of 21,680 adults from six U.S. communities. The highest quintile of serum homocysteine carried a non-statistically significant adjusted odds ratio of 1.55 (95% CI, 0.93-2.58) compared to the lowest quintile in the overall cohort but a significant association among adults aged 45-64 years (OR = 2.05, 95% CI, 1.10-3.83) and an inverse association in those > or = 65 years of age. Carriers of the MTHFR C677T polymorphism were not at higher risk for VTE than those with normal genotype (OR = 0.74, 95% CI = 0.56-0.98). Our prospective data showed, at most, a weak relationship between homocysteine and VTE risk, with associations larger among younger participants. MTHFR C677T was not a risk factor for VTE.
Keywords: Aged; Aging; Animals; Case-Control Studies; Cohort Studies; Factor V; Female; Genotype; Homocysteine; Humans; Longitudinal Studies; Male; Methylenetetrahydrofolate Reductase (NADPH2); Middle Aged; Odds Ratio; Oxidoreductases Acting on CH-NH Group Donors; Polymorphism, Genetic; Prospective Studies; Risk Factors; Venous Thrombosis

"Successful aging": effect of subclinical cardiovascular disease. - Newman, Anne B; Arnold, Alice M; Naydeck, Barbara L; Fried, Linda P; Burke, Gregory L; Enright, Paul; Gottdiener, John; Hirsch, Calvin; O'Leary, Daniel; Tracy, Russell (Arch Intern Med, 2003)
BACKGROUND: Cardiovascular diseases are the primary cause of death in older adults. Among those without clinical disease, high levels of subclinical disease are associated with poor survival. The effect of the extent of subclinical cardiovascular disease on the quality of the remaining years has not been defined. METHODS: In a longitudinal cohort study, 2932 men and women aged 65 years and older were followed up for 8 years to determine the likelihood of maintaining intact health and functioning. Successful aging was defined as remaining free of cardiovascular disease, cancer, and chronic obstructive pulmonary disease and with intact physical and cognitive functioning. RESULTS: Younger age at study entry and a lower extent of subclinical cardiovascular disease were independently associated with the likelihood of maintaining successful aging. In age-stratified summaries, those with subclinical disease had a trajectory of decline similar to subjects 5 years older without subclinical vascular disease. Regression analyses showed that the decline associated with subclinical disease was equivalent to 6.5 (95% confidence interval, 6.4-6.6) years of aging for women and 5.6 (95% confidence interval, 5.4-5.8) years of aging for men. Individual measures of the extent of cardiovascular disease, diabetes mellitus, smoking, and higher C-reactive protein level were also independently predictive of fewer years of successful aging, but none of these factors substantially attenuated the effect of age itself. CONCLUSIONS: There is a graded relationship between the extent of vascular disease measured noninvasively and the likelihood of maintaining intact health and function. Prevention of subclinical vascular disease may increase the quality and the quantity of years in late life.
Keywords: Aged; Aged, 80 and over; Aging; C-Reactive Protein; Cardiovascular Diseases; Female; Health Status; Humans; Longitudinal Studies; Male; Quality of Life; Regression Analysis; Risk Factors

Associates of bone mineral density in older African Americans. - Robbins, John; Hirsch, Calvin; Cauley, Jane (J Natl Med Assoc, 2004)
OBJECTIVES: To assess correlates of bone mineral density (BMD) in older African Americans. PARTICIPANTS: 189 women and 115 men over age 64. METHODS: Variables investigated: BMD by dual X-ray absorptiometry (DXA), medications, cardiovascular disease risk factors, demographic, lifestyle factors and functional status. Variables showing univariate correlation with BMD (p < or = 0.1) were entered into sex-stratified linear regression models. RESULTS: Age range 67-96 (mean 75). The mean BMD (gm/ cm2 +/- standard deviation) is reported for three sites. Total body: 1.03 (+/- 0.12) in women, 1.21 (+/- 0.11) in men. Spine: 1.05 (+/- 0.24) in women, 1.22 (+/- 0.26) in men. Total hip: 0.85 (+/- 0.15) in women, 1.04 (+/- 0.17) in men. Gender was significantly associated with BMD (t-test, p < 0.001). The R2 for tested variables were highly significant only for weight. Age was only significant for total hip in women (p < 0.05). Each kilogram of weight change was associated with a 5.3-6.8 mg/cm2 change in BMD. CONCLUSIONS: In a population-based cohort of older African Americans, average BMD was significantly greater in men than women. Weight accounted for most of the explained variability (R2) in BMD; age added little to the overall R2. Lower-weight, older African-American men and women are at significantly increased risk for low BMD and, thus, likely to be at greater risk for osteoporotic fracture.
Keywords: Aged; Body Weight; Bone Density; Cross-Sectional Studies; Female; Humans; Male; Osteoporosis; Risk Factors

The association between lipid levels and the risks of incident myocardial infarction, stroke, and total mortality: The Cardiovascular Health Study. - Psaty, Bruce M; Anderson, Melissa; Kronmal, Richard A; Tracy, Russell P; Orchard, Trevor; Fried, Linda P; Lumley, Thomas; Robbins, John; Burke, Greg; Newman, Anne B; Furberg, Curt D (J Am Geriatr Soc, 2004)
OBJECTIVES: To assess the association between lipid levels and cardiovascular events in older adults. DESIGN: A prospective population-based study. SETTING: Four field centers in U.S. communities. PARTICIPANTS: A total of 5,201 adults aged 65 and older living in U.S. communities, plus a recruitment of 687 African Americans 3 years later. MEASUREMENTS: Fasting lipid measures included low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol, and triglycerides. RESULTS: At baseline, 1,954 men and 2,931 women were at risk for an incident myocardial infarction (MI) or stroke. During an average 7.5-year follow-up, 436 subjects had a coronary event, 332 had an ischemic stroke, 104 a hemorrhagic stroke, and 1,096 died. After adjustment, lipid measures were not major predictors of the outcomes of MI, ischemic stroke, hemorrhagic stroke, and total mortality. For total cholesterol and LDL-C, the associations with MI and ischemic stroke were only marginally significant. HDL-C was inversely associated with MI risk (hazard ratio=0.85 per standard deviation of 15.7 mg/dL, 95% confidence interval=0.76-0.96). For the outcome of ischemic stroke, high levels of HDL-C were associated with a decreased risk in men but not women. Lipid measures were generally only weakly associated with the risks of hemorrhagic stroke or total mortality. CONCLUSION: In this population-based study of older adults, most lipid measures were weakly associated with cardiovascular events. The association between low HDL-C and increased MI risk was nonetheless strong and consistent.
Keywords: African Americans; African Continental Ancestry Group; Aged; Female; Health Surveys; Humans; Incidence; Lipids; Male; Mortality; Myocardial Infarction; Population Surveillance; Prospective Studies; Risk Factors; Stroke; United States

The association of fasting glucose levels with congestive heart failure in diabetic adults > or =65 years: the Cardiovascular Health Study. - Barzilay, Joshua I; Kronmal, Richard A; Gottdiener, John S; Smith, Nicholas L; Burke, Gregory L; Tracy, Russell; Savage, Peter J; Carlson, Michelle (J Am Coll Cardiol, 2004)
OBJECTIVES: The purpose of this study was to determine if fasting glucose levels are an independent risk factor for congestive heart failure (CHF) in elderly individuals with diabetes mellitus (DM) with or without coronary heart disease (CHD). BACKGROUND: Diabetes mellitus and CHF frequently coexist in the elderly. It is not clear whether fasting glucose levels in the setting of DM are a risk factor for incident CHF in the elderly. METHODS: A cohort of 829 diabetic participants, age > or =65 years, without prevalent CHF, was followed for five to eight years. The Cox proportional hazards modeling was used to determine the risk of CHF by fasting glucose levels. The cohort was categorized by the presence or absence of prevalent CHD. RESULTS: For a 1 standard deviation (60.6 mg/dl) increase in fasting glucose, the adjusted hazard ratios for incident CHF among participants without CHD at baseline, with or without an incident myocardial infarction (MI) or CHD event on follow-up, was 1.41 (95% confidence interval 1.24 to 1.61; p < 0.0001). Among those with prevalent CHD at baseline, with or without another incident MI or CHD event on follow-up, the corresponding adjusted hazard ratio was 1.27 (95% confidence interval 1.02 to 1.58; p < 0.05). CONCLUSIONS: Among older adults with DM, elevated fasting glucose levels are a risk factor for incident CHF. The relationship of fasting glucose to CHF differs somewhat by the presence or absence of prevalent CHD.
Keywords: Aged; Biomarkers; Blood Glucose; Blood Pressure; Coronary Disease; Diabetes Mellitus; Diabetic Angiopathies; Fasting; Female; Follow-Up Studies; Heart Failure; Humans; Incidence; Male; Proportional Hazards Models; Risk Factors; Statistics as Topic; Stroke Volume; Ventricular Function, Left

The association of personal and neighborhood socioeconomic indicators with subclinical cardiovascular disease in an elderly cohort. The cardiovascular health study. - Nordstrom, Cheryl K; Diez Roux, Ana V; Jackson, Sharon A; Gardin, Julius M (Soc Sci Med, 2004)
There has been recent interest in determining whether neighborhood characteristics are related to the cardiovascular health of residents. However, there are no data regarding the relationship between neighborhood socioeconomic status (SES) and prevalence of subclinical cardiovascular disease (CVD) in the elderly. We related personal SES (education, income, and occupation type) and neighborhood socioeconomic characteristics (a block-group score summing six variables reflecting neighborhood income and wealth, education, and occupation) to the prevalence of subclinical CVD (asymptomatic peripheral vascular disease or carotid atherosclerosis, electrocardiogram or echocardiogram abnormalities, and/or positive responses to Rose Questionnaire claudication or angina pectoris) among 3545 persons aged 65 and over, without prevalent CVD, in the Cardiovascular Health Study. Sixty percent of participants had at least one indicator of subclinical disease. Compared to those without, those with subclinical disease had significantly lower education, income, and neighborhood scores and were more likely to have blue-collar jobs. After adjustment for age, gender, and race, those in the lowest SES groups had increased prevalence of subclinical disease compared with those in the highest SES groups (OR = 1.50; 95% CI 1.21, 1.86 for income; OR = 1.41; 95% CI 1.18, 1.69 for education; OR = 1.39; 95% CI 1.16, 1.67 for block-group score). Those reporting a blue-collar lifetime occupation had greater prevalence of subclinical disease relative to those reporting a white-collar occupation (OR = 1.29; 95% CI 1.02-1.59). After adjustment for behavioral and biomedical risk factors, all of these associations were reduced. Neighborhood score tended to remain inversely associated with subclinical disease after adjustment for personal socioeconomic indicators but associations were not statistically significant. Personal income and blue-collar occupation remained significantly associated with subclinical disease after simultaneous adjustment for neighborhood score and education. Personal and neighborhood socioeconomic indicators were associated with subclinical disease prevalence in this elderly cohort. These relationships were reduced after controlling for traditional CVD risk factors.
Keywords: Aged; California; Cardiovascular Diseases; Cohort Studies; Female; Geography; Humans; Male; Maryland; Medicare; North Carolina; Pennsylvania; Residence Characteristics; Risk Factors; Social Class; Socioeconomic Factors; Surveys and Questionnaires

The Cardiovascular Health Study: a national treasure of cardiovascular information about the elderly. - Wenger, Nanette K; Weber, Michael A; Scheidt, Stephen (Am J Geriatr Cardiol, 2004)
Keywords: Aged; Cardiovascular Diseases; Geriatric Assessment; Humans; Risk Factors

The Cardiovascular Health Study: risk factors, subclinical disease, and clinical cardiovascular disease in older adults. - Newman, Anne B; Siscovick, David (Am J Geriatr Cardiol, 2004)
Keywords: Aged; Cardiovascular Diseases; Female; Geriatric Assessment; Humans; Male; Risk Factors

Chronic renal insufficiency and cardiovascular events in the elderly: findings from the Cardiovascular Health Study. - Shlipak, Michael G; Fried, Linda F; Stehman-Breen, Catherine; Siscovick, David; Newman, Anne B (Am J Geriatr Cardiol, 2004)
In the Cardiovascular Health Study, the authors sought to evaluate the impact of chronic renal insufficiency (CRI) on cardiovascular risk status and outcomes in a representative sample of community-dwelling elderly adults. Defined as a serum creatinine level > or =1.3 mg/dL in women and > or =1.5 mg/dL in men, CRI was present in 647 (11%) of 5808 participants. At baseline, the prevalence of clinical or subclinical cardiovascular disease was 64% in participants with CRI and 43% in those without CRI (odds ratio, 2.34; 95% confidence interval, 1.96-2.80). The incidence of cardiovascular disease events during follow-up was 3% per year in participants with creatinine levels <1.10 mg/dL and increased steadily to reach 7% per year in those with creatinine > or =1.70 mg/dL. Among the possible mediators for the association between CRI and cardiovascular morbidity are inflammatory (C-reactive protein, fibrinogen, and interleukin-6) and hemostatic (factor VII, factor VIII, plasmin-antiplasmin product, and D-dimer) biomarkers, all of which were significantly elevated in Cardiovascular Health Study participants with CRI. Future studies should evaluate the contribution of novel and traditional cardiovascular risk factors to the cardiovascular risk of elderly persons with CRI. The identification of CRI in the elderly and the use of cardiovascular prevention therapies represent a major opportunity to reduce their burden of cardiovascular morbidity.
Keywords: Aged; Blood Coagulation Factors; Cardiovascular Diseases; Chronic Disease; Creatinine; Cystatin C; Cystatins; Female; Fibrinogen; Geriatric Assessment; Humans; Incidence; Male; Prevalence; Renal Insufficiency; Risk Factors

Cognitive impairment and decline are associated with carotid artery disease in patients without clinically evident cerebrovascular disease. - Johnston, S Claiborne; O'Meara, Ellen S; Manolio, Teri A; Lefkowitz, David; O'Leary, Daniel H; Goldstein, Steven; Carlson, Michelle C; Fried, Linda P; Longstreth, W T (Ann Intern Med, 2004)
BACKGROUND: Whether carotid artery disease is a cause of cognitive impairment in persons who have not had stroke is unknown. If this is the case, diminished performance on the Modified Mini-Mental State Examination should be more common in persons with left carotid artery disease than in those with right carotid artery disease. OBJECTIVE: To determine whether left carotid artery disease is associated with cognitive impairment. DESIGN: Cross-sectional and cohort study. SETTING: Four U.S. communities participating in the Cardiovascular Health Study. PATIENTS: 4006 right-handed men and women 65 years of age or older without history of stroke, transient ischemic attack, or carotid endarterectomy. MEASUREMENTS: Internal carotid artery stenosis and intima-media thickness of the common carotid artery were assessed by using duplex ultrasonography. Cognitive impairment was defined as a score less than 80 on the Modified Mini-Mental State Examination, and cognitive decline was defined as an average decrease of more than 1 point annually in Modified Mini-Mental State Examination score during up to 5 years of follow-up. Multivariate logistic regression models were used to estimate the risk for cognitive impairment and decline associated with left internal carotid artery stenosis and intima-media thickness, after adjustment for measures of right-sided disease and risk factors for vascular disease. RESULTS: After adjustment for right-sided stenosis, high-grade (> or =75% narrowing of diameter) stenosis of the left internal carotid artery (32 patients) was associated with cognitive impairment (odds ratio, 6.7 [95% CI, 2.4 to 18.1] compared with no stenosis) and cognitive decline (odds ratio, 2.6 [CI, 1.1 to 6.3]). Intima-media thickness of the left common carotid artery was associated with cognitive impairment and decline in univariate analysis, but this effect did not persist after adjustment. CONCLUSIONS: Cognitive impairment and decline are associated with asymptomatic high-grade stenosis of the left internal carotid artery. The persistence of the association after adjustment for right-sided stenosis indicates that the association is not due to underlying vascular risk factors or atherosclerosis in general.
Keywords: Aged; Carotid Stenosis; Cognition Disorders; Cohort Studies; Cross-Sectional Studies; Female; Humans; Male; Neuropsychological Tests; Odds Ratio; Risk Factors; Tunica Intima

Congestive heart failure in the elderly: the Cardiovascular Health Study. - Mathew, Sunil T; Gottdiener, John S; Kitzman, Dalane; Aurigemma, Gerard (Am J Geriatr Cardiol, 2004)
Congestive heart failure in the elderly is recognized as a national public health priority; however, clinical diagnosis can be problematic in elderly persons, many of whom have a history of heart failure in the presence of normal or only minimally decreased ejection fraction. Findings of the Cardiovascular Health Study have underscored the common substrate and predictors underlying heart failure both with decreased ejection fraction and with normal ejection fraction (i.e., diastolic heart failure). Coronary heart disease, systolic blood pressure, and C-reactive protein (a measure of inflammation) are predictive of heart failure independent of ejection fraction. Left atrial size, arguably a marker of the effects of impaired diastolic filling over time, is increased in both systolic and diastolic heart failure of the elderly, as is atrial natriuretic peptide. The outcome of heart failure in elderly persons is poor both for systolic and diastolic heart failure. Moreover, many community-dwelling elderly persons have decreased ejection fraction without heart failure. In these persons the chance of death is similar to that of participants with diastolic heart failure. Since most clinical trials have studied younger patients with predominantly systolic heart failure, the appropriate therapy for heart failure in elderly persons remains to be determined.
Keywords: Aged; Aged, 80 and over; Atrial Natriuretic Factor; Blood Pressure; Diagnosis, Differential; Female; Geriatric Assessment; Heart Atria; Heart Failure; Heart Rate; Humans; Incidence; Male; Prevalence; Risk Factors; Stroke Volume; United States; Ventricular Dysfunction, Left

Deep vein thrombosis and pulmonary embolism in two cohorts: the longitudinal investigation of thromboembolism etiology. - Cushman, Mary; Tsai, Albert W; White, Richard H; Heckbert, Susan R; Rosamond, Wayne D; Enright, Paul; Folsom, Aaron R (Am J Med, 2004)
PURPOSE: To determine the incidence of deep vein thrombosis and pulmonary embolism in two cohorts representing regions of the United States. METHODS: The sample comprised 21,680 participants of the Atherosclerosis Risk in Communities study and the Cardiovascular Health Study. Subjects were aged >/=45 years, resided in six communities, and were followed for 7.6 years. All hospitalizations were identified and thromboses were validated by chart review. RESULTS: The age-standardized incidence of first-time venous thromboembolism was 1.92 per 1000 person-years. Rates were higher in men than women, and increased with age in both sexes. There was no antecedent trauma, surgery, immobilization, or diagnosis of cancer for 48% (175/366) of events. The 28-day case-fatality rate was 11% (29/265) after a first venous thromboembolism and 25% (17/67) for cancer-associated thrombosis. The recurrence rate 2 years after a first venous thromboembolism was 7.7% per year (95% confidence interval [CI]: 4.5% to 10.9% per year). Cancer was the only factor independently associated with 28-day fatality (relative risk [RR] = 5.2; 95% CI: 1.4 to 19.9) or recurrent thrombosis (RR = 9.2; 95% CI: 2.0 to 41.7). CONCLUSION: The incidence of venous thromboembolism in this cohort of middle- and older-aged subjects was similar to that observed in more geographically homogeneous samples. Half of cases were idiopathic. Short-term mortality and 2-year recurrence rates were appreciable, especially among subjects with cancer. Based on this study we estimate that 187,000 cases of first-time venous thromboembolism are diagnosed yearly in the United States among those aged 45 years or older.
Keywords: Aged; Case-Control Studies; Cohort Studies; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Neoplasms; Population Surveillance; Pulmonary Embolism; Recurrence; Risk Factors; Survival Rate; Venous Thrombosis

Incidence and prevalence of dementia in the Cardiovascular Health Study. - Fitzpatrick, Annette L; Kuller, Lewis H; Ives, Diane G; Lopez, Oscar L; Jagust, William; Breitner, John C S; Jones, Beverly; Lyketsos, Constantine; Dulberg, Corinne (J Am Geriatr Soc, 2004)
OBJECTIVES: To estimate the incidence and prevalence of dementia, Alzheimer's disease (AD), and vascular dementia (VaD) in the Cardiovascular Health Study (CHS) cohort. DESIGN: Longitudinal cohort study using prospectively and retrospectively collected data to evaluate dementia. SETTING: Four U.S. communities. PARTICIPANTS: There were 3,602 CHS participants, including 2,865 white and 492 African-American participants free of dementia, who completed a cranial magnetic resonance image between 1992 and 1994 and were followed for an average of 5.4 years. MEASUREMENTS: Dementia was classified by neurologist/psychiatrist committee review using neuropsychological tests, neurological examinations, medical records, physician questionnaires, and proxy/informant interviews. Demographics and apolipoprotein E (APOE) genotype were collected at baseline. Incidence by type of dementia was determined using National Institute of Neurological and Communicative Disorders and Stroke-Alzheimer's Disease and Related Disorders Association criteria for AD and Alzheimer's Disease Diagnostic and Treatment Center's State of California criteria for VaD. RESULTS: Classification resulted in 227 persons with prevalent dementia at entry into the study and 480 incident cases during follow-up. Incidence rates of dementia scaled to age 80 were 34.7 per 1,000 person-years for white women, 35.3 for white men, 58.8 for African-American women, and 53.0 for African-American men. Sex differences were not significant within race. Adjusted for age and education, racial differences were only of borderline significance and may have been influenced by ascertainment methodology. Rates differed substantially by educational attainment but were only significant for whites. Those with the APOE epsilon4 allele had an incidence rate at age 80 of 56.4, compared with 29.6 for those without this allele (P<.001). In whites, type-specific incidence at age 80 was 19.2 for AD versus 14.6 for VaD. These rates were 34.7 and 27.2 for African Americans. At termination of observation, women had only a slightly higher prevalence of dementia (16.0%) than men (14.7%). CONCLUSION: Sex and racial differences were not found, and VaD was higher than reported in other studies. These data provide new estimates of dementia incidence in a community sample for projection of future burden.
Keywords: African Americans; Age Distribution; Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Dementia; Dementia, Vascular; Education; European Continental Ancestry Group; Female; Humans; Incidence; Longitudinal Studies; Male; Prevalence; Proportional Hazards Models; Risk Factors; Sex Distribution; United States

Increased left ventricular mass is a risk factor for the development of a depressed left ventricular ejection fraction within five years: the Cardiovascular Health Study. - Drazner, Mark H; Rame, J Eduardo; Marino, Emily K; Gottdiener, John S; Kitzman, Dalane W; Gardin, Julius M; Manolio, Teri A; Dries, Daniel L; Siscovick, David S (J Am Coll Cardiol, 2004)
OBJECTIVES: Our aim in this study was to determine whether increased left ventricular mass (LVM) is a risk factor for the development of a reduced left ventricular ejection fraction (LVEF). BACKGROUND: Prior studies have shown that increased LVM is a risk factor for heart failure but not whether it is a risk factor for a low LVEF. METHODS: As part of the Cardiovascular Health Study, a prospective population-based longitudinal study, we performed echocardiograms upon participant enrollment and again at follow-up of 4.9 +/- 0.14 years. In the present analysis, we identified 3,042 participants who had at baseline a normal LVEF and an assessment of LVM (either by electrocardiogram or echocardiogram), and at follow-up a measurable LVEF. The frequency of the development of a qualitatively depressed LVEF on two-dimensional echocardiography, corresponding approximately to an LVEF <55%, was analyzed by quartiles of baseline LVM. Multivariable regression determined whether LVM was independently associated with the development of depressed LVEF. RESULTS: Baseline quartile of echocardiographic LVM indexed to body surface area was associated with development of a depressed LVEF (4.8% in quartile 1, 4.4% in quartile 2, 7.5% in quartile 3, and 14.1% in quartile 4 [p < 0.001]). A similar relationship was seen in the subgroup of participants without myocardial infarction (p < 0.001). In multivariable regression that adjusted for confounders, both baseline echocardiographic (p < 0.001) and electrocardiographic (p < 0.001) LVM remained associated with development of depressed LVEF. CONCLUSIONS: Increased LVM as assessed by electrocardiography or echocardiography is an independent risk factor for the development of depressed LVEF.
Keywords: Aged; Body Surface Area; Coronary Artery Disease; Diastole; Echocardiography; Electrocardiography; Female; Follow-Up Studies; Heart Ventricles; Humans; Hypertrophy, Left Ventricular; Longitudinal Studies; Male; Multivariate Analysis; Prospective Studies; Risk Factors; Sensitivity and Specificity; Statistics as Topic; Stroke Volume; Ventricular Dysfunction, Left

Lifestyles of older adults: can we influence cardiovascular risk in older adults? - Mozaffarian, Dariush; Fried, Linda P; Burke, Gregory L; Fitzpatrick, Annette; Siscovick, David S (Am J Geriatr Cardiol, 2004)
Influences of lifestyle habits on cardiovascular disease risk among older adults are not well established. The authors present evidence from the Cardiovascular Health Study that dietary, physical activity, and smoking habits assessed late in life are associated with cardiovascular disease risk among adults aged 65 years or older. Persons consuming fatty fish twice per week had a 47% lower risk of coronary death compared with those who consumed fatty fish less than once per month, while cereal fiber intake (about two whole-grain bread slices per day) was associated with a 14% lower risk of myocardial infarction or stroke. Modest alcohol intake (1-6 drinks per week) predicted the fewest subclinical cerebrovascular abnormalities. Compared with little activity, moderate and high leisure-time activity predicted 28% and 44% lower mortality, respectively, while compared with nonexercisers, low, moderate, and high exercise intensity predicted 30%, 37%, and 53% more years of healthy life, respectively. Former and current smokers had 25% and 44% fewer years of healthy life than those who never smoked; lifetime smoking (pack-years) predicted higher mortality. Clinical practice and public health implications, gaps in knowledge, and future research directions are summarized.
Keywords: Aged; Alcohol Drinking; Cardiovascular Diseases; Diet Fads; Dietary Fiber; Exercise; Feeding Behavior; Humans; Life Style; Predictive Value of Tests; Risk Factors; Smoking

Medications and cardiovascular health in older adults: room for improvement in prevention and treatment. - Rhoads, Caroline S; Psaty, Bruce M; Olson, Jean L; Furberg, Curt D (Am J Geriatr Cardiol, 2004)
Keywords: Aged; Antihypertensive Agents; Atrial Fibrillation; Cardiovascular Diseases; Diabetes Mellitus; Health Knowledge, Attitudes, Practice; Heart Failure; Humans; Hyperlipidemias; Hypertension; Hypolipidemic Agents; Risk Factors

Neighbourhood environments and mortality in an elderly cohort: results from the cardiovascular health study. - Diez Roux, Ana V; Borrell, Luisa N; Haan, Mary; Jackson, Sharon A; Schultz, Richard (J Epidemiol Community Health, 2004)
BACKGROUND: It has been postulated that neighbourhood conditions are related to the health of the elderly population but longitudinal studies are rare and confounding by individual level variables remains a possibility. METHODS: Data were obtained from the cardiovascular health study, a population based study of adults aged 65 years and older. Census block groups were used as proxies for neighbourhoods. A summary score was used to characterise the neighbourhood socioeconomic environment. Information on personal socioeconomic indicators, cardiovascular disease prevalence, and cardiovascular risk factors was obtained from the baseline examination. Proportional hazards regression and propensity score matching were used to control for individual level variables. RESULTS: Over the eight year follow up there were 1346 deaths among the 5074 participants, of which 43% were attributable to cardiovascular disease. Among white participants, living in the most disadvantaged neighbourhood group was associated with higher rates of cardiovascular death, after adjustment for income, education, and occupation (hazard ratio (HR) 1.5, 95% confidence intervals (CI) 1.2 to 1.9). No neighbourhood differences were observed for non-cardiovascular deaths. Estimates for black participants were 1.3 (95% CI 0.7 to 2.3) for cardiovascular deaths and 1.4 (95% CI 0.8 to 2.4) for non-cardiovascular deaths, but sample size was small. In white participants, associations of neighbourhood characteristics with cardiovascular mortality persisted after adjustment for prevalent baseline disease and cardiovascular risk factors. The use of propensity score matching led to similar results (HR for the lowest compared with the highest neighbourhood score group: 1.6 95% CI 1.1 to 2.5, controlling for personal socioeconomic indicators). CONCLUSION: Neighbourhood disadvantage is related to rates of cardiovascular death in elderly white adults.
Keywords: African Americans; Aged; Cardiovascular Diseases; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Income; Male; Poverty Areas; Residence Characteristics; Risk Factors; Socioeconomic Factors; United States

Plasma total homocysteine levels and cranial magnetic resonance imaging findings in elderly persons: the Cardiovascular Health Study. - Longstreth, W T; Katz, Ronit; Olson, Jean; Bernick, Charles; Carr, J Jeffrey; Malinow, M René; Hess, David L; Cushman, Mary; Schwartz, Stephen M (Arch Neurol, 2004)
BACKGROUND: An elevated plasma total homocysteine (tHcy) level is associated with an increased risk of vascular disease. Some studies have shown associations between tHcy level and small-vessel disease of the brain on magnetic resonance imaging (MRI). DESIGN: In the Cardiovascular Health Study, 622 elderly participants without a history of transient ischemic attack or stroke had results for tHcy level and cranial MRI. We sought associations between tHcy level and MRI findings of ventricular grade, sulcal grade, white matter grade, and infarcts. We controlled for other factors, including levels of creatinine, folate, and vitamins B(6) and B(12) and methylenetetrahydrofolate reductase genotype. RESULTS: After controlling for age and sex, tHcy level was not associated with the individual MRI findings. Further adjustments for other factors and other blood tests had little effect on these findings. The only significant finding was a linear trend across quintiles of tHcy level and a pattern of MRI findings combining infarcts and high white matter grade. The linear trend remained significant after controlling for other risk factors and atherosclerotic markers (top quintile vs bottom quintile odds ratio, 3.3; 95% confidence interval, 0.96-11.20; P =.04 for linear trend) but was slightly diminished after further controlling for creatinine, folate, and vitamins B(6) and B(12) (odds ratio, 3.2; 95% confidence interval, 0.81-13.10; P =.07 for linear trend). CONCLUSION: We were unable to confirm the results of previous studies with respect to tHcy level and individual MRI findings, although an association was seen for an MRI pattern combining infarcts and high white matter grade.
Keywords: Aged; Aging; Brain; Brain Infarction; Female; Homocysteine; Humans; Magnetic Resonance Imaging; Male; Odds Ratio; Radiography; Risk Factors

Predictors of falling cholesterol levels in older adults: the Cardiovascular Health Study. - Manolio, Teri A; Cushman, Mary; Gottdiener, John S; Dobs, Adrian; Kuller, Lewis H; Kronmal, Richard A (Ann Epidemiol, 2004)
PURPOSE: To estimate 4-year change in serum total cholesterol levels in a population-based sample of older adults and identify independent predictors of cholesterol decline. METHODS: Prospective study of 2837 adults aged 65 years and older with serum cholesterol measured in 1992-1993 and 1996-1997. RESULTS: Mean serum cholesterol levels declined 6.3 mg/dl between the two examinations. Declines were greater in white (-7.3 mg/dl) than black (-1.4 mg/dl) participants and in those in good/excellent health (-0.9 mg/dl) vs. fair/poor health (-3.1 mg/dl; both p < 0.01). Factors associated with greater decline on multivariate analysis included age, male gender, and higher white cell count, albumin, and baseline cholesterol. Cholesterol levels declined 2.0 mg/dl per 6 year increment in baseline age and 6.8 mg/dl more in men than women after adjustment for other factors. C-reactive protein levels were unrelated to cholesterol change. CONCLUSION: Declining cholesterol levels were associated with male gender, advanced age, weight loss, and white blood cell count but not with C-reactive protein levels. The role of declining cholesterol synthesis, due to as yet undefined age-related changes or to cytokine-mediated reductions related to illness, should be examined to help clarify the mechanisms of the sometimes marked declines in cholesterol levels observed at advanced ages.
Keywords: African Americans; Age Factors; Aged; Cardiovascular Diseases; Cholesterol; European Continental Ancestry Group; Female; Forecasting; Health Status; Humans; Male; Medicare; Prospective Studies; Risk Factors; Sex Distribution; Sex Factors; United States

Racial differences in endothelial function in postmenopausal women. - Loehr, Laura R; Espeland, Mark A; Sutton-Tyrrell, Kim; Burke, Gregory L; Crouse, John R; Herrington, David M (Am Heart J, 2004)
OBJECTIVE: Racial differences in cardiovascular mortality among women remain largely unexplained. Preliminary data suggest that African American and Caucasian differences in endothelial function may parallel differential cardiovascular disease (CVD) risk in women. To further study differences in endothelial function between African American and Caucasian women, we analyzed measures of brachial artery flow-mediated dilation (FMD) in women enrolled in the Cardiovascular Health Study (CHS). METHODS AND RESULTS: Brachial artery FMD was measured in the fasting state using established ultrasound techniques in 1330 Caucasian and 297 African American female participants in CHS (mean age 78.4 +/- 4.4 years). General linear models were used to compare FMD between African American and Caucasian women after adjusting for baseline brachial diameter, hypertension, diabetes, smoking, cholesterol, systolic blood pressure, body mass index, waist/hip ratio, age, education, income level; use of angiotensin-converting enzyme inhibitors, beta-blockers, nitroglycerin, estrogens and lipid-lowering drugs; and presence of clinical or subclinical disease. Adjusted absolute change and percent change in brachial artery diameter was significantly reduced in African American women compared with Caucasian women (P <.0001 and P =.0002, respectively). Similar results were found when the women were stratified by history of CVD (- CVD, P =.02; + CVD, P =.001) and CVD or subclinical vascular disease (- disease, P =.01, + disease, P =.03). CONCLUSIONS: In this cohort, brachial artery FMD was lower in African American women compared to Caucasian women, and this difference persisted after adjustment by multivariable analysis. The increased CVD risk in African American women may be related to impaired endothelial function. It remains to be determined whether African American women may uniquely benefit by interventions designed to improve endothelial health.
Keywords: African Continental Ancestry Group; Aged; Brachial Artery; Cohort Studies; Endothelium, Vascular; European Continental Ancestry Group; Female; Humans; Multivariate Analysis; Postmenopause; Risk Factors; Vasodilation

The relationship of cardiovascular risk factors to microalbuminuria in older adults with or without diabetes mellitus or hypertension: the cardiovascular health study. - Barzilay, Joshua I; Peterson, Do; Cushman, Mary; Heckbert, Susan R; Cao, Jie J; Blaum, Caroline; Tracy, Russell P; Klein, Ronald; Herrington, David M (Am J Kidney Dis, 2004)
BACKGROUND: Microalbuminuria is a risk factor for coronary heart disease (CHD). It occurs most commonly in the settings of diabetes and hypertension. The mechanisms by which it increases CHD risk are uncertain. METHODS: We examined the cross-sectional association of microalbuminuria with a broad range of CHD risk factors in 3 groups of adults aged 65 years or older with and without microalbuminuria: those with (1) no diabetes or hypertension (n = 1,098), (2) hypertension only (n = 1,450), and (3) diabetes with or without hypertension (n = 465). RESULTS: Three factors were related to microalbuminuria in all 3 groups: age, elevated systolic blood pressure, and markers of systemic inflammation. In patients with neither diabetes nor hypertension, increasing C-reactive protein levels were associated with microalbuminuria (odds ratio per 1-mg/L increase, 1.46; 95% confidence interval [CI], 1.15 to 1.84). Among those with diabetes, an increase in white blood cell (WBC) count was associated with microalbuminuria (odds ratio per 1,000-cell/mL increase, 2.57; 95% CI, 1.12 to 5.89). Among those with hypertension, an increase in WBC count (odds ratio per 1,000-cell/mL increase, 1.83; 95% CI, 1.04 to 3.23) and fibrinogen level (odds ratio per 10-mg/dL increase, 1.02; 95% CI, 1.00 to 1.05) were significantly associated with microalbuminuria. In all 3 groups, prevalent CHD was related to an elevated WBC count. In none of the 3 groups was brachial artery reactivity to ischemia, an in vivo marker of endothelial function, related to microalbuminuria. CONCLUSION: Microalbuminuria is associated with age, systolic blood pressure, and markers of inflammation. These associations reflect potential mechanisms by which microalbuminuria is related to CHD risk.
Keywords: Age Distribution; Aged; Aged, 80 and over; Albuminuria; Biomarkers; Brachial Artery; Comorbidity; Coronary Disease; Cross-Sectional Studies; Diabetes Mellitus; Female; Humans; Hypertension; Inflammation; Logistic Models; Male; Multivariate Analysis; Odds Ratio; Risk Factors; Smoking; Ultrasonography

The relationship of fasting serum radioimmune insulin levels to incident coronary heart disease in an insulin-treated diabetic cohort. - Kronmal, Richard A; Barzilay, Joshua I; Tracy, Russell P; Savage, Peter J; Orchard, Trevor J; Burke, Gregory L (J Clin Endocrinol Metab, 2004)
It is not known whether insulin levels, in the setting of insulin treatment, are an independent risk factor for coronary heart disease (CHD). We studied a cohort of 116 insulin-treated individuals, 65 yr or older, who were followed for 5.6-9 yr. All were free of CHD at baseline. There were 47 incident CHD events. In Cox proportional hazards modeling, with fasting immune-reactive insulin levels as a continuous variable, the hazard ratio for CHD was statistically significant (P < 0.0001). When insulin levels were divided into intervals, those in the third interval [43-150 microU/ml (258-900 pmol/liter)] had an adjusted 30% increased relative risk (95% confidence interval, 0.57, 2.98) compared with those in the first interval [<20 microU/ml (<120 pmol/liter)]. Those in the fourth interval [151-400 microU/ml (906-2400 pmol/liter)] had an adjusted 5.6-fold increased risk (2.3-13.1; P < 0.0001). Approximately 15% of the cohort had such elevated insulin levels. Immune-reactive insulin levels were strongly correlated with specific insulin, proinsulin, and insulin antibody levels. Markedly elevated fasting immune-reactive insulin levels were an independent risk factor for CHD in this study of insulin-treated older adults. These observational findings should be confirmed through larger prospective studies, given their implications for insulin therapy.
Keywords: Aged; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 1; Fasting; Female; Follow-Up Studies; Humans; Hypoglycemic Agents; Incidence; Insulin; Male; Radioimmunoassay; Risk Factors

Respiratory muscle strength and the risk of incident cardiovascular events. - van der Palen, J; Rea, T D; Manolio, T A; Lumley, T; Newman, A B; Tracy, R P; Enright, P L; Psaty, B M (Thorax, 2004)
BACKGROUND: Maximal inspiratory pressure (MIP) is a measure of inspiratory muscle strength. The prognostic importance of MIP for cardiovascular events among elderly community dwelling individuals is unknown. Diminished forced vital capacity (FVC) is a risk factor for cardiovascular events which remains largely unexplained. METHODS: MIP was measured at the baseline examination of the Cardiovascular Health Study. Participants had to be free of prevalent congestive heart failure (CHF), myocardial infarction (MI), and stroke. RESULTS: Subjects in the lowest quintile of MIP had a 1.5-fold increased risk of MI (HR 1.48, 95% CI 1.07 to 2.06) and cardiovascular disease (CVD) death (HR 1.54, 95% CI 1.09 to 2.15) after adjustment for non-pulmonary function covariates. There was a potential inverse relationship with stroke (HR 1.36, 95% CI 0.97 to 1.90), but there was little evidence of an association between MIP and CHF (HR 1.22, 95% CI 0.93 to 1.60). The addition of FVC to models attenuated the HR associated with MIP only modestly; similarly, addition of MIP attenuated the HR associated with FVC only modestly. CONCLUSIONS: A reduced MIP is an independent risk factor for MI and CVD death, and a suggestion of an increased risk for stroke. This association with MIP appeared to be mediated through mechanisms other than inflammation.
Keywords: Cardiovascular Diseases; Female; Follow-Up Studies; Forced Expiratory Volume; Humans; Male; Maximal Voluntary Ventilation; Prospective Studies; Respiratory Muscles; Risk Factors; Vital Capacity

Risk of congestive heart failure in an elderly population treated with peripheral alpha-1 antagonists. - Bryson, Chris L; Smith, Nicholas L; Kuller, Lewis H; Chaves, Paulo H M; Manolio, Teri A; Lewis, William; Boyko, Edward J; Furberg, Curt D; Psaty, Bruce M (J Am Geriatr Soc, 2004)
OBJECTIVES: To compare the risk of congestive heart failure (CHF) in elderly individuals treated with any peripheral alpha-1 antagonist for hypertension with any thiazide, test whether the risk persists in subjects without cardiovascular disease (CVD) at baseline, and examine CHF risk in normotensive men with prostatism treated with alpha antagonists. DESIGN: Prospective cohort study. SETTING: Four U.S. sites: Washington County, Maryland; Allegheny County, Pennsylvania; Sacramento County, California; and Forsyth County, North Carolina. PARTICIPANTS: A total of 5,888 community-dwelling subjects aged 65 and older. MEASUREMENTS: Adjudicated incident CHF. RESULTS: The 3,105 participants with treated hypertension were at risk for CHF; 22% of men and 8% of women took alpha antagonists during follow-up. The age-adjusted risk of CHF in those receiving monotherapy treated with alpha antagonists was 1.90 (95% confidence interval=1.03-3.50) compared with thiazides. In subjects without CVD at baseline receiving monotherapy, women taking an alpha antagonist had a 3.6 times greater age-adjusted risk of CHF, whereas men had no difference in risk. Adjustment for systolic blood pressure attenuated statistical differences in risk. There were 930 men without hypertension at risk for CHF; 5% used alpha antagonists during follow-up, with no observed increase in CHF risk. CONCLUSION: Subjects receiving alpha antagonist monotherapy for hypertension had a two to three times greater risk of incident CHF, also seen in lower-risk subjects, but differences in blood pressure control partly explained this.
Keywords: Adrenergic alpha-Antagonists; Aged; Antihypertensive Agents; Benzothiadiazines; Blood Pressure; Cohort Studies; Diuretics; Female; Heart Failure; Humans; Hypertension; Male; Risk Factors; Sodium Chloride Symporter Inhibitors; United States

Self-reported alcohol consumption and falls in older adults: cross-sectional and longitudinal analyses of the cardiovascular health study. - Mukamal, Kenneth J; Mittleman, Murray A; Longstreth, W T; Newman, Anne B; Fried, Linda P; Siscovick, David S (J Am Geriatr Soc, 2004)
OBJECTIVES: To assess the cross-sectional and longitudinal associations between alcohol consumption and risk of falls in older adults. DESIGN: Cross-sectional and longitudinal analyses. SETTING: Four U.S. communities. PARTICIPANTS: A total of 5,841 older adults enrolled in the Cardiovascular Health Study, an ongoing, population-based, prospective cohort study, participated. MEASUREMENTS: Self-reported alcohol consumption at baseline, self-reported frequent falls at baseline, and the 4-year risk of falls of participants who denied frequent falls at baseline. RESULTS: Cross-sectional analysis indicated an apparent inverse association between alcohol consumption and risk of frequent falls (adjusted odds ratio in consumers of 14 or more drinks per week=0.41; 95% confidence interval (CI)=0.14-1.17; P for trend=.06), but longitudinal analysis indicated a similar 4-year risk of falls in abstainers and light to moderate drinkers but a 25% higher risk in consumers of 14 or more drinks per week (95% CI=3-52%; P for trend=.07). Similar results were found in analyses stratified by age, sex, race, and physical activity. CONCLUSION: Consumption of 14 or more drinks per week is associated with an increased risk of subsequent falls in older adults. Cross-sectional studies may fail to identify this risk of heavier drinking, perhaps because older adults at risk for falls decrease their alcohol use over time or because heavier drinkers at risk for falls tend not to enroll in cohort studies. However, because this study relied upon annual reporting of falls, further prospective studies should be conducted to confirm these findings.
Keywords: Accidental Falls; Aged; Alcohol Drinking; Chi-Square Distribution; Cross-Sectional Studies; Female; Humans; Longitudinal Studies; Male; Regression Analysis; Risk Factors; Self Disclosure; United States

Sleep-disordered breathing, glucose intolerance, and insulin resistance: the Sleep Heart Health Study. - Punjabi, Naresh M; Shahar, Eyal; Redline, Susan; Gottlieb, Daniel J; Givelber, Rachel; Resnick, Helaine E (Am J Epidemiol, 2004)
Clinic-based studies suggest that sleep-disordered breathing (SDB) is associated with glucose intolerance and insulin resistance. However, in the available studies, researchers have not rigorously controlled for confounding variables to assess the independent relation between SDB and impaired glucose metabolism. The objective of this study was to determine whether SDB was associated with glucose intolerance and insulin resistance among community-dwelling subjects (n=2,656) participating in the Sleep Heart Health Study (1994-1999). SDB was characterized with the respiratory disturbance index and measurements of oxygen saturation during sleep. Fasting and 2-hour glucose levels measured during an oral glucose tolerance test were used to assess glycemic status. Relative to subjects with a respiratory disturbance index of less than 5.0 events/hour (the reference category), subjects with mild SDB (5.0-14.9 events/hour) and moderate to severe SDB (> or =15 events/hour) had adjusted odds ratios of 1.27 (95% confidence interval: 0.98, 1.64) and 1.46 (95% confidence interval: 1.09, 1.97), respectively, for fasting glucose intolerance (p for trend < 0.01). Sleep-related hypoxemia was also associated with glucose intolerance independently of age, gender, body mass index, and waist circumference. The results of this study suggest that SDB is independently associated with glucose intolerance and insulin resistance and may lead to type 2 diabetes mellitus.
Keywords: Aged; Blood Gas Analysis; Body Constitution; Body Mass Index; Cohort Studies; Confounding Factors, Epidemiologic; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Fasting; Female; Glucose Intolerance; Glucose Tolerance Test; Humans; Insulin Resistance; Linear Models; Male; Middle Aged; Multivariate Analysis; Oxyhemoglobins; Polysomnography; Research Design; Risk Factors; Severity of Illness Index; Sleep Apnea Syndromes

Stroke risk factors and loss of high cognitive function. - Elkins, J S; O'Meara, E S; Longstreth, W T; Carlson, M C; Manolio, T A; Johnston, S C (Neurology, 2004)
BACKGROUND: Modifiable stroke risk factors may contribute to age-associated declines in cognitive function. Individuals with high levels of cognitive function after midlife may have less exposure to these stroke risk factors or may be less susceptible to their effects on cognition. METHODS: The Cardiovascular Health Study (CHS)* is a population-based, longitudinal cohort study of 5,888 people age 65 years and older. Participants (n = 4,129) who were free of dementia, stroke, or TIA at the time of baseline cranial MRI were selected for analysis. High cognitive function at baseline was defined by performance at or above midlife norms on the Modified Mini-Mental State Examination (3MS). RESULTS: The odds of having high cognitive function at baseline decreased by quartile of stroke risk (highest vs lowest risk quartile, adjusted odds ratio [OR] 0.68; 95% CI 0.52 to 0.88; p for trend = 0.005). Stroke risk was a predictor of decline on the 3MS in those with typical levels of cognitive function at baseline, even in the absence of incident stroke or TIA (highest vs lowest risk quartile for 3MS decline, adjusted OR 2.11; 95% CI 1.42 to 3.13; p for trend < 0.001). In contrast, stroke risk was not associated with decline on the 3MS in those with high cognitive function at baseline (p = 0.03 for interaction). CONCLUSIONS: In a cohort of older adults without stroke, TIA, or dementia, cognitive function and incident cognitive decline were associated with risk for stroke. Additional studies are needed to determine whether modification of stroke risk factors can reduce the cognitive decline that is often attributed to normal aging.
Keywords: Aged; Aged, 80 and over; Aging; Cognition Disorders; Cohort Studies; Comorbidity; Female; Follow-Up Studies; Higher Nervous Activity; Humans; Incidence; Male; Risk Assessment; Risk Factors; Sampling Studies; Sensitivity and Specificity; Severity of Illness Index; Stroke; United States

Subclinical cardiovascular disease in older adults: insights from the Cardiovascular Health Study. - Chaves, Paulo H M; Kuller, Lewis H; O'Leary, Daniel H; Manolio, Teri A; Newman, Anne B (Am J Geriatr Cardiol, 2004)
Knowledge about the epidemiology of subclinical cardiovascular disease (SCVD) in older adults may hold the key for improved opportunities for primary prevention of cardiovascular disease (CVD), a top clinical and public health priority. This review reports findings on the prevalence of SCVD and the ability of SCVD measures to predict incident and adverse outcomes from one of the largest (N=5888) and most comprehensive prospective observational studies on SCVD in older adults, the Cardiovascular Health Study. According to a composite index that combined SCVD measures from different vascular beds, the overall prevalence of SCVD was 37%, making it as common as clinically overt CVD in older adults. SCVD measures strongly predicted incident CVD, stroke, mortality, frailty, and physical and cognitive decline, even after adjustment for traditional CVD risk factors. Ongoing research will address the potential use of SCVD for clinical decision making in older adults.
Keywords: Aged; Cardiovascular Diseases; Coronary Artery Disease; Heart Failure; Humans; Longitudinal Studies; Prevalence; Risk Assessment; Risk Factors

Traditional and novel risk factors in older adults: cardiovascular risk assessment late in life. - Mukamal, Kenneth J; Kronmal, Richard A; Tracy, Russell P; Cushman, Mary; Siscovick, David S (Am J Geriatr Cardiol, 2004)
As a population-based, longitudinal study of nearly 6000 older American adults, the Cardiovascular Health Study provides an excellent opportunity to assess the roles of traditional and novel cardiovascular risk factors in the development of coronary heart disease. Cardiovascular Health Study investigators have analyzed both traditional risk factors, such as diabetes, hypertension, and smoking, and new risk factors, such as hemostatic factors, inflammatory markers, exposure to infectious agents, and genetic determinants. These analyses have led to several important conclusions. First, older adults without previous cardiovascular events have a tremendous burden of subclinical vascular disease, which may change how physicians view risk factor modification in this age group. Second, some traditional cardiovascular risk factors lose importance as predictors of cardiovascular disease among older adults. Third, even modest elevations in fasting blood glucose or systolic blood pressure-below the levels used to define diabetes or hypertension-may have prognostic implications. Fourth, novel cardiovascular risk factors may add further information about cardiovascular disease risk in older adults. Promising potential candidates identified in the Cardiovascular Health Study include markers of hemostatic activation, fibrinogen, factor VIII coagulant activity, C-reactive protein, and exposure to herpes simplex virus-1 and possibly chlamydia. Future Cardiovascular Health Study investigations will help to clarify which combination of traditional and newer risk factors provides the best estimate of cardiovascular risk for older adults.
Keywords: Aged; Blood Coagulation Factors; Cardiovascular Diseases; Cohort Studies; Diabetes Complications; Female; Genetic Predisposition to Disease; Humans; Hypertension; Infections; Inflammation; Lipids; Longitudinal Studies; Male; Obesity; Predictive Value of Tests; Risk Factors; Smoking; United States

White matter hyperintensity on cranial magnetic resonance imaging: a predictor of stroke. - Kuller, Lewis H; Longstreth, W T; Arnold, Alice M; Bernick, Charles; Bryan, R Nick; Beauchamp, Norman J (Stroke, 2004)
BACKGROUND AND PURPOSE: We have previously reported that several "silent" infarcts found on magnetic resonance imaging (MRI) were a risk factor for stroke. Several recent reports have shown that high white matter grade (WMG) and increasing WMG over time were risk factors for stroke. We tested the hypothesis that high WMG > or =2 was a predictor of risk for stroke, independent of other risk factors. METHODS: We examined the extent of white matter hyperintensity on cranial MRI of 3293 participants from the Cardiovascular Health Study (CHS). The degree of white matter hyperintensity was graded from least severe (grade=0) to most severe (grade=9). Participants were followed-up for an average of 7 years for the occurrence of a stroke. Clinical stroke diagnoses were based on hospital records reviewed by an adjudication committee expert in stroke diagnosis. During this period, 278 strokes occurred. Results The relative risk of stroke increased significantly as the WMG increased. The risk of stroke was 2.8% per year for participants with high WMG (grades > or =5), compared with only 0.6% for participants with grades 0 to 1.Conclusions The risk of stroke with high WMG is independent of traditional stroke risk factors and persists when controlling for MRI infarcts, another subclinical imaging marker of cerebrovascular disease. Assessment of white matter disease may be valuable in assessing future risk of stroke.
Keywords: Aged; Brain; Female; Humans; Leukoaraiosis; Magnetic Resonance Imaging; Male; Radiography; Risk Factors; Stroke

Age-dependent associations between sleep-disordered breathing and hypertension: importance of discriminating between systolic/diastolic hypertension and isolated systolic hypertension in the Sleep Heart Health Study. - Haas, Donald C; Foster, Gregory L; Nieto, F Javier; Redline, Susan; Resnick, Helaine E; Robbins, John A; Young, Terry; Pickering, Thomas G (Circulation, 2005)
BACKGROUND: Sleep-disordered breathing (SDB) is associated with hypertension in the middle-aged. The association is less clear in older persons. Most middle-aged hypertensives have systolic/diastolic hypertension, whereas isolated systolic hypertension (ISH) is common among persons over 60 years. Mechanistically, only systolic/diastolic hypertension is expected to be associated with SDB, but few studies of SDB and hypertension distinguish systolic/diastolic hypertension from ISH. Prior investigations may have underestimated an association between SDB and systolic/diastolic hypertension in the elderly by categorizing individuals with ISH as simply hypertensive. METHODS AND RESULTS: We conducted cross-sectional analyses of 6120 participants in the Sleep Heart Health Study, stratified by age: 40 to 59 (n=2477) and > or =60 years. Outcome measures included apnea-hypopnea index (AHI; average number of apneas plus hypopneas per hour of sleep), systolic/diastolic hypertension (> or =140 and > or =90 mm Hg), and ISH (> or =140 and <90 mm Hg). With adjustment for covariates, ISH was not associated with SDB in either age category. In those aged<60 years, AHI was significantly associated with higher odds of systolic/diastolic hypertension (AHI 15 to 29.9, OR=2.38 [95% CI 1.30 to 4.38]; AHI > or =30, OR=2.24 [95% CI 1.10 to 4.54]). Among those aged > or =60 years, no adjusted association between AHI and systolic/diastolic hypertension was found. CONCLUSIONS: SDB is associated with systolic/diastolic hypertension in those aged <60 years. No association was found between SDB and systolic/diastolic hypertension in those aged > or =60 years or between SDB and ISH in either age category. These findings have implications for SDB screening and treatment. Distinguishing between hypertensive subtypes reveals a stronger association between SDB and hypertension for those aged <60 years than previously reported.
Keywords: Adult; Age Factors; Aged; Antihypertensive Agents; Cross-Sectional Studies; Diastole; Female; Humans; Hypertension; Male; Middle Aged; Risk Factors; Sleep Apnea Syndromes; Sleep Apnea, Central; Systole

Alcohol use and risk of ischemic stroke among older adults: the cardiovascular health study. - Mukamal, Kenneth J; Chung, Hyoju; Jenny, Nancy S; Kuller, Lewis H; Longstreth, W T; Mittleman, Murray A; Burke, Gregory L; Cushman, Mary; Beauchamp, Norman J; Siscovick, David S (Stroke, 2005)
BACKGROUND AND PURPOSE: The association of light to moderate alcohol consumption with risk of ischemic stroke remains uncertain, as are the roles of potentially mediating factors and modification by apolipoprotein E (apoE) genotype. METHODS: We studied the prospective association of alcohol consumption and risk of ischemic stroke among 4410 participants free of cardiovascular disease at baseline in the Cardiovascular Health Study, a population-based cohort study of older adults from 4 US communities. Participants reported their consumption of alcoholic beverages yearly. RESULTS: During an average follow-up period of 9.2 years, 434 cases of incident ischemic stroke occurred. Compared with long-term abstainers, the multivariate relative risks of ischemic stroke were 0.85 (95% CI, 0.63 to 1.13), 0.75 (95% CI, 0.53 to 1.06), 0.82 (95% CI, 0.51 to 1.30), and 1.03 (95% CI, 0.68 to 1.57) among consumers of <1, 1 to 6, 7 to 13, and > or =14 drinks per week (P quadratic trend 0.06). ApoE genotype appeared to modify the alcohol-ischemic stroke relationship (P interaction 0.08), with generally lower risks among drinkers than abstainers in apoE4-negative participants but higher risks among drinkers than abstainers among apoE4-positive participants. We could not identify candidate mediators among lipid, inflammatory, and prothrombotic factors. CONCLUSIONS: In this study of older adults, the association of alcohol use and risk of ischemic stroke was U-shaped, with modestly lower risk among consumers of 1 to 6 drinks per week. However, apoE genotype may modify this association, and even moderate alcohol intake may be associated with an increased risk of ischemic stroke among apoE4-positive older adults.
Keywords: Aged; Alcohol Drinking; Apolipoproteins E; Brain Infarction; Brain Ischemia; Cohort Studies; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genotype; Humans; Hypertension; Inflammation; Ischemia; Lipids; Male; Middle Aged; Multivariate Analysis; Myocardial Infarction; Prospective Studies; Risk; Risk Factors; Stroke; Substance-Related Disorders; Thrombosis; Time Factors; Vascular Diseases

Association between screening for osteoporosis and the incidence of hip fracture. - Kern, Lisa M; Powe, Neil R; Levine, Michael A; Fitzpatrick, Annette L; Harris, Tamara B; Robbins, John; Fried, Linda P (Ann Intern Med, 2005)
BACKGROUND: Because direct evidence for the effectiveness of screening is lacking, guidelines disagree on whether people should be screened for osteoporosis. OBJECTIVE: To determine whether population-based screening for osteoporosis in older adults is associated with fewer incident hip fractures than usual medical care. DESIGN: Nonconcurrent cohort study. SETTING: Population-based cohort enrolled in the Cardiovascular Health Study (CHS) from 4 states (California, Pennsylvania, Maryland, and North Carolina). PATIENTS: 3107 adults 65 years of age and older who attended their CHS study visits in 1994-1995. MEASUREMENTS: 31 participant characteristics (including demographic characteristics, medical histories, medications, and physical examination findings) and incident hip fractures over 6 years of follow-up. INTERVENTION: Bone density scans (dual-energy x-ray absorptiometry [DEXA] at the hip) for participants in California and Pennsylvania (n = 1422) and usual care for participants in Maryland and North Carolina (n = 1685). RESULTS: The incidence of hip fractures per 1000 person-years was 4.8 in the screened group and 8.2 in the usual care group. Screening was associated with a statistically significant lower hazard of hip fracture than usual care after adjustment for sex and propensity to be screened (Cox proportional hazard ratio, 0.64 [95% CI, 0.41 to 0.99]). LIMITATIONS: The mechanism of the association was unclear. A small unmeasured confounder that decreased the hazard of hip fracture could diminish or erase the observed association. CONCLUSIONS: Use of hip DEXA scans to screen for osteoporosis in older adults was associated with 36% fewer incident hip fractures over 6 years compared with usual medical care. Further research is needed to explore the mechanism of this association.
Keywords: Absorptiometry, Photon; Aged; Aged, 80 and over; Cohort Studies; Female; Hip Fractures; Humans; Incidence; Male; Mass Screening; Osteoporosis; Risk Factors; Sensitivity and Specificity

Benefits of fatty fish on dementia risk are stronger for those without APOE epsilon4. - Huang, T L; Zandi, P P; Tucker, K L; Fitzpatrick, A L; Kuller, L H; Fried, L P; Burke, G L; Carlson, M C (Neurology, 2005)
OBJECTIVE: To compare associations of lean fish vs fatty fish (tuna or other fish) intake with dementia, Alzheimer disease (AD), and vascular dementia (VaD) and in relation to APOE epsilon4 status in the Cardiovascular Health Cognition Study (CHCS). METHODS: Fish intake was assessed by food frequency questionnaires. Incident dementia, AD, and VaD were determined through a series of cognitive tests, physician's assessment, and committee consensus. We used Cox proportional hazards regression to calculate hazard ratios of dementia, AD, and VaD with lean fried fish, fatty fish, or total fish intake, which were then stratified by the presence of APOE epsilon4. RESULTS: Although consumption of lean fried fish had no protective effect, consumption of fatty fish more than twice per week was associated with a reduction in risk of dementia by 28% (95% CI: 0.51 to 1.02), and AD by 41% (95% CI: 0.36 to 0.95) in comparison to those who ate fish less than once per month. Stratification by APOE epsilon4 showed this effect to be selective to those without the epsilon4 allele. Adjustment by education and income attenuated the effect. CONCLUSION: In the Cardiovascular Health Cognition Study, consumption of fatty fish was associated with a reduced risk of dementia and Alzheimer disease for those without the APOE epsilon4 allele.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Apolipoproteins E; Cohort Studies; Dementia; Dietary Fats, Unsaturated; Fatty Acids, Omega-3; Feeding Behavior; Female; Fish Oils; Fish Products; Food, Formulated; Genetic Predisposition to Disease; Humans; Incidence; Male; Risk Factors; Socioeconomic Factors; Surveys and Questionnaires

beta(2)-Adrenergic receptor polymorphisms and determinants of cardiovascular risk: the Cardiovascular Health Study. - Hindorff, Lucia A; Heckbert, Susan R; Psaty, Bruce M; Lumley, Thomas; Siscovick, David S; Herrington, David M; Edwards, Karen L; Tracy, Russell P (Am J Hypertens, 2005)
BACKGROUND: Common Arg16Gly and Gln27Glu polymorphisms of the beta(2)-adrenergic receptor (beta(2)AR) have been associated with hypertension and coronary disease. This analysis of older adults in the Cardiovascular Health Study examined whether these polymorphisms were associated with blood pressure (BP), subclinical atherosclerosis, and, among treated hypertensive individuals, differences in coronary disease risk according to antihypertensive drug class. METHODS: Altogether, 5249 participants (4441 white and 808 African American, median follow-up time 10.2 years) were genotyped for both polymorphisms. Ankle-arm index (AAI), carotid intima-media thickness (IMT), and brachial flow-mediated dilation were measured cross-sectionally. All estimates were adjusted for ethnicity. RESULTS: Relative to Gln27 homozygotes, carrying the Glu27 allele was not associated with new-onset hypertension (hazard ratio [HR] = 1.01, 95% confidence interval [CI] = 0.87 to 1.16), BP control (odds ratio [OR] = 0.97, 95% CI = 0.89 to 1.06), AAI (mean difference 0.0042 +/- 0.0052), carotid IMT (mean difference 0.0044 +/- 0.02 mm), or brachial flow-mediated dilation (mean difference in baseline diameter -0.028 +/- 0.036 mm; the most marked of three measures). Among treated hypertensive individuals, coronary disease risk was similar in Glu27 carriers relative to Gln27 homozygotes in subgroups defined by use of beta-blockers (HR = 1.09, 95% CI = 0.64 to 1.87) or other antihypertensive medications (HR = 1.00, 95% CI = 0.78 to 1.28). Results were similar for the Arg16Gly polymorphism. CONCLUSIONS: The association of beta(2)AR genotype with coronary disease previously reported in this older adult population is not likely to be explained by BP levels, subclinical atherosclerosis, or antihypertensive treatment. Other measures of vascular response, gene-gene or gene-environment interactions, or characteristics developing earlier in life may mediate the association between beta(2)AR genotype and coronary disease and merit further research.
Keywords: African Americans; Antihypertensive Agents; Arteriosclerosis; Coronary Artery Disease; European Continental Ancestry Group; Female; Genotype; Homozygote; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Genetic; Receptors, Adrenergic, beta-2; Risk Factors

Cardiovascular mortality risk in chronic kidney disease: comparison of traditional and novel risk factors. - Shlipak, Michael G; Fried, Linda F; Cushman, Mary; Manolio, Teri A; Peterson, Do; Stehman-Breen, Catherine; Bleyer, Anthony; Newman, Anne; Siscovick, David; Psaty, Bruce (JAMA, 2005)
CONTEXT: Elderly persons with chronic kidney disease have substantial risk for cardiovascular mortality, but the relative importance of traditional and novel risk factors is unknown. OBJECTIVE: To compare traditional and novel risk factors as predictors of cardiovascular mortality. DESIGN, SETTING, AND PATIENTS: A total of 5808 community-dwelling persons aged 65 years or older living in 4 communities in the United States participated in the Cardiovascular Health Study cohort. Participants were initially recruited from 1989 to June 1990; an additional 687 black participants were recruited in 1992-1993. The average length of follow-up in this longitudinal study was 8.6 years. MAIN OUTCOME MEASURES: Cardiovascular mortality among those with and without chronic kidney disease. Chronic kidney disease was defined as an estimated glomerular filtration rate of less than 60 mL/min per 1.73 m2. RESULTS: Among the participants, 1249 (22%) had chronic kidney disease at baseline. The cardiovascular mortality risk rate was 32 deaths/1000 person-years among those with chronic kidney disease vs 16/1000 person-years among those without it. In multivariate analyses, diabetes, systolic hypertension, smoking, low physical activity, nonuse of alcohol, and left ventricular hypertrophy were predictors of cardiovascular mortality in persons with chronic kidney disease (all P values <.05). Among the novel risk factors, only log C-reactive protein (P = .05) and log interleukin 6 (P<.001) were associated with the outcome as linear predictors. Traditional risk factors were associated with the largest absolute increases in risks for cardiovascular deaths among persons with chronic kidney disease: for left ventricular hypertrophy, there were 25 deaths per 1000 person-years; current smoking, 20 per 1000 person-years; physical inactivity, 15 per 1000 person-years; systolic hypertension, 14 per 1000 person-years; diabetes, 14 per 1000 person-years; and nonuse of alcohol, 11 per 1000 person-years vs 5 deaths per 1000 person-years for those with increased C-reactive protein and 5 per 1000 person-years for those with increased interleukin 6 levels. A receiver operating characteristic analysis found that traditional risk factors had an area under the curve of 0.73 (95% confidence interval, 0.70-0.77) among those with chronic kidney disease. Adding novel risk factors only increased the area under the curve to 0.74 (95% confidence interval, 0.71-0.78; P for difference = .15). CONCLUSIONS: Traditional cardiovascular risk factors had larger associations with cardiovascular mortality than novel risk factors in elderly persons with chronic kidney disease. Future research should investigate whether aggressive lifestyle intervention in patients with chronic kidney disease can reduce their substantial cardiovascular risk.
Keywords: Aged; Cardiovascular Diseases; Chronic Disease; Humans; Kidney Diseases; Longitudinal Studies; Risk Factors

Cardiovascular risk factors for retinal vein occlusion and arteriolar emboli: the Atherosclerosis Risk in Communities & Cardiovascular Health studies. - Wong, Tien Yin; Larsen, Emily K Marino; Klein, Ronald; Mitchell, Paul; Couper, David J; Klein, Barbara E K; Hubbard, Larry D; Siscovick, David S; Sharrett, A Richey (Ophthalmology, 2005)
OBJECTIVE: To examine the associations of retinal vein occlusion and arteriolar emboli with cardiovascular disease. DESIGN: Population-based cross-sectional study. PARTICIPANTS: Pooled from the Atherosclerosis Risk in Communities Study (n = 12,642; mean age, 60 years) and the Cardiovascular Health Study (n = 2824; mean age, 79 years). METHODS: Retinal vein occlusion and arteriolar emboli were identified from a single nonmydriatic retinal photograph using a standardized protocol. Photographs were also graded for arteriovenous nicking and focal arteriolar narrowing. All participants had a comprehensive systemic evaluation, including standardized carotid ultrasonography. MAIN OUTCOME MEASURES: Retinal vein occlusion and arteriolar emboli. RESULTS: Prevalences of retinal vein occlusion and arteriolar emboli were 0.3% (n = 39 cases) and 0.2% (n = 34 cases), respectively. After adjusting for age, retinal vein occlusion was associated with hypertension (odds ratio [OR], 2.96; 95% confidence interval [CI], 1.43-6.14), systolic blood pressure (BP) (OR, 4.12; 95% CI, 1.40-12.16; highest quartile vs. lowest), diastolic BP (OR, 2.64; 95% CI, 1.07-6.46; highest quartile vs. lowest), carotid artery plaque (OR, 5.62; 95% CI, 2.60-12.16), body mass index (OR, 3.88; 95% CI, 1.23-12.18; highest quartile vs. lowest), plasma fibrinogen (OR, 3.29; 95% CI, 1.08-10.02; highest quartile vs. lowest), arteriovenous nicking (OR, 4.09; 95% CI, 2.00-8.36), and focal arteriolar narrowing (OR, 5.17; 95% CI, 2.59-10.29). After adjusting for age, retinal arteriolar emboli were associated with hypertension (OR, 3.14; 95% CI, 1.44-6.84), systolic BP (OR, 3.46; 95% CI, 1.13-10.65; highest quartile vs. lowest), prevalent coronary heart disease (OR, 2.33; 95% CI, 1.01-5.42), carotid artery plaque (OR, 4.62; 95% CI, 1.85-11.57), plasma lipoprotein (a) (OR, 3.69; 95% CI, 1.20-11.41; highest quartile vs. lowest), plasma fibrinogen (OR, 3.09; 95% CI, 0.98-9.76; highest quartile vs. lowest), and current cigarette smoking (OR, 3.08; 95% CI, 1.47-6.47). Approximately a quarter of participants with retinal vein occlusion and arteriolar emboli had evidence of carotid artery plaque as defined from ultrasound. CONCLUSIONS: Retinal vein occlusion and retinal arteriolar emboli are associated with carotid artery disease, hypertension, and other cardiovascular risk factors.
Keywords: Aged; Aged, 80 and over; Arterioles; Blood Pressure; Cardiovascular Diseases; Carotid Stenosis; Coronary Artery Disease; Cross-Sectional Studies; Embolism; Female; Fibrinogen; Humans; Hypertension; Lipoprotein(a); Male; Meta-Analysis as Topic; Middle Aged; Retinal Artery; Retinal Vein Occlusion; Risk Factors

Common promoter polymorphisms of inflammation and thrombosis genes and longevity in older adults: the cardiovascular health study. - Reiner, Alexander P; Diehr, Paula; Browner, Warren S; Humphries, Stephen E; Jenny, Nancy S; Cushman, Mary; Tracy, Russell P; Walston, Jeremy; Lumley, Thomas; Newman, Anne B; Kuller, Lewis H; Psaty, Bruce M (Atherosclerosis, 2005)
Inflammatory response genes may influence life span or quality at advanced ages. Using data from the population-based cardiovascular health study (CHS) cohort, we examined the associations between promoter polymorphisms of several inflammation and thrombosis genes with longevity. We ascertained genotypes for interleukin (IL)-6 -174 G/C, beta-fibrinogen -455 G/A, plasminogen activator inhibitor (PAI)-1 -675 4G/5G, and thrombin-activatable fibrinolysis inhibitor (TAFI) -438 G/A in 2224 men and women > or = 65 years old at baseline. During 10 years of follow-up, men with the TAFI -438 A/A genotype had decreased mortality due to all causes, and lived, on average, 0.9 more years of life, or 1.1 more years of healthy life, than men with the -438 G allele. The effects of TAFI -438 G/A in women were smaller and not statistically significant. PAI-1 4G/4G genotype appeared to be associated with lower non-cardiovascular mortality in men, but with greater cardiovascular mortality in women. In exploratory analyses, we observed a possible interaction among anti-inflammatory drugs, interleukin-6 -174 C/C genotype, and longevity. These findings suggest that modulators of fibrinolytic activity may have a generalized influence on aging, and merit further investigation in studies of genetic determinants of human longevity.
Keywords: Aged; Aging; Carboxypeptidase B2; Cause of Death; Cohort Studies; Female; Genotype; Health Status; Humans; Inflammation; Longevity; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Polymorphism, Genetic; Promoter Regions, Genetic; Prospective Studies; Risk Factors; Thrombosis

Coronary artery calcium: associations with brain magnetic resonance imaging abnormalities and cognitive status. - Rosano, Caterina; Naydeck, Barbara; Kuller, Lewis H; Longstreth, William T; Newman, Anne B (J Am Geriatr Soc, 2005)
OBJECTIVES: To evaluate the association between coronary atherosclerosis and subclinical brain magnetic resonance imaging (MRI) abnormalities and between coronary atherosclerosis and abnormal cognitive function (dementia/mild cognitive impairment). DESIGN: Cross-sectional. SETTING: The Cardiovascular Health Study (CHS), an epidemiological study of risk factors for cardiovascular disease in older adults. PARTICIPANTS: Four hundred nine men and women, mean age 79, recruited from the Pittsburgh center of the CHS. MEASUREMENTS: Coronary atherosclerosis was defined according to the level of coronary artery calcification (CAC), as measured using electronic beam tomography. Subclinical brain MRI abnormalities included ventricular enlargement, white matter hyperintensities, and number of subcortical brain infarcts. Brain MRI and CAC measurements were performed between 1998 and 2000 at the Pittsburgh center of the CHS. Prevalence of brain MRI abnormalities and abnormal cognitive status were examined across quartiles of the CAC score, before and after controlling for age. Multivariate logistic regression models were used to assess whether CAC level was associated with abnormalities of brain MRI or abnormal cognitive status. RESULTS: Older adults with high CAC scores were more likely to have more-severe brain MRI abnormalities, including subcortical infarction and high white matter hyperintensities. The associations between CAC and ventricular enlargement showed a similar but not significant trend. The presence of any of the MRI abnormalities attenuated the association between CAC and abnormal cognitive status. CONCLUSION: Older adults with higher levels of CAC were more likely to have more-severe brain MRI abnormalities and abnormal cognitive status.
Keywords: Aged; Brain; Calcinosis; Cognition Disorders; Coronary Artery Disease; Cross-Sectional Studies; Dementia; Female; Humans; Logistic Models; Magnetic Resonance Imaging; Male; Risk Factors; United States

C-reactive protein and the 10-year incidence of coronary heart disease in older men and women: the cardiovascular health study. - Cushman, Mary; Arnold, Alice M; Psaty, Bruce M; Manolio, Teri A; Kuller, Lewis H; Burke, Gregory L; Polak, Joseph F; Tracy, Russell P (Circulation, 2005)
BACKGROUND: High C-reactive protein (CRP) is associated with increased coronary heart disease risk. Few long-term data in the elderly are available. METHODS AND RESULTS: Baseline CRP was measured in 3971 men and women > or =65 years of age without prior vascular diseases; 26% had elevated concentrations (>3 mg/L). With 10 years of follow-up, 547 participants developed coronary heart disease (CHD; defined as myocardial infarction or coronary death). With elevated CRP, the 10-year cumulative CHD incidences were 33% in men and 17% in women. The age-, ethnicity-, and sex-adjusted relative risk of CHD for CRP >3 mg/L compared with <1 mg/L was 1.82 (95% CI, 1.46 to 2.28). Adjusting for conventional risk factors reduced the relative risk to 1.45 (95% CI, 1.14 to 1.86). The population-attributable risk of CHD for elevated CRP was 11%. Risk relationships did not differ in subgroups defined by baseline risk factors. We assessed whether CRP improved prediction by the Framingham Risk Score. Among men with a 10-year Framingham-predicted risk of 10% to 20%, the observed CHD incidence was 32% for elevated CRP. Among women, CRP discriminated best among those with a 10-year predicted risk >20%; the incidences were 31% and 10% for elevated and normal CRP levels, respectively. CONCLUSIONS: In older men and women, elevated CRP was associated with increased 10-year risk of CHD, regardless of the presence or absence of cardiac risk factors. A single CRP measurement provided information beyond conventional risk assessment, especially in intermediate-Framingham-risk men and high-Framingham-risk women.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; Coronary Disease; Female; Humans; Incidence; Inflammation; Male; Myocardial Infarction; Predictive Value of Tests; Risk Factors

Cystatin C and incident peripheral arterial disease events in the elderly: results from the Cardiovascular Health Study. - O'Hare, Ann M; Newman, Anne B; Katz, Ronit; Fried, Linda F; Stehman-Breen, Catherine O; Seliger, Stephen L; Siscovick, David S; Shlipak, Michael G (Arch Intern Med, 2005)
BACKGROUND: The association of cystatin C, a novel marker of renal function, with risk for developing complications related to peripheral arterial disease (PAD) has not been examined. METHODS: We evaluated the hypothesis that a high cystatin C concentration is independently associated with future PAD events among 4025 participants in the Cardiovascular Health Study who underwent serum cystatin C measurement at the 1992-1993 visit and who did not have PAD at baseline. The association of cystatin C quintiles with time to first lower-extremity PAD procedure (bypass surgery, angioplasty, or amputation) was evaluated using multivariable proportional hazards models. Secondary analyses were conducted using quintiles of serum creatinine level and estimated glomerular filtration rate (eGFR). RESULTS: The annualized risk of undergoing a procedure for PAD was 0.43% per year among participants in the highest cystatin C quintile (>1.27 mg/L) compared with 0.21% per year or less in all other quintiles. After multivariable adjustment for known risk factors for PAD, elevated cystatin C levels remained associated with the outcome (hazard ratio, 2.5 for highest vs lowest quintile of cystatin C, 95% confidence interval, 1.2-5.1). The highest quintiles of serum creatinine level and eGFR were not associated with future PAD events in either unadjusted or adjusted analyses. CONCLUSION: Elevated concentrations of cystatin C were independently predictive of incident PAD events among community-dwelling elderly patients.
Keywords: Aged; Cohort Studies; Cystatin C; Cystatins; Female; Health Surveys; Humans; Longitudinal Studies; Male; Peripheral Vascular Diseases; Predictive Value of Tests; Risk Factors; ROC Curve; United States

Cystatin C concentration as a risk factor for heart failure in older adults. - Sarnak, Mark J; Katz, Ronit; Stehman-Breen, Catherine O; Fried, Linda F; Jenny, Nancy Swords; Psaty, Bruce M; Newman, Anne B; Siscovick, David; Shlipak, Michael G (Ann Intern Med, 2005)
BACKGROUND: Previous studies that evaluated the association of kidney function with incident heart failure may be limited by the insensitivity of serum creatinine concentration for detecting abnormal kidney function. OBJECTIVE: To compare serum concentrations of cystatin C (a novel marker of kidney function) and creatinine as predictors of incident heart failure. DESIGN: Observational study based on measurement of serum cystatin C from frozen sera obtained at the 1992-1993 visit of the Cardiovascular Health Study. Follow-up occurred every 6 months. SETTING: Adults 65 years of age or older from 4 communities in the United States. PARTICIPANTS: 4384 persons without previous heart failure who had measurements of serum cystatin C and serum creatinine. MEASUREMENTS: Incident heart failure. RESULTS: The mean (+/-SD) serum concentrations of cystatin C and creatinine were 82 +/- 25 nmol/L (1.10 +/- 0.33 mg/L) and 89 +/- 34 micromol/L (1.01 +/- 0.39 mg/dL), respectively. During a median follow-up of 8.3 years (maximum, 9.1 years), 763 (17%) participants developed heart failure. After adjustment for demographic factors, traditional and novel cardiovascular risk factors, cardiovascular disease status, and medication use, sequential quintiles of cystatin C concentration were associated with a stepwise increased risk for heart failure in Cox proportional hazards models (hazard ratios, 1.0 [reference], 1.30 [95% CI, 0.96 to 1.75], 1.44 [CI, 1.07 to 1.94], 1.58 [CI, 1.18 to 2.12], and 2.16 [CI, 1.61 to 2.91]). In contrast, quintiles of serum creatinine concentration were not associated with risk for heart failure in adjusted analysis (hazard ratios, 1.0 [reference], 0.77 [CI, 0.59 to 1.01], 0.85 [CI, 0.64 to 1.13], 0.97 [CI, 0.72 to 1.29], and 1.14 [CI, 0.87 to 1.49]). LIMITATIONS: The mechanism by which cystatin C concentration predicts risk for heart failure remains unclear. CONCLUSIONS: The cystatin C concentration is an independent risk factor for heart failure in older adults and appears to provide a better measure of risk assessment than the serum creatinine concentration. *For a full list of participating Cardiovascular Health Study investigators and institutions, see http://www.chs-nhlbi.org.
Keywords: Aged; Biomarkers; Creatinine; Cystatin C; Cystatins; Female; Follow-Up Studies; Glomerular Filtration Rate; Heart Failure; Humans; Incidence; Kidney; Kidney Function Tests; Male; Risk Factors; United States

Dementia and Alzheimer's disease incidence in relationship to cardiovascular disease in the Cardiovascular Health Study cohort. - Newman, Anne B; Fitzpatrick, Annette L; Lopez, Oscar; Jackson, Sharon; Lyketsos, Constantine; Jagust, William; Ives, Diane; DeKosky, Steven T; Kuller, Lewis H (J Am Geriatr Soc, 2005)
OBJECTIVES: To determine whether coronary artery disease, peripheral arterial disease (PAD), or noninvasive markers of cardiovascular disease (CVD) predict the onset of dementia and Alzheimer's disease (AD). DESIGN: Longitudinal cohort study. SETTING: Four U.S. communities. PARTICIPANTS: Men and women (N=3,602) with a brain magnetic resonance imaging (MRI) scan but no dementia were followed for 5.4 years. Participants with stroke were excluded. MEASUREMENTS: Neurologists and psychiatrists classified incident cases of dementia and subtype using neuropsychological tests, examination, medical records and informant interviews. CVD was defined at the time of the MRI scan. Noninvasive tests of CVD were assessed within 1 year of the MRI. Apolipoprotein E allele status, age, race, sex, education, Mini-Mental State Examination score, and income were assessed as potential confounders. RESULTS: The incidence of dementia was higher in those with prevalent CVD, particularly in the subgroup with PAD. The rate of AD was 34.4 per 1,000 person-years for those with a history of CVD, versus 22.2 per 1,000 person-years without a history of CVD (adjusted hazard ratio (HR)=1.3, 95% confidence interval (CI)=1.0-1.7). Rates of AD were highest in those with PAD (57.4 vs 23.7 per 100 person-years, adjusted HR=2.4, 95% CI=1.4-4.2). Results were similar with further exclusion of those with vascular dementia from the AD group. A gradient of increasing risk was noted with the extent of vascular disease. CONCLUSION: Older adults with CVD other than stroke had a higher risk of dementia and AD than did those without CVD. The risk was highest in people with PAD, suggesting that extensive peripheral atherosclerosis is a risk factor for AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Dementia; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Peripheral Vascular Diseases; Risk Factors

Determinants of vascular dementia in the Cardiovascular Health Cognition Study. - Kuller, L H; Lopez, O L; Jagust, W J; Becker, J T; DeKosky, S T; Lyketsos, C; Kawas, C; Breitner, J C S; Fitzpatrick, A; Dulberg, C (Neurology, 2005)
OBJECTIVE: The authors evaluated 3,375 participants without dementia at the time of MRI in 1991 to 1994 over 5.7 years for incident dementia and type of dementia. METHODS: Incidence of and risk factors for vascular dementia (VaD) were measured using both pre-MRI and modified State of California Alzheimer's Disease Diagnostic and Treatment Centers (ADDTC) post-MRI review and further classified Alzheimer disease (AD) by the National Institute of Neurological and Communicative Disorders and Stroke and the Alzheimer's Disease and Related Disorders Association (NINCDS-ADRDA) criteria. RESULTS: Approximately 44% (213) of 480 incident dementia cases were classified as possible or probable VaD by ADDTC. The incidence of VaD increased with age and was greater in blacks than whites. Risk factors for VaD included age, Modified Mini-Mental State Examination, high white matter grade, number of MRI infarcts, ventricular size, and history of stroke. CONCLUSIONS: Vascular disease in the brain is prevalent among incident dementia cases. There is a substantial overlap between cases classified as Alzheimer disease by Neurological and Communicative Disorders and Stroke and the Alzheimer's Disease and Related Disorders Association and vascular dementia (VaD) by modified State of California Alzheimer's Disease Diagnostic and Treatment Centers criteria. The substantial contribution of vascular disease would be missed without inclusion of MRI. Treatment of risk factors for VaD could have an important impact on incidence of dementia.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Brain; Cardiovascular Diseases; Cerebral Arteries; Cerebral Infarction; Cohort Studies; Comorbidity; Continental Population Groups; Dementia, Vascular; Female; Humans; Lateral Ventricles; Magnetic Resonance Imaging; Male; Nerve Fibers, Myelinated; Neuropsychological Tests; Risk Factors; Sex Factors

Factors associated with incidence and persistence of symptoms of disturbed sleep in an elderly cohort: the Cardiovascular Health Study. - Quan, Stuart F; Katz, Ronit; Olson, Jean; Bonekat, William; Enright, Paul L; Young, Terry; Newman, Anne (Am J Med Sci, 2005)
BACKGROUND: There are limited data pertaining to the factors influencing the incidence and persistence of sleep symptoms in the elderly. The purpose of this study was to determine the incidence and nonremission rates of the following sleep symptoms: trouble falling asleep (TFA), frequent awakenings (FA), and excessive daytime sleepiness (EDS) in the Cardiovascular Health Study (CHS), a prospective multicenter study of cardiovascular disease in a large cohort of elderly adults. Factors influencing these rates were assessed as well. METHODS: 4467 participants in CHS were surveyed for the presence of TFA, FA, and EDS as well as other health problems at their baseline examination and at a follow-up examination 1 to 4 years later. RESULTS: Annualized incidence and nonremission rates were the following: TFA (2.8% and 15.4%), FA (12.3% and 22.7%), and EDS (4.4% and 13.4%). Women were more likely to have incident and persistent TFA. Depression was the primary factor predicting the incidence of all three sleep symptoms. However, other health conditions, including respiratory symptoms and cardiovascular disease, and limitation in activities of daily living were important as well. Depression also was the most important factor associated with persistence of these sleep symptoms. The role of other health conditions in determining nonremission was much more limited. CONCLUSIONS: Incidence of sleep disturbances in the elderly is related to depression, health conditions, and physical functioning. However, persistence of sleep disturbances is best predicted by the presence of depression.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Depression; Female; Health Status; Humans; Incidence; Logistic Models; Male; Odds Ratio; Prevalence; Risk Factors; Sex Factors; Sleep Initiation and Maintenance Disorders; Surveys and Questionnaires

Fish intake and risk of incident heart failure. - Mozaffarian, Dariush; Bryson, Chris L; Lemaitre, Rozenn N; Burke, Gregory L; Siscovick, David S (J Am Coll Cardiol, 2005)
OBJECTIVES: Our aim was to investigate the relation between fish consumption and incidence of congestive heart failure (CHF). BACKGROUND: The incidence and health burden of CHF are rising, particularly in older persons. Although n-3 fatty acids have effects that could favorably influence risk of CHF, the relation between fish intake and CHF incidence is unknown. METHODS: Among 4,738 adults age > or =65 years and free of CHF at baseline in 1989-90, usual dietary intake was assessed using a food frequency questionnaire. In a participant subsample, consumption of tuna or other broiled or baked fish, but not fried fish, correlated with plasma phospholipid n-3 fatty acids. Incidence of CHF was prospectively adjudicated. RESULTS: During 12 years' follow-up, 955 participants developed CHF. In multivariate-adjusted analyses, tuna/other fish consumption was inversely associated with incident CHF, with 20% lower risk with intake 1 to 2 times/week (hazard ratio [HR] = 0.80, 95% confidence interval [CI] = 0.64 to 0.99), 31% lower risk with intake 3 to 4 times/week (HR = 0.69, 95% CI = 0.52 to 0.91), and 32% lower risk with intake > or =5 times/week (HR = 0.68, 95% CI = 0.45 to 1.03), compared with intake <1 time/month (p trend = 0.009). In similar analyses, fried fish consumption was positively associated with incident CHF (p trend = 0.01). Dietary long-chain n-3 fatty acid intake was also inversely associated with CHF (p trend = 0.009), with 37% lower risk in the highest quintile of intake (HR = 0.73, 95% CI = 0.57 to 0.94) compared with the lowest. CONCLUSIONS: Among older adults, consumption of tuna or other broiled or baked fish, but not fried fish, is associated with lower incidence of CHF. Confirmation in additional studies and evaluation of potential mechanisms is warranted.
Keywords: Aged; Animals; Cohort Studies; Cooking; Diet; Diet Surveys; Disease-Free Survival; Female; Fishes; Heart Failure; Humans; Incidence; Male; Risk Factors; United States

Hospitalization for pneumonia in the Cardiovascular Health Study: incidence, mortality, and influence on longer-term survival. - O'Meara, Ellen S; White, Mark; Siscovick, David S; Lyles, Mary F; Kuller, Lewis H (J Am Geriatr Soc, 2005)
OBJECTIVES: To estimate the rate of hospitalization for pneumonia in community-dwelling older adults and to assess its risk factors and contribution to mortality. DESIGN: Prospective observational study. SETTING: The Cardiovascular Health Study (CHS) in four U.S. communities. PARTICIPANTS: Five thousand eight hundred eighty-eight men and women aged 65 and older who were followed for a median 10.7 years. MEASUREMENTS: Participants were interviewed about medical history and demographics; evaluated for lung, physical, and cognitive function; and followed for hospitalizations, cardiovascular disease, and death. RESULTS: Nearly 10% of the cohort was hospitalized for pneumonia, for a rate of 11.1 per 1,000 person-years (95% confidence interval (CI)=10.2-12.0). Risk factors included older age, male sex, current and past smoking, poor physical and lung function, and history of cardiovascular disease and chronic obstructive pulmonary disease. Ten percent of participants died during their incident pneumonia hospitalization, and death rates were high in those who survived to discharge. Compared with participants who had not been hospitalized for pneumonia, the relative risk of total mortality was 4.9 (95% CI=4.1-6.0) during the first year after hospitalization and 2.6 (95% CI=2.2-3.1) thereafter, adjusted for age, sex, and race. The respective relative risks were 3.9 (95% CI=3.1-4.8) and 2.0 (95% CI=1.6-2.4) after further adjustment for baseline history of cardiovascular disease; diabetes mellitus; smoking; and measures of lung, physical, and cognitive function. CONCLUSION: In older people, hospitalization for pneumonia is common and is associated with an elevated risk of death, as shown in this population-based, prospective cohort.
Keywords: Aged; Aged, 80 and over; Cognition; Comorbidity; Diabetes Complications; Female; Hospitalization; Humans; Male; Mortality; Pneumonia; Prospective Studies; Respiratory Physiological Phenomena; Risk Factors; Smoking

Incidence, manifestations, and predictors of worsening white matter on serial cranial magnetic resonance imaging in the elderly: the Cardiovascular Health Study. - Longstreth, W T; Arnold, Alice M; Beauchamp, Norman J; Manolio, Teri A; Lefkowitz, David; Jungreis, Charles; Hirsch, Calvin H; O'Leary, Daniel H; Furberg, Curt D (Stroke, 2005)
BACKGROUND AND PURPOSE: Magnetic resonance imaging (MRI) scans in the elderly commonly show white matter findings that may raise concerns. We sought to document incidence, manifestations, and predictors of worsening white matter grade on serial imaging. METHODS: The Cardiovascular Health Study is a population-based, longitudinal study of 5888 people aged 65 years and older, of whom 1919 have had extensive initial and follow-up evaluations, including 2 MRI scans separated by 5 years. Scans were read without clinical information in standard side-by-side fashion to determine worsening white matter grade. RESULTS: Worsening was evident in 538 participants (28%), mostly (85%) by 1 grade. Although similar at initial scan, participants with worsening white matter grade, compared with those without, experienced greater decline on modified Mini-Mental State examination and Digit-Symbol Substitution test (both P< or =0.001) after controlling for potential confounding factors, including occurrence of transient ischemic attack or stroke between scans. Independent predictors of worsening white matter grade included cigarette smoking before initial scan and infarct on initial scan. Otherwise, predictors differed according to white matter grade on initial scan. For low initial grade, increased age, increased diastolic blood pressure, increased high-density lipoprotein cholesterol, and decreased low-density lipoprotein cholesterol were associated with increased risk of worsening. For high initial grade, any cardiovascular disease and low ankle-arm index were associated with decreased risk of worsening, whereas use of diuretics and statins were associated with increased risk. CONCLUSIONS: Worsening white matter grade on serial MRI scans in elderly is common, is associated with cognitive decline, and has complex relations with cardiovascular risk factors.
Keywords: Aged; Brain; Cardiovascular Diseases; Cognition Disorders; Female; Humans; Incidence; Leukoaraiosis; Longitudinal Studies; Magnetic Resonance Imaging; Male; Risk Factors; Stroke

Physical activity, APOE genotype, and dementia risk: findings from the Cardiovascular Health Cognition Study. - Podewils, Laura Jean; Guallar, Eliseo; Kuller, Lewis H; Fried, Linda P; Lopez, Oscar L; Carlson, Michelle; Lyketsos, Constantine G (Am J Epidemiol, 2005)
Physical activity may help preserve cognitive function and decrease dementia risk, but epidemiologic findings are inconsistent. The authors conducted a prospective study to determine the association between physical activity and risk of dementia, Alzheimer's disease, and vascular dementia. The US study population comprised 3,375 men and women aged 65 years or older, free of dementia at baseline, who participated in the Cardiovascular Health Cognition Study in 1992-2000. Leisure-time energy expenditure and an activity index reflecting number of different physical activities were calculated. Analyses were based on Cox proportional hazards models. There were 480 incident cases of dementia over an average of 5.4 years of follow-up. After multivariate adjustment, participants in the highest quartile of physical energy expenditure had a relative risk of dementia of 0.85 (95% confidence interval: 0.61, 1.19) compared with those in the lowest quartile, and participants engaging in >or=4 activities had a relative risk of dementia of 0.51 (95% confidence interval: 0.33, 0.79) compared with those engaging in 0-1 activity. These associations were more marked in apolipoprotein E genotype (APOE) epsilon4 allele noncarriers but were absent in carriers. A similar pattern was observed for Alzheimer's disease and vascular dementia. Mechanisms to explain the observed relations deserve further study.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Dementia; Dementia, Vascular; Female; Genotype; Humans; Male; Motor Activity; Proportional Hazards Models; Prospective Studies; Risk Factors; United States

Population structure, admixture, and aging-related phenotypes in African American adults: the Cardiovascular Health Study. - Reiner, Alexander P; Ziv, Elad; Lind, Denise L; Nievergelt, Caroline M; Schork, Nicholas J; Cummings, Steven R; Phong, Angie; Burchard, Esteban González; Harris, Tamara B; Psaty, Bruce M; Kwok, Pui-Yan (Am J Hum Genet, 2005)
U.S. populations are genetically admixed, but surprisingly little empirical data exists documenting the impact of such heterogeneity on type I and type II error in genetic-association studies of unrelated individuals. By applying several complementary analytical techniques, we characterize genetic background heterogeneity among 810 self-identified African American subjects sampled as part of a multisite cohort study of cardiovascular disease in older adults. On the basis of the typing of 24 ancestry-informative biallelic single-nucleotide-polymorphism markers, there was evidence of substantial population substructure and admixture. We used an allele-sharing-based clustering algorithm to infer evidence for four genetically distinct subpopulations. Using multivariable regression models, we demonstrate the complex interplay of genetic and socioeconomic factors on quantitative phenotypes related to cardiovascular disease and aging. Blood glucose level correlated with individual African ancestry, whereas body mass index was associated more strongly with genetic similarity. Blood pressure, HDL cholesterol level, C-reactive protein level, and carotid wall thickness were not associated with genetic background. Blood pressure and HDL cholesterol level varied by geographic site, whereas C-reactive protein level differed by occupation. Both ancestry and genetic similarity predicted the number and quality of years lived during follow-up, but socioeconomic factors largely accounted for these associations. When the 24 genetic markers were tested individually, there were an excess number of marker-trait associations, most of which were attenuated by adjustment for genetic ancestry. We conclude that the genetic demography underlying older individuals who self identify as African American is complex, and that controlling for both genetic admixture and socioeconomic characteristics will be required in assessing genetic associations with chronic-disease-related traits in African Americans. Complementary methods that identify discrete subgroups on the basis of genetic similarity may help to further characterize the complex biodemographic structure of human populations.
Keywords: African Americans; Aged; Aging; Algorithms; Cardiovascular Diseases; Cohort Studies; Female; Genetics, Population; Genotype; Humans; Male; Models, Genetic; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Socioeconomic Factors

A prospective study of anemia status, hemoglobin concentration, and mortality in an elderly cohort: the Cardiovascular Health Study. - Zakai, Neil A; Katz, Ronit; Hirsch, Calvin; Shlipak, Michael G; Chaves, Paulo H M; Newman, Anne B; Cushman, Mary (Arch Intern Med, 2005)
BACKGROUND: Anemia is viewed as a negative prognostic factor in the elderly population; its independent impact on survival is unclear. METHODS: Baseline hemoglobin quintiles and anemia, as defined by the World Health Organization criteria, were assessed in relation to mortality in the Cardiovascular Health Study, a prospective cohort study with 11.2 years of follow-up of 5888 community-dwelling men and women 65 years or older, enrolled in 1989-1990 or 1992-1993 in 4 US communities. RESULTS: A total of 1205 participants were in the lowest hemoglobin quintile (<13.7 g/dL for men; <12.6 g/dL for women), and 498 (8.5%) were anemic (<13 g/dL for men; <12 g/dL for women). A reverse J-shaped relationship with mortality was observed; age-, sex-, and race-adjusted hazard ratios (95% confidence interval [CI]) in the first and fifth quintiles, compared with the fourth quintile, were 1.42 (95% CI, 1.25-1.62) and 1.24 (95% CI, 1.09-1.42). After multivariate adjustment, these hazard ratios were 1.33 (95% CI, 1.15-1.54) and 1.17 (95% CI, 1.01-1.36). The demographic- and fully-adjusted hazard ratios of anemia for mortality were 1.57 (95% CI, 1.38-1.78) and 1.38 (95% CI, 1.19-1.54). Adjustment for causes and consequences of anemia (renal function, inflammation, or frailty) did not reduce associations. CONCLUSIONS: Lower and higher hemoglobin concentrations and anemia by World Health Organization criteria were independently associated with increased mortality. The World Health Organization criteria did not identify risk as well as a lower hemoglobin value. Additional study is needed on the clinically valid definition for and causes of anemia in the elderly and on the increased mortality at the extremes of hemoglobin concentrations.
Keywords: Age Factors; Aged; Anemia; California; Female; Follow-Up Studies; Health Status; Hemoglobins; Humans; Male; Maryland; Multivariate Analysis; North Carolina; Observation; Pennsylvania; Prospective Studies; Risk Factors; Severity of Illness Index; Survival Rate

Prostate carcinoma incidence in relation to prediagnostic circulating levels of insulin-like growth factor I, insulin-like growth factor binding protein 3, and insulin. - Chen, Chu; Lewis, S Kay; Voigt, Lynda; Fitzpatrick, Annette; Plymate, Stephen R; Weiss, Noel S (Cancer, 2005)
BACKGROUND: There have been several epidemiologic studies investigating the association between circulating levels of insulin-like growth factor I (IGF-I), insulin-like growth factor binding protein 3 (IGFBP-3), and insulin in relation to the risk of prostate carcinoma, with conflicting results. To examine this issue further, the authors conducted a nested case-control study within the Cardiovascular Health Study cohort. METHODS: In men who were diagnosed with prostate carcinoma (cases) between 1990 and 1999 (n=174), the levels of IGF-I, IGFBP-3, and insulin were measured on blood samples that were obtained 1-9 years prior to diagnosis (mean, 3.4 years). Similar measurements were made on 174 male participants without prostate carcinoma (controls) who were matched to cases based on the year blood was drawn, survival until the date of diagnosis, race, and age. RESULTS: Relative to the men with IGF-I levels in the first (lowest) quartile of the distribution, the risk of prostate carcinoma for men in the second, third, and fourth (upper) quartiles were 0.77 (95% confidence interval [95% CI], 0.43-1.38), 0.73 (95% CI, 0.41-1.30), and 0.67 (95% CI, 0.37-1.25), respectively. The results were influenced little by adjustment for levels of IGFBP-3 or, instead, by evaluating the molar IGF-I/IGFBP-3 ratio. An analysis that was restricted to men who had plasma prostate-specific antigen levels <4 ng/mL at the time of the blood draw yielded similar results. The corresponding relative risks for IGFBP-3 were 0.91 (95% CI, 0.49-1.68), 0.47 (95% CI, 0.25-0.94), and 0.65 (95% CI, 0.35-1.20), respectively. The distribution of serum insulin levels in cases and controls were nearly identical. CONCLUSIONS: The IGF-I level was not associated positively with the risk of prostate carcinoma; however, an increase in the IGFBP-3 level was associated with a modest decrease in risk.
Keywords: Aged; Aged, 80 and over; Carcinoma; Case-Control Studies; Humans; Hypoglycemic Agents; Incidence; Insulin; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Prostatic Neoplasms; Risk Factors

Renal duplex parameters, blood pressure, and renal function in elderly people. - Pearce, Jeffrey D; Edwards, Matthew S; Craven, Timothy E; English, William P; Mondi, Matthew M; Reavis, Scott W; Hansen, Kimberley J (Am J Kidney Dis, 2005)
BACKGROUND: Changes in renal artery and renal parenchyma perfusion are believed to correlate with severity of hypertension and worsened renal function, but population-based studies of these associations are not available. This study examines relationships between parameters derived from renal duplex sonography (RDS), blood pressure (BP), and excretory renal function in a population-based cohort of elderly Americans. METHODS: Through an ancillary study to the Cardiovascular Health Study, 758 participants (37% men; mean age, 77 years) underwent RDS in which flow velocities and frequency shifts were determined from spectral analysis of Doppler-shifted signals obtained from the renal artery and parenchyma. Associations of these duplex parameters with BP and inverse serum creatinine were examined by using multivariate regression techniques. RESULTS: Main renal artery peak systolic flow velocity (PSV) showed independent associations with BP, with an SD increase in PSV (0.53 m/s) associated with a 3.3-mm Hg increase in systolic BP (SBP) and a 2.4-mm Hg decrease in diastolic BP (DBP). An SD decrease in end-diastolic frequency shift (EDF; 131 kHz) was associated with a 6.0-mm Hg increase in SBP, a 4.2-mm Hg decrease in DBP, and a significant 3.7% decrease in inverse serum creatinine. CONCLUSION: Increases in renal artery PSV and decreases in parenchymal EDF are associated with increased SBP and decreased DBP. Moreover, decreased parenchymal EDF showed significant associations with impaired excretory renal function. These results suggest that renal duplex parameters are associated with renal parenchymal changes caused by hypertension and progressive renal dysfunction in elderly people.
Keywords: African Americans; Aged; Aging; Arteriosclerosis; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Creatinine; Cross-Sectional Studies; Diastole; Disease Progression; European Continental Ancestry Group; Female; Humans; Hypertension, Renovascular; Kidney; Kidney Diseases; Kidney Function Tests; Male; Renal Artery; Renal Artery Obstruction; Renal Circulation; Risk Factors; Sampling Studies; Systole; Ultrasonography, Doppler, Duplex; United States

Risk factors for declining ankle-brachial index in men and women 65 years or older: the Cardiovascular Health Study. - Kennedy, Margaret; Solomon, Cam; Manolio, Teri A; Criqui, Michael H; Newman, Anne B; Polak, Joseph F; Burke, Gregory L; Enright, Paul; Cushman, Mary (Arch Intern Med, 2005)
BACKGROUND: An ankle-brachial index (ABI) of less than 0.9 is a noninvasive measure of lower extremity arterial disease and a predictor of cardiovascular events. Little information is available on longitudinal change in ABI or on risk factors for declining ABI in a community-based population. METHODS: To assess risk factors for ABI decline, we studied 5888 participants in the Cardiovascular Health Study cohort (men and women 65 years or older). We measured ABI in 1992-1993 and again in 1998-1999. At baseline, we excluded individuals with an ABI less than 0.9, ABI greater than 1.4, or confirmed symptomatic lower extremity arterial disease (n = 823). The group with ABI decline included 218 participants with decline greater than 0.15 and to 0.9 or less. The comparison group comprised the remaining 2071 participants with follow-up ABI. RESULTS: The percentage of participants with ABI decline was 9.5% over 6 years of follow-up. The mean +/- SD decline was 0.33 +/- 0.12 in cases of ABI decline and 0.02 +/- 0.13 in non-cases. Independent predictors of ABI decline, reported as odds ratios, were age, 1.96 (95% confidence interval [CI], 1.42-2.71) for 75 to 84 years and 3.79 (95% CI, 1.36-10.5) for those older than 85 years compared with those younger than 75 years; current cigarette use, 1.74 (95% CI, 1.02-2.96); hypertension, 1.64 (95% CI, 1.18-2.28); diabetes, 1.77 (95% CI, 1.14-2.76); higher low-density lipoprotein cholesterol level, 1.60 (95% CI, 1.03-2.51), and lipid-lowering drug use 1.74 (95% CI, 1.05-2.89). CONCLUSION: Worsening lower extremity arterial disease, assessed as ABI decline, occurred in 9.5% of this elderly cohort over 6 years and was associated with modifiable vascular disease risk factors.
Keywords: Aged; Aged, 80 and over; Ankle; Brachial Artery; Cardiovascular Diseases; Female; Humans; Male; Peripheral Vascular Diseases; Risk Assessment; Risk Factors

Sleepiness in patients with moderate to severe sleep-disordered breathing. - Kapur, Vishesh K; Baldwin, Carol M; Resnick, Helaine E; Gottlieb, Daniel J; Nieto, F Javier (Sleep, 2005)
BACKGROUND: Population-based studies suggest that complaints of sleepiness are absent in many individuals with sleep-disordered breathing. We investigated the prevalence of sleepiness as well as factors associated with sleepiness in individuals with moderate to severe sleep-disordered breathing (apnea-hypopnea index > or = 15). DESIGN: Cross-sectional study. SETTING: The Sleep Heart Health Study. PARTICIPANTS: Sleep Heart Health Study participants (N = 6440). MEASUREMENTS AND RESULTS: Sleepiness was defined as an Epworth Sleepiness Scale score >10 or a report of at least frequently feeling unrested or sleepy. Forty-six percent of participants with moderate to severe sleep-disordered breathing (n = 1149) reported sleepiness. Characteristics associated with sleepiness after adjustment for confounders included presence of respiratory disease, shorter self-reported weekday and weekend sleep, sleep durations, complaints of insufficient sleep, complaints of sleep maintenance insomnia, early morning awakening, habitual snoring, and complaints of awakening with leg cramps or leg jerks. Some respiratory polysomnography measures were associated with sleepiness, but sleep-stage percentages and measures of sleep disruption were not. CONCLUSIONS: In this community-based cohort, subjective sleepiness is absent in many individuals with significant sleep-disordered breathing. Comorbid conditions, including respiratory disease, sleep restriction, insomnia, and nocturnal leg complaints, are important risk factors for sleepiness in individuals with moderate to severe sleep-disordered breathing.
Keywords: Aged; Body Mass Index; Cohort Studies; Cross-Sectional Studies; Disorders of Excessive Somnolence; Female; Humans; Male; Middle Aged; Oxygen; Polysomnography; Prevalence; Risk Factors; Severity of Illness Index; Sleep Apnea Syndromes; Sleep Arousal Disorders; Sleep Stages; Surveys and Questionnaires

Sometimes higher heart rate variability is not better heart rate variability: results of graphical and nonlinear analyses. - Stein, Phyllis K; Domitrovich, Peter P; Hui, Nelson; Rautaharju, Pentti; Gottdiener, John (J Cardiovasc Electrophysiol, 2005)
OBJECTIVE: To determine the prevalence and effect on traditional heart rate variability (HRV) indices of abnormal HRV patterns in the elderly. METHODS: Hourly Poincaré plots and plots of spectral HRV from normal-to-normal interbeat intervals and hourly nonlinear HRV values were examined in a subset of 290 consecutive participants in the Cardiovascular Health Study. Only subjects in normal sinus rhythm with > or = 18 hours of usable data were included. Eligible subjects were 71 +/- 5 years. During 7 years of follow-up, 21.7% had died. Hours were scored as normal (0), borderline (0.5), or abnormal (1) from a combination of plot appearance and HRV. Summed scores were normalized to 100% to create an abnormality score (ABN). Short-term HRV versus each 5th percentile of ABN was plotted and a cutpoint for markedly increased HRV identified. The t-tests compared HRV for subjects above and below this cutpoint. Cox regression evaluated the association of ABN and mortality. RESULTS: Of 5,815 eligible hourly plots, 64.4% were normal, 14.5% borderline, and 21.1% abnormal. HR, SDNN, SDNNIDX, ln VLF and LF power, and power law slope did not differ by the cutpoint for increased short-term HRV, while SDANN and ln ULF power were significantly lower for those above the cutpoint. However, many HRV indices including LF/HF ratio and normalized LF and HF power were significantly different between groups (P < 0.001). Increased ABN was significantly associated with mortality (P = 0.019). Despite similar values for many HRV indices, being in the group above the cutpoint was significantly associated with mortality (P = 0.04). CONCLUSIONS: Abnormal HR patterns that elevate many HRV indices are prevalent among the elderly and associated with higher risk of mortality. Consideration of abnormal HRV may improve HRV-based risk stratification.
Keywords: Aged; Aged, 80 and over; Algorithms; Arrhythmia, Sinus; Cohort Studies; Diagnosis, Computer-Assisted; Electrocardiography; Female; Heart Rate; Humans; Male; Models, Cardiovascular; Nonlinear Dynamics; Numerical Analysis, Computer-Assisted; Prevalence; Proportional Hazards Models; Reproducibility of Results; Risk Assessment; Risk Factors; Sensitivity and Specificity; United States

Subclinical brain magnetic resonance imaging abnormalities predict physical functional decline in high-functioning older adults. - Rosano, Caterina; Kuller, Lewis H; Chung, Hyoju; Arnold, Alice M; Longstreth, William T; Newman, Anne B (J Am Geriatr Soc, 2005)
OBJECTIVES: To determine whether severity of subclinical brain magnetic resonance imaging (MRI) abnormalities predicts incident self-reported physical impairment or rate of decline in motor performance. DESIGN: Longitudinal analysis, average follow-up time: 4.0 years. SETTING: Cardiovascular Health Study (CHS). PARTICIPANTS: CHS participants with modified Mini-Mental State Examination (3MS) score of 80 or greater, no self-reported disability, no history of stroke, and at least one assessment of mobility (n=2,450, mean age=74.4). MEASUREMENTS: Brain MRI abnormalities (ventricular enlargement, white matter hyperintensities, subcortical and basal ganglia small brain infarcts), self-reported physical impairment (difficulty walking half a mile or with one or more activities of daily living), and motor performance (gait speed, timed chair stand). RESULTS: After adjusting for demographics, cardiovascular risk factors, and diseases, risk of incident self-reported physical impairment was 35% greater for those with severe ventricular enlargement than for those with minimal ventricular enlargement, 22% greater for those with moderate white matter hyperintensities than for those with minimal white matter hyperintensities, and 26% greater for participants with at least one brain infarct than for those with no infarcts. Those with moderate to severe brain abnormalities experienced faster gait speed decline (0.02 m/s per year) than those with no MRI abnormalities (0.01 m/s per year). Further adjustment for incident stroke, incident dementia, and 3MS score did not substantially attenuate hazard ratios for incident self-reported physical impairment or coefficients for decline in gait speed. CONCLUSION: Subclinical structural brain abnormalities in high-functioning older adults can increase the risk of developing physical disabilities and declining in motor performance.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Brain; Female; Follow-Up Studies; Gait; Humans; Incidence; Magnetic Resonance Imaging; Male; Proportional Hazards Models; Psychomotor Disorders; Risk Factors; United States

10-year follow-up of subclinical cardiovascular disease and risk of coronary heart disease in the Cardiovascular Health Study. - Kuller, Lewis H; Arnold, Alice M; Psaty, Bruce M; Robbins, John A; O'Leary, Daniel H; Tracy, Russell P; Burke, Gregory L; Manolio, Teri A; Chaves, Paolo H M (Arch Intern Med, 2006)
BACKGROUND: The incidence of coronary heart disease (CHD) is very high among individuals 65 years or older. METHODS: We evaluated the relationships between measurements of subclinical disease at baseline (1989-1990) and at the third-year follow-up examination (1992-1993) and subsequent incidence of cardiovascular disease and total mortality as of June 2001. Approximately 61% of the participants without clinical cardiovascular disease at baseline had subclinical disease based on our previously described criteria from the Cardiovascular Health Study. RESULTS: The incidence of CHD was substantially increased for participants with subclinical disease compared with those who had no subclinical disease: 30.5 per 1000 person-years with and 16.3 per 1000 person-years without for white individuals, and 31.2 per 1000 person-years with and 12.5 per 1000 person-years without for black individuals. The risk persisted over the entire follow-up period. Incidence rates were higher for men than for women with or without subclinical disease, but there was little difference in rates for black individuals and white individuals. CONCLUSIONS: In multivariable models, subclinical disease at baseline remained a significant predictor of CHD in both men and women; the hazard ratios (95% confidence intervals) of their relative risks were 1.64 (1.30-2.06) and 1.49 (1.21-1.84), respectively. The presence of subclinical disease substantially increased the risk of subsequent CHD for participants with hypertension, diabetes mellitus, or elevated C-reactive protein. In summary, subclinical disease is very prevalent among older individuals, is independently associated with risk of CHD even over a 10-year follow-up period, and substantially increases the risk of CHD among participants with hypertension or diabetes mellitus.
Keywords: African Continental Ancestry Group; Aged; Blood Chemical Analysis; Cardiovascular Diseases; Comorbidity; Coronary Disease; Echocardiography; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Male; Multivariate Analysis; Prevalence; Proportional Hazards Models; Regression Analysis; Risk Factors; Sex Distribution; United States

The association of alcohol consumption and incident heart failure: the Cardiovascular Health Study. - Bryson, Chris L; Mukamal, Kenneth J; Mittleman, Murray A; Fried, Linda P; Hirsch, Calvin H; Kitzman, Dalane W; Siscovick, David S (J Am Coll Cardiol, 2006)
OBJECTIVES: We investigated the association between alcohol consumption and incident congestive heart failure (CHF) both overall and after adjusting for incident myocardial infarction (MI). BACKGROUND: Moderate alcohol consumption has been associated with lower risk of CHF and MI. METHODS: The Cardiovascular Health study, a prospective cohort study of cardiovascular disease risk factors and outcomes, followed 5,888 subjects > or =65 years old for 7 to 10 years. Cox models were used to estimate the adjusted risk of CHF by reported alcohol consumption. RESULTS: There were 5,595 subjects at baseline at risk for incident CHF with alcohol data and 1,056 events during follow-up. Compared with abstainers, the adjusted risk of CHF was lower among subjects who reported consuming 1 to 6 drinks per week (hazard ratio [HR] 0.82, 95% confidence interval [CI] 0.67 to 1.00, p = 0.05) and 7 to 13 drinks per week (HR 0.66, 95% CI 0.47 to 0.91, p = 0.01). Time-dependent adjustment for incident MI altered only slightly the association between moderate alcohol consumption and CHF (for 1 to 6 drinks per week, HR 0.84, 95% CI 0.65 to 1.04; for 7 to 13 drinks per week, HR 0.69, 95% CI 0.49 to 0.99). Baseline former drinkers had a higher risk of CHF than abstainers (HR 1.51, p < 0.01), but those who quit during the study did not have a higher risk (HR 0.83, 95% CI 0.66 to 1.03). CONCLUSIONS: Moderate alcohol use is associated with a lower risk of incident CHF among older adults, even after accounting for incident MI and other factors.
Keywords: Aged; Alcohol Drinking; Chi-Square Distribution; Comorbidity; Female; Heart Failure; Humans; Life Style; Male; Multicenter Studies as Topic; Myocardial Infarction; Proportional Hazards Models; Risk Factors; Smoking

The association of microalbuminuria with clinical cardiovascular disease and subclinical atherosclerosis in the elderly: the Cardiovascular Health Study. - Cao, Jie J; Barzilay, Joshua I; Peterson, Do; Manolio, Teri A; Psaty, Bruce M; Kuller, Lewis; Wexler, Jason; Bleyer, Anthony J; Cushman, Mary (Atherosclerosis, 2006)
PURPOSE: Microalbuminuria (MA) is a risk factor for cardiovascular disease (CVD). It is not known whether this association is due to the effect of MA on the development of subclinical atherosclerosis or whether MA destabilizes subclinical atherosclerosis, leading to clinical events. METHODS: In a cross-sectional analysis we evaluated 3312 Cardiovascular Health Study participants, age >or=65 years, who had MA testing. Participants were divided into three groups: those without diabetes or hypertension (33%), those with hypertension (52%) and those with diabetes, with or without hypertension (15%). Clinical CVD was defined as presence of coronary heart disease (angina, MI, CABG, PTCA), cerebrovascular disease (stroke, TIA) and peripheral arterial disease (requiring intervention). Among those without clinical disease, subclinical atherosclerosis was defined as increased carotid artery intima-media thickness, decreased ankle arm index or increased left ventricular mass. RESULTS: In each of the three groups of participants, the adjusted odds of prevalent clinical CVD in the presence of MA was 1.70-1.80-fold increased, independent of other risk factors. MA was not associated with risk of subclinical atherosclerosis in those without hypertension or diabetes (OR 1.14 [95% CI 0.59, 2.23]), whereas it was associated with subclinical atherosclerosis in those with hypertension (OR 1.58 [95% CI 1.08, 2.30]) or diabetes (OR 2.51 [95% CI 1.27, 4.94]). CONCLUSION: In the absence of hypertension or diabetes, MA was associated with clinical CVD but not with subclinical atherosclerosis. Thus, a hypothesis may be made that the mechanism of association of MA with clinical vascular disease involves destabilization of the vasculature, leading to clinical disease.
Keywords: Aged; Aged, 80 and over; Albuminuria; Atherosclerosis; Cardiovascular Diseases; Coronary Disease; Diabetes Mellitus; Female; Humans; Hypertension; Male; Peripheral Vascular Diseases; Prevalence; Risk Factors; Stroke; United States

Association of nocturnal arrhythmias with sleep-disordered breathing: The Sleep Heart Health Study. - Mehra, Reena; Benjamin, Emelia J; Shahar, Eyal; Gottlieb, Daniel J; Nawabit, Rawan; Kirchner, H Lester; Sahadevan, Jayakumar; Redline, Susan (Am J Respir Crit Care Med, 2006)
RATIONALE: Sleep-disordered breathing recurrent intermittent hypoxia and sympathetic nervous system activity surges provide the milieu for cardiac arrhythmia development. OBJECTIVE: We postulate that the prevalence of nocturnal cardiac arrhythmias is higher among subjects with than without sleep-disordered breathing. METHODS: The prevalence of arrhythmias was compared in two samples of participants from the Sleep Heart Health Study frequency-matched on age, sex, race/ethnicity, and body mass index: (1) 228 subjects with sleep-disordered breathing (respiratory disturbance index>or=30) and (2) 338 subjects without sleep-disordered breathing (respiratory disturbance index<5). RESULTS: Atrial fibrillation, nonsustained ventricular tachycardia, and complex ventricular ectopy (nonsustained ventricular tachycardia or bigeminy or trigeminy or quadrigeminy) were more common in subjects with sleep-disordered breathing compared with those without sleep-disordered breathing: 4.8 versus 0.9% (p=0.003) for atrial fibrillation; 5.3 versus 1.2% (p=0.004) for nonsustained ventricular tachycardia; 25.0 versus 14.5% (p=0.002) for complex ventricular ectopy. Compared with those without sleep-disordered breathing and adjusting for age, sex, body mass index, and prevalent coronary heart disease, individuals with sleep-disordered breathing had four times the odds of atrial fibrillation (odds ratio [OR], 4.02; 95% confidence interval [CI], 1.03-15.74), three times the odds of nonsustained ventricular tachycardia (OR, 3.40; 95% CI, 1.03-11.20), and almost twice the odds of complex ventricular ectopy (OR, 1.74; 95% CI, 1.11-2.74). A significant relation was also observed between sleep-disordered breathing and ventricular ectopic beats/h (p<0.0003) considered as a continuous outcome. CONCLUSIONS: Individuals with severe sleep-disordered breathing have two- to fourfold higher odds of complex arrhythmias than those without sleep-disordered breathing even after adjustment for potential confounders.
Keywords: Aged; Aged, 80 and over; Arrhythmias, Cardiac; Circadian Rhythm; Electrocardiography; Female; Follow-Up Studies; Humans; Male; Middle Aged; Odds Ratio; Polysomnography; Prevalence; Retrospective Studies; Risk Factors; Severity of Illness Index; Sleep; Sleep Apnea, Obstructive

Cardiovascular morbidity and mortality in community-dwelling elderly individuals with calcification of the fibrous skeleton of the base of the heart and aortosclerosis (The Cardiovascular Health Study). - Barasch, Eddy; Gottdiener, John S; Marino Larsen, Emily K; Chaves, Paulo H M; Newman, Anne B (Am J Cardiol, 2006)
In the elderly, mitral annular calcification (MAC) and aortic valve sclerosis (AVS) are associated with increased cardiovascular morbidity and mortality. Aortic annular calcification (AAC) commonly occurs with MAC. However, the prognostic value of AAC, singly or in combination with MAC and AVS, for incident cardiovascular disease and mortality is unknown. From the Cardiovascular Health Study, we analyzed 3,782 participants (76 +/- 5 years of age, 60% women) who had an echocardiogram at the 1994 to 1995 examination and who were prospectively followed for an average of 6.6 years (range 0.01 to 8.5). All 3 calcification categories were associated with incident congestive heart failure (MAC: hazard ratio [HR] 1.71, 95% confidence interval [CI] 1.35 to 2.18, AAC: HR 1.62, 95% CI 1.28 to 2.06, and AVS: HR 1.50, 95% CI 1.19 to 1.89) and death. A stronger association with incident cardiovascular disease and mortality was observed with a larger number of calcification categories and with increased MAC severity. Moreover, in the participants with prevalent cardiovascular disease at echocardiographic examination (n = 1,054), MAC and AAC were still associated with cardiovascular mortality (MAC: HR 1.91, 95% CI 1.04 to 3.50; AAC: HR 2.11, 95% CI 1.16 to 3.85) even in fully adjusted models. In conclusion, MAC, AAC, and AVS are associated with a significant risk of incident congestive heart failure, cardiovascular and all-cause mortalities, and worse outcome in older patients with preexisting cardiovascular disease. Elderly patients with these findings represent a high-risk group and may require close medical attention.
Keywords: Aged; Aortic Valve; Calcinosis; Echocardiography; Female; Follow-Up Studies; Heart Failure; Heart Valve Diseases; Humans; Male; Mitral Valve; Prospective Studies; Risk Factors; Sclerosis; Severity of Illness Index; United States

Characteristics and baseline clinical predictors of future fatal versus nonfatal coronary heart disease events in older adults: the Cardiovascular Health Study. - Pearte, Camille A; Furberg, Curt D; O'Meara, Ellen S; Psaty, Bruce M; Kuller, Lewis; Powe, Neil R; Manolio, Teri (Circulation, 2006)
BACKGROUND: Although >80% of annual coronary heart disease (CHD) deaths occur in adults aged >65 years and the population is aging rapidly, CHD event fatality and its predictors in the elderly have not been well described. METHODS AND RESULTS: The first myocardial infarction (MI) or CHD death among the 5888 adults aged > or =65 years occurring during enrollment in the Cardiovascular Health Study during 1989-2001 was identified and adjudicated. Characteristics measured at examinations before the event were examined for associations with case fatality (death before hospitalization or hospital discharge) and for differences in predictors by demographics or clinical history. During a median follow-up of 8.2 years, 985 CHD events occurred, of which 30% were fatal. Case fatality decreased slightly over time, ranging from 28% to 30% per year in the early 1990s versus 23% by 2000-2001; with adjustment for age at MI and gender, there was a 6% lower odds of fatality with each successive year (odds ratio [OR], 0.94; 95% confidence interval [CI], 0.90 to 0.98). Case fatality was similar by race and gender but higher with age and prior CHD (MI, angina, or revascularization). When considered alone, many subclinical disease measures, such as common carotid intima-media thickness, ankle-arm index, left ventricular mass by ECG, and a major ECG abnormality, and traditional risk factors, such as diabetes and hypertension, were associated with fatality. In multivariable analysis, independent predictors of fatality were prior congestive heart failure (OR, 3.20; 95% CI, 2.32 to 4.41), prior CHD rather than only history of MI (OR, 2.51; 95% CI, 1.84 to 3.43), diabetes (OR, 1.66; 95% CI, 1.10 to 2.31), and age (OR, 1.21 per 5 years; 95% CI, 1.07 to 1.37), adjusted for gender and each other. Prior congestive heart failure, regardless of left ventricular systolic function, age, gender, or prior CHD, conferred a > or =3-fold increased risk of fatality in almost all subgroups. CONCLUSIONS: Among community-dwelling older adults, CHD case fatality remains substantial, with easily identifiable risk factors that may be different from those that predict incident disease. In the elderly in whom the risk/benefit of therapies may be influenced by multiple competing comorbidities and care needs, risk stratification possibly may be improved further by focusing more aggressive care on specific patients, especially those with a history of congestive heart failure or prior CHD.
Keywords: Age Factors; Aged; Aged, 80 and over; Carotid Artery, Common; Cohort Studies; Comorbidity; Coronary Disease; Diabetes Mellitus; Electrocardiography; Female; Follow-Up Studies; Forecasting; Heart Failure; Heart Ventricles; Hospitalization; Humans; Hyperlipidemias; Hypertension; Male; Multivariate Analysis; Myocardial Infarction; Organ Size; Predictive Value of Tests; Risk Factors; Sampling Studies; Tunica Intima; Tunica Media; United States

Cigarette smoking and nocturnal sleep architecture. - Zhang, Lin; Samet, Jonathan; Caffo, Brian; Punjabi, Naresh M (Am J Epidemiol, 2006)
Cigarette smoking has been associated with a high prevalence of sleep-related complaints. However, its effects on sleep architecture have not been fully examined. The primary objective of this investigation was to assess the impact of cigarette smoking on sleep architecture. Polysomnography was used to characterize sleep architecture among 6,400 participants of the Sleep Heart Health Study (United States, 1994-1999). Sleep parameters included total sleep time, latency to sleep onset, sleep efficiency, and percentage of time in each sleep stage. The study sample consisted of 2,916 never smokers, 2,705 former smokers, and 779 current smokers. Compared with never smokers, current smokers had a longer initial sleep latency (5.4 minutes, 95% confidence interval (CI): 2.9, 7.9) and less total sleep time (14.0 minutes, 95% CI: 6.4, 21.7). Furthermore, relative to never smokers, current smokers also had more stage 1 sleep (relative proportion = 1.24, 95% CI: 1.14, 1.33) and less slow wave sleep (relative proportion = 0.86, 95% CI: 0.78, 0.95). Finally, no differences in sleep architecture were noted between former and never smokers. The results of this study show that cigarette smoking is independently associated with disturbances in sleep architecture, including a longer latency to sleep onset and a shift toward lighter stages of sleep. Nicotine in cigarette smoke and acute withdrawal from it may contribute to disturbances in sleep architecture.
Keywords: Aged; Arousal; Chi-Square Distribution; Female; Humans; Male; Middle Aged; Polysomnography; Prevalence; Regression Analysis; Risk Factors; Sleep Stages; Sleep Wake Disorders; Smoking; United States

Clinical course of mesenteric artery stenosis in elderly americans. - Wilson, David B; Mostafavi, Kian; Craven, Timothy E; Ayerdi, Juan; Edwards, Matthew S; Hansen, Kimberley J (Arch Intern Med, 2006)
BACKGROUND: To examine prospectively the relationship between stenosis or occlusion of the celiac and superior mesenteric arteries and symptoms of chronic intestinal ischemia in free-living elderly patients in the United States. METHODS: As part of an ancillary study to the Cardiovascular Health Study, participants in the Forsyth County (North Carolina) cohort underwent visceral duplex ultrasonography of the celiac and superior mesenteric arteries. Critical mesenteric artery stenosis (MAS) or occlusion was defined by Doppler flow ultrasound-derived criteria. Clinical outcomes were assessed at annual follow-up examinations and review of death certificates. Multivariate associations between the presence of MAS and all-cause mortality and adverse cardiovascular events were analyzed. Participants with MAS were contacted to determine the presence of symptoms consistent with chronic intestinal ischemia. RESULTS: Of 553 participants who underwent visceral duplex ultrasonography, 97 (17.5%) had disease of the celiac or superior mesenteric artery. At a mean follow-up of 6(1/2) years, 20 participants with MAS (20.6%) and 93 without MAS (20.4%) had died (relative risk, 1.01; 95% confidence interval, 0.66-1.55). No deaths were attributed to intestinal infarction. No association existed between the presence of MAS and prevalent cardiovascular disease, all-cause mortality, or adverse cardiovascular events. A questionnaire was completed by 71% of the surviving participants with MAS. No participant reported symptoms or weight loss consistent with chronic intestinal ischemia. CONCLUSIONS: Mesenteric artery stenosis was a common finding in free-living elderly patients. At long-term follow-up, the presence of asymptomatic MAS was not associated with death or adverse cardiovascular events. Participants with asymptomatic MAS by duplex ultrasonographic criteria did not experience intestinal infarction or develop chronic intestinal ischemia.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Comorbidity; Female; Humans; Male; Mesenteric Arteries; Mesenteric Vascular Occlusion; Proportional Hazards Models; Prospective Studies; Radiography; Risk Factors; Surveys and Questionnaires; Ultrasonography

Clinical significance of calcification of the fibrous skeleton of the heart and aortosclerosis in community dwelling elderly. The Cardiovascular Health Study (CHS). - Barasch, Eddy; Gottdiener, John S; Larsen, Emily K Marino; Chaves, Paulo H M; Newman, Anne B; Manolio, Teri A (Am Heart J, 2006)
BACKGROUND: Mitral annular calcification (MAC), aortic annular calcification (AAC), and aortic valve sclerosis (AVS) are associated with aging, and MAC and AVS are markers of advanced atherosclerosis. No studies have examined the prevalence and the clinical relevance of all 3 forms of calcification in a single free-living elderly population. METHODS: We used 2-dimensional echocardiography to evaluate MAC, AAC, AVS and all 3 combined in 3929 participants, mean age 76 +/- 5 years, 60% women, in the Cardiovascular Health Study, a prospective community-based observational study designed to assess cardiovascular disease (CVD) risk factors and outcomes in elderly persons. RESULTS: Mitral annular calcification was found in 1640 (42 %) subjects, AAC in 1710 (44 %), AVS in 2114 (54 %), and all 3 combined in 662 (17 %). The participants with these findings were older than those without them, and those with MAC had worse cardiovascular, renal, metabolic, and functional profile than those with AAC and AVS. Age-, sex-, and race-adjusted logistic regression analysis found a significant association between the 3 calcification categories and CVD, the strongest being between the combined group with congestive heart failure (odds ratio 2.04, 95% CI 1.34-3.09). In highly adjusted models, only MAC was associated with CVD, and the strength of association was related to the severity of MAC. CONCLUSIONS: In free-living elderly, MAC, AAC, and AVS are highly prevalent and are associated with CVD. Mitral annular calcification in particular has strong association with CVD, and with an adverse biomedical profile.
Keywords: Aged; Aortic Valve; Calcinosis; Female; Heart Valve Diseases; Humans; Male; Mitral Valve; Prevalence; Prospective Studies; Risk Factors; Sclerosis; Ultrasonography

Cystatin C and prognosis for cardiovascular and kidney outcomes in elderly persons without chronic kidney disease. - Shlipak, Michael G; Katz, Ronit; Sarnak, Mark J; Fried, Linda F; Newman, Anne B; Stehman-Breen, Catherine; Seliger, Stephen L; Kestenbaum, Brian; Psaty, Bruce; Tracy, Russell P; Siscovick, David S (Ann Intern Med, 2006)
BACKGROUND: Cystatin C is an alternative measure of kidney function that may have prognostic importance among elderly persons who do not meet standard criteria for chronic kidney disease (estimated glomerular filtration rate [GFR] > or =60 mL/min per 1.73 m2). OBJECTIVE: To evaluate cystatin C as a prognostic biomarker for death, cardiovascular disease, and incident chronic kidney disease among elderly persons without chronic kidney disease. DESIGN: Cohort study. SETTING: The Cardiovascular Health Study, a population-based cohort recruited from 4 communities in the United States. PARTICIPANTS: 4663 elderly persons. MEASUREMENTS: Measures of kidney function were creatinine-based estimated GFR by using the Modification of Diet in Renal Disease equation and cystatin C concentration. Outcomes were death, cardiovascular death, noncardiovascular death, heart failure, stroke, myocardial infarction, and incident chronic kidney disease during follow-up (median, 9.3 years). RESULTS: At baseline, 78% of participants did not have chronic kidney disease (estimated GFR > or =60 mL/min per 1.73 m2) and mean cystatin C concentration, creatinine concentration, and estimated GFR were 1.0 mg/L, 79.6 micromol/L (0.9 mg/dL), and 83 mL/min per 1.73 m2, respectively. Cystatin C concentrations (per SD, 0.18 mg/L) had strong associations with death (hazard ratio, 1.33 [95% CI, 1.25 to 1.40]), cardiovascular death (hazard ratio, 1.42 [CI, 1.30 to 1.54]), noncardiovascular death (hazard ratio, 1.26 [CI, 1.17 to 1.36]), incident heart failure (hazard ratio, 1.28 [CI, 1.17 to 1.40]), stroke (hazard ratio, 1.22 [CI, 1.08 to 1.38]), and myocardial infarction (hazard ratio, 1.20 [CI, 1.06 to 1.36]) among these participants. Serum creatinine concentrations had much weaker associations with each outcome and only predicted cardiovascular death. Participants without chronic kidney disease who had elevated cystatin C concentrations (> or =1.0 mg/L) had a 4-fold risk for progressing to chronic kidney disease after 4 years of follow-up compared with those with cystatin C concentrations less than 1.0 mg/L. LIMITATIONS: Because this study did not directly measure GFR or albuminuria, the extent to which cystatin C may be influenced by nonrenal factors was not determined and participants with albuminuria might have been misclassified as having no kidney disease. CONCLUSIONS: Among elderly persons without chronic kidney disease, cystatin C is a prognostic biomarker of risk for death, cardiovascular disease, and chronic kidney disease. In this setting, cystatin C seems to identify a "preclinical" state of kidney dysfunction that is not detected with serum creatinine or estimated GFR.
Keywords: Aged; Biomarkers; Cardiovascular Diseases; Creatinine; Cystatin C; Cystatins; Glomerular Filtration Rate; Humans; Kidney; Longitudinal Studies; Prognosis; Proportional Hazards Models; Renal Insufficiency, Chronic; Risk Factors

Depressive symptoms, vascular disease, and mild cognitive impairment: findings from the Cardiovascular Health Study. - Barnes, Deborah E; Alexopoulos, George S; Lopez, Oscar L; Williamson, Jeff D; Yaffe, Kristine (Arch Gen Psychiatry, 2006)
CONTEXT: Depressive symptoms are common in patients with dementia and may be associated with increased risk of developing dementia. It has been hypothesized that depressive symptoms and dementia may be attributable to underlying vascular disease in some older persons. OBJECTIVES: To test the hypotheses (1) that depressive symptoms are associated with increased risk of developing mild cognitive impairment (MCI), a preclinical state that often precedes dementia, and (2) that the association between depressive symptoms and MCI is attributable to underlying vascular disease. DESIGN: Prospective, population-based, longitudinal study. SETTING: Random sample of adults 65 years or older recruited from 4 US communities. PARTICIPANTS: Subjects were 2220 participants in the Cardiovascular Health Study Cognition Study with high cognitive function at baseline. Depressive symptoms were measured at baseline using the 10-item Center for Epidemiological Studies Depression Scale and were classified as none (0-2 points), low (3-7 points), and moderate or high (>/=8 points). Vascular disease measures at baseline included confirmed history of stroke, transient ischemic attack, diabetes mellitus, or hypertension; carotid artery stenosis; ankle-arm blood pressure index; and small or large infarcts or white matter disease on cerebral magnetic resonance imaging. Mild cognitive impairment was diagnosed after 6 years of follow-up based on the consensus of a team of dementia experts using standard clinical criteria. MAIN OUTCOME MEASURE: Diagnosis of MCI. RESULTS: Depressive symptoms at baseline were associated with increased risk of MCI (10.0%, 13.3%, and 19.7% for those with no, low, and moderate or high depressive symptoms, respectively). This association was diminished only slightly by adjustment for vascular disease measures and demographics. Vascular disease measures also were associated with increased risk of MCI, and these associations were not diminished by adjustment for depressive symptoms or demographics. CONCLUSION: Depressive symptoms were associated with increased risk of MCI, and this association was independent of underlying vascular disease.
Keywords: Aged; Cerebrovascular Disorders; Cognition Disorders; Comorbidity; Dementia; Dementia, Vascular; Depressive Disorder; Female; Follow-Up Studies; Geriatric Assessment; Humans; Longitudinal Studies; Male; Prospective Studies; Psychiatric Status Rating Scales; Risk Factors; Sampling Studies; Vascular Diseases

Education, cognitive test scores, and black-white differences in dementia risk. - Shadlen, Marie-Florence; Siscovick, David; Fitzpatrick, Annette L; Dulberg, Corinne; Kuller, Lewis H; Jackson, Sharon (J Am Geriatr Soc, 2006)
OBJECTIVES: To compare dementia risks of elderly black and white subjects and to determine whether differences in education and cognitive test scores contribute to the inconsistency in reported differences between these groups. DESIGN: Longitudinal, 6-year follow-up. PARTICIPANTS: Two thousand seven hundred eighty-six older black and white subjects in the Cardiovascular Health Study. MEASUREMENTS: Age, education (>10 years vs < or =10 years), Modified Mini-Mental State Examination score (3MS, < or =85 vs >85). Potential confounders were sex, depression, apolipoprotein E4 genotype, vascular disease, and baseline magnetic resonance imaging changes. RESULTS: White subjects with low education and black subjects with high education had twice the risk of dementia of white subjects with high education (95% confidence interval (CI)=1.5-2.4 and 95% CI=1.4-2.7); black subjects with low education had five times the risk of dementia (95% CI=3.4-7.7). Likewise, for subjects with low 3MSE scores, black subjects had 6.7 times the risk of dementia (95% CI=4.7-9.7) and white subjects had 2.7 times the risk of dementia (95% CI=2.2-3.5) as white subjects with high 3MSE scores. Finally, in Cox models, there was no significant black-white difference in dementia risk after adjustment for all confounders and baseline 3MSE. CONCLUSION: Black race was associated with greater dementia risk even after adjustment for education and other potential confounders. This black-white difference in dementia risk was markedly attenuated after adjustment for baseline cognitive screening scores. The apparent race effect may reflect gaps in the quality of education or differences in the trajectory of impaired cognitive function experienced by the two groups. Future investigations might take these findings into consideration for the design of studies evaluating black-white differences in dementia risk.
Keywords: African Continental Ancestry Group; Aged; Cognition; Dementia; Educational Status; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Male; Psychological Tests; Retrospective Studies; Risk Factors; United States

Factors associated with geographic variations in stroke incidence among older populations in four US communities. - El-Saed, Aiman; Kuller, Lewis H; Newman, Anne B; Lopez, Oscar; Costantino, Joseph; McTigue, Kathleen; Cushman, Mary; Kronmal, Richard (Stroke, 2006)
BACKGROUND AND PURPOSE: In the Cardiovascular Health Study (CHS), we previously observed lower stroke incidence in Allegheny County, PA compared with the other 3 study sites. The purpose of this study was to study possible reasons for the lower stroke incidence in Allegheny County. METHODS: CHS participants 65 years or older who were stroke-free at baseline (n=5639) were followed between 1989 to 1990 and 2000 for the development of stroke. Risk factors at baseline and their subsequent control were compared among both groups. Site-specific hazard ratios for stroke incidence were calculated using Cox regression models. RESULTS: The unadjusted hazard ratio for total stroke incidence in Forsyth County, NC; Sacramento County, CA; and Washington County, MD combined compared with Allegheny County, PA was 1.74 (95% CI: 1.42, 2.14). After adjustment for age and other traditional risk factors, there was modest reduction of the excess hazard in non-Allegheny sites compared with Allegheny County (hazard ratio=1.52, 95% CI: 1.17, 1.98). Between baseline and the seventh-year visits, control of hypertension, diabetes, lipids, smoking, atrial fibrillation and transient ischemic attack were similar across sites. White matter grade > or = 3 on the baseline brain MRI was less common in Allegheny County (25.8% versus 36.3%, respectively; P<0.001) and accounted for 25% of the excess hazard in non-Allegheny sites compared with Allegheny County. CONCLUSIONS: Site differences in stroke risk factors at baseline and subsequent control only partially explain site differences in stroke incidence. White matter grade as a possible integrated measure of exposure and control of risk factors may help in explaining geographic variations in stroke incidence.
Keywords: Aged; Brain; California; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Maryland; North Carolina; Pennsylvania; Proportional Hazards Models; Risk Assessment; Risk Factors; Stroke

Metabolic syndrome and cardiovascular disease in older people: The cardiovascular health study. - McNeill, Ann Marie; Katz, Ronit; Girman, Cynthia J; Rosamond, Wayne D; Wagenknecht, Lynne E; Barzilay, Joshua I; Tracy, Russell P; Savage, Peter J; Jackson, Sharon A (J Am Geriatr Soc, 2006)
OBJECTIVES: To assess the prospective association between metabolic syndrome (MetS) and cardiovascular disease (CVD) in older people and to evaluate the effect of lowering the threshold for impaired fasting glucose (IFG) on the prevalence of IFG and MetS and the risk of CVD. DESIGN: Prospective cohort study. SETTING: Four field centers in U.S. communities. PARTICIPANTS: Three thousand five hundred eighty-five subjects in the Cardiovascular Health Study free of diabetes mellitus and CVD at baseline (mean age 72, 62% female, 14% black). MEASUREMENTS: Baseline measures of MetS components and adjudicated incident CVD events. MetS (2001) was defined first using the original criteria from the Third Adult Treatment Panel Report of the National Cholesterol Education Program (> or =3 of the following: large waist circumference (women >88 cm, men >102 cm), elevated triglycerides (> or =1.70 mmol/L), low high-density lipoprotein cholesterol (men <1.04 mmol/L, women <1.30 mmol/L), elevated fasting glucose (6.1-6.9 mmol/L), and high blood pressure (> or =130/85 mmHg or self-reported use of medications for hypertension). Subjects were also classified according to the revised definition of the MetS (2005) that applies the lower threshold for fasting glucose (5.6-6.9 mmol/L). RESULTS: During follow-up (median 11 years), 818 coronary heart disease (CHD), 401 stroke, and 554 congestive heart failure (CHF) events occurred. Age- and race-adjusted hazard ratios (HRs) for CHD, stroke, and CHF were 1.30 (95% confidence interval (CI) = 1.07-1.57), 0.94 (95% CI = 0.73-1.21), and 1.40 (95% CI = 1.12-1.76) for women and 1.35 (95% CI = 1.10-1.66), 1.51 (95% CI = 1.08-2.12), and 1.47 (95% CI = 1.14-1.90) for men, respectively. Overall, women and men with MetS (2005) were 20% to 30% more likely to experience any CVD event than subjects without MetS (2005). Using the lower cut-point for IFG resulted in a near tripling in IFG prevalence (16% to 46%) and an additional 9% classified with MetS (2005) but HRs similar to those estimated from the original MetS (2001) criteria. High blood pressure was the component most strongly associated with incident CHD. CONCLUSION: Results from this study of an elderly, population-based cohort provide support for earlier investigations in primarily middle-aged populations that link the presence of MetS with the development of CVD and further underscore the importance of recognizing and treating its individual components, particularly high blood pressure.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Blood Glucose; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Fasting; Female; Humans; Incidence; Male; Metabolic Syndrome; Risk Factors; Sex Factors

Mortality and cardiovascular risk across the ankle-arm index spectrum: results from the Cardiovascular Health Study. - O'Hare, Ann M; Katz, Ronit; Shlipak, Michael G; Cushman, Mary; Newman, Anne B (Circulation, 2006)
BACKGROUND: A low ankle-arm index (AAI) is a strong predictor of mortality and cardiovascular events. A high AAI also appears to be associated with higher mortality risk in select populations. However, mortality and cardiovascular risk across the AAI spectrum have not been described in a more broadly defined population. METHODS AND RESULTS: We examined total and cardiovascular mortality and cardiovascular events across the AAI spectrum among 5748 participants in the Cardiovascular Health Study (CHS). The mean age of the sample population was 73+/-6 years, and the sample included 3289 women (57%) and 883 blacks (15%). The median duration of follow-up was 11.1 (0.1 to 12) years for mortality and 9.6 (0.1 to 12.1) years for cardiovascular events. There were 2311 deaths (953 of which were cardiovascular) and 1491 cardiovascular events during follow-up. After adjustment for potential confounders, AAI measurements < or =0.60 (hazard ratio [HR] 1.82, 95% CI 1.42 to 2.32), 0.61 to 0.7 (HR 2.08, 95% CI 1.61 to 2.69), 0.71 to 0.8 (HR 1.80, 95% CI 1.44 to 2.26), 0.81 to 0.9 (HR 1.73 95% CI 1.43 to 2.11), 0.91 to 1.0 (HR 1.40, 95% CI 1.20 to 1.63), and >1.40 (HR 1.57, 95% CI 1.07 to 2.31) were associated with higher mortality risk from all causes compared with the referent group (AAI 1.11 to 1.20). The pattern was similar for cardiovascular mortality. For cardiovascular events, risk was higher at all AAI levels <1 but not for AAI levels >1.4 (HR 1.00, 95% CI 0.57 to 1.74). The association of a high AAI with mortality was stronger in men than in women and in younger than in older cohort members. CONCLUSIONS: In a cohort of community-dwelling elders, mortality risk was higher than the referent category of 1.11 to 1.2 among participants with AAI values above the traditional cutpoint of 0.9 (ie, 0.91 to 1.0 and >1.4), and the specific association of AAI with mortality varied by age and gender.
Keywords: Aged; Ankle; Arm; Blood Pressure; Body Mass Index; Cholesterol, LDL; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Peripheral Vascular Diseases; Risk Factors; Smoking

New-onset diabetes and risk of all-cause and cardiovascular mortality: the Cardiovascular Health Study. - Smith, Nicholas L; Barzilay, Joshua I; Kronmal, Richard; Lumley, Thomas; Enquobahrie, Daniel; Psaty, Bruce M (Diabetes Care, 2006)
OBJECTIVE: Cardiovascular risk associated with new-onset diabetes is not well characterized. We hypothesized that risk of all-cause and cardiovascular mortality would be similar among participants with and without new-onset diabetes in the first years of follow-up and rise over time for new-onset diabetes. RESEARCH DESIGN AND METHODS: The Cardiovascular Health Study (CHS) is a longitudinal study of cardiovascular risk factors in adults aged > or =65 years. We used CHS participants to define a cohort (n = 282) with new-onset diabetes during 11 years of follow-up. New-onset diabetes was defined by initiation of antidiabetes medication or by fasting plasma glucose >125 mg/dl among CHS participants without diabetes at study entry. Three CHS participants without diabetes were matched for age, sex, and race to each participant with new-onset diabetes at the time of diabetes identification (n = 837). Survival analysis provided adjusted hazard ratios (HRs) for all-cause and cardiovascular mortality. RESULTS: During a median of 5.9 years of follow-up, there were 352 deaths, of which 41% were cardiovascular. In adjusted analyses, new-onset diabetes was associated with an HR of 1.9 (95% CI 1.4-2.5) for all-cause and 2.2 (1.4-3.4) for cardiovascular mortality compared with no diabetes. Mortality risks were elevated within 2 years of onset, especially cardiovascular risk (4.3 [95% CI 1.7-10.8]), and did not increase over time. CONCLUSIONS: Our findings indicate that there may be a mortality differential soon after diabetes onset in older adults and suggest that long-term macrovascular damage from atherosclerosis may not be primarily responsible for increased risk.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Blood Glucose; Cardiovascular Diseases; Diabetes Complications; Diabetes Mellitus; Follow-Up Studies; Humans; Kaplan-Meier Estimate; Risk Factors; Survival Rate; Time Factors

Quantitative retinal venular caliber and risk of cardiovascular disease in older persons: the cardiovascular health study. - Wong, Tien Yin; Kamineni, Aruna; Klein, Ronald; Sharrett, A Richey; Klein, Barbara E; Siscovick, David S; Cushman, Mary; Duncan, Bruce B (Arch Intern Med, 2006)
BACKGROUND: Small vessel disease may contribute to the risk of cardiovascular disease in older persons. We describe the relation of retinal vascular caliber to incident coronary heart disease (CHD) and stroke in elderly persons. METHODS: Prospective population-based cohort study composed of 1992 men and women aged 69 to 97 years living in 4 US communities. Retinal arteriolar and venular calibers were measured from retinal photographs using a computer-assisted method. Incident CHD and stroke events were ascertained using standardized methods. RESULTS: After 5 years of follow-up, there were 115 incident CHD events and 113 incident stroke events. Participants with larger retinal venular caliber had a higher incidence of CHD (11.7%; 95% confidence interval [CI], 8.7%-15.8%, vs 8.1%; 95% CI, 5.7%-11.6%), comparing largest with smallest venular caliber quartiles, and stroke (8.4%; 95% CI, 6.0-11.7, vs 5.8%; 95% CI, 3.9-8.4). At multivariable analysis, controlling for age, sex, race, arteriolar caliber, systolic and diastolic blood pressure, diabetes, glucose concentration, cigarette smoking, pack-years of smoking, and high-density-lipoprotein and low-density lipoprotein cholesterol levels, larger retinal venular caliber was associated with incident CHD (rate ratio, 3.0; 95% CI, 1.6-5.7, comparing largest with smallest venular caliber quartiles; P(trend) = .001) and incident stroke (rate ratio, 2.2; 95% CI, 1.1-4.3; P(trend) = .02). Additional adjustment for C-reactive protein and common and internal carotid artery intimal-media thickness had minimal effect on these associations. At multivariable analysis, smaller retinal arteriolar caliber was associated with incident CHD (rate ratio, 2.0; 95% CI, 1.1-3.7, comparing largest with smallest arteriolar caliber quartiles; P = .03) but not stroke (rate ratio,1.1; 95% CI, 0.5-2.2; P = .73). CONCLUSION: Larger retinal venular caliber is independently associated with risk of cardiovascular disease in elderly persons.
Keywords: Aged; Aged, 80 and over; Algorithms; Cardiovascular Diseases; Cohort Studies; Female; Humans; Image Processing, Computer-Assisted; Incidence; Male; Photography; Prospective Studies; Retinal Diseases; Retinal Vein; Retinal Vessels; Risk Factors; Stroke; United States

Regression dilution methods for meta-analysis: assessing long-term variability in plasma fibrinogen among 27,247 adults in 15 prospective studies. - Wood, Angela M; White, Ian; Thompson, Simon G; Lewington, Sarah; Danesh, John (Int J Epidemiol, 2006)
BACKGROUND: Within-person variability in measured values of a risk factor can bias its association with disease. The extent of this regression dilution bias for plasma fibrinogen was investigated using repeat measurement data collected at varying time intervals on 27 247 adults in 15 prospective studies. METHODS: Regression dilution ratios (RDRs) were estimated from a linear regression of repeat measurements on baseline values in each study and for each time interval, and pooled allowing for within- and between-study heterogeneity. RDRs were estimated both without and with adjustment for confounders, and factors were investigated that might influence the RDRs. RESULTS: The unadjusted overall RDR was 0.51 (95% CI: 0.47, 0.55), which decreased to 0.46 (95% CI: 0.42, 0.49) after adjustment for age, sex and measured values of other established vascular risk factors. The RDR did not vary materially by assay method, age, sex or smoking status, but decreased at higher levels of baseline fibrinogen. CONCLUSION: It is appropriate to use an RDR of 0.5 to correct approximately for regression dilution bias in plasma fibrinogen values; however, this correction factor may produce somewhat conservative hazard ratios in adjusted analyses, at higher fibrinogen concentrations and in follow-up beyond a decade. More generally, the methods described in this report have widespread applicability to quantifying regression dilution bias in repeatability data from multiple prospective studies.
Keywords: Adult; Age Factors; Bias; Cardiovascular Diseases; Female; Fibrinogen; Humans; Male; Meta-Analysis as Topic; Prospective Studies; Regression Analysis; Risk Factors; Sex Factors; Smoking; Time Factors

The sensitivity and specificity of markers for event times. - Cai, Tianxi; Pepe, Margaret Sullivan; Zheng, Yingye; Lumley, Thomas; Jenny, Nancy Swords (Biostatistics, 2006)
The statistical literature on assessing the accuracy of risk factors or disease markers as diagnostic tests deals almost exclusively with settings where the test, Y, is measured concurrently with disease status D. In practice, however, disease status may vary over time and there is often a time lag between when the marker is measured and the occurrence of disease. One example concerns the Framingham risk score (FR-score) as a marker for the future risk of cardiovascular events, events that occur after the score is ascertained. To evaluate such a marker, one needs to take the time lag into account since the predictive accuracy may be higher when the marker is measured closer to the time of disease occurrence. We therefore consider inference for sensitivity and specificity functions that are defined as functions of time. Semiparametric regression models are proposed. Data from a cohort study are used to estimate model parameters. One issue that arises in practice is that event times may be censored. In this research, we extend in several respects the work by Leisenring et al. (1997) that dealt only with parametric models for binary tests and uncensored data. We propose semiparametric models that accommodate continuous tests and censoring. Asymptotic distribution theory for parameter estimates is developed and procedures for making statistical inference are evaluated with simulation studies. We illustrate our methods with data from the Cardiovascular Health Study, relating the FR-score measured at enrollment to subsequent risk of cardiovascular events.
Keywords: Aged; Aged, 80 and over; Biomarkers; Biometry; Cardiovascular Diseases; Female; Humans; Male; Models, Statistical; Risk Factors; ROC Curve; Sensitivity and Specificity; Time Factors

Soluble intracellular adhesion molecule-1 is associated with cardiovascular disease risk and mortality in older adults. - Jenny, N S; Arnold, A M; Kuller, L H; Sharrett, A R; Fried, L P; Psaty, B M; Tracy, R P (J Thromb Haemost, 2006)
BACKGROUND: Intracellular adhesion molecule-1 (ICAM-1) regulates leukocyte-endothelial attachment, a process crucial to atherosclerosis. Circulating soluble ICAM-1 (sICAM-1) may serve as a marker of cardiovascular disease (CVD) progression. OBJECTIVES: We examined the association of sICAM-1 with measures of subclinical CVD and risk of incident CVD events and death in older men and women (age > or = 65 years) from the Cardiovascular Health Study. METHODS: Selected participants were free of clinical CVD at baseline. Non-exclusive incident case groups were angina (n = 534), myocardial infarction (n = 304), stroke (n = 327), and death (n = 842; CVD death = 310). A total 643 subjects were free of events during follow-up. RESULTS: sICAM-1 was positively associated with C-reactive protein, interleukin-6 and fibrinogen and measures of subclinical CVD in these older men and women. In Cox regression models adjusted for age, gender, and race, increasing levels of sICAM-1 were associated with increased risk of all cause mortality in men and women. Hazard ratios (95% confidence intervals) for a one standard deviation increase in sICAM-1 (89.7 ng mL(-1)) were 1.3 (1.1-1.4) in men and 1.2 (1.1-1.3) in women. sICAM-1 was associated with increased risk of CVD death in women (1.2; 1.0-1.5), but not men (1.1; 0.9-1.3). There were no associations of sICAM-1 with non-fatal CVD events. CONCLUSIONS: While sICAM-1 was associated with death in older men and women, there was a more marked association between sICAM-1 and CVD death in women.
Keywords: Aged; Aged, 80 and over; Angina Pectoris; Biomarkers; Cardiovascular Diseases; Female; Humans; Incidence; Intercellular Adhesion Molecule-1; Male; Mortality; Myocardial Infarction; Regression Analysis; Risk Factors; Sex Factors; Solubility; Stroke

Subclinical atherosclerosis and the risk of future venous thrombosis in the Cardiovascular Health Study. - van der Hagen, P B; Folsom, A R; Jenny, N S; Heckbert, S R; O'Meara, E S; Reich, L M; Rosendaal, F R; Cushman, M (J Thromb Haemost, 2006)
BACKGROUND: Recent reports have suggested an association of atherosclerosis with risk of venous thrombosis. OBJECTIVE: To confirm whether subclinical atherosclerosis is a risk factor for venous thrombosis (VT) among men and women age 65 and older. METHODS: Participants of the Cardiovascular Health Study (n = 4,108) without baseline clinical cardiovascular disease, anticoagulant use or previous VT were followed for a median of 11.7 years after non-invasive assessment of subclinical atherosclerosis using carotid ultrasound (intima-media thickness and presence of plaques), ankle-brachial blood pressure index and electrocardiogram. Each event was classified as idiopathic or secondary. We used Cox proportional hazards regression to estimate the relative risk of overall and idiopathic VT for individuals with and without baseline subclinical atherosclerosis. RESULTS: There were 133 first time VT events. No subclinical atherosclerosis measures were associated with increased risk of overall or idiopathic VT. The adjusted relative risks of overall and idiopathic VT for presence of any type of subclinical disease were 0.60 (95% confidence interval 0.39-0.91) and 0.32 (0.18-0.59), respectively. Most of this association was explained by an inverse association of high-risk carotid plaques (prevalent in 54% of those at risk) with VT. CONCLUSION: Non-invasively measured subclinical atherosclerosis was not associated with increased risk of overall or idiopathic VT in this observational study. Carotid plaques and arterial events during follow up were inversely associated, a finding that requires further study.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Carotid Artery Thrombosis; Cohort Studies; Female; Humans; Male; Proportional Hazards Models; Risk Factors; Ultrasonography; Venous Thrombosis

Thyroid status, cardiovascular risk, and mortality in older adults. - Cappola, Anne R; Fried, Linda P; Arnold, Alice M; Danese, Mark D; Kuller, Lewis H; Burke, Gregory L; Tracy, Russell P; Ladenson, Paul W (JAMA, 2006)
CONTEXT: Previous studies have suggested that subclinical abnormalities in thyroid-stimulating hormone levels are associated with detrimental effects on the cardiovascular system. OBJECTIVE: To determine the relationship between baseline thyroid status and incident atrial fibrillation, incident cardiovascular disease, and mortality in older men and women not taking thyroid medication. DESIGN, SETTING, AND PARTICIPANTS: A total of 3233 US community-dwelling individuals aged 65 years or older with baseline serum thyroid-stimulating hormone levels were enrolled in 1989-1990 in the Cardiovascular Health Study, a large, prospective cohort study. MAIN OUTCOME MEASURES: Incident atrial fibrillation, coronary heart disease, cerebrovascular disease, cardiovascular death, and all-cause death assessed through June 2002. Analyses are reported for 4 groups defined according to thyroid function test results: subclinical hyperthyroidism, euthyroidism, subclinical hypothyroidism, and overt hypothyroidism. RESULTS: Individuals with overt thyrotoxicosis (n = 4) were excluded because of small numbers. Eighty-two percent of participants (n = 2639) had normal thyroid function, 15% (n = 496) had subclinical hypothyroidism, 1.6% (n = 51) had overt hypothyroidism, and 1.5% (n = 47) had subclinical hyperthyroidism. After exclusion of those with prevalent atrial fibrillation, individuals with subclinical hyperthyroidism had a greater incidence of atrial fibrillation compared with those with normal thyroid function (67 events vs 31 events per 1000 person-years; adjusted hazard ratio, 1.98; 95% confidence interval, 1.29-3.03). No differences were seen between the subclinical hyperthyroidism group and euthyroidism group for incident coronary heart disease, cerebrovascular disease, cardiovascular death, or all-cause death. Likewise, there were no differences between the subclinical hypothyroidism or overt hypothyroidism groups and the euthyroidism group for cardiovascular outcomes or mortality. Specifically, individuals with subclinical hypothyroidism had an adjusted hazard ratio of 1.07 (95% confidence interval, 0.90-1.28) for incident coronary heart disease. CONCLUSION: Our data show an association between subclinical hyperthyroidism and development of atrial fibrillation but do not support the hypothesis that unrecognized subclinical hyperthyroidism or subclinical hypothyroidism is associated with other cardiovascular disorders or mortality.
Keywords: Aged; Atrial Fibrillation; Cardiovascular Diseases; Female; Humans; Hyperthyroidism; Hypothyroidism; Male; Proportional Hazards Models; Risk Factors; Thyroid Gland; Thyrotropin

Usefulness of aortic root dimension in persons > or = 65 years of age in predicting heart failure, stroke, cardiovascular mortality, all-cause mortality and acute myocardial infarction (from the Cardiovascular Health Study). - Gardin, Julius M; Arnold, Alice M; Polak, Joseph; Jackson, Sharon; Smith, Vivienne; Gottdiener, John (Am J Cardiol, 2006)
Echocardiographic measures of left ventricular (LV) function and structure as well as left atrial size have been reported to predict adverse cardiovascular disease (CVD) outcomes. Although anatomic changes of the aortic root are likely to reflect effects of hypertension and atherosclerosis, few data are available on the predictive value of aortic root dimension (ARD) for outcome in free-living populations. The purpose of this investigation was to determine whether in a cohort of patients aged > or = 65 years ARD was associated with traditional coronary heart disease (CHD) risk factors and with 10-year incident CVD outcomes. In the National Heart, Lung, and Blood Institute-sponsored Cardiovascular Health Study, 3,933 free-living black and white men and women > or = 65 years of age without prevalent CVD had 2-dimensional directed M-mode echocardiographic measurements of ARD as part of a comprehensive evaluation. ARD was associated with age and gender (greater in men) but not race. ARD was also positively associated with diastolic blood pressure, LV hypertrophy, major electrocardiographic abnormalities, and other echocardiographic measures, including LV mass, ventricular septal and posterior wall thickness, and LV dimension. After adjustment for other known risk factors, high ARD was associated with an increased risk for incident congestive heart failure (CHF) in men (hazard ratio for upper compared with all other quintiles 1.47, p = 0.014), stroke in men and women (hazard ratio 1.39 per cm, p = 0.015), CVD mortality in men and women (hazard ratio 1.48 per cm, p = 0.007), and total mortality in men and women taking antihypertensive medications (hazard ratio 1.46 per cm, p = 0.007), but not with incident myocardial infarction (MI) (hazard ratio 0.89, p = 0.39). In conclusion, in a cohort of patients aged > or = 65 years without clinical CVD at baseline, ARD was associated with several CHD risk factors and measures of subclinical disease and was predictive of incident CHF, stroke, CVD mortality, and all-cause mortality, but not of incident MI.
Keywords: Age Factors; Aged; Aged, 80 and over; Aorta; Cardiovascular Diseases; Echocardiography, Doppler; Female; Heart Failure; Humans; Hypertrophy, Left Ventricular; Male; Multicenter Studies as Topic; Myocardial Infarction; Predictive Value of Tests; Risk Factors; Sex Factors; Stroke

ABO blood group, other risk factors and incidence of venous thromboembolism: the Longitudinal Investigation of Thromboembolism Etiology (LITE). - Ohira, T; Cushman, M; Tsai, M Y; Zhang, Y; Heckbert, S R; Zakai, N A; Rosamond, W D; Folsom, A R (J Thromb Haemost, 2007)
BACKGROUND: Numerous case-control studies have reported higher prevalence of non-O blood type among venous thromboembolism (VTE) patients than controls, but potential mechanisms or effect modifiers for the association are not fully established. PATIENTS/METHODS: Using a nested case-control design combining the Atherosclerosis Risk in Communities and the Cardiovascular Health Study cohort, ABO blood type and other VTE risk factors were measured on pre-event blood samples of 492 participants who subsequently developed VTE and 1008 participants who remained free of VTE. RESULTS: A total of 64.4% of cases and 52.5% of controls had non-O blood type. Among controls, mean values of factor VIIIc (FVIIIc) and von Willebrand factor among the non-O blood type group were higher than among the O group. Compared with O blood type, the age-adjusted odds ratio (OR) of VTE for non-O blood type was 1.64 (95% CI, 1.32-2.05) and was similar for the two parent studies and race groups. Further adjustment for sex, race, body mass index, diabetes mellitus and FVIIIc reduced the OR: 1.31 (95% CI, 1.02-1.68). Factor V Leiden (FV Leiden) appeared to modify the non-O blood type association with VTE in a supra-additive fashion, with an age-, sex- and race-adjusted OR of 6.77 (95% CI, 3.65-12.6) for having both risk factors. CONCLUSIONS: Non-O blood type was independently associated with risk of VTE, and added to the risk associated with FV Leiden.
Keywords: ABO Blood-Group System; Aged; Case-Control Studies; Diabetes Complications; Factor V; Factor VIII; Female; Humans; Longitudinal Studies; Male; Middle Aged; Risk Factors; Thromboembolism; Venous Thrombosis; von Willebrand Factor

Alcohol consumption and lipoprotein subclasses in older adults. - Mukamal, Kenneth J; Mackey, Rachel H; Kuller, Lewis H; Tracy, Russell P; Kronmal, Richard A; Mittleman, Murray A; Siscovick, David S (J Clin Endocrinol Metab, 2007)
CONTEXT: Limited evidence suggests that alcohol intake may be associated with lipoprotein subclass distribution, which could mediate its relationship with coronary heart disease. OBJECTIVES: The objective was to determine the relationship of alcohol intake with lipoprotein particle subclasses. DESIGN, SETTING, AND PARTICIPANTS: The study included a cross-sectional analysis of 1850 participants of the Cardiovascular Health Study aged 65 yr and older and free of clinical cardiovascular disease. MAIN OUTCOME MEASURE: Lipoprotein subclass distribution was measured with nuclear magnetic resonance spectroscopy, according to self-reported alcohol intake. RESULTS: Alcohol intake was associated with total low-density lipoprotein (LDL) particles in a U-shaped manner. Consumers of one or more drinks per week had the highest number of large LDL particles, whereas consumers of 7-13 drinks per week had the lowest number of small LDL particles. Alcohol intake was strongly positively associated with large- and medium-sized high-density lipoprotein (HDL) particles but had an inverse relationship with concentrations of small HDL particles and small- and medium-sized very-low-density lipoprotein particles. Average particle sizes of all three lipoproteins were positively associated with alcohol intake. Associations were generally stronger among women than men but in similar directions. Beverage type did not consistently modify these findings. CONCLUSIONS: Alcohol intake is associated with less total LDL particles, lower levels of small LDL, HDL, and very-low-density lipoprotein particles, and higher levels of large LDL and medium- and large-sized HDL particles in older adults free of prevalent clinical cardiovascular disease.
Keywords: Aged; Alcohol Drinking; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Cholesterol, VLDL; Coronary Disease; Cross-Sectional Studies; Female; Humans; Magnetic Resonance Spectroscopy; Male; Prevalence; Risk Factors

Alcohol consumption and risk and prognosis of atrial fibrillation among older adults: the Cardiovascular Health Study. - Mukamal, Kenneth J; Psaty, Bruce M; Rautaharju, Pentti M; Furberg, Curt D; Kuller, Lewis H; Mittleman, Murray A; Gottdiener, John S; Siscovick, David S (Am Heart J, 2007)
BACKGROUND: The relationship of alcohol consumption with risk of atrial fibrillation (AF) is inconsistent in previous studies, and its relationship with prognosis of AF is undetermined. METHODS: As part of the Cardiovascular Health Study, a population-based cohort of adults 65 years and older from 4 US communities, 5609 participants reported their use of beer, wine, and spirits yearly. We identified cases of AF with routine study electrocardiograms and validated discharge diagnoses from hospitalizations. RESULTS: A total of 1232 cases of AF were documented during a mean of 9.1 years of follow-up. Compared with long-term abstainers, the multivariable-adjusted hazard ratios were 1.25 (95% CI, 1.02-1.54) among former drinkers, 1.09 (95% CI, 0.94-1.28) among consumers of less than 1 drink per week, 1.00 (95% CI, 0.84-1.19) among consumers of 1 to 6 drinks per week, 1.06 (95% CI, 0.82-1.37) among consumers of 7 to 13 drinks per week, and 1.09 (95% CI, 0.88-1.37) among consumers of 14 or more drinks per week (P trend = 0.64). In analyses of mortality among participants with AF, the hazard ratios were 1.27 (95% CI, 1.06-1.52) among former drinkers, 0.94 (95% CI, 0.76-1.18) among consumers of less than 1 drink per week, 0.98 (95% CI, 0.78-1.23) among consumers of 1 to 6 drinks per week, 0.73 (95% CI, 0.51-1.03) among consumers of 7 to 13 drinks per week, and 0.81 (95% CI, 0.59-1.11) among consumers of 14 or more drinks per week (P trend = 0.12). CONCLUSIONS: Current moderate alcohol consumption is not associated with risk of AF or with risk of death after diagnosis of AF, but former drinking identifies individuals at higher risk.
Keywords: Aged; Alcohol Drinking; Atrial Fibrillation; Female; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Prognosis; Risk Factors

Alcohol consumption, bone density, and hip fracture among older adults: the cardiovascular health study. - Mukamal, K J; Robbins, J A; Cauley, J A; Kern, L M; Siscovick, D S (Osteoporos Int, 2007)
INTRODUCTION: Previous studies have found inconsistent relationships of alcohol consumption with risk of hip fracture, and the importance of bone mineral density and risk of falls in mediating such a relationship has not been determined. METHODS: As part of the Cardiovascular Health Study, a population-based cohort study of adults aged 65 years and older from four U.S. communities, 5,865 participants reported their use of beer, wine, and liquor yearly. We identified cases of hip fracture unrelated to malignancy or motor vehicle accidents using hospitalization discharge diagnoses. A subgroup of 1,567 participants in two communities underwent dual-energy x-ray absorptiometry scans to assess bone mineral density. RESULTS: A total of 412 cases of hip fracture occurred during an average of 12 years of follow-up. There was a significant U-shaped relationship between alcohol intake and risk of hip fracture (p quadratic 0.02). Compared with long-term abstainers, the adjusted hazard ratios for hip fracture were 0.78 (95% confidence interval [CI], 0.61-1.00) among consumers of up to 14 drinks per week and 1.18 (95% CI, 0.77-1.81) among consumers of 14 or more drinks per week. Alcohol intake was associated with bone mineral density of the total hip and femoral neck in a stepwise manner, with approximately 5% (95% CI, 1%-9%) higher bone density among consumers of 14 or more drinks per week than among abstainers. These relationships were all similar among men and women. CONCLUSIONS: Among older adults, moderate alcohol consumption has a U-shaped relationship with risk of hip fracture, but a graded positive relationship with bone mineral density at the hip.
Keywords: Absorptiometry, Photon; Aged; Alcohol Drinking; Alcoholic Beverages; Apolipoproteins E; Bone Density; Female; Femur Neck; Genotype; Hip; Hip Fractures; Humans; Longitudinal Studies; Male; Risk Assessment; Risk Factors; Sex Distribution; United States

Apolipoprotein e gene and age-related maculopathy in older individuals: the cardiovascular health study. - Tikellis, Gabriella; Sun, Cong; Gorin, Michael B; Klein, Ronald; Klein, Barbara E K; Larsen, Emily K Marino; Siscovick, David S; Hubbard, Larry D; Wong, Tien Y (Arch Ophthalmol, 2007)
OBJECTIVE: To examine the association between the apolipoprotein E (APOE) gene and age-related maculopathy (ARM) in an older population. METHODS: Two thousand one hundred seventy persons 65 years and older sampled from 4 US communities had ARM signs assessed from retinal photographs using a modified Wisconsin Age-Related Maculopathy Grading System. DNA extracted from blood samples was analyzed for common APOE alleles. RESULTS: After controlling for age, sex, cigarette smoking, and other factors, white participants carrying the epsilon2 allele had an increased risk of late ARM (odds ratio, 2.53 [95% confidence interval, 1.08-5.90]) while carriers of the epsilon4 allele had a lower risk of late ARM (odds ratio, 0.69 [95% confidence interval, 0.19-2.50]). There were too few late ARM cases in African American individuals for analysis. CONCLUSION: APOE polymorphism is associated with late ARM in older white persons 65 years and older. Consistent with previous studies, the APOE epsilon2 allele is associated with a significant increased risk of late ARM development, whereas the epsilon4 allele may confer some protection.
Keywords: African Americans; Aged; Aged, 80 and over; Alleles; Apolipoprotein E2; Apolipoprotein E3; Apolipoprotein E4; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genotype; Humans; Macular Degeneration; Male; Odds Ratio; Polymorphism, Genetic; Risk Factors

Are microvascular abnormalities in the retina associated with depression symptoms? The Cardiovascular Health Study. - Sun, Cong; Tikellis, Gabriella; Klein, Ronald; Steffens, David C; Larsen, Emily K Marino; Siscovick, David S; Klein, Barbara E K; Wong, Tien Y (Am J Geriatr Psychiatry, 2007)
OBJECTIVE: Depression has been linked with vascular risk factors and stroke. The authors examined the relationship between retinal microvascular abnormalities and depression symptoms in an elderly population. METHODS: The Cardiovascular Health Study is a population-based study conducted in four U.S. communities initiated in 1989-1990. A total of 2,420 persons aged 65 years and older were included in the current analyses. During the 1997-1998 examination, retinal photographs were performed and assessed for retinal microvascular abnormalities (retinopathy, focal arteriolar narrowing, arteriovenous nicking, generalized retinal arteriolar narrowing, and generalized retinal venular dilation) according to standardized methods. Depression symptoms were assessed by a modified version of the Centers for Epidemiologic Studies Depression (CES-D) scale annually from 1989 through 1997-1998 and was defined as a CES-D score of >9. RESULTS: Participants with retinal microvascular abnormalities were not more likely to have depression symptoms, with adjusted odds ratio (OR) (95% confidence intervals) of 1.08 (0.71-1.65) for retinopathy, OR 1.09 (0.71-1.68) for focal arteriolar narrowing, OR 0.85 (0.52-1.40) for arteriovenous nicking, OR 0.97 (0.70-1.34) for generalized arteriolar narrowing, and OR 0.79 (0.56-1.12) for generalized venular dilation. Retinal microvascular abnormalities were not related to depression symptoms in multinomial logistic regression comparing the three top quartiles of the depression CES-D scores with the lowest quartile. CONCLUSIONS: Our study did not find an association between retinal microvascular abnormalities and depression symptoms in older people.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cardiovascular Diseases; Cohort Studies; Comorbidity; Cross-Sectional Studies; Depression; Female; Fluorescein Angiography; Humans; Male; Microcirculation; Personality Inventory; Retinal Artery Occlusion; Retinal Diseases; Retinal Vein Occlusion; Risk Factors; Statistics as Topic; United States

Association of carotid artery intima-media thickness, plaques, and C-reactive protein with future cardiovascular disease and all-cause mortality: the Cardiovascular Health Study. - Cao, Jie J; Arnold, Alice M; Manolio, Teri A; Polak, Joseph F; Psaty, Bruce M; Hirsch, Calvin H; Kuller, Lewis H; Cushman, Mary (Circulation, 2007)
BACKGROUND: Carotid atherosclerosis, measured as carotid intima-media thickness or as characteristics of plaques, has been linked to cardiovascular disease (CVD) and to C-reactive protein (CRP) levels. We investigated the relationship between carotid atherosclerosis and CRP and their joint roles in CVD prediction. METHODS AND RESULTS: Of 5888 participants in the Cardiovascular Health Study, an observational study of adults aged > or = 65 years, 5020 without baseline CVD were included in the analysis. They were followed up for as long as 12 years for CVD incidence and all-cause mortality after baseline ultrasound and CRP measurement. When CRP was elevated (> 3 mg/L) among those with detectable atherosclerosis on ultrasound, there was a 72% (95% CI, 1.46 to 2.01) increased risk for CVD death and a 52% (95% CI, 1.37 to 1.68) increased risk for all-cause mortality. Elevated CRP in the absence of atherosclerosis did not increase CVD or all-cause mortality risk. The proportion of excess risk attributable to the interaction of high CRP and atherosclerosis was 54% for CVD death and 79% for all-cause mortality. Addition of CRP or carotid atherosclerosis to conventional risk factors modestly increased in the ability to predict CVD, as measured by the c statistic. CONCLUSIONS: In older adults, elevated CRP was associated with increased risk for CVD and all-cause mortality only in those with detectable atherosclerosis based on carotid ultrasound. Despite the significant associations of CRP and carotid atherosclerosis with CVD, these measures modestly improve the prediction of CVD outcomes after one accounts for the conventional risk factors.
Keywords: African Americans; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Carotid Artery Diseases; Cohort Studies; Comorbidity; Diabetes Mellitus; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Hyperlipidemias; Hypertension; Incidence; Inflammation; Kaplan-Meier Estimate; Male; Mass Screening; Mortality; Myocardial Infarction; Obesity; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; ROC Curve; Smoking; Stroke; Survival Analysis; Tunica Intima; Tunica Media; Ultrasonography; United States

Association of kidney function with incident hip fracture in older adults. - Fried, Linda F; Biggs, Mary Louise; Shlipak, Michael G; Seliger, Stephen; Kestenbaum, Bryan; Stehman-Breen, Catherine; Sarnak, Mark; Siscovick, David; Harris, Tamara; Cauley, Jane; Newman, Anne B; Robbins, John (J Am Soc Nephrol, 2007)
Kidney dysfunction is associated with bone loss, and patients with ESRD have an increased risk for hip fracture. However, the association of mild to moderate kidney disease with hip fracture has not been studied previously. The association of kidney function with incident hip fracture was examined among participants in the Cardiovascular Health Study, a community-based cohort of older individuals. The primary measure of kidney function was serum cystatin C, a measure that does not depend on lean mass. Hip fractures were identified using International Classification of Diseases, Ninth Revision codes for hospitalizations. A total of 4699 individuals had cystatin C measured in 1992 to 1993 and did not have a hip fracture before cystatin C measurement. The association of kidney function with hip fracture was analyzed with Cox proportional hazards models. Analyses were conducted separately for men and women. After a mean follow-up of 7.1 yr, 195 incident hip fractures occurred in women and 79 occurred in men. Higher cystatin C levels were associated with a higher risk for fracture in women (hazard ratio [HR] 1.26; 95% confidence interval [CI] 1.14 to 1.38 per SD) and in men (HR 1.27; 95% CI 1.11 to 1.46). After multivariable adjustment, higher cystatin C levels were significantly associated with hip fracture in women (HR 1.16; 95% CI 1.01, 1.33) but not in men (HR 1.14; 95% CI 0.86 to 1.52), although the magnitude of the association was similar. Kidney dysfunction, as assessed by cystatin C, is associated with an increased risk for hip fracture. Further studies are needed to evaluate potential mediators of this relationship and to assess whether interventions can decrease this risk.
Keywords: Aged; Aged, 80 and over; Cystatin C; Cystatins; Female; Hip Fractures; Humans; Kidney; Kidney Failure, Chronic; Longitudinal Studies; Male; Osteoporosis; Prospective Studies; Risk Factors; Sex Factors

Association of physical activity with sleep-disordered breathing. - Quan, Stuart F; O'Connor, George T; Quan, Jason S; Redline, Susan; Resnick, Helaine E; Shahar, Eyal; Siscovick, David; Sherrill, Duane L (Sleep Breath, 2007)
This study was performed to determine whether there is a protective association between participation in vigorous or vigorous/moderately vigorous physical activity and the prevalence of sleep-disordered breathing (SDB). Polysomnographic and questionnaire data from the baseline examination of 4,275 participants in the Sleep Heart Health Study (SHHS) were analyzed in relation to information on amount of physical activity and other potentially relevant factors collected from five SHHS parent cohorts (Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, Framingham Heart Study, Strong Heart Study, and Tucson Epidemiologic Study of Airways Obstructive Diseases). Logistic regression models were fitted to determine if amount and strenuousness of physical activity was associated with the presence of SDB. At least 3 h per week of vigorous physical activity reduced the odds of SDB, defined as a respiratory disturbance index (RDI) of at least 15 apneas/hypopneas per hour (Adjusted OR, 0.68; 95%CI, 0.51-0.91). A qualitatively similar but slightly weaker association was observed when SDB was defined as a RDI > or = 10 per hour (Adjusted OR, 0.81; 95%CI, 0.64-1.02). These findings remained after adjustment for sleepiness and restricting analyses to participants with good health. Three or more hours of moderately vigorous or vigorous physical activity also appeared to confer some protection against SDB, but these associations were weaker. Gender- and obesity-stratified analyses suggested that the protective association between physical activity and SDB occurred primarily in men and those who were obese. A program of regular vigorous physical activity of at least 3 h per week may be a useful adjunctive treatment modality for SDB, but this association needs confirmation with a prospective clinical trial.
Keywords: Adult; Cardiac Rehabilitation; Cardiovascular Diseases; Cohort Studies; Exercise; Female; Humans; Longitudinal Studies; Male; Middle Aged; Obesity; Polysomnography; Pulmonary Disease, Chronic Obstructive; Pulmonary Ventilation; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Sleep Apnea, Obstructive; Sleep Stages; Weight Loss

Association of total insulin-like growth factor-I, insulin-like growth factor binding protein-1 (IGFBP-1), and IGFBP-3 levels with incident coronary events and ischemic stroke. - Kaplan, Robert C; McGinn, Aileen P; Pollak, Michael N; Kuller, Lewis H; Strickler, Howard D; Rohan, Tom E; Cappola, Anne R; Xue, XiaoNan; Psaty, Bruce M (J Clin Endocrinol Metab, 2007)
CONTEXT: Prior observational studies have demonstrated that the GH/IGF axis is associated with cardiovascular disease. However, this association has not been extensively studied among older adults. OBJECTIVE: The objective of this study was to assess the association between levels of total IGF-I and IGF binding proteins (IGFBP-1, IGFBP-3) and risk of incident coronary events and ischemic stroke. DESIGN AND PARTICIPANTS: A case-cohort analysis was conducted among adults 65 yr and older in the Cardiovascular Health Study. MAIN OUTCOME MEASURES: A total of 534 coronary events [316 nonfatal myocardial infarctions (MIs), 48 fatal MIs, and 170 fatal coronary heart disease events] and 370 ischemic strokes were identified on follow-up. Comparison subjects were 1122 randomly selected participants from the Cardiovascular Health Study. RESULTS: Mean follow-up time was 6.7 yr for coronary events, 5.6 yr for strokes, and 9.3 yr for comparison subjects. Hazard ratios (95% confidence intervals) associated with baseline levels of total IGF-I and IGFBPs were estimated using multivariate adjusted Cox proportional hazards models. Neither IGF-I nor IGFBP-1 levels predicted risk of incident coronary events or stroke. IGFBP-3 had an inverse association with risk of coronary events [adjusted hazard ratio per sd=0.88 (0.78-1.00), P=0.05] but was not associated with stroke. Exploratory analyses suggested that low IGF-I and low IGFBP-3 levels were significantly associated with higher risk of nonfatal MI (P<0.05) but not with risk of fatal MI or fatal coronary heart disease. CONCLUSION: Circulating levels of total IGF-I or IGFBP-1 were not associated with risk of total coronary events or ischemic stroke among older adults, whereas low IGFBP-3 level was associated with increased risk of incident coronary events.
Keywords: Aged; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; Coronary Disease; Female; Humans; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Multivariate Analysis; Risk Factors; Stroke

Associations between findings on cranial magnetic resonance imaging and retinal photography in the elderly: the Cardiovascular Health Study. - Longstreth, Wt; Larsen, Emily K Marino; Klein, Ronald; Wong, Tien Yin; Sharrett, A Richey; Lefkowitz, David; Manolio, Teri A (Am J Epidemiol, 2007)
Associations between findings on cranial magnetic resonance imaging (MRI) and retinal photographs have been described mostly in middle-aged people. In the Cardiovascular Health Study, 1,717 elderly participants underwent MRI and retinal photography between 1991 and 1999. Associations were sought between MRI findings and four findings of retinal microvascular disease: retinopathy, focal arteriolar narrowing, arteriovenous nicking, and the arteriovenous ratio--the last based upon semiautomated measurements of arterioles and venules. After controlling for age and gender, the authors found associations between MRI findings and the smaller arteriovenous ratio (per standard deviation decrease): prevalent infarcts (odds ratio = 1.18, 95% confidence interval: 1.05, 1.34; p = 0.007), white matter grade (regression coefficient, 0.093; p = 0.011), incident infarct (odds ratio = 1.26, 95% confidence interval: 1.09, 1.46; p = 0.002), and worsening white matter grade (odds ratio = 1.12, 95% confidence interval: 0.98, 1.29; p = 0.09). Arteriovenous nicking was also associated with prevalent (odds ratio = 1.84, 95% confidence interval: 1.23, 2.76; p = 0.003) and incident (odds ratio = 1.84, 95% confidence interval: 1.15, 2.94; p = 0.011) infarcts. Adjustment for hypertension and diabetes had minimal effect. Evidence of small vessel disease in the retina increases the likelihood of finding it in the brain. Associations were less prominent in this elderly population than have been described in middle-aged people.
Keywords: Age Factors; Aged; Aged, 80 and over; Arteriosclerosis; Cerebral Infarction; Female; Humans; Leukoaraiosis; Longitudinal Studies; Magnetic Resonance Imaging; Male; Microcirculation; Photography; Retina; Retinal Diseases; Retinal Vessels; Risk Assessment; Risk Factors

Associations of plasma fibrinogen levels with established cardiovascular disease risk factors, inflammatory markers, and other characteristics: individual participant meta-analysis of 154,211 adults in 31 prospective studies: the fibrinogen studies collab - Kaptoge, S; White, I R; Thompson, S G; Wood, A M; Lewington, S; Lowe, G D O; Danesh, J (Am J Epidemiol, 2007)
Long-term increases in plasma fibrinogen levels of 1 g/liter are associated with an approximate doubling of risk of major cardiovascular disease outcomes, but causality remains uncertain. To quantify cross-sectional associations of fibrinogen levels with established risk factors and other characteristics, the investigators combined individual data on 154,211 apparently healthy adults from 31 prospective studies conducted between 1967 and 2003, using a linear mixed model that included random effects at the cohort level. Fibrinogen levels increased with age and showed continuous, approximately linear relations with several risk markers and slightly curvilinear associations with log triglycerides, albumin, and tobacco and alcohol consumption. Female sex, Black ethnicity, lower socioeconomic status, and alcohol abstinence were each associated with modestly higher fibrinogen levels. Approximately one third of the variation in fibrinogen levels was explained by cohort, age, and sex. An additional 7% was explained by established risk factors (notably, positive associations with smoking and body mass index and an inverse association with high density lipoprotein cholesterol), and a further 10% was explained by inflammatory markers (notably, a positive association with C-reactive protein). The association with body mass index was twice as strong in women as in men, whereas the association with smoking was much stronger in men. These findings substantially advance understanding of the correlates and possible determinants of fibrinogen levels.
Keywords: Adult; African Americans; Age Factors; Biomarkers; Body Mass Index; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Female; Fibrinogen; Humans; Linear Models; Male; Prospective Studies; Risk Factors; Sex Factors; Smoking; Social Class; United States

Brachial flow-mediated dilation predicts incident cardiovascular events in older adults: the Cardiovascular Health Study. - Yeboah, Joseph; Crouse, John R; Hsu, Fang-Chi; Burke, Gregory L; Herrington, David M (Circulation, 2007)
BACKGROUND: The relationship between impaired brachial flow-mediated dilation (FMD) and subsequent clinical cardiovascular events is not well established, especially in older adults whose FMD is often diminished. We assessed the hypothesis that FMD predicts incident cardiovascular events in a population-based cohort of older adults. METHODS AND RESULTS: FMD was measured at the 1997 to 1998 Cardiovascular Health Study clinic visit in 2792 adults aged 72 to 98 years (82.7% white, 58.6% women) recruited at 4 clinic sites in the United States. Log-rank test and Cox proportional hazard models were used to examine the association between FMD and adjudicated cardiovascular events. A total of 674 subjects (24.1%) had an adjudicated event over the 5-year follow-up period. Event-free survival rates for cardiovascular events were significantly higher in subjects with FMD greater than the sex-specific medians than in subjects with FMD less than or equal to the sex-specific medians (78.3% versus 73.6%, log-rank P=0.006). FMD remained a significant predictor of cardiovascular events after adjustment for age, gender, diabetes mellitus, cigarette smoking, systolic and diastolic blood pressure, baseline cardiovascular disease status, and total cholesterol (hazard ratio, 0.91 [95% CI, 0.83 to 0.99], P=0.02 per unit SD of FMD) but added only approximately 1% to the prognostic accuracy of the best Cox model. Brachial artery diameter was also predictive of CV events in the adjusted Cox proportional hazard model (hazard ratio, 1.12 [95% CI, 1.02 to 1.28], P=0.025) and also added approximately 1% to the accuracy of our best Cox model. CONCLUSIONS: FMD is a predictor of future cardiovascular events but adds very little to the prognostic accuracy of traditional cardiovascular risk scores/factors in older adults. FMD and brachial artery diameter may have similar predictive values for cardiovascular events in older adults.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Biomarkers; Brachial Artery; Cardiovascular Diseases; Cohort Studies; Disease-Free Survival; Endothelium, Vascular; Female; Hemorheology; Humans; Hyperemia; Male; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Prospective Studies; Reproducibility of Results; Risk Factors; Stress, Mechanical; Tourniquets; Ultrasonography; United States; Vasodilation

Cerebral ventricular changes associated with transitions between normal cognitive function, mild cognitive impairment, and dementia. - Carmichael, Owen T; Kuller, Lewis H; Lopez, Oscar L; Thompson, Paul M; Dutton, Rebecca A; Lu, Allen; Lee, Sharon E; Lee, Jessica Y; Aizenstein, Howard J; Meltzer, Carolyn C; Liu, Yanxi; Toga, Arthur W; et al. (Alzheimer Dis Assoc Disord, 2007)
Expansion of the cerebral ventricles may occur at an accelerated rate in subjects with dementia, but the time course of expansion during transitions between normal cognitive function, mild cognitive impairment (MCI), and dementia is not well understood. Furthermore, the effects of cardiovascular risk factors on rate of ventricular expansion are unclear. We used a fully automated segmentation technique to measure change rate in lateral ventricle-to-brain ratio (VBR) on 145 longitudinal pairs of magnetic resonance images of subjects in the Cardiovascular Health Study Cognition Study from the Pittsburgh Center. A multivariate model analyzed VBR change rate, accounting for dementia statuses at both imaging times (normal, MCI, or dementia), age, sex, education, race, magnetic resonance-defined infarcts, Center for Epidemiology Studies Depression Scale, baseline ventricular volume, and cardiovascular risk factors. VBR change was faster in subjects who were demented or transitioned from MCI to dementia, compared with subjects normal at both images and subjects who transitioned from normal to MCI or dementia. Patients with diabetes had faster VBR change. Ventricular expansion may accelerate late in the progression from normal cognitive function to dementia, and may be modulated by diabetes.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cerebral Ventricles; Cognition Disorders; Dementia; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Risk Factors; Severity of Illness Index; Time Factors

Clinical factors, but not C-reactive protein, predict progression of calcific aortic-valve disease: the Cardiovascular Health Study. - Novaro, Gian M; Katz, Ronit; Aviles, Ronnier J; Gottdiener, John S; Cushman, Mary; Psaty, Bruce M; Otto, Catherine M; Griffin, Brian P (J Am Coll Cardiol, 2007)
OBJECTIVES: The purpose of this study was to examine the relationship between C-reactive protein (CRP) and calcific aortic valve disease in a large, randomly selected, population-based cohort. BACKGROUND: The pathobiology of calcific aortic stenosis involves an active inflammatory, atheromatous, osteogenic process. Elevations in CRP, a measure of systemic inflammation, have been associated with aortic stenosis. METHODS: Two-dimensional and Doppler echocardiography and CRP measurement were performed at baseline in 5,621 participants in the Cardiovascular Health Study. Multivariable analysis was used to identify CRP as a predictor of baseline and incident aortic stenosis. RESULTS: At a mean echocardiographic follow-up of 5 years, 9% of subjects with aortic sclerosis progressed to some degree of aortic stenosis. Increasing age (odds ratio [OR] 1.13, 95% confidence interval [CI] 1.09 to 1.16; p < 0.001) and male gender (OR 3.05, 95% CI 1.76 to 5.27; p < 0.001) were related to risk of incident aortic stenosis, whereas increasing height (OR 0.96, 95% CI 0.94 to 0.99; p = 0.013) and African-American ethnicity conveyed a lower risk (OR 0.49, 95% CI 0.25 to 0.95; p = 0.035). C-reactive protein, treated as a continuous variable, was not associated with baseline aortic stenosis, progression to aortic sclerosis (adjusted OR 0.93, 95% CI 0.85 to 1.02; p = 0.107), or progression to aortic stenosis (adjusted OR 0.85, 95% CI 0.70 to 1.03; p = 0.092). CONCLUSIONS: In this large population-based cohort, approximately 9% of subjects with aortic sclerosis progressed to aortic stenosis over a 5-year follow-up period. There was no association between CRP levels and the presence of calcific aortic-valve disease or incident aortic stenosis. C-reactive protein appears to be a poor predictor of subclinical calcific aortic-valve disease.
Keywords: Aged; Aged, 80 and over; Aortic Valve; Aortic Valve Stenosis; C-Reactive Protein; Calcinosis; Cardiovascular Diseases; Cohort Studies; Disease Progression; Female; Follow-Up Studies; Heart Valve Diseases; Humans; Male; Risk Factors

Depressive symptoms, inflammation, and ischemic stroke in older adults: a prospective analysis in the cardiovascular health study. - Arbelaez, Jose J; Ariyo, Abraham A; Crum, Rosa M; Fried, Linda P; Ford, Daniel E (J Am Geriatr Soc, 2007)
OBJECTIVES: To investigate the mediator role of inflammation in any relationship between depressive symptoms and ischemic stroke. DESIGN: Longitudinal prospective study. SETTING: Review of medical records, death certificates, and the Medicare healthcare utilization database for hospitalizations. PARTICIPANTS: Total of 5,525 elderly men and women aged 65 and older who were prospectively followed from 1989 to 2000 as participants in the Cardiovascular Health Study. MEASUREMENTS: Depression symptom scores, inflammatory markers. RESULTS: Greater depressive symptoms were associated with risk of ischemic stroke (unadjusted hazard ratio (HR)=1.32, 95% confidence interval (CI)=1.09-1.59; HR=1.26, 95% CI=1.03-1.54, adjusted for traditional risk factors). When a term for inflammation (C-reactive protein (CRP)) was introduced in the model, the HRs were not appreciably altered (unadjusted HR=1.31, 95% CI=1.08-1.58; adjusted HR=1.25, 95% CI=1.02-1.53), indicating that CRP at baseline was not a mediator in this relationship. In analyses stratified according to CRP levels, a J-shaped relationship between depressive symptoms and stroke was evident in the unadjusted analyses; in the fully adjusted model, only CRP in the highest tertile was associated with a higher risk for stroke in the presence of higher depressive symptoms scores. CONCLUSION: The analyses from this prospective study provide evidence of a positive association between depressive symptoms and risk of incident stroke. Inflammation, as measured according to CRP at baseline, did not appear to mediate the relationship between depressive symptoms and stroke.
Keywords: Aged; C-Reactive Protein; Cardiovascular Diseases; Cerebral Infarction; Cohort Studies; Depression; Female; Geriatric Assessment; Humans; Inflammation; Kaplan-Meier Estimate; Longitudinal Studies; Male; Multivariate Analysis; Personality Assessment; Proportional Hazards Models; Prospective Studies; Psychoneuroimmunology; Risk Factors; Socioeconomic Factors; Statistics as Topic; United States

Determinants of serum total and free testosterone levels in women over the age of 65 years. - Cappola, Anne R; Ratcliffe, Sarah J; Bhasin, Shalender; Blackman, Marc R; Cauley, Jane; Robbins, John; Zmuda, Joseph M; Harris, Tamara; Fried, Linda P (J Clin Endocrinol Metab, 2007)
CONTEXT: Little is known about testosterone (T) levels and their determinants in women of late postmenopausal age. OBJECTIVE: We describe levels of total and free T and selected factors that influence these levels in a random sample of older women. DESIGN: Levels of serum total T and free T by microdialysis were measured using ultrasensitive assays in 347 community-dwelling women aged 65-98 yr enrolled in the Cardiovascular Health Study. Cross-sectional analyses were performed to define factors associated with total and free T levels. RESULTS: In adjusted models: 1) total T levels declined with age until 80, whereas free T levels did not vary by age; 2) women with bilateral oophorectomy had 23% lower total T and 16% lower free T levels than those with at least one intact ovary; 3) oral estrogen users had total and free T levels that were 47% lower than never users; 4) obese women had 47% higher total T and 20% higher free T levels, and overweight women had 24% higher total T and 14% higher free T levels, than normal weight women; and 5) free T levels were 51% higher in black women. Corticosteroid users had 75% lower total T and 43% lower free T levels than nonusers. CONCLUSIONS: Bilateral oophorectomy, estrogen use, corticosteroid use, and low body mass index are independent risk factors for lower T levels in women aged 65 yr and over. Although highly prevalent in women of this age, the physiological significance of low T levels in late postmenopausal women requires further investigation.
Keywords: Age Distribution; Aged; Aged, 80 and over; Aging; Body Mass Index; Cross-Sectional Studies; Estrogen Replacement Therapy; Female; Humans; Hypogonadism; Multivariate Analysis; Nonlinear Dynamics; Obesity; Ovariectomy; Ovary; Postmenopause; Predictive Value of Tests; Prevalence; Risk Factors; Testosterone

The Emerging Risk Factors Collaboration: analysis of individual data on lipid, inflammatory and other markers in over 1.1 million participants in 104 prospective studies of cardiovascular diseases. - Danesh, J; Erqou, S; Walker, M; Thompson, S G; Tipping, R; Ford, C; Pressel, S; Walldius, G; Jungner, I; Folsom, A R; Chambless, L E; Knuiman, M; et al. (Eur J Epidemiol, 2007)
Many long-term prospective studies have reported on associations of cardiovascular diseases with circulating lipid markers and/or inflammatory markers. Studies have not, however, generally been designed to provide reliable estimates under different circumstances and to correct for within-person variability. The Emerging Risk Factors Collaboration has established a central database on over 1.1 million participants from 104 prospective population-based studies, in which subsets have information on lipid and inflammatory markers, other characteristics, as well as major cardiovascular morbidity and cause-specific mortality. Information on repeat measurements on relevant characteristics has been collected in approximately 340,000 participants to enable estimation of and correction for within-person variability. Re-analysis of individual data will yield up to approximately 69,000 incident fatal or nonfatal first ever major cardiovascular outcomes recorded during about 11.7 million person years at risk. The primary analyses will involve age-specific regression models in people without known baseline cardiovascular disease in relation to fatal or nonfatal first ever coronary heart disease outcomes. This initiative will characterize more precisely and in greater detail than has previously been possible the shape and strength of the age- and sex-specific associations of several lipid and inflammatory markers with incident coronary heart disease outcomes (and, secondarily, with other incident cardiovascular outcomes) under a wide range of circumstances. It will, therefore, help to determine to what extent such associations are independent from possible confounding factors and to what extent such markers (separately and in combination) provide incremental predictive value.
Keywords: Albumins; Biomarkers; Cardiovascular Diseases; Databases, Factual; Far East; Humans; Inflammation; Leukocyte Count; Lipids; Lipoproteins, HDL; Prospective Studies; Risk Factors; Triglycerides

Factor VII coagulant activity, factor VII -670A/C and -402G/A polymorphisms, and risk of venous thromboembolism. - Folsom, A R; Cushman, M; Heckbert, S R; Ohira, T; Rasmussen-Torvik, L; Tsai, M Y (J Thromb Haemost, 2007)
BACKGROUND: Most epidemiological studies have found no association between levels of factor (F) VII:C and venous thromboembolism (VTE). Our Longitudinal Investigation of Thromboembolism Etiology (LITE) had, in contrast, reported an independent, increased risk of VTE after 7.8 years of follow-up for those with high baseline levels of FVII:C. OBJECTIVE: To confirm whether FVII:C is associated with VTE after 12.6 years of follow-up and to examine whether two FVII gene polymorphisms (-670A/C and -402G/A) are related to VTE occurrence. METHODS: In 19 091 LITE participants with no prior history of VTE or cancer, we measured FVII:C at baseline and identified 404 new VTEs. We also performed a nested case-control study to relate the polymorphisms to VTE (n = 490 without exclusion for cancer or prior VTE). RESULTS: FVII:C was not independently associated with VTE occurrence after extended follow-up. Multivariable-adjusted rate ratios for VTE were 1.00, 1.00, 0.94, 1.00, and 1.38 (P-trend = 0.48) for the <25th, 25th-49th, 50th-74th, 75th-94th, and >or=95th percentiles of FVII:C, respectively. The -670C and -402A alleles were in high linkage disequilibrium, and both were associated with greater FVII:C levels. However, neither polymorphism was associated with VTE occurrence. CONCLUSION: After extended follow-up, LITE offers little evidence that a greater FVII level is a risk factor for VTE.
Keywords: Alleles; Antigens; Coagulants; Factor VII; Female; Genotype; Humans; Male; Polymorphism, Genetic; Prospective Studies; Risk Factors; Thromboembolism; Venous Thrombosis

Focal atrophy and cerebrovascular disease increase dementia risk among cognitively normal older adults. - Rosano, Caterina; Aizenstein, Howard J; Wu, Minjie; Newman, Anne B; Becker, James T; Lopez, Oscar L; Kuller, Lewis H (J Neuroimaging, 2007)
BACKGROUND AND PURPOSE: This study investigated the association of medial temporal lobe (MTL) atrophy and cerebrovascular disease (white matter hyperintensities [WMH], subclinical infarcts) with the risk of developing Alzheimer's disease (AD) among cognitively normal older adults. METHODS: Risk of developing AD was examined for 155 cognitively normal older adults (77.4 years, 60% women, 81% white). The MTL volumes and the presence of WMH and of subclinical infarcts were determined from brain magnetic resonance imaging (MRI) at the beginning of the study. Follow-up cognitive evaluations (average 4.3 years) identified those who developed AD. RESULTS: The presence of either MTL atrophy or subclinical infarcts was independently and significantly associated with a greater risk to develop AD (OR [95% CI]: 4.4 [1.5, 12.3] and 2.7 [1.0, 7.1], respectively). In addition, those participants with both MTL atrophy and at least one brain infarct had a 7-fold increase in the risk of developing AD (OR [95% CI]: 7.0 [1.5, 33.1]), compared to those who had neither of these conditions. CONCLUSIONS: In cognitively normal older adults, markers of neurodegeneration (as reflected by MTL atrophy) and of cerebrovascular disease (as reflected by infarcts on MRI) independently contribute to the risk to develop AD.
Keywords: Aged; Alzheimer Disease; Analysis of Variance; Atrophy; Cerebrovascular Disorders; Cognition; Female; Humans; Logistic Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Risk Factors; Temporal Lobe; United States

Frailty and risk of venous thromboembolism in older adults. - Folsom, Aaron R; Boland, Lori L; Cushman, Mary; Heckbert, Susan R; Rosamond, Wayne D; Walston, Jeremy D (J Gerontol A Biol Sci Med Sci, 2007)
BACKGROUND: Frailty is a common risk factor for morbidity and mortality in elderly persons. Recent evidence links frailty to activation of coagulation and inflammatory pathways. We aimed to determine whether frailty in community-dwelling older adults is a risk factor for venous thromboembolism (VTE). METHODS: We conducted a prospective cohort study in four U.S. communities involving 4859 participants 65 years old and older. At baseline, in 1989-1993, we assessed frailty based on weight loss, grip strength, feelings of exhaustion, walk time, and physical activity. Incident VTE (deep vein thrombosis or pulmonary embolus) through 2002 was identified by review of hospital records. RESULTS: Fifty-two percent of the sample was classified as having intermediate or definite frailty. After adjustment for age, race, sex, body mass index, and diabetes, the relative risk of total VTE (n = 150) for people who were frail compared with no frailty was 1.31 (95% confidence interval [CI], 0.93-1.84). The comparably adjusted relative risk for idiopathic VTE (n = 58) was 1.79 (95% CI, 1.02-3.13). CONCLUSIONS: The incidence rates of idiopathic VTE was higher in community-dwelling older adults with baseline frailty compared with no frailty. Further studies of the clotting process in frailty may allow the development of an improved strategy to determine VTE risk in this vulnerable subset of older adults.
Keywords: Age Factors; Aged; Aged, 80 and over; Female; Follow-Up Studies; Frail Elderly; Humans; Male; Morbidity; Motor Activity; Prospective Studies; Risk Factors; Thromboembolism; United States; Venous Thrombosis

Gait variability and the risk of incident mobility disability in community-dwelling older adults. - Brach, Jennifer S; Studenski, Stephanie A; Perera, Subashan; VanSwearingen, Jessie M; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2007)
BACKGROUND: Gait speed is a strong predictor of incident walking disability. The objective was to determine if gait variability adds to the prediction of incident mobility disability independent of gait speed. METHODS: Participants included 379 older adults (mean age = 79 years; 78% Caucasian, and 40% men) in the Cardiovascular Health Study at the Pittsburgh site. All could ambulate independently and reported no difficulty walking a half mile. Gait characteristics were determined from a 4-meter computerized walkway. For each gait parameter, variability was defined as the standard deviation from the individual steps from two passes. Incident walking disability was obtained by phone interview every 6 months for 54 months and was defined as new difficulty walking a half mile or inability to walk a half mile. RESULTS: Of the 379 participants, 222 (58.6%) developed incident mobility disability. In unadjusted Cox proportional hazards models gait speed, mean step length, mean stance time, and stance time variability were associated with incident mobility disability. After adjusting for gait speed, demographics, chronic conditions, prescription medications, health status, and physical activity level, only stance time variability remained an important indicator of disability. In the adjusted model, an increase in stance time variability of 0.01 seconds was associated with a 13% higher incidence of mobility disability (hazard ratio 1.13, 95% confidence interval, 1.01-1.27). CONCLUSIONS: Stance time variability is an independent predictor of future mobility disability. Future efforts are needed to determine whether interventions that decrease stance time variability will also delay mobility disability.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Gait; Gait Disorders, Neurologic; Humans; Male; Mobility Limitation; Prospective Studies; Risk Factors; Walking

Gait variability is associated with subclinical brain vascular abnormalities in high-functioning older adults. - Rosano, Caterina; Brach, Jennifer; Studenski, Stephanie; Longstreth, W T; Newman, Anne B (Neuroepidemiology, 2007)
BACKGROUND: Gait variability is an index of how much gait parameters, such as step length, change from one step to the next. Gait variability increases with age and in individuals affected by cortical and subcortical neurodegenerative conditions, and it is associated with falls and incident mobility disability. The brain anatomical correlates of gait variability have not been studied in high-functioning community-dwelling older adults. METHODS: Gait variability and brain MRIs were assessed in a cohort of 331 men and women (mean age = 78.3 years) free from stroke, dementia or Parkinson's disease. Gait variability was computed for spatial parameters (step length and step width) and for temporal parameters (stance time). Subclinical brain vascular abnormalities were measured on brain MRIs as infarcts and white matter hyperintensities. RESULTS: Greater variability of step length was associated with greater prevalence of infarcts, including infarcts in the basal ganglia, and with greater white matter hyperintensities severity, independent of age, gender, cognitive function and cardiovascular disease. Weaker associations were found between the other variability measures and the MRI measures. CONCLUSION: In this group of older adults free from neurodegenerative diseases, a greater variability of step length was associated with greater burden of subclinical brain vascular abnormalities as defined by MRI.
Keywords: Accidental Falls; Activities of Daily Living; Aged; Aged, 80 and over; Basal Ganglia Cerebrovascular Disease; Brain; Cerebral Infarction; Comorbidity; Female; Gait Disorders, Neurologic; Geriatric Assessment; Health Surveys; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mobility Limitation; Neurodegenerative Diseases; Neurologic Examination; Risk Factors; United States

Individual and neighborhood socioeconomic status and progressive chronic kidney disease in an elderly population: The Cardiovascular Health Study. - Merkin, Sharon Stein; Diez Roux, Ana V; Coresh, Josef; Fried, Linda F; Jackson, Sharon A; Powe, Neil R (Soc Sci Med, 2007)
Few studies have focused on the association between socioeconomic status (SES) and progressive chronic kidney disease (pCKD) in an elderly population. We conducted a cohort study of 4735 Cardiovascular Health Study participants, ages 65 and older and living in 4 US communities, to examine the independent risk of pCKD associated with income, education and living in a low SES area. pCKD was defined as creatinine elevation 0.4 mg/dL (35 micromol/L) over a 4-7 year follow-up or CKD hospitalization. Area SES was characterized using measures of income, wealth, education and occupation for 1990 (corresponding to time of enrollment) US Census block groups of residence. Age and study site-adjusted incidence rates (per 1000 person years) of pCKD by quartiles of area-level SES score, income and education showed decreasing rates with increasing SES. Cox proportional hazards models showed that living in the lowest SES area quartile, as opposed to the highest, was associated with 50% greater risk of pCKD, after adjusting for age, gender, study site, baseline creatinine, and individual-level SES. This increased risk and trend persisted after adjusting for lifestyle risk factors, diabetes and hypertension. We found no significant independent associations between pCKD and individual-level income or education (after adjusting for all other SES factors). As such, living in a low SES area is associated with greater risk of pCKD in an elderly US population.
Keywords: Age Factors; Aged; Cohort Studies; Female; Humans; Incidence; Kidney Failure, Chronic; Male; Proportional Hazards Models; Residence Characteristics; Risk Factors; Sex Factors; Social Class; United States

Inflammation and hemostasis biomarkers and cardiovascular risk in the elderly: the Cardiovascular Health Study. - Zakai, N A; Katz, R; Jenny, N S; Psaty, B M; Reiner, A P; Schwartz, S M; Cushman, M (J Thromb Haemost, 2007)
BACKGROUND: There are few studies of inflammation and hemostasis biomarkers and cardiovascular disease risk (CVD) in older adults. OBJECTIVES: To assess multiple biomarkers simultaneously and in combinations for CVD risk assessment in older individuals. PATIENTS/METHODS: Thirteen biomarkers, interleukin-6 (IL-6), C-reactive protein (CRP), D-dimer, fibrinogen, factor VII, factor VIII, leukocyte count (WBC), platelet count, lipoprotein(a), soluble intercellular adhesion molecule-1 (sICAM-1), albumin, homocysteine and uric acid, were correlated with incident CVD in 4510 individuals in the Cardiovascular Health Study. Baseline biomarkers were analyzed as gender-specific SD increments and quintiles in proportional hazards models adjusted for demographics, CVD risk factors and medications. RESULTS: Over 9 years with 1700 CVD events, seven biomarkers were associated with CVD. Adjusted hazard ratios (HRs, 95% CI) per SD increment were 1.16 (1.09, 1.23) for IL-6, 1.16 (1.09, 1.23) for CRP, 1.13 (1.05, 1.21) for D-dimer, 1.17 (1.09, 1.25) for homocysteine, 1.06 (1.00, 1.12) for WBC, 1.06 (1.00, 1.12) for factor VIII, and 1.07 (1.00, 1.13) for lipoprotein(a). Fibrinogen was associated with CVD in men only (HR 1.12, 95% CI 1.04, 1.22) and sICAM-1 in women only (HR 1.16, 95% CI 1.05, 1.27). IL-6 and CRP remained associated with CVD when modeled with WBC. Participants were classified by all combinations of two biomarkers being high or low (IL-6, CRP, WBC, factor VIII, cholesterol/HDL). All were associated with CVD when cholesterol/HDL was low and none when CRP was low. CONCLUSIONS: Seven biomarkers were associated with CVD in older adults, with CRP having some advantages compared with others. Even larger studies are needed to better characterize these associations.
Keywords: Aged; Aging; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Cholesterol; Cohort Studies; Factor VIII; Female; Fibrinogen; Hemostasis; Homocysteine; Humans; Inflammation Mediators; Interleukin-6; Leukocyte Count; Lipoprotein(a); Male; Prospective Studies; Risk Factors

Inflammation biomarkers and near-term death in older men. - Jenny, Nancy Swords; Yanez, N David; Psaty, Bruce M; Kuller, Lewis H; Hirsch, Calvin H; Tracy, Russell P (Am J Epidemiol, 2007)
Associations of C-reactive protein (CRP) and fibrinogen with death may weaken over time. Combining both markers may improve prediction of death in older adults. In 5,828 Cardiovascular Health Study participants (United States, 1989-2000), 383 deaths (183 cardiovascular disease (CVD)) in years 1-3 (early) and 914 deaths (396 CVD) in years 4-8 (late) occurred. For men, when comparing highest to lowest quartiles, hazard ratios for early death were 4.1 (95% confidence interval (CI): 2.7, 6.3) for CRP and 4.1 (95% CI: 2.7, 6.4) for fibrinogen in models adjusted for CVD risk. For early CVD death, hazard ratios were 4.3 (95% CI: 2.2, 8.4) and 3.4 (95% CI: 1.8, 6.3), respectively. When comparing men in the highest quartiles of both biomarkers with those in the lowest, hazard ratios were 9.6 (95% CI: 4.3, 21.1) for early death and 13.5 (95% CI: 3.2, 56.5) for early CVD death. Associations were weaker for late deaths. For women, CRP (hazard ratio = 2.3, 95% CI: 1.4, 3.9), but not fibrinogen (hazard ratio = 1.3, 95% CI: 0.8, 2.2), was associated with early death. Results were similar for CVD death. Neither was associated with late deaths. CRP and fibrinogen were more strongly associated with death in older men than women and more strongly associated with early than late death. Combining both markers may identify older men at greatest risk of near-term death.
Keywords: Age Distribution; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Diabetes Complications; Epidemiologic Studies; Female; Fibrinogen; Follow-Up Studies; Humans; Hypercholesterolemia; Hypertension; Inflammation; Male; Middle Aged; Obesity; Population Surveillance; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Factors; Sex Distribution; Smoking; Time Factors; United States

Leukocyte telomere length and cardiovascular disease in the cardiovascular health study. - Fitzpatrick, Annette L; Kronmal, Richard A; Gardner, Jeffrey P; Psaty, Bruce M; Jenny, Nancy S; Tracy, Russell P; Walston, Jeremy; Kimura, Masyuki; Aviv, Abraham (Am J Epidemiol, 2007)
The telomere length of replicating somatic cells is inversely correlated with age and has been reported to be associated cross-sectionally with cardiovascular disease (CVD). Leukocyte telomere length, as expressed by mean terminal restriction fragment (TRF) length, was measured in 419 randomly selected participants from the Cardiovascular Health Study, comprising a community-dwelling cohort recruited in four US communities. The authors investigated associations between TRF length and selected measures of subclinical CVD/risk factors for CVD (data were collected at the 1992/1993 clinic visit) and incident CVD (ascertained through June 2002). In these participants (average age = 74.2 years (standard deviation, 5.2)), mean TRF length was 6.3 kilobase pairs (standard deviation, 0.62). Significant or borderline inverse associations were found between TRF length and diabetes, glucose, insulin, diastolic blood pressure, carotid intima-media thickness, and interleukin-6. Associations with body size and C-reactive protein were modified by gender and age, occurring only in men and in participants aged 73 years or younger. In younger (but not older) participants, each shortened kilobase pair of TRF corresponded with a threefold increased risk of myocardial infarction (hazard ratio = 3.08, 95% confidence interval: 1.22, 7.73) and stroke (hazard ratio = 3.22, 95% confidence interval: 1.29, 8.02). These results support the hypotheses that telomere attrition may be related to diseases of aging through mechanisms involving oxidative stress, inflammation, and progression to CVD.
Keywords: Aged; Cardiovascular Diseases; DNA; Female; Humans; Inflammation; Leukocytes; Male; Myocardial Infarction; Oxidative Stress; Pilot Projects; Polymorphism, Restriction Fragment Length; Risk; Risk Assessment; Risk Factors; Telomere

Potential interactions between complementary/alternative products and conventional medicines in a Medicare population. - Elmer, Gary W; Lafferty, William E; Tyree, Patrick T; Lind, Bonnie K (Ann Pharmacother, 2007)
BACKGROUND: Despite the high prevalence of complementary and alternative medicine (CAM) product use among the elderly, little is known about the extent of concurrent CAM-conventional medicine use and the potential for adverse reactions. OBJECTIVE: To determine the prevalence of CAM product use concurrent with conventional medications, prescription and nonprescription, in a Medicare population and assess the risk for adverse interactions. METHODS: Retrospective analysis was performed on Cardiovascular Health Study interview data from 1994, 1995, 1997, and 1999. The prevalence of concurrent combinations of CAM products and conventional drugs was tabulated. The adverse interaction risks were categorized as unknown, theoretical, and significant. RESULTS: Of 5052 participants, the median age was 75, 60.2% were female, 16.6% were African American, and 83.4% were white. The percent using CAM products during the 4 time periods was 6.3%, 6.7%, 12.8%, and 15.1%. The percent using both CAM products and conventional drugs was 6.0%, 6.2%, 11.7%, and 14.4%. Of these, 294 (5.8%) individuals took combinations considered to have a significant risk for an adverse interaction. Combinations with risk were observed on 393 separate interviews. Most (379) involved a risk of bleeding due to use of ginkgo, garlic, or ginseng together with aspirin, warfarin, ticlopidine, or pentoxifylline. An additional 786 observations of combinations were considered to have some, albeit theoretical or uncertain, risk for an adverse interaction. CONCLUSIONS: Concurrent use of CAM products and conventional medicines in a Medicare population was found to be common. Research to define the risks of combining ginkgo and garlic supplements with aspirin should be of high priority.
Keywords: Aged; Complementary Therapies; Drug Interactions; Drug-Related Side Effects and Adverse Reactions; Female; Hemorrhage; Herb-Drug Interactions; Humans; Male; Medicare; Pharmaceutical Preparations; Phytotherapy; Plant Extracts; Plant Preparations; Retrospective Studies; Risk Factors; Washington

The relationship of heart rate and heart rate variability to non-diabetic fasting glucose levels and the metabolic syndrome: the Cardiovascular Health Study. - Stein, P K; Barzilay, J I; Domitrovich, P P; Chaves, P M; Gottdiener, J S; Heckbert, S R; Kronmal, R A (Diabet Med, 2007)
BACKGROUND: Increased heart rate (HR) and diminished heart rate variability (HRV) are signs of early cardiovascular autonomic neuropathy. We tested the hypotheses that increased HR and diminished HRV are present in people: (i) with increased fasting glucose (FG) levels not in the range of diabetes mellitus (DM), and (ii) in people with the metabolic syndrome (MetS) independent of elevated FG levels. METHODS: HR and HRV were determined in 1267 adults (mean age 72 years) who had Holter monitoring and FG measures: 536 had normal FG levels (NORM, FG 4.5-5.5 mmol/l), 363 had mildly impaired FG (IFG-1, FG 5.6-6.0 mmol/l), 182 had significantly impaired FG (IFG-2, FG 6.1-6.9 mmol/l) and 178 had DM (FG > 6.9 mmol/l or use of glucose-lowering agents/insulin). HR and HRV in NORM/IFG-1 was further compared by the number of components of the MetS and compared by the presence or absence of MetS in IFG-2/DM. RESULTS: HRV indices were more impaired in IFG-2 and DM than in NORM or IFG-1. There were few differences in HRV indices between NORM and IFG-1 or between IFG-2 and DM. In NORM/IFG-1 participants, having > or = 2 components of the MetS was associated with a greater decrease in HRV compared with having no or one components. In IFG-2/DM participants, MetS was associated with decreased HRV compared with no MetS. CONCLUSIONS: Increased HR and diminished HRV occur in the non-diabetic FG range. Diminished HRV is associated with the MetS, independent of FG levels. Both these results suggest that factors associated with increasing non-diabetic FG levels and the MetS play a role in the onset of cardiac autonomic impairment.
Keywords: Aged; Aged, 80 and over; Arrhythmias, Cardiac; Blood Glucose; Fasting; Female; Glucose Intolerance; Heart Rate; Humans; Male; Metabolic Syndrome; Risk Factors

Retinal microvascular signs, cognitive function, and dementia in older persons: the Cardiovascular Health Study. - Baker, Michelle L; Marino Larsen, Emily K; Kuller, Lewis H; Klein, Ronald; Klein, Barbara E K; Siscovick, David S; Bernick, Charles; Manolio, Teri A; Wong, Tien Yin (Stroke, 2007)
BACKGROUND AND PURPOSE: Cerebral microvascular disease may be a risk factor for the development of dementia in elderly persons. We describe the association of retinal microvascular signs with cognitive function and dementia among older individuals. METHODS: In the population-based Cardiovascular Health Study, 2211 persons aged 69 to 97 years at recruitment had retinal photography. Photographs were evaluated for retinopathy (eg, microaneurysms, retinal hemorrhages), focal arteriolar narrowing, arteriovenous nicking, and retinal arteriolar and venular caliber. Cognitive status was determined from the Digit-Symbol Substitution Test and Modified Mini-Mental State Examination. Participants were also further evaluated for the presence of dementia with detailed neuropsychological testing. Persons with a prior stroke or taking antipsychotic or antidepressant medications were excluded. RESULTS: After adjusting for age, gender, race, field center, education level, internal carotid intima-media thickness, body mass index, hypertension, diabetes, and cigarette smoking status, persons with retinopathy had lower mean Digit-Symbol Substitution Test scores but not Modified Mini-Mental State Examination than those without retinopathy (39 versus 41, P=0.002). In hypertensive persons, retinopathy (multivariable-adjusted OR, 2.10; 95% CI, 1.04 to 4.24) and focal arteriolar narrowing (OR, 3.02; 95% CI, 1.51 to 6.02) were associated with dementia. These associations were not present in individuals without hypertension. CONCLUSIONS: In older persons, our study shows a modest cross-sectional association between retinopathy signs with poorer cognitive function and, in persons with hypertension, with dementia. These data support a possible role of cerebral microvascular disease in the pathogenesis of impaired cognitive function and dementia in older hypertensive persons.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cognition; Cross-Sectional Studies; Dementia; Female; Humans; Longitudinal Studies; Male; Microcirculation; Neuropsychological Tests; Retinal Vessels; Risk Factors

Risk factors for intracerebral hemorrhage in a pooled prospective study. - Sturgeon, Jared D; Folsom, Aaron R; Longstreth, W T; Shahar, Eyal; Rosamond, Wayne D; Cushman, Mary (Stroke, 2007)
BACKGROUND AND PURPOSE: Few prospective studies have reported risk factors for intracerebral hemorrhage (ICH), and results are inconsistent. We studied risk factors for ICH in a pooled cohort of the Atherosclerosis Risk in Communities Study (ARIC) and the Cardiovascular Health Study (CHS). METHODS: The ARIC cohort was recruited in 1987 to 1989 and involves 15 792 men and women, aged 45 to 64 years at baseline, sampled from 4 US communities. The CHS cohort was recruited in 1989 to 1993 and involves 5888 men and women, aged 65 or over at baseline, sampled from 4 US communities. Baseline measurements included many potential vascular risk factors. The cohorts were followed for incident stroke events. RESULTS: Over 263 489 person-years of follow-up, 135 incident ICH events occurred. In a multivariable model, age, African-American ethnicity (versus Whites), and hypertension were positively associated with incident ICH, whereas low-density lipoprotein cholesterol and triglycerides were inversely related to incident ICH. Participants with systolic blood pressure >or=160 mm Hg or diastolic blood pressure >/=110 mm Hg had 5.55 (95% CI 3.07 to 10.0) times the rate of ICH as nonhypertensives. Sex, smoking, alcohol intake, body mass index, waist-to-hip ratio, waist circumference, and diabetes were not related to ICH. CONCLUSIONS: In this pooled cohort the risk factors for ICH were older age, African-American ethnicity, hypertension, lower LDL-C, and lower triglycerides.
Keywords: African Americans; Age Distribution; Cerebral Hemorrhage; Cholesterol, LDL; Female; Follow-Up Studies; Humans; Hypertension; Incidence; Male; Middle Aged; Multivariate Analysis; Predictive Value of Tests; Prevalence; Prospective Studies; Risk Factors; Stroke; Triglycerides

Serum amyloid P and cardiovascular disease in older men and women: results from the Cardiovascular Health Study. - Jenny, Nancy Swords; Arnold, Alice M; Kuller, Lewis H; Tracy, Russell P; Psaty, Bruce M (Arterioscler Thromb Vasc Biol, 2007)
OBJECTIVE: Serum amyloid P (SAP), a pentraxin like C-reactive protein (CRP), functions in innate immunity. However, associations of SAP with cardiovascular disease (CVD) are unknown. METHODS AND RESULTS: We examined these associations in the Cardiovascular Health Study using a case-cohort design. Nonexclusive case groups were incident angina (n=523), myocardial infarction (MI; n=308), stroke (n=323), and CVD death (n=288). 786 participants had no events. SAP was correlated with CRP, CVD risk factors (obesity, blood pressure, lipids), common and internal carotid wall thickness, and ankle-brachial index (all P<0.02). In Cox regression models adjusted for age, sex, and ethnicity, a standard deviation increase in SAP (9.8 mg/L) was associated with angina (hazard ratio; 95% confidence interval 1.3; 1.2 to 1.5) and MI (1.3; 1.1 to 1.5), but not stroke (1.1; 0.9 to 1.3) or CVD death (1.1; 0.9 to 1.3). Adding CRP to the models had no significant effect on associations. Adjusting for CVD risk factors slightly attenuated SAP associations with CVD events; however, associations with angina and MI remained significant. CONCLUSIONS: Although both are pentraxins, SAP and CRP may represent different facets of inflammation. The association of SAP with CVD in these older adults further supports the role of innate immunity in atherosclerosis.
Keywords: Aged; Aged, 80 and over; Aging; Angina, Unstable; Atherosclerosis; C-Reactive Protein; Cardiovascular Diseases; Case-Control Studies; Female; Humans; Hypertension; Immunity, Innate; Male; Myocardial Infarction; Obesity; Prevalence; Proportional Hazards Models; Risk Factors; Serum Amyloid P-Component

USF1 gene variants, cardiovascular risk, and mortality in European Americans: analysis of two US cohort studies. - Reiner, Alexander P; Carlson, Christopher S; Jenny, Nancy S; Durda, J Peter; Siscovick, David S; Nickerson, Deborah A; Tracy, Russell P (Arterioscler Thromb Vasc Biol, 2007)
OBJECTIVE: A common haplotype of the upstream transcription factor 1 gene (USF1) has been associated with decreased susceptibility to familial combined hyperlipidemia (FCHL) and, paradoxically, with increased risk of cardiovascular disease (CVD) and all-cause mortality. METHODS AND RESULTS: We assessed associations between USF1 tagSNPs, CVD risk factors, and aging-related phenotypes using data from 2 large population-based cohorts, Coronary Artery Risk Development in Young Adults (CARDIA) and the Cardiovascular Health Study (CHS), comprising younger and older adults, respectively. In CARDIA, each additional copy of the FCHL low-risk allele was associated with 2.4 mg/dL lower levels of LDL cholesterol (P=0.01) and decreased risk of subclinical atherosclerosis as assessed by coronary artery calcium (odds ratio 0.79; 95%CI 0.63 to 0.98). Whereas there was little association between USF1 genotype and metabolic or CVD traits in older adults from CHS, the USF1 low-risk dyslipidemia allele was associated with higher plasma C-reactive protein and interleukin (IL)-6 levels and with increased risk of mortality, particularly attributable to noncardiovascular causes. CONCLUSIONS: There appears to be a complex and possibly age-dependent relationship between USF1 genotype, atherosclerosis phenotypes, and CVD risk. USF1 may influence mortality through pathways distinct from atherosclerosis. Alternatively, linkage disequilibrium with neighboring polymorphisms in other genes such as F11R may be responsible for the observed USF1 genotype-phenotype associations in older adults.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Aging; Blood Glucose; C-Reactive Protein; Calcium; Cardiovascular Diseases; Carotid Artery, Common; Cohort Studies; Coronary Artery Disease; Coronary Vessels; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Predisposition to Disease; Humans; Hyperlipidemia, Familial Combined; Insulin; Interleukin-6; Linkage Disequilibrium; Lipids; Male; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States; Upstream Stimulatory Factors

Ventricular structure and function in hypertensive participants with heart failure and a normal ejection fraction: the Cardiovascular Health Study. - Maurer, Mathew S; Burkhoff, Daniel; Fried, Linda P; Gottdiener, John; King, Donald L; Kitzman, Dalane W (J Am Coll Cardiol, 2007)
OBJECTIVES: The purpose of this study was to evaluate left ventricular (LV) size and structure in elderly subjects with hypertension (HTN) and heart failure who have a normal ejection fraction (HFNEF) in a large population-based sample. BACKGROUND: The pathophysiology of HFNEF is incompletely understood but is generally attributed to LV diastolic dysfunction with normal or reduced LV diastolic chamber size despite greater than normal filling pressures. METHODS: In the Cardiovascular Health Study (n = 5,888), demographic and clinical characteristics and ventricular structure and function were compared in healthy normal subjects (healthy; n = 499), subjects with HTN but not heart failure (HTN; n = 2,184), and subjects with HTN and HFNEF (HFNEF; n = 167). RESULTS: Subjects with HFNEF were older, more obese, and more often African American than healthy and HTN subjects and had a higher prevalence of diabetes, coronary heart disease, and anemia than HTN subjects. Serum creatinine and cystatin-C were increased in HFNEF subjects. Average LV diastolic dimension was significantly increased in HFNEF subjects (5.2 +/- 0.8 cm) compared with healthy (4.8 +/- 0.6 cm) and HTN (4.9 +/- 0.6 cm) subjects. As a result, average calculated stroke volume (89 +/- 25 ml vs. 78 +/- 20 ml and 80 +/- 20 ml) and cardiac output (6.0 +/- 2.0 l/min vs. 4.8 +/- 1.3 l/min and 5.1 +/- 1.4 l/min) were increased in HFNEF compared with healthy and HTN subjects, respectively. CONCLUSIONS: As a group, HFNEF subjects have increased LV diastolic diameter and increased calculated stroke volume. They also have increased prevalence of multiple comorbidities, including anemia, renal dysfunction, and obesity, that can cause volume overload. These data suggest that extracardiac factors, via volume overload, may contribute to the pathophysiology of HFNEF in the elderly.
Keywords: Age Distribution; Aged; Body Size; Case-Control Studies; Cohort Studies; Comorbidity; Continental Population Groups; Echocardiography; Female; Heart Failure; Heart Ventricles; Humans; Hypertension; Longitudinal Studies; Male; Multivariate Analysis; Prevalence; Regression Analysis; Risk Factors; Sex Distribution; Stroke Volume; United States

White matter grade and ventricular volume on brain MRI as markers of longevity in the cardiovascular health study. - Kuller, Lewis H; Arnold, Alice M; Longstreth, W T; Manolio, Teri A; O'Leary, Daniel H; Burke, Gregory L; Fried, Linda P; Newman, Anne B (Neurobiol Aging, 2007)
High white matter grade (WMG) on magnetic resonance imaging (MRI) is a risk factor for dementia, stroke and disability. Higher ventricular size is a marker of brain "atrophy." In the Cardiovascular Health Study (CHS) (n=3245) mean age 75 years, 50% black and 40% men, we evaluated WM and ventricular grade (VG), total, cardiovascular and noncardiovascular mortality and longevity before and after adjusting for numerous determinants of longevity over an approximate 10-12 years of follow-up. A low WMG and VG was a marker for low total, cardiovascular and noncardiovascular mortality and for increased longevity over 10+ years of follow-up. We estimated that a 75-year-old with WMG below median would have about a 5-6 years greater longevity and for VG about 3 years, than above the median even after adjustment for numerous risk factors. Low WMG and VG on MRI is a powerful determinant of long-term survival among older individuals.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Biomarkers; Brain; Cardiovascular Diseases; Cerebral Ventricles; European Continental Ancestry Group; Female; Geriatric Assessment; Health Status; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Retrospective Studies; Risk Factors; Sex Factors

Abdominal aortic aneurysms, increasing infrarenal aortic diameter, and risk of total mortality and incident cardiovascular disease events: 10-year follow-up data from the Cardiovascular Health Study. - Freiberg, Matthew S; Arnold, Alice M; Newman, Anne B; Edwards, Matthew S; Kraemer, Kevin L; Kuller, Lewis H (Circulation, 2008)
BACKGROUND: Long-term data describing small abdominal aortic aneurysms (AAAs) and increasing infrarenal aortic diameters and their relationship to future surgical repair, total mortality, and incident cardiovascular disease (CVD) events, particularly among women, are sparse. METHODS AND RESULTS: In 1992 to 1993, 4734 Cardiovascular Health Study participants > or = 65 years old had an abdominal aortic ultrasound evaluation. Of those screened, 416 had an AAA (infrarenal aortic diameter > or = 3.0 cm or an infrarenal/suprarenal ratio > or = 1.2). By 2002, there were 56 surgical AAA repairs and 10 AAA-related deaths. A single ultrasound screening demonstrated that aneurysm dilation > or = 3 cm identified 68% of all AAA repairs over the next 10 years and 6 of the 10 AAA-related deaths in 4% of the total population and that a > or = 2.5-cm dilation identified 91% of all AAA repairs and 9 of the 10 deaths in 10% of the total population. With adjusted Cox proportional hazard models, AAAs were associated with a higher risk of total mortality (hazard ratio 1.44, 95% confidence interval 1.25 to 1.66) and incident CVD events (hazard ratio 1.52, 95% confidence interval 1.25 to 1.85). Compared with diameters < 2.0 cm, infrarenal aortic diameters 2.0 to < 3.0 cm were associated with increased risk of incident CVD events in women and total mortality in men. CONCLUSIONS: This study suggests that a 1-time screening of the abdominal aorta can acceptably identify individuals with a clinically significant AAA. Infrarenal aortic diameters > 2.0 cm are associated with a significantly increased risk of future CVD events and total mortality.
Keywords: Aged; Aged, 80 and over; Aorta, Abdominal; Aortic Aneurysm, Abdominal; Cause of Death; Female; Follow-Up Studies; Humans; Incidence; Intermittent Claudication; Kidney; Male; Prospective Studies; Risk Factors; Sex Distribution; Ultrasonography

Adiponectin and risk of coronary heart disease in older men and women. - Kizer, Jorge R; Barzilay, Joshua I; Kuller, Lewis H; Gottdiener, John S (J Clin Endocrinol Metab, 2008)
CONTEXT: Despite established insulin-sensitizing and antiatherogenic preclinical effects, epidemiological investigations of adiponectin have yielded conflicting findings, and its relationship with coronary heart disease (CHD) remains uncertain. OBJECTIVE: Our objective was to investigate the relationship between adiponectin and CHD in older adults. DESIGN, SETTING, AND PARTICIPANTS: This was a case-control study (n = 1386) nested within the population-based Cardiovascular Health Study from 1992--2001. Controls were frequency-matched to cases by age, sex, race, subclinical cardiovascular disease, and center. MAIN OUTCOME MEASURES: Incident CHD was defined as angina pectoris, percutaneous or surgical revascularization, nonfatal myocardial infarction (MI), or CHD death. A more restrictive CHD endpoint was limited to nonfatal MI and CHD death. RESULTS: Adiponectin exhibited significant negative correlations with baseline adiposity, insulin resistance, dyslipidemia, inflammatory markers, and leptin. After controlling for matching factors, adjustment for waist to hip ratio, hypertension, smoking, alcohol, low-density lipoprotein cholesterol, creatinine, and leptin revealed a modestly increased risk of incident CHD with adiponectin concentrations at the upper end [odds ratio = 1.37 (quintile 5 vs. 1-4), 95% confidence interval 1.02-1.84]. This association was stronger when the outcome was limited to nonfatal MI and fatal CHD (odds ratio = 1.69, 95% confidence interval 1.23-2.32). The findings were not influenced by additional adjustment for weight change, health status, or cystatin C, nor were they abolished by adjustment for potential mediators. CONCLUSIONS: This study shows an association between adiponectin and increased risk of first-ever CHD in older adults. Further research is needed to elucidate the basis for the concurrent beneficial and detrimental aspects of this relationship, and under what circumstances one or the other may predominate.
Keywords: Adiponectin; Age Factors; Aged; Aged, 80 and over; Body Weight; Case-Control Studies; Cohort Studies; Coronary Disease; Female; Humans; Longitudinal Studies; Male; Odds Ratio; Risk Factors

Albuminuria and dementia in the elderly: a community study. - Barzilay, Joshua I; Fitzpatrick, Annette L; Luchsinger, Jose; Yasar, Sevil; Bernick, Charles; Jenny, Nancy S; Kuller, Lewis H (Am J Kidney Dis, 2008)
BACKGROUND: Dementia is associated with microvascular disease of the retina. In this study, we examine whether cognitive status (normal cognition, mild cognitive impairment, and dementia) is associated with albuminuria, a microvascular disorder of the kidney. STUDY DESIGN: Cross-sectional analysis. SETTING & PARTICIPANTS: 2,316 participants from the Cardiovascular Health Cognition Study who underwent brain magnetic resonance imaging and testing for albuminuria. PREDICTOR: Doubling of albuminuria. OUTCOME: Dementia defined according to neuropsychological and clinical evaluation. MEASUREMENTS: Multinomial logistic modeling was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) of dementia and mild cognitive impairment with doubling of albuminuria compared with the odds with normal cognition. RESULTS: 283 participants (12.2%) had dementia, 344 (14.9%) had mild cognitive impairment, and 1,689 (72.9%) had normal cognition. Compared with participants with normal cognition, doubling of albuminuria was associated with increased odds of dementia (OR, 1.22; 95% CI, 1.15 to 1.29). Adjustment for prevalent cardiovascular disease and cardiovascular risk factors, lipid levels, C-reactive protein level, estimated glomerular filtration rate, and apolipoprotein E-4 genotype attenuated this association, but it remained statistically significant (OR, 1.12; 95% CI, 1.03 to 1.22). Mild cognitive impairment was associated with albuminuria on unadjusted analysis, but not with adjustment for other factors. LIMITATIONS: Results are cross-sectional; causality cannot be imputed. CONCLUSIONS: The odds of dementia increased in the presence of albuminuria. These findings suggest a role of shared susceptibility for microvascular disease in the brain and kidney in older adults.
Keywords: Age Factors; Aged; Aged, 80 and over; Albuminuria; Brain; Cognition; Cross-Sectional Studies; Dementia; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Odds Ratio; Population Surveillance; Prognosis; Retrospective Studies; Risk Factors

Alcohol consumption and lower extremity arterial disease among older adults: the cardiovascular health study. - Mukamal, Kenneth J; Kennedy, Margaret; Cushman, Mary; Kuller, Lewis H; Newman, Anne B; Polak, Joseph; Criqui, Michael H; Siscovick, David S (Am J Epidemiol, 2008)
Few studies of the relation of alcohol intake to lower-extremity arterial disease (LEAD) have included clinical events and objective measurements repeated longitudinally. As part of the Cardiovascular Health Study, a study of older adults from four US communities, 5,635 participants reported their use of beer, wine, and spirits yearly. Incident LEAD was identified by hospitalization surveillance. Technicians measured ankle-brachial index 6 years apart in 2,298 participants. A total of 172 cases of LEAD were documented during a mean of 7.5 years of follow-up between 1989 and 1999. Compared with abstention, the multivariable-adjusted hazard ratios were 1.10 (95% confidence interval (CI): 0.71, 1.71) for <1 alcoholic drink per week, 0.56 (95% CI: 0.33, 0.95) for 1-13 drinks per week, and 1.02 (95% CI: 0.53, 1.97) for > or =14 drinks per week (p for quadratic trend = 0.04). These relations were consistent within strata of sex, age, and apolipoprotein E genotype, and neither lipids nor inflammatory markers appeared to be important intermediates. Change in ankle-brachial index showed a similar relation (p for quadratic trend = 0.01). Alcohol consumption of 1-13 drinks per week in older adults may be associated with lower risk of LEAD, but heavier drinking is not associated with lower risk.
Keywords: Aged; Alcohol Drinking; Female; Follow-Up Studies; Health Surveys; Humans; Intermittent Claudication; Male; Prevalence; Prospective Studies; Risk Factors; Surveys and Questionnaires; Time Factors; United States

Ankle brachial index combined with Framingham Risk Score to predict cardiovascular events and mortality: a meta-analysis. - Fowkes, F G R; Murray, G D; Butcher, I; Heald, C L; Lee, R J; Chambless, L E; Folsom, A R; Hirsch, A T; Dramaix, M; deBacker, G; Wautrecht, J-C; Kornitzer, M; et al. (JAMA, 2008)
CONTEXT: Prediction models to identify healthy individuals at high risk of cardiovascular disease have limited accuracy. A low ankle brachial index (ABI) is an indicator of atherosclerosis and has the potential to improve prediction. OBJECTIVE: To determine if the ABI provides information on the risk of cardiovascular events and mortality independently of the Framingham risk score (FRS) and can improve risk prediction. DATA SOURCES: Relevant studies were identified. A search of MEDLINE (1950 to February 2008) and EMBASE (1980 to February 2008) was conducted using common text words for the term ankle brachial index combined with text words and Medical Subject Headings to capture prospective cohort designs. Review of reference lists and conference proceedings, and correspondence with experts was conducted to identify additional published and unpublished studies. STUDY SELECTION: Studies were included if participants were derived from a general population, ABI was measured at baseline, and individuals were followed up to detect total and cardiovascular mortality. DATA EXTRACTION: Prespecified data on individuals in each selected study were extracted into a combined data set and an individual participant data meta-analysis was conducted on individuals who had no previous history of coronary heart disease. RESULTS: Sixteen population cohort studies fulfilling the inclusion criteria were included. During 480,325 person-years of follow-up of 24,955 men and 23,339 women, the risk of death by ABI had a reverse J-shaped distribution with a normal (low risk) ABI of 1.11 to 1.40. The 10-year cardiovascular mortality in men with a low ABI (< or = 0.90) was 18.7% (95% confidence interval [CI], 13.3%-24.1%) and with normal ABI (1.11-1.40) was 4.4% (95% CI, 3.2%-5.7%) (hazard ratio [HR], 4.2; 95% CI, 3.3-5.4). Corresponding mortalities in women were 12.6% (95% CI, 6.2%-19.0%) and 4.1% (95% CI, 2.2%-6.1%) (HR, 3.5; 95% CI, 2.4-5.1). The HRs remained elevated after adjusting for FRS (2.9 [95% CI, 2.3-3.7] for men vs 3.0 [95% CI, 2.0-4.4] for women). A low ABI (< or = 0.90) was associated with approximately twice the 10-year total mortality, cardiovascular mortality, and major coronary event rate compared with the overall rate in each FRS category. Inclusion of the ABI in cardiovascular risk stratification using the FRS would result in reclassification of the risk category and modification of treatment recommendations in approximately 19% of men and 36% of women. CONCLUSION: Measurement of the ABI may improve the accuracy of cardiovascular risk prediction beyond the FRS.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Ankle; Atherosclerosis; Blood Pressure; Brachial Artery; Cardiovascular Diseases; Cohort Studies; Confidence Intervals; Female; Global Health; Humans; Male; Middle Aged; Odds Ratio; Predictive Value of Tests; Risk Assessment; Risk Factors; Severity of Illness Index

Association between lower digit symbol substitution test score and slower gait and greater risk of mortality and of developing incident disability in well-functioning older adults. - Rosano, Caterina; Newman, Anne B; Katz, Ronit; Hirsch, Calvin H; Kuller, Lewis H (J Am Geriatr Soc, 2008)
OBJECTIVES: To determine whether, in well-functioning older adults, a lower score on the Digit Symbol Substitution Test (DSST) and slower gait are associated with greater risk of mortality and of developing incident disability independent of other risk factors, including brain structural abnormalities (white matter hyperintensities, brain infarcts, ventricular enlargement) and whether the combination of varying levels of DSST score and gait speed are associated with a greater risk of mortality and disability than low DSST or slow gait alone. DESIGN: Observational cohort study. SETTING: Community. PARTICIPANTS: Three thousand one hundred fifty-six (43% men, 29% black, mean age 70.4) participants in the Cardiovascular Health Study (CHS), free from stroke and physical disability and with a modified Mini-Mental State Examination (3MS) score of 80 or higher. MEASUREMENTS: Total mortality and incident disability (self-report of any difficulty performing one or more of the six activities of daily living) ascertained over a median follow-up time of 8.4 years. RESULTS: By the end of follow-up, 704 participants had died and 1,096 had incident disability. In Cox proportional hazards models adjusted for age, sex, race, education, cardiovascular disease, and brain magnetic resonance imaging abnormalities, lower DSST score and slower gait remained significantly associated with greater risk of mortality and of incident disability. Mortality rates were higher in those who had both low DSST score (<27 points) and slow gait (speed <1.0 m/s) than in those who had only low DSST score, only slow gait, or neither (rates per 1,000 person years (p-y): 61.2, 42.8, 20.8, and 16.3, respectively). A similar risk gradient was observed for incident disability (82.0, 57.9, 47.9, and 36.0/1,000 p-y, respectively). CONCLUSION: In well-functioning older adults, low DSST score and slow gait, alone or in combination, could be risk factors for mortality and for developing disability, independent of other risk factors, including measures of brain integrity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Analysis of Variance; Atrophy; Brain; Brain Diseases; Cause of Death; Cohort Studies; Disability Evaluation; Discrimination Learning; Female; Gait; Humans; Male; Memory, Short-Term; Mobility Limitation; Neuropsychological Tests; Pattern Recognition, Visual; Psychometrics; Psychomotor Performance; Risk Factors

Associations between common fibrinogen gene polymorphisms and cardiovascular disease in older adults. The Cardiovascular Health Study. - Carty, Cara L; Cushman, Mary; Jones, Daniel; Lange, Leslie A; Hindorff, Lucia A; Rice, Kenneth; Jenny, Nancy S; Durda, J Peter; Walston, Jeremy; Carlson, Christopher S; Nickerson, Debbie; Tracy, Russell P; et al. (Thromb Haemost, 2008)
Elevated plasma fibrinogen is a risk factor for cardiovascular disease (CVD), but associations between fibrinogen single nucleotide polymorphisms (SNPs) and disease risk are inconsistent. We investigated whether common (> or = 5% minor allele frequency) variation in the fibrinogen genes (FGA, FGB, FGG) is associated with fibrinogen concentration, carotid artery intima-medial thickness (IMT) and risk of incident myocardial infarction (MI), ischemic stroke and CVD mortality in European- (EA) and African-descent (AA) adults (> or = 65 years) from the Cardiovascular Health Study. TagSNPs were genotyped in 3,969 EA and 719 AA free of MI or stroke at baseline. Race-specific models included multiple testing correction and adjustment for sex, age and site. Among EA, minor alleles of FGA3807, FGB1437 and FGG902 were associated with higher fibrinogen levels; whereas FGA251, FGA2224, FGA6534 and FGG10034 were associated with lower levels, p<0.004 for each. Strongest associations were seen for FGB1437; each additional copy of the minor allele was associated with 13 mg/dl (95%CI: 9-16) higher fibrinogen level. Similar trends in AA were not significant. Fibrinogen haplotypes were not significantly associated with internal or common carotid IMT. No associations with MI or CVD mortality were seen in EA, though FGB1038 and FGG902 were significantly associated with increased and decreased risk of stroke in men, respectively, as were related haplotypes. FGB1038 was also associated with CVD mortality in AA, HR = 1.9 (95%CI: 1.3-2.7). In conclusion, while fibrinogen genetic variation was strongly associated with fibrinogen levels, there was less evidence of association with the more complex outcomes of IMT and CVD events.
Keywords: African Americans; Age Factors; Aged; Brain Ischemia; Cardiovascular Diseases; Carotid Artery Diseases; European Continental Ancestry Group; Female; Fibrinogen; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Population Surveillance; Proportional Hazards Models; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke; United States

Cardiovascular risk factors and incident acute renal failure in older adults: the cardiovascular health study. - Mittalhenkle, Anuja; Stehman-Breen, Catherine O; Shlipak, Michael G; Fried, Linda F; Katz, Ronit; Young, Bessie A; Seliger, Stephen; Gillen, Daniel; Newman, Anne B; Psaty, Bruce M; Siscovick, David (Clin J Am Soc Nephrol, 2008)
BACKGROUND AND OBJECTIVES: Although the elderly are at increased risk for acute renal failure, few prospective studies have identified risk factors for acute renal failure in the elderly. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: The associations of cardiovascular disease risk factors, subclinical cardiovascular disease, and clinical coronary heart disease with the risk for development of acute renal failure were examined in older adults in the Cardiovascular Health Study, a prospective cohort study of community-dwelling older adults. Incident hospitalized cases of acute renal failure were identified through hospital discharge International Classification of Diseases, Ninth Revision codes and confirmed through physician diagnoses of acute renal failure in discharge summaries. RESULTS: Acute renal failure developed in 225 (3.9%) of the 5731 patients during a median follow-up period of 10.2 yr. In multivariate analyses, diabetes, current smoking, hypertension, C-reactive protein, and fibrinogen were associated with acute renal failure. Prevalent coronary heart disease was associated with incident acute renal failure, and among patients without prevalent coronary heart disease, subclinical vascular disease measures were also associated with acute renal failure: Low ankle-arm index (< or =0.9), common carotid intima-media thickness, and internal carotid intima-media thickness. CONCLUSIONS: In this large, population-based, prospective cohort study, cardiovascular risk factors and both subclinical and clinical vascular disease were associated with incident acute renal failure in the elderly.
Keywords: Acute Kidney Injury; Aged; Cardiovascular Diseases; Female; Follow-Up Studies; Humans; Male; Prospective Studies; Risk Factors

Chronic kidney disease increases risk for venous thromboembolism. - Wattanakit, Keattiyoat; Cushman, Mary; Stehman-Breen, Catherine; Heckbert, Susan R; Folsom, Aaron R (J Am Soc Nephrol, 2008)
Chronic kidney disease (CKD) is associated with increased risk for cardiovascular disease morbidity and mortality, but its association with incident venous thromboembolism (VTE) in non-dialysis-dependent patients has not been evaluated in a community-based population. With the use of data from the Longitudinal Investigation of Thromboembolism Etiology (LITE) study, 19,073 middle-aged and elderly adults were categorized on the basis of estimated GFR, and cystatin C (available in 4734 participants) was divided into quintiles. During a mean follow-up time of 11.8 yr, 413 participants developed VTE. Compared with participants with normal kidney function, relative risk for VTE was 1.28 (95% confidence interval [CI] 1.02 to 1.59) for those with mildly decreased kidney function and 2.09 (95% CI 1.47 to 2.96) for those with stage 3/4 CKD, when adjusted for age, gender, race, and center. After additional adjustment for cardiovascular disease risk factors, an increased risk for VTE was still observed in participants with stage 3/4 CKD, with a multivariable adjusted relative risk of 1.71 (95% CI 1.18 to 2.49). There was no significant association between cystatin C and VTE. In conclusion, middle-aged and elderly patients with CKD (stages 3 through 4) are at increased risk for incident VTE, suggesting that VTE prophylaxis may be particularly important in this population.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Diabetic Nephropathies; Factor VIII; Female; Glomerular Filtration Rate; Humans; Hypertension; Kidney Failure, Chronic; Longitudinal Studies; Male; Middle Aged; Risk Factors; Thromboembolism; Venous Thrombosis

Coronary artery calcium and physical function in older adults: the Cardiovascular Health Study. - Inzitari, Marco; Naydeck, Barbara L; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2008)
BACKGROUND: In older adults without clinical cardiovascular disease, coronary artery calcium (CAC) is associated with other subclinical vascular diseases, which, in turn, predict physical dysfunction. However, the association between CAC and physical function is unstudied. METHODS: In 387 older community-dwellers from the Cardiovascular Health Study without clinical cardiovascular diseases (mean age +/- standard deviation = 78.7 +/- 3.7, 35% men, 22% African Americans), CAC was measured using electron beam tomography, and physical performance was assessed by usual pace gait speed, chair stand, and tandem stand. Differences in physical performance across CAC quartiles were investigated in the whole cohort and by gender. Associations with gait speed (m/s) were assessed in multivariable models using both the continuous form of CAC score (log(CAC)) and quartiles of CAC, adjusting for demographics and comorbidities. RESULTS: No differences in physical performance were observed across CAC quartiles in the whole group. In gender-stratified analyses, a significant association was shown among women, who had progressively lower gait speed across CAC quartiles: Those with CAC > 220 walked more than 0.1 m/s slower than those with CAC < 35 (age-adjusted ptrend =.017). After multivariable adjustment, the association remained statistically significant for women in both linear (log(CAC) and gait speed, p =.025) and logistic models: Each of the top three CAC quartiles (35-220, 221-659, and > or = 660) had a more than twofold odds of walking slower than 1 m/s, compared to the lowest CAC quartile (< 35; p =.021). CONCLUSIONS: In this sample of older community-dwellers without overt cardiovascular disease, CAC was inversely related to gait speed in women, but not in men.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Calcinosis; Coronary Artery Disease; Female; Geriatric Assessment; Humans; Male; Regression Analysis; Risk Factors; Tomography, X-Ray Computed; Walking

Dietary fish and omega-3 fatty acid consumption and heart rate variability in US adults. - Mozaffarian, Dariush; Stein, Phyllis K; Prineas, Ronald J; Siscovick, David S (Circulation, 2008)
BACKGROUND: Fish and omega-3 fatty acid consumption reduce risk of cardiac death, but mechanisms are not well established. Heart rate variability (HRV) predicts cardiac death and reflects specific electrophysiological pathways and influences. We hypothesized that habitual consumption of fish and marine omega-3 fatty acids would be associated with more favorable HRV, elucidating electrophysiological influences and supporting effects on clinical risk. METHODS AND RESULTS: In a population-based cohort of older US adults, we evaluated cross-sectional associations of usual dietary fish and omega-3 consumption during the prior year and ECG-derived (n=4263) and 24-hour Holter monitor-derived (n=1152) HRV. After multivariable adjustment, consumption of tuna or other broiled/baked fish was associated with specific HRV components, including indices suggesting greater vagal predominance and moderated baroreceptor responses (eg, higher root mean square successive differences of normal-to-normal intervals [P=0.001]; higher normalized high-frequency power [P=0.008]; and lower low-frequency/high-frequency ratio [P=0.03]) and less erratic sinoatrial node firing (eg, lower Poincaré ratio [P=0.02] and higher short-term fractal scaling exponent [P=0.005]) but not measures of circadian fluctuations (eg, 24-hour standard deviation of normal-to-normal intervals). Findings were similar for estimated dietary consumption of marine omega-3 fatty acids. For magnitudes of observed differences in HRV comparing the highest to lowest category of fish intake, differences in relative risk of cardiac death during 10.8 years of follow-up ranged from 1.1% (for difference in standard deviation of normal-to-normal intervals) to 5.9% and 8.4% (for differences in Poincaré ratio and short-term fractal scaling exponent) lower risk. CONCLUSIONS: Habitual tuna/other fish and marine omega-3 consumption are associated with specific HRV components in older adults, particularly indices of vagal activity, baroreceptor responses, and sinoatrial node function. Cellular mechanisms and implications for clinical risk deserve further investigation.
Keywords: Aged; Aged, 80 and over; Animals; Cardiovascular Diseases; Cohort Studies; Cross-Sectional Studies; Electrocardiography; Fatty Acids, Omega-3; Female; Fishes; Heart Rate; Humans; Male; Risk Factors; Seafood; Tuna; United States

Distribution and correlates of lipoprotein-associated phospholipase A2 in an elderly cohort: the Cardiovascular Health Study. - Furberg, Curt D; Nelson, Jeanenne J; Solomon, Cam; Cushman, Mary; Jenny, Nancy Swords; Psaty, Bruce M (J Am Geriatr Soc, 2008)
OBJECTIVES: To determine whether high levels of lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) are associated with prevalent cardiovascular disease (CVD) and to evaluate factors most influencing Lp-PLA(2) levels in a community-based cohort of older adults. DESIGN: Cross-sectional. SETTING: The Cardiovascular Health Study (CHS), a population-based cohort study of men and women aged 65 and older. PARTICIPANTS: Five thousand five hundred thirty-one CHS participants. MEASUREMENTS: Levels of Lp-PLA(2) activity were determined using stored blood samples from the baseline examination. RESULTS: Mean Lp-PLA(2) was higher in participants with electrocardiographically determined ventricular conduction defect and major Q-wave abnormality and was positively correlated with left ventricular (LV) mass. It was high in those with echocardiographically determined abnormal LV ejection fraction, which persisted after adjustment. Mean Lp-PLA(2) was also higher in participants with mild renal insufficiency and kidney disease. After multivariable adjustment, there was a modest but significant 27% greater risk of prevalent CHF per standard deviation increment of Lp-PLA(2) and a modest but significant 12% greater risk of prevalent myocardial infarction. Lp-PLA(2) was weakly but mainly most strongly correlated with cholesterol and lipoproteins, but those correlations were not especially strong. Lp-PLA(2) was weakly positively correlated with soluble intercellular adhesion molecule-1 but not interleukin-6. In total, all factors considered could explain only 29% of Lp-PLA(2) activity. CONCLUSION: Novel findings in the study are the associations, in those aged 65 and older, between Lp-PLA(2) activity and LV dysfunction, CHF, and renal disease. CVD risk factors only minimally explain levels of Lp-PLA(2).
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Atherosclerosis; Body Mass Index; Cardiac Output, Low; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Cross-Sectional Studies; Electrocardiography; Female; Heart Failure; Humans; Hypertrophy, Left Ventricular; Long QT Syndrome; Male; Reference Values; Renal Insufficiency; Risk Factors; Statistics as Topic; Triglycerides

Enhanced risk for Alzheimer disease in persons with type 2 diabetes and APOE epsilon4: the Cardiovascular Health Study Cognition Study. - Irie, Fumiko; Fitzpatrick, Annette L; Lopez, Oscar L; Kuller, Lewis H; Peila, Rita; Newman, Anne B; Launer, Lenore J (Arch Neurol, 2008)
BACKGROUND: Diabetes and the apolipoprotein E epsilon4 allele (APOE epsilon4) increase the risk for Alzheimer disease (AD). We hypothesize that APOE epsilon4 may modify the risk for AD in individuals with diabetes. OBJECTIVE: To examine the joint effect of type 2 diabetes and APOE epsilon4 on the risk of AD, AD with vascular dementia (mixed AD), and vascular dementia without AD. DESIGN: The Cardiovascular Health Study (CHS) Cognition Study (1992-2000) is a prospective study designed to identify all existing and new cases of dementia among study participants. Diagnoses were made according to international criteria for dementia and subtypes. There were 2547 dementia-free participants in the CHS Cognition Study cohort with complete information on APOE epsilon4 and type 2 diabetes status; among these, 411 new cases of dementia developed. Risk of dementia was estimated with a Cox proportional hazard model adjusted for age and other demographic and cardiovascular risk factors. RESULTS: Compared with those who had neither type 2 diabetes nor APOE epsilon4, those with both factors had a significantly higher risk of AD (hazard ratio, 4.58; 95% confidence interval, 2.18-9.65) and mixed AD (hazard ratio, 3.89; 95% confidence interval, 1.46-10.40). CONCLUSION: These data suggest that having both diabetes and APOE epsilon4 increases the risk of dementia, especially for AD and mixed AD.
Keywords: African Americans; Age Factors; Aged; Alzheimer Disease; Apolipoprotein E4; Cognition; Cohort Studies; Confidence Intervals; Dementia, Vascular; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Genotype; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors

Hemostatic and inflammatory risk factors for intracerebral hemorrhage in a pooled cohort. - Sturgeon, Jared D; Folsom, Aaron R; Longstreth, W T; Shahar, Eyal; Rosamond, Wayne D; Cushman, Mary (Stroke, 2008)
BACKGROUND AND PURPOSE: The purpose of this study was to identify novel risk factors for intracerebral hemorrhagic stroke (ICH). METHODS: Risk factors were assessed at baseline in a pooled cohort of the Atherosclerosis Risk in Communities Study (ARIC) and the Cardiovascular Health Study (CHS) involving 21,680 adults aged 45 or over. Over 263,489 person-years of follow-up, we identified 135 incident ICH events. RESULTS: In multivariable models, for each SD higher baseline level of fibrinogen, the relative rate of incident ICH increased 35% (95% CI, 17% to 55%). Fibrinogen was more strongly related to ICH in ARIC than in CHS. In multivariable models, those with von Willebrand factor levels above the median were 1.72 (95% CI, 0.97 to 3.03) times more likely to have an incident ICH as those below the median. Factor VIII was significantly positively related to ICH in ARIC (relative rate per standard deviation of 1.31; 95% CI, 1.07 to 1.62), but not in CHS. There was no relation in multivariable models between lipoprotein (a), Factor VII, white blood cell count, or C-reactive protein and ICH. CONCLUSIONS: Greater plasma fibrinogen and, to some degree, von Willebrand factor were associated with increased rates of ICH in these prospective studies, whereas Factor VIII was related to ICH in younger ARIC study participants only.
Keywords: Age Distribution; Aged; Biomarkers; C-Reactive Protein; Cerebral Hemorrhage; Cohort Studies; Factor VIII; Female; Fibrinogen; Follow-Up Studies; Humans; Leukocyte Count; Lipoprotein(a); Male; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Stroke; United States; Vasculitis; von Willebrand Factor

High insulinlike growth factor binding protein 1 level predicts incident congestive heart failure in the elderly. - Kaplan, Robert C; McGinn, Aileen P; Pollak, Michael N; Kuller, Lewis; Strickler, Howard D; Rohan, Thomas E; Cappola, Anne R; Xue, XiaoNan; Psaty, Bruce M (Am Heart J, 2008)
BACKGROUND: Low levels of insulinlike growth factor 1 (IGF-I) may influence the development of age-related cardiovascular diseases including congestive heart failure (CHF). Insulinlike growth factor binding protein 1 (IGFBP-1), which increases during catabolic states and inhibits anabolic IGF-I effects, is increased in patients with CHF and has been associated prospectively with increased mortality among older adults and survivors of myocardial infarction. We investigated the association between fasting plasma levels of IGF-I, IGFBP-1, IGFBP-3, and insulin and risk of incident CHF in the prospective Cardiovascular Health Study. METHODS: From among 5,888 adults 65 years old and older in the Cardiovascular Health Study, we studied 566 incident CHF cases and 1,072 comparison subjects after exclusion of underweight individuals (body mass index <18.5 kg/m(2)) and insulin users. Hazard ratios (HRs) with 95% CIs for CHF were estimated after adjustment for age, race, sex, hypertension, systolic blood pressure, lipid levels, left ventricular hypertrophy, coronary disease, C-reactive protein, health status, diabetes, and body mass index. RESULTS: High baseline IGFBP-1 level was a significant predictor of CHF, independent of established CHF risk factors and inflammation markers. The HR per SD of IGFBP-1 was 1.22 (95% CI 1.07-1.39, P < .01). Relative to the lowest IGFBP-1 tertile, the HR was 1.29 (95% CI 0.96-1.74, P = .09) for the second IGFBP-1 tertile and 1.47 (95% CI 1.06-2.04; P = .02) for the highest IGFBP-1 tertile (tertile cut points 19.5 and 35.8 ng/mL). Total IGF-I, IGFBP-3, or insulin levels had no association with CHF after adjustment for CHF risk factors. CONCLUSIONS: High circulating IGFBP-1 level may be a CHF risk factor among older adults.
Keywords: Aged; Aged, 80 and over; Female; Heart Failure; Humans; Incidence; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Predictive Value of Tests; Prospective Studies; Risk Factors

Higher levels of inflammation factors and greater insulin resistance are independently associated with higher heart rate and lower heart rate variability in normoglycemic older individuals: the Cardiovascular Health Study. - Stein, Phyllis K; Barzilay, Joshua I; Chaves, Paulo H M; Traber, Jennifer; Domitrovich, Peter P; Heckbert, Susan R; Gottdiener, John S (J Am Geriatr Soc, 2008)
OBJECTIVES: To explore the relationship between (1) insulin resistance and inflammation factors with (2) higher heart rate (HR) and lower heart rate variability (HRV) in normoglycemic older adults. DESIGN: Cross-sectional population-based study. PARTICIPANTS: Five hundred forty-five adults aged 65 and older with normoglycemia (fasting glucose <100 mg/dL) who participated in the Cardiovascular Health Study. MEASUREMENTS: Serum levels of three inflammation proteins (C-reactive protein (CRP), interleukin 6 (IL-6), and fibrinogen); insulin resistance, quantified according to the homeostasis assessment model (HOMA-IR); HR; and four representative measures of HRV (the standard deviation of normal beat to beat intervals (SDNN), the root mean square of successive differences (rMSSD), very low frequency power (VLF), and the low- to high-frequency power ratio (LF/HF)) derived from 24-hour Holter recordings. RESULTS: High CRP and IL-6 levels were associated with higher HR and lower SDNN and VLF after adjustment for multiple covariates, including HOMA-IR and clinical cardiovascular disease. High IL-6 was also associated with lower LF/HF. Significant univariate inverse relationships between HOMA-IR and HR and HRV were also found, but the strengths of these relationships were attenuated after adjustment for inflammation factors. CONCLUSION: Increased levels of inflammation markers and HOMA-IR are associated with higher HR and lower HRV. These findings suggest that inflammation may contribute to the pathogenesis of cardiovascular autonomic decline in older adults.
Keywords: Aged; C-Reactive Protein; Cardiovascular Diseases; Cross-Sectional Studies; Electrocardiography, Ambulatory; Female; Fibrinogen; Heart Rate; Humans; Inflammation Mediators; Insulin Resistance; Interleukin-6; Male; Risk Factors

Incident physical disability in people with lower extremity peripheral arterial disease: the role of cardiovascular disease. - Brach, Jennifer S; Solomon, Cam; Naydeck, Barbara L; Sutton-Tyrrell, Kim; Enright, Paul L; Jenny, Nancy Swords; Chaves, Paulo M; Newman, Anne B (J Am Geriatr Soc, 2008)
OBJECTIVES: To evaluate the risk of incident physical disability and the decline in gait speed over a 6-year follow-up associated with a low ankle-arm index (AAI) in older adults. DESIGN: Observational cohort study. SETTING: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Allegheny County, Pennsylvania. PARTICIPANTS: Four thousand seven hundred five older adults, 58% women and 17.6% black, participating in the Cardiovascular Health Study. MEASUREMENTS: AAI was measured in 1992/93 (baseline). Self-reported mobility, activity of daily living (ADL), and instrumental activity of daily living (IADL) disability and gait speed were recorded at baseline and at 1-year intervals over 6 years of follow-up. Mobility disability was defined as any difficulty walking half a mile and ADL and IADL disability was defined as any difficulty with 11 specific ADL and IADL tasks. Individuals with mobility, ADL, or IADL disability at baseline were excluded from the respective incident disability analyses. RESULTS: Lower baseline AAI values were associated with increased risk of mobility disability and ADL/IADL disability. Clinical cardiovascular disease (CVD), diabetes mellitus, and interim CVD events partially explained these associations for mobility disability and clinical CVD and diabetes mellitus partially explained these associations for ADL and IADL disability. Individuals with an AAI less than 0.9 had on average a mean decrease in gait speed of 0.02 m/s per year, or a decline of 0.12 m/s over the 6-year follow-up. Prevalent CVD partly explained this decrease but interim CVD events did not further attenuate it. CONCLUSION: Low AAI serves as marker of future disability risk. Reduction of disability risk in patients with a low AAI should consider cardiovascular comorbidity and the prevention of additional disabling CVD events.
Keywords: Activities of Daily Living; Aged; Cardiovascular Diseases; Cohort Studies; Comorbidity; Disability Evaluation; Female; Gait; Geriatric Assessment; Humans; Lower Extremity; Male; Mobility Limitation; Peripheral Vascular Diseases; Proportional Hazards Models; Risk Assessment; Risk Factors; United States

Insulin-like growth factors, their binding proteins, and prostate cancer risk: analysis of individual patient data from 12 prospective studies. - Roddam, Andrew W; Allen, Naomi E; Appleby, Paul; Key, Timothy J; Ferrucci, Luigi; Carter, H Ballentine; Metter, E Jeffrey; Chen, Chu; Weiss, Noel S; Fitzpatrick, Annette; Hsing, Ann W; Lacey, James V; et al. (Ann Intern Med, 2008)
BACKGROUND: Some, but not all, published results have shown an association between circulating blood levels of some insulin-like growth factors (IGFs) and their binding proteins (IGFBPs) and the subsequent risk for prostate cancer. PURPOSE: To assess the association between levels of IGFs and IGFBPs and the subsequent risk for prostate cancer. DATA SOURCES: Studies identified in PubMed, Web of Science, and CancerLit. STUDY SELECTION: The principal investigators of all studies that published data on circulating concentrations of sex steroids, IGFs, or IGFBPs and prostate cancer risk using prospectively collected blood samples were invited to collaborate. DATA EXTRACTION: Investigators provided individual participant data on circulating concentrations of IGF-I, IGF-II, IGFBP-II, and IGFBP-III and participant characteristics to a central data set in Oxford, United Kingdom. DATA SYNTHESIS: The study included data on 3700 men with prostate cancer and 5200 control participants. On average, case patients were 61.5 years of age at blood collection and received a diagnosis of prostate cancer 5 years after blood collection. The greater the serum IGF-I concentration, the greater the subsequent risk for prostate cancer (odds ratio [OR] in the highest vs. lowest quintile, 1.38 [95% CI, 1.19 to 1.60]; P < 0.001 for trend). Neither IGF-II nor IGFBP-II concentrations were associated with prostate cancer risk, but statistical power was limited. Insulin-like growth factor I and IGFBP-III were correlated (r = 0.58), and although IGFBP-III concentration seemed to be associated with prostate cancer risk, this was secondary to its association with IGF-I levels. Insulin-like growth factor I concentrations seemed to be more positively associated with low-grade than high-grade disease; otherwise, the association between IGFs and IGFBPs and prostate cancer risk had no statistically significant heterogeneity related to stage or grade of disease, time between blood collection and diagnosis, age and year of diagnosis, prostate-specific antigen level at recruitment, body mass index, smoking, or alcohol intake. LIMITATIONS: Insulin-like growth factor concentrations were measured in only 1 sample for each participant, and the laboratory methods to measure IGFs differed in each study. Not all patients had disease stage or grade information, and the diagnosis of prostate cancer may differ among the studies. CONCLUSION: High circulating IGF-I concentrations are associated with a moderately increased risk for prostate cancer.
Keywords: Aged; Humans; Insulin-Like Growth Factor Binding Protein 2; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor Binding Proteins; Insulin-Like Growth Factor I; Insulin-Like Growth Factor II; Male; Middle Aged; Prospective Studies; Prostatic Neoplasms; Risk Factors; Somatomedins

Knee height and arm span: a reflection of early life environment and risk of dementia. - Huang, T L; Carlson, M C; Fitzpatrick, A L; Kuller, L H; Fried, L P; Zandi, P P (Neurology, 2008)
OBJECTIVES: To determine if anthropometric measures, as markers of early life environment, are associated with risk of dementia, Alzheimer disease (AD), and vascular dementia (VaD). METHODS: A total of 2,798 subjects were followed as part of the Cardiovascular Health Cognition Study for an average of 5.4 years; 480 developed dementia. Knee height was measured 3 years prior to and arm span 4 years after the study's baseline. Cox proportional hazard models were used to examine their association with subsequent risk of dementia, AD, and VaD. RESULTS: Among women, greater knee height and arm span were associated with lower risks of dementia (knee height: HR per 1-inch increase 0.84; 95% CI 0.74-0.96; arm span: HR per 1-inch increase 0.93; 95% CI 0.88-0.98) and AD (knee height: HR per 1-inch increase 0.78; 95% CI 0.65-0.93; arm span: HR per 1-inch increase 0.90; 95% CI 0.85-0.96). Women in the lowest quartile of arm span had approximately 1.5 times greater risk of dementia (HR 1.45; 95% CI 1.03-2.05) and AD (HR 1.70; 95% CI 1.10-2.62) than other women. Among men, only arm span was associated with lower risks of dementia (HR per 1-inch increase 0.94; 95% CI 0.89-1.00) and AD (HR per 1-inch increase 0.92; 95% CI 0.84-1.00). For each gender, knee height was not associated with VaD, while arm span was associated with a nonsignificant lower risk of VaD. CONCLUSIONS: Our findings with knee height and arm span are consistent with previous reports and suggest early life environment may play an important role in the determination of future dementia risk.
Keywords: Aged; Aged, 80 and over; Aging; Anthropometry; Arm; Body Height; Brain; Child; Child, Preschool; Dementia; Environment; Female; Follow-Up Studies; Humans; Infant; Infant, Newborn; Knee; Male; Middle Aged; Prospective Studies; Risk Factors; Sex Characteristics; Skeleton

Left ventricular mass predicts heart failure not related to previous myocardial infarction: the Cardiovascular Health Study. - de Simone, Giovanni; Gottdiener, John S; Chinali, Marcello; Maurer, Mathew S (Eur Heart J, 2008)
AIMS: The relationship of left ventricular hypertrophy (LVH) to incident heart failure (HF) not attributable to myocardial infarction (MI) has not been defined. We assessed whether LVH is an independent predictor of MI-independent HF. METHODS AND RESULTS: LVH was assessed by echocardiographic LV mass index (in g/m2.7) and excess of LV mass (eLVM, in % of the observed value) relative to the amount predicted by sex, stroke work, and height, using a prognostically validated equation in 2078 participants of Cardiovascular Health Study without prevalent MI and normal systolic function. Increasing eLVM was associated with progressively increasing left atrial dimension and concentric geometry, decreasing systolic (P < 0.0001), and diastolic function (P < 0.04). After adjustment for age, sex, obesity, diabetes, hypertension, and antihypertensive therapy, and accounting for by incident MI, hazard of HF increased by 1% for each 1% increase in eLVM and by 3% for each g/m2.7 increase in LV mass index (both P < 0.0001). The results were confirmed when also C-reactive protein and measures of systolic (endocardial shortening) and diastolic function (categories of E/A ratio) were added to the Cox models. CONCLUSION: In an elderly population, LVH, measured as LV mass index or eLVM is an independent predictor of incident HF not related to prevalent or incident MI.
Keywords: Aged; Aged, 80 and over; Diabetic Angiopathies; Echocardiography; Female; Heart Failure; Humans; Hypertension; Hypertrophy, Left Ventricular; Male; Myocardial Infarction; Obesity; Risk Factors

Lipoprotein-associated phospholipase A2 and risk of venous thrombosis in older adults. - Olson, Nels; O'Meara, Ellen S; Jenny, Nancy S; Folsom, Aaron R; Bovill, Edwin G; Furberg, Curt D; Heckbert, Susan R; Psaty, Bruce M; Cushman, Mary (Am J Hematol, 2008)
Lipoprotein-associated phospholipase A2 (Lp-PLA2) is an enzyme involved in inflammation and platelet function. Inherited deficiency and elevated levels are associated with atherosclerosis. Given potential common etiologies of atherosclerosis and venous thrombosis (VT), we hypothesized that low and high Lp-PLA2 would be associated with VT risk. Lp-PLA(2) mass and activity were measured in baseline samples of Cardiovascular Health Study participants (5,888 men and women age > or =65), excluding 354 reporting pre-baseline VT. The study endpoint was VT unrelated to cancer after 11.6 years follow-up. Hazard ratios were estimated using Cox proportional hazard models, adjusting for age, race, sex, and body-mass index. With 129 cases of VT, there was no association of Lp-PLA2 activity with risk. Adjusted hazard ratios were 1.19 (CI 0.62, 2.29) and 0.87 (CI 0.43, 1.76) for the lowest and highest decile, respectively, compared to the 10-25th percentile. Corresponding hazard ratios for Lp-PLA2 mass were 1.63 (CI 0.79, 3.34) and 1.33 (CI 0.61, 2.87). Results were robust to several definitions of low or high Lp-PLA2. While the association of Lp-PLA(2) levels with arterial disease events implies a role for this enzyme in atherogenesis, our findings suggest that it is not prothrombotic.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Female; Humans; Male; Risk Factors; Venous Thrombosis

Metabolic syndrome, endothelial dysfunction, and risk of cardiovascular events: the Northern Manhattan Study (NOMAS). - Suzuki, Takeki; Hirata, Kumiko; Elkind, Mitchell S V; Jin, Zhezhen; Rundek, Tanja; Miyake, Yumiko; Boden-Albala, Bernadette; Di Tullio, Marco R; Sacco, Ralph; Homma, Shunichi (Am Heart J, 2008)
BACKGROUND: Metabolic syndrome (MetS) predisposes to cardiovascular disease. Endothelial dysfunction is thought to be an important factor in the pathogenesis of atherosclerosis. We tested the hypothesis that both MetS and endothelial dysfunction are vascular risk factors and provide additive prognostic values in predicting cardiovascular events in a multiethnic community sample. METHODS: The study population consisted of 819 subjects (467 female, mean age 66.5 +/- 8.8 years, 66% Hispanic) enrolled in the NOMAS. Metabolic syndrome was defined using the revised Adult Treatment Panel III criteria. Brachial artery flow-mediated dilation (FMD) was measured using high-resolution ultrasound. Endothelial dysfunction was defined as FMD <8.44% (lower 3 quartiles). Cox proportional hazards models were used to assess the effect of MetS and endothelial dysfunction on risk of cardiovascular events. RESULTS: During 81 +/- 21 months of follow-up, events occurred in 84 subjects. Metabolic syndrome was independently associated with cardiovascular events in a multivariate model, including cardiovascular risk factors (adjusted hazard ratio 2.08, 95% CI 1.27-3.40). Subjects with both MetS and endothelial dysfunction were at higher risk for cardiovascular events than those with either one of them alone (adjusted hazard ratio 2.60, 95% CI 1.14-5.92). CONCLUSIONS: Metabolic syndrome is associated with incident cardiovascular events. Combined use of MetS and FMD identifies those who are at higher risk of cardiovascular events. Metabolic syndrome and noninvasive FMD testing can be used concurrently for cardiovascular risk prediction.
Keywords: Adult; Aged; Brachial Artery; Endothelium, Vascular; Female; Humans; Kaplan-Meier Estimate; Male; Metabolic Syndrome; Middle Aged; Prognosis; Prospective Studies; Risk Factors; Stroke; Vascular Diseases

No advantage of A beta 42-lowering NSAIDs for prevention of Alzheimer dementia in six pooled cohort studies. - Szekely, C A; Green, R C; Breitner, J C S; Østbye, T; Beiser, A S; Corrada, M M; Dodge, H H; Ganguli, M; Kawas, C H; Kuller, L H; Psaty, B M; Resnick, S M; et al. (Neurology, 2008)
INTRODUCTION: Observational studies show reduced incidence of Alzheimer dementia (AD) in users of nonsteroidal anti-inflammatory drugs (NSAIDs). One hypothesis holds that the subset of NSAIDs known as selective A beta(42)-lowering agents (SALAs) is responsible for this apparent reduction in AD risk. METHODS: We pooled individual-level data from six prospective studies to obtain a sufficient sample to examine AD risk in users of SALA vs non-SALA NSAIDs. RESULTS: Of 13,499 initially dementia-free participants (70,863 person-years), 820 developed incident AD. Users of NSAIDs (29.6%) showed reduced risk of AD (adjusted hazard ratio [aHR] 0.77, 95% CI 0.65-0.91). The point estimates were similar for SALAs (aHR 0.87, CI 0.72-1.04) and non-SALAs (aHR 0.75, CI 0.56-1.01). Because 573 NSAID users (14.5%) reported taking both a SALA and non-SALA, we examined their use alone and in combination. Resulting aHRs were 0.82 (CI 0.67-0.99) for SALA only, 0.60 (CI 0.40-0.90) for non-SALA only, and 0.87 (CI 0.57-1.33) for both NSAIDs (Wald test for differences, p = 0.32). The 40.7% of participants who used aspirin also showed reduced risk of AD, even when they used no other NSAIDs (aHR 0.78, CI 0.66-0.92). By contrast, there was no association with use of acetaminophen (aHR 0.93, CI 0.76-1.13). CONCLUSIONS: In this pooled dataset, nonsteroidal anti-inflammatory drug (NSAID) use reduced the risk of Alzheimer dementia (AD). However, there was no apparent advantage in AD risk reduction for the subset of NSAIDs shown to selectively lower A beta(42), suggesting that all conventional NSAIDs including aspirin have a similar protective effect in humans.
Keywords: Acetaminophen; Adolescent; Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analgesics, Non-Narcotic; Anti-Inflammatory Agents, Non-Steroidal; Aspirin; Cohort Studies; Female; Humans; Male; Middle Aged; Neuroprotective Agents; Peptide Fragments; Proportional Hazards Models; Prospective Studies; Risk Factors

Novel measures of heart rate variability predict cardiovascular mortality in older adults independent of traditional cardiovascular risk factors: the Cardiovascular Health Study (CHS). - Stein, Phyllis K; Barzilay, Joshua I; Chaves, Paulo H M; Mistretta, Stephanie Q; Domitrovich, Peter P; Gottdiener, John S; Rich, Michael W; Kleiger, Robert E (J Cardiovasc Electrophysiol, 2008)
UNLABELLED: Novel HRV Predicts CV Mortality in the Elderly. BACKGROUND: It is unknown whether abnormal heart rate turbulence (HRT) and abnormal fractal properties of heart rate variability identify older adults at increased risk of cardiovascular death (CVdth). METHODS: Data from 1,172 community-dwelling adults, ages 72 +/- 5 (65-93) years, who participated in the Cardiovascular Health Study (CHS), a study of risk factors for CV disease in people >or=65 years. HRT and the short-term fractal scaling exponent (DFA1) derived from 24-hour Holter recordings. HRT categorized as: normal (turbulence slope [TS] and turbulence onset [TO] normal) or abnormal (TS and/or TO abnormal). DFA1 categorized as low (<or=1) or high (>1). Cox regression analyses stratified by Framingham Risk Score (FRS) strata (low = <10, mid = 10-20, and high >20) and adjusted for prevalent clinical cardiovascular disease (CVD), diabetes, and quartiles of ventricular premature beat counts (VPCs). RESULTS: CVdths (N = 172) occurred over a median follow-up of 12.3 years. Within each FRS stratum, low DFA1 + abnormal HRT predicted risk of CVdth (RR = 7.7 for low FRS; 3.6, mid FRS; 2.8, high FRS). Among high FRS stratum participants, low DFA1 alone also predicted CVdth (RR = 2.0). VPCs in the highest quartile predicted CVdth, but only in the high FRS group. Clinical CV disease predicted CVdth at each FRS stratum (RR = 2.9, low; 2.6, mid; and 1.9, high). Diabetes predicted CVdth in the highest FRS group only (RR = 2.2). CONCLUSIONS: The combination of low DFA1 + abnormal HRT is a strong risk factor for CVdth among older adults even after adjustment for conventional CVD risk measures and the presence of CVD.
Keywords: Aged; Aged, 80 and over; Arrhythmias, Cardiac; Death, Sudden, Cardiac; Electrocardiography, Ambulatory; Female; Heart Rate; Humans; Male; Maryland; Reproducibility of Results; Risk Assessment; Risk Factors; Sensitivity and Specificity; Survival Analysis; Survival Rate

NSAID use and dementia risk in the Cardiovascular Health Study: role of APOE and NSAID type. - Szekely, C A; Breitner, J C S; Fitzpatrick, A L; Rea, T D; Psaty, B M; Kuller, L H; Zandi, P P (Neurology, 2008)
BACKGROUND: Epidemiologic and laboratory studies suggest that nonsteroidal antiinflammatory drugs (NSAIDs) reduce risk of Alzheimer disease (AD). We therefore investigated the association between use of NSAIDs, aspirin, and the non-NSAID analgesic acetaminophen with incidence of dementia and AD. METHODS: Participants in the Cardiovascular Health Cognition Study included 3,229 individuals aged 65 or older, free of dementia at baseline, with information on medication use. We used Cox proportional hazards regression to estimate the association of medication use with incident all-cause dementia, AD, and vascular dementia (VaD). Additional analyses considered the NSAID-AD relationship as a function of age, presence of at least one epsilon 4 allele at APOE, race, and individual NSAIDs' reported ability to reduce production of the amyloid-beta peptide variant A beta(42). RESULTS: Use of NSAIDs was associated with a lower risk of dementia (adjusted hazard ratio or aHR 0.76, 95% CI or CI 0.60-0.96) and, in particular, AD (aHR 0.63, CI 0.45-0.88), but not VaD (aHR 0.92, CI 0.65-1.28). No similar trends were observed with acetaminophen (aHR 0.99, CI 0.79-1.24). Closer examination suggested AD risk reduction with NSAIDs only in participants having an APOE epsilon 4 allele (aHR 0.34, CI 0.18-0.65; aHR for others 0.88, CI 0.59-1.32). There was no advantage in AD risk reduction with NSAIDs reported to selectively reduce A beta(42). CONCLUSIONS: Results were consistent with previous cohort studies showing reduced risk of AD in NSAID users, but this association was found only in those with an APOE epsilon 4 allele, and there was no advantage for A beta(42)-lowering NSAIDs.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anti-Inflammatory Agents, Non-Steroidal; Apolipoproteins E; Cardiovascular System; Dementia; Female; Humans; Incidence; Male; Proportional Hazards Models; Prospective Studies; Risk Factors

Plasma amyloid levels and the risk of AD in normal subjects in the Cardiovascular Health Study. - Lopez, O L; Kuller, L H; Mehta, P D; Becker, J T; Gach, H M; Sweet, R A; Chang, Y F; Tracy, R; DeKosky, S T (Neurology, 2008)
OBJECTIVES: To examine the association between incident Alzheimer disease (AD), and plasma A beta 1-40 and A beta 1-42 levels in normal and mild cognitive impairment (MCI) subjects in a subgroup of participants of the Cardiovascular Health Study Cognition Study. METHODS: We determined the plasma A beta 1-40 and A beta 1-42 levels of 274 nondemented subjects (232 normals and 42 with MCI) in 1998-1999 and repeated the measurements in 2002-2003. The mean age of the subjects at baseline was 79.3 +/- 3.6 years. We examined the association between A beta levels and incident AD over the ensuing 4.5 years, controlling for age, cystatin C level (marker of glomerular function), apolipoprotein E-4 allele, Modified-Mini-Mental State Examination scores, and MRI-identified infarcts. RESULTS: In an unadjusted prospective model in normal subjects, both A beta 1-40 and A beta 1-42 levels in 1998-1999 were associated with incident AD (n = 55) in 2002-2003 (longitudinal analysis). In the fully adjusted multivariate model, neither A beta 1-42 nor A beta 1-40 nor their ratio was associated with incident AD. However, adjustment had a very small effect on point estimates for A beta 1-42, from an odds ratio (OR) of 1.61 (p = 0.007) in the unadjusted model to an OR of 1.46 (p = 0.08) in the fully adjusted model. In 2002-2003 (cross-sectional analysis), only the unadjusted models showed that both peptides were associated with AD. CONCLUSIONS: Plasma A beta levels are affected by age and by systemic and CNS vascular risk factors. After controlling for these conditions, A beta-40 and A beta 1-42 are weak predictors of conversion to Alzheimer disease (AD) in normal subjects and are only weakly associated with AD in cross-sectional analysis. Consequently, plasma levels of A beta do not seem to be useful biomarkers for AD.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Biomarkers; Brain; Cerebrovascular Disorders; Comorbidity; Cross-Sectional Studies; Cystatin C; Cystatins; Female; Humans; Incidence; Longitudinal Studies; Magnetic Resonance Imaging; Male; Models, Statistical; Neuropsychological Tests; Peptide Fragments; Predictive Value of Tests; Prospective Studies; Reference Values; Risk Factors

Relation of sleep-disordered breathing to carotid plaque and intima-media thickness. - Wattanakit, Keattiyoat; Boland, Lori; Punjabi, Naresh M; Shahar, Eyal (Atherosclerosis, 2008)
BACKGROUND: Sleep-disordered breathing (SDB) is associated with clinical cardiovascular disease (CVD), but its relation to subclinical atherosclerosis remains to be determined. METHODS: We analyzed the cross-sectional associations of SDB, measured by the respiratory disturbance index (RDI), a hypoxemia index, and an arousal index, with carotid plaque and carotid intima-media thickness (IMT), measured by ultrasound. The sample included 985 participants in the Sleep Heart Health Study (mean age-62, median RDI-8.7) with no history of coronary heart disease and stroke, of whom 396 had evidence of a carotid plaque. RESULTS: As compared with the first quartile of the RDI (0-1.2), the crude odds ratio for carotid plaque was 1.14, 1.27, and 1.48 for the second (1.3-4.1), third (4.2-10.7), and fourth (>10.7) quartile, respectively. After adjustment for CVD risk factors, the corresponding odds ratios were reduced (1.00, 1.04, 1.07, and 1.25). Similarly, the unadjusted mean carotid IMT increased with RDI, but adjusted means (mm) were similar (0.84, 0.85, 0.84, 0.85). Spline regression models did not show monotonicity of the dose-response functions at the right end of the RDI distribution. Neither the hypoxemia index nor the arousal index was associated with carotid plaque or carotid IMT. CONCLUSION: The results of this study suggest that crude, positive associations between SDB and subclinical atherosclerosis can be attributed to confounding by CVD risk factors.
Keywords: Aged; Carotid Arteries; Carotid Artery Diseases; Female; Humans; Male; Middle Aged; Odds Ratio; Risk Factors; Sleep Apnea Syndromes; Tunica Intima; Tunica Media; Ultrasonography

The relationship between exercise and risk of venous thrombosis in elderly people. - van Stralen, Karlijn J; Doggen, Carine J M; Lumley, Thomas; Cushman, Mary; Folsom, Aaron R; Psaty, Bruce M; Siscovick, David; Rosendaal, Frits R; Heckbert, Susan R (J Am Geriatr Soc, 2008)
OBJECTIVES: To study whether exercise is associated with the risk of venous thrombosis in elderly people. DESIGN: Observational study with a median follow-up of 11.6 years. SETTING: The Cardiovascular Health Study in four U.S. communities. PARTICIPANTS: People aged 65 and older without prior venous thrombosis (deep venous thrombosis or pulmonary embolism). MEASUREMENTS: Self-reported exercise was measured two or three times during follow-up and was defined as expending more than 500 kcal/wk on exercise, including walking for exercise. Venous thrombosis cases were verified using medical record review. RESULTS: Of 5,534 participants, 171 developed a first venous thrombosis. Self-reported exercise at baseline was not related to the risk of venous thrombosis after adjustment for sex, age, race, self-reported health, and body mass index (adjusted hazard ratio (HR(adj))=1.16, 95% confidence interval (CI)=0.84-1.61), although with exercise modeled as a time-varying exposure, overall results were in the direction of greater risk of venous thrombosis (HR(adj)=1.38, 95% CI=0.99-1.91). For mild-intensity exercise, such as walking, there was a nonsignificant finding in the direction of benefit (HR(adj)=0.75, 95% CI=0.49-1.16), but strenuous exercise, such as jogging, was associated with greater risk of venous thrombosis (HR(adj)=1.75, 95% CI=1.08-2.83) than no exercise at all. CONCLUSION: In elderly people, strenuous exercise was associated with a higher risk of venous thrombosis than no exercise at all. Future studies are needed to explain this unexpected higher risk.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cohort Studies; Energy Metabolism; Exercise; Female; Humans; Male; Prevalence; Risk Factors; United States; Venous Thrombosis

Stance time and step width variability have unique contributing impairments in older persons. - Brach, Jennifer S; Studenski, Stephanie; Perera, Subashan; VanSwearingen, Jessie M; Newman, Anne B (Gait Posture, 2008)
Gait variability may have multiple causes. We hypothesized that central nervous system (CNS) impairments would affect motor control and be manifested as increased stance time and step length variability, while sensory impairments would affect balance and be manifested as increased step width variability. Older adults (mean+/-standard deviation (S.D.) age=79.4+/-4.1, n=558) from the Pittsburgh site of the Cardiovascular Health Study participated. The S.D. across steps was the indicator of gait variability, determined for three gait measures, step length, stance time and step width, using a computerized walkway. Impairment measures included CNS function (modified mini-mental state examination, Trails A and B, Digit Symbol Substitution, finger tapping), sensory function (lower extremity (LE) vibration, vision), strength (grip strength, repeated chair stands), mood, and LE pain. Linear regression models were fit for the three gait variability characteristics using impairment measures as independent variables, adjusted for age, race, gender, and height. Analyses were repeated stratified by gait speed. All measures of CNS impairment were directly related to stance time variability (p<0.01), with increased CNS impairment associated with increased stance time variability. CNS impairments were not related to step length or width variability. Both sensory impairments were inversely related to step width (p<0.01) but not step length or stance time variability. CNS impairments affected stance time variability especially in slow walkers while sensory impairments affected step width variability in fast walkers. Specific patterns of gait variability may imply different underlying causes. Types of gait variability should be specified. Interventions may be targeted at specific types of gait variability.
Keywords: Aged; Aged, 80 and over; Biomechanical Phenomena; Female; Gait Disorders, Neurologic; Humans; Linear Models; Longitudinal Studies; Male; Neuropsychological Tests; Postural Balance; Range of Motion, Articular; Risk Factors; Signal Processing, Computer-Assisted

Subclinical thyroid dysfunction, cardiac function, and the risk of heart failure. The Cardiovascular Health study. - Rodondi, Nicolas; Bauer, Douglas C; Cappola, Anne R; Cornuz, Jacques; Robbins, John; Fried, Linda P; Ladenson, Paul W; Vittinghoff, Eric; Gottdiener, John S; Newman, Anne B (J Am Coll Cardiol, 2008)
OBJECTIVES: The goal of this study was to determine whether subclinical thyroid dysfunction was associated with incident heart failure (HF) and echocardiogram abnormalities. BACKGROUND: Subclinical hypothyroidism and hyperthyroidism have been associated with cardiac dysfunction. However, long-term data on the risk of HF are limited. METHODS: We studied 3,044 adults>or=65 years of age who initially were free of HF in the Cardiovascular Health Study. We compared adjudicated HF events over a mean 12-year follow-up and changes in cardiac function over the course of 5 years among euthyroid participants, those with subclinical hypothyroidism (subdivided by thyroid-stimulating hormone [TSH] levels: 4.5 to 9.9, >or=10.0 mU/l), and those with subclinical hyperthyroidism. RESULTS: Over the course of 12 years, 736 participants developed HF events. Participants with TSH>or=10.0 mU/l had a greater incidence of HF compared with euthyroid participants (41.7 vs. 22.9 per 1,000 person years, p=0.01; adjusted hazard ratio: 1.88; 95% confidence interval: 1.05 to 3.34). Baseline peak E velocity, which is an echocardiographic measurement of diastolic function associated with incident HF in the CHS cohort, was greater in those patients with TSH>or=10.0 mU/l compared with euthyroid participants (0.80 m/s vs. 0.72 m/s, p=0.002). Over the course of 5 years, left ventricular mass increased among those with TSH>or=10.0 mU/l, but other echocardiographic measurements were unchanged. Those patients with TSH 4.5 to 9.9 mU/l or with subclinical hyperthyroidism had no increase in risk of HF. CONCLUSIONS: Compared with euthyroid older adults, those adults with TSH>or=10.0 mU/l have a moderately increased risk of HF and alterations in cardiac function but not older adults with TSH<10.0 mU/l. Clinical trials should assess whether the risk of HF might be ameliorated by thyroxine replacement in individuals with TSH>or=10.0 mU/l.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Echocardiography; Female; Heart; Heart Failure; Heart Function Tests; Humans; Hyperthyroidism; Hypertrophy, Left Ventricular; Hypothyroidism; Male; Risk Factors; Time Factors

Subjective and objective sleep quality in patients on conventional thrice-weekly hemodialysis: comparison with matched controls from the sleep heart health study. - Unruh, Mark L; Sanders, Mark H; Redline, Susan; Piraino, Beth M; Umans, Jason G; Chami, Hassan; Budhiraja, Rohit; Punjabi, Naresh M; Buysse, Daniel; Newman, Anne B (Am J Kidney Dis, 2008)
BACKGROUND: Studies examining sleep in the hemodialysis (HD) population have largely lacked an adequate comparison group. It therefore is uncertain whether poor sleep quality in the HD population reflects age, chronic health conditions, or effects of conventional HD therapy. STUDY DESIGN: Cross-sectional matched-group study. SETTING & PARTICIPANTS: Forty-six in-center HD patients were compared with 137 community participants participating in the Sleep Heart Health Study matched for age, sex, body mass index, and race. PREDICTOR: HD patients compared with community-dwelling non-HD participants. OUTCOMES & MEASUREMENTS: Home unattended polysomnography was performed and scored by using similar protocols. Sleep habits and sleepiness were assessed by using the Sleep Habits Questionnaire and Epworth Sleepiness Scale. RESULTS: Average age of study samples was 63 years, 72% were white, and average body mass index was 28 +/- 5 kg/m(2). HD patients were significantly more likely than community participants to have short sleep (odds ratio, 3.27; 95% confidence interval, 1.16 to 9.25) and decreased sleep efficiency (odds ratio, 5.5; 95% confidence interval, 1.5 to 19.6). HD patients reported more difficulty getting back to sleep (odds ratio, 2.25; 95% confidence interval, 1.11 to 4.60) and waking up too early (odds ratio, 2.39; 95% confidence interval, 1.01 to 5.66). There was no association between polysomnography sleep time and self-reported sleep time (r = 0.09; P = 0.6) or between the Epworth Sleepiness Scale and severity of sleep apnea (r = 0.10; P = 0.5) in the HD population. LIMITATIONS: The study was limited to participants older than 45 years. CONCLUSIONS: Kidney failure treated with thrice-weekly HD is significantly associated with poor subjective and objective sleep quality.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cross-Sectional Studies; Disease Progression; Female; Follow-Up Studies; Heart Rate; Humans; Incidence; Kidney Failure, Chronic; Male; Middle Aged; Odds Ratio; Pennsylvania; Polysomnography; Prognosis; Renal Dialysis; Retrospective Studies; Risk Factors; Severity of Illness Index; Sleep; Sleep Apnea Syndromes; Surveys and Questionnaires

Total insulinlike growth factor 1 and insulinlike growth factor binding protein levels, functional status, and mortality in older adults. - Kaplan, Robert C; McGinn, Aileen P; Pollak, Michael N; Kuller, Lewis; Strickler, Howard D; Rohan, Thomas E; Xue, XiaoNan; Kritchevsky, Stephen B; Newman, Anne B; Psaty, Bruce M (J Am Geriatr Soc, 2008)
OBJECTIVES: To assess the association between total insulinlike growth factor (IGF)-1, IGF binding protein-1 (IGFBP-1), and IGFBP-3 levels and functioning and mortality in older adults. DESIGN: Cohort study. SETTING/PARTICIPANTS: One thousand one hundred twenty-two individuals aged 65 and older without prior cardiovascular disease events participating in the Cardiovascular Health Study. MEASUREMENTS: Baseline fasting plasma levels of IGF-1, IGFBP-1, and IGFBP-3 (defined as tertiles, T1-T3) were examined in relationship to handgrip strength, time to walk 15 feet, development of new difficulties with activities of daily living (ADLs), and mortality. RESULTS: Higher IGFBP-1 predicted worse handgrip strength (P-trend(T1-T3)<.01) and slower walking speed (P-trend(T1-T3)=.03), lower IGF-1 had a borderline significant association with worse handgrip strength (P-trend(T1-T3)=.06), and better grip strength was observed in the middle IGFBP-3 tertile than in the low or high tertiles (P=.03). Adjusted for age, sex, and race, high IGFBP-1 predicted greater mortality (P-trend(T1-T3)<.001, hazard ratio (HR)(T3vsT1)=1.48, 95% confidence interval (CI)=1.15-1.90); this association was borderline significant after additional confounder adjustment (P-trend(T1-T3)=.05, HR(T3vsT1)=1.35, 95% CI=0.98-1.87). High IGFBP-1 was associated with greater risk of incident ADL difficulties after adjustment for age, sex, race, and other confounders (P-trend(T1-T3)=.04, HR(T3vsT1)=1.40, CI=1.01-1.94). Neither IGF-1 nor IGFBP-3 level predicted mortality or incident ADL difficulties. CONCLUSION: In adults aged 65 and older, high IGFBP-1 levels were associated with greater risk of mortality and poorer functional ability, whereas IGF-1 and IGFBP-3 had little association with these outcomes.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Enzyme-Linked Immunosorbent Assay; Fasting; Female; Follow-Up Studies; Hand Strength; Humans; Incidence; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Middle Aged; Prognosis; Prospective Studies; Risk Factors; Survival Rate; United States; Walking

Weight, mortality, years of healthy life, and active life expectancy in older adults. - Diehr, Paula; O'Meara, Ellen S; Fitzpatrick, Annette; Newman, Anne B; Kuller, Lewis; Burke, Gregory (J Am Geriatr Soc, 2008)
OBJECTIVES: To determine whether weight categories predict subsequent mortality and morbidity in older adults. DESIGN: Multistate life tables, using data from the Cardiovascular Health Study, a longitudinal population-based cohort of older adults. SETTING: Data were provided by community-dwelling seniors in four U.S. counties: Forsyth County, North Carolina; Sacramento County, California; Washington County, Maryland; and Allegheny County, Pennsylvania. PARTICIPANTS: Five thousand eight hundred eighty-eight adults aged 65 and older at baseline. MEASUREMENTS: The age- and sex-specific probabilities of transition from one health state to another and from one weight category to another were estimated. From these probabilities, future life expectancy, years of healthy life, active life expectancy, and the number of years spent in each weight and health category after age 65 were estimated. RESULTS: Women who are healthy and of normal weight at age 65 have a life expectancy of 22.1 years. Of that, they spend, on average, 9.6 years as overweight or obese and 5.3 years in fair or poor health. For both men and women, being underweight at age 65 was associated with worse outcomes than being normal weight, whereas being overweight or obese was rarely associated with worse outcomes than being normal weight and was sometimes associated with significantly better outcomes. CONCLUSION: Similar to middle-aged populations, older adults are likely to be or to become overweight or obese, but higher weight is not associated with worse health in this age group. Thus, the number of older adults at a "healthy" weight may be much higher than currently believed.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Body Mass Index; Body Weight; Female; Health Status Indicators; Humans; Life Expectancy; Life Style; Male; Prognosis; Risk Factors; Sex Factors; Survival Rate; United States

Age-related macular degeneration and risk of coronary heart disease and stroke: the Cardiovascular Health Study. - Sun, Cong; Klein, Ronald; Wong, Tien Y (Ophthalmology, 2009)
PURPOSE: To examine the associations of age-related macular degeneration (AMD) with incident coronary heart disease (CHD) and stroke in the Cardiovascular Health Study. DESIGN: Population-based prospective cohort study. PARTICIPANTS: A total of 1786 white and African-American participants free of CHD or 2228 participants free of stroke, aged 69 to 97 years. METHODS: AMD was evaluated from photographs taken in 1997 and 1998. MAIN OUTCOME MEASURES: Incident CHD and stroke ascertained using standardized methods. RESULTS: Of the 1786 persons free of CHD, 303 developed incident CHD over 7 years. Participants with early AMD (n = 277) had a higher cumulative incidence of CHD than participants without early AMD (25.8% vs. 18.9%, P = 0.001). By adjusting for age, gender, race, systolic and diastolic blood pressure, hypertension status, fasting glucose, triglyceride, low-density lipoprotein cholesterol, cigarette smoking, pack years of smoking, and C-reactive protein, the presence of early AMD was associated with an increased risk of incident CHD (hazard ratio 1.57; 95% confidence interval, 1.17-2.22). Late AMD (n = 25) was not associated with incident CHD (hazard ratio 0.78; 95% confidence interval, 0.25-2.48). Among 2228 persons at risk, 198 developed incident stroke; neither early nor late AMD was associated with incident stroke. CONCLUSIONS: This study suggests persons with early AMD have a higher risk of CHD but not stroke in a population aged 69 to 97 years. This provides further support that AMD is associated with underlying systemic vascular disease.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Blood Pressure; Cholesterol, LDL; Coronary Disease; European Continental Ancestry Group; Female; Humans; Incidence; Macular Degeneration; Male; Prospective Studies; Risk Factors; Sex Factors; Stroke; Triglycerides; United States

Angiotensin-converting enzyme inhibitors and cognitive decline in older adults with hypertension: results from the Cardiovascular Health Study. - Sink, Kaycee M; Leng, Xiaoyan; Williamson, Jeff; Kritchevsky, Stephen B; Yaffe, Kristine; Kuller, Lewis; Yasar, Sevil; Atkinson, Hal; Robbins, Mike; Psaty, Bruce; Goff, David C (Arch Intern Med, 2009)
BACKGROUND: Hypertension (HTN) is a risk factor for dementia, and animal studies suggest that centrally active angiotensin-converting enzyme (ACE) inhibitors (those that cross the blood-brain barrier) may protect against dementia beyond HTN control. METHODS: Participants in the Cardiovascular Health Study Cognition Substudy with treated HTN and no diagnosis of congestive heart failure (n = 1054; mean age, 75 years) were followed up for a median of 6 years to determine whether cumulative exposure to ACE inhibitors (as a class and by central activity), compared with other anti-HTN agents, was associated with a lower risk of incident dementia, cognitive decline (by Modified Mini-Mental State Examination [3MSE]), or incident disability in instrumental activities of daily living (IADLs). RESULTS: Among 414 participants who were exposed to ACE inhibitors and 640 who were not, there were 158 cases of incident dementia. Compared with other anti-HTN drugs, there was no association between exposure to all ACE inhibitors and risk of dementia (hazard ratio [HR], 1.01; 95% confidence interval [CI], 0.88-1.15), difference in 3MSE scores (-0.32 points per year; P = .15), or odds of disability in IADLs (odds ratio [OR], 1.06; 95% CI, 0.99-1.14). Adjusted results were similar. However, centrally active ACE inhibitors were associated with 65% less decline in 3MSE scores per year of exposure (P = .01), and noncentrally active ACE inhibitors were associated with a greater risk of incident dementia (adjusted HR, 1.20; 95% CI, 1.00-1.43 per year of exposure) and greater odds of disability in IADLs (adjusted OR, 1.16; 95% CI, 1.03-1.30 per year of exposure) compared with other anti-HTN drugs. CONCLUSIONS: While ACE inhibitors as a class do not appear to be independently associated with dementia risk or cognitive decline in older hypertensive adults, there may be within-class differences in regard to these outcomes. These results should be confirmed with a randomized clinical trial of a centrally active ACE inhibitor in the prevention of cognitive decline and dementia.
Keywords: Aged; Angiotensin-Converting Enzyme Inhibitors; Blood-Brain Barrier; Cognition; Dementia; Female; Follow-Up Studies; Humans; Hypertension; Incidence; Male; Prospective Studies; Risk Factors

Association of chronic kidney disease with the spectrum of ankle brachial index the CHS (Cardiovascular Health Study). - Ix, Joachim H; Katz, Ronit; de Boer, Ian H; Kestenbaum, Brian R; Allison, Matthew A; Siscovick, David S; Newman, Anne B; Sarnak, Mark J; Shlipak, Michael G; Criqui, Michael H (J Am Coll Cardiol, 2009)
OBJECTIVES: This study sought to determine the association of chronic kidney disease (CKD) with high ankle brachial index (ABI) measurement and to compare its strength with that of CKD with a low ABI. BACKGROUND: CKD is an important risk factor for cardiovascular disease (CVD) events. A high ABI, a marker of lower extremity arterial stiffness, is associated with CVD events and mortality. The association between CKD and high ABI is unknown. METHODS: The CHS (Cardiovascular Health Study) enrolled community-living people >65 years of age and measured kidney function and ABI. Glomerular filtration rate (GFR) was estimated using equations that incorporated either cystatin C or creatinine, and CKD was defined by estimated GFR <60 ml/min/1.73 m(2). The ABI was categorized as low (<0.90), low-normal (0.90 to 1.09), normal (1.10 to 1.40), and high (>1.40 or incompressible). Multinomial logistic regression was used to evaluate the associations of CKD with ABI categories. RESULTS: Among 4,513 participants, 23% had CKD, 13% had a low ABI, and 3% had a high ABI. In models adjusted for age, sex, race, hypertension, diabetes, smoking, body mass index, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and C-reactive protein, cystatin C-based CKD was associated with both low ABI (relative risk [RR]: 2.0; 95% confidence interval [CI]: 1.6 to 2.5; p <0.001) and high ABI (RR: 1.6; 95% CI: 1.0 to 2.3; p = 0.03). Results were similar when CKD was defined by creatinine. CONCLUSIONS: CKD is associated with both the high and the low extremes of ABI in community-living older people. Future studies should evaluate whether arterial stiffness is an important mechanism leading to CVD in people with CKD.
Keywords: Aged; Aged, 80 and over; Ankle Brachial Index; C-Reactive Protein; Cardiovascular Diseases; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Female; Glomerular Filtration Rate; Humans; Kidney Diseases; Lipids; Male; Risk Factors

Association of renal function with cardiac calcifications in older adults: the cardiovascular health study. - Asselbergs, Folkert W; Mozaffarian, Dariush; Katz, Ronit; Kestenbaum, Bryan; Fried, Linda F; Gottdiener, John S; Shlipak, Michael G; Siscovick, David S (Nephrol Dial Transplant, 2009)
BACKGROUND: Aortic valve sclerosis (AVS) and mitral annulus calcification (MAC) are highly prevalent in patients with end-stage renal disease. It is less well established whether milder kidney disease is associated with cardiac calcifications. We evaluated the relationships between renal function and MAC, aortic annular calcification (AAC) and AVS in the elderly. METHODS: From the Cardiovascular Health Study, a community-based cohort of ambulatory adults >or= age 65, a total of 3929 individuals (mean +/- SD age 74 +/- 5 years, 60% women) were evaluated with two-dimensional echocardiography. Renal function was assessed by means of creatinine-based estimated glomerular filtration rate (eGFR) and cystatin C. RESULTS: The prevalences of MAC and AAC were significantly higher in individuals with an eGFR < 45 mL/ min/1.73 m(2) (P < 0.01 for each), and cystatin C levels were significantly higher in individuals with MAC or AAC compared to individuals without these cardiac calcifications (P < 0.001 for each). After multivariate-adjustment, an eGFR <45 mL/min/1.73 m(2) was significantly associated with MAC [odds ratio 1.54 (95% CI 1.16-2.06), P = 0.003] and not associated with AAC [1.30 (0.97-1.74), P = 0.085] and AVS [1.15 (0.86-1.53), P = 0.355]. In addition, cystatin C levels were independently associated with MAC [odds ratio per SD 1.12 (1.05-1.21), P = 0.001] and not associated with AAC [1.07 (1.00-1.15), P = 0.054] and AVS [0.99 (0.93-1.06), P = 0.82]. Furthermore, the prevalence of multiple cardiac calcifications was higher in subjects with an eGFR < 45 mL/ min/1.73 m(2) and increased per quartile of cystatin C (P-values < 0.001). In addition, a significant trend was observed between an eGFR < 45 mL/min/1.73 m(2), increasing levels of cystatin C and the number of cardiac calcifications (P < 0.05). CONCLUSIONS: In a community-based cohort of the elderly, moderate kidney disease as defined by an eGFR <45 mL/min/1.73m(2) and elevated levels of cystatin C was associated with prevalent MAC. In addition, a significant trend was observed between an eGFR <45 mL/min/1.73m(2), increasing levels of cystatin C and the number of cardiac calcifications. No associations were found between renal function and AAC or AVS.
Keywords: Aged; Aortic Valve; Calcinosis; Case-Control Studies; Cohort Studies; Creatinine; Cystatin C; Female; Glomerular Filtration Rate; Heart Valve Diseases; Humans; Kidney Diseases; Male; Mitral Valve; Risk Factors

Associations of pentraxin 3 with cardiovascular disease and all-cause death: the Cardiovascular Health Study. - Jenny, Nancy Swords; Arnold, Alice M; Kuller, Lewis H; Tracy, Russell P; Psaty, Bruce M (Arterioscler Thromb Vasc Biol, 2009)
OBJECTIVE: We examined associations of pentraxin 3 (PTX3), a vascular inflammation marker, with incident cardiovascular disease (CVD) and all-cause death. METHODS AND RESULTS: 1583 Cardiovascular Health Study participants free of prevalent CVD were included. Nonexclusive case groups were angina (n=476), myocardial infarction (MI; n=237), stroke (n=310), CVD death (n=282), and all-cause death (n=772). 535 participants had no events. PTX3 levels were higher in those with subclinical CVD (1.90+/-1.89 ng/mL) than those without (1.71+/-1.88 ng/mL; P=0.001). Using Cox regression adjusted for age, sex, and ethnicity, a standard deviation increase in PTX3 (1.89 ng/mL) was associated with CVD death (hazard ratio 1.11; 95% confidence interval 1.02 to 1.21) and all-cause death (1.08; 1.02 to 1.15). PTX3 was not associated with angina (1.09; 0.98 to 1.20), MI (0.96; 0.81 to 1.12), or stroke (1.06; 0.95 to 1.18). Adding C-reactive protein (CRP) or CVD risk factors to the models had no significant effects on associations. CONCLUSIONS: In these older adults, PTX3 was associated with CVD and all-cause death independent of CRP and CVD risk factors. PTX3 likely reflects different aspects of inflammation than CRP and may provide insight into vascular health in aging and chronic diseases of aging that lead to death.
Keywords: Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Case-Control Studies; Female; Health Surveys; Humans; Inflammation Mediators; Linear Models; Male; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Serum Amyloid P-Component; Time Factors; United States; Up-Regulation

Change in cardiovascular risk factors with progression of kidney disease. - Fried, Linda F; Katz, Ronit; Cushman, Mary; Sarnak, Mark; Shlipak, Michael G; Kuller, Lewis; Newman, Anne B (Am J Nephrol, 2009)
BACKGROUND: Prior studies evaluating the relationship of kidney disease with cardiovascular risk factors have been limited by their cross-sectional design. We evaluated the change in lipids, inflammatory and procoagulant biomarkers with decline in kidney function in a nested case-cohort study in the Cardiovascular Health Study, a community-based study of adults aged >65 years. METHODS: Individuals with an increase in serum creatinine >or=0.3 mg/dl (baseline to 3 years later, n = 207) were matched to controls of similar age, race, gender, diabetes and baseline serum creatinine, but whose change in creatinine was <0.3 mg/dl. Baseline and change in risk factors were analyzed with conditional logistic regression. RESULTS: Changes in C-reactive protein were similar. In contrast, cases had larger increases in fibrinogen (OR 1.38 per standard deviation, 95% confidence interval 1.08-1.76) and factor VIII [1.38 (1.10-1.72)] and larger decreases in HDL [OR 0.80 (0.64, 1.00)]. Change in interleukin-6 was greater in cases than controls, but this did not persist after multivariate adjustment. However, in linear regression, change in interleukin-6 was correlated with change in creatinine. CONCLUSION: Cardiovascular risk factors and kidney function may change concurrently. This could lead to an increased risk of cardiovascular disease as kidney function worsens.
Keywords: Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; Cholesterol, HDL; Creatinine; Diabetes Mellitus; Factor VIII; Female; Follow-Up Studies; Humans; Hypertension, Renal; Interleukin-6; Logistic Models; Male; Prevalence; Renal Insufficiency, Chronic; Risk Factors; Vasculitis

Clinical and subclinical cardiovascular disease and kidney function decline in the elderly. - Shlipak, Michael G; Katz, Ronit; Kestenbaum, Bryan; Fried, Linda F; Siscovick, David; Sarnak, Mark J (Atherosclerosis, 2009)
OBJECTIVE: Kidney function decline in elderly persons may be the result of microvascular atherosclerosis. As a proxy for the renovascular system, we evaluated the association of clinical and subclinical cardiovascular disease (CVD) with kidney function decline. METHODS: This study included 4380 subjects from the Cardiovascular Health Study, a longitudinal, community-based cohort of persons aged >or=65 from 4 U.S. communities. Creatinine and cystatin C were measured at baseline, year 3, and year 7; eligible subjects had at least two measures. Creatinine-based estimated glomerular filtration rate (eGFR(creat)) was calculated using the MDRD equation. Rapid kidney function decline was defined as an annual eGFR loss >3 mL/min/1.73 m(2). Predictors of rapid kidney decline included prevalent and subclinical measures of CVD. RESULTS: Mean decline in eGFR(creat) was 0.4+/-2.6/year; 714 (16%) had rapid progression. In multivariate models adjusted for demographics, cardiovascular risk factors, and inflammation, prevalent stroke (OR, 95% CI: 1.55, 1.16-2.08) and heart failure (OR, 95% CI: 1.80, 1.40-2.31) were independent predictors of rapid kidney decline. Among persons without clinical CV, the subclinical disease measures ankle-arm index <0.9 (OR, 95% CI: 1.67, 1.25-2.24), common carotid intima-media thickness (>or=1.14 mm) (OR, 95% CI: 1.52, 1.12-2.06) and internal carotid intima-media thickness (>1.82 mm) (OR, 95% CI: 1.50, 1.12-2.02) had independent associations with rapid kidney function decline. Results were similar using cystatin C. CONCLUSION: Clinical atherosclerosis and heart failure and subclinical measures of CVD have independent associations with kidney function decline progression in the elderly, suggesting an underlying role of renal atherosclerosis.
Keywords: Age Factors; Aged; Atherosclerosis; Cardiovascular Diseases; Creatinine; Cystatin C; Female; Glomerular Filtration Rate; Heart Failure; Humans; Kidney; Kidney Diseases; Linear Models; Longitudinal Studies; Male; Odds Ratio; Risk Assessment; Risk Factors; Time Factors; United States

Coagulation factors IX through XIII and the risk of future venous thrombosis: the Longitudinal Investigation of Thromboembolism Etiology. - Cushman, Mary; O'Meara, Ellen S; Folsom, Aaron R; Heckbert, Susan R (Blood, 2009)
Higher levels of procoagulant factors and factor XII deficiency may be risk factors for first venous thromboembolism (VTE). We studied associations of coagulation factors IX through XIII with risk of future VTE in 2 general population samples. Using a nested case-control study combining the 21 860 participants of the Atherosclerosis Risk in Communities study and the Cardiovascular Health Study, we determined antigenic levels of these coagulation factors in primarily pre-event blood samples from 462 participants who subsequently developed VTE and 1047 participants who remained free of VTE. Only elevated levels of factors IX and XI were associated with increased risk of VTE after adjustment for age, sex, race, and study. For factor IX, the odds ratio (OR) was 1.4 (95% confidence interval [CI], 1.0-2.0) comparing the top to bottom quintile. The OR for factor XI was higher: 2.0 (95% CI, 1.4-2.9). With further adjustment for body mass index and diabetes, only elevated factor XI remained associated with VTE risk: OR 1.8 (95% CI, 1.3-2.7). Associations were similar by study and whether the thrombosis was idiopathic or secondary. Factor XII deficiency was not related to VTE risk. Among these procoagulant factors, only elevated factor XI was a risk factor for VTE.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Factor IX; Factor X; Factor XI; Factor XII; Factor XIII; Female; Humans; Longitudinal Studies; Male; Middle Aged; Odds Ratio; Prospective Studies; Risk Factors; Venous Thromboembolism

Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium: Design of prospective meta-analyses of genome-wide association studies from 5 cohorts. - Psaty, Bruce M; O'Donnell, Christopher J; Gudnason, Vilmundur; Lunetta, Kathryn L; Folsom, Aaron R; Rotter, Jerome I; Uitterlinden, André G; Harris, Tamara B; Witteman, Jacqueline C M; Boerwinkle, Eric (Circ Cardiovasc Genet, 2009)
BACKGROUND: The primary aim of genome-wide association studies is to identify novel genetic loci associated with interindividual variation in the levels of risk factors, the degree of subclinical disease, or the risk of clinical disease. The requirement for large sample sizes and the importance of replication have served as powerful incentives for scientific collaboration. Methods- The Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium was formed to facilitate genome-wide association studies meta-analyses and replication opportunities among multiple large population-based cohort studies, which collect data in a standardized fashion and represent the preferred method for estimating disease incidence. The design of the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium includes 5 prospective cohort studies from the United States and Europe: the Age, Gene/Environment Susceptibility-Reykjavik Study, the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. With genome-wide data on a total of about 38 000 individuals, these cohort studies have a large number of health-related phenotypes measured in similar ways. For each harmonized trait, within-cohort genome-wide association study analyses are combined by meta-analysis. A prospective meta-analysis of data from all 5 cohorts, with a properly selected level of genome-wide statistical significance, is a powerful approach to finding genuine phenotypic associations with novel genetic loci. CONCLUSIONS: The Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium and collaborating non-member studies or consortia provide an excellent framework for the identification of the genetic determinants of risk factors, subclinical-disease measures, and clinical events.
Keywords: Adult; Aged; Aging; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Diseases; Humans; Male; Meta-Analysis as Topic; Middle Aged; Phenotype; Research Design; Risk Factors

Common coding variants of the HNF1A gene are associated with multiple cardiovascular risk phenotypes in community-based samples of younger and older European-American adults: the Coronary Artery Risk Development in Young Adults Study and The Cardiovascula - Reiner, Alexander P; Gross, Myron D; Carlson, Christopher S; Bielinski, Suzette J; Lange, Leslie A; Fornage, Myriam; Jenny, Nancy S; Walston, Jeremy; Tracy, Russell P; Williams, O Dale; Jacobs, David R; Nickerson, Deborah A (Circ Cardiovasc Genet, 2009)
BACKGROUND: The transcription factor hepatocyte nuclear factor (HNF)-1 alpha regulates the activity of a number of genes involved in innate immunity, blood coagulation, lipid and glucose transport and metabolism, and cellular detoxification. Common polymorphisms of the HNF-1 alpha gene (HNF1A) were recently associated with plasma C-reactive protein and gamma-glutamyl transferase concentration in middle-aged to older European Americans (EA). METHODS AND RESULTS: We assessed whether common variants of HNF1A are associated with C-reactive protein, gamma-glutamyl transferase, and other atherosclerotic and metabolic risk factors, in the large, population-based Coronary Artery Risk Development in Young Adults Study of healthy young EA (n=2154) and African American (AA; n=2083) adults. The minor alleles of Ile27Leu (rs1169288) and Ser486Asn (rs2464196) were associated with 0.10 to 0.15 standard deviation units lower C-reactive protein and gamma-glutamyl transferase levels in EA. The same HNF1A coding variants were associated with higher low-density lipoprotein cholesterol, apolipoprotein B, creatinine, and fibrinogen in EA. We replicated the associations between HNF1A coding variants and C-reactive protein, fibrinogen, low-density lipoprotein cholesterol, and renal function in a second population-based sample of EA adults 65 years and older from the Cardiovascular Health Study. The HNF1A Ser486Asn and/or Ile27Leu variants were also associated with increased risk of subclinical coronary atherosclerosis in Coronary Artery Risk Development in Young Adults and with incident coronary heart disease in Cardiovascular Health Study. The Ile27Leu and Ser486Asn variants were 3-fold less common in AA than in EA. There was little evidence of association between HNF1A genotype and atherosclerosis-related phenotypes in AA. CONCLUSIONS: Common polymorphisms of HNF1A seem to influence multiple phenotypes related to cardiovascular risk in the general population of younger and older EA adults.
Keywords: Adolescent; Adult; African Americans; Aged; Aged, 80 and over; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, LDL; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; gamma-Glutamyltransferase; Genetic Predisposition to Disease; Genotype; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Common variants at ten loci influence QT interval duration in the QTGEN Study. - Newton-Cheh, Christopher; Eijgelsheim, Mark; Rice, Kenneth M; de Bakker, Paul I W; Yin, Xiaoyan; Estrada, Karol; Bis, Joshua C; Marciante, Kristin; Rivadeneira, Fernando; Noseworthy, Peter A; Sotoodehnia, Nona; Smith, Nicholas L; et al. (Nat Genet, 2009)
QT interval duration, reflecting myocardial repolarization on the electrocardiogram, is a heritable risk factor for sudden cardiac death and drug-induced arrhythmias. We conducted a meta-analysis of three genome-wide association studies in 13,685 individuals of European ancestry from the Framingham Heart Study, the Rotterdam Study and the Cardiovascular Health Study, as part of the QTGEN consortium. We observed associations at P < 5 x 10(-8) with variants in NOS1AP, KCNQ1, KCNE1, KCNH2 and SCN5A, known to be involved in myocardial repolarization and mendelian long-QT syndromes. Associations were found at five newly identified loci, including 16q21 near NDRG4 and GINS3, 6q22 near PLN, 1p36 near RNF207, 16p13 near LITAF and 17q12 near LIG3 and RFFL. Collectively, the 14 independent variants at these 10 loci explain 5.4-6.5% of the variation in QT interval. These results, together with an accompanying paper, offer insights into myocardial repolarization and suggest candidate genes that could predispose to sudden cardiac death and drug-induced arrhythmias.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Aged; Arrhythmias, Cardiac; Chromosome Mapping; Death, Sudden, Cardiac; Electroencephalography; ERG1 Potassium Channel; Ether-A-Go-Go Potassium Channels; European Continental Ancestry Group; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Humans; KCNQ1 Potassium Channel; Meta-Analysis as Topic; Muscle Proteins; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Potassium Channels, Voltage-Gated; Risk Factors; Sodium Channels

C-reactive protein, interleukin-6, and prostate cancer risk in men aged 65 years and older. - Pierce, Brandon L; Biggs, Mary L; DeCambre, Marvalyn; Reiner, Alexander P; Li, Christopher; Fitzpatrick, Annette; Carlson, Christopher S; Stanford, Janet L; Austin, Melissa A (Cancer Causes Control, 2009)
Inflammation is believed to play a role in prostate cancer (PCa) etiology, but it is unclear whether inflammatory markers C-reactive protein (CRP) and interleukin-6 (IL-6) associate with PCa risk in older men. Using Cox regression, we assessed the relationship between baseline concentrations of CRP and IL-6 and the subsequent PCa risk in the Cardiovascular Health Study, a population-based cohort study of mostly European American men of ages >64 years (n = 2,234; mean follow-up = 8.7 years; 215 incident PCa cases). We also tested associations between CRP and IL-6 tagSNPs and PCa risk, focusing on SNPs that are known to associate with circulating CRP and/or IL-6. Neither CRP nor IL-6 blood concentrations was associated with PCa risk. The C allele of IL-6 SNP rs1800795 (-174), a known functional variant, was associated with increased risk in a dominant model (HR = 1.44; 95% CI = 1.03-2.01; p = 0.03), but was not statistically significant after accounting for multiple tests (permutation p = 0.21). Our results suggest that circulating CRP and IL-6 do not influence PCa risk. SNPs at the CRP locus are not associated with PCa risk in this cohort, while the association between rs1800795 and PCa risk warrants further investigation.
Keywords: African Americans; Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; European Continental Ancestry Group; Humans; Inflammation; Interleukin-6; Male; Polymorphism, Single Nucleotide; Prospective Studies; Prostatic Neoplasms; Risk Factors

Cystatin C, albuminuria, and mortality among older adults with diabetes. - de Boer, Ian H; Katz, Ronit; Cao, Jie J; Fried, Linda F; Kestenbaum, Bryan; Mukamal, Ken; Rifkin, Dena E; Sarnak, Mark J; Shlipak, Michael G; Siscovick, David S (Diabetes Care, 2009)
OBJECTIVE: Albuminuria and impaired glomerular filtration rate (GFR) are each associated with poor health outcomes among individuals with diabetes. Joint associations of albuminuria and impaired GFR with mortality have not been comprehensively evaluated in this population. RESEARCH DESIGN AND METHODS: This is a cohort study among Cardiovascular Health Study participants with diabetes, mean age 78 years. GFR was estimated using serum cystatin C and serum creatinine. Albumin-to-creatinine ratio (ACR) was measured in single-voided urine samples. RESULTS: Of 691 participants, 378 died over 10 years of follow-up. Cystatin C-estimated GFR <60 ml/min per 1.73 m(2), creatinine-based estimated GFR <60 ml/min per 1.73 m(2), and urine ACR > or =30 mg/g were each associated with increased mortality risk with hazard ratios of 1.73 (95% CI 1.37-2.18), 1.54 (1.21-1.97), and 1.73 (1.39-2.17), respectively, adjusting for age, sex, race, diabetes duration, hypoglycemic medications, hypertension, BMI, smoking, cholesterol, lipid-lowering medications, prevalent cardiovascular disease (CVD), and prevalent heart failure. Cystatin C-estimated GFR and urine ACR were additive in terms of mortality risk. Cystatin C-estimated GFR predicted mortality more strongly than creatinine-based estimated GFR. CONCLUSIONS: Albuminuria and impaired GFR were independent, additive risk factors for mortality among older adults with diabetes. These findings support current recommendations to regularly assess both albuminuria and GFR in the clinical care of patients with diabetes; a focus on interventions to prevent or treat CVD in the presence of albuminuria, impaired GFR, or both; and further consideration of cystatin C use in clinical care.
Keywords: Aged; Aged, 80 and over; Albuminuria; Creatinine; Cystatin C; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Kidney Function Tests; Male; Risk Factors

Depressed mood is not a risk factor for incident dementia in a community-based cohort. - Becker, James T; Chang, Yue-Fang; Lopez, Oscar L; Dew, Mary Amanda; Sweet, Robert A; Barnes, Deborah; Yaffe, Kristine; Young, Jeffrey; Kuller, Lewis; Reynolds, Charles F (Am J Geriatr Psychiatry, 2009)
OBJECTIVES: To determine the relationship between depressed mood and the development of Alzheimer disease in cognitively normal individuals. DESIGN: Longitudinal and observational. SETTING: Community-based cohort study. PARTICIPANTS: A total of 288 participants in the Cardiovascular Health Study-Cognition Study (mean age: 77.52, SD =3.65, range: 70-89). All of the participants were adjudicated as cognitively normal in 1998/1999, and all had at least three visits before 1998/1999 with measures of cognition and mood state. The mean length of follow-up from 1998-1999 to 2007 was 7.1 years (range: 1-9 years, median =9 years). MEASUREMENTS: The Center for Epidemiological Studies-Depression Scale (CESD) was used to index mood state, and the Modified Mini-Mental State Examination (3MSE) was the index of cognitive function among participants before 1998/1999. These measures were considered in two ways: participants were classified according to: 1) whether they showed a high-negative correlation between their CESD and 3MSE scores (i.e., indicating that greater depression was linked to poorer cognition) and 2) whether they showed persistently elevated CESD scores. The study outcome, development of dementia (N = 48), was based on consensus classifications, which was based on detailed neuropsychological and neurological exams. RESULTS: The authors could find no consistent relationship between mood state, either alone or in relation to cognitive status, and the subsequent development of dementia. Those individuals whose cognitive functions were highly correlated with their mood state were no more likely to develop dementia than other participants. Those who had persistently depressed mood were also no more likely to develop dementia than those without persistently depressed mood. CONCLUSION: Within the confines of this prospective, community-based study of elderly adults, the authors could not find strong evidence to support the hypothesis that mood disturbance was linked with the development of dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Dementia; Depression; Female; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Prospective Studies; Psychiatric Status Rating Scales; Residence Characteristics; Risk Factors

Early age-related macular degeneration, cognitive function, and dementia: the Cardiovascular Health Study. - Baker, Michelle L; Wang, Jie Jin; Rogers, Sophie; Klein, Ronald; Kuller, Lewis H; Larsen, Emily K; Wong, Tien Yin (Arch Ophthalmol, 2009)
OBJECTIVE: To describe the association of cognitive function and dementia with early age-related macular degeneration (AMD) in older individuals. METHODS: This population-based study included 2,088 persons aged 69 to 97 years who participated in the Cardiovascular Health Study. The AMD was assessed from retinal photographs based on a modified Wisconsin AMD grading system. Cognitive function was assessed using the Digit Symbol Substitution Test (DSST) and the Modified Mini-Mental State Examination. Participants were also evaluated for dementia using detailed neuropsychological testing. RESULTS: After controlling for age, sex, race, and study center, persons with low DSST scores (lowest quartile of scores, < or =30) were more likely to have early AMD (odds ratio, 1.38; 95% confidence interval, 1.03-1.85) than were persons with higher DSST scores. In analyses further controlling for education, systolic blood pressure, total cholesterol level, diabetes mellitus, smoking status, and apolipoprotein E genotype, this association was stronger (odds ratio, 2.00; 95% confidence interval, 1.29-3.10). There was no association of low Modified Mini-Mental State Examination scores, dementia, or Alzheimer disease with early AMD. CONCLUSIONS: In this older population, cognitive impairment may share common age-related pathogenesis and risk factors with early AMD.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cognition Disorders; Dementia; Female; Humans; Intelligence Tests; Macular Degeneration; Male; Neuropsychological Tests; Odds Ratio; Prospective Studies; Risk Factors; United States

Gene variants associated with ischemic stroke: the cardiovascular health study. - Luke, May M; O'Meara, Ellen S; Rowland, Charles M; Shiffman, Dov; Bare, Lance A; Arellano, Andre R; Longstreth, W T; Lumley, Thomas; Rice, Kenneth; Tracy, Russell P; Devlin, James J; Psaty, Bruce M (Stroke, 2009)
BACKGROUND AND PURPOSE: The purpose of this study was to determine whether 74 single nucleotide polymorphisms (SNPs), which had been associated with coronary heart disease, are associated with incident ischemic stroke. METHODS: Based on antecedent studies of coronary heart disease, we prespecified the risk allele for each of the 74 SNPs. We used Cox proportional hazards models that adjusted for traditional risk factors to estimate the associations of these SNPs with incident ischemic stroke during 14 years of follow-up in a population-based study of older adults: the Cardiovascular Health Study (CHS). RESULTS: In white CHS participants, the prespecified risk alleles of 7 of the 74 SNPs (in HPS1, ITGAE, ABCG2, MYH15, FSTL4, CALM1, and BAT2) were nominally associated with increased risk of stroke (one-sided P<0.05, false discovery rate=0.42). In black participants, the prespecified risk alleles of 5 SNPs (in KRT4, LY6G5B, EDG1, DMXL2, and ABCG2) were nominally associated with stroke (one-sided P<0.05, false discovery rate=0.55). The Val12Met SNP in ABCG2 was associated with stroke in both white (hazard ratio, 1.46; 90% CI, 1.05 to 2.03) and black (hazard ratio, 3.59; 90% CI, 1.11 to 11.6) participants of CHS. Kaplan-Meier estimates of the 10-year cumulative incidence of stroke were greater among Val allele homozygotes than among Met allele carriers in both white (10% versus 6%) and black (12% versus 3%) participants of CHS. CONCLUSIONS: The Val12Met SNP in ABCG2 (encoding a transporter of sterols and xenobiotics) was associated with incident ischemic stroke in white and black participants of CHS.
Keywords: African Continental Ancestry Group; Aged; Alleles; Brain Ischemia; Cardiovascular Diseases; Coronary Disease; Ethnic Groups; European Continental Ancestry Group; Female; Gene Frequency; Genetic Variation; Humans; Kaplan-Meier Estimate; Male; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Stroke; United States

Genetic variants associated with cardiac structure and function: a meta-analysis and replication of genome-wide association data. - Vasan, Ramachandran S; Glazer, Nicole L; Felix, Janine F; Lieb, Wolfgang; Wild, Philipp S; Felix, Stephan B; Watzinger, Norbert; Larson, Martin G; Smith, Nicholas L; Dehghan, Abbas; Grosshennig, Anika; Schillert, Arne; et al. (JAMA, 2009)
CONTEXT: Echocardiographic measures of left ventricular (LV) structure and function are heritable phenotypes of cardiovascular disease. OBJECTIVE: To identify common genetic variants associated with cardiac structure and function by conducting a meta-analysis of genome-wide association data in 5 population-based cohort studies (stage 1) with replication (stage 2) in 2 other community-based samples. DESIGN, SETTING, AND PARTICIPANTS: Within each of 5 community-based cohorts comprising the EchoGen consortium (stage 1; n = 12 612 individuals of European ancestry; 55% women, aged 26-95 years; examinations between 1978-2008), we estimated the association between approximately 2.5 million single-nucleotide polymorphisms (SNPs; imputed to the HapMap CEU panel) and echocardiographic traits. In stage 2, SNPs significantly associated with traits in stage 1 were tested for association in 2 other cohorts (n = 4094 people of European ancestry). Using a prespecified P value threshold of 5 x 10(-7) to indicate genome-wide significance, we performed an inverse variance-weighted fixed-effects meta-analysis of genome-wide association data from each cohort. MAIN OUTCOME MEASURES: Echocardiographic traits: LV mass, internal dimensions, wall thickness, systolic dysfunction, aortic root, and left atrial size. RESULTS: In stage 1, 16 genetic loci were associated with 5 echocardiographic traits: 1 each with LV internal dimensions and systolic dysfunction, 3 each with LV mass and wall thickness, and 8 with aortic root size. In stage 2, 5 loci replicated (6q22 locus associated with LV diastolic dimensions, explaining <1% of trait variance; 5q23, 12p12, 12q14, and 17p13 associated with aortic root size, explaining 1%-3% of trait variance). CONCLUSIONS: We identified 5 genetic loci harboring common variants that were associated with variation in LV diastolic dimensions and aortic root size, but such findings explained a very small proportion of variance. Further studies are required to replicate these findings, identify the causal variants at or near these loci, characterize their functional significance, and determine whether they are related to overt cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Aorta; Cardiovascular Diseases; Echocardiography; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart Atria; Heart Ventricles; Humans; Male; Middle Aged; Organ Size; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Ventricular Dysfunction, Left; Ventricular Function, Left

Genetic variations in nitric oxide synthase 1 adaptor protein are associated with sudden cardiac death in US white community-based populations. - Kao, W H Linda; Arking, Dan E; Post, Wendy; Rea, Thomas D; Sotoodehnia, Nona; Prineas, Ronald J; Bishe, Bryan; Doan, Betty Q; Boerwinkle, Eric; Psaty, Bruce M; Tomaselli, Gordon F; Coresh, Josef; et al. (Circulation, 2009)
BACKGROUND: The ECG QT interval is associated with risk of sudden cardiac death (SCD). A previous genome-wide association study demonstrated that allelic variants (rs10494366 and rs4657139) in the nitric oxide synthase 1 adaptor protein (NOS1AP), which encodes a carboxy-terminal PDZ ligand of neuronal nitric oxide synthase, are associated with the QT interval in white adults. The present analysis was conducted to validate the association between NOS1AP variants and the QT interval and to examine the association with SCD in a combined population of 19 295 black and white adults from the Atherosclerosis Risk In Communities Study and the Cardiovascular Health Study. METHODS AND RESULTS: We examined 19 tagging single-nucleotide polymorphisms in the genomic blocks containing rs10494366 and rs4657139 in NOS1AP. SCD was defined as a sudden pulseless condition of cardiac origin in a previously stable individual. General linear models and Cox proportional hazards regression models were used. Multiple single-nucleotide polymorphisms in NOS1AP, including rs10494366, rs4657139, and rs16847548, were significantly associated with adjusted QT interval in whites (P<0.0001). In whites, after adjustment for age, sex, and study, the relative hazard of SCD associated with each C allele at rs16847548 was 1.31 (95% confidence interval 1.10 to 1.56, P=0.002), assuming an additive model. In addition, a downstream neighboring single-nucleotide polymorphism, rs12567209, which was not correlated with rs16847548 or QT interval, was also independently associated with SCD in whites (relative hazard 0.57, 95% confidence interval 0.39 to 0.83, P=0.003). Adjustment for QT interval and coronary heart disease risk factors attenuated but did not eliminate the association between rs16847548 and SCD, and such adjustment had no effect on the association between rs12567209 and SCD. No significant associations between tagging single-nucleotide polymorphisms in NOS1AP and either QT interval or SCD were observed in blacks. CONCLUSIONS: In a combined analysis of 2 population-based prospective cohort studies, sequence variations in NOS1AP were associated with baseline QT interval and the risk of SCD in white US adults.
Keywords: Adaptor Proteins, Signal Transducing; Aged; Death, Sudden, Cardiac; Electrocardiography; European Continental Ancestry Group; Genotype; Humans; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genome-wide association studies of cardiovascular risk factors: design, conduct and interpretation. - Bis, J C; Glazer, N L; Psaty, B M (J Thromb Haemost, 2009)
Relying on known biology, candidate-gene studies have been only modestly successful in identifying genetic variants associated with cardiovascular risk factors. Genome-wide association (GWA) studies, in contrast, allow broad scans across millions of loci in search of unsuspected genetic associations with phenotypes. The large numbers of statistical tests in GWA studies and the large sample sizes required to detect modest-sized associations have served as a powerful incentive for the development of large collaborative efforts such as the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. This article uses published data on three phenotypes, fibrinogen, uric acid, and electrocardiographic QT interval duration, from the CHARGE Consortium to describe several methodologic issues in the design, conduct, and interpretation of GWA studies, including the use of imputation and the need for additional genotyping. Even with large studies, novel genetic loci explain only a small proportion of the variance of cardiovascular phenotypes.
Keywords: Cardiovascular Diseases; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Quantitative Trait Loci; Risk Factors

Genomewide association studies of stroke. - Ikram, M Arfan; Seshadri, Sudha; Bis, Joshua C; Fornage, Myriam; DeStefano, Anita L; Aulchenko, Yurii S; Debette, Stephanie; Lumley, Thomas; Folsom, Aaron R; van den Herik, Evita G; Bos, Michiel J; Beiser, Alexa; et al. (N Engl J Med, 2009)
BACKGROUND: The genes underlying the risk of stroke in the general population remain undetermined. METHODS: We carried out an analysis of genomewide association data generated from four large cohorts composing the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, including 19,602 white persons (mean [+/-SD] age, 63+/-8 years) in whom 1544 incident strokes (1164 ischemic strokes) developed over an average follow-up of 11 years. We tested the markers most strongly associated with stroke in a replication cohort of 2430 black persons with 215 incident strokes (191 ischemic strokes), another cohort of 574 black persons with 85 incident strokes (68 ischemic strokes), and 652 Dutch persons with ischemic stroke and 3613 unaffected persons. RESULTS: Two intergenic single-nucleotide polymorphisms on chromosome 12p13 and within 11 kb of the gene NINJ2 were associated with stroke (P<5x10(-8)). NINJ2 encodes an adhesion molecule expressed in glia and shows increased expression after nerve injury. Direct genotyping showed that rs12425791 was associated with an increased risk of total (i.e., all types) and ischemic stroke, with hazard ratios of 1.30 (95% confidence interval [CI], 1.19 to 1.42) and 1.33 (95% CI, 1.21 to 1.47), respectively, yielding population attributable risks of 11% and 12% in the discovery cohorts. Corresponding hazard ratios were 1.35 (95% CI, 1.01 to 1.79; P=0.04) and 1.42 (95% CI, 1.06 to 1.91; P=0.02) in the large cohort of black persons and 1.17 (95% CI, 1.01 to 1.37; P=0.03) and 1.19 (95% CI, 1.01 to 1.41; P=0.04) in the Dutch sample; the results of an underpowered analysis of the smaller black cohort were nonsignificant. CONCLUSIONS: A genetic locus on chromosome 12p13 is associated with an increased risk of stroke.
Keywords: African Continental Ancestry Group; Aged; Chromosomes, Human, Pair 12; Cohort Studies; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk Factors; Stroke

Heart rate variability and its changes over 5 years in older adults. - Stein, Phyllis K; Barzilay, Joshua I; Chaves, Paulo H M; Domitrovich, Peter P; Gottdiener, John S (Age Ageing, 2009)
PURPOSE: to characterise the association between age, ageing and heart rate variability (HRV) in older individuals, 585 adults age >65 years with two 24-h Holter recordings in the Cardiovascular Health Study were studied. METHODS: heart rate (HR), ventricular premature contractions (VPCs), atrial premature contractions (APCs), frequency-domain, ratio-based and non-linear HRV and heart rate turbulence (HRT) were examined cross-sectionally by 5-year age groups and prospectively over 5 years. Analyses adjusted for gender, lower versus elevated cardiovascular (CV) risk and for the change in CV risk. RESULTS: HR declined, and VPCs and APCs increased per 5-year increase in age. Frequency-domain HRV decreased more at 65-69, less at 70-74 and minimally at > or =75 years, independent of CVD risk or change in CVD risk. Ratio and non-linear HRV continued to decline to > or =75 years old. Ratio HRV and HRT slope were more strongly related to CVD risk than frequency-domain HRV. CONCLUSIONS: cardiac autonomic function, assessed by frequency-domain HRV, declines most at 65-70 and levels off at age >75. The decline is independent of CVD risk or change in CVD risk. Ratio-based and non-linear HRV and HRT slope continued to change with increasing age and were more closely related to CVD risk than frequency-domain HRV.
Keywords: Age Distribution; Aged; Aging; Atrial Premature Complexes; Autonomic Nervous System; Cardiovascular Diseases; Cross-Sectional Studies; Electrocardiography, Ambulatory; Female; Heart Rate; Humans; Hypertension; Male; Nonlinear Dynamics; Prevalence; Prospective Studies; Risk Factors; Ventricular Premature Complexes

High frequency of and factors associated with thyroid hormone over-replacement and under-replacement in men and women aged 65 and over. - Somwaru, Lily L; Arnold, Alice M; Joshi, Neha; Fried, Linda P; Cappola, Anne R (J Clin Endocrinol Metab, 2009)
CONTEXT: Thyroid hormone use is common in older populations, but the frequency of over- or under-replacement is debated. OBJECTIVE: We sought to describe the frequency of and factors associated with thyroid hormone over- or under-replacement in a population of older men and women. DESIGN: Participants were 3678 U.S. community dwelling individuals aged 65 yr or older enrolled in the Cardiovascular Health Study who had thyroid function tests in 1989-1990. Thyroid hormone users (n = 339) were identified and classified into low TSH (<0.45 mU/liter), euthyroid (0.45-4.5 mU/liter), and high TSH (>4.5 mU/liter). RESULTS: Of the 339 thyroid hormone users, 41% had a low TSH, 16% had a high TSH, and 43% were in the euthyroid range. In multivariable analyses, lower weight (P < 0.001) was independently associated with low TSH status. For every 10 kg lower weight, the likelihood of having low TSH increased by 65% [odd ratio (OR) 1.65; 95% confidence interval (CI) 1.31-2.07]. Those with renal insufficiency were less likely to have low TSH levels (P = 0.02). The presence of diabetes was independently associated with having low (OR 3.35; 95% CI 1.46-7.65) and high TSH levels (OR 2.66; 95% CI 1.14-6.21). CONCLUSIONS: There is a very high prevalence of thyroid function testing abnormalities in older people taking thyroid hormone preparations, particularly in those of low weight or with diabetes. Because of potential adverse cardiovascular and skeletal effects from over-replacement, older people represent a key population for increased TSH monitoring on therapy.
Keywords: Aged; Body Mass Index; Body Weight; Diabetes Mellitus; Dose-Response Relationship, Drug; Drug Therapy, Combination; Female; Hormone Replacement Therapy; Humans; Male; Multivariate Analysis; Renal Insufficiency; Risk Factors; Thyroid Diseases; Thyroid Hormones; Thyrotropin; Thyroxine; Triiodothyronine

Inflammation and stress-related candidate genes, plasma interleukin-6 levels, and longevity in older adults. - Walston, Jeremy D; Matteini, Amy M; Nievergelt, Caroline; Lange, Leslie A; Fallin, Dani M; Barzilai, Nir; Ziv, Elad; Pawlikowska, Ludmila; Kwok, Pui; Cummings, Steve R; Kooperberg, Charles; LaCroix, Andrea; et al. (Exp Gerontol, 2009)
Interleukin-6 (IL-6) is an inflammatory cytokine that influences the development of inflammatory and aging-related disorders and ultimately longevity. In order to study the influence of variants in genes that regulate inflammatory response on IL-6 levels and longevity, we screened a panel of 477 tag SNPs across 87 candidate genes in >5000 older participants from the population-based Cardiovascular Health Study (CHS). Baseline plasma IL-6 concentration was first confirmed as a strong predictor of all-cause mortality. Functional alleles of the IL6R and PARP1 genes were significantly associated with 15%-20% higher baseline IL-6 concentration per copy among CHS European-American (EA) participants (all p<10(-4)). In a case/control analysis nested within this EA cohort, the minor allele of PARP1 rs1805415 was nominally associated with decreased longevity (p=0.001), but there was no evidence of association between IL6R genotype and longevity. The PARP1 rs1805415--longevity association was subsequently replicated in one of two independent case/control studies. In a pooled analysis of all three studies, the "risk" of longevity associated with the minor allele of PARP1 rs1805415 was 0.79 (95%CI 0.62-1.02; p=0.07). These findings warrant further study of the potential role of PARP1 genotype in inflammatory and aging-related phenotypes.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Case-Control Studies; Female; Genetic Variation; Genotype; Humans; Inflammation; Interleukin-6; Longevity; Male; Phenotype; Poly (ADP-Ribose) Polymerase-1; Poly(ADP-ribose) Polymerases; Risk Factors

Insomnia did not predict incident hypertension in older adults in the cardiovascular health study. - Phillips, Barbara; Bůzková, Petra; Enright, Paul (Sleep, 2009)
STUDY OBJECTIVE: We hypothesized that the sleep complaints of insomnia predict incident hypertension, particularly in African Americans. The purpose of this study was to analyze insomnia complaints as predictors of incident hypertension in the Cardiovascular Health Study (CHS), stratifying by gender and allowing for race and sleep variable interaction. DESIGN: This is a prospective cohort study over a 6-year period of follow-up. SETTING: This is a community-based study of participants in Forsyth County, North Carolina; Pittsburgh, Pennsylvania; Sacramento County, California; and Washington County, Maryland. PARTICIPANTS: The study analyzed data from 1419 older individuals (baseline mean age 73.4 +/- 4.4 years) from the Cardiovascular Health Study who were not hypertensive at baseline. INTERVENTIONS: none. MEASUREMENTS: We constructed relative risks of incident hypertension over a 6-year period for insomnia complaints singly and in combination. RESULTS: Difficulty falling asleep, singly or in combination with other sleep complaints, predicted a statistically significant reduction of risk for incident hypertension for non-African American men in 6 years of follow-up. Insomnia complaints did not predict incident hypertension in 6 years of follow-up in women or in African Americans, although there may not have been enough power to show a significant association for African Americans. CONCLUSIONS: Insomnia did not predict hypertension in this older cohort which was free of hypertension at baseline. Difficulty falling asleep was associated with reduced risk of hypertension in non-African American men.
Keywords: African Americans; Aged; Cohort Studies; Comorbidity; European Continental Ancestry Group; Female; Follow-Up Studies; Health Surveys; Humans; Hypertension; Male; Prospective Studies; Risk Factors; Sleep Initiation and Maintenance Disorders; United States

Lifestyle risk factors and new-onset diabetes mellitus in older adults: the cardiovascular health study. - Mozaffarian, Dariush; Kamineni, Aruna; Carnethon, Mercedes; Djoussé, Luc; Mukamal, Kenneth J; Siscovick, David (Arch Intern Med, 2009)
BACKGROUND: The combined impact of lifestyle factors on incidence of diabetes mellitus later in life is not well established. The objective of this study was to determine how lifestyle factors, assessed in combination, relate to new-onset diabetes in a broad and relatively unselected population of older adults. METHODS: We prospectively examined associations of lifestyle factors, measured using repeated assessments later in life, with incident diabetes mellitus during a 10-year period (1989-1998) among 4883 men and women 65 years or older (mean [SD] age at baseline, 73 [6] years) enrolled in the Cardiovascular Health Study. Low-risk lifestyle groups were defined by physical activity level (leisure-time activity and walking pace) above the median; dietary score (higher fiber intake and polyunsaturated to saturated fat ratio, lower trans-fat intake and lower mean glycemic index) in the top 2 quintiles; never smoked or former smoker more than 20 years ago or for fewer than 5 pack-years; alcohol use (predominantly light or moderate); body mass index less than 25 (calculated as weight in kilograms divided by height in meters squared); and waist circumference of 88 cm for women or 92 cm for men. The main outcome measure was incident diabetes defined annually by new use of insulin or oral hypoglycemic medications. We also evaluated fasting and 2-hour postchallenge glucose levels. RESULTS: During 34,539 person-years, 337 new cases of drug-treated diabetes mellitus occurred (9.8 per 1000 person-years). After adjustment for age, sex, race, educational level, and annual income, each lifestyle factor was independently associated with incident diabetes. Overall, the rate of incident diabetes was 35% lower (relative risk, 0.65; 95% confidence interval, 0.59-0.71) for each 1 additional lifestyle factor in the low-risk group. Participants whose physical activity level and dietary, smoking, and alcohol habits were all in the low-risk group had an 82% lower incidence of diabetes (relative risk, 0.18; 95% confidence interval, 0.06-0.56) compared with all other participants. When absence of adiposity (either body mass index <25 or waist circumference < or =88/92 cm for women/men) was added to the other 4 low-risk lifestyle factors, incidence of diabetes was 89% lower (relative risk, 0.11; 95% confidence interval, 0.01-0.76). Overall, 9 of 10 new cases of diabetes appeared to be attributable to these 5 lifestyle factors. Associations were slightly attenuated, but still highly significant, for incident diabetes defined by medication use or glucose level. CONCLUSION: Even later in life, combined lifestyle factors are associated with a markedly lower incidence of new-onset diabetes mellitus.
Keywords: Age of Onset; Aged; Aged, 80 and over; Diabetes Mellitus, Type 2; Female; Humans; Incidence; Life Style; Male; National Heart, Lung, and Blood Institute (U.S.); Prospective Studies; Risk Factors; United States

Lipoprotein(a) concentration and the risk of coronary heart disease, stroke, and nonvascular mortality. - Erqou, Sebhat; Kaptoge, Stephen; Perry, Philip L; Di Angelantonio, Emanuele; Thompson, Alexander; White, Ian R; Marcovina, Santica M; Collins, Rory; Thompson, Simon G; Danesh, John (JAMA, 2009)
CONTEXT: Circulating concentration of lipoprotein(a) (Lp[a]), a large glycoprotein attached to a low-density lipoprotein-like particle, may be associated with risk of coronary heart disease (CHD) and stroke. OBJECTIVE: To assess the relationship of Lp(a) concentration with risk of major vascular and nonvascular outcomes. STUDY SELECTION: Long-term prospective studies that recorded Lp(a) concentration and subsequent major vascular morbidity and/or cause-specific mortality published between January 1970 and March 2009 were identified through electronic searches of MEDLINE and other databases, manual searches of reference lists, and discussion with collaborators. DATA EXTRACTION: Individual records were provided for each of 126,634 participants in 36 prospective studies. During 1.3 million person-years of follow-up, 22,076 first-ever fatal or nonfatal vascular disease outcomes or nonvascular deaths were recorded, including 9336 CHD outcomes, 1903 ischemic strokes, 338 hemorrhagic strokes, 751 unclassified strokes, 1091 other vascular deaths, 8114 nonvascular deaths, and 242 deaths of unknown cause. Within-study regression analyses were adjusted for within-person variation and combined using meta-analysis. Analyses excluded participants with known preexisting CHD or stroke at baseline. DATA SYNTHESIS: Lipoprotein(a) concentration was weakly correlated with several conventional vascular risk factors and it was highly consistent within individuals over several years. Associations of Lp(a) with CHD risk were broadly continuous in shape. In the 24 cohort studies, the rates of CHD in the top and bottom thirds of baseline Lp(a) distributions, respectively, were 5.6 (95% confidence interval [CI], 5.4-5.9) per 1000 person-years and 4.4 (95% CI, 4.2-4.6) per 1000 person-years. The risk ratio for CHD, adjusted for age and sex only, was 1.16 (95% CI, 1.11-1.22) per 3.5-fold higher usual Lp(a) concentration (ie, per 1 SD), and it was 1.13 (95% CI, 1.09-1.18) following further adjustment for lipids and other conventional risk factors. The corresponding adjusted risk ratios were 1.10 (95% CI, 1.02-1.18) for ischemic stroke, 1.01 (95% CI, 0.98-1.05) for the aggregate of nonvascular mortality, 1.00 (95% CI, 0.97-1.04) for cancer deaths, and 1.00 (95% CI, 0.95-1.06) for nonvascular deaths other than cancer. CONCLUSION: Under a wide range of circumstances, there are continuous, independent, and modest associations of Lp(a) concentration with risk of CHD and stroke that appear exclusive to vascular outcomes.
Keywords: Cause of Death; Coronary Disease; Humans; Lipoprotein(a); Risk Factors; Stroke

Lipoprotein-associated phospholipase A(2) and risk of congestive heart failure in older adults: the Cardiovascular Health Study. - Suzuki, Takeki; Solomon, Cam; Jenny, Nancy Swords; Tracy, Russell; Nelson, Jeanenne J; Psaty, Bruce M; Furberg, Curt; Cushman, Mary (Circ Heart Fail, 2009)
BACKGROUND: Inflammation may be a causative factor in congestive heart failure (CHF). Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) is an inflammation marker associated with vascular risk. One previous study showed an association of Lp-PLA(2) activity with CHF risk, but there were only 94 CHF cases and Lp-PLA(2) antigen, which is available clinically in the United States, was not measured. METHODS AND RESULTS: We measured baseline Lp-PLA(2) antigen and activity in 3991 men and women without baseline CHF or cardiovascular disease who were participating in the Cardiovascular Health Study, a prospective observational study of adults 65 years or older. Cox proportional hazards models adjusted for age, sex, clinic site, race, low-density and high-density lipoprotein cholesterol, body mass index, systolic and diastolic blood pressure, hypertension, smoking status, pack-years, and diabetes were used to calculate hazard ratios and 95% CIs for incident CHF. Further models adjusted for coronary disease events during follow-up and C-reactive protein. Eight hundred twenty-nine participants developed CHF during 12.1 years. Adjusted hazard ratios for CHF with Lp-PLA(2) in the fourth compared with the first quartile were 1.44 (95% CI, 1.16 to 1.79) for Lp-PLA(2) antigen and 1.06 (95% CI, 0.84 to 1.32) for activity. Adjustment for incident coronary disease attenuated the hazard ratio for Lp-PLA(2) antigen to 1.26 (95% CI, 1.02 to 1.57), adjustment for C-reactive protein had minimal impact. CONCLUSIONS: Lp-PLA(2) antigen was associated with risk of future CHF in older people, independent of CHF and coronary risk factors, and partly mediated by coronary disease events. Further clinical and basic research is needed to better understand the role of Lp-PLA(2) in CHF.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Biomarkers; C-Reactive Protein; Female; Fibrinogen; Heart Failure; Humans; Incidence; Inflammation Mediators; Interleukin-6; Kaplan-Meier Estimate; Male; Population Surveillance; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Long-term function in an older cohort--the cardiovascular health study all stars study. - Newman, Anne B; Arnold, Alice M; Sachs, Michael C; Ives, Diane G; Cushman, Mary; Strotmeyer, Elsa S; Ding, Jingzhong; Kritchevsky, Stephen B; Chaves, Paulo H M; Fried, Linda P; Robbins, John (J Am Geriatr Soc, 2009)
OBJECTIVES: To evaluate shared and unique risk factors for maintaining physical and cognitive function into the ninth decade and beyond. DESIGN: Longitudinal cohort study. SETTING: Four U.S. communities. PARTICIPANTS: One thousand six hundred seventy-seven participants in the Cardiovascular Health Study All Stars Study, assessed in 2005/06. Median age was 85 (range 77-102), 66.5% were women, and 16.6% were black. MEASUREMENTS: Intact function was defined as no difficulty with any activities of daily living and a score of 80 or higher on the Modified Mini-Mental State Examination. Baseline characteristics assessed in 1992/93 included demographics, behavioral health factors, chronic disease history, subclinical disease markers, cardiovascular risk factors, and inflammatory markers. Multinomial logistic regression was used to compare risk for physical disability, cognitive impairment,and combined impairments with no functional impairment. RESULTS: Of the 1,677 participants evaluated in both domains, 891 (53%) were functionally intact. Continuous measures of function, including the Digit Symbol Substitution Test and gait speed, showed that all groups, including the most functional, had declined over time. The functional group had less decline but also tended to have higher starting values. Functional individuals had a higher baseline health profile than those with either or cognitive impairment or both impairments combined. Women and individuals with greater weight had higher rates of physical impairment but not cognitive impairment. Risk factors common to both types of impairment included cardiovascular disease and hypertension. CONCLUSION: Intact function was found in only approximately half of these older adults in the ninth decade and beyond. High baseline function and low vascular disease risk characterized functional aging.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Attention; Cardiovascular Diseases; Chronic Disease; Cohort Studies; Comorbidity; Cross-Sectional Studies; Female; Follow-Up Studies; Gait; Geriatric Assessment; Hand Strength; Health Surveys; Humans; Male; Memory, Short-Term; Mental Status Schedule; Proportional Hazards Models; Psychometrics; Risk Factors; United States

Meta-analysis: retinal vessel caliber and risk for coronary heart disease. - McGeechan, Kevin; Liew, Gerald; Macaskill, Petra; Irwig, Les; Klein, Ronald; Klein, Barbara E K; Wang, Jie Jin; Mitchell, Paul; Vingerling, Johannes R; Dejong, Paulus T V M; Witteman, Jacqueline C M; Breteler, Monique M B; et al. (Ann Intern Med, 2009)
BACKGROUND: Retinal vessel caliber may be a novel marker of coronary heart disease (CHD) risk. However, the sex-specific effect, magnitude of association, and effect independent of traditional CHD disease risk factors remain unclear. PURPOSE: To determine the association between retinal vessel caliber and risk for CHD. DATA SOURCES: Relevant studies in any language identified through MEDLINE (1950 to June 2009) and EMBASE (1950 to June 2009) databases. STUDY SELECTION: Studies were included if they examined a general population, measured retinal vessel caliber from retinal photographs, and documented CHD risk factors and incident CHD events. DATA EXTRACTION: 6 population-based prospective cohort studies provided data for individual participant meta-analysis. DATA SYNTHESIS: Proportional hazards models, adjusted for traditional CHD risk factors, were constructed for retinal vessel caliber and incident CHD in women and men. Among 22,159 participants who were free of CHD and followed for 5 to 14 years, 2219 (10.0%) incident CHD events occurred. Retinal vessel caliber changes (wider venules and narrower arterioles) were each associated with an increased risk for CHD in women (pooled multivariable-adjusted hazard ratios, 1.16 [95% CI, 1.06 to 1.26] per 20-microm increase in venular caliber and 1.17 [CI, 1.07 to 1.28] per 20-microm decrease in arteriolar caliber) but not in men (1.02 [CI, 0.94 to 1.10] per 20-microm increase in venular caliber and 1.02 [CI, 0.95 to 1.10] per 20-microm decrease in arteriolar caliber). Women without hypertension or diabetes had higher hazard ratios. LIMITATION: Error in the measurement of retinal vessel caliber and Framingham variables was not taken into account. CONCLUSION: Retinal vessel caliber changes were independently associated with an increased risk for CHD events in women.
Keywords: Adult; Aged; Arterioles; Biomarkers; Coronary Disease; Female; Humans; Male; Middle Aged; Proportional Hazards Models; Retinal Vessels; Risk Factors; Sex Factors; Venules

Metabolic syndrome and risk of venous thromboembolism: Longitudinal Investigation of Thromboembolism Etiology. - Steffen, L M; Cushman, M; Peacock, J M; Heckbert, S R; Jacobs, D R; Rosamond, W D; Folsom, A R (J Thromb Haemost, 2009)
SUMMARY BACKGROUND: In a recent case-control study, the odds of metabolic syndrome (MetSyn) among deep vein thrombosis cases were almost twice those among controls. We tested the hypothesis that the incidence of non-cancer-related venous thromboembolism (VTE) is higher among adults with MetSyn and further, that associations are stronger for idiopathic than secondary VTE. METHODS: A total of 20 374 middle-aged and elderly adults were followed for over 12 years for incident VTE in the Longitudinal Investigation of Thromboembolism Etiology (LITE). All hospitalizations were identified and VTEs validated by chart review. Baseline MetSyn was defined using ATP III guidelines, including >or=3 of the following components: abdominal obesity, elevated blood pressure, low HDL-cholesterol, high triglycerides and high glucose. Because sex modified the relation between MetSyn and VTE (p(interaction) = 0.001), proportional hazards regression analyses were stratified by sex to assess the associations of MetSyn and its components with risk of incident non-cancer-related VTE, adjusting for potential confounders. RESULTS: Incident VTE (n = 358) included 196 idiopathic events. Baseline MetSyn was associated with risk of total VTE (hazard ratio (HR) = 1.84, 95% CI = 1.30, 2.59) and idiopathic VTE (HR = 1.59, 95% CI = 1.02, 2.47) among men, but not women. The association was largely attributable to abdominal obesity (HR of VTE = 2.10, 95% CI = 1.51, 2.93, in men; HR of VTE = 1.70, 95% CI = 1.24, 2.34, in women), with no additional contribution by the other MetSyn components. CONCLUSION: Although abdominal obesity was associated with increased risk of VTE in both men and women, MetSyn and its other components do not seem important in VTE etiology.
Keywords: Blood Coagulation Factors; Blood Glucose; Blood Pressure; Body Mass Index; Cohort Studies; Female; Fibrinogen; Humans; Lipids; Longitudinal Studies; Male; Metabolic Syndrome; Proportional Hazards Models; Risk Factors; Venous Thromboembolism

N-terminal pro-B-type natriuretic peptide is a major predictor of the development of atrial fibrillation: the Cardiovascular Health Study. - Patton, Kristen K; Ellinor, Patrick T; Heckbert, Susan R; Christenson, Robert H; DeFilippi, Christopher; Gottdiener, John S; Kronmal, Richard A (Circulation, 2009)
BACKGROUND: Atrial fibrillation (AF), the most common cardiac rhythm abnormality, is associated with significant morbidity, mortality, and healthcare expenditures. Elevated B-type natriuretic peptide levels have been associated with the risk of heart failure, AF, and mortality. METHODS AND RESULTS: The relation between N-terminal pro-B-type natriuretic peptide (NT-proBNP) and AF was studied in 5445 Cardiovascular Health Study participants with the use of relative risk regression for predicting prevalent AF and Cox proportional hazards for predicting incident AF. NT-proBNP levels were strongly associated with prevalent AF, with an unadjusted prevalence ratio of 128 for the highest quintile (95% confidence interval, 17.9 to 913.3; P<0.001) and adjusted prevalence ratio of 147 for the highest quintile (95% confidence interval, 20.4 to 1064.3; P<0.001) compared with the lowest. After a median follow-up of 10 years (maximum of 16 years), there were 1126 cases of incident AF (a rate of 2.2 per 100 person-years). NT-proBNP was highly predictive of incident AF, with an unadjusted hazard ratio of 5.2 (95% confidence interval, 4.3 to 6.4; P<0.001) for the development of AF for the highest quintile compared with the lowest; for the same contrast, NT-proBNP remained the strongest predictor of incident AF after adjustment for an extensive number of covariates, including age, sex, medication use, blood pressure, echocardiographic parameters, diabetes mellitus, and heart failure, with an adjusted hazard ratio of 4.0 (95% confidence interval, 3.2 to 5.0; P<0.001). CONCLUSIONS: In a community-based population of older adults, NT-proBNP was a remarkable predictor of incident AF, independent of any other previously described risk factor.
Keywords: Aged; Aged, 80 and over; Atrial Fibrillation; Female; Humans; Immunoassay; Longitudinal Studies; Male; Natriuretic Peptide, Brain; Peptide Fragments; Predictive Value of Tests; Prevalence; Proportional Hazards Models; Risk Factors

Obesity and change in estimated GFR among older adults. - de Boer, Ian H; Katz, Ronit; Fried, Linda F; Ix, Joachim H; Luchsinger, Jose; Sarnak, Mark J; Shlipak, Michael G; Siscovick, David S; Kestenbaum, Bryan (Am J Kidney Dis, 2009)
BACKGROUND: The prevalence of chronic kidney disease is growing most rapidly among older adults; however, determinants of impaired kidney function in this population are not well understood. Obesity assessed in midlife has been associated with chronic kidney disease. STUDY DESIGN: Cohort study. SETTING & PARTICIPANTS: 4,295 participants in the community-based Cardiovascular Health Study, aged >or= 65 years. PREDICTORS: Body mass index, waist circumference, and fat mass measured using bioelectrical impedance. OUTCOME: Change in glomerular filtration rate (GFR) during 7 years of follow-up. MEASUREMENTS: Longitudinal estimates of GFR calculated using the 4-variable Modification of Diet in Renal Disease (MDRD) Study equation. RESULTS: Estimated GFR decreased by an average of 0.4 +/- 3.6 mL/min/1.73 m(2)/y, and rapid GFR loss (>3 mL/min/1.73 m(2)/y) occurred in 693 participants (16%). Baseline body mass index, waist circumference, and fat mass were each associated with increased risk of rapid GFR loss: ORs, 1.19 (95% CI, 1.09-1.30) per 5 kg/m(2), 1.25 (95% CI, 1.16-1.36) per 12 cm, and 1.14 (95% CI, 1.05-1.24) per 10 kg after adjustment for age, sex, race, and smoking. The magnitude of increased risk was larger for participants with estimated GFR < 60 mL/min/1.73 m(2) at baseline (P for interaction < 0.05). Associations were substantially attenuated by further adjustment for diabetes, hypertension, and C-reactive protein level. Obesity measurements were not associated with change in GFR estimated using serum cystatin C level. LIMITATIONS: Few participants with advanced chronic kidney disease at baseline, no direct GFR measurements. CONCLUSION: Obesity may be a modifiable risk factor for the development and progression of kidney disease in older adults.
Keywords: Aged; Aging; Body Composition; Body Mass Index; Chronic Disease; Cohort Studies; Creatinine; Cystatin C; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Longitudinal Studies; Male; Obesity; Risk Factors

Peak thrombin generation and subsequent venous thromboembolism: the Longitudinal Investigation of Thromboembolism Etiology (LITE) study. - Lutsey, P L; Folsom, A R; Heckbert, S R; Cushman, M (J Thromb Haemost, 2009)
BACKGROUND: Thrombin is an enzyme that is essential for the acceleration of the coagulation cascade and the conversion of fibrinogen to clottable fibrin. OBJECTIVES: We evaluated the relationship of basal peak thrombin generation with the risk of future venous thromboembolism (VTE), and determined whether associations were independent of other coagulation markers. METHODS: The Longitudinal Investigation of Thromboembolism Etiology (LITE) study investigated VTE in two prospective population-based cohorts: the Atherosclerosis Risk in Communities (ARIC) study and the Cardiovascular Health Study (CHS). Peak thrombin generation was measured on stored plasma in a nested case-control sample (434 cases and 1004 controls). Logistic regression was used to estimate the relationship of peak thrombin generation with VTE, adjusted for age, sex, race, center, and body mass index. Mediation was evaluated by additionally adjusting for factor VIII and D-dimer. RESULTS: Relative to the first quartile of peak thrombin generation, the odds ratio (OR) of VTE for those above the median was 1.74 [95% confidence interval (CI) 1.28-2.37]. The association was modestly attenuated by adjustment for FVIII and D-dimer (OR 1.47, 95% CI 1.05-2.05). Associations appeared to be stronger for idiopathic than for secondary VTE. Elevated peak thrombin generation more than added to the VTE risk associated with FV Leiden or low activated partial thromboplastin time. CONCLUSIONS: In this prospective study of two independent cohorts, elevated basal peak thrombin generation was associated with subsequent risk of VTE, independently of established VTE risk factors.
Keywords: Adult; Aged; Biomarkers; Blood Coagulation Factors; Case-Control Studies; Ethnic Groups; Factor VIII; Female; Fibrin Fibrinogen Degradation Products; Humans; Male; Middle Aged; Partial Thromboplastin Time; Prospective Studies; Risk Factors; Thrombin; United States; Venous Thromboembolism

Predicting risk of dementia in older adults: The late-life dementia risk index. - Barnes, D E; Covinsky, K E; Whitmer, R A; Kuller, L H; Lopez, O L; Yaffe, K (Neurology, 2009)
OBJECTIVE: To develop a late-life dementia risk index that can accurately stratify older adults into those with a low, moderate, or high risk of developing dementia within 6 years. METHODS: Subjects were 3,375 participants in the Cardiovascular Health Cognition Study without evidence of dementia at baseline. We used logistic regression to identify those factors most predictive of developing incident dementia within 6 years and developed a point system based on the logistic regression coefficients. RESULTS: Subjects had a mean age of 76 years at baseline; 59% were women and 15% were African American. Fourteen percent (n = 480) developed dementia within 6 years. The final late-life dementia risk index included older age (1-2 points), poor cognitive test performance (2-4 points), body mass index <18.5 (2 points), > or =1 apolipoprotein E epsilon4 alleles (1 point), cerebral MRI findings of white matter disease (1 point) or ventricular enlargement (1 point), internal carotid artery thickening on ultrasound (1 point), history of bypass surgery (1 point), slow physical performance (1 point), and lack of alcohol consumption (1 point) (c statistic, 0.81; 95% confidence interval, 0.79-0.83). Four percent of subjects with low scores developed dementia over 6 years compared with 23% of subjects with moderate scores and 56% of subjects with high scores. CONCLUSIONS: The late-life dementia risk index accurately stratified older adults into those with low, moderate, and high risk of developing dementia. This tool could be used in clinical or research settings to target prevention and intervention strategies toward high-risk individuals.
Keywords: Age Factors; Aged; Aged, 80 and over; Alcohol Drinking; Apolipoprotein E4; Body Mass Index; Carotid Stenosis; Cerebrum; Cognition Disorders; Cohort Studies; Coronary Artery Bypass; Dementia; Female; Genetic Markers; Health Status Indicators; Humans; Logistic Models; Male; Predictive Value of Tests; Risk Assessment; Risk Factors; Risk Reduction Behavior

Prediction of incident stroke events based on retinal vessel caliber: a systematic review and individual-participant meta-analysis. - McGeechan, Kevin; Liew, Gerald; Macaskill, Petra; Irwig, Les; Klein, Ronald; Klein, Barbara E K; Wang, Jie Jin; Mitchell, Paul; Vingerling, Johannes R; de Jong, Paulus T V M; Witteman, Jacqueline C M; Breteler, Monique M B; et al. (Am J Epidemiol, 2009)
The caliber of the retinal vessels has been shown to be associated with stroke events. However, the consistency and magnitude of association, and the changes in predicted risk independent of traditional risk factors, are unclear. To determine the association between retinal vessel caliber and the risk of stroke events, the investigators combined individual data from 20,798 people, who were free of stroke at baseline, in 6 cohort studies identified from a search of the Medline (National Library of Medicine, Bethesda, Maryland) and EMBASE (Elsevier B.V., Amsterdam, the Netherlands) databases. During follow-up of 5-12 years, 945 (4.5%) incident stroke events were recorded. Wider retinal venular caliber predicted stroke (pooled hazard ratio = 1.15, 95% confidence interval: 1.05, 1.25 per 20-micron increase in caliber), but the caliber of retinal arterioles was not associated with stroke (pooled hazard ratio = 1.00, 95% confidence interval: 0.92, 1.08). There was weak evidence of heterogeneity in the hazard ratio for retinal venular caliber, which may be attributable to differences in follow-up strategies across studies. Inclusion of retinal venular caliber in prediction models containing traditional stroke risk factors reassigned 10.1% of people at intermediate risk into different, mostly lower, risk categories.
Keywords: Aged; Fluorescein Angiography; Humans; Middle Aged; Predictive Value of Tests; Proportional Hazards Models; Retinal Artery; Retinal Vein; Retinal Vessels; Risk Factors; Stroke

Prospective study of sleep-disordered breathing and hypertension: the Sleep Heart Health Study. - O'Connor, George T; Caffo, Brian; Newman, Anne B; Quan, Stuart F; Rapoport, David M; Redline, Susan; Resnick, Helaine E; Samet, Jonathan; Shahar, Eyal (Am J Respir Crit Care Med, 2009)
RATIONALE: Cross-sectional epidemiologic studies show an association between sleep-disordered breathing and hypertension, but only one cohort study has examined sleep-disordered breathing as a risk factor for incident hypertension. OBJECTIVES: To examine whether sleep-disordered breathing increases the risk of incident hypertension among persons 40 years of age and older. METHODS: In a prospective cohort study, we analyzed data from 2,470 participants who at baseline did not have hypertension, defined as blood pressure of at least 140/90 mm Hg or taking antihypertensive medication. The apnea-hypopnea index (AHI), the number of apneas plus hypopneas per hour of sleep, was measured by overnight in-home polysomnography. We estimated odds ratios for developing hypertension during 5 years of follow-up according to baseline AHI. MEASUREMENTS AND MAIN RESULTS: The odds ratios for incident hypertension increased with increasing baseline AHI; however, this relationship was attenuated and not statistically significant after adjustment for baseline body-mass index. Although not statistically significant, the observed association between a baseline AHI greater than 30 and future hypertension (odds ratio, 1.51; 95% confidence interval, 0.93-2.47) does not exclude the possibility of a modest association. CONCLUSIONS: Among middle-aged and older persons without hypertension, much of the relationship between AHI and risk of incident hypertension was accounted for by obesity. After adjustment for body mass index, the AHI was not a significant predictor of future hypertension, although a modest influence of an AHI greater than 30 on hypertension could not be excluded.
Keywords: Adult; Blood Pressure; Confidence Intervals; Cross-Sectional Studies; Female; Follow-Up Studies; Humans; Hypertension; Incidence; Male; Middle Aged; Odds Ratio; Polysomnography; Prognosis; Prospective Studies; Risk Factors; Sleep Apnea Syndromes; Time Factors; United States

Rapid decline of kidney function increases cardiovascular risk in the elderly. - Shlipak, Michael G; Katz, Ronit; Kestenbaum, Bryan; Siscovick, David; Fried, Linda; Newman, Anne; Rifkin, Dena; Sarnak, Mark J (J Am Soc Nephrol, 2009)
Chronic kidney disease (CKD), defined at a specific time point, is an important risk factor for cardiovascular disease. Whether the rate of kidney function decline contributes additional cardiovascular risk is unknown. In the Cardiovascular Health Study, we compared the associations of changes in kidney function during the first 7 yr with the incidence of heart failure (HF), myocardial infarction (MI), stroke, and peripheral arterial disease (PAD) during the subsequent 8 yr. We defined a rapid decline in cystatin C-based estimated GFR as >3 ml/min per 1.73 m(2)/yr, on the basis of determination at baseline, year 3, and year 7. Among eligible participants, 1083 (24%) had rapid kidney decline. The incidence of each type of cardiovascular event was significantly higher among patients with rapid decline (all P < 0.001). After multivariate adjustment for demographics, cardiovascular disease risk factors, and baseline kidney function, rapid kidney function decline was significantly associated with HF (adjusted hazard ratio [HR] 1.32; 95% confidence interval [CI] 1.13 to 1.53), MI (HR 1.48; 95% CI 1.21 to 1.83), and PAD (HR 1.67; 95% CI 1.02 to 2.75) but not with stroke (HR 1.19; 95% CI 0.97 to 1.45). The association of rapid decline with each outcome did not differ by the presence or absence of CKD. In conclusion, declining kidney function associates with higher risk for HF, MI, and PAD among patients with or without CKD.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Creatinine; Cystatin C; Female; Glomerular Filtration Rate; Heart Failure; Humans; Longitudinal Studies; Male; Myocardial Infarction; Peripheral Vascular Diseases; Renal Insufficiency, Chronic; Risk Factors; Stroke; Time Factors; United States

Rate of kidney function decline in older adults: a comparison using creatinine and cystatin C. - Shlipak, Michael G; Katz, Ronit; Kestenbaum, Bryan; Fried, Linda F; Newman, Anne B; Siscovick, David S; Stevens, Lesley; Sarnak, Mark J (Am J Nephrol, 2009)
BACKGROUND/AIMS: The aim of this study was to determine the decline in the estimated glomerular filtration rate (eGFR) in elderly persons and to compare estimates based on creatinine and cystatin C. METHODS: In the Cardiovascular Health Study, GFR changes in an elderly cohort were estimated from serum creatinine and cystatin C measured at baseline, year 3 and year 7 in 4,380 participants (age 72 +/- 5 years at entry). Outcomes were mean eGFR decline, incident chronic kidney disease (CKD) and rapid decline in eGFR (annual loss >3 ml/min/1.73 m(2)). RESULTS: Mean annual eGFR loss as estimated from creatinine was 0.4 +/- 3.6 ml/min/1.73 m(2), with 16% of the participants experiencing a rapid decline. Mean eGFR loss as estimated from cystatin C was 1.8 +/- 2.6, with 25% of the participants experiencing a rapid decline (p < 0.001 for both). Among participants without baseline CKD, incident CKD was detected at year 7 in 10% (n = 263) using creatinine and 19% (n = 544) using cystatin C (p < 0.001). Increasing age was the strongest predictor of rapid decline; adjusted odds ratios were 1.38 (1.16-1.65), 1.62 (1.31-1.99) and 2.96 (2.28-3.84) for participants aged 70-74, 75-79 and 80+ at baseline, compared with those aged 65-69. CONCLUSION: In elderly persons, cystatin C estimated substantially larger declines in kidney function than creatinine did. Defining the optimal measurement of kidney function in elderly persons should be a high priority for future research.
Keywords: Age Factors; Aged; Creatinine; Cystatin C; Disease Progression; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Male; Risk Factors

Sibling history of myocardial infarction or stroke and risk of cardiovascular disease in the elderly: the Cardiovascular Health Study. - Yanez, N David; Burke, Gregory L; Manolio, Teri; Gardin, Julius M; Polak, Joseph (Ann Epidemiol, 2009)
PURPOSE: To assess the relationship between sibling history of myocardial infarction (MI) or stroke with cardiovascular disease (CVD) and risk factors in older adults. METHODS: Prospective cohort study of 5,888 older adults participating in the Cardiovascular Health Study (CHS). History of MI and stroke in siblings was obtained by self-report. Participants with positive sibling histories were compared to those with negative histories to determine if prevalent or incident disease (coronary heart disease [CHD], MI, stroke, angina), subclinical CVD (carotid wall thickness, left ventricular mass, hypertension, diabetes, ankle-brachial index), CVD risk factors differed between groups. RESULTS: More than 91% (n = 5,383) of CHS participants reported at least one sibling. Sibling history of MI was associated with increased disease prevalence (CHD, MI, angina) and incidence (CHD, angina). Sibling history of stroke was associated with increased disease prevalence (CHD, angina). Sibling history of either MI or stroke was associated with increased disease prevalence and incidence for CHD, MI and angina, more subclinical disease, and a higher CVD risk profile. CONCLUSIONS: Sibling history of MI and stroke were markers of higher CVD risk status even in older adults. Of clinical importance, participants with positive sibling history have numerous risk factors amenable to intervention.
Keywords: Aged; Atherosclerosis; Female; Genetic Predisposition to Disease; Humans; Incidence; Male; Myocardial Infarction; Odds Ratio; Prevalence; Prospective Studies; Risk Factors; Siblings; Stroke; United States

Sleep-disordered breathing and frailty in the Cardiovascular Health Study Cohort. - Endeshaw, Yohannes W; Unruh, Mark L; Kutner, Michael; Newman, Anne B; Bliwise, Donald L (Am J Epidemiol, 2009)
Sleep-disordered breathing (SDB) is associated with pathophysiology that may influence the development and progression of frailty. Using data collected in 1995-1996, the authors explored the relation between SDB and components of frailty among 1,042 participants of the Cardiovascular Health Study. Diagnosis of SDB was based on the results of overnight polysomnography, and severe SDB was defined as an apnea-hypopnea index of >30 per hour of sleep. Slow walking speed, low grip strength, exhaustion, low physical activity, and unexplained weight loss were referred to as frailty indicator variables. There were 584 (56%) female and 458 (44%) male participants, and the mean age was 77 (standard deviation, 4) years. There was independent association between severe SDB and 1 or more frailty indicator variables (adjusted odds ratio = 4.85, 95% confidence interval: 1.40, 16.78), slow walking speed (adjusted odds ratio = 2.67, 95% confidence interval: 1.04, 6.84), and low grip strength (adjusted odds ratio = 3.29, 95% confidence interval: 1.36, 7.96) among female study participants. The finding of an independent association between SDB and frailty indicator variables among older women could have important implications in interventions aimed at preventing or delaying the progression of frailty.
Keywords: Activities of Daily Living; Aged; Cardiovascular Diseases; Cardiovascular System; Cohort Studies; Confidence Intervals; Exercise Tolerance; Female; Frail Elderly; Hand Strength; Humans; Logistic Models; Male; Mobility Limitation; Models, Statistical; Motor Activity; Muscle Strength; Odds Ratio; Polysomnography; Psychometrics; Risk Factors; Sleep Apnea, Obstructive; Weight Loss

Sleep-disordered breathing and mortality: a prospective cohort study. - Punjabi, Naresh M; Caffo, Brian S; Goodwin, James L; Gottlieb, Daniel J; Newman, Anne B; O'Connor, George T; Rapoport, David M; Redline, Susan; Resnick, Helaine E; Robbins, John A; Shahar, Eyal; Unruh, Mark L; et al. (PLoS Med, 2009)
BACKGROUND: Sleep-disordered breathing is a common condition associated with adverse health outcomes including hypertension and cardiovascular disease. The overall objective of this study was to determine whether sleep-disordered breathing and its sequelae of intermittent hypoxemia and recurrent arousals are associated with mortality in a community sample of adults aged 40 years or older. METHODS AND FINDINGS: We prospectively examined whether sleep-disordered breathing was associated with an increased risk of death from any cause in 6,441 men and women participating in the Sleep Heart Health Study. Sleep-disordered breathing was assessed with the apnea-hypopnea index (AHI) based on an in-home polysomnogram. Survival analysis and proportional hazards regression models were used to calculate hazard ratios for mortality after adjusting for age, sex, race, smoking status, body mass index, and prevalent medical conditions. The average follow-up period for the cohort was 8.2 y during which 1,047 participants (587 men and 460 women) died. Compared to those without sleep-disordered breathing (AHI: <5 events/h), the fully adjusted hazard ratios for all-cause mortality in those with mild (AHI: 5.0-14.9 events/h), moderate (AHI: 15.0-29.9 events/h), and severe (AHI: >or=30.0 events/h) sleep-disordered breathing were 0.93 (95% CI: 0.80-1.08), 1.17 (95% CI: 0.97-1.42), and 1.46 (95% CI: 1.14-1.86), respectively. Stratified analyses by sex and age showed that the increased risk of death associated with severe sleep-disordered breathing was statistically significant in men aged 40-70 y (hazard ratio: 2.09; 95% CI: 1.31-3.33). Measures of sleep-related intermittent hypoxemia, but not sleep fragmentation, were independently associated with all-cause mortality. Coronary artery disease-related mortality associated with sleep-disordered breathing showed a pattern of association similar to all-cause mortality. CONCLUSIONS: Sleep-disordered breathing is associated with all-cause mortality and specifically that due to coronary artery disease, particularly in men aged 40-70 y with severe sleep-disordered breathing. Please see later in the article for the Editors' Summary.
Keywords: Aged; Coronary Artery Disease; Female; Humans; Hypoxia; Male; Middle Aged; Odds Ratio; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Survival Analysis

Spousal suffering and partner's depression and cardiovascular disease: the Cardiovascular Health Study. - Schulz, Richard; Beach, Scott R; Hebert, Randy S; Martire, Lynn M; Monin, Joan K; Tompkins, Connie A; Albert, Steven M (Am J Geriatr Psychiatry, 2009)
OBJECTIVES: To assess the effects of suffering in a spouse on prevalent and incident psychiatric (depression) and physical morbidity (cardiovascular disease [CVD]) in their partner, controlling for known risk factors for depression and CVD. DESIGN: Descriptive longitudinal study. PARTICIPANTS: A total of 1,330 older married couples enrolled in the Cardiovascular Health Study, a large epidemiologic study of the elderly. MEASUREMENTS: Predictor variables were physical, psychological, and existential/spiritual indicators of suffering. Primary outcomes were prevalent and incident depression and CVD. RESULTS: Controlling for known risk factors for depression, the authors found a dose-response relationship between suffering in a spouse and concurrent depression in their partner as well as a relationship between suffering and the partner's future risk for depression. With respect to CVD, and controlling for subclinical CVD at baseline, husbands whose wives reported high levels of suffering also had higher rates of prevalent CVD, but there were no significant associations between wives suffering and husbands incident CVD. There were no associations between husbands' suffering and wives' prevalent or incident CVD. CONCLUSION: Exposure to spousal suffering is an independent and unique source of distress in married couples that contributes to psychiatric and physical morbidity. More attention should be paid to the interpersonal effects of suffering in married couples and to its role in contributing to morbidity.
Keywords: Activities of Daily Living; Aged; Cardiovascular Diseases; Caregivers; Depression; Female; Follow-Up Studies; Humans; Incidence; Logistic Models; Longitudinal Studies; Male; Prevalence; Risk Factors; Socioeconomic Factors; Spouses; Stress, Psychological; Surveys and Questionnaires

Using telephone and informant assessments to estimate missing Modified Mini-Mental State Exam scores and rates of cognitive decline. The cardiovascular health study. - Arnold, Alice M; Newman, Anne B; Dermond, Norma; Haan, Mary; Fitzpatrick, Annette (Neuroepidemiology, 2009)
AIM: To estimate an equivalent to the Modified Mini-Mental State Exam (3MSE), and to compare changes in the 3MSE with and without the estimated scores. METHODS: Comparability study on a subset of 405 participants, aged >or=70 years, from the Cardiovascular Health Study (CHS), a longitudinal study in 4 United States communities. The 3MSE, the Telephone Interview for Cognitive Status (TICS) and the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) were administered within 30 days of one another. Regression models were developed to predict the 3MSE score from the TICS and/or IQCODE, and the predicted values were used to estimate missing 3MSE scores in longitudinal follow-up of 4,274 CHS participants. RESULTS: The TICS explained 67% of the variability in 3MSE scores, with a correlation of 0.82 between predicted and observed scores. The IQCODE alone was not a good estimate of 3MSE score, but improved the model fit when added to the TICS model. Using estimated 3MSE scores classified more participants with low cognition, and rates of decline were greater than when only the observed 3MSE scores were considered. CONCLUSIONS: 3MSE scores can be reliably estimated from the TICS, with or without the IQCODE. Incorporating these estimates captured more cognitive decline in older adults.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; Cognition Disorders; Female; Humans; Interviews as Topic; Longitudinal Studies; Male; Predictive Value of Tests; Psychiatric Status Rating Scales; Regression Analysis; Risk Factors; ROC Curve; United States

Albuminuria and the risk of incident stroke and stroke types in older adults. - Aguilar, M I; O'Meara, E S; Seliger, S; Longstreth, W T; Hart, R G; Pergola, P E; Shlipak, M G; Katz, R; Sarnak, M J; Rifkin, D E (Neurology, 2010)
BACKGROUND: The kidney biomarker that best reflects risk of stroke is unknown. We sought to evaluate the association of stroke with 3 kidney biomarkers: albuminuria, cystatin C, and glomerular filtration rate. METHODS: These 3 biomarkers were determined in 3,287 participants without history of stroke from the Cardiovascular Health Study, a longitudinal cohort study of men and women age 65 years and older from 4 US communities. The biomarkers were albuminuria ascertained using urinary albumin-to-creatinine ratio (UACR) from morning spot urine, creatinine-based estimated glomerular filtration rate (eGFR), and cystatin C. Outcomes were incident stroke (any, ischemic, or hemorrhagic) during follow-up between 1996 and 2006. RESULTS: A total of 390 participants had an incident stroke: 81% ischemic, 12% hemorrhagic, and 7% unclassified. In adjusted Cox regression models, UACR was more strongly related to any stroke, ischemic stroke, and hemorrhagic stroke than eGFR and cystatin C. The hazard ratio (HR) of any stroke comparing the top to bottom quintile of UACR was 2.10 (95% confidence interval [CI] 1.47-3.00), while HR for eGFR was 1.29 (95% CI 0.91-1.84) and for cystatin C was 1.22 (95% CI 0.85-1.74). When considering clinically relevant categories, elevated UACR was associated with increased hazard of any stroke and ischemic stroke regardless of eGFR or cystatin C categories. CONCLUSIONS: UACR was the kidney biomarker most strongly associated with risk of incident stroke. Results in this elderly cohort may not be applicable to younger populations. These findings suggest that measures of glomerular filtration and permeability have differential effects on stroke risk.
Keywords: Aged; Aged, 80 and over; Albuminuria; Community Health Services; Confidence Intervals; Female; Geriatric Assessment; Glomerular Filtration Rate; Humans; Incidence; Longitudinal Studies; Male; Proportional Hazards Models; Retrospective Studies; Risk Factors; Stroke

Albuminuria, impaired kidney function and cardiovascular outcomes or mortality in the elderly. - Rifkin, Dena E; Katz, Ronit; Chonchol, Michel; Fried, Linda F; Cao, Jie; de Boer, Ian H; Siscovick, David S; Shlipak, Michael G; Sarnak, Mark J (Nephrol Dial Transplant, 2010)
BACKGROUND: Kidney disease is a risk factor for mortality and cardiovascular disease in older adults, but the separate and combined effects of albuminuria and cystatin C, a novel marker of glomerular filtration, are not known. METHODS: We examined associations of these markers with mortality and cardiovascular outcomes during a median follow-up of 8.3 years in 3291 older adults in the Cardiovascular Health Study. Kidney disease was assessed using urinary albumin/creatinine ratio (ACR), cystatin C and Modification of Diet in Renal Disease estimated glomerular filtration rate (eGFR). We defined subgroups based on presence of microalbuminuria (MA, ACR > 30 mg/g) and categories of normal kidney function (cystatin C < 1.0 mg/L and eGFR > 60 mL/min/1.73 m(2)); preclinical kidney disease (cystatin C level > 1.0 mg/l but eGFR > 60 mL/min/1.73 m(2)); and chronic kidney disease (CKD) (eGFR < 60 mL/min/1.73 m(2)). Cox proportional hazards models were used to examine associations between these six subgroups and all-cause or cardiovascular mortality, myocardial infarction and heart failure. RESULTS: One thousand one hundred fifty (34.9%) had normal kidney function (12.2% with MA), 1518 (46.1%) had preclinical kidney disease (17.9% with MA) and 622 (18.9%) had CKD (47% with MA). After adjustment, the presence of either preclinical kidney disease or MA was associated with an over 50% increase in mortality risk; the presence of both was associated with a 2.4-fold mortality risk. Those with CKD and MA were at highest risk, with a nearly 4-fold mortality risk. CONCLUSION: Elevated cystatin C and albuminuria are common, identify different subsets of the older population, and are independent, graded risk factors for cardiovascular disease and mortality.
Keywords: Aged; Albuminuria; Cardiovascular Diseases; Creatinine; Cystatin C; Female; Glomerular Filtration Rate; Heart Failure; Humans; Male; Myocardial Infarction; Risk Factors

Association between adiposity in midlife and older age and risk of diabetes in older adults. - Biggs, Mary L; Mukamal, Kenneth J; Luchsinger, José A; Ix, Joachim H; Carnethon, Mercedes R; Newman, Anne B; de Boer, Ian H; Strotmeyer, Elsa S; Mozaffarian, Dariush; Siscovick, David S (JAMA, 2010)
CONTEXT: Adiposity is a well-recognized risk factor for type 2 diabetes among young and middle-aged adults, but the relationship between body composition and type 2 diabetes is not well described among older adults. OBJECTIVE: To examine the relationship between adiposity, changes in adiposity, and risk of incident type 2 diabetes in adults 65 years of age and older. DESIGN, SETTING, AND PARTICIPANTS: Prospective cohort study (1989-2007) of 4193 men and women 65 years of age and older in the Cardiovascular Health Study. Measures of adiposity were derived from anthropometry and bioelectrical impedance data at baseline and anthropometry repeated 3 years later. MAIN OUTCOME MEASURE: Incident diabetes was ascertained based on use of antidiabetic medication or a fasting glucose level of 126 mg/dL or greater. RESULTS: Over median follow-up of 12.4 years (range, 0.9-17.8 years), 339 cases of incident diabetes were ascertained (7.1/1000 person-years). The adjusted hazard ratio (HR) (95% confidence interval [CI]) of type 2 diabetes for participants in the highest quintile of baseline measures compared with those in the lowest was 4.3 (95% CI, 2.9-6.5) for body mass index (BMI [calculated as weight in kilograms divided by height in meters squared]), 3.0 (95% CI, 2.0-4.3) for BMI at 50 years of age, 4.2 (95% CI, 2.8-6.4) for weight, 4.0 (95% CI, 2.6-6.0) for fat mass, 4.2 (95% CI, 2.8-6.2) for waist circumference, 2.4 (95% CI, 1.6-3.5) for waist-hip ratio, and 3.8 (95% CI, 2.6-5.5) for waist-height ratio. However, when stratified by age, participants 75 years of age and older had HRs approximately half as large as those 65 to 74 years of age. Compared with weight-stable participants (+/-2 kg), those who gained the most weight from 50 years of age to baseline (> or = 9 kg), and from baseline to the third follow-up visit (> or = 6 kg), had HRs for type 2 diabetes of 2.8 (95% CI, 1.9-4.3) and 2.0 (95% CI, 1.1-3.7), respectively. Participants with a greater than 10-cm increase in waist size from baseline to the third follow-up visit had an HR of type 2 diabetes of 1.7 (95% CI, 1.1-2.8) compared with those who gained or lost 2 cm or less. CONCLUSION: Among older adults, overall and central adiposity, and weight gain during middle age and after the age of 65 years are associated with risk of diabetes.
Keywords: Adiposity; Age Factors; Aged; Body Mass Index; Diabetes Mellitus, Type 2; Female; Humans; Incidence; Male; Prospective Studies; Risk Factors; United States; Weight Gain

Association between depressive symptoms and fibrosis markers: the Cardiovascular Health Study. - Kop, Willem J; Kuhl, Emily A; Barasch, Eddy; Jenny, Nancy S; Gottlieb, Stephen S; Gottdiener, John S (Brain Behav Immun, 2010)
OBJECTIVE: Fibrosis plays an important role in heart failure (HF) and other diseases that occur more frequently with increasing age. Depression is associated with an increased risk of heart failure and other age-related diseases. This study examined the association between depressive symptoms and fibrosis markers in adults aged 65 years and above. METHODS: Fibrosis markers and depressive symptoms were assessed in 870 participants (age=80.9+/-5.9 yrs, 49% women) using a case-control design based on heart failure status (307 HF patients and 563 age- and sex-matched controls, of whom 284 with CVD risk factors (hypertension, diabetes mellitus, or hypercholesterolemia) and 279 controls without these CVD risk factors). Fibrosis markers were procollagen type I (PIP), type I collagen (CITP), and procollagen type III (PIIINP). Inflammation markers included C-reactive protein, white blood cell counts and fibrinogen. Depression was assessed using the Center for Epidemiological Studies-Depression (CES-D) scale using a previously validated cut-off point for depression (CES-D > or = 8). Covariates included demographic and clinical variables. RESULTS: Depression was associated with higher levels of PIP (median=411.0, inter-quartile range (IQR)=324.4-472.7 ng/mL vs. 387.6, IQR=342.0-512.5 ng/mL, p=0.006) and CITP (4.99, IQR=3.53-6.85 vs. 4.53, IQR=3.26-6.22 microg/L, p=0.024), but not PIIIINP (4.07, IQR=2.75-5.54 microg/L vs. 3.58, IQR=2.71-5.01 microg/L, p=0.29) compared to individuals without depression. Inflammation markers were also elevated in depressed participants (CRP, p=0.014; WBC, p=0.075; fibrinogen, p=0.074), but these inflammation markers did not account for the relationship between depression and fibrosis markers. CONCLUSIONS: Depression is associated with elevated fibrosis markers and may therefore adversely affect heart failure and other age-related diseases in which extra-cellular matrix formation plays a pathophysiological role.
Keywords: Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Collagen Type I; Depression; Electrocardiography; Endomyocardial Fibrosis; Fatigue; Female; Fibrosis; Health Surveys; Heart Failure; Humans; Inflammation Mediators; Male; Multivariate Analysis; Peptide Fragments; Procollagen; Psychiatric Status Rating Scales; Risk Factors; Socioeconomic Factors

Association of Holter-based measures including T-wave alternans with risk of sudden cardiac death in the community-dwelling elderly: the Cardiovascular Health Study. - Stein, Phyllis K; Sanghavi, Devang; Sotoodehnia, Nona; Siscovick, David S; Gottdiener, John (J Electrocardiol, 2010)
BACKGROUND: Sudden cardiac death (SCD) can be the first manifestation of cardiovascular disease. Development of screening methods for higher/lower risk is critical. METHODS: The Cardiovascular Health Study is a population-based study of risk factors for coronary heart disease and stroke those 65 years or older. Forty-nine (of 1649) with usable Holters and in normal sinus rhythm had SCD during follow-up and were matched with 2 controls, alive at the time of death of the case and not experiencing SCD on follow-up. Univariate and multivariate conditional logistic regression determined the association of Holter-based information and SCD. RESULTS: In univariate models, the upper half of ventricular premature contraction (VPC) counts, abnormal heart rate turbulence, decreased normalized low-frequency power, increased T-wave alternans (TWA), and decreased the short-term fractal scaling exponent (DFA(1)) were associated with SCD, but time domain heart rate variability was not. In multivariate models, the upper half of VPC counts (odds ratio [OR], 6.6) and having TWA of 37 muV or greater on channel 2 (OR, 4.8) were independently associated with SCD. Also, the upper half of VPC counts (OR, 6.9) and having a DFA(1) of less than 1.05 (OR, 5.0) were independently associated with SCD. When additive effects were explored, having both higher VPCs and higher TWA was associated with an OR of 8.2 for SCD compared with 2.6 for having either. Also, having both higher VPCs and lower DFA(1) was associated with an OR of 9.6 for SCD compared with 3.1 for having either. CONCLUSIONS: Results support a potential role for 24-hour Holter recordings to identify older adults at increased or lower risk of SCD.
Keywords: Comorbidity; Coronary Artery Disease; Death, Sudden, Cardiac; Electrocardiography, Ambulatory; Female; Humans; Male; Prevalence; Prognosis; Reproducibility of Results; Risk Assessment; Risk Factors; Sensitivity and Specificity; Survival Analysis; Survival Rate; United States; Ventricular Premature Complexes

Associations between renal duplex parameters and adverse cardiovascular events in the elderly: a prospective cohort study. - Pearce, Jeffrey D; Craven, Timothy E; Edwards, Matthew S; Corriere, Matthew A; Crutchley, Teresa A; Fleming, Shawn H; Hansen, Kimberley J (Am J Kidney Dis, 2010)
BACKGROUND: Atherosclerotic renovascular disease is associated with an increased risk of cardiovascular disease (CVD) events. This study examines associations between Doppler-derived parameters from the renal artery and renal parenchyma and all-cause mortality and fatal and nonfatal CVD events in a cohort of elderly Americans. STUDY DESIGN: Cohort study. SETTING: A subset of participants from the Cardiovascular Health Study (CHS). Through an ancillary study, 870 (70% recruitment) Forsyth County, NC, CHS participants consented to undergo renal duplex sonography to define the prevalence of renovascular disease in the elderly, resulting in 726 (36% men; mean age, 77 years) technically adequate complete studies included in this investigation. PREDICTOR: Renal duplex sonography-derived Doppler signals from the main renal arteries and renal parenchyma. Spectral analysis from Doppler-shifted frequencies and angle of insonation were used to estimate renal artery peak systolic and end diastolic velocity (both in meters per second). Color Doppler was used to identify the corticomedullary junction. Using a 3-mm Doppler sample, the parenchymal peak systolic and end diastolic frequency shift (both in kilohertz) were obtained. Resistive index was calculated as (1 - [end diastolic frequency shift/peak systolic frequency shift]) using Doppler samples from the hilar arteries of the left or right kidney with the higher main renal artery peak systolic velocity. OUTCOMES & MEASUREMENTS: Proportional hazard regression analysis was used to determine associations between renal duplex sonography-derived Doppler signals and CVD events and all-cause mortality adjusted for accepted cardiovascular risk factors. Index CVD outcomes were defined as coronary events (angina, myocardial infarction, and coronary artery bypass grafting/percutaneous coronary intervention), cerebrovascular events (stroke or transient ischemic attack), and any CVD event (angina, congestive heart failure, myocardial infarction, stroke, transient ischemic attack, and coronary artery bypass grafting [CABG]/percutaneous transluminal coronary intervention [PTCI]). RESULTS: During follow-up, 221 deaths (31%), 229 CVD events (32%), 122 coronary events (17%), and 92 cerebrovascular events (13%) were observed. Renal duplex sonography-derived Doppler signals from the renal parenchyma were associated independently with all-cause mortality and CVD outcomes. In particular, increased parenchymal end diastolic frequency shift was associated significantly with any CVD event (HR, 0.73; 95% CI, 0.62-0.87; P < 0.001). Marginally significant associations were observed between increases in parenchymal end diastolic frequency shift and decreased risk of death (HR, 0.86; 95% CI, 0.73-1.00; P = 0.06) and decreased risk of cerebrovascular events (HR, 0.78; 95% CI, 0.61-1.01; P = 0.06). Parenchymal end diastolic frequency shift was not significantly predictive of coronary events (HR, 0.84; 95% CI, 0.67-1.06; P = 0.1). LIMITATIONS: CHS participants showed a "healthy cohort" effect that may underestimate the rate of CVD events in the general population. CONCLUSION: Renal duplex sonographic Doppler signals from the renal parenchyma showed significant associations with subsequent CVD events after controlling for other significant risk factors. In particular, a standard deviation increase in parenchymal end diastolic frequency shift was associated with 27% risk reduction in any CVD event.
Keywords: Aged; Cardiovascular Diseases; Cohort Studies; Female; Humans; Kidney Diseases; Male; Renal Artery; Risk Factors; Ultrasonography, Doppler, Duplex

Autonomic nervous system dysfunction and inflammation contribute to the increased cardiovascular mortality risk associated with depression. - Kop, Willem J; Stein, Phyllis K; Tracy, Russell P; Barzilay, Joshua I; Schulz, Richard; Gottdiener, John S (Psychosom Med, 2010)
OBJECTIVE: To investigate prospectively whether autonomic nervous system (ANS) dysfunction and inflammation play a role in the increased cardiovascular disease (CVD)-related mortality risk associated with depression. METHODS: Participants in the Cardiovascular Health Study (n = 907; mean age, 71.3 ± 4.6 years; 59.1% women) were evaluated for ANS indices derived from heart rate variability (HRV) analysis (frequency and time domain HRV, and nonlinear indices, including detrended fluctuation analysis (DFA(1)) and heart rate turbulence). Inflammation markers included C-reactive protein, interleukin-6, fibrinogen, and white blood cell count). Depressive symptoms were assessed, using the 10-item Centers for Epidemiological Studies Depression scale. Cox proportional hazards models were used to investigate the mortality risk associated with depression, ANS, and inflammation markers, adjusting for demographic and clinical covariates. RESULTS: Depression was associated with ANS dysfunction (DFA(1), p = .018), and increased inflammation markers (white blood cell count, p = .012, fibrinogen p = .043) adjusting for covariates. CVD-related mortality occurred in 121 participants during a median follow-up of 13.3 years. Depression was associated with an increased CVD mortality risk (hazard ratio, 1.88; 95% confidence interval, 1.23-2.86). Multivariable analyses showed that depression was an independent predictor of CVD mortality (hazard ratio, 1.72; 95% confidence interval, 1.05-2.83) when adjusting for independent HRV and inflammation predictors (DFA(1), heart rate turbulence, interleukin-6), attenuating the depression-CVD mortality association by 12.7% (p < .001). CONCLUSION: Autonomic dysfunction and inflammation contribute to the increased cardiovascular mortality risk associated with depression, but a large portion of the predictive value of depression remains unexplained by these neuroimmunological measures.
Keywords: Aged; Autonomic Nervous System Diseases; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Cause of Death; Cohort Studies; Comorbidity; Depressive Disorder; Electrocardiography; Female; Follow-Up Studies; Heart Rate; Humans; Inflammation; Interleukin-6; Leukocyte Count; Male; Risk Factors

Body weight dynamics and their association with physical function and mortality in older adults: the Cardiovascular Health Study. - Arnold, Alice M; Newman, Anne B; Cushman, Mary; Ding, Jingzhong; Kritchevsky, Stephen (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: To estimate the associations of weight dynamics with physical functioning and mortality in older adults. METHODS: Longitudinal cohort study using prospectively collected data on weight, physical function, and health status in four U.S. Communities in the Cardiovascular Health Study. Included were 3,278 participants (2,013 women and 541 African Americans), aged 65 or older at enrollment, who had at least five weight measurements. Weight was measured at annual clinic visits between 1992 and 1999, and summary measures of mean weight, coefficient of variation, average annual weight change, and episodes of loss and gain (cycling) were calculated. Participants were followed from 1999 to 2006 for activities of daily living (ADL) difficulty, incident mobility limitations, and mortality. RESULTS: Higher mean weight, weight variability, and weight cycling increased the risk of new onset of ADL difficulties and mobility limitations. After adjustment for risk factors, the hazard ratio (95% confidence interval) for weight cycling for incident ADL impairment was 1.28 (1.12, 1.47), similar to that for several comorbidities in our model, including cancer and diabetes. Lower weight, weight loss, higher variability, and weight cycling were all risk factors for mortality, after adjustment for demographic risk factors, height, self-report health status, and comorbidities. CONCLUSIONS: Variations in weight are important indicators of future physical limitations and mortality in the elderly and may reflect difficulties in maintaining homeostasis throughout older ages. Monitoring the weight of an older person for fluctuations or episodes of both loss and gain is an important aspect of geriatric care.
Keywords: Activities of Daily Living; Age Factors; Aged, 80 and over; Body Weight; Cardiovascular Diseases; Female; Follow-Up Studies; Health Status; Humans; Longevity; Male; Prospective Studies; Risk Factors; Survival Rate; United States

Cancer linked to Alzheimer disease but not vascular dementia. - Roe, C M; Fitzpatrick, A L; Xiong, C; Sieh, W; Kuller, L; Miller, J P; Williams, M M; Kopan, R; Behrens, M I; Morris, J C (Neurology, 2010)
OBJECTIVE: To investigate whether cancer is associated with Alzheimer disease (AD) and vascular dementia (VaD). METHODS: Cox proportional hazards models were used to test associations between prevalent dementia and risk of future cancer hospitalization, and associations between prevalent cancer and risk of subsequent dementia. Participants in the Cardiovascular Health Study-Cognition Substudy, a prospective cohort study, aged 65 years or older (n = 3,020) were followed a mean of 5.4 years for dementia and 8.3 years for cancer. RESULTS: The presence of any AD (pure AD + mixed AD/VaD; hazard ratio [HR] = 0.41, 95% confidence interval [CI] = 0.20-0.84) and pure AD (HR = 0.31, 95% CI = 0.12-0.86) was associated with a reduced risk of future cancer hospitalization, adjusted for demographic factors, smoking, obesity, and physical activity. No significant associations were found between dementia at baseline and rate of cancer hospitalizations for participants with diagnoses of VaD. Prevalent cancer was associated with reduced risk of any AD (HR = 0.72; 95% CI = 0.52-0.997) and pure AD (HR = 0.57; 95% CI = 0.36-0.90) among white subjects after adjustment for demographics, number of APOE epsilon4 alleles, hypertension, diabetes, and coronary heart disease; the opposite association was found among minorities, but the sample size was too small to provide stable estimates. No significant association was found between cancer and subsequent development of VaD. CONCLUSIONS: In white older adults, prevalent Alzheimer disease (AD) was longitudinally associated with a reduced risk of cancer, and a history of cancer was associated with a reduced risk of AD. Together with other work showing associations between cancer and Parkinson disease, these findings suggest the possibility that cancer is linked to neurodegeneration.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Dementia, Vascular; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Hospitalization; Humans; Male; Neoplasms; Nerve Degeneration; Parkinson Disease; Prevalence; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors

Change in circulating adiponectin in advanced old age: determinants and impact on physical function and mortality. The Cardiovascular Health Study All Stars Study. - Kizer, Jorge R; Arnold, Alice M; Strotmeyer, Elsa S; Ives, Diane G; Cushman, Mary; Ding, Jingzhong; Kritchevsky, Stephen B; Chaves, Paulo H M; Hirsch, Calvin H; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: Cross-sectional studies show that adiponectin is higher in older than in younger adults but long-term change in adiponectin, its determinants, and its relationship to functional decline or survival in the elderly population have not been evaluated. METHODS: We investigated predictors of longitudinal change in adiponectin, and the association of this adipokine or its antecedent change with physical deterioration and all-cause mortality in 988 participants in a population-based study who completed examinations in 1996-1997 and 2005-2006, had serial adiponectin measurements and underwent follow-up through June 2009. RESULTS: Adiponectin level rose significantly during follow-up, but the increase was smaller in blacks, was associated with declining weight or fasting glucose and, in men, lower albumin, and was affected by medications. Adiponectin was independently associated with greater physical decline, but the relationship for adiponectin change was driven by concomitant weight decrease. Both adiponectin and its change independently predicted mortality, even after adjustment for weight change. The association for adiponectin and mortality was observed in whites but not in blacks and only for levels in the upper range (hazard ratio = 1.85, 95% confidence interval = 1.36-2.52 per SD ≥ 20 mg/L), whereas that for adiponectin change was linear throughout in both racial groups (hazard ratio = 1.30, 95% confidence interval = 1.10-1.52 per SD). CONCLUSIONS: Adiponectin levels increase over time in long-lived adults and are associated with greater physical disability and mortality. Such increases may occur in response to age-related homeostatic dysregulation. Additional investigation is required to define the underlying mechanisms and whether this represents a marker or causal factor for mortality in this age group.
Keywords: Adiponectin; Age Factors; Aged; Aging; Analysis of Variance; Cardiovascular Diseases; Cause of Death; Chi-Square Distribution; Cohort Studies; Cross-Sectional Studies; Female; Health Status; Humans; Linear Models; Male; Physical Fitness; Proportional Hazards Models; Risk Factors; Sex Factors; Time Factors; United States

Circulating palmitoleic acid and risk of metabolic abnormalities and new-onset diabetes. - Mozaffarian, Dariush; Cao, Haiming; King, Irena B; Lemaitre, Rozenn N; Song, Xiaoling; Siscovick, David S; Hotamisligil, Gökhan S (Am J Clin Nutr, 2010)
BACKGROUND: Animal experiments suggest that circulating palmitoleic acid (cis-16:1n-7) from adipocyte de novo fatty acid synthesis may directly regulate insulin resistance and metabolic dysregulation. OBJECTIVE: We investigated the independent determinants of circulating palmitoleate in free-living humans and whether palmitoleate is related to lower metabolic risk and the incidence of diabetes. DESIGN: In a prospective cohort of 3630 US men and women in the Cardiovascular Health Study, plasma phospholipid fatty acids, anthropometric variables, blood lipids, inflammatory markers, and glucose and insulin concentrations were measured between 1992 and 2006 by using standardized methods. Independent determinants of plasma phospholipid palmitoleate and relations of palmitoleate with metabolic risk factors were investigated by using multivariable-adjusted linear regression. Relations with incident diabetes (296 incident cases) were investigated by using Cox proportional hazards. RESULTS: The mean (± SD) palmitoleate value was 0.49 ± 0.20% (range: 0.11-2.55%) of total fatty acids. Greater body mass index, carbohydrate intake, protein intake, and alcohol use were each independent lifestyle correlates of higher palmitoleate concentrations. In multivariable analyses that adjusted for these factors and other potential confounders, higher palmitoleate concentrations were independently associated with lower LDL cholesterol (P < 0.001), higher HDL cholesterol (P < 0.001), lower total:HDL-cholesterol ratio (P = 0.04), and lower fibrinogen (P < 0.001). However, palmitoleate was also associated with higher triglycerides (P < 0.001) and (in men only) with greater insulin resistance (P < 0.001). Palmitoleate was not significantly associated with incident diabetes. CONCLUSIONS: Adiposity (energy imbalance), carbohydrate consumption, and alcohol use-even within typical ranges-are associated with higher circulating palmitoleate concentrations. Circulating palmitoleate is robustly associated with multiple metabolic risk factors but in mixed directions, perhaps related to divergent lifestyle determinants or endogenous sources (liver, adipose tissue) of fatty acid synthesis.
Keywords: Aged; Aged, 80 and over; Alcohol Drinking; Body Mass Index; Cholesterol; Cholesterol, HDL; Diabetes Mellitus; Diet; Dietary Carbohydrates; Fatty Acids, Monounsaturated; Female; Fibrinogen; Humans; Insulin Resistance; Life Style; Lipids; Male; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors; Triglycerides

Cognition and the risk of hospitalization for serious falls in the elderly: results from the Cardiovascular Health Study. - Welmerink, Diana B; Longstreth, W T; Lyles, Mary F; Fitzpatrick, Annette L (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: Many elderly adults fall every year, sometimes resulting in serious injury and hospitalization. Although impaired cognition is a risk factor for injurious falls, little is known about cognitive decline above the threshold of impairment and risk of serious falls in community-dwelling seniors. METHODS: In total, 702 of 5,356 older adults participating in the Cardiovascular Health Study experienced an injurious fall between 1990 and 2005, as indicated by hospitalization records. General cognition was measured annually with the Modified Mini-Mental State Examination and processing speed with the Digit Symbol Substitution Test. The Cox regression model was used to calculate hazard ratio and 95% confidence interval with and without time-dependent covariates and adjusted for known risk factors. RESULTS: Participants with slightly decreased Digit Symbol Substitution Test scores were at increased risk for a serious fall (hazard ratio = 1.58, 95% confidence interval = 1.15-2.17). The risk continued to increase with each quartile decrease in Digit Symbol Substitution Test score. Participants without prevalent cardiovascular disease at baseline and decreased Modified Mini-Mental State Examination scores (80-89) had a 45% increased risk for a serious fall and those at high risk for dementia (<80) were at twice the risk as participants scoring above 90 (hazard ratio = 2.16, 95% confidence interval = 1.60-2.91). CONCLUSIONS: Both decreased general cognition and decreased processing speed appear to be potential risk factors for serious falls in the elderly. When assessing the risk of serious falls in elderly patients, clinicians should consider usual factors like gait instability and sensory impairment as well as less obvious ones such as cardiovascular disease and cognitive function in nondemented adults.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Chi-Square Distribution; Cognition Disorders; Female; Follow-Up Studies; Geriatric Assessment; Hospitalization; Humans; Male; Mental Status Schedule; Physical Examination; Proportional Hazards Models; Risk Assessment; Risk Factors; Surveys and Questionnaires

Commentary on "Developing a national strategy to prevent dementia: Leon Thal Symposium 2009." Dementia risk indices: A framework for identifying individuals with a high dementia risk. - Barnes, Deborah E; Covinsky, Kenneth E; Whitmer, Rachel A; Kuller, Lewis H; Lopez, Oscar L; Yaffe, Kristine (Alzheimers Dement, 2010)
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Dementia; Diagnosis, Differential; Disability Evaluation; Early Diagnosis; Humans; National Health Programs; Predictive Value of Tests; Prognosis; Risk Assessment; Risk Factors; United States

C-reactive protein concentration and risk of coronary heart disease, stroke, and mortality: an individual participant meta-analysis. - Kaptoge, Stephen; Di Angelantonio, Emanuele; Lowe, Gordon; Pepys, Mark B; Thompson, Simon G; Collins, Rory; Danesh, John (Lancet, 2010)
BACKGROUND: Associations of C-reactive protein (CRP) concentration with risk of major diseases can best be assessed by long-term prospective follow-up of large numbers of people. We assessed the associations of CRP concentration with risk of vascular and non-vascular outcomes under different circumstances. METHODS: We meta-analysed individual records of 160 309 people without a history of vascular disease (ie, 1.31 million person-years at risk, 27 769 fatal or non-fatal disease outcomes) from 54 long-term prospective studies. Within-study regression analyses were adjusted for within-person variation in risk factor levels. RESULTS: Log(e) CRP concentration was linearly associated with several conventional risk factors and inflammatory markers, and nearly log-linearly with the risk of ischaemic vascular disease and non-vascular mortality. Risk ratios (RRs) for coronary heart disease per 1-SD higher log(e) CRP concentration (three-fold higher) were 1.63 (95% CI 1.51-1.76) when initially adjusted for age and sex only, and 1.37 (1.27-1.48) when adjusted further for conventional risk factors; 1.44 (1.32-1.57) and 1.27 (1.15-1.40) for ischaemic stroke; 1.71 (1.53-1.91) and 1.55 (1.37-1.76) for vascular mortality; and 1.55 (1.41-1.69) and 1.54 (1.40-1.68) for non-vascular mortality. RRs were largely unchanged after exclusion of smokers or initial follow-up. After further adjustment for fibrinogen, the corresponding RRs were 1.23 (1.07-1.42) for coronary heart disease; 1.32 (1.18-1.49) for ischaemic stroke; 1.34 (1.18-1.52) for vascular mortality; and 1.34 (1.20-1.50) for non-vascular mortality. INTERPRETATION: CRP concentration has continuous associations with the risk of coronary heart disease, ischaemic stroke, vascular mortality, and death from several cancers and lung disease that are each of broadly similar size. The relevance of CRP to such a range of disorders is unclear. Associations with ischaemic vascular disease depend considerably on conventional risk factors and other markers of inflammation. FUNDING: British Heart Foundation, UK Medical Research Council, BUPA Foundation, and GlaxoSmithKline.
Keywords: Alcohol Drinking; Biomarkers; Blood Pressure; Body Mass Index; C-Reactive Protein; Cholesterol; Coronary Disease; Databases, Factual; Diabetes Mellitus; Female; Fibrinogen; Humans; Interleukin-6; Leukocyte Count; Lung Diseases; Male; Middle Aged; Motor Activity; Neoplasms; Regression Analysis; Risk Assessment; Risk Factors; Serum Albumin; Sex Factors; Smoking; Stroke; Triglycerides

CRP gene variation and risk of community-acquired pneumonia. - Mukamal, Kenneth J; Pai, Jennifer K; O'Meara, Ellen S; Tracy, Russell P; Psaty, Bruce M; Kuller, Lewis H; Newman, Anne B; Yende, Sachin; Curhan, Gary C; Siscovick, David S; Rimm, Eric B (Respirology, 2010)
BACKGROUND AND OBJECTIVE: CRP has several potentially antibacterial effects, and variation in the CRP gene is known to influence CRP levels. Whether this variation influences risk of infection, and hence whether CRP has anti-infective activity in humans, is uncertain. METHODS: We evaluated a series of haplotype-tagging single nucleotide polymorphisms among 5374 individuals in the Cardiovascular Health Study, a cohort of older adults from four communities, who were followed for community-acquired pneumonia for 12-13 years. Secondarily, we evaluated whether these polymorphisms varied among men in the Health Professionals Follow-up Study who self-reported pneumonia on biennial questionnaires. RESULTS: There were 581 (507 white and 74 black) Cardiovascular Health Study participants with incident hospitalizations for pneumonia. No single nucleotide polymorphism or haplotypes were associated with risk among white Cardiovascular Health Study participants. Among black participants, the haplotype tagged by A790T was associated with lower risk of incident pneumonia (hazard ratio 0.5; 95% confidence interval: 0.3-0.9) and with higher CRP levels. In Health Professionals Follow-up Study, a separate haplotype was associated with less frequent self-reported pneumonia but not with circulating CRP levels. CONCLUSIONS: Some genetic variants in CRP may be associated with risk of pneumonia, but haplotypes associated with risk are variably associated with baseline CRP levels. If CRP is a relevant component of innate immunity in humans, the inducibility or tissue-specificity of expression may be at least as important as chronic circulating levels.
Keywords: African Americans; Aged; Aged, 80 and over; Body Mass Index; C-Reactive Protein; Cohort Studies; Community-Acquired Infections; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Pneumonia; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Smoking

Cystatin C and sudden cardiac death risk in the elderly. - Deo, Rajat; Sotoodehnia, Nona; Katz, Ronit; Sarnak, Mark J; Fried, Linda F; Chonchol, Michel; Kestenbaum, Bryan; Psaty, Bruce M; Siscovick, David S; Shlipak, Michael G (Circ Cardiovasc Qual Outcomes, 2010)
BACKGROUND: Recent studies have demonstrated an association between moderate kidney dysfunction and sudden cardiac death in people with cardiovascular disease. METHODS AND RESULTS: The study was a longitudinal analysis among 4465 participants from the Cardiovascular Health Study without prevalent cardiovascular disease at baseline. Cystatin C and creatinine were measured from baseline sera. Sudden cardiac death (SCD) was defined as a sudden pulseless condition from a cardiac origin in a previously stable individual that occurred out of the hospital or in the emergency room. The association between cystatin C tertiles and SCD was determined with multivariate Cox proportional hazards. A similar analysis compared SCD incidence across creatinine-based estimated glomerular filtration rate (eGFR) tertiles. Over a median follow-up of 11.2 years, 91 adjudicated SCD events occurred. The annual incidence of SCD events increased across cystatin C tertiles: 10 events per 10 000 person years in tertile 1, 25 events per 10 000 person years in tertile 2, and 32 events per 10 000 person-years in the highest cystatin C tertile. These associations persisted after multivariate adjustment: hazards ratio=2.72; 95% confidence interval, 1.44 to 5.16 in tertile 2 and hazards ratio=2.67; 95% confidence interval, 1.33 to 5.35 in tertile 3. After multivariate adjustment, the rate of SCD also increased in a linear distribution across creatinine-based eGFR tertiles: 15 events per 10 000 person-years in tertile 1, 22 events per 10 000 person-years in tertile 2, and 27 events per 10 000 person-years in tertile 3. No significant associations, however, remained between creatinine-based eGFR and SCD after multivariable adjustment. CONCLUSIONS: Impaired kidney function, as measured by cystatin C, has an independent association with SCD risk among elderly persons without clinical cardiovascular disease.
Keywords: Age Factors; Aged; Biomarkers; Chi-Square Distribution; Creatinine; Cystatin C; Death, Sudden, Cardiac; Female; Glomerular Filtration Rate; Humans; Incidence; Kidney Diseases; Longitudinal Studies; Male; Proportional Hazards Models; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation

Diabetes and coronary heart disease as risk factors for mortality in older adults. - Carnethon, Mercedes R; Biggs, Mary L; Barzilay, Joshua; Kuller, Lewis H; Mozaffarian, Dariush; Mukamal, Kenneth; Smith, Nicholas L; Siscovick, David (Am J Med, 2010)
BACKGROUND: Type 2 diabetes has been described as a coronary heart disease (CHD) "risk equivalent." We tested whether cardiovascular and all-cause mortality rates were similar between participants with prevalent CHD vs diabetes in an older adult population in whom both glucose disorders and preexisting atherosclerosis are common. METHODS: The Cardiovascular Health Study is a longitudinal study of men and women (n=5784) aged > or =65 years at baseline who were followed from baseline (1989/1992-1993) through 2005 for mortality. Diabetes was defined by fasting plasma glucose > or =7.0 mmol/L or use of diabetes control medications. Prevalent CHD was determined by confirmed history of myocardial infarction, angina, or coronary revascularization. RESULTS: Following multivariable adjustment for other cardiovascular disease risk factors and subclinical atherosclerosis, CHD mortality risk was similar between participants with CHD alone vs diabetes alone (hazard ratio [HR] 1.04, 95% confidence interval [CI], 0.83-1.30). The proportion of mortality attributable to prevalent diabetes (population-attributable risk percent=8.4%) and prevalent CHD (6.7%) was similar in women, but the proportion of mortality attributable to CHD (16.5%) as compared with diabetes (6.4%) was markedly higher in men. Patterns were similar for cardiovascular disease mortality. By contrast, the adjusted relative hazard of total mortality was lower among participants with CHD alone (HR 0.85, 95% CI, 0.75-0.96) as compared with those who had diabetes alone. CONCLUSIONS: Among older adults, diabetes alone confers a risk for cardiovascular mortality similar to that from established clinical CHD. The public health burden of both diabetes and CHD is substantial, particularly among women.
Keywords: Aged; Coronary Disease; Diabetes Mellitus, Type 2; Female; Follow-Up Studies; Humans; Male; Prevalence; Risk Factors; Sex Distribution; Survival Rate; Time Factors; United States

Diabetes mellitus, fasting blood glucose concentration, and risk of vascular disease: a collaborative meta-analysis of 102 prospective studies. - Sarwar, N; Gao, P; Seshasai, S R Kondapally; Gobin, R; Kaptoge, S; Di Angelantonio, E; Ingelsson, E; Lawlor, D A; Selvin, E; Stampfer, M; Stehouwer, C D A; Lewington, S; et al. (Lancet, 2010)
BACKGROUND: Uncertainties persist about the magnitude of associations of diabetes mellitus and fasting glucose concentration with risk of coronary heart disease and major stroke subtypes. We aimed to quantify these associations for a wide range of circumstances. METHODS: We undertook a meta-analysis of individual records of diabetes, fasting blood glucose concentration, and other risk factors in people without initial vascular disease from studies in the Emerging Risk Factors Collaboration. We combined within-study regressions that were adjusted for age, sex, smoking, systolic blood pressure, and body-mass index to calculate hazard ratios (HRs) for vascular disease. FINDINGS: Analyses included data for 698 782 people (52 765 non-fatal or fatal vascular outcomes; 8.49 million person-years at risk) from 102 prospective studies. Adjusted HRs with diabetes were: 2.00 (95% CI 1.83-2.19) for coronary heart disease; 2.27 (1.95-2.65) for ischaemic stroke; 1.56 (1.19-2.05) for haemorrhagic stroke; 1.84 (1.59-2.13) for unclassified stroke; and 1.73 (1.51-1.98) for the aggregate of other vascular deaths. HRs did not change appreciably after further adjustment for lipid, inflammatory, or renal markers. HRs for coronary heart disease were higher in women than in men, at 40-59 years than at 70 years and older, and with fatal than with non-fatal disease. At an adult population-wide prevalence of 10%, diabetes was estimated to account for 11% (10-12%) of vascular deaths. Fasting blood glucose concentration was non-linearly related to vascular risk, with no significant associations between 3.90 mmol/L and 5.59 mmol/L. Compared with fasting blood glucose concentrations of 3.90-5.59 mmol/L, HRs for coronary heart disease were: 1.07 (0.97-1.18) for lower than 3.90 mmol/L; 1.11 (1.04-1.18) for 5.60-6.09 mmol/L; and 1.17 (1.08-1.26) for 6.10-6.99 mmol/L. In people without a history of diabetes, information about fasting blood glucose concentration or impaired fasting glucose status did not significantly improve metrics of vascular disease prediction when added to information about several conventional risk factors. INTERPRETATION: Diabetes confers about a two-fold excess risk for a wide range of vascular diseases, independently from other conventional risk factors. In people without diabetes, fasting blood glucose concentration is modestly and non-linearly associated with risk of vascular disease. FUNDING: British Heart Foundation, UK Medical Research Council, and Pfizer.
Keywords: Adult; Aged; Blood Glucose; Coronary Disease; Diabetes Complications; Diabetes Mellitus; Fasting; Female; Humans; Male; Middle Aged; Risk Factors; Stroke

Dynamic cardiovascular risk assessment in elderly people. The role of repeated N-terminal pro-B-type natriuretic peptide testing. - deFilippi, Christopher R; Christenson, Robert H; Gottdiener, John S; Kop, Willem J; Seliger, Stephen L (J Am Coll Cardiol, 2010)
OBJECTIVES: This study sought to determine whether serial measurement of N-terminal pro-B-type natriuretic peptide (NT-proBNP) in community-dwelling elderly people would provide additional prognostic information to that from traditional risk factors. BACKGROUND: Accurate cardiovascular risk stratification is challenging in elderly people. METHODS: NT-proBNP was measured at baseline and 2 to 3 years later in 2,975 community-dwelling older adults free of heart failure in the longitudinal CHS (Cardiovascular Health Study). This investigation examined the risk of new-onset heart failure (HF) and death from cardiovascular causes associated with baseline NT-proBNP and changes in NT-proBNP levels, adjusting for potential confounders. RESULTS: NT-proBNP levels in the highest quintile (>267.7 pg/ml) were independently associated with greater risks of HF (hazard ratio [HR]: 3.05; 95% confidence interval [CI]: 2.46 to 3.78) and cardiovascular death (HR: 3.02; 95% CI: 2.36 to 3.86) compared with the lowest quintile (<47.5 pg/ml). The inflection point for elevated risk occurred at NT-proBNP 190 pg/ml. Among participants with initially low NT-proBNP (<190 pg/ml), those who developed a >25% increase on follow-up to >190 pg/ml (21%) were at greater adjusted risk of HF (HR: 2.13; 95% CI: 1.68 to 2.71) and cardiovascular death (HR: 1.91; 95% CI: 1.43 to 2.53) compared with those with sustained low levels. Among participants with initially high NT-proBNP, those who developed a >25% increase (40%) were at higher risk of HF (HR: 2.06; 95% CI: 1.56 to 2.72) and cardiovascular death (HR: 1.88; 95% CI: 1.37 to 2.57), whereas those who developed a >25% decrease to <or=190 pg/ml (15%) were at lower risk of HF (HR: 0.58; 95% CI: 0.36 to 0.93) and cardiovascular death (HR: 0.57; 95% CI: 0.32 to 1.01) compared with those with unchanged high values. CONCLUSIONS: NT-proBNP levels independently predict heart failure and cardiovascular death in older adults. NT-proBNP levels frequently change over time, and these fluctuations reflect dynamic changes in cardiovascular risk.
Keywords: Aged; Biomarkers; Female; Heart Failure; Humans; Male; Natriuretic Peptide, Brain; Peptide Fragments; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; United States

Egg consumption and risk of type 2 diabetes in older adults. - Djoussé, Luc; Kamineni, Aruna; Nelson, Tracy L; Carnethon, Mercedes; Mozaffarian, Dariush; Siscovick, David; Mukamal, Kenneth J (Am J Clin Nutr, 2010)
BACKGROUND: Type 2 diabetes (T2D) remains an important public health issue in the United States. There are limited and inconsistent data on the association between egg consumption and fasting glucose or incident diabetes. OBJECTIVES: We assessed the association between egg intake and incident diabetes in older adults. DESIGN: In this prospective study of 3898 men and women from the Cardiovascular Health Study (1989-2007), we assessed egg consumption by using a picture-sorted food questionnaire and ascertained incident T2D annually by using information on hypoglycemic agents and plasma glucose. We used Cox proportional hazards models to estimate adjusted relative risks. RESULTS: During a mean follow-up of 11.3 y, 313 new cases of T2D occurred. Crude incidence rates of T2D were 7.39, 6.83, 7.00, 6.72, and 12.20 per 1000 person-years in people who reported egg consumption of never, <1 egg/mo, 1-3 eggs/mo, 1-4 eggs/wk, and almost daily, respectively. In multivariable-adjusted models, there was no association between egg consumption and increased risk of T2D in either sex and overall. In a secondary analysis, dietary cholesterol was not associated with incident diabetes (P for trend = 0.47). In addition, egg consumption was not associated with clinically meaningful differences in fasting glucose, fasting insulin, or measures of insulin resistance despite small absolute analytic differences that were significant. CONCLUSION: In this cohort of older adults with limited egg intake, there was no association between egg consumption or dietary cholesterol and increased risk of incident T2D.
Keywords: Aged; Blood Glucose; Cholesterol, Dietary; Diabetes Mellitus, Type 2; Diet; Diet Surveys; Eggs; Feeding Behavior; Female; Humans; Insulin; Insulin Resistance; Male; Proportional Hazards Models; Prospective Studies; Risk Factors; Surveys and Questionnaires

European ancestry as a risk factor for atrial fibrillation in African Americans. - Marcus, Gregory M; Alonso, Alvaro; Peralta, Carmen A; Lettre, Guillaume; Vittinghoff, Eric; Lubitz, Steven A; Fox, Ervin R; Levitzky, Yamini S; Mehra, Reena; Kerr, Kathleen F; Deo, Rajat; Sotoodehnia, Nona; et al. (Circulation, 2010)
BACKGROUND: Despite a higher burden of standard atrial fibrillation (AF) risk factors, African Americans have a lower risk of AF than whites. It is unknown whether the higher risk is due to genetic or environmental factors. Because African Americans have varying degrees of European ancestry, we sought to test the hypothesis that European ancestry is an independent risk factor for AF. METHODS AND RESULTS: We studied whites (n=4543) and African Americans (n=822) in the Cardiovascular Health Study (CHS) and whites (n=10 902) and African Americans (n=3517) in the Atherosclerosis Risk in Communities (ARIC) Study (n=3517). Percent European ancestry in African Americans was estimated with 1747 ancestry informative markers from the Illumina custom ITMAT-Broad-CARe array. Among African Americans without baseline AF, 120 of 804 CHS participants and 181 of 3517 ARIC participants developed incident AF. A meta-analysis from the 2 studies revealed that every 10% increase in European ancestry increased the risk of AF by 13% (hazard ratio, 1.13; 95% confidence interval, 1.03 to 1.23; P=0.007). After adjustment for potential confounders, European ancestry remained a predictor of incident AF in each cohort alone, with a combined estimated hazard ratio for each 10% increase in European ancestry of 1.17 (95% confidence interval, 1.07 to 1.29; P=0.001). A second analysis using 3192 ancestry informative markers from a genome-wide Affymetrix 6.0 array in ARIC African Americans yielded similar results. CONCLUSIONS: European ancestry predicted risk of incident AF. Our study suggests that investigating genetic variants contributing to differential AF risk in individuals of African versus European ancestry will be informative.
Keywords: African Americans; Aged; Atrial Fibrillation; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Risk Factors

Fish consumption, bone mineral density, and risk of hip fracture among older adults: the cardiovascular health study. - Virtanen, Jyrki K; Mozaffarian, Dariush; Cauley, Jane A; Mukamal, Kenneth J; Robbins, John; Siscovick, David S (J Bone Miner Res, 2010)
Marine n-3 polyunsaturated fatty acids (PUFAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) may be beneficial for bone health, but few studies have investigated the association with fish consumption. Our aim was to study associations of fish and EPA + DHA consumption with bone mineral density (BMD) and hip fracture risk and determine whether high linoleic acid (LA) intake, the major dietary n-6 PUFA, modifies the associations. The study population consisted of 5045 participants aged 65 years and older from the Cardiovascular Health Study. Data on BMD were available for 1305 participants. Food-frequency questionnaire was used to assess dietary intake, and hip fracture incidence was assessed prospectively by review of hospitalization records. After multivariable adjustment, femoral neck BMD was 0.01 g/cm(2) lower in the highest versus lowest tuna/other-fish intake category (p = .05 for trend). EPA + DHA intake (higher versus lower median of 0.32 g/day) was associated with lower femoral neck BMD (0.66 versus 0.71 g/cm(2), p < .001) among those with LA intake greater than the median 12.1 g/day (p = .03 for interaction). No significant associations were found with total-hip BMD. During mean follow-up of 11.1 years, 505 hip fractures occurred. Fish or EPA + DHA consumption was not significantly associated with fracture incidence [hazard ratio (HR) for extreme categories: HR = 1.23, 95% confidence interval (CI) 0.83-1.84 for tuna/other fish; HR = 1.16, 95% CI 0.91-1.49 for fried fish; and HR = 0.98, 95% CI 0.71-1.36 for EPA + DHA]. High LA intake did not modify these associations. In this large prospective cohort of older adults, fish consumption was associated with very small differences in BMD and had no association with hip fracture risk.
Keywords: Aged; Aged, 80 and over; Animals; Bone Density; Diet; Female; Fishes; Hip Fractures; Humans; Male; Risk Factors; Surveys and Questionnaires

Genetic predictors of medically refractory ulcerative colitis. - Haritunians, Talin; Taylor, Kent D; Targan, Stephan R; Dubinsky, Marla; Ippoliti, Andrew; Kwon, Soonil; Guo, Xiuqing; Melmed, Gil Y; Berel, Dror; Mengesha, Emebet; Psaty, Bruce M; Glazer, Nicole L; et al. (Inflamm Bowel Dis, 2010)
BACKGROUND: Acute severe ulcerative colitis (UC) remains a significant clinical challenge and the ability to predict, at an early stage, those individuals at risk of colectomy for medically refractory UC (MR-UC) would be a major clinical advance. The aim of this study was to use a genome-wide association study (GWAS) in a well-characterized cohort of UC patients to identify genetic variation that contributes to MR-UC. METHODS: A GWAS comparing 324 MR-UC patients with 537 non-MR-UC patients was analyzed using logistic regression and Cox proportional hazards methods. In addition, the MR-UC patients were compared with 2601 healthy controls. RESULTS: MR-UC was associated with more extensive disease (P = 2.7 × 10(-6)) and a positive family history of UC (P = 0.004). A risk score based on the combination of 46 single nucleotide polymorphisms (SNPs) associated with MR-UC explained 48% of the variance for colectomy risk in our cohort. Risk scores divided into quarters showed the risk of colectomy to be 0%, 17%, 74%, and 100% in the four groups. Comparison of the MR-UC subjects with healthy controls confirmed the contribution of the major histocompatibility complex to severe UC (peak association: rs17207986, P = 1.4 × 10(-16)) and provided genome-wide suggestive association at the TNFSF15 (TL1A) locus (peak association: rs11554257, P = 1.4 × 10(-6)). CONCLUSIONS: A SNP-based risk scoring system, identified here by GWAS analyses, may provide a useful adjunct to clinical parameters for predicting the natural history of UC. Furthermore, discovery of genetic processes underlying disease severity may help to identify pathways for novel therapeutic intervention in severe UC.
Keywords: Acute Disease; Adolescent; Adult; Cohort Studies; Colectomy; Colitis, Ulcerative; Female; Genetic Loci; Genome-Wide Association Study; Humans; Major Histocompatibility Complex; Male; Polymorphism, Single Nucleotide; Risk Factors; Severity of Illness Index; Tumor Necrosis Factor Ligand Superfamily Member 15; Young Adult

Genomic variation associated with mortality among adults of European and African ancestry with heart failure: the cohorts for heart and aging research in genomic epidemiology consortium. - Morrison, Alanna C; Felix, Janine F; Cupples, L Adrienne; Glazer, Nicole L; Loehr, Laura R; Dehghan, Abbas; Demissie, Serkalem; Bis, Joshua C; Rosamond, Wayne D; Aulchenko, Yurii S; Wang, Ying A; Haritunians, Talin; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Prognosis and survival are significant concerns for individuals with heart failure (HF). To better understand the pathophysiology of HF prognosis, the association between 2,366,858 single-nucleotide polymorphisms (SNPs) and all-cause mortality was evaluated among individuals with incident HF from 4 community-based prospective cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. METHODS AND RESULTS: Participants were 2526 individuals of European ancestry and 466 individuals of African ancestry who experienced an incident HF event during follow-up in the respective cohorts. Within each study, the association between genetic variants and time to mortality among individuals with HF was assessed by Cox proportional hazards models that included adjustment for sex and age at the time of the HF event. Prospective fixed-effect meta-analyses were conducted for the 4 study populations of European ancestry (N=1645 deaths) and for the 2 populations of African ancestry (N=281 deaths). Genome-wide significance was set at P=5.0x10(-7). Meta-analytic findings among individuals of European ancestry revealed 1 genome-wide significant locus on chromosome 3p22 in an intron of CKLF-like MARVEL transmembrane domain containing 7 (CMTM7, P=3.2x10(-7)). Eight additional loci in individuals of European ancestry and 4 loci in individuals of African ancestry were identified by high-signal SNPs (P<1.0x10(-5)) but did not meet genome-wide significance. CONCLUSIONS: This study identified a novel locus associated with all-cause mortality among individuals of European ancestry with HF. This finding warrants additional investigation, including replication, in other studies of HF.
Keywords: African Americans; Aged; Aged, 80 and over; Chemokines; Cohort Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart Failure; Humans; Introns; Male; MARVEL Domain-Containing Proteins; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Geriatric impairments and disability: the cardiovascular health study. - Chaudhry, Sarwat I; McAvay, Gail; Ning, Yuming; Allore, Heather G; Newman, Anne B; Gill, Thomas M (J Am Geriatr Soc, 2010)
OBJECTIVES: To determine the relative importance of geriatric impairments (in muscle strength, physical capacity, cognition, vision, hearing, and psychological status) and chronic diseases in predicting subsequent functional disability in longitudinal analyses. DESIGN: Longitudinal data from the Cardiovascular Health Study were analyzed. Multivariable Cox hazards regression modeling was used to analyze associations between time-dependent predictors and onset of disability in activities of daily living (ADLs) and mobility. SETTING: Four communities across the United States (Sacramento County, CA; Washington County, MD; Forsyth County, NC; and Allegheny County, PA). PARTICIPANTS: Five thousand eight hundred eighty-eight elderly persons. MEASUREMENTS: Data were collected annually through in-person examinations. RESULTS: ADL disability developed in 15% of participants and mobility disability in 30%. A single multivariable model was developed that included demographics, marital status, body mass index, and number of impairments and diseases. The hazard ratios (HRs) of having one, two, and three or more geriatric impairments (vs none) for the outcome of ADL disability were 2.12 (95% confidence interval (CI)=1.63-2.75), 4.25 (95% CI=3.30-5.48), and 7.87 (95% CI=6.10-10.17), respectively, and for having one, two, and three or more chronic diseases were 1.75 (95% CI=1.41-2.19), 2.45 (95% CI=1.95-3.07), and 3.26 (95% CI=2.53-4.19), respectively. Similarly, the HRs of having one, two, and three or more impairments for the outcome of mobility disability were 1.48 (95% CI=1.27-1.73), 2.08 (95% CI=1.77-2.45), and 3.70 (95% CI=3.09-4.42), respectively, and for having one, two, and three or more diseases were 2.06 (95% CI=1.76-2.40), 2.80 (95% CI=2.36-3.31), and 4.20 (95% CI=3.44-5.14), respectively. CONCLUSION: Number of geriatric impairments was more strongly associated than number of chronic diseases with subsequent ADL disability and nearly as strongly associated with the subsequent mobility disability.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cardiac Rehabilitation; Cardiovascular Diseases; Disabled Persons; Female; Follow-Up Studies; Geriatric Assessment; Health Status; Humans; Male; Morbidity; Retrospective Studies; Risk Factors; Time Factors; United States

Glycosylated hemoglobin and the risk of death and cardiovascular mortality in the elderly. - Chonchol, M; Katz, R; Fried, L F; Sarnak, M J; Siscovick, D S; Newman, A B; Strotmeyer, E S; Bertoni, A; Shlipak, M G (Nutr Metab Cardiovasc Dis, 2010)
BACKGROUND AND AIMS: Glycosylated hemoglobin (HbA(1c)) has been associated with incident cardiovascular disease (CVD), but the findings are inconsistent. We tested the hypothesis that HbA(1c) may be associated with an increased risk of death and cardiovascular mortality in older adults. METHODS AND RESULTS: We evaluated the association between HbA(1c) with all-cause and cardiovascular mortality in 810 participants without a history of diabetes in a sub-study of the Cardiovascular Health Study (CHS), a community cohort study of individuals > or =65 years of age. Glycosylated hemoglobin was measured at baseline and all-cause and cardiovascular mortality was assessed during the follow-up period. The relation between baseline HbA(1c) and death was evaluated with multivariate Cox proportional hazards regression models. After a median follow-up of 14.2 years, 416 deaths were observed. The crude incidence rates of all-cause mortality across HbA(1c) groups were: 4.4% per year, 4.3% per year and 4.6% per year for tertile 1 (< or =5.6%), tertile 2 (5.61-6.20%) and tertile 3 (> or =6.21%), respectively. In unadjusted and fully adjusted analyses, baseline HbA(1c) was not associated with all-cause mortality and cardiovascular mortality (hazard ratio: 1.16 [95% confidence interval 0.91-1.47] and hazard ratio: 1.31 [95% confidence interval 0.90-1.93], respectively for the highest HbA(1c) tertile compared with the lowest). CONCLUSION: These results suggest that HbA(1c) does not significantly predict all-cause and cardiovascular mortality in non-diabetic community-dwelling older adults.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cardiovascular Diseases; Cohort Studies; Disease Progression; Female; Glycated Hemoglobin A; Health Surveys; Heart Failure; Humans; Incidence; Male; Myocardial Infarction; Risk Factors; Statistics as Topic; Stroke; United States

Hip fractures and heart failure: findings from the Cardiovascular Health Study. - Carbone, Laura; Bůzková, Petra; Fink, Howard A; Lee, Jennifer S; Chen, Zhao; Ahmed, Ali; Parashar, Susmita; Robbins, John R (Eur Heart J, 2010)
AIMS: The aim of the study was to find the epidemiology of hip fractures in heart failure. The increasing survival rate for patients with heart failure places them at risk for other diseases of ageing, including osteoporosis. METHODS AND RESULTS: We included 5613 persons from the Cardiovascular Health Study (CHS) with an average of 11.5 year follow-up. We determined incidence rates and hazard ratios (HRs) in persons with heart failure compared with persons without heart failure and mortality hazards following these fractures. Annualized incidence rates for hip fractures were 14 per 1000 person-years in heart failure and 6.8 per 1000 person-years without heart failure. Unadjusted and multivariable adjusted HRs for hip fracture associated with heart failure in men were 1.87 (95% CI 1.2-2.93) and 1.59 (95% CI 0.93-2.72), respectively. Respective HRs for women were 1.75 (95% CI 1.27-2.4) and 1.41 (95% CI 0.98-2.03). Mortality hazard was approximately 2-fold greater in patients with heart failure and hip fracture compared with those having heart failure alone. CONCLUSION: Persons with heart failure are at high risk for hip fractures. However, much of the association between hip fractures and heart failure is explained by shared risk factors. Hip fractures are a substantial contributor to mortality in men and women with heart failure.
Keywords: Aged; Female; Heart Failure; Hip Fractures; Humans; Incidence; Male; Risk Factors; United States

Independent susceptibility markers for atrial fibrillation on chromosome 4q25. - Lubitz, Steven A; Sinner, Moritz F; Lunetta, Kathryn L; Makino, Seiko; Pfeufer, Arne; Rahman, Rosanna; Veltman, Caroline E; Barnard, John; Bis, Joshua C; Danik, Stephan P; Sonni, Akshata; Shea, Marisa A; et al. (Circulation, 2010)
BACKGROUND: Genetic variants on chromosome 4q25 are associated with atrial fibrillation (AF). We sought to determine whether there is more than 1 susceptibility signal at this locus. METHODS AND RESULTS: Thirty-four haplotype-tagging single-nucleotide polymorphisms (SNPs) at the 4q25 locus were genotyped in 790 case and 1177 control subjects from Massachusetts General Hospital and tested for association with AF. We replicated SNPs associated with AF after adjustment for the most significantly associated SNP in 5066 case and 30 661 referent subjects from the German Competence Network for Atrial Fibrillation, Atherosclerosis Risk In Communities Study, Cleveland Clinic Lone AF Study, Cardiovascular Health Study, and Rotterdam Study. All subjects were of European ancestry. A multimarker risk score composed of SNPs that tagged distinct AF susceptibility signals was constructed and tested for association with AF, and all results were subjected to meta-analysis. The previously reported SNP, rs2200733, was most significantly associated with AF (minor allele odds ratio 1.80, 95% confidence interval 1.50 to 2.15, P=1.2 x 10(-20)) in the discovery sample. Adjustment for rs2200733 genotype revealed 2 additional susceptibility signals marked by rs17570669 and rs3853445. A graded risk of AF was observed with an increasing number of AF risk alleles at SNPs that tagged these 3 susceptibility signals. CONCLUSIONS: We identified 2 novel AF susceptibility signals on chromosome 4q25. Consideration of multiple susceptibility signals at chromosome 4q25 identifies individuals with an increased risk of AF and may localize regulatory elements at the locus with biological relevance in the pathogenesis of AF.
Keywords: Aged; Aged, 80 and over; Atrial Fibrillation; Chromosome Mapping; Chromosomes, Human, Pair 4; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Lipoprotein-associated phospholipase A(2) and risk of coronary disease, stroke, and mortality: collaborative analysis of 32 prospective studies. - Thompson, Alexander; Gao, Pei; Orfei, Lia; Watson, Sarah; Di Angelantonio, Emanuele; Kaptoge, Stephen; Ballantyne, Christie; Cannon, Christopher P; Criqui, Michael; Cushman, Mary; Hofman, Albert; Packard, Chris; et al. (Lancet, 2010)
BACKGROUND: Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)), an inflammatory enzyme expressed in atherosclerotic plaques, is a therapeutic target being assessed in trials of vascular disease prevention. We investigated associations of circulating Lp-PLA(2) mass and activity with risk of coronary heart disease, stroke, and mortality under different circumstances. METHODS: With use of individual records from 79 036 participants in 32 prospective studies (yielding 17 722 incident fatal or non-fatal outcomes during 474 976 person-years at risk), we did a meta-analysis of within-study regressions to calculate risk ratios (RRs) per 1 SD higher value of Lp-PLA(2) or other risk factor. The primary outcome was coronary heart disease. FINDINGS: Lp-PLA(2) activity and mass were associated with each other (r=0.51, 95% CI 0.47-0.56) and proatherogenic lipids. We noted roughly log-linear associations of Lp-PLA(2) activity and mass with risk of coronary heart disease and vascular death. RRs, adjusted for conventional risk factors, were: 1.10 (95% CI 1.05-1.16) with Lp-PLA(2) activity and 1.11 (1.07-1.16) with Lp-PLA(2) mass for coronary heart disease; 1.08 (0.97-1.20) and 1.14 (1.02-1.27) for ischaemic stroke; 1.16 (1.09-1.24) and 1.13 (1.05-1.22) for vascular mortality; and 1.10 (1.04-1.17) and 1.10 (1.03-1.18) for non-vascular mortality, respectively. RRs with Lp-PLA(2) did not differ significantly in people with and without initial stable vascular disease, apart from for vascular death with Lp-PLA(2) mass. Adjusted RRs for coronary heart disease were 1.10 (1.02-1.18) with non-HDL cholesterol and 1.10 (1.00-1.21) with systolic blood pressure. INTERPRETATION: Lp-PLA(2) activity and mass each show continuous associations with risk of coronary heart disease, similar in magnitude to that with non-HDL cholesterol or systolic blood pressure in this population. Associations of Lp-PLA(2) mass and activity are not exclusive to vascular outcomes, and the vascular associations depend at least partly on lipids. FUNDING: UK Medical Research Council, GlaxoSmithKline, and British Heart Foundation.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Blood Pressure; Coronary Disease; Female; Humans; Linear Models; Lipids; Male; Middle Aged; Prospective Studies; Risk Assessment; Risk Factors; Stroke; Systole

Multiple genetic loci influence serum urate levels and their relationship with gout and cardiovascular disease risk factors. - Yang, Qiong; Köttgen, Anna; Dehghan, Abbas; Smith, Albert V; Glazer, Nicole L; Chen, Ming-Huei; Chasman, Daniel I; Aspelund, Thor; Eiriksdottir, Gudny; Harris, Tamara B; Launer, Lenore; Nalls, Michael; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Elevated serum urate levels can lead to gout and are associated with cardiovascular risk factors. We performed a genome-wide association study to search for genetic susceptibility loci for serum urate and gout and investigated the causal nature of the associations of serum urate with gout and selected cardiovascular risk factors and coronary heart disease (CHD). METHODS AND RESULTS: Meta-analyses of genome-wide association studies (GWAS) were performed in 5 population-based cohorts of the Cohorts for Heart and Aging Research in Genome Epidemiology consortium for serum urate and gout in 28 283 white participants. The effect of the most significant single-nucleotide polymorphism at all genome-wide significant loci on serum urate was added to create a genetic urate score. Findings were replicated in the Women's Genome Health Study (n=22 054). Single-nucleotide polymorphisms at 8 genetic loci achieved genome-wide significance with serum urate levels (P=4×10(-8) to 2×10(-242) in SLC22A11, GCKR, R3HDM2-INHBC region, RREB1, PDZK1, SLC2A9, ABCG2, and SLC17A1). Only 2 loci (SLC2A9, ABCG2) showed genome-wide significant association with gout. The genetic urate score was strongly associated with serum urate and gout (odds ratio, 12.4 per 100 μmol/L; P=3×10(-39)) but not with blood pressure, glucose, estimated glomerular filtration rate, chronic kidney disease, or CHD. The lack of association between the genetic score and the latter phenotypes also was observed in the Women's Genome Health Study. CONCLUSIONS: The genetic urate score analysis suggested a causal relationship between serum urate and gout but did not provide evidence for one between serum urate and cardiovascular risk factors and CHD.
Keywords: Cardiovascular Diseases; Coronary Disease; Female; Genetic Loci; Genome-Wide Association Study; Gout; Humans; Male; Risk Factors; Uric Acid

New loci associated with kidney function and chronic kidney disease. - Köttgen, Anna; Pattaro, Cristian; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Glazer, Nicole L; Parsa, Afshin; Gao, Xiaoyi; Yang, Qiong; Smith, Albert V; O'Connell, Jeffrey R; Li, Man; et al. (Nat Genet, 2010)
Chronic kidney disease (CKD) is a significant public health problem, and recent genetic studies have identified common CKD susceptibility variants. The CKDGen consortium performed a meta-analysis of genome-wide association data in 67,093 individuals of European ancestry from 20 predominantly population-based studies in order to identify new susceptibility loci for reduced renal function as estimated by serum creatinine (eGFRcrea), serum cystatin c (eGFRcys) and CKD (eGFRcrea < 60 ml/min/1.73 m(2); n = 5,807 individuals with CKD (cases)). Follow-up of the 23 new genome-wide-significant loci (P < 5 x 10(-8)) in 22,982 replication samples identified 13 new loci affecting renal function and CKD (in or near LASS2, GCKR, ALMS1, TFDP2, DAB2, SLC34A1, VEGFA, PRKAG2, PIP5K1B, ATXN2, DACH1, UBE2Q2 and SLC7A9) and 7 loci suspected to affect creatinine production and secretion (CPS1, SLC22A2, TMEM60, WDR37, SLC6A13, WDR72 and BCAS3). These results further our understanding of the biologic mechanisms of kidney function by identifying loci that potentially influence nephrogenesis, podocyte function, angiogenesis, solute transport and metabolic functions of the kidney.
Keywords: Cohort Studies; Creatinine; Cystatin C; Diet; Europe; Genetic Markers; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Models, Genetic; Risk Factors

A novel approach to prediction of mild obstructive sleep disordered breathing in a population-based sample: the Sleep Heart Health Study. - Caffo, Brian; Diener-West, Marie; Punjabi, Naresh M; Samet, Jonathan (Sleep, 2010)
This manuscript considers a data-mining approach for the prediction of mild obstructive sleep disordered breathing, defined as an elevated respiratory disturbance index (RDI), in 5,530 participants in a community-based study, the Sleep Heart Health Study. The prediction algorithm was built using modern ensemble learning algorithms, boosting in specific, which allowed for assessing potential high-dimensional interactions between predictor variables or classifiers. To evaluate the performance of the algorithm, the data were split into training and validation sets for varying thresholds for predicting the probability of a high RDI (≥7 events per hour in the given results). Based on a moderate classification threshold from the boosting algorithm, the estimated post-test odds of a high RDI were 2.20 times higher than the pre-test odds given a positive test, while the corresponding post-test odds were decreased by 52% given a negative test (sensitivity and specificity of 0.66 and 0.70, respectively). In rank order, the following variables had the largest impact on prediction performance: neck circumference, body mass index, age, snoring frequency, waist circumference, and snoring loudness.
Keywords: Age Factors; Aged; Algorithms; Body Mass Index; Cohort Studies; Female; Humans; Male; Middle Aged; Predictive Value of Tests; Risk Factors; ROC Curve; Sleep Apnea Syndromes; Snoring; Waist Circumference

Obesity is linked with lower brain volume in 700 AD and MCI patients. - Ho, April J; Raji, Cyrus A; Becker, James T; Lopez, Oscar L; Kuller, Lewis H; Hua, Xue; Lee, Suh; Hibar, Derrek; Dinov, Ivo D; Stein, Jason L; Jack, Clifford R; Weiner, Michael W; et al. (Neurobiol Aging, 2010)
Obesity is associated with lower brain volumes in cognitively normal elderly subjects, but no study has yet investigated the effects of obesity on brain structure in patients with mild cognitive impairment (MCI) or Alzheimer's disease (AD). To determine if higher body mass index (BMI) is associated with brain volume deficits in cognitively impaired elderly subjects, we analyzed brain magnetic resonance imaging (MRI) scans of 700 MCI or AD patients from 2 different cohorts: the Alzheimer's Disease Neuroimaging Initiative (ADNI) and the Cardiovascular Health Study-Cognition Study (CHS-CS). Tensor-based morphometry (TBM) was used to create 3-dimensional maps of regional tissue excess or deficits in subjects with MCI (ADNI, n = 399; CHS-CS, n = 77) and AD (ADNI, n = 188; CHS, n = 36). In both AD and MCI groups, higher body mass index was associated with brain volume deficits in frontal, temporal, parietal, and occipital lobes; the atrophic pattern was consistent in both ADNI and CHS populations. Cardiovascular risk factors, especially obesity, should be considered as influencing brain structure in those already afflicted by cognitive impairment and dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Body Mass Index; Brain; Cognition Disorders; Cohort Studies; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Obesity; Organ Size; Prospective Studies; Risk Factors

Post hoc Parkinson's disease: identifying an uncommon disease in the Cardiovascular Health Study. - Ton, T G; Jain, S; Boudreau, R; Thacker, E L; Strotmeyer, E S; Newman, A B; Longstreth, W T; Checkoway, H (Neuroepidemiology, 2010)
BACKGROUND: Although ongoing cohort studies offer a unique opportunity to apply existing information collected prospectively to further the scientific understanding of Parkinson's disease (PD), they typically have limited information for clinical diagnosis. METHODS: We used combinations of self-report, International Classification of Diseases - 9th edition codes and antiparkinsonian medications to identify PD in the Cardiovascular Health Study. To determine whether the expected inverse association between smoking and PD is evident using our outcome definitions, we assessed baseline smoking characteristics for various definitions of PD. RESULTS: We identified 60 cases with prevalent PD (1.0%; 95% confidence interval, CI = 0.8-1.3%) and 154 with incident PD by year 14. Clear associations were observed for current smokers (odds ratio, OR = 0.50; 95% CI = 0.26-0.95) and for those who smoked ≥50 pack-years (OR = 0.53; 95% CI = 0.29-0.96). Estimates for smoking were similar when ≥2 data sources were required. Estimates for self-report alone were attenuated towards null. CONCLUSIONS: Using multiple data sources to identify PD represents an alternative method of outcome identification in a cohort that would otherwise not be possible for PD research. Ongoing cohort studies can provide settings in which rapid replication and explorations of new hypotheses for PD are possible.
Keywords: Aged; Aged, 80 and over; Cardiovascular System; Cohort Studies; Female; Health Status; Humans; Incidence; Male; Odds Ratio; Parkinson Disease; Prevalence; Prospective Studies; Risk Factors; Smoking; Surveys and Questionnaires; United States

Secondhand smoke, vascular disease, and dementia incidence: findings from the cardiovascular health cognition study. - Barnes, Deborah E; Haight, Thaddeus J; Mehta, Kala M; Carlson, Michelle C; Kuller, Lewis H; Tager, Ira B (Am J Epidemiol, 2010)
Recent studies have found that smoking is associated with an increased risk of dementia, but the effects of secondhand smoke (SHS) on dementia risk are not known to have previously been studied. The authors used Cox proportional hazards marginal structural models to examine the association between self-reported lifetime household SHS exposure and risk of incident dementia over 6 years among 970 US participants in the Cardiovascular Health Cognition Study (performed from 1991 to 1999) who were never smokers and were free of clinical cardiovascular disease (CVD), dementia, and mild cognitive impairment at baseline. In addition, because prior studies have found that SHS is associated with increased risk of CVD and that CVD is associated with increased risk of dementia, the authors tested for interactions between SHS and measures of clinical and subclinical CVD on dementia risk. Moderate (16-25 years) and high (>25 years) SHS exposure levels were not independently associated with dementia risk; however, subjects with >25 years of SHS exposure and >25% carotid artery stenosis had a 3-fold increase (hazard ratio = 3.00, 95% confidence interval: 1.03, 9.72) in dementia risk compared with subjects with no/low (0-15 years) SHS exposure and < or =25% carotid artery stenosis. High lifetime SHS exposure may increase the risk of dementia in elderly with undiagnosed CVD.
Keywords: Aged; Dementia; Female; Humans; Incidence; Male; Risk Factors; Tobacco Smoke Pollution; Vascular Diseases

Serum albumin and risk of venous thromboembolism. - Folsom, Aaron R; Lutsey, Pamela L; Heckbert, Susan R; Cushman, Mary (Thromb Haemost, 2010)
The incidence of venous thromboembolism (VTE) is increased in patients with albuminuria. However, whether a low serum albumin concentration is associated with increased risk of VTE has been a matter of controversy. We determined the association of serum albumin with VTE incidence in two large, prospective, population-based cohorts: the Atherosclerosis Risk in Communities (ARIC) Study (n = 15,300) and the Cardiovascular Health Study (CHS) (n = 5,400). Validated VTE occurrence (n = 462 in ARIC and n = 174 in CHS) was ascertained during follow-up. In both studies, after adjustment for age, sex, race, use of hormone replacement therapy, estimated glomerular filtration rate, history of cancer, and diabetes, serum albumin tended to be associated inversely with VTE. The adjusted hazard ratio per standard deviation lower albumin was 1.18 (95% confidence interval [CI] = 1.08, 1.31) in ARIC and 1.10 (95% CI = 0.94, 1.29) in CHS. The hazard ratio for albumin below (vs. above) the fifth percentile was 1.28 (95% CI = 0.90, 1.84) in ARIC and 1.80 (95% CI = 1.11, 2.93) in CHS. In conclusion, low serum albumin was a modest marker of increased VTE risk. The observed association likely does not reflect cause and effect, but rather that low serum albumin reflects a hyperinflammatory or hypercoagulable state. Whether this association has clinical relevance warrants further study.
Keywords: Aged; Biomarkers; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Risk Factors; Serum Albumin; United States; Venous Thromboembolism

Subclinical thyroid dysfunction and incident hip fracture in older adults. - Lee, Jennifer S; Bůzková, Petra; Fink, Howard A; Vu, Joseph; Carbone, Laura; Chen, Zhao; Cauley, Jane; Bauer, Doug C; Cappola, Anne R; Robbins, John (Arch Intern Med, 2010)
BACKGROUND: Subclinical thyroid dysfunction is common in older adults and affects bone metabolism, but its effects on fracture risk have not been reported. We sought to determine prospectively whether older men and women with subclinical hyperthyroidism or hypothyroidism have an increased risk of hip fracture. METHODS: Prospective cohort of 3567 US community-dwelling adults, 65 years or older, with biochemically defined subclinical thyroid dysfunction or euthyroidism was enrolled from June 10, 1989, through May 30, 1990, and followed up through 2004. Main outcome measures included incidence and hazard ratios (HRs), with 95% confidence intervals (CIs), of confirmed incident hip fractures for groups with subclinical hypothyroidism, subclinical hyperthyroidism, and euthyroidism as defined at baseline. RESULTS: During 39 952 person-years (median follow-up, 13 years), hip fracture incidence (per 1000 men-years) was 13.65 in men with subclinical hyperthyroidism (n = 29) and 10.27 in men with subclinical hypothyroidism (n = 184), both greater than 5.0 in men with euthyroidism (n = 1159). Men with subclinical hypothyroidism had a multivariable-adjusted HR of 2.31 (95% CI, 1.25-4.27); those with subclinical hyperthyroidism, 3.27 (0.99-11.30). After excluding those with baseline use of thyroid-altering medications, men with endogenous subclinical hyperthyroidism had a higher HR of 4.91 (95% CI, 1.13-21.27), as did men with endogenous subclinical hypothyroidism (2.45, 1.27-4.73). Hip fracture incidence (per 1000 women-years) was 8.93 in women with subclinical hypothyroidism (n = 359) and 10.90 in women with subclinical hyperthyroidism (n = 142) compared with 10.18 in women with euthyroidism (n = 1694). No clear association between subclinical dysfunction and fracture was observed in women. CONCLUSIONS: Older men with subclinical hyperthyroidism or hypothyroidism are at increased risk for hip fracture. Whether treatment of the subclinical syndrome reduces this risk is unknown.
Keywords: Aged; Female; Follow-Up Studies; Hip Fractures; Humans; Hyperthyroidism; Hypothyroidism; Incidence; Male; Multivariate Analysis; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Distribution; Thyrotropin; United States

Trans-palmitoleic acid, metabolic risk factors, and new-onset diabetes in U.S. adults: a cohort study. - Mozaffarian, Dariush; Cao, Haiming; King, Irena B; Lemaitre, Rozenn N; Song, Xiaoling; Siscovick, David S; Hotamisligil, Gökhan S (Ann Intern Med, 2010)
BACKGROUND: Palmitoleic acid (cis-16:1n-7), which is produced by endogenous fat synthesis, has been linked to both beneficial and deleterious metabolic effects, potentially confounded by diverse determinants and tissue sources of endogenous production. Trans-palmitoleate (trans-16:1n-7) represents a distinctly exogenous source of 16:1n-7, unconfounded by endogenous synthesis or its determinants, that may be uniquely informative. OBJECTIVE: To investigate whether circulating trans-palmitoleate is independently related to lower metabolic risk and incident type 2 diabetes. DESIGN: Prospective cohort study from 1992 to 2006. SETTING: Four U.S. communities. PATIENTS: 3736 adults in the Cardiovascular Health Study. MEASUREMENTS: Anthropometric characteristics and levels of plasma phospholipid fatty acids, blood lipids, inflammatory markers, and glucose-insulin measured at baseline in 1992 and dietary habits measured 3 years earlier. Multivariate-adjusted models were used to investigate how demographic, clinical, and lifestyle factors independently related to plasma phospholipid trans-palmitoleate; how trans-palmitoleate related to major metabolic risk factors; and how trans-palmitoleate related to new-onset diabetes (304 incident cases). Findings were validated for metabolic risk factors in an independent cohort of 327 women. RESULTS: In multivariate analyses, whole-fat dairy consumption was most strongly associated with higher trans-palmitoleate levels. Higher trans-palmitoleate levels were associated with slightly lower adiposity and, independently, with higher high-density lipoprotein cholesterol levels (1.9% across quintiles; P = 0.040), lower triglyceride levels (-19.0%; P < 0.001), a lower total cholesterol-HDL cholesterol ratio (-4.7%; P < 0.001), lower C-reactive protein levels (-13.8%; P = 0.05), and lower insulin resistance (-16.7%, P < 0.001). Trans-palmitoleate was also associated with a substantially lower incidence of diabetes, with multivariate hazard ratios of 0.41 (95% CI, 0.27 to 0.64) and 0.38 (CI, 0.24 to 0.62) in quintiles 4 and 5 versus quintile 1 (P for trend < 0.001). Findings were independent of estimated dairy consumption or other fatty acid dairy biomarkers. Protective associations with metabolic risk factors were confirmed in the validation cohort. LIMITATION: Results could be affected by measurement error or residual confounding. CONCLUSION: Circulating trans-palmitoleate is associated with lower insulin resistance, presence of atherogenic dyslipidemia, and incident diabetes. Our findings may explain previously observed metabolic benefits of dairy consumption and support the need for detailed further experimental and clinical investigation. PRIMARY FUNDING SOURCE: National Heart, Lung, and Blood Institute and National Institute of Diabetes and Digestive and Kidney Diseases of the National Institutes of Health.
Keywords: Adiposity; Aged; C-Reactive Protein; Cholesterol; Cholesterol, HDL; Dairy Products; Diabetes Mellitus, Type 2; Fatty Acids, Monounsaturated; Feeding Behavior; Female; Humans; Incidence; Insulin Resistance; Male; Prospective Studies; Risk Factors; Triglycerides; United States

Triglyceride-mediated pathways and coronary disease: collaborative analysis of 101 studies. - Sarwar, Nadeem; Sandhu, Manjinder S; Ricketts, Sally L; Butterworth, Adam S; Di Angelantonio, Emanuele; Boekholdt, S Matthijs; Ouwehand, Willem; Watkins, Hugh; Samani, Nilesh J; Saleheen, Danish; Lawlor, Debbie; Reilly, Muredach P; et al. (Lancet, 2010)
BACKGROUND: Whether triglyceride-mediated pathways are causally relevant to coronary heart disease is uncertain. We studied a genetic variant that regulates triglyceride concentration to help judge likelihood of causality. METHODS: We assessed the -1131T>C (rs662799) promoter polymorphism of the apolipoprotein A5 (APOA5) gene in relation to triglyceride concentration, several other risk factors, and risk of coronary heart disease. We compared disease risk for genetically-raised triglyceride concentration (20,842 patients with coronary heart disease, 35,206 controls) with that recorded for equivalent differences in circulating triglyceride concentration in prospective studies (302 430 participants with no history of cardiovascular disease; 12,785 incident cases of coronary heart disease during 2.79 million person-years at risk). We analysed -1131T>C in 1795 people without a history of cardiovascular disease who had information about lipoprotein concentration and diameter obtained by nuclear magnetic resonance spectroscopy. FINDINGS: The minor allele frequency of -1131T>C was 8% (95% CI 7-9). -1131T>C was not significantly associated with several non-lipid risk factors or LDL cholesterol, and it was modestly associated with lower HDL cholesterol (mean difference per C allele 3.5% [95% CI 2.6-4.6]; 0.053 mmol/L [0.039-0.068]), lower apolipoprotein AI (1.3% [0.3-2.3]; 0.023 g/L [0.005-0.041]), and higher apolipoprotein B (3.2% [1.3-5.1]; 0.027 g/L [0.011-0.043]). By contrast, for every C allele inherited, mean triglyceride concentration was 16.0% (95% CI 12.9-18.7), or 0.25 mmol/L (0.20-0.29), higher (p=4.4x10(-24)). The odds ratio for coronary heart disease was 1.18 (95% CI 1.11-1.26; p=2.6x10(-7)) per C allele, which was concordant with the hazard ratio of 1.10 (95% CI 1.08-1.12) per 16% higher triglyceride concentration recorded in prospective studies. -1131T>C was significantly associated with higher VLDL particle concentration (mean difference per C allele 12.2 nmol/L [95% CI 7.7-16.7]; p=9.3x10(-8)) and smaller HDL particle size (0.14 nm [0.08-0.20]; p=7.0x10(-5)), factors that could mediate the effects of triglyceride. INTERPRETATION: These data are consistent with a causal association between triglyceride-mediated pathways and coronary heart disease. FUNDING: British Heart Foundation, UK Medical Research Council, Novartis.
Keywords: Apolipoprotein A-V; Apolipoproteins; Apolipoproteins A; Coronary Disease; Gene Frequency; Genotype; Humans; Lipids; Lipoproteins, HDL; Lipoproteins, LDL; Lipoproteins, VLDL; Mendelian Randomization Analysis; Particle Size; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Risk Factors; Triglycerides

Utility of sleep stage transitions in assessing sleep continuity. - Laffan, Alison; Caffo, Brian; Swihart, Bruce J; Punjabi, Naresh M (Sleep, 2010)
STUDY OBJECTIVES: Sleep continuity is commonly assessed with polysomnographic measures such as sleep efficiency, sleep stage percentages, and the arousal index. The aim of this study was to examine whether the transition rate between different sleep stages could be used as an index of sleep continuity to predict self-reported sleep quality independent of other commonly used metrics. DESIGN AND SETTING: Analysis of the Sleep Heart Health Study polysomnographic data. PARTICIPANTS: A community cohort. MEASUREMENTS AND RESULTS: Sleep recordings on 5,684 participants were deemed to be of sufficient quality to allow visual scoring of NREM and REM sleep. For each participant, we tabulated the frequency of transitions between wake, NREM sleep, and REM sleep. An overall transition rate was determined as the number of all transitions per hour sleep. Stage-specific transition rates between wake, NREM sleep, and REM sleep were also determined. A 5-point Likert scale was used to assess the subjective experience of restless and light sleep the morning after the sleep study. Multivariable regression models showed that a high overall sleep stage transition rate was associated with restless and light sleep independent of several covariates including total sleep time, percentages of sleep stages, wake time after sleep onset, and the arousal index. Compared to the lowest quartile of the overall transition rate (<7.76 events/h), the odds ratios for restless sleep were 1.27, 1.42, and 1.38, for the second (7.77-10.10 events/h), third (10.11-13.34 events/h), and fourth (≥13.35 events/h) quartiles, respectively. Analysis of stage-specific transition rates showed that transitions between wake and NREM sleep were also independently associated with restless and light sleep. CONCLUSIONS: Assessing overall and stage-specific transition rates provides a complementary approach for assessing sleep continuity. Incorporating such measures, along with conventional metrics, could yield useful insights into the significance of sleep continuity for clinical outcomes.
Keywords: Age Factors; Aged; Arousal; Body Mass Index; Cohort Studies; Female; Humans; Male; Middle Aged; Polysomnography; Predictive Value of Tests; Risk Factors; Sex Factors; Sleep Stages; Sleep Wake Disorders

Validation of an atrial fibrillation risk algorithm in whites and African Americans. - Schnabel, Renate B; Aspelund, Thor; Li, Guo; Sullivan, Lisa M; Suchy-Dicey, Astrid; Harris, Tamara B; Pencina, Michael J; D'Agostino, Ralph B; Levy, Daniel; Kannel, William B; Wang, Thomas J; Kronmal, Richard A; et al. (Arch Intern Med, 2010)
BACKGROUND: We sought to validate a recently published risk algorithm for incident atrial fibrillation (AF) in independent cohorts and other racial groups. METHODS: We evaluated the performance of a Framingham Heart Study (FHS)-derived risk algorithm modified for 5-year incidence of AF in the FHS (n = 4764 participants) and 2 geographically and racially diverse cohorts in the age range 45 to 95 years: AGES (the Age, Gene/Environment Susceptibility-Reykjavik Study) (n = 4238) and CHS (the Cardiovascular Health Study) (n = 5410, of whom 874 [16.2%] were African Americans). The risk algorithm included age, sex, body mass index, systolic blood pressure, electrocardiographic PR interval, hypertension treatment, and heart failure. RESULTS: We found 1359 incident AF events in 100 074 person-years of follow-up. Unadjusted 5-year event rates differed by cohort (AGES, 12.8 cases/1000 person-years; CHS whites, 22.7 cases/1000 person-years; and FHS, 4.5 cases/1000 person-years) and by race (CHS African Americans, 18.4 cases/1000 person-years). The strongest risk factors in all samples were age and heart failure. The relative risks for incident AF associated with risk factors were comparable across cohorts and race groups. After recalibration for baseline incidence and risk factor distribution, the Framingham algorithm, reported in C statistic, performed reasonably well in all samples: AGES, 0.67 (95% confidence interval [CI], 0.64-0.71); CHS whites, 0.68 (95% CI, 0.66-0.70); and CHS African Americans, 0.66 (95% CI, 0.61-0.71). Risk factors combined in the algorithm explained between 47.0% (AGES) and 63.6% (FHS) of the population-attributable risk. CONCLUSIONS: Risk of incident AF in community-dwelling whites and African Americans can be assessed reliably by routinely available and potentially modifiable clinical variables. Seven risk factors accounted for up to 64% of risk.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Aged, 80 and over; Algorithms; Atrial Fibrillation; Blood Pressure; Body Mass Index; Cohort Studies; Electrocardiography; Europe; European Continental Ancestry Group; Female; Follow-Up Studies; Heart Failure; Humans; Hypertension; Incidence; Kaplan-Meier Estimate; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Sex Factors; Systole; United States

Association of coagulation-related and inflammation-related genes and factor VIIc levels with stroke: the Cardiovascular Health Study. - Zakai, N A; Lange, L; Longstreth, W T; O'Meara, E S; Kelley, J L; Fornage, M; Nikerson, D; Cushman, M; Reiner, A P (J Thromb Haemost, 2011)
BACKGROUND: Thrombosis and inflammation are critical in stroke etiology, but associations of coagulation and inflammation gene variants with stroke, and particularly factor VII levels, are inconclusive. OBJECTIVES: To test the associations between 736 single-nucleotide polymorphisms (SNPs) between tagging haplotype patterns of 130 coagulation and inflammation genes, and stroke events, in the 5888 participants aged ≥ 65 years of the observational Cardiovascular Health Study cohort. PATIENTS/METHODS: With 16 years of follow-up, age-adjusted and sex-adjusted Cox models were used to estimate associations of SNPs and FVIIc levels with future stroke. RESULTS: Eight hundred and fifteen strokes occurred in 5255 genotyped participants without baseline stroke (748 ischemic strokes; 586 among whites). Among whites, six SNPs were associated with stroke, with a nominal P-value of < 0.01: rs6046 and rs3093261 (F7); rs4918851 and rs3781387 (HABP2); and rs3138055 (NFKB1A) and rs4648004 (NFKB1). Two of these SNPs were associated with FVIIc levels (units of percentage activity): rs6046 (β = -18.5, P = 2.38 × 10(-83)) and rs3093261 (β = 2.99, P = 3.93 × 10(-6)). After adjustment for age, sex, race, and cardiovascular risk factors, the association of FVIIc quintiles (Q) with stroke were as follows (hazard ratio; 95% confidence interval): Q1, reference; Q2, 1.4, 1.1-1.9); Q3, 1.1, 0.8-1.5); Q4, 1.5, 1.1-2.0); and Q5, 1.6, 1.2-2.2). Associations between SNPs and stroke were independent of FVIIc levels. CONCLUSIONS: Variations in FVII-related genes and FVIIc levels were associated with risk of incident ischemic stroke in this elderly cohort, suggesting a potential causal role for FVII in stroke etiology.
Keywords: Blood Coagulation Factors; Cardiovascular Diseases; Cohort Studies; Factor VII; Female; Humans; Inflammation; Male; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Stroke

The association of genetic variants in interleukin-1 genes with cognition: findings from the cardiovascular health study. - Benke, K S; Carlson, M C; Doan, B Q; Walston, J D; Xue, Q L; Reiner, A P; Fried, L P; Arking, D E; Chakravarti, A; Fallin, M D (Exp Gerontol, 2011)
The inflammatory cytokine interleukin-1 (IL1) potentially plays a role in cognitive deterioration through pathology due to a dementing disorder or due to an aging process. Study of genetic variants in the IL1 genes has been mostly limited to diseases such as Alzheimer's, however, there may be benefit to studying a continuous measure of cognition. Using data from the Cardiovascular Health Study, we evaluate genetic variation in the genes encoding inflammatory agonists IL1A and IL1B, and the antagonist IL1RN, with repeated measures of global cognition (3MS) and processing speed (DSST), using mixed effects models. We found statistically significant minor allele SNP associations with baseline performance on the 3MS in the IL1RN gene for Caucasians (rs17042917: beta=0.47, 95%CI=0.09, 0.85, p=0.016; rs4251961: beta=-0.36, 95%CI=-0.13,-0.60, p=0.0027; rs931471: beta=0.39, 95%CI=0.13, 0.65, p=0.0032), and the IL1B gene for African Americans (rs1143627: beta=1.6, 95%CI=0.48, 2.8; p=0.006 and rs1143634: beta=2.09, 95%CI=0.39, 3.8; p=0.016). Associations appear to be weaker in a subgroup with higher education level. Upon removing those diagnosed with dementia, effect sizes and statistical significance attenuated. These results provide supporting evidence that genetic variants in IL1 genes may be involved in inflammatory-related lowered cognition, that higher education may modify genetic predisposition, and that these associations may be driven by a dementia process.
Keywords: African Americans; Aged; Aged, 80 and over; Cognition; Cognition Disorders; Dementia; Educational Status; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Interleukin 1 Receptor Antagonist Protein; Interleukin-1alpha; Interleukin-1beta; Linkage Disequilibrium; Longitudinal Studies; Male; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; United States

Association of genomic loci from a cardiovascular gene SNP array with fibrinogen levels in European Americans and African-Americans from six cohort studies: the Candidate Gene Association Resource (CARe). - Wassel, Christina L; Lange, Leslie A; Keating, Brendan J; Taylor, Kira C; Johnson, Andrew D; Palmer, Cameron; Ho, Lindsey A; Smith, Nicholas L; Lange, Ethan M; Li, Yun; Yang, Qiong; Delaney, Joseph A; et al. (Blood, 2011)
Several common genomic loci, involving various immunity- and metabolism-related genes, have been associated with plasma fibrinogen in European Americans (EAs). The genetic determinants of fibrinogen in African Americans (AAs) are poorly characterized. Using a vascular gene-centric array in 23,634 EA and 6657 AA participants from 6 studies comprising the Candidate Gene Association Resource project, we examined the association of 47,539 common and lower frequency variants with fibrinogen concentration. We identified a rare Pro265Leu variant in FGB (rs6054) associated with lower fibrinogen. Common fibrinogen gene single nucleotide polymorphisms (FGB rs1800787 and FGG rs2066861) significantly associated with fibrinogen in EAs were prevalent in AAs and showed consistent associations. Several fibrinogen locus single nucleotide polymorphism associated with lower fibrinogen were exclusive to AAs; these include a newly reported association with FGA rs10050257. For IL6R, IL1RN, and NLRP3 inflammatory gene loci, associations with fibrinogen were concordant between EAs and AAs, but not at other loci (CPS1, PCCB, and SCL22A5-IRF1). The association of FGG rs2066861 with fibrinogen differed according to assay type used to measure fibrinogen. Further characterization of common and lower-frequency genetic variants that contribute to interpopulation differences in fibrinogen phenotype may help refine our understanding of the contribution of hemostasis and inflammation to atherothrombotic risk.
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Association of incident cardiovascular disease with progression of sleep-disordered breathing. - Chami, Hassan A; Resnick, Helaine E; Quan, Stuart F; Gottlieb, Daniel J (Circulation, 2011)
BACKGROUND: Prospective data suggest that sleep-disordered breathing enhances risk for incident and recurrent cardiovascular disease (CVD). However, a reverse causal pathway whereby incident CVD causes or worsens sleep-disordered breathing has not been studied. METHODS AND RESULTS: A total of 2721 Sleep Heart Health Study participants (mean age 62, standard deviation=10 years; 57% women; 23% minority) without CVD at baseline underwent 2 polysomnograms 5 years apart. Incident CVD events, including myocardial infarction, congestive heart failure, and stroke, were ascertained and adjudicated. The relation of incident CVD to change in apnea-hypopnea index between the 2 polysomnograms was tested with general linear models, with adjustment for age, sex, race, study center, history of diabetes mellitus, change in body mass index, change in neck circumference, percent sleep time spent in supine sleep, and time between the 2 polysomnograms. Incident CVD occurred in 95 participants between the first and second polysomnograms. Compared with participants without incident CVD, those with incident CVD experienced larger increases in apnea-hypopnea index between polysomnograms. The difference in adjusted mean apnea-hypopnea index change between subjects with and without incident CVD was 2.75 events per hour (95% confidence interval, 0.26 to 5.24; P=0.032). This association persisted after subjects with central sleep apnea were excluded. Compared with participants without incident CVD, participants with incident CVD had greater increases in both mean obstructive and central apnea indices, by 1.75 events per hour (95% confidence interval, 0.10 to 1.75; P=0.04) and by 1.07 events per hour (95% confidence interval, 0.40 to 1.74; P=0.001), respectively. CONCLUSIONS: In a diverse, community-based sample of middle-aged and older adults, incident CVD was associated with worsening sleep-disordered breathing over 5 years.
Keywords: Aged; Cardiovascular Diseases; Disease Progression; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Polysomnography; Risk Factors; Sleep Apnea Syndromes

Association of serum phosphate levels with aortic valve sclerosis and annular calcification: the cardiovascular health study. - Linefsky, Jason P; O'Brien, Kevin D; Katz, Ronit; de Boer, Ian H; Barasch, Eddy; Jenny, Nancy S; Siscovick, David S; Kestenbaum, Bryan (J Am Coll Cardiol, 2011)
OBJECTIVES: This study was conducted to evaluate mineral metabolism markers as potential risk factors for calcific aortic valve disease. BACKGROUND: Mineral metabolism disturbances are common among older people and may contribute to cardiac valvular calcification. Associations of serum mineral metabolism markers with cardiac valvular calcification have not been evaluated in a well-characterized general population of older adults. METHODS: We measured serum levels of phosphate, calcium, parathyroid hormone, and 25-hydroxyvitamin D in 1,938 Cardiovascular Health Study participants who were free of clinical cardiovascular disease and who underwent echocardiographic measurements of aortic valve sclerosis (AVS), mitral annular calcification (MAC), and aortic annular calcification (AAC). We used logistic regression models to estimate associations of mineral metabolism markers with AVS, MAC, and AAC after adjustment for relevant confounding variables, including kidney function. RESULTS: The respective prevalences of AVS, MAC, and AAC were 54%, 39%, and 44%. Each 0.5 mg/dl higher serum phosphate concentration was associated with greater adjusted odds of AVS (odds ratio [OR]: 1.17, 95% confidence interval [CI]: 1.04 to 1.31, p = 0.01), MAC (OR: 1.12, 95% CI: 1.00 to 1.26, p = 0.05), and AAC (OR: 1.12, 95% CI: 0.99 to 1.25, p = 0.05). In contrast, serum calcium, parathyroid hormone, and 25-hydroxyvitamin D concentrations were not associated with aortic or mitral calcification. CONCLUSIONS: Higher serum phosphate levels within the normal range were associated with valvular and annular calcification in a community-based cohort of older adults. Phosphate may be a novel risk factor for calcific aortic valve disease and warrants further study.
Keywords: Aged; Aortic Valve; Calcinosis; Calcium; Female; Heart Valve Diseases; Humans; Male; Mitral Valve; Parathyroid Hormone; Phosphates; Risk Factors; Sclerosis; Vitamin D

Candidate gene association study for diabetic retinopathy in persons with type 2 diabetes: the Candidate gene Association Resource (CARe). - Sobrin, Lucia; Green, Todd; Sim, Xueling; Jensen, Richard A; Tai, E Shyong; Tay, Wan Ting; Wang, Jie Jin; Mitchell, Paul; Sandholm, Niina; Liu, Yiyuan; Hietala, Kustaa; Iyengar, Sudha K; et al. (Invest Ophthalmol Vis Sci, 2011)
PURPOSE: To investigate whether variants in cardiovascular candidate genes, some of which have been previously associated with type 2 diabetes (T2D), diabetic retinopathy (DR), and diabetic nephropathy (DN), are associated with DR in the Candidate gene Association Resource (CARe). METHODS: Persons with T2D who were enrolled in the study (n = 2691) had fundus photography and genotyping of single nucleotide polymorphisms (SNPs) in 2000 candidate genes. Two case definitions were investigated: Early Treatment Diabetic Retinopathy Study (ETDRS) grades ≥ 14 and ≥ 30. The χ² analyses for each CARe cohort were combined by Cochran-Mantel-Haenszel (CMH) pooling of odds ratios (ORs) and corrected for multiple hypothesis testing. Logistic regression was performed with adjustment for other DR risk factors. Results from replication in independent cohorts were analyzed with CMH meta-analysis methods. RESULTS: Among 39 genes previously associated with DR, DN, or T2D, three SNPs in P-selectin (SELP) were associated with DR. The strongest association was to rs6128 (OR = 0.43, P = 0.0001, after Bonferroni correction). These associations remained significant after adjustment for DR risk factors. Among other genes examined, several variants were associated with DR with significant P values, including rs6856425 tagging α-l-iduronidase (IDUA) (P = 2.1 × 10(-5), after Bonferroni correction). However, replication in independent cohorts did not reveal study-wide significant effects. The P values after replication were 0.55 and 0.10 for rs6128 and rs6856425, respectively. CONCLUSIONS: Genes associated with DN, T2D, and vascular diseases do not appear to be consistently associated with DR. A few genetic variants associated with DR, particularly those in SELP and near IDUA, should be investigated in additional DR cohorts.
Keywords: Cardiovascular Diseases; Diabetes Mellitus, Type 2; Diabetic Nephropathies; Diabetic Retinopathy; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Iduronidase; Odds Ratio; P-Selectin; Polymorphism, Single Nucleotide; Risk Factors

Carotid intima-media thickness, electrocardiographic left ventricular hypertrophy, and incidence of intracerebral hemorrhage. - Folsom, Aaron R; Yatsuya, Hiroshi; Psaty, Bruce M; Shahar, Eyal; Longstreth, W T (Stroke, 2011)
BACKGROUND AND PURPOSE: Carotid intima-media thickness and electrocardiographic left ventricular hypertrophy are 2 subclinical cardiovascular disease measures associated with increased risk of total and ischemic strokes. Increased intima-media thickness and electrocardiographic left ventricular hypertrophy also may reflect end-organ hypertensive effects. Information is scant on the associations of these subclinical measures with intracerebral hemorrhage (ICH). We hypothesized that greater carotid intima-media thickness and the presence of electrocardiographic left ventricular hypertrophy would be independently associated with increased ICH incidence. METHODS: Among 18,155 participants initially free of stroke in the Atherosclerosis Risk in Communities Study (ARIC) and the Cardiovascular Health Study (CHS), we assessed carotid intima-media thickness, carotid plaque, and electrocardiographic left ventricular hypertrophy. Over a median of 18 years of follow-up, 162 incident ICH events occurred. RESULTS: After adjustment for other ICH risk factors, carotid intima-media thickness was associated positively with incidence of ICH in both ARIC and CHS. The risk was lowest in study-specific Quartile 1, elevated 1.6- to 2.6-fold in Quartiles 2 to 3, and elevated 2.5 to 3.7-fold in Quartile 4 (P<0.05 for both studies). In CHS, having a carotid plaque was associated with a 2-fold (95% CI, 1.1-3.4) greater ICH risk than having no plaque, but only 1.2-fold (95% CI, 0.76-2.0) greater ICH risk in ARIC. Electrocardiographic left ventricular hypertrophy carried a hazard ratio of ICH of 1.7 (95% CI, 0.77-3.7) in CHS and 2.8 (95% CI, 1.2-6.4) in ARIC. CONCLUSIONS: Our data suggest that people with carotid atherosclerosis and possibly left ventricular hypertrophy are at increased risk not only of ischemic stroke, but also of ICH.
Keywords: Carotid Intima-Media Thickness; Cerebral Hemorrhage; Cohort Studies; Electrocardiography; Female; Follow-Up Studies; Humans; Hypertrophy, Left Ventricular; Incidence; Male; Middle Aged; Prospective Studies; Risk Factors

Chronic kidney disease and the risk of end-stage renal disease versus death. - Dalrymple, Lorien S; Katz, Ronit; Kestenbaum, Bryan; Shlipak, Michael G; Sarnak, Mark J; Stehman-Breen, Catherine; Seliger, Stephen; Siscovick, David; Newman, Anne B; Fried, Linda (J Gen Intern Med, 2011)
BACKGROUND: Among older adults with chronic kidney disease (CKD), the comparative event rates of end-stage renal disease (ESRD) and cause-specific death are unknown. OBJECTIVE: To compare the rates of ESRD, cardiovascular and non-cardiovascular death and examine risk factors for ESRD and all-cause mortality in Cardiovascular Health Study (CHS) participants. DESIGN: The CHS is a longitudinal cohort study of community-dwelling adults aged 65 years and older. PARTICIPANTS: 1,268 participants with an estimated glomerular filtration rate (eGFR) < 60 ml/min per 1.73 m(2) were followed until the time of first event (ESRD, cardiovascular or non-cardiovascular death) or until March 31, 2003. MAIN MEASURES: The outcomes were ESRD, cardiovascular- and non-cardiovascular death. Rates of each event were calculated, and a Cox Proportional Hazards Model with a competing risk framework was used to examine risk factors for ESRD as compared with death. Predictors included age, gender, race, BMI, hypertension, diabetes, cardiovascular disease, heart failure, tobacco use, eGFR, and total cholesterol. KEY RESULTS: During 9.7 years of follow-up, 5% of the cohort progressed to ESRD, and 61% of the cohort died. The rate (per 100 person-years) was 0.5 for ESRD and 6.8 for all-cause mortality (3.0 for cardiovascular and 3.8 for non-cardiovascular mortality). In the competing risk framework, lower eGFR, male gender, African-American race, and higher BMI were associated with an increased risk of ESRD. CONCLUSIONS: Older adults with CKD are 13-fold more likely to die from any cause than progress to ESRD and are 6-fold more likely to die from cardiovascular causes than develop ESRD.
Keywords: Aged; Aged, 80 and over; Cause of Death; Cohort Studies; Female; Follow-Up Studies; Humans; Kidney Failure, Chronic; Longitudinal Studies; Male; Prospective Studies; Renal Insufficiency, Chronic; Risk Factors; Treatment Outcome

Chronic kidney disease in octogenarians. - Shastri, Shani; Tighiouart, Hocine; Katz, Ronit; Rifkin, Dena E; Fried, Linda F; Shlipak, Michael G; Newman, Anne B; Sarnak, Mark J (Clin J Am Soc Nephrol, 2011)
BACKGROUND AND OBJECTIVES: There are limited data on the prevalence of chronic kidney disease (CKD) and its clinical importance in the very old. We examined the prevalence of CKD in octogenarians and its association with cardiovascular disease (CVD). DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: In a cross-sectional analysis of 1028 participants from the Cardiovascular Health Study All Stars, we evaluated association of prevalent CKD with CVD using multivariable logistic regression. CKD was defined as eGFR of <60 ml/min per 1.73 m(2). GFR was estimated using CKD-Epi creatinine and cystatin C equations that incorporate coefficients for age, gender, and race (eGFR(EPI), eGFR(CYS3var)) and the one-variable cystatin C equation (eGFR(CYS1var)). Prevalent CVD was defined as a composite of coronary heart disease, heart failure, and stroke. RESULTS: Mean age was 86 years, 64% were women, 86% were Caucasians, 14% had diabetes, and 39% had prevalent CVD. Mean eGFR(EPI), eGFR(CYS3var), and eGFR(CYS1var) were 59, 62, and 70 ml/min per 1.73 m(2), and 51%, 46%, and 33% had CKD, respectively. Associations of CKD with CVD varied by equation in adjusted analyses: CKD(EPI) (OR, 1.53; 95% CI, 1.15 to 2.03), CKD(CYS3var) (OR, 1.67; 95% CI, 1.25, 2.23), and CKD(CYS1var) (OR, 2.09; 95% CI, 1.55, 2.83). CONCLUSIONS: Reduced eGFR is highly prevalent in octogenarians, and the eGFR(CYS1var) equation yielded the lowest prevalence of CKD but the strongest association with prevalent CVD. Because there are no validated estimating equations in the elderly, estimation of kidney function on the basis of on any one equation should be interpreted with caution.
Keywords: Age Factors; Aged, 80 and over; Analysis of Variance; Biomarkers; Cardiovascular Diseases; Chi-Square Distribution; Chronic Disease; Creatinine; Cross-Sectional Studies; Cystatin C; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Logistic Models; Male; Models, Biological; Prevalence; Risk Assessment; Risk Factors; United States

Circulating long-chain ω-3 fatty acids and incidence of congestive heart failure in older adults: the cardiovascular health study: a cohort study. - Mozaffarian, Dariush; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Spiegelman, Donna; Sacks, Frank M; Rimm, Eric B; Siscovick, David S (Ann Intern Med, 2011)
BACKGROUND: Few previous studies have evaluated associations between long-chain ω-3 fatty acids and incidence of congestive heart failure (CHF), and those that have are typically based on diet questionnaires and yield conflicting results. Circulating fatty acid concentrations provide objective biomarkers of exposure. OBJECTIVE: To determine whether plasma phospholipid concentrations of long-chain ω-3 fatty acids, including eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA), were associated with incident CHF. DESIGN: Prospective cohort study. SETTING: 4 U.S. communities. PATIENTS: 2735 U.S. adults without prevalent heart disease who were enrolled in the Cardiovascular Health Study from 1992 to 2006. MEASUREMENTS: Plasma phospholipid fatty acid concentrations and other cardiovascular risk factors were measured in 1992 by using standardized methods. Relationships with incident CHF (555 cases during 26 490 person-years, adjudicated by using medical records) were assessed by using Cox proportional hazards models. RESULTS: After multivariate adjustment, plasma phospholipid EPA concentration was inversely associated with incident CHF; risk was approximately 50% lower in the highest versus the lowest quartile (hazard ratio [HR], 0.52 [95% CI, 0.38 to 0.72]; P for trend = 0.001). In similar analyses, trends toward lower risk were seen for DPA (HR, 0.76 [CI, 0.56 to 1.04]; P for trend = 0.057) and total long-chain ω-3 fatty acids (HR, 0.70 [CI, 0.49 to 0.99]; P for trend = 0.062) but not for DHA (HR, 0.84 [CI, 0.58 to 1.21]; P for trend = 0.38). In analyses censored to the middle of follow-up (7 years) to minimize exposure misclassification over time, multivariate-adjusted HRs were 0.48 for EPA (CI, 0.32 to 0.71; P for trend = 0.005), 0.61 for DPA (CI, 0.39 to 0.95; P for trend = 0.033), 0.64 for DHA (CI, 0.40 to 1.04; P for trend = 0.057), and 0.51 for total ω-3 fatty acids (CI, 0.32 to 0.80; P for trend = 0.003). LIMITATIONS: Temporal changes in fatty acid concentrations over time may have caused underestimation of associations. Unmeasured or imperfectly measured covariates may have caused residual confounding. CONCLUSION: Circulating individual and total ω-3 fatty acid concentrations are associated with lower incidence of CHF in older adults. PRIMARY FUNDING SOURCE: National Institutes of Health.
Keywords: Aged; Biomarkers; Docosahexaenoic Acids; Eicosapentaenoic Acid; Fatty Acids, Omega-3; Fatty Acids, Unsaturated; Feeding Behavior; Heart Failure; Humans; Incidence; Proportional Hazards Models; Prospective Studies; Risk Factors

Comparing costs associated with risk stratification rules for t-year survival. - Cai, Tianxi; Tian, Lu; Lloyd-Jones, Donald M (Biostatistics, 2011)
Accurate risk prediction is an important step in developing optimal strategies for disease prevention and treatment. Based on the predicted risks, patients can be stratified to different risk categories where each category corresponds to a particular clinical intervention. Incorrect or suboptimal interventions are likely to result in unnecessary financial and medical consequences. It is thus essential to account for the costs associated with the clinical interventions when developing and evaluating risk stratification (RS) rules for clinical use. In this article, we propose to quantify the value of an RS rule based on the total expected cost attributed to incorrect assignment of risk groups due to the rule. We have established the relationship between cost parameters and optimal threshold values used in the stratification rule that minimizes the total expected cost over the entire population of interest. Statistical inference procedures are developed for evaluating and comparing given RS rules and examined through simulation studies. The proposed procedures are illustrated with an example from the Cardiovascular Health Study.
Keywords: Biostatistics; Coronary Disease; Cost-Benefit Analysis; Costs and Cost Analysis; Humans; Models, Statistical; Risk Assessment; Risk Factors; Time Factors

Comparison of characteristics and outcomes of asymptomatic versus symptomatic left ventricular dysfunction in subjects 65 years old or older (from the Cardiovascular Health Study). - Pandhi, Jay; Gottdiener, John S; Bartz, Traci M; Kop, Willem J; Mehra, Mandeep R (Am J Cardiol, 2011)
Although asymptomatic left ventricular (LV) systolic dysfunction (ALVSD) is common, its phenotype and prognosis for incident heart failure (HF) and mortality are insufficiently understood. Echocardiography was done in 5,649 participants in the Cardiovascular Health Study (age 73.0 ± 5.6 years, 57.6% women). The clinical characteristics and cardiovascular risk factors of the participants with ALVSD were compared to those with normal LV function (ejection fraction ≥55%) and with symptomatic LV systolic dysfunction (SLVSD; ejection fraction <55% and a history of HF). Cox proportional hazards models were used to estimate the risk of incident HF and mortality in those with ALVSD. Also, comparisons were made among the LV ejection fraction subgroups using previously validated cutoff values (<45% and 45% to 55%), adjusting for the demographic and cardiovascular disease risk factors. Those with ALVSD (7.3%) were more likely to have cardiovascular risk factors than those in the reference group (without LV dysfunction or symptomatic HF) but less likely than those with SLVSD. The HF rate was 24 occurrences per 1,000 person-years in the reference group and 57 occurrences per 1,000 person-years in those with ALVSD. The HF rate was 45 occurrences per 1,000 person-years for those with ALVSD and mildly impaired LV dysfunction and 93 occurrences per 1,000 person-years for those with ALVSD and moderate to severe LV dysfunction. The mortality rate was 51 deaths per 1,000 person-years in the reference group, 90 deaths per 1,000 person-years in the ALVSD group, and 156 deaths per 1,000 person-years in the SLVSD group. Adjusting for covariates, compared to the reference group, ALVSD was associated with an increased risk of incident HF (hazard ratio 1.60, 95% confidence interval 1.35 to 1.91), cardiovascular mortality (hazard ratio 2.13, 95% confidence interval 1.81 to 2.51), and all-cause mortality (hazard ratio 1.46, 95% confidence interval 1.29 to 1.64). In conclusion, subjects with ALVSD are characterized by a greater prevalence of cardiovascular risk factors and co-morbidities than those with normal LV function and without HF. However, the prevalence is lower than in those with SLVSD. Patients with ALVSD are at an increased risk of HF and mortality, particularly those with greater severity of LV impairment.
Keywords: Aged; Female; Heart Failure, Systolic; Humans; Male; Prevalence; Risk Factors; Ultrasonography; Ventricular Dysfunction, Left

The contribution of a 9p21.3 variant, a KIF6 variant, and C-reactive protein to predicting risk of myocardial infarction in a prospective study. - Shiffman, Dov; O'Meara, Ellen S; Rowland, Charles M; Louie, Judy Z; Cushman, Mary; Tracy, Russell P; Devlin, James J; Psaty, Bruce M (BMC Cardiovasc Disord, 2011)
BACKGROUND: Genetic risk factors might improve prediction of coronary events. Several variants at chromosome 9p21.3 have been widely reported to be associated with coronary heart disease (CHD) in prospective and case-control studies. A variant of KIF6 (719Arg) has also been reported to be associated with increased risk of CHD in large prospective studies, but not in case-control studies. We asked whether the addition of genetic information (the 9p21.3 or KIF6 variants) or a well-established non-genetic risk factor (C-reactive protein [CRP]) can improve risk prediction by the Framingham Risk Score (FRS) in the Cardiovascular Health Study (CHS)--a prospective observational study of risk factors for cardiovascular disease among > 5,000 participants aged 65 or older. METHODS: Improvement of risk prediction was assessed by change in the area under the receiver-operator characteristic curve (AUC) and by net reclassification improvement (NRI). RESULTS: Among white participants the FRS was improved by addition of KIF6 719Arg carrier status among men as assessed by the AUC (from 0.581 to 0.596, P = 0.03) but not by NRI (NRI = 0.027, P = 0.32). Adding both CRP and 719Arg carrier status to the FRS improved risk prediction by the AUC (0.608, P = 0.02) and NRI (0.093, P = 0.008) in men, but not women (P ≥ 0.24). CONCLUSIONS: While none of these risk markers individually or in combination improved risk prediction among women, a combination of KIF6 719Arg carrier status and CRP levels modestly improved risk prediction among white men; although this improvement is not significant after multiple-testing correction. These observations should be investigated in other prospective studies.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; C-Reactive Protein; Case-Control Studies; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Variation; Humans; Kinesin; Male; Myocardial Infarction; Predictive Value of Tests; Prospective Studies; Risk Factors

Cystatin C identifies chronic kidney disease patients at higher risk for complications. - Peralta, Carmen A; Katz, Ronit; Sarnak, Mark J; Ix, Joachim; Fried, Linda F; de Boer, Ian; Palmas, Walter; Siscovick, David; Levey, Andrew S; Shlipak, Michael G (J Am Soc Nephrol, 2011)
Although cystatin C is a stronger predictor of clinical outcomes associated with CKD than creatinine, the clinical role for cystatin C is unclear. We included 11,909 participants from the Multi-Ethnic Study of Atherosclerosis (MESA) and the Cardiovascular Health Study (CHS) and assessed risks for death, cardiovascular events, heart failure, and ESRD among persons categorized into mutually exclusive groups on the basis of the biomarkers that supported a diagnosis of CKD (eGFR <60 ml/min per 1.73 m(2)): creatinine only, cystatin C only, both, or neither. We used CKD-EPI equations to estimate GFR from these biomarkers. In MESA, 9% had CKD by the creatinine-based equation only, 2% had CKD by the cystatin C-based equation only, and 4% had CKD by both equations; in CHS, these percentages were 12, 4, and 13%, respectively. Compared with those without CKD, the adjusted hazard ratios (HR) for mortality in MESA were: 0.80 (95% CI 0.50 to 1.26) for CKD by creatinine only; 3.23 (95% CI 1.84 to 5.67) for CKD by cystatin C only; and 1.93 (95% CI 1.27 to 2.92) for CKD by both; in CHS, the adjusted HR were 1.09 (95% CI 0.98 to 1.21), 1.78 (95% CI 1.53 to 2.08), and 1.74 (95% CI 1.58 to 1.93), respectively. The pattern was similar for cardiovascular disease (CVD), heart failure, and kidney failure outcomes. In conclusion, among adults diagnosed with CKD using the creatinine-based CKD-EPI equation, the adverse prognosis is limited to the subset who also have CKD according to the cystatin C-based equation. Cystatin C may have a role in identifying persons with CKD who have the highest risk for complications.
Keywords: Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Chronic Disease; Creatinine; Cystatin C; Disease Progression; Female; Glomerular Filtration Rate; Heart Failure; Humans; Kidney Diseases; Kidney Failure, Chronic; Male; Middle Aged; Predictive Value of Tests; Retrospective Studies; Risk Factors

Electrocardiographic and clinical predictors separating atherosclerotic sudden cardiac death from incident coronary heart disease. - Soliman, Elsayed Z; Prineas, Ronald J; Case, L Douglas; Russell, Gregory; Rosamond, Wayne; Rea, Thomas; Sotoodehnia, Nona; Post, Wendy S; Siscovick, David; Psaty, Bruce M; Burke, Gregory L (Heart, 2011)
OBJECTIVE: To identify specific ECG and clinical predictors that separate atherosclerotic sudden cardiac death (SCD) from incident coronary heart disease (CHD) (non-fatal events and non-sudden death) in the combined cohorts of the Atherosclerosis Risk in Communities study and the Cardiovascular Health Study. METHODS: This analysis included 18,497 participants (58% females, 24% black individuals, mean age 58 years) who were initially free of clinical CHD. A competing risk analysis was conducted to examine the prognostic significance of baseline clinical characteristics and an extensive electronic database of ECG measurements for prediction of 229 cases of SCD as a first event versus 2297 incident CHD cases (2122 non-fatal events and 175 non-sudden death) that occurred during a median follow-up time of 13 years in the Cardiovascular Health Study and 14 years in the Atherosclerosis Risk in Communities study. RESULTS: After adjusting for common CHD risk factors, a number of clinical characteristics and ECG measurements were independently predictive of SCD and CHD. However, the risk of SCD versus incident CHD was significantly different for race/ethnicity, hypertension, body mass index (BMI), heart rate, QTc, abnormally inverted T wave in any ECG lead group and level of ST elevation in V2. Black race/ethnicity (compared to non-black) was predictive of high SCD risk but less risk of incident CHD (p value for differences in the risk (HR) for SCD versus CHD <0.0001). Hypertension, increased heart rate, prolongation of QTc and abnormally inverted T wave were stronger predictors of high SCD risk compared to CHD (p value=0.0460, 0.0398, 0.0158 and 0.0265, respectively). BMI was not predictive of incident CHD but was predictive of high SCD risk in a quadratic fashion (p value=0.0220). On the other hand, elevated ST height as measured at the J point and that measured at 60 ms after the J point in V2 were not predictive of SCD but were predictive of high incident CHD risk (p value=0.0251 and 0.0155, respectively). CONCLUSIONS: SCD and CHD have many risk factors in common. Hypertension, race/ethnicity, BMI, heart rate, QTc, abnormally inverted T wave in any ECG lead group and level of ST elevation in V2 have the potential to separate between the risks of SCD and CHD. These results need to be validated in another cohort.
Keywords: Adult; Aged; Aged, 80 and over; Body Mass Index; Continental Population Groups; Coronary Disease; Death, Sudden, Cardiac; Electrocardiography; Ethnic Groups; Female; Heart Rate; Humans; Hypertension; Male; Middle Aged; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Adjustment; Risk Factors; Time Factors; United States

Fatty acids in the de novo lipogenesis pathway and risk of coronary heart disease: the Cardiovascular Health Study. - Wu, Jason H Y; Lemaitre, Rozenn N; Imamura, Fumiaki; King, Irena B; Song, Xiaoling; Spiegelman, Donna; Siscovick, David S; Mozaffarian, Dariush (Am J Clin Nutr, 2011)
BACKGROUND: De novo lipogenesis (DNL) is an endogenous pathway whereby carbohydrates and proteins are converted to fatty acids. DNL could affect coronary heart disease (CHD) or sudden cardiac arrest (SCA) via generation of specific fatty acids. Whether these fatty acids are prospectively associated with SCA or other CHD events is unknown. OBJECTIVE: The objective was to investigate the relations of 4 fatty acids in the DNL pathway-palmitic acid (16:0), palmitoleic acid (16:1n-7), 7-hexadecenoic acid (16:1n-9), and cis-vaccenic acid (18:1n-7)-with incident CHD, including fatal CHD, nonfatal myocardial infarction (NFMI), and SCA. DESIGN: A community-based prospective study was conducted in 2890 men and women aged ≥65 y, who were free of known CHD at baseline and who were followed from 1992 to 2006. Cardiovascular disease risk factors and plasma phospholipid fatty acids were measured at baseline by using standardized methods. Incident CHD was ascertained prospectively and was centrally adjudicated by using medical records. Risk was assessed by using multivariable-adjusted Cox proportional hazards. RESULTS: During 29,835 person-years of follow-up, 631 CHD and 71 SCA events occurred. Both 18:1n-7 and 16:1n-9 were associated with a higher risk of SCA [multivariable-adjusted hazard ratio (95% CI) for the interquintile range: 7.63 (2.58, 22.6) for 18:1n-7 and 2.30 (1.16, 4.55) for 16:1n-9] but not of total CHD, fatal CHD, or NFMI. In secondary analyses censored to mid-follow-up (7 y) to minimize the effects of changes in concentrations over time, 16:1n-9 was also associated with a significantly higher risk of total CHD (2.11; 1.76, 2.54), including a higher risk of CHD death, NFMI, and SCA; 16:0 and 16:1n-7 were not associated with clinical CHD outcomes. CONCLUSION: Higher plasma phospholipid 18:1n-7 and 16:1n-9 concentrations were prospectively associated with an elevated risk of SCA but not of other CHD events, except in secondary analyses.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Coronary Disease; Death, Sudden, Cardiac; Diet; Fatty Acids; Female; Humans; Lipogenesis; Male; Phospholipids; Proportional Hazards Models; Prospective Studies; Risk Factors

Gender differences between the Minnesota code and Novacode electrocardiographic prognostication of coronary heart disease in the cardiovascular health study. - Zhang, Zhu-Ming; Prineas, Ronald J; Case, Doug; Psaty, Bruce M; Suzuki, Takeki; Burke, Gregory L (Am J Cardiol, 2011)
The Minnesota Code (MC) and Novacode (Nova) are the most widely used electrocardiographic (ECG) classification systems. The comparative strengths of their classifications for Q- and ST-T-wave abnormalities in predicting coronary heart disease (CHD) events and total mortality have not been evaluated separately by gender. We studied standard 12-lead electrocardiograms at rest from 4,988 participants in the Cardiovascular Health Study. Average age at baseline was 73 years, 60% of participants were women 85% were white, and 22% had a history of cardiovascular disease or presence of ECG myocardial infarction by MC or Nova. Starting in 1989 with an average 17-year follow-up, 65% of participants died and 33% had incident CHD in a cohort free of cardiovascular disease at baseline. Of these, electrocardiograms with major Q-wave or major ST-T abnormalities by MC or Nova predicted increased risk for CHD events and total mortality with no significant differences in predictability between men and women. The study also found that women had fewer major Q-wave changes but more major ST-T abnormalities than men. However, there were no gender differences in predicting CHD events and total mortality. In conclusion, ECG classification systems for myocardial infarction/ischemia abnormalities by MC or Nova are valuable and useful for men and women in clinical trials and epidemiologic studies.
Keywords: Aged; Coronary Disease; Electrocardiography; Female; Humans; Incidence; Male; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Sex Factors; United States

Genetic determinants of lipid traits in diverse populations from the population architecture using genomics and epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Taylor, Kira; Schumacher, Fredrick R; Hindorff, Lucia A; Ambite, José L; Anderson, Garnet; Best, Lyle G; Brown-Gentry, Kristin; Bůzková, Petra; Carlson, Christopher S; Cochran, Barbara; et al. (PLoS Genet, 2011)
For the past five years, genome-wide association studies (GWAS) have identified hundreds of common variants associated with human diseases and traits, including high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels. Approximately 95 loci associated with lipid levels have been identified primarily among populations of European ancestry. The Population Architecture using Genomics and Epidemiology (PAGE) study was established in 2008 to characterize GWAS-identified variants in diverse population-based studies. We genotyped 49 GWAS-identified SNPs associated with one or more lipid traits in at least two PAGE studies and across six racial/ethnic groups. We performed a meta-analysis testing for SNP associations with fasting HDL-C, LDL-C, and ln(TG) levels in self-identified European American (~20,000), African American (~9,000), American Indian (~6,000), Mexican American/Hispanic (~2,500), Japanese/East Asian (~690), and Pacific Islander/Native Hawaiian (~175) adults, regardless of lipid-lowering medication use. We replicated 55 of 60 (92%) SNP associations tested in European Americans at p<0.05. Despite sufficient power, we were unable to replicate ABCA1 rs4149268 and rs1883025, CETP rs1864163, and TTC39B rs471364 previously associated with HDL-C and MAFB rs6102059 previously associated with LDL-C. Based on significance (p<0.05) and consistent direction of effect, a majority of replicated genotype-phentoype associations for HDL-C, LDL-C, and ln(TG) in European Americans generalized to African Americans (48%, 61%, and 57%), American Indians (45%, 64%, and 77%), and Mexican Americans/Hispanics (57%, 56%, and 86%). Overall, 16 associations generalized across all three populations. For the associations that did not generalize, differences in effect sizes, allele frequencies, and linkage disequilibrium offer clues to the next generation of association studies for these traits.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Continental Population Groups; Female; Gene Frequency; Genetics, Population; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Lipid Metabolism; Lipoproteins, HDL; Lipoproteins, LDL; Male; Middle Aged; Molecular Epidemiology; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Triglycerides; Young Adult

High blood pressure accelerates gait slowing in well-functioning older adults over 18-years of follow-up. - Rosano, Caterina; Longstreth, William T; Boudreau, Robert; Taylor, Christopher A; Du, Yan; Kuller, Lewis H; Newman, Anne B (J Am Geriatr Soc, 2011)
OBJECTIVES: To examine whether the association between hypertension and decline in gait speed is significant in well-functioning older adults and whether other health-related factors, such as brain, kidney, and heart function, can explain it. DESIGN: Longitudinal cohort study. SETTING: Cardiovascular Health Study. PARTICIPANTS: Of 2,733 potential participants with a brain magnetic resonance imaging (MRI) scan, measures of mobility and systolic blood pressure (BP), no self-reported disability in 1992 to 1994 (baseline), and with at least 1 follow-up gait speed measurement through 1997 to 1999, 643 (aged 73.6, 57% female, 15% black) who had received a second MRI in 1997 to 1999 and an additional gait speed measure in 2005 to 2006 were included. MEASUREMENTS: Mixed models with random slopes and intercepts were adjusted for age, race, and sex. Main explanatory factors included white matter hyperintensity progression, baseline cystatin-C, and left cardiac ventricular mass. Incidence of stroke and dementia, BP trajectories, and intake of antihypertensive medications during follow-up were tested as other potential explanatory factors. RESULTS: Higher systolic BP was associated with faster rate of gait speed decline in this selected group of 643 participants, and results were similar in the parent cohort (N = 2,733). Participants with high BP (n = 293) had a significantly faster rate of gait speed decline than those with baseline BP less than 140/90 mmHg and no history of hypertension (n = 350). Rates were similar for those with history of hypertension who were uncontrolled (n = 110) or controlled (n = 87) at baseline and for those who were newly diagnosed (n = 96) at baseline. Adjustment for explanatory factors or for other covariates (education, prevalent cardiovascular disease, physical activity, vision, mood, cognition, muscle strength, body mass index, osteoporosis) did not change the results. CONCLUSION: High BP accelerates gait slowing in well-functioning older adults over a long period of time, even for those who control their BP or develop hypertension later in life. Health-related measurements did not explain these associations. Future studies to investigate the mechanisms linking hypertension to slowing gait in older adults are warranted.
Keywords: Aged; Antihypertensive Agents; Comorbidity; Female; Follow-Up Studies; Gait; Geriatric Assessment; Humans; Hypertension; Longitudinal Studies; Magnetic Resonance Imaging; Male; Risk Factors; Statistics, Nonparametric

Hypertension, white matter hyperintensities, and concurrent impairments in mobility, cognition, and mood: the Cardiovascular Health Study. - Hajjar, Ihab; Quach, Lien; Yang, Frances; Chaves, Paulo H M; Newman, Anne B; Mukamal, Kenneth; Longstreth, Will; Inzitari, Marco; Lipsitz, Lewis A (Circulation, 2011)
BACKGROUND: Our objective was to investigate the association between hypertension and concurrent impairments in mobility, cognition, and mood; the role of brain white matter hyperintensities in mediating this association; and the impact of these impairments on disability and mortality in elderly hypertensive individuals. METHODS AND RESULTS: -Blood pressure, gait speed, digit symbol substitution test, and the Center for Epidemiological Studies Depression Scale were measured yearly (1992-1999) on 4700 participants in the Cardiovascular Health Study (age: 74.7, 58% women, 17% blacks, 68% hypertension, 3600 had brain magnetic resonance imaging in 1992-1993, survival data 1992-2005). Using latent profile analysis at baseline, we found that 498 (11%) subjects had concurrent impairments and 3086 (66%) were intact on all 3 measures. Between 1992 and 1999, 651 (21%) became impaired in all 3 domains. Hypertensive individuals were more likely to be impaired at baseline (odds ratio 1.23, 95% confidence interval 1.04 to 1.42, P=0.01) and become impaired during the follow-up (hazard ratio=1.3, 95% confidence interval 1.02 to 1.66, P=0.037). A greater degree of white matter hyperintensities was associated with impairments in the 3 domains (P=0.007) and mediated the association with hypertension (P=0.19 for hypertension after adjusting for white matter hyperintensities in the model, 21% hazard ratio change). Impairments in the 3 domains increased subsequent disability with hypertension (P<0.0001). Hypertension mortality also was increased in those impaired (compared with unimpaired hypertensive individuals: HR=1.10, 95% confidence interval 1.04 to 1.17, P=0.004). CONCLUSIONS: Hypertension increases the risk of concurrent impairments in mobility, cognition, and mood, which increases disability and mortality. This association is mediated in part by microvascular brain injury.
Keywords: Aged; Aged, 80 and over; Brain; Cognition Disorders; Female; Humans; Hypertension; Kaplan-Meier Estimate; Longitudinal Studies; Magnetic Resonance Imaging; Male; Microcirculation; Mobility Limitation; Mood Disorders; Nerve Fibers, Myelinated; Retrospective Studies; Risk Factors

Kidney function decline in the elderly: impact of lipoprotein-associated phospholipase A(2). - Peralta, Carmen A; Katz, Ronit; Shlipak, Michael; Dubin, Ruth; DeBoer, Ian; Jenny, Nancy; Fitzpatrick, Annette; Koro, Carol; Kestenbaum, Bryan; Ix, Joachim; Sarnak, Mark; Cushman, Mary (Am J Nephrol, 2011)
BACKGROUND: Whether lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) levels are associated with kidney function decline has not been well studied. METHODS: We investigated associations of Lp-PLA(2) antigen and activity with kidney function decline and rapid decline over 5.7 years in the Cardiovascular Health Study (n = 4,359). We estimated kidney function by cystatin C (eGFRcys) in repeated measures, and defined rapid decline as ≥3 ml/min/1.73 m(2) per year. We stratified by baseline preserved GFR (≥60 ml/min/1.73 m(2)). RESULTS: Mean age was 72 ± 5 years. Average eGFRcys decline was -1.79 ml/min/1.73 m(2) (SD = 2.60) per year. Among persons with preserved GFR, compared to the lowest quartile of Lp-PLA(2) antigen, eGFRcys decline was faster among persons in the second, β -0.31 (95% CI -0.52, -0.10), third -0.19 (-0.41, 0.02) and fourth quartiles -0.26 (-0.48, -0.04) after full adjustment. Persons in the highest quartile of Lp-PLA(2) antigen had increased odds of rapid decline 1.34 (1.03, 1.75), compared to the lowest. There was no significant association between levels of Lp-PLA(2) activity and eGFRcys decline or rapid decline. Associations were not statistically significant among persons with low eGFR (<60 ml/min/1.73 m(2)) at baseline. CONCLUSION: Higher levels of Lp-PLA(2) antigen but not activity were significantly associated with faster rates of kidney function decline. These findings may suggest a novel vascular pathway for kidney disease progression.
Keywords: Aged; Cardiovascular Diseases; Creatinine; Cystatin C; Disease Progression; Female; Geriatrics; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Male; Middle Aged; Phospholipases A2; Risk Factors; Treatment Outcome

Large-scale candidate gene analysis in whites and African Americans identifies IL6R polymorphism in relation to atrial fibrillation: the National Heart, Lung, and Blood Institute's Candidate Gene Association Resource (CARe) project. - Schnabel, Renate B; Kerr, Kathleen F; Lubitz, Steven A; Alkylbekova, Ermeg L; Marcus, Gregory M; Sinner, Moritz F; Magnani, Jared W; Wolf, Philip A; Deo, Rajat; Lloyd-Jones, Donald M; Lunetta, Kathryn L; Mehra, Reena; et al. (Circ Cardiovasc Genet, 2011)
BACKGROUND: The genetic background of atrial fibrillation (AF) in whites and African Americans is largely unknown. Genes in cardiovascular pathways have not been systematically investigated. METHODS AND RESULTS: We examined a panel of approximately 50,000 common single-nucleotide polymorphisms (SNPs) in 2095 cardiovascular candidate genes and AF in 3 cohorts with participants of European (n=18,524; 2260 cases) or African American descent (n=3662; 263 cases) in the National Heart, Lung, and Blood Institute's Candidate Gene Association Resource. Results in whites were followed up in the German Competence Network for AF (n=906, 468 cases). The top result was assessed in relation to incident ischemic stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology Stroke Consortium (n=19,602 whites, 1544 incident strokes). SNP rs4845625 in the IL6R gene was associated with AF (relative risk [RR] C allele, 0.90; 95% confidence interval [CI], 0.85-0.95; P=0.0005) in whites but did not reach statistical significance in African Americans (RR, 0.86; 95% CI, 0.72-1.03; P=0.09). The results were comparable in the German AF Network replication, (RR, 0.71; 95% CI, 0.57-0.89; P=0.003). No association between rs4845625 and stroke was observed in whites. The known chromosome 4 locus near PITX2 in whites also was associated with AF in African Americans (rs4611994; hazard ratio, 1.40; 95% CI, 1.16-1.69; P=0.0005). CONCLUSIONS: In a community-based cohort meta-analysis, we identified genetic association in IL6R with AF in whites. Additionally, we demonstrated that the chromosome 4 locus known from recent genome-wide association studies in whites is associated with AF in African Americans.
Keywords: African Americans; Aged; Alleles; Atrial Fibrillation; Chromosomes, Human, Pair 4; Cohort Studies; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors; Stroke; United States

Left ventricular ejection fraction assessment in older adults: an adjunct to natriuretic peptide testing to identify risk of new-onset heart failure and cardiovascular death? - deFilippi, Christopher R; Christenson, Robert H; Kop, Willem J; Gottdiener, John S; Zhan, Min; Seliger, Stephen L (J Am Coll Cardiol, 2011)
OBJECTIVES: The goal of this paper was to determine whether assessment of left ventricular ejection fraction (LVEF) enhances prediction of new-onset heart failure (HF) and cardiovascular mortality over and above N-terminal pro-B-type natriuretic peptide (NT-proBNP) level in older adults. BACKGROUND: Elevated NT-proBNP levels are common in older adults and are associated with increased risk of HF. METHODS: NT-proBNP and LVEF were measured in 4,137 older adults free of HF. Repeat measures of NT-proBNP were performed 2 to 3 years later and echocardiography was repeated 5 years later (n = 2,375), with a median follow-up of 10.7 years. The addition of an abnormal (<55%) LVEF (n = 317 [7.7%]) to initially elevated or rising NT-proBNP levels was evaluated to determine risk of HF or cardiovascular mortality. Changes in NT-proBNP levels were also assessed for estimating the risk of conversion from a normal to abnormal LVEF. RESULTS: For participants with a low baseline NT-proBNP level (<190 pg/ml; n = 2,918), addition of an abnormal LVEF did not improve the estimation of risk of HF and identified a moderate increase in adjusted risk for cardiovascular mortality (hazard ratio: 1.69 [95% confidence interval: 1.22 to 2.31]). Among those whose NT-proBNP subsequently increased ≥25% to ≥190 pg/ml, an abnormal LVEF was likewise associated with an increased risk of cardiovascular mortality but not HF. Participants with an initially high NT-proBNP level (≥190 pg/ml) were at greater risk overall for both outcomes, and those with an abnormal LVEF were at the highest risk. However, an abnormal LVEF did not improve model classification or risk stratification for either endpoint when added to demographic factors and change in NT-proBNP. An initially elevated NT-proBNP or rising level was associated with an increased risk of developing an abnormal LVEF. CONCLUSIONS: Assessment of LVEF in HF-free older adults based on NT-proBNP levels should be considered on an individual basis, as such assessments do not routinely improve prognostication.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; Cohort Studies; Death; Female; Follow-Up Studies; Heart Failure; Humans; Male; Natriuretic Peptide, Brain; Peptide Fragments; Prospective Studies; Risk Factors; Stroke Volume; Survival Rate; Ventricular Function, Left

Lipoprotein-associated phospholipase A(2) and future risk of subclinical disease and cardiovascular events in individuals with type 2 diabetes: the Cardiovascular Health Study. - Nelson, T L; Kamineni, A; Psaty, B; Cushman, M; Jenny, N S; Hokanson, J; Furberg, C; Mukamal, K J (Diabetologia, 2011)
AIMS/HYPOTHESIS: Type 2 diabetes is an established risk factor for cardiovascular disease (CVD). This increased risk may be due in part to the increased levels of inflammatory factors associated with diabetes. Lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) is a risk marker for CVD and has pro-inflammatory effects in atherosclerotic plaques. We therefore sought to determine whether Lp-PLA(2) levels partially explain the greater prevalence of subclinical CVD and greater incidence of CVD outcomes associated with type 2 diabetes in the Cardiovascular Health Study. METHODS: We conducted a cross-sectional and prospective study of 4,062 men and women without previous CVD from the Cardiovascular Health Study (1989 to 2007). Lp-PLA(2) mass and activity were measured in baseline plasma. Subclinical disease was determined at baseline and incident CVD was ascertained annually. We used logistic regression for cross-sectional analyses and Cox proportional hazards models for incident analyses. RESULTS: At baseline, Lp-PLA(2) mass did not differ significantly by type 2 diabetes status; however, Lp-PLA(2) activity was significantly higher among type 2 diabetic individuals. Baseline subclinical disease was significantly associated with baseline diabetes and this association was similar in models unadjusted or adjusted for Lp-PLA(2) (OR 1.68 [95% CI 1.31-2.15] vs OR 1.67 [95% CI 1.30-2.13]). Baseline type 2 diabetes was also significantly associated with incident CVD events, including fatal CHD, fatal myocardial infarction (MI) and non-fatal MI in multivariable analyses. There were no differences in these estimates after further adjustment for Lp-PLA(2) activity. CONCLUSIONS/INTERPRETATION: In this older cohort, differences in Lp-PLA(2) activity did not explain any of the excess risk for subclinical disease or CVD outcomes related to diabetes.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Cardiovascular Diseases; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Humans; Male; Proportional Hazards Models; Prospective Studies; Risk Factors

Longer legs are associated with greater risk of incident venous thromboembolism independent of total body height. The Longitudinal Study of Thromboembolism Etiology (LITE). - Lutsey, Pamela L; Cushman, Mary; Heckbert, Susan R; Tang, Weihong; Folsom, Aaron R (Thromb Haemost, 2011)
Several studies have reported that taller individuals are at greater risk of venous thromboembolism (VTE). We hypothesised that longer leg length would be positively associated with incident VTE, and would explain the height association. LITE ascertained VTE in a prospective population-based sample of 21,860 individuals aged 45 and older. Leg length was measured as standing height minus torso length. Cox regression models were adjusted for age, race, sex, waist circumference, diabetes, and factor VIII. To evaluate whether leg length was associated with VTE risk independent of height, we standardised leg length and height per 1 standard deviation (SD), and then included them simultaneously in Cox regression models. A total of 641 incident VTE cases accrued over a median follow-up of 16 years. Participants in the highest quintile of leg length were at 59% (95% CI: 22%-108%) greater risk of VTE, relative to the lowest quintile. For height, risk was 45% (12%-88%) greater for those in the highest quintile, compared to the lowest. When leg length and height were modelled simultaneously leg length remained associated with VTE risk (HR per 1 SD: 1.21 (1.04-1.40) while height was unrelated (HR per 1 SD: 1.00 (0.86-1.16). To conclude, participants with longer legs were at greater risk of incident VTE, and leg length explained the relation of height to VTE. It remains to be established whether this finding is due to greater venous surface area, a larger number of venous valves, or greater hydrostatic pressure among individuals with longer legs.
Keywords: Adult; Aged; Anthropometry; Body Height; Female; Follow-Up Studies; Humans; Leg; Male; Middle Aged; Population Groups; Prospective Studies; Risk Factors; United States; Venous Thromboembolism

Longitudinal changes in adiponectin and inflammatory markers and relation to survival in the oldest old: the Cardiovascular Health Study All Stars study. - Kizer, Jorge R; Arnold, Alice M; Jenny, Nancy S; Cushman, Mary; Strotmeyer, Elsa S; Ives, Diane G; Ding, Jingzhong; Kritchevsky, Stephen B; Chaves, Paulo H M; Hirsch, Calvin H; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2011)
BACKGROUND: Adiponectin has anti-inflammatory properties, and its production is suppressed by inflammatory factors. Although elevated levels of adiponectin and inflammatory markers each predict mortality in older adults, the implications of their interdependent actions have not been examined. METHODS: We investigated the joint associations of levels and interval changes in adiponectin, C-reactive protein (CRP), and interleukin 6 (IL-6) with risk of death in 840 older adults participating in a population-based study. Adiponectin, CRP, and IL-6 were measured in samples collected 8.9 (8.2-9.8) years apart, and all-cause mortality was subsequently ascertained (n = 176). RESULTS: Interval changes and end levels of adiponectin, CRP, and IL-6 showed mostly positive, independent associations with mortality, without evidence of multiplicative interaction. Joint models, however, showed an U-shaped relationship between end level of adiponectin and outcome (hazard ratio [HR] [95% CI] = 0.72 [0.52-0.99] per standard deviation [SD] for levels <20.0 mg/L; HR = 1.91 [1.61-3.44] per SD for levels ≥20.0 mg/L). Participants with the greatest longitudinal increases (upper quartile) in both adiponectin and inflammatory markers had a higher risk of death (HR = 2.85 [1.78-4.58]) than those with large increases in adiponectin alone (HR = 1.87 [1.20-2.92]) (p = .043), but not inflammatory markers alone (HR = 2.48 [1.67-3.67]) (p = .55), as compared with smaller changes for both. CONCLUSION: Higher levels or interval change in adiponectin and inflammatory markers predict increased mortality in older persons independent of each other, although for adiponectin, the association appears inverse below 20 mg/L. These findings suggest that inflammatory and noninflammatory mechanisms governing aging-related decline operate in parallel and provide a potential explanation for paradoxical adiponectin-outcome associations reported previously.
Keywords: Adiponectin; Aged, 80 and over; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Chi-Square Distribution; Enzyme-Linked Immunosorbent Assay; Female; Humans; Inflammation; Interleukin-6; Male; Mortality; Predictive Value of Tests; Risk Factors; Sensitivity and Specificity; Survival Analysis; United States

Lower estimated GFR and higher albuminuria are associated with adverse kidney outcomes. A collaborative meta-analysis of general and high-risk population cohorts. - Gansevoort, Ron T; Matsushita, Kunihiro; van der Velde, Marije; Astor, Brad C; Woodward, Mark; Levey, Andrew S; de Jong, Paul E; Coresh, Josef (Kidney Int, 2011)
Both a low estimated glomerular filtration rate (eGFR) and albuminuria are known risk factors for end-stage renal disease (ESRD). To determine their joint contribution to ESRD and other kidney outcomes, we performed a meta-analysis of nine general population cohorts with 845,125 participants and an additional eight cohorts with 173,892 patients, the latter selected because of their high risk for chronic kidney disease (CKD). In the general population, the risk for ESRD was unrelated to eGFR at values between 75 and 105 ml/min per 1.73 m(2) but increased exponentially at lower levels. Hazard ratios for eGFRs averaging 60, 45, and 15 were 4, 29, and 454, respectively, compared with an eGFR of 95, after adjustment for albuminuria and cardiovascular risk factors. Log albuminuria was linearly associated with log ESRD risk without thresholds. Adjusted hazard ratios at albumin-to-creatinine ratios of 30, 300, and 1000 mg/g were 5, 13, and 28, respectively, compared with an albumin-to-creatinine ratio of 5. Albuminuria and eGFR were associated with ESRD, without evidence for multiplicative interaction. Similar associations were found for acute kidney injury and progressive CKD. In high-risk cohorts, the findings were generally comparable. Thus, lower eGFR and higher albuminuria are risk factors for ESRD, acute kidney injury and progressive CKD in both general and high-risk populations, independent of each other and of cardiovascular risk factors.
Keywords: Aged; Albuminuria; Cohort Studies; Creatinine; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Prognosis; Proportional Hazards Models; Risk Factors

Measures of adiposity and future risk of ischemic stroke and coronary heart disease in older men and women. - Kizer, Jorge R; Biggs, Mary L; Ix, Joachim H; Mukamal, Kenneth J; Zieman, Susan J; de Boer, Ian H; Mozaffarian, Dariush; Barzilay, Joshua I; Strotmeyer, Elsa S; Luchsinger, José A; Elkind, Mitchell S V; Longstreth, W T; et al. (Am J Epidemiol, 2011)
The relation between measures of general and central adiposity and individual cardiovascular endpoints remains understudied in older adults. This study investigated the association of measures of body size and composition with incident ischemic stroke or coronary heart disease (1989-2007) in 3,754 community-dwelling US adults aged 65-100 years. Standardized anthropometry and bioelectric impedance measurements were obtained at baseline. Body mass index at age 50 years (BMI50) was calculated on the basis of recalled weight. Although only waist/hip ratio was significantly associated with ischemic stroke in quintile analysis in women, dichotomized body mass index (BMI) (≥ 30 kg/m²) was the only significant predictor in men. For coronary heart disease, there were significant positive adjusted associations for all adiposity measures, without interaction by sex. This was true for both quintiles and conventional cutpoints for obesity, although BMI-defined overweight (25-29.9 kg/m² was significant at midlife but not at baseline. Strengths of association for extreme quintiles (quintile 5 vs. quintile 1) were broadly comparable, but the highest effect estimates were for waist/hip ratio (hazard ratio = 1.56, 95% confidence interval: 1.25, 1.94) and BMI50 (hazard ratio = 1.71, 95% confidence interval: 1.37, 2.14), both of which remained significant after adjustment for mediators, BMI, or each other. Whether these differences translate to better risk prediction will require meta-analytical approaches, as will determination of prognostic cutpoints.
Keywords: Adiposity; Age Factors; Aged; Aged, 80 and over; Brain Ischemia; Coronary Disease; Female; Humans; Incidence; Male; Middle Aged; Obesity; Prevalence; Retrospective Studies; Risk Factors; Sex Factors; United States

Meta-analysis of genome-wide association studies from the CHARGE consortium identifies common variants associated with carotid intima media thickness and plaque. - Bis, Joshua C; Kavousi, Maryam; Franceschini, Nora; Isaacs, Aaron; Abecasis, Goncalo R; Schminke, Ulf; Post, Wendy S; Smith, Albert V; Cupples, L Adrienne; Markus, Hugh S; Schmidt, Reinhold; Huffman, Jennifer E; et al. (Nat Genet, 2011)
Carotid intima media thickness (cIMT) and plaque determined by ultrasonography are established measures of subclinical atherosclerosis that each predicts future cardiovascular disease events. We conducted a meta-analysis of genome-wide association data in 31,211 participants of European ancestry from nine large studies in the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. We then sought additional evidence to support our findings among 11,273 individuals using data from seven additional studies. In the combined meta-analysis, we identified three genomic regions associated with common carotid intima media thickness and two different regions associated with the presence of carotid plaque (P < 5 × 10(-8)). The associated SNPs mapped in or near genes related to cellular signaling, lipid metabolism and blood pressure homeostasis, and two of the regions were associated with coronary artery disease (P < 0.006) in the Coronary Artery Disease Genome-Wide Replication and Meta-Analysis (CARDIoGRAM) consortium. Our findings may provide new insight into pathways leading to subclinical atherosclerosis and subsequent cardiovascular events.
Keywords: Adult; Aged; Aging; Atherosclerosis; Carotid Intima-Media Thickness; Cohort Studies; Coronary Artery Disease; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Heart; Humans; Middle Aged; Phenotype; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Risk Factors

Meta-analysis of genome-wide association studies in >80 000 subjects identifies multiple loci for C-reactive protein levels. - Dehghan, Abbas; Dupuis, Josée; Barbalic, Maja; Bis, Joshua C; Eiriksdottir, Gudny; Lu, Chen; Pellikka, Niina; Wallaschofski, Henri; Kettunen, Johannes; Henneman, Peter; Baumert, Jens; Strachan, David P; et al. (Circulation, 2011)
BACKGROUND: C-reactive protein (CRP) is a heritable marker of chronic inflammation that is strongly associated with cardiovascular disease. We sought to identify genetic variants that are associated with CRP levels. METHODS AND RESULTS: We performed a genome-wide association analysis of CRP in 66 185 participants from 15 population-based studies. We sought replication for the genome-wide significant and suggestive loci in a replication panel comprising 16 540 individuals from 10 independent studies. We found 18 genome-wide significant loci, and we provided evidence of replication for 8 of them. Our results confirm 7 previously known loci and introduce 11 novel loci that are implicated in pathways related to the metabolic syndrome (APOC1, HNF1A, LEPR, GCKR, HNF4A, and PTPN2) or the immune system (CRP, IL6R, NLRP3, IL1F10, and IRF1) or that reside in regions previously not known to play a role in chronic inflammation (PPP1R3B, SALL1, PABPC4, ASCL1, RORA, and BCL7B). We found a significant interaction of body mass index with LEPR (P<2.9×10(-6)). A weighted genetic risk score that was developed to summarize the effect of risk alleles was strongly associated with CRP levels and explained ≈5% of the trait variance; however, there was no evidence for these genetic variants explaining the association of CRP with coronary heart disease. CONCLUSIONS: We identified 18 loci that were associated with CRP levels. Our study highlights immune response and metabolic regulatory pathways involved in the regulation of chronic inflammation.
Keywords: Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Vasculitis

Neighborhood disadvantage and ischemic stroke: the Cardiovascular Health Study (CHS). - Brown, Arleen F; Liang, Li-Jung; Vassar, Stefanie D; Stein-Merkin, Sharon; Longstreth, W T; Ovbiagele, Bruce; Yan, Tingjian; Escarce, José J (Stroke, 2011)
BACKGROUND AND PURPOSE: Neighborhood characteristics may influence the risk of stroke and contribute to socioeconomic disparities in stroke incidence. The objectives of this study were to examine the relationship between neighborhood socioeconomic status and incident ischemic stroke and examine potential mediators of these associations. METHODS: We analyzed data from 3834 whites and 785 blacks enrolled in the Cardiovascular Health Study, a multicenter, population-based, longitudinal study of adults ages≥65 years from 4 US counties. The primary outcome was adjudicated incident ischemic stroke. Neighborhood socioeconomic status was measured using a composite of 6 census tract variables. Race-stratified multilevel Cox proportional hazard models were constructed adjusted for sociodemographic, behavioral, and biological risk factors. RESULTS: Among whites, in models adjusted for sociodemographic characteristics, stroke hazard was significantly higher among residents of neighborhoods in the lowest compared with the highest neighborhood socioeconomic status quartile (hazard ratio, 1.32; 95% CI, 1.01-1.72) with greater attenuation of the hazard ratio after adjustment for biological risk factors (hazard ratio, 1.16; 0.88-1.52) than for behavioral risk factors (hazard ratio, 1.30; 0.99-1.70). Among blacks, we found no significant associations between neighborhood socioeconomic status and ischemic stroke. CONCLUSIONS: Higher risk of incident ischemic stroke was observed in the most disadvantaged neighborhoods among whites, but not among blacks. The relationship between neighborhood socioeconomic status and stroke among whites appears to be mediated more strongly by biological than behavioral risk factors.
Keywords: Aged; Aged, 80 and over; Brain Ischemia; Female; Health Status Disparities; Humans; Incidence; Longitudinal Studies; Male; Poverty; Residence Characteristics; Risk; Risk Factors; Social Class; Social Environment; Socioeconomic Factors; Stroke; Urban Population

The Next PAGE in understanding complex traits: design for the analysis of Population Architecture Using Genetics and Epidemiology (PAGE) Study. - Matise, Tara C; Ambite, Jose Luis; Buyske, Steven; Carlson, Christopher S; Cole, Shelley A; Crawford, Dana C; Haiman, Christopher A; Heiss, Gerardo; Kooperberg, Charles; Marchand, Loic Le; Manolio, Teri A; North, Kari E; et al. (Am J Epidemiol, 2011)
Genetic studies have identified thousands of variants associated with complex traits. However, most association studies are limited to populations of European descent and a single phenotype. The Population Architecture using Genomics and Epidemiology (PAGE) Study was initiated in 2008 by the National Human Genome Research Institute to investigate the epidemiologic architecture of well-replicated genetic variants associated with complex diseases in several large, ethnically diverse population-based studies. Combining DNA samples and hundreds of phenotypes from multiple cohorts, PAGE is well-suited to address generalization of associations and variability of effects in diverse populations; identify genetic and environmental modifiers; evaluate disease subtypes, intermediate phenotypes, and biomarkers; and investigate associations with novel phenotypes. PAGE investigators harmonize phenotypes across studies where possible and perform coordinated cohort-specific analyses and meta-analyses. PAGE researchers are genotyping thousands of genetic variants in up to 121,000 DNA samples from African-American, white, Hispanic/Latino, Asian/Pacific Islander, and American Indian participants. Initial analyses will focus on single nucleotide polymorphisms (SNPs) associated with obesity, lipids, cardiovascular disease, type 2 diabetes, inflammation, various cancers, and related biomarkers. PAGE SNPs are also assessed for pleiotropy using the "phenome-wide association study" approach, testing each SNP for associations with hundreds of phenotypes. PAGE data will be deposited into the National Center for Biotechnology Information's Database of Genotypes and Phenotypes and made available via a custom browser.
Keywords: Epidemiologic Methods; Epidemiologic Research Design; Ethnic Groups; Genetic Association Studies; Genetics, Population; Genome-Wide Association Study; Humans; Interinstitutional Relations; Multifactorial Inheritance; National Human Genome Research Institute (U.S.); Phenotype; Pilot Projects; Research Design; Risk Factors; United States

Predictive value of depressive symptoms and B-type natriuretic peptide for new-onset heart failure and mortality. - van den Broek, Krista C; deFilippi, Christopher R; Christenson, Robert H; Seliger, Stephen L; Gottdiener, John S; Kop, Willem J (Am J Cardiol, 2011)
Depression and natriuretic peptides predict heart failure (HF) progression, but the unique contributions of depression and biomarkers associated with HF outcomes are not known. The present study determined the additive predictive value of depression and aminoterminal pro-B-type natriuretic peptide (NT-proBNP) for new-onset HF in HF-free subjects and mortality in patients with HF. The participants in the Cardiovascular Health Study were assessed for depressive symptoms using the Center for Epidemiologic Studies Depression Scale and NT-proBNP using an electrochemiluminescence immunoassay. The validated cutoff values for depression (Center for Epidemiologic Studies Depression Scale ≥8) and NT-proBNP (≥190 pg/ml) were used. The risks of incident HF and mortality (cardiovascular disease-related and all-cause) were examined during a median follow-up of 11 years, adjusting for demographics, clinical factors, and health behaviors. In patients with HF (n = 208), depression was associated with an elevated risk of cardiovascular disease mortality (hazard ratios [HR] 2.07, 95% confidence interval [CI] 1.31 to 3.27) and all-cause mortality (HR 1.49, 95% CI 1.05 to 2.11), independent of the NT-proBNP level and covariates. The combined presence of depression and elevated NT-proBNP was associated with substantially elevated covariate-adjusted risks of cardiovascular disease mortality (HR 5.42, 95% CI 2.38 to 12.36) and all-cause mortality (HR 3.72, 95% CI 2.20 to 6.37). In the 4,114 HF-free subjects, new-onset HF was independently predicted by an elevated NT-proBNP level (HR 2.27, 95% CI 1.97 to 2.62) but not depression (HR 1.08, 95% CI 0.92 to 1.26) in covariate-adjusted analysis. In conclusion, depression and NT-proBNP displayed additive predictive value for mortality in patients with HF. These associations can be explained by complementary pathophysiologic mechanisms. The presence of both elevated depression and NT-proBNP levels might improve the identification of patients with HF with a high risk of mortality.
Keywords: Aged; Depression; Disease Progression; Female; Follow-Up Studies; Heart Failure; Humans; Incidence; Male; Natriuretic Peptide, Brain; Prognosis; Retrospective Studies; Risk Factors; Survival Rate; United States

Predictors of thyroid hormone initiation in older adults: results from the cardiovascular health study. - Somwaru, Lily L; Arnold, Alice M; Cappola, Anne R (J Gerontol A Biol Sci Med Sci, 2011)
BACKGROUND: Despite widespread use, there are no data on initiation of thyroid hormone use in older people. We report the prevalence of thyroid hormone use and predictors of thyroid hormone initiation in a population of older men and women. METHODS: Thyroid hormone medication data were collected annually from 1989 to 2006 in community-dwelling individuals aged 65 years and older enrolled in the Cardiovascular Health Study (N = 5,888). Associations of age, sex, race, body mass index, education, and coronary heart disease with initiation were evaluated using discrete-time survival analysis. RESULTS: In 1989-1990, 8.9% (95% confidence interval 8.1%-9.7%) of participants were taking a thyroid hormone preparation, increasing to 20.0% (95% confidence interval 8.2%-21.8%) over 16 years. The average initiation rate was 1% per year. The initiation rate was nonlinear with age, and those aged 85 years and older initiated thyroid hormone more than twice as frequently as those aged 65-69 years (hazard ratio = 2.34; 95% confidence interval 1.43-3.85). White women were more likely to initiate thyroid hormone than any other race and sex group. Higher body mass index was independently associated with higher risk for initiation (p = .002) as was greater education (p = .02) and prevalent coronary heart disease (p = .03). CONCLUSIONS: Thyroid hormone use is common in older people. The indications and benefits of thyroid hormone use in older individuals with the highest rate of thyroid hormone initiation-the oldest old, overweight and obese individuals, and those with coronary heart disease-should be investigated.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cardiovascular Diseases; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Follow-Up Studies; Humans; Hypothyroidism; Incidence; Male; Prevalence; Prognosis; Retrospective Studies; Risk Factors; Sex Factors; Thyroid Hormones; Thyroxine; Time Factors; United States

Relationship of abnormal heart rate turbulence and elevated CRP to cardiac mortality in low, intermediate, and high-risk older adults. - Stein, Phyllis K; Barzilay, Joshua I (J Cardiovasc Electrophysiol, 2011)
INTRODUCTION: We examined whether heart rate turbulence (HRT) and C-reactive protein (CRP) add to traditional risk factors for cardiac mortality in older adults at low, intermediate, and high risk. METHODS AND RESULTS: One thousand two hundred and seventy-two individuals, age ≥ 65 years, with 24-hour Holter recordings were studied. HRT, which quantifies heart rate response to ventricular premature contractions, was categorized as: both turbulence onset (TO) and turbulence slope (TS) normal; TO abnormal; TS abnormal; or both abnormal. Independent risks for cardiac mortality associated with HRT or, for comparison, elevated CRP (>3.0 mg/L), were calculated using Cox regression analysis adjusted for traditional cardiovascular disease risk factors and stratified by the presence of no, isolated subclinical (i.e., intermediate risk) or clinical cardiovascular disease. Having TS + TO abnormal compared to both normal was associated with cardiac mortality in the low-risk group [HR 7.9, 95% confidence interval (CI) 2.8-22.5, (P < 0.001)]. In the high and intermediate risk groups, abnormal TS and TS + TO ([HR 2.2, 95% CI 1.5-4.0, P = 0.016] and [HR 2.7, 95% CI 1.2-5.9, P = 0.012]), respectively, were also significantly associated with cardiac mortality. In contrast, elevated CRP was associated with increased cardiac mortality risk only in low-risk individuals [HR 2.5, 95% CI 1.3-5.1, P = 0.009]. Among low risk, the c-statistic was 0.706 for the base model, 0.725 for the base model with CRP, and 0.767 for the base model with HRT. CONCLUSIONS: Abnormal HRT independently adds to risk stratification of low, intermediate and high-risk individuals, but HRT and CRP appear to both add to stratification of those considered low risk.
Keywords: Aged; C-Reactive Protein; Cardiovascular Diseases; Comorbidity; Electrocardiography, Ambulatory; Female; Humans; Incidence; Male; Risk Assessment; Risk Factors; Statistics as Topic; Survival Analysis; Survival Rate; United States; Ventricular Premature Complexes

Retinal microvascular signs and functional loss in older persons: the cardiovascular health study. - Kim, Dae Hyun; Newman, Anne B; Hajjar, Ihab; Strotmeyer, Elsa S; Klein, Ronald; Newton, Elizabeth; Sarnak, Mark J; Burke, Gregory L; Lipsitz, Lewis A (Stroke, 2011)
BACKGROUND AND PURPOSE: We hypothesized that retinal microvascular signs are associated with executive dysfunction, slow gait, and depressive mood, which are characteristic features of microvascular disease affecting frontal subcortical regions of the brain. METHODS: In the Cardiovascular Health Study, 1744 participants (mean age, 78) free of stroke had retinal photographs and carotid ultrasound during the 1997 to 1998 visit. We examined the cross-sectional association of retinal signs with the digit-symbol substitution test (DSST) score, gait speed, the Center for Epidemiologic Studies-Depression score, and depressive mood, defined as Center for Epidemiologic Studies-Depression score >9 or antidepressant use. RESULTS: After adjusting for potential confounders, retinal signs were associated with lower DSST score (generalized arteriolar narrowing and arteriovenous nicking), slower gait (retinopathy), and depressive mood (generalized arteriolar narrowing). A higher number of retinal signs was associated with lower DSST score (-0.76 and -2.79 points for 1 sign and ≥2 signs versus none; P<0.001) and slower gait (-0.009 and -0.083 m/s; P=0.047), but not with the square root of Center for Epidemiologic Studies-Depression score (0.079 and -0.208; P=0.072). In addition, coexistence of retinal signs (generalized arteriolar narrowing and arteriovenous nicking) and carotid atherosclerosis was associated with lower DSST score compared with either process alone (P for interaction <0.01). Notably, further adjustment for ventricular size, white matter disease, and infarcts on MRI did not attenuate the association. CONCLUSIONS: Retinal signs are associated with executive dysfunction and slow gait, and possibly with depressive mood, suggesting a common process involving small vessels.
Keywords: Aged; Cardiovascular Diseases; Depressive Disorder; Frontal Lobe; Humans; Microcirculation; Neuropsychological Tests; Retinal Diseases; Retinal Vessels; Risk Factors

Risk factors for onset of disability among older persons newly diagnosed with heart failure: the Cardiovascular Health Study. - Chaudhry, Sarwat I; McAvay, Gail; Ning, Yuming; Allore, Heather G; Newman, Anne B; Gill, Thomas M (J Card Fail, 2011)
BACKGROUND: As the heart failure population continues to age, disability is becoming an increasingly important issue. Our objective was to identify risk factors for the onset of disability in activities of daily living among older persons with heart failure. METHODS: The study population included participants with newly diagnosed heart failure from the Cardiovascular Health Study, a longitudinal study of community-living, older persons. Data were collected through annual examinations. Cox regression modeling was used to examine associations between time-dependent predictors and onset of disability. RESULTS: Of 461 participants newly diagnosed with heart failure (mean age 78.7 [SD 5.89]), 23% subsequently developed disability. The first year after heart failure diagnosis was the period of greatest risk for onset of disability (chi-square P value <.001). Factors that were independently associated with disability included: impaired gait speed (HR 2.29, 95% CI 1.34-3.90); impaired cognition (HR 1.87, 95% CI 1.14-3.05); and depressive symptoms (HR 1.72, 95% CI 1.04-2.83). CONCLUSIONS: Onset of disability is a common occurrence among older persons newly diagnosed with heart failure. Risk factors for onset of disability in this population are potentially modifiable, and should be routinely assessed in an effort to reduce disability in this growing population.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Disability Evaluation; Disabled Persons; Female; Health Status; Heart Failure; Humans; Longitudinal Studies; Male; Risk Factors

The risk of Parkinson disease associated with urate in a community-based cohort of older adults. - Jain, S; Ton, T G; Boudreau, R M; Yang, M; Thacker, E L; Studenski, S; Longstreth, W T; Strotmeyer, E S; Newman, A B (Neuroepidemiology, 2011)
BACKGROUND/AIMS: Studies suggest an inverse association between urate concentration and the risk of Parkinson disease (PD). We investigated this in the Cardiovascular Health Study in an elderly community-based cohort of adults. METHODS: The association of baseline urate (µmol/l) and incident PD over 14 years was assessed with locally weighted scatterplot smoothing (LOESS) regression from which categories of low (<300 µmol/l), middle (300-500 µmol/l), and high (>500 µmol/l) urate ranges were derived. Multivariate logistic regression models assessed the risk of PD for each urate range. Linear and quadratic terms were tested when modeling the association between urate and the risk of PD. RESULTS: Women had significantly lower urate concentrations than did men [316.8 µmol/l (SD 88.0) vs. 367.4 µmol/l (SD 87.7), p < 0.0001] and in women no associations between urate and PD risk were observed. In men, LOESS curves suggested a U-shaped or threshold effect between urate and PD risk. With the middle range as reference, the risk of developing PD was significantly increased for urate <300 µmol/l (OR 1.69, 95% CI 1.03-2.78) but not for urate >500 µmol/l (OR 1.55, 95% CI 0.72-3.32) in men. A negative linear term was significant for urate <500 µmol/l, and across the entire range a convex quadratic term was significant. CONCLUSIONS: Results suggest a more complex relationship than previously reported between urate levels and the risk of PD in men. Low urate concentrations were associated with a higher PD risk and high urate concentrations were not associated with a further decrease in PD risk.
Keywords: Aged; California; Cohort Studies; Female; Humans; Male; Maryland; North Carolina; Parkinson Disease; Pennsylvania; Prospective Studies; Risk Factors; Sex Distribution; Sex Factors; Uric Acid

Vitamin D, parathyroid hormone, and sudden cardiac death: results from the Cardiovascular Health Study. - Deo, Rajat; Katz, Ronit; Shlipak, Michael G; Sotoodehnia, Nona; Psaty, Bruce M; Sarnak, Mark J; Fried, Linda F; Chonchol, Michel; de Boer, Ian H; Enquobahrie, Daniel; Siscovick, David; Kestenbaum, Bryan (Hypertension, 2011)
Recent studies have demonstrated greater risks of cardiovascular events and mortality among persons who have lower 25-hydroxyvitamin D (25-OHD) and higher parathyroid hormone (PTH) levels. We sought to evaluate the association between markers of mineral metabolism and sudden cardiac death (SCD) among the 2312 participants from the Cardiovascular Health Study who were free of clinical cardiovascular disease at baseline. We estimated associations of baseline 25-OHD and PTH concentrations individually and in combination with SCD using Cox proportional hazards models after adjustment for demographics, cardiovascular risk factors, and kidney function. During a median follow-up of 14 years, there were 73 adjudicated SCD events. The annual incidence of SCD was greater among subjects who had lower 25-OHD concentrations, 2 events per 1000 for 25-OHD ≥20 ng/mL and 4 events per 1000 for 25-OHD <20 ng/mL. Similarly, SCD incidence was greater among subjects who had higher PTH concentrations, 2 events per 1000 for PTH <65 pg/mL and 4 events per 1000 for PTH ≥65 pg/mL. Multivariate adjustment attenuated associations of 25-OHD and PTH with SCD. Finally, 267 participants (11.7% of the cohort) had high PTH and low 25-OHD concentrations. This combination was associated with a >2-fold risk of SCD after adjustment (hazard ratio: 2.19 [95% CI: 1.17-4.10]; P=0.017) compared with participants with normal levels of PTH and 25-OHD. The combination of lower 25-OHD and higher PTH concentrations appears to be associated independently with SCD risk among older adults without cardiovascular disease.
Keywords: Aged; Cardiovascular Diseases; Comorbidity; Death, Sudden, Cardiac; Diabetes Mellitus; Female; Follow-Up Studies; Humans; Hypertension; Incidence; Kidney; Male; Middle Aged; Minerals; Parathyroid Hormone; Proportional Hazards Models; Risk Factors; Socioeconomic Factors; United States; Vitamin D

Adiposity and incident heart failure in older adults: the cardiovascular health study. - Djoussé, Luc; Bartz, Traci M; Ix, Joachim H; Zieman, Susan J; Delaney, Joseph A; Mukamal, Kenneth J; Gottdiener, John S; Siscovick, David S; Kizer, Jorge R (Obesity (Silver Spring), 2012)
While several studies have reported a positive association between overall adiposity and heart failure (HF) risk, limited and inconsistent data are available on the relation between central adiposity and incident HF in older adults. We sought to examine the association between waist circumference (WC) and incident HF and assess whether sex modifies the relation between WC and HF. Prospective study using data on 4,861 participants of the Cardiovascular Health Study (1989-2007). HF was adjudicated by a committee using information from medical records and medications. We used Cox proportional hazard models to compute hazard ratio (HR). The mean age was 73.0 years for men and 72.3 years for women; 42.5% were men and 15.3% were African Americans. WC was positively associated with an increased risk of HF: each standard deviation of WC was associated with a 14% increased risk of HF (95% CI: 3%-26%) in a multivariable model. There was not a statistically significant sex-by-WC interaction (P = 0.081). BMI was positively associated with incident HF (HR: 1.22 (95% CI: 1.15-1.29) per standard deviation increase of BMI); however, this association was attenuated and became nonstatistically significant upon additional adjustment for WC (HR: 1.09 (95% CI: 0.99-1.21)). In conclusion, a higher WC is associated with an increased risk of HF independent of BMI in community-living older men and women.
Keywords: Adiposity; Aged; Aging; Body Fat Distribution; Body Mass Index; Female; Heart Failure; Humans; Incidence; Independent Living; Male; Obesity; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors; United States; Waist Circumference

Apolipoprotein E and kidney function in older adults. - Seshasai, Rebecca Kurnik; Katz, Ronit; de Boer, Ian H; Siscovick, David; Shlipak, Michael G; Rifkin, Dena E; Sarnak, Mark J (Clin Nephrol, 2012)
BACKGROUND: Previous studies suggest that the ε4 and ε2 alleles of apolipoprotein E (APOE) may be associated with decreased and increased risks of CKD, respectively, but there are limited data in older adults. We evaluated the associations of apolipoprotein E alleles with kidney function among older adults in the cardiovascular health study (CHS). METHODS: Caucasian participants had APOE allelic analysis and serum creatinine and cystatin C measured at baseline (n = 3,844 for cross sectional analysis) and in follow up (n = 3,226 for longitudinal analysis). APOE variation was evaluated as an additive model with number of ε2, ε3 and ε4 alleles. GFR was estimated using the CKD epidemiology equation (eGFRcreat) and the cystatin C demographic equation (eGFRcys). The primary outcome was CKD defined by eGFR < 60 ml/min/1.73 m2. The secondary outcome was rapid progression defined by annual loss of eGFR > 3 ml/min/1.73 m2. RESULTS: Mean eGFRcreat was 72 ml/min/1.73 m2 (25% CKD). Compared with the ε3 allele, the APOE ε4 allele was associated with reduced risk of CKD by eGFRcreat: unadjusted odds ratio (OR) and 95% confidence interval (CI) 0.79 (0.67 - 0.93) per allele, fully adjusted OR (95% CI) 0.80 (0.68 - 0.96) per allele. Results were consistent using eGFRcys. There was no association of the ε2 allele with CKD or between the apolipoprotein E gene with rapid progression. CONCLUSIONS: The apolipoprotein ε4 allele was associated with lower odds of CKD in elderly Caucasian individuals. Future research should confirm these findings in other races and explore mechanisms to explain these results.
Keywords: Aged; Aged, 80 and over; Alleles; Apolipoproteins E; Confidence Intervals; Creatinine; Cross-Sectional Studies; Cystatin C; Disease Progression; European Continental Ancestry Group; Female; Gene Frequency; Genotype; Glomerular Filtration Rate; Humans; Kidney; Male; Odds Ratio; Renal Insufficiency, Chronic; Risk Factors

Association between chromosome 9p21 variants and the ankle-brachial index identified by a meta-analysis of 21 genome-wide association studies. - Murabito, Joanne M; White, Charles C; Kavousi, Maryam; Sun, Yan V; Feitosa, Mary F; Nambi, Vijay; Lamina, Claudia; Schillert, Arne; Coassin, Stefan; Bis, Joshua C; Broer, Linda; Crawford, Dana C; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Genetic determinants of peripheral arterial disease (PAD) remain largely unknown. To identify genetic variants associated with the ankle-brachial index (ABI), a noninvasive measure of PAD, we conducted a meta-analysis of genome-wide association study data from 21 population-based cohorts. METHODS AND RESULTS: Continuous ABI and PAD (ABI ≤0.9) phenotypes adjusted for age and sex were examined. Each study conducted genotyping and imputed data to the ≈2.5 million single nucleotide polymorphisms (SNPs) in HapMap. Linear and logistic regression models were used to test each SNP for association with ABI and PAD using additive genetic models. Study-specific data were combined using fixed effects inverse variance weighted meta-analyses. There were a total of 41 692 participants of European ancestry (≈60% women, mean ABI 1.02 to 1.19), including 3409 participants with PAD and with genome-wide association study data available. In the discovery meta-analysis, rs10757269 on chromosome 9 near CDKN2B had the strongest association with ABI (β=-0.006, P=2.46×10(-8)). We sought replication of the 6 strongest SNP associations in 5 population-based studies and 3 clinical samples (n=16 717). The association for rs10757269 strengthened in the combined discovery and replication analysis (P=2.65×10(-9)). No other SNP associations for ABI or PAD achieved genome-wide significance. However, 2 previously reported candidate genes for PAD and 1 SNP associated with coronary artery disease were associated with ABI: DAB21P (rs13290547, P=3.6×10(-5)), CYBA (rs3794624, P=6.3×10(-5)), and rs1122608 (LDLR, P=0.0026). CONCLUSIONS: Genome-wide association studies in more than 40 000 individuals identified 1 genome wide significant association on chromosome 9p21 with ABI. Two candidate genes for PAD and 1 SNP for coronary artery disease are associated with ABI.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Ankle Brachial Index; Chromosomes, Human, Pair 9; Cohort Studies; Cyclin-Dependent Kinase Inhibitor p15; Female; Genome-Wide Association Study; Genotype; HapMap Project; Humans; Logistic Models; Male; Middle Aged; Peripheral Vascular Diseases; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Sex Factors

Association of fetuin-a with incident diabetes mellitus in community-living older adults: the cardiovascular health study. - Ix, Joachim H; Biggs, Mary L; Mukamal, Kenneth J; Kizer, Jorge R; Zieman, Susan J; Siscovick, David S; Mozzaffarian, Dariush; Jensen, Majken K; Nelson, Lauren; Ruderman, Neil; Djoussé, Luc (Circulation, 2012)
BACKGROUND: The liver-secreted protein fetuin-A induces peripheral insulin resistance in vitro. In a pilot study, we observed that higher fetuin-A levels were associated with diabetes mellitus in older persons. However, this finding has not been confirmed in large cohorts. We sought to confirm the association of fetuin-A with incident diabetes mellitus in older persons and to determine whether the association differs by age, sex, and race and among persons with cardiovascular disease (CVD). METHODS AND RESULTS: Among 3710 community-living individuals ≥ 65 years of age without diabetes mellitus at baseline, fetuin-A was measured in serum collected in 1992 to 1993. Participants were followed up for 10.6 years (median) for incident diabetes mellitus. Cox regression models evaluated the association of fetuin-A with incident diabetes mellitus. Interaction terms evaluated heterogeneity by age, sex, race, and CVD. Mean age was 75 years; 60 were female; 15 were black; and 16 had CVD. Mean fetuin-A concentrations were 0.47 ± 0.10 g/L. During follow-up, 305 incident diabetes cases occurred. Each 0.10-g/L (SD)-greater fetuin-A was associated with 19 higher risk of diabetes mellitus (hazard ratio, 1.19; 95 confidence interval, 1.06-1.33) after adjustment for demographics, lifestyle factors, albumin, kidney function, and CVD. Further adjustment for potential mediators (body mass index, waist circumference, hypertension, lipids, and C-reactive protein) moderately attenuated the association (hazard ratio, 1.13; 95 confidence interval, 1.00-1.28). Results were similar by sex, race, and CVD status but were stronger in persons <75 years old (P for interaction=0.01). CONCLUSIONS: Higher fetuin-A is associated with incident diabetes mellitus in older persons regardless of sex, race, or prevalent CVD status. The association may be attenuated in those ≥ 75 years of age.
Keywords: African Continental Ancestry Group; Age Distribution; Aged; Aged, 80 and over; alpha-2-HS-Glycoprotein; Body Mass Index; C-Reactive Protein; Cardiovascular Diseases; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Humans; Incidence; Life Style; Lipids; Male; Pilot Projects; Prevalence; Proportional Hazards Models; Residence Characteristics; Risk Factors; Sex Distribution

Association of mild to moderate chronic kidney disease with venous thromboembolism: pooled analysis of five prospective general population cohorts. - Mahmoodi, Bakhtawar K; Gansevoort, Ron T; Næss, Inger Anne; Lutsey, Pamela L; Brækkan, Sigrid K; Veeger, Nic J G M; Brodin, Ellen E; Meijer, Karina; Sang, Yingying; Matsushita, Kunihiro; Hallan, Stein I; Hammerstrøm, Jens; et al. (Circulation, 2012)
BACKGROUND: Recent findings suggest that chronic kidney disease (CKD) may be associated with an increased risk of venous thromboembolism (VTE). Given the high prevalence of mild-to-moderate CKD in the general population, in depth analysis of this association is warranted. METHODS AND RESULTS: We pooled individual participant data from 5 community-based cohorts from Europe (second Nord-Trøndelag Health Study [HUNT2], Prevention of Renal and Vascular End-stage Disease [PREVEND], and the Tromsø study) and the United States (Atherosclerosis Risks in Communities [ARIC] and Cardiovascular Health Study [CHS]) to assess the association of estimated glomerular filtration rate (eGFR), albuminuria, and CKD with objectively verified VTE. To estimate adjusted hazard ratios for VTE, categorical and continuous spline models were fit by using Cox regression with shared-frailty or random-effect meta-analysis. A total of 1178 VTE events occurred over 599 453 person-years follow-up. Relative to eGFR 100 mL/min per 1.73 m(2), hazard ratios for VTE were 1.29 (95% confidence interval, 1.04-1.59) for eGFR 75, 1.31 (1.00-1.71) for eGFR 60, 1.82 (1.27-2.60) for eGFR 45, and 1.95 (1.26-3.01) for eGFR 30 mL/min per 1.73 m(2). In comparison with an albumin-to-creatinine ratio (ACR) of 5.0 mg/g, the hazard ratios for VTE were 1.34 (1.04-1.72) for ACR 30 mg/g, 1.60 (1.08-2.36) for ACR 300 mg/g, and 1.92 (1.19-3.09) for ACR 1000 mg/g. There was no interaction between clinical categories of eGFR and ACR (P=0.20). The adjusted hazard ratio for CKD, defined as eGFR <60 mL/min per 1.73 m(2) or albuminuria ≥30 mg/g, (versus no CKD) was 1.54 (95% confidence interval, 1.15-2.06). Associations were consistent in subgroups according to age, sex, and comorbidities, and for unprovoked versus provoked VTE, as well. CONCLUSIONS: Both eGFR and ACR are independently associated with increased risk of VTE in the general population, even across the normal eGFR and ACR ranges.
Keywords: Aged; Cohort Studies; Europe; Female; Humans; Incidence; Male; Middle Aged; Prevalence; Renal Insufficiency, Chronic; Risk Factors; Severity of Illness Index; Venous Thromboembolism

Association of plasma phospholipid long-chain ω-3 fatty acids with incident atrial fibrillation in older adults: the cardiovascular health study. - Wu, Jason H Y; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Sacks, Frank M; Rimm, Eric B; Heckbert, Susan R; Siscovick, David S; Mozaffarian, Dariush (Circulation, 2012)
BACKGROUND: Experimental studies suggest that long-chain n-3 polyunsaturated fatty acids (n-3 PUFAs) may reduce the risk of atrial fibrillation (AF). Prior studies evaluating fish or n-3 PUFA consumption from dietary questionnaires and incident AF have been conflicting. Circulating levels of n-3 PUFAs provide an objective measurement of exposure. METHODS AND RESULTS: Among 3326 US men and women ≥65 years of age and free of AF or heart failure at baseline, plasma phospholipid levels of eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid were measured at baseline by use of standardized methods. Incident AF (789 cases) was identified prospectively from hospital discharge records and study visit ECGs during 31 169 person-years of follow-up (1992-2006). In multivariable Cox models adjusted for other risk factors, the relative risk in the top versus lowest quartile of total n-3 PUFAs (eicosapentaenoic acid+docosapentaenoic acid+docosahexaenoic acid) levels was 0.71 (95% confidence interval, 0.57-0.89; P for trend=0.004) and of DHA levels was 0.77 (95% confidence interval, 0.62-0.96; P for trend=0.01). Eicosapentaenoic acid and docosapentaenoic acid levels were not significantly associated with incident AF. Evaluated nonparametrically, both total n-3 PUFAs and docosahexaenoic acid showed graded and linear inverse associations with incidence of AF. Adjustment for intervening events such as heart failure or myocardial infarction during follow-up did not appreciably alter results. CONCLUSIONS: In older adults, higher circulating total long-chain n-3 PUFA and docosahexaenoic acid levels were associated with lower risk of incident AF. These results highlight the need to evaluate whether increased dietary intake of these fatty acids could be effective for the primary prevention of AF.
Keywords: Aged; Atrial Fibrillation; Biomarkers; Dietary Fats; Docosahexaenoic Acids; Eicosapentaenoic Acid; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Incidence; Male; Proportional Hazards Models; Risk Factors; Seafood

Associations between incident ischemic stroke events and stroke and cardiovascular disease-related genome-wide association studies single nucleotide polymorphisms in the Population Architecture Using Genomics and Epidemiology study. - Carty, Cara L; Bůzková, Petra; Fornage, Myriam; Franceschini, Nora; Cole, Shelley; Heiss, Gerardo; Hindorff, Lucia A; Howard, Barbara V; Mann, Sue; Martin, Lisa W; Zhang, Ying; Matise, Tara C; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Genome-wide association studies (GWAS) have identified loci associated with ischemic stroke (IS) and cardiovascular disease (CVD) in European-descent individuals, but their replication in different populations has been largely unexplored. METHODS AND RESULTS: Nine single nucleotide polymorphisms (SNPs) selected from GWAS and meta-analyses of stroke, and 86 SNPs previously associated with myocardial infarction and CVD risk factors, including blood lipids (high density lipoprotein [HDL], low density lipoprotein [LDL], and triglycerides), type 2 diabetes, and body mass index (BMI), were investigated for associations with incident IS in European Americans (EA) N=26 276, African-Americans (AA) N=8970, and American Indians (AI) N=3570 from the Population Architecture using Genomics and Epidemiology Study. Ancestry-specific fixed effects meta-analysis with inverse variance weighting was used to combine study-specific log hazard ratios from Cox proportional hazards models. Two of 9 stroke SNPs (rs783396 and rs1804689) were significantly associated with [corrected] IS hazard in AA; none were significant in this large EA cohort. Of 73 CVD risk factor SNPs tested in EA, 2 (HDL and triglycerides SNPs) were associated with IS. In AA, SNPs associated with LDL, HDL, and BMI were significantly associated with IS (3 of 86 SNPs tested). Out of 58 SNPs tested in AI, 1 LDL SNP was significantly associated with IS. CONCLUSIONS: Our analyses showing lack of replication in spite of reasonable power for many stroke SNPs and differing results by ancestry highlight the need to follow up on GWAS findings and conduct genetic association studies in diverse populations. We found modest IS associations with BMI and lipids SNPs, though these findings require confirmation.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Female; Genetics, Population; Genome-Wide Association Study; Genomics; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Triglycerides

Associations of kidney disease measures with mortality and end-stage renal disease in individuals with and without diabetes: a meta-analysis. - Fox, Caroline S; Matsushita, Kunihiro; Woodward, Mark; Bilo, Henk J G; Chalmers, John; Heerspink, Hiddo J Lambers; Lee, Brian J; Perkins, Robert M; Rossing, Peter; Sairenchi, Toshimi; Tonelli, Marcello; Vassalotti, Joseph A; et al. (Lancet, 2012)
BACKGROUND: Chronic kidney disease is characterised by low estimated glomerular filtration rate (eGFR) and high albuminuria, and is associated with adverse outcomes. Whether these risks are modified by diabetes is unknown. METHODS: We did a meta-analysis of studies selected according to Chronic Kidney Disease Prognosis Consortium criteria. Data transfer and analyses were done between March, 2011, and June, 2012. We used Cox proportional hazards models to estimate the hazard ratios (HR) of mortality and end-stage renal disease (ESRD) associated with eGFR and albuminuria in individuals with and without diabetes. FINDINGS: We analysed data for 1,024,977 participants (128,505 with diabetes) from 30 general population and high-risk cardiovascular cohorts and 13 chronic kidney disease cohorts. In the combined general population and high-risk cohorts with data for all-cause mortality, 75,306 deaths occurred during a mean follow-up of 8·5 years (SD 5·0). In the 23 studies with data for cardiovascular mortality, 21,237 deaths occurred from cardiovascular disease during a mean follow-up of 9·2 years (SD 4·9). In the general and high-risk cohorts, mortality risks were 1·2-1·9 times higher for participants with diabetes than for those without diabetes across the ranges of eGFR and albumin-to-creatinine ratio (ACR). With fixed eGFR and ACR reference points in the diabetes and no diabetes groups, HR of mortality outcomes according to lower eGFR and higher ACR were much the same in participants with and without diabetes (eg, for all-cause mortality at eGFR 45 mL/min per 1·73 m(2) [vs 95 mL/min per 1·73 m(2)], HR 1·35; 95% CI 1·18-1·55; vs 1·33; 1·19-1·48 and at ACR 30 mg/g [vs 5 mg/g], 1·50; 1·35-1·65 vs 1·52; 1·38-1·67). The overall interactions were not significant. We identified much the same findings for ESRD in the chronic kidney disease cohorts. INTERPRETATION: Despite higher risks for mortality and ESRD in diabetes, the relative risks of these outcomes by eGFR and ACR are much the same irrespective of the presence or absence of diabetes, emphasising the importance of kidney disease as a predictor of clinical outcomes. FUNDING: US National Kidney Foundation.
Keywords: Aged; Albuminuria; Cardiovascular Diseases; Cause of Death; Diabetic Nephropathies; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Risk Factors

Cardiac microinjury measured by troponin T predicts collagen metabolism in adults aged >=65 years with heart failure. - Kop, Willem J; Gottdiener, John S; deFilippi, Christopher R; Barasch, Eddy; Seliger, Stephen L; Jenny, Nancy S; Christenson, Robert H (Circ Heart Fail, 2012)
BACKGROUND: Repeated myocardial microinjuries lead to collagen deposition and fibrosis, thereby increasing the risk of clinical heart failure. Little is known about the longitudinal association between increases in myocardial injury and the biology of collagen synthesis and deposition. METHODS AND RESULTS: Repeated measures of highly sensitive cardiac troponin T (cTnT) were obtained in participants of the Cardiovascular Health Study (N=353; mean age, 74±6 years; 52% women) at baseline and at 3 years follow-up. Biomarkers of collagen metabolism were obtained at follow-up and included carboxyterminal propeptide of procollagen type I, carboxyterminal telopeptide of type I collagen, and aminoterminal propeptide of procollagen III. Multivariable linear regression analyses were used to examine the association between baseline cTnT and changes in cTnT with collagen metabolism markers at follow-up adjusting for demographics, heart failure status, and cardiovascular risk factors. Results indicated that cTnT increases over 3-years were significantly associated with higher levels of carboxyterminal telopeptide of type I collagen (β=0.22, P<0.001) and aminoterminal propeptide of procollagen III (β=0.12, P=0.035) at follow-up when adjusting for demographic, clinical, and biochemical covariates including baseline cTnT. These associations were stronger in patients with heart failure than in control subjects. Conclusions- Increases in myocardial microinjury measured by changes in cTnT adversely affect markers of collagen metabolism. These findings are important to the biology of myocardial fibrosis and tissue repair. Serial evaluation of cTnT combined with collagen metabolism markers may further elucidate the pathophysiology of heart failure.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; Case-Control Studies; Chi-Square Distribution; Collagen; Collagen Type I; Female; Fibrosis; Heart Failure; Humans; Linear Models; Longitudinal Studies; Male; Multivariate Analysis; Myocardium; Peptide Fragments; Peptides; Predictive Value of Tests; Procollagen; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; Troponin T; Up-Regulation

Chronic kidney disease, insulin resistance, and incident diabetes in older adults. - Pham, Hien; Robinson-Cohen, Cassianne; Biggs, Mary L; Ix, Joachim H; Mukamal, Kenneth J; Fried, Linda F; Kestenbaum, Bryan; Siscovick, David S; de Boer, Ian H (Clin J Am Soc Nephrol, 2012)
BACKGROUND AND OBJECTIVES: Insulin resistance is a complication of advanced CKD. Insulin resistance is less well characterized in earlier stages of CKD. The response of the pancreatic β cell, effects on glucose tolerance, and risk of diabetes are not clear. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: The Cardiovascular Health Study included 4680 adults without baseline diabetes. The Chronic Kidney Disease Epidemiology Collaboration creatinine equation was used to obtain the estimated GFR (eGFR). Insulin resistance was evaluated as fasting insulin concentration. The insulin sensitivity index, β cell function, and glucose tolerance were assessed by oral glucose tolerance testing. Incident diabetes was defined as fasting glucose ≥126 mg/dl, nonfasting glucose ≥200 mg/dl, or use of glucose-lowering medications. RESULTS: Mean age was 72.5 years (range, 65-98 years). Mean eGFR was 72.2 (SD 17.1) ml/min per 1.73 m(2). After adjustment, each 10 ml/min per 1.73 m(2) lower eGFR was associated with a 2.2% higher fasting insulin concentration (95% confidence interval [CI], 1.4%, 2.9%; P<0.001) and a 1.1% lower insulin sensitivity index (95% CI, 0.03%, 2.2%; P=0.04). Surprisingly, eGFR was associated with an augmented β cell function index (P<0.001), lower 2-hour glucose concentration (P=0.002), and decreased risk of glucose intolerance (P=0.006). Over a median 12 years' follow-up, 437 participants (9.3%) developed diabetes. eGFR was not associated with the risk of incident diabetes. CONCLUSIONS: Among older adults, lower eGFR was associated with insulin resistance. However, with lower eGFR, β cell function was appropriately augmented and risks of impaired glucose tolerance and incident diabetes were not increased.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; Chronic Disease; Creatinine; Diabetes Mellitus; Female; Glomerular Filtration Rate; Glucose Tolerance Test; Health Surveys; Humans; Hypoglycemic Agents; Incidence; Insulin; Insulin Resistance; Insulin-Secreting Cells; Kidney; Kidney Diseases; Linear Models; Male; Proportional Hazards Models; Risk Assessment; Risk Factors; United States

Circulating and dietary α-linolenic acid and incidence of congestive heart failure in older adults: the Cardiovascular Health Study. - Lemaitre, Rozenn N; Sitlani, Colleen; Song, Xiaoling; King, Irena B; McKnight, Barbara; Spiegelman, Donna; Sacks, Frank M; Djoussé, Luc; Rimm, Eric B; Siscovick, David S; Mozaffarian, Dariush (Am J Clin Nutr, 2012)
BACKGROUND: Few studies have evaluated the association between the n-3 fatty acid α-linolenic acid (ALA) and the incidence of congestive heart failure (CHF). OBJECTIVE: We investigated whether plasma phospholipid concentrations and estimated dietary consumption of ALA are associated with incident CHF. DESIGN: We used data from the Cardiovascular Health Study, a prospective cohort study of cardiovascular diseases among adults aged ≥65 y, from 4 US communities. A total of 2957 participants free of prevalent heart disease and with available fatty acid measurements were included in biomarker analyses (30,722 person-years and 686 incident CHF events). A total of 4432 participants free of prevalent heart disease were included in dietary analyses (52,609 person-years and 1072 events). We investigated the association of ALA with incident CHF by using Cox regression. RESULTS: After adjustment for age, sex, race, education, smoking status, BMI, waist circumference, and alcohol consumption, plasma phospholipid ALA was not associated with incident CHF (HR for the highest compared with the lowest quartile: 0.97; 95% CI: 0.79, 1.21; P-trend = 0.85). Likewise, dietary ALA was not associated with incident CHF (adjusted HR for the highest compared with the lowest quartile: 0.96; 95% CI: 0.82, 1.20; P-trend = 0.97). We observed no association of biomarker or dietary ALA with nonvalvular CHF subtype. We also found little evidence of an association between ALA and CHF in subgroups based on age, sex, diabetes, fish consumption, BMI, or FADS2 genotype (rs1535). CONCLUSION: ALA intake is not associated with incident CHF in older adults. This trial was registered at clinicaltrials.gov as NCT00005133.
Keywords: Aged; Alcohol Drinking; alpha-Linolenic Acid; Biomarkers; Body Mass Index; Cardiovascular Diseases; Diet; Fatty Acid Desaturases; Female; Follow-Up Studies; Heart Failure; Humans; Incidence; Male; Polymorphism, Single Nucleotide; Prevalence; Prospective Studies; Risk Factors; Smoking; Surveys and Questionnaires; United States

Consistent directions of effect for established type 2 diabetes risk variants across populations: the population architecture using Genomics and Epidemiology (PAGE) Consortium. - Haiman, Christopher A; Fesinmeyer, Megan D; Spencer, Kylee L; Bůzková, Petra; Voruganti, V Saroja; Wan, Peggy; Haessler, Jeff; Franceschini, Nora; Monroe, Kristine R; Howard, Barbara V; Jackson, Rebecca D; Florez, Jose C; et al. (Diabetes, 2012)
Common genetic risk variants for type 2 diabetes (T2D) have primarily been identified in populations of European and Asian ancestry. We tested whether the direction of association with 20 T2D risk variants generalizes across six major racial/ethnic groups in the U.S. as part of the Population Architecture using Genomics and Epidemiology Consortium (16,235 diabetes case and 46,122 control subjects of European American, African American, Hispanic, East Asian, American Indian, and Native Hawaiian ancestry). The percentage of positive (odds ratio [OR] >1 for putative risk allele) associations ranged from 69% in American Indians to 100% in European Americans. Of the nine variants where we observed significant heterogeneity of effect by racial/ethnic group (P(heterogeneity) < 0.05), eight were positively associated with risk (OR >1) in at least five groups. The marked directional consistency of association observed for most genetic variants across populations implies a shared functional common variant in each region. Fine-mapping of all loci will be required to reveal markers of risk that are important within and across populations.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Metagenomics; Middle Aged; Population Groups; Risk; Risk Factors

Decline in circulating insulin-like growth factors and mortality in older adults: cardiovascular health study all-stars study. - Kaplan, Robert C; Bůzková, Petra; Cappola, Anne R; Strickler, Howard D; McGinn, Aileen P; Mercer, Laina D; Arnold, Alice M; Pollak, Michael N; Newman, Anne B (J Clin Endocrinol Metab, 2012)
BACKGROUND: The association between changes in IGF-I and IGF binding protein (IGFBP) levels and mortality in older adults is unknown. STUDY DESIGN: Participants were 997 persons 77 to 100 yr old enrolled in the Cardiovascular Health Study All Stars Study. Plasma levels of IGF-I, IGFBP-1, and IGFBP-3 were assessed at two study examinations (1996-1997 and 2005-2006). Mortality was assessed between 2006 and 2010. RESULTS: Cumulative mortality (CM) was similar among individuals who had at least 10% decreases over time in IGF-I levels (CM = 29.6%), individuals who had at least 10% increases over time in IGF-I levels (CM = 24.7%), and individuals who had IGF-I levels remaining within ±10% over time (CM = 23.5%). Adjusted for age, sex, race, diabetes, body mass index, creatinine, albumin, and C-reactive protein, decreasing IGF-I level had no significant association with overall cancer mortality or noncancer mortality. Levels of IGFBP-1 increased markedly over time by 38% (median). Individuals with the largest increases in IGFBP-1 level over time had significantly increased risk of mortality. The adjusted hazard ratio per sd of IGFBP-1 change was 1.40 for overall cancer mortality (95% confidence interval = 1.10, 1.77; P = 0.01) and 1.14 for noncancer mortality (95% confidence interval = 1.02, 1.27; P = 0.02). Changes in IGFBP-3 levels were not significantly associated with mortality. CONCLUSION: Among older adults, decreasing IGF-I level over time does not predict subsequent all-cause mortality, whereas increasing IGFBP-1 predicts increased risk of mortality.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Insulin-Like Growth Factor Binding Protein 1; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Longitudinal Studies; Male; Mortality; Predictive Value of Tests; Risk Factors

Development and validation of a coronary risk prediction model for older U.S. and European persons in the Cardiovascular Health Study and the Rotterdam Study. - Koller, Michael T; Leening, Maarten J G; Wolbers, Marcel; Steyerberg, Ewout W; Hunink, M G Myriam; Schoop, Rotraut; Hofman, Albert; Bucher, Heiner C; Psaty, Bruce M; Lloyd-Jones, Donald M; Witteman, Jacqueline C M (Ann Intern Med, 2012)
BACKGROUND: Risk scores for prediction of coronary heart disease (CHD) in older adults are needed. OBJECTIVE: To develop a sex-specific CHD risk prediction model for older adults that accounts for competing risks for death. DESIGN: 2 observational cohort studies, using data from 4946 participants in the Cardiovascular Health Study (CHS) and 4303 participants in the Rotterdam Study (RS). SETTING: Community settings in the United States (CHS) and Rotterdam, the Netherlands (RS). PARTICIPANTS: Persons aged 65 years or older who were free of cardiovascular disease. MEASUREMENTS: A composite of nonfatal myocardial infarction and coronary death. RESULTS: During a median follow-up of 16.5 and 14.9 years, 1166 CHS and 698 RS participants had CHD events, respectively. Deaths from noncoronary causes largely exceeded the number of CHD events, complicating accurate CHD risk predictions. The prediction model had moderate ability to discriminate between events and nonevents (c-statistic, 0.63 in both U.S. and European men and 0.67 and 0.68 in U.S. and European women). The model was well-calibrated; predicted risks were in good agreement with observed risks. Compared with the Framingham point scores, the prediction model classified elderly U.S. persons into higher risk categories but elderly European persons into lower risk categories. Differences in classification accuracy were not consistent and depended on cohort and sex. Adding newer cardiovascular risk markers to the model did not substantially improve performance. LIMITATION: The model may be less applicable in nonwhite populations, and the comparison Framingham model was not designed for adults older than 79 years. CONCLUSION: A CHD risk prediction model that accounts for deaths from noncoronary causes among older adults provided well-calibrated risk estimates but was not substantially more accurate than Framingham point scores. Moreover, adding newer risk markers did not improve accuracy. These findings emphasize the difficulties of predicting CHD risk in elderly persons and the need to improve these predictions. PRIMARY FUNDING SOURCE: National Heart, Lung, and Blood Institute; National Institute of Neurological Disorders and Stroke; The Netherlands Organisation for Scientific Research; and the Netherlands Organisation for Health Research and Development.
Keywords: Aged; Aged, 80 and over; Algorithms; Cause of Death; Coronary Disease; European Continental Ancestry Group; Female; Humans; Incidence; Male; Models, Statistical; Multivariate Analysis; Netherlands; Prospective Studies; Risk Assessment; Risk Factors; United States

Echocardiographic diastolic parameters and risk of atrial fibrillation: the Cardiovascular Health Study. - Rosenberg, Michael A; Gottdiener, John S; Heckbert, Susan R; Mukamal, Kenneth J (Eur Heart J, 2012)
AIMS: Atrial fibrillation (AF) is the most common sustained arrhythmia in the elderly, and shares several risk factors with diastolic dysfunction, including hypertension and advanced age. The purpose of this study is to examine diastolic dysfunction as a risk for incident AF. METHODS AND RESULTS: We examined the association of echocardiographic parameters of diastolic function with the incidence of AF in 4480 participants enrolled in the Cardiovascular Health Study, an ongoing cohort of community-dwelling older adults from four US communities. Participants underwent baseline echocardiography in 1989-1990 and were followed for incident AF on routine follow-up and hospitalizations. After 50 941 person-years of follow-up (median follow-up time 12.1 years), 1219 participants developed AF. In multivariable-adjusted age-stratified Cox models, diastolic echocardiographic parameters were significantly associated with the risk of incident AF. The most significant parameters were the Doppler peak E-wave velocity and left atrial diameter, which demonstrated a positive nonlinear association [HR 1.5 (CI 1.3-1.9) and HR 1.7 (CI 1.4-2.1) for highest vs. lowest quintile, respectively], and Doppler A-wave velocity time integral, which displayed a U-shaped relationship with the risk of AF [HR 0.7 (CI 0.6-0.9) for middle vs. lowest quintile]. Each diastolic parameter displayed a significant association with adjusted NT-proBNP levels, although the nature of the association did not entirely parallel the risk of AF. Further cluster analysis revealed unique patterns of diastolic function that may identify patients at risk for AF. CONCLUSION: In a community-based population of older adults, echocardiographic measures of diastolic function are significantly associated with an increased risk of AF.
Keywords: Aged; Atrial Fibrillation; Blood Flow Velocity; Diastole; Echocardiography, Doppler; Female; Humans; Kaplan-Meier Estimate; Longitudinal Studies; Male; Natriuretic Peptide, Brain; Peptide Fragments; Risk Factors; United States; Ventricular Dysfunction, Left

Effect of Alzheimer's disease risk genes on trajectories of cognitive function in the Cardiovascular Health Study. - Sweet, Robert A; Seltman, Howard; Emanuel, James E; Lopez, Oscar L; Becker, James T; Bis, Joshua C; Weamer, Elise A; Demichele-Sweet, Mary Ann A; Kuller, Lewis H (Am J Psychiatry, 2012)
OBJECTIVE: The trajectory of cognitive decline in patients with late-onset Alzheimer's disease varies widely. Genetic variations in CLU, PICALM, and CR1 are associated with Alzheimer's disease, but it is unknown whether they exert their effects by altering cognitive trajectory in elderly individuals at risk for the disease. METHOD: The authors developed a Bayesian model to fit cognitive trajectories in a cohort of elderly subjects and test for genetic effects. They first validated the model's ability to detect the previously established effects of APOE ε4 alleles on age at cognitive decline and of psychosis on the rate of cognitive decline in 802 subjects from the Cardiovascular Health Cognition Study who did not have dementia at study entry and developed incident dementia during follow-up. The authors then evaluated the effects of CLU, PICALM, and CR1 on age and rate of decline in 1,831 subjects who did not have dementia at study entry and then did or did not develop incident dementia by study's end. RESULTS: The model generated robust fits to the observed cognitive trajectory data, and validation analysis supported the model's utility. CLU and CR1 were associated with more rapid cognitive decline. PICALM was associated with an earlier age at midpoint of cognitive decline. Associations remained after accounting for the effects of APOE and demographic factors. CONCLUSIONS: Evaluation of cognitive trajectories provides a powerful approach to dissecting genetic effects on the processes leading to cognitive deterioration and Alzheimer's disease.
Keywords: Age of Onset; Aged; Alleles; Alzheimer Disease; Apolipoprotein E4; Bayes Theorem; Clusterin; Cohort Studies; Dementia; Disease Progression; Female; Genetic Predisposition to Disease; Humans; Male; Models, Psychological; Monomeric Clathrin Assembly Proteins; Polymorphism, Single Nucleotide; Receptors, Complement 3b; Risk Factors

Fine-mapping and initial characterization of QT interval loci in African Americans. - Avery, Christy L; Sethupathy, Praveen; Buyske, Steven; He, Qianchuan; Lin, Dan-Yu; Arking, Dan E; Carty, Cara L; Duggan, David; Fesinmeyer, Megan D; Hindorff, Lucia A; Jeff, Janina M; Klein, Liviu; et al. (PLoS Genet, 2012)
The QT interval (QT) is heritable and its prolongation is a risk factor for ventricular tachyarrhythmias and sudden death. Most genetic studies of QT have examined European ancestral populations; however, the increased genetic diversity in African Americans provides opportunities to narrow association signals and identify population-specific variants. We therefore evaluated 6,670 SNPs spanning eleven previously identified QT loci in 8,644 African American participants from two Population Architecture using Genomics and Epidemiology (PAGE) studies: the Atherosclerosis Risk in Communities study and Women's Health Initiative Clinical Trial. Of the fifteen known independent QT variants at the eleven previously identified loci, six were significantly associated with QT in African American populations (P≤1.20×10(-4)): ATP1B1, PLN1, KCNQ1, NDRG4, and two NOS1AP independent signals. We also identified three population-specific signals significantly associated with QT in African Americans (P≤1.37×10(-5)): one at NOS1AP and two at ATP1B1. Linkage disequilibrium (LD) patterns in African Americans assisted in narrowing the region likely to contain the functional variants for several loci. For example, African American LD patterns showed that 0 SNPs were in LD with NOS1AP signal rs12143842, compared with European LD patterns that indicated 87 SNPs, which spanned 114.2 Kb, were in LD with rs12143842. Finally, bioinformatic-based characterization of the nine African American signals pointed to functional candidates located exclusively within non-coding regions, including predicted binding sites for transcription factors such as TBX5, which has been implicated in cardiac structure and conductance. In this detailed evaluation of QT loci, we identified several African Americans SNPs that better define the association with QT and successfully narrowed intervals surrounding established loci. These results demonstrate that the same loci influence variation in QT across multiple populations, that novel signals exist in African Americans, and that the SNPs identified as strong candidates for functional evaluation implicate gene regulatory dysfunction in QT prolongation.
Keywords: African Americans; Aged; Computational Biology; Electrocardiography; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Metagenomics; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors; Tachycardia; United States

Genetic determinants of the ankle-brachial index: a meta-analysis of a cardiovascular candidate gene 50K SNP panel in the candidate gene association resource (CARe) consortium. - Wassel, Christina L; Lamina, Claudia; Nambi, Vijay; Coassin, Stefan; Mukamal, Kenneth J; Ganesh, Santhi K; Jacobs, David R; Franceschini, Nora; Papanicolaou, George J; Gibson, Quince; Yanek, Lisa R; van der Harst, Pim; et al. (Atherosclerosis, 2012)
BACKGROUND: Candidate gene association studies for peripheral artery disease (PAD), including subclinical disease assessed with the ankle-brachial index (ABI), have been limited by the modest number of genes examined. We conducted a two stage meta-analysis of ∼50,000 SNPs across ∼2100 candidate genes to identify genetic variants for ABI. METHODS AND RESULTS: We studied subjects of European ancestry from 8 studies (n=21,547, 55% women, mean age 44-73 years) and African American ancestry from 5 studies (n=7267, 60% women, mean age 41-73 years) involved in the candidate gene association resource (CARe) consortium. In each ethnic group, additive genetic models were used (with each additional copy of the minor allele corresponding to the given beta) to test each SNP for association with continuous ABI (excluding ABI>1.40) and PAD (defined as ABI<0.90) using linear or logistic regression with adjustment for known PAD risk factors and population stratification. We then conducted a fixed-effects inverse-variance weighted meta-analyses considering a p<2×10(-6) to denote statistical significance. RESULTS: In the European ancestry discovery meta-analyses, rs2171209 in SYTL3 (β=-0.007, p=6.02×10(-7)) and rs290481 in TCF7L2 (β=-0.008, p=7.01×10(-7)) were significantly associated with ABI. None of the SNP associations for PAD were significant, though a SNP in CYP2B6 (p=4.99×10(-5)) was among the strongest associations. These 3 genes are linked to key PAD risk factors (lipoprotein(a), type 2 diabetes, and smoking behavior, respectively). We sought replication in 6 population-based and 3 clinical samples (n=15,440) for rs290481 and rs2171209. However, in the replication stage (rs2171209, p=0.75; rs290481, p=0.19) and in the combined discovery and replication analysis the SNP-ABI associations were no longer significant (rs2171209, p=1.14×10(-3); rs290481, p=8.88×10(-5)). In African Americans, none of the SNP associations for ABI or PAD achieved an experiment-wide level of significance. CONCLUSIONS: Genetic determinants of ABI and PAD remain elusive. Follow-up of these preliminary findings may uncover important biology given the known gene-risk factor associations. New and more powerful approaches to PAD gene discovery are warranted.
Keywords: Adult; African Americans; Aged; Ankle Brachial Index; Aryl Hydrocarbon Hydroxylases; Cytochrome P-450 CYP2B6; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Oxidoreductases, N-Demethylating; Peripheral Arterial Disease; Polymorphism, Single Nucleotide; Risk Factors; Transcription Factor 7-Like 2 Protein

Genetic risk factors for ischaemic stroke and its subtypes (the METASTROKE collaboration): a meta-analysis of genome-wide association studies. - Traylor, Matthew; Farrall, Martin; Holliday, Elizabeth G; Sudlow, Cathie; Hopewell, Jemma C; Cheng, Yu-Ching; Fornage, Myriam; Ikram, M Arfan; Malik, Rainer; Bevan, Steve; Thorsteinsdottir, Unnur; Nalls, Mike A; et al. (Lancet Neurol, 2012)
BACKGROUND: Various genome-wide association studies (GWAS) have been done in ischaemic stroke, identifying a few loci associated with the disease, but sample sizes have been 3500 cases or less. We established the METASTROKE collaboration with the aim of validating associations from previous GWAS and identifying novel genetic associations through meta-analysis of GWAS datasets for ischaemic stroke and its subtypes. METHODS: We meta-analysed data from 15 ischaemic stroke cohorts with a total of 12 389 individuals with ischaemic stroke and 62 004 controls, all of European ancestry. For the associations reaching genome-wide significance in METASTROKE, we did a further analysis, conditioning on the lead single nucleotide polymorphism in every associated region. Replication of novel suggestive signals was done in 13 347 cases and 29 083 controls. FINDINGS: We verified previous associations for cardioembolic stroke near PITX2 (p=2·8×10(-16)) and ZFHX3 (p=2·28×10(-8)), and for large-vessel stroke at a 9p21 locus (p=3·32×10(-5)) and HDAC9 (p=2·03×10(-12)). Additionally, we verified that all associations were subtype specific. Conditional analysis in the three regions for which the associations reached genome-wide significance (PITX2, ZFHX3, and HDAC9) indicated that all the signal in each region could be attributed to one risk haplotype. We also identified 12 potentially novel loci at p<5×10(-6). However, we were unable to replicate any of these novel associations in the replication cohort. INTERPRETATION: Our results show that, although genetic variants can be detected in patients with ischaemic stroke when compared with controls, all associations we were able to confirm are specific to a stroke subtype. This finding has two implications. First, to maximise success of genetic studies in ischaemic stroke, detailed stroke subtyping is required. Second, different genetic pathophysiological mechanisms seem to be associated with different stroke subtypes. FUNDING: Wellcome Trust, UK Medical Research Council (MRC), Australian National and Medical Health Research Council, National Institutes of Health (NIH) including National Heart, Lung and Blood Institute (NHLBI), the National Institute on Aging (NIA), the National Human Genome Research Institute (NHGRI), and the National Institute of Neurological Disorders and Stroke (NINDS).
Keywords: Brain Ischemia; Databases, Genetic; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Risk Factors; Stroke

Genetic variation in F3 (tissue factor) and the risk of incident venous thrombosis: meta-analysis of eight studies. - Smith, N L; Heit, J A; Tang, W; Teichert, M; Chasman, D I; Morange, P-E (J Thromb Haemost, 2012)
Keywords: Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; Incidence; Male; Middle Aged; Phenotype; Regression Analysis; Risk Assessment; Risk Factors; Thromboplastin; Venous Thrombosis

Genome-wide meta-analysis identifies 56 bone mineral density loci and reveals 14 loci associated with risk of fracture. - Estrada, Karol; Styrkarsdottir, Unnur; Evangelou, Evangelos; Hsu, Yi-Hsiang; Duncan, Emma L; Ntzani, Evangelia E; Oei, Ling; Albagha, Omar M E; Amin, Najaf; Kemp, John P; Koller, Daniel L; Li, Guo; et al. (Nat Genet, 2012)
Bone mineral density (BMD) is the most widely used predictor of fracture risk. We performed the largest meta-analysis to date on lumbar spine and femoral neck BMD, including 17 genome-wide association studies and 32,961 individuals of European and east Asian ancestry. We tested the top BMD-associated markers for replication in 50,933 independent subjects and for association with risk of low-trauma fracture in 31,016 individuals with a history of fracture (cases) and 102,444 controls. We identified 56 loci (32 new) associated with BMD at genome-wide significance (P < 5 × 10(-8)). Several of these factors cluster within the RANK-RANKL-OPG, mesenchymal stem cell differentiation, endochondral ossification and Wnt signaling pathways. However, we also discovered loci that were localized to genes not known to have a role in bone biology. Fourteen BMD-associated loci were also associated with fracture risk (P < 5 × 10(-4), Bonferroni corrected), of which six reached P < 5 × 10(-8), including at 18p11.21 (FAM210A), 7q21.3 (SLC25A13), 11q13.2 (LRP5), 4q22.1 (MEPE), 2p16.2 (SPTBN1) and 10q21.1 (DKK1). These findings shed light on the genetic architecture and pathophysiological mechanisms underlying BMD variation and fracture susceptibility.
Keywords: Bone Density; Computational Biology; European Continental Ancestry Group; Extracellular Matrix Proteins; Female; Femur Neck; Fractures, Bone; Gene Expression Profiling; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Glycoproteins; Humans; Intercellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-5; Lumbar Vertebrae; Male; Mitochondrial Membrane Transport Proteins; Osteoporosis; Phosphoproteins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Spectrin

Heart rate response to a timed walk and cardiovascular outcomes in older adults: the cardiovascular health study. - Girotra, Saket; Kitzman, Dalane W; Kop, Willem J; Stein, Phyllis K; Gottdiener, John S; Mukamal, Kenneth J (Cardiology, 2012)
OBJECTIVES: To determine the relationship between heart rate response during low-grade physical exertion (6-min walk) with mortality and adverse cardiovascular outcomes in the elderly. METHODS: Participants in the Cardiovascular Health Study who completed a 6-min walk test were included. We used delta heart rate (difference between postwalk heart rate and resting heart rate) as a measure of chronotropic response and examined its association with (1) all-cause mortality and (2) incident coronary heart disease event, using multivariable Cox regression models. RESULTS: We included 2,224 participants (mean age 77 ± 4 years; 60% women; 85% white). The average delta heart rate was 26 beats/min. Participants in the lowest tertile of delta heart rate (<20 beats/min) had higher risk-adjusted mortality [hazard ratio (HR) 1.18, 95% confidence interval (CI) 1.00-1.40] and incident coronary heart disease (HR 1.37, 95% CI 1.05-1.78) compared to subjects in the highest tertile (≥30 beats/min), with a significant linear trend across tertiles (p for trend <0.05 for both outcomes). This relationship was not significant after adjustment for distance walked. CONCLUSION: Impaired chronotropic response during a 6-min walk test was associated with an increased risk of mortality and incident coronary heart disease among the elderly. This association was attenuated after adjusting for distance walked.
Keywords: Aged; Cause of Death; Coronary Disease; Exercise Test; Female; Heart Rate; Humans; Male; Physical Exertion; Prognosis; Prospective Studies; Risk Factors; Time Factors; Walking

Impact of blood pressure and blood pressure change during middle age on the remaining lifetime risk for cardiovascular disease: the cardiovascular lifetime risk pooling project. - Allen, Norrina; Berry, Jarett D; Ning, Hongyan; Van Horn, Linda; Dyer, Alan; Lloyd-Jones, Donald M (Circulation, 2012)
BACKGROUND: Prior estimates of lifetime risk (LTR) for cardiovascular disease (CVD) examined the impact of blood pressure (BP) at the index age and did not account for changes in BP over time. We examined how changes in BP during middle age affect LTR for CVD, coronary heart disease, and stroke. METHODS AND RESULTS: Data from 7 diverse US cohort studies were pooled. Remaining LTRs for CVD, coronary heart disease, and stroke were estimated for white and black men and women with death free of CVD as a competing event. LTRs for CVD by BP strata and by changes in BP over an average of 14 years were estimated. Starting at 55 years of age, we followed up 61 585 men and women for 700 000 person-years. LTR for CVD was 52.5% (95% confidence interval, 51.3-53.7) for men and 39.9% (95% confidence interval, 38.7-41.0) for women. LTR for CVD was higher for blacks and increased with increasing BP at index age. Individuals who maintained or decreased their BP to normal levels had the lowest remaining LTR for CVD, 22% to 41%, compared with individuals who had or developed hypertension by 55 years of age, 42% to 69%, suggesting a dose-response effect for the length of time at high BP levels. CONCLUSIONS: Individuals who experience increases or decreases in BP in middle age have associated higher and lower remaining LTR for CVD. Prevention efforts should continue to emphasize the importance of lowering BP and avoiding or delaying the incidence of hypertension to reduce the LTR for CVD.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Female; Follow-Up Studies; Humans; Hypertension; Life Tables; Longitudinal Studies; Male; Middle Aged; Risk Factors

Incidence of mild cognitive impairment in the Pittsburgh Cardiovascular Health Study-Cognition Study. - Lopez, Oscar L; Becker, James T; Chang, Yue-Fang; Sweet, Robert A; DeKosky, Steven T; Gach, Michael H; Carmichael, Owen T; McDade, Eric; Kuller, Lewis H (Neurology, 2012)
OBJECTIVES AND METHODS: The purpose of this study was to examine the incidence of mild cognitive impairment (MCI) and patterns of progression from incident MCI to dementia in 285 cognitively normal subjects (mean age, 78.9 years) in the Cardiovascular Health Study-Cognition Study from 1998-1999 to 2010-2011. RESULTS: Two hundred (70%) of the participants progressed to MCI; the age-adjusted incidence of MCI was 111.09 (95% confidence interval, 88.13-142.95) per 1,000 person-years. A total of 107 (53.5%) of the incident MCI subjects progressed to dementia. The mean time from MCI to dementia was 2.8 ± 1.8 years. Forty (20%) of the incident MCI cases had an "unstable" course: 19 (9.5%) converted to MCI and later returned to normal; 10 (5%) converted to MCI, to normal, and later back to MCI; 7 (3.5%) converted to MCI, to normal, to MCI, and later to dementia; and 4 (2%) converted to MCI, to normal, and later to dementia. There was an increased mortality rate among the cognitively normal group (110.10 per 1,000 person-years) compared to those with incident MCI who converted to dementia (41.32 per 1,000 person-years). CONCLUSIONS: The majority of the subjects aged >80 years developed an MCI syndrome, and half of them progressed to dementia. Once the MCI syndrome was present, the symptoms of dementia appeared within 2 to 3 years. Progression from normal to MCI or from normal to MCI to dementia is not always linear; subjects who developed MCI and later returned to normal can subsequently progress to dementia. Competing mortality and morbidity influence the study of incident MCI and dementia in population cohorts.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Dementia; Disease Progression; Female; Health Surveys; Humans; Incidence; Male; Risk Factors; Severity of Illness Index

Insulin resistance and incident peripheral artery disease in the Cardiovascular Health Study. - Britton, Kathryn A; Mukamal, Kenneth J; Ix, Joachim H; Siscovick, David S; Newman, Anne B; de Boer, Ian H; Thacker, Evan L; Biggs, Mary L; Gaziano, J Michael; Djoussé, Luc (Vasc Med, 2012)
Type 2 diabetes is a risk factor for peripheral artery disease (PAD), and insulin resistance is a key feature of diabetes and pre-diabetes. No longitudinal epidemiological study has examined the relation between insulin resistance and PAD. Our study analyzed the association of quartiles of the homeostatic model of insulin resistance (HOMA-IR) and the development of PAD defined by two methods. PAD was first defined as the development of an abnormal ankle-brachial index (ABI) (dichotomous outcome) after 6 years of follow-up. PAD was alternatively defined as the development of clinical PAD (time-to-event analysis). The study samples included adults over the age of 65 years who were enrolled in the Cardiovascular Health Study, had fasting measurements of insulin and glucose, had ABI measurements, and were not receiving treatment for diabetes. Multivariable models were adjusted for potential confounders, including age, sex, field center and cohort, body mass index (BMI), smoking status, alcohol use, and exercise intensity. Additional models adjusted for potential mediators, including blood pressure, lipids, kidney function, and prevalent vascular disease. In the ABI analysis (n = 2108), multivariable adjusted models demonstrated a positive relation between HOMA-IR and incident PAD (odds ratio = 1.80 comparing the 4th versus 1st quartile of HOMA-IR, 95% confidence interval [CI] 1.20-2.71). In the clinical PAD analysis (n = 4208), we found a similar relation (hazard ratio = 2.30 comparing the 4th versus 1st quartile of HOMA-IR, 95% CI 1.15-4.58). As expected, further adjustment for potential mediators led to some attenuation of effect estimates. In conclusion, insulin resistance is associated with a higher risk of PAD in older adults.
Keywords: Aged; Ankle Brachial Index; Biomarkers; Blood Glucose; Diabetes Mellitus, Type 2; Diabetic Angiopathies; Fasting; Female; Health Surveys; Humans; Incidence; Insulin; Insulin Resistance; Logistic Models; Longitudinal Studies; Male; Odds Ratio; Peripheral Arterial Disease; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Insulin resistance, cystatin C, and mortality among older adults. - de Boer, Ian H; Katz, Ronit; Chonchol, Michel B; Fried, Linda F; Ix, Joachim H; Kestenbaum, Bryan; Mukamal, Kenneth J; Peralta, Carmen A; Siscovick, David S (Diabetes Care, 2012)
OBJECTIVE: Insulin resistance is a risk factor for cardiovascular and noncardiovascular diseases. Impaired kidney function is linked with insulin resistance and may affect relationships of insulin resistance with health outcomes. RESEARCH DESIGN AND METHODS: We performed a cohort study of 3,138 Cardiovascular Health Study participants (age ≥ 65 years) without diabetes. Insulin sensitivity index (ISI) was calculated from fasting and 2-h postload insulin and glucose concentrations. Associations of ISI and fasting insulin concentration with all-cause mortality were tested using Cox proportional hazards models, adjusting for demographic variables, prevalent cardiovascular disease, lifestyle variables, waist circumference, and LDL cholesterol. Subsequent models were additionally adjusted for or stratified by glomerular filtration rate estimated using serum cystatin C (eGFR). RESULTS: A total of 1,810 participants died during the 14.7-year median follow-up. Compared with the highest quartile of ISI, the lowest quartile (most insulin resistant) was associated with 21% (95% CI 6-41) and 11% (-3 to 29) higher risks of death without and with adjustment for eGFR, respectively. Compared with the lowest quartile of fasting insulin concentration, the highest quartile was associated with 22% (4-43) and 4% (-12 to 22) higher risks of death without and with adjustment for eGFR, respectively. Similar attenuation by eGFR was observed when blood pressure, triglycerides, HDL cholesterol, and C-reactive protein were included in models. CONCLUSIONS: Insulin resistance measured as ISI or fasting insulin concentration is associated with increased risk of death among older adults, adjusting for conventional confounding characteristics. Impaired kidney function may mediate or confound this relationship.
Keywords: Aged; Aged, 80 and over; Blood Glucose; Blood Pressure; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Cystatin C; Fasting; Female; Glomerular Filtration Rate; Humans; Insulin Resistance; Life Style; Male; Mortality; Predictive Value of Tests; Proportional Hazards Models; Renal Insufficiency; Risk Factors; Triglycerides; Waist Circumference

Kidney function and mortality in octogenarians: Cardiovascular Health Study All Stars. - Shastri, Shani; Katz, Ronit; Rifkin, Dena E; Fried, Linda F; Odden, Michelle C; Peralta, Carmen A; Chonchol, Michel; Siscovick, David; Shlipak, Michael G; Newman, Anne B; Sarnak, Mark J (J Am Geriatr Soc, 2012)
OBJECTIVES: To examine the association between kidney function and all-cause mortality in octogenarians. DESIGN: Retrospective analysis of prospectively collected data. SETTING: Community. PARTICIPANTS: Serum creatinine and cystatin C were measured in 1,053 Cardiovascular Health Study (CHS) All Stars participants. MEASUREMENTS: Estimated glomerular filtration rate (eGFR) was determined using the Chronic Kidney Disease Epidemiology Collaboration creatinine (eGFR(CR) ) and cystatin C one-variable (eGFR(CYS) ) equations. The association between quintiles of kidney function and all-cause mortality was analyzed using unadjusted and adjusted Cox proportional hazards models. RESULTS: Mean age of the participants was 85, 64% were female, 66% had hypertension, 14% had diabetes mellitus, and 39% had prevalent cardiovascular disease. There were 154 deaths over a median follow-up of 2.6 years. The association between eGFR(CR) and all-cause mortality was U-shaped. In comparison with the reference quintile (64-75 mL/min per 1.73 m(2) ), the highest (≥ 75 mL/min per 1.73 m(2) ) and lowest (≤ 43 mL/min per 1.73 m(2) ) quintiles of eGFR(CR) were independently associated with mortality (hazard ratio (HR) = 2.49, 95% confidence interval (CI) = 1.36-4.55; HR = 2.28, 95% CI = 1.26-4.10, respectively). The association between eGFR(CYS) and all-cause mortality was linear in those with eGFR(CYS) of less than 60 mL/min per 1.73 m(2) , and in the multivariate analyses, the lowest quintile of eGFR(CYS) (<52 mL/min per 1.73 m(2) ) was significantly associated with mortality (HR = 2.04, 95% CI = 1.12-3.71) compared with the highest quintile (>0.88 mL/min per 1.73 m(2) ). CONCLUSION: Moderate reduction in kidney function is a risk factor for all-cause mortality in octogenarians. The association between eGFR(CR) and all-cause mortality differed from that observed with eGFR(CYS) ; the relationship was U-shaped for eGFR(CR) , whereas the risk was primarily present in the lowest quintile for eGFR(CYS) .
Keywords: Aged, 80 and over; Analysis of Variance; Cardiovascular Diseases; Chi-Square Distribution; Creatinine; Cystatin C; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Hypertension; Kidney Diseases; Male; Prevalence; Proportional Hazards Models; Retrospective Studies; Risk Factors; United States

Lifetime risk and years lived free of total cardiovascular disease. - Wilkins, John T; Ning, Hongyan; Berry, Jarett; Zhao, Lihui; Dyer, Alan R; Lloyd-Jones, Donald M (JAMA, 2012)
CONTEXT: Estimates of lifetime risk for total cardiovascular disease (CVD) may provide projections of the future population burden of CVD and may assist in clinician-patient risk communication. To date, no lifetime risk estimates of total CVD have been reported. OBJECTIVES: To calculate lifetime risk estimates of total CVD by index age (45, 55, 65, 75 years) and risk factor strata and to estimate years lived free of CVD across risk factor strata. DESIGN, SETTING, AND PARTICIPANTS: Pooled survival analysis of as many as 905,115 person-years of data from 1964 through 2008 from 5 National Heart, Lung, and Blood Institute-funded community-based cohorts: Framingham Heart Study, Framingham Offspring Study, Atherosclerosis Risk in Communities Study, Chicago Heart Association Detection Project in Industry Study, and Cardiovascular Health Study. All participants were free of CVD at baseline with risk factor data (blood pressure [BP], total cholesterol [TC], diabetes, and smoking status) and total CVD outcome data. MAIN OUTCOME MEASURES: Any total CVD event (including fatal and nonfatal coronary heart disease, all forms of stroke, congestive heart failure, and other CVD deaths). RESULTS: At an index age of 45 years, overall lifetime risk for total CVD was 60.3% (95% CI, 59.3%-61.2%) for men and 55.6% (95% CI, 54.5%-56.7%) for women. Men had higher lifetime risk estimates than women across all index ages. At index ages 55 and 65 years, men and women with at least 1 elevated risk factor (BP, 140-149/90-99 mm Hg; or TC, 200-239 mg/dL; but no diabetes or smoking), 1 major risk factor, or at least 2 major risk factors (BP, ≥160/100 mm Hg or receiving treatment; TC, ≥240 mg/dL or receiving treatment; diabetes mellitus; or current smoking) had lifetime risk estimates to age 95 years that exceeded 50%. Despite an optimal risk factor profile (BP, <120/80 mm Hg; TC, <180 mg/dL; and no smoking or diabetes), men and women at the index age of 55 years had lifetime risks (through 85 years of age) for total CVD of greater than 40% and 30%, respectively. Compared with participants with at least 2 major risk factors, those with an optimal risk factor profile lived up to 14 years longer free of total CVD. CONCLUSIONS: Lifetime risk estimates for total CVD were high (>30%) for all individuals, even those with optimal risk factors in middle age. However, maintenance of optimal risk factor levels in middle age was associated with substantially longer morbidity-free survival.
Keywords: Adult; Aged; Blood Pressure; Cardiovascular Diseases; Cohort Studies; Diabetes Mellitus; Female; Forecasting; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Morbidity; Risk; Risk Factors; Smoking

Lifetime risks of cardiovascular disease. - Berry, Jarett D; Dyer, Alan; Cai, Xuan; Garside, Daniel B; Ning, Hongyan; Thomas, Avis; Greenland, Philip; Van Horn, Linda; Tracy, Russell P; Lloyd-Jones, Donald M (N Engl J Med, 2012)
BACKGROUND: The lifetime risks of cardiovascular disease have not been reported across the age spectrum in black adults and white adults. METHODS: We conducted a meta-analysis at the individual level using data from 18 cohort studies involving a total of 257,384 black men and women and white men and women whose risk factors for cardiovascular disease were measured at the ages of 45, 55, 65, and 75 years. Blood pressure, cholesterol level, smoking status, and diabetes status were used to stratify participants according to risk factors into five mutually exclusive categories. The remaining lifetime risks of cardiovascular events were estimated for participants in each category at each age, with death free of cardiovascular disease treated as a competing event. RESULTS: We observed marked differences in the lifetime risks of cardiovascular disease across risk-factor strata. Among participants who were 55 years of age, those with an optimal risk-factor profile (total cholesterol level, <180 mg per deciliter [4.7 mmol per liter]; blood pressure, <120 mm Hg systolic and 80 mm Hg diastolic; nonsmoking status; and nondiabetic status) had substantially lower risks of death from cardiovascular disease through the age of 80 years than participants with two or more major risk factors (4.7% vs. 29.6% among men, 6.4% vs. 20.5% among women). Those with an optimal risk-factor profile also had lower lifetime risks of fatal coronary heart disease or nonfatal myocardial infarction (3.6% vs. 37.5% among men, <1% vs. 18.3% among women) and fatal or nonfatal stroke (2.3% vs. 8.3% among men, 5.3% vs. 10.7% among women). Similar trends within risk-factor strata were observed among blacks and whites and across diverse birth cohorts. CONCLUSIONS: Differences in risk-factor burden translate into marked differences in the lifetime risk of cardiovascular disease, and these differences are consistent across race and birth cohorts. (Funded by the National Heart, Lung, and Blood Institute.).
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; Cohort Effect; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Risk; Risk Assessment; Risk Factors; United States

Lipoprotein-associated phospholipase A2 (Lp-PLA2) and future risk of type 2 diabetes: results from the Cardiovascular Health Study. - Nelson, T L; Biggs, M L; Kizer, J R; Cushman, M; Hokanson, J E; Furberg, C D; Mukamal, K J (J Clin Endocrinol Metab, 2012)
INTRODUCTION: Lipoprotein-associated phospholipase A2 (Lp-PLA(2)) has been consistently associated with cardiovascular disease (CVD) risk factors and predictive of CVD outcomes; furthermore, it is consistently higher among type 2 diabetics than nondiabetics. However, the relationships of circulating Lp-PLA(2) mass and activity with incident type 2 diabetes mellitus have not been examined. Therefore, the purpose of this study was to determine the association of Lp-PLA(2) mass and activity with type 2 diabetes among older adults. METHODS: We conducted analyses of Lp-PLA(2) and prevalent and incident diabetes among 5474 men and women from the Cardiovascular Health Study (1989-2007). Lp-PLA(2) mass and activity were measured in baseline plasma. Diabetes status was ascertained annually with medication inventories and repeated blood glucose measurements. Generalized linear and Cox proportional hazards models were used to adjust for confounding factors including body mass index and inflammation. RESULTS: At baseline, the top two quintiles of Lp-PLA(2) activity were significantly associated with prevalent type 2 diabetes with a multivariable relative risk = 1.35 [95% confidence interval (CI) = 1.11-1.63] for quintile 4, and relative risk = 1.33 (95% CI = 1.07-1.66) for quintile 5. Among participants free of diabetes at baseline, we found a significant positive association with both the homeostatic model assessment for insulin resistance and β-cell function per SD increase in Lp-PLA(2) activity (P values for both <0.01). In prospective analyses, the risk of incident type 2 diabetes was significantly higher among those in the highest quintile of Lp-PLA(2) activity [multivariable hazard ratio = 1.45 (95% CI = 1.01-2.07)] compared with the lowest quintile. Lp-PLA(2) mass was not significantly associated with incident type 2 diabetes. DISCUSSION: Lp-PLA(2) activity is positively associated with insulin resistance and predicts incident type 2 diabetes among older adults independent of multiple factors associated with diabetes pathogenesis.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Aged, 80 and over; Cardiovascular Diseases; Diabetes Mellitus, Type 2; Female; Humans; Incidence; Insulin Resistance; Male; Middle Aged; Predictive Value of Tests; Prevalence; Prospective Studies; Risk; Risk Factors

Long-term assessment of inflammation and healthy aging in late life: the Cardiovascular Health Study All Stars. - Jenny, Nancy S; French, Benjamin; Arnold, Alice M; Strotmeyer, Elsa S; Cushman, Mary; Chaves, Paulo H M; Ding, Jingzhong; Fried, Linda P; Kritchevsky, Stephen B; Rifkin, Dena E; Sarnak, Mark J; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2012)
BACKGROUND: Associations of inflammation with age-related pathologies are documented; however, it is not understood how changes in inflammation over time impact healthy aging. METHODS: We examined associations of long-term change in C-reactive protein (CRP) and interleukin-6 (IL-6) with concurrent onset of physical and cognitive impairment, subsequent cardiovascular disease (CVD), and mortality in 1,051 participants in the Cardiovascular Health Study All Stars Study. Biomarkers were measured in 1996-1997 and 2005-2006. RESULTS: In 2005-2006, median age was 84.9 years, 63% were women and 17% non-white; 21% had at least a doubling in CRP over time and 23% had at least a doubling in IL-6. Adjusting for demographics, CVD risk factors, and 1996-1997 CRP level, each doubling in CRP change over 9 years was associated with higher risk of physical or cognitive impairment (odds ratio 1.29; 95% confidence interval 1.15, 1.45). Results were similar for IL-6 (1.45; 1.20, 1.76). A doubling in IL-6 change over time, but not CRP, was associated with incident CVD events; hazard ratio (95% confidence interval) 1.34 (1.03, 1.75). Doubling in change in each biomarker was individually associated with mortality (CRP: 1.12 [1.03, 1.22]; IL-6 1.39 [1.16, 1.65]). In models containing both change and 2005-2006 level, only level was associated with CVD events and mortality. CONCLUSIONS: Although increases in inflammation markers over 9 years were associated with higher concurrent risk of functional impairment and subsequent CVD events and mortality, final levels of each biomarker appeared to be more important in determining risk of subsequent events than change over time.
Keywords: Aged; Aged, 80 and over; Aging; C-Reactive Protein; Cardiovascular Diseases; Cognition; Cohort Studies; Cross-Sectional Studies; Female; Humans; Inflammation; Inflammation Mediators; Interleukin-6; Longitudinal Studies; Male; Risk Factors; Vermont

Markers of inflammation in prevalent and incident Parkinson's disease in the Cardiovascular Health Study. - Ton, Thanh G N; Jain, Samay; Biggs, Mary L; Thacker, Evan L; Strotmeyer, Elsa S; Boudreau, Robert; Newman, Anne B; Longstreth, W T; Checkoway, Harvey (Parkinsonism Relat Disord, 2012)
BACKGROUND: Studies demonstrate existence of inflammation in prevalent Parkinson's disease (PD). We assessed associations of baseline levels of inflammatory markers with prevalent PD at baseline (1989) and incident PD identified over 13 years of follow-up of the Cardiovascular Health Study. METHODS: Blood samples at baseline were measured for fibrinogen, interleukin-6, tumor necrosis factor-α, C-reactive protein, albumin, and white blood cells. The analysis included 60 prevalent and 154 incident PD cases. RESULTS: Risk of prevalent PD was significantly higher per doubling of IL-6 among women (odds ratio [OR]=1.5, 95% confidence interval [CI]: 1.0, 2.4) and WBC among men (OR: 2.4, 95% CI: 1.2, 4.9) in multivariate models. Risk of incident PD was not associated with higher levels of any biomarker after adjusting for age, smoking, African American race, and history of diabetes. Inverse associations with incident PD were observed per doubling of C-reactive protein (OR=0.9; 95% CI: 0.8, 1.0) and of fibrinogen among women (OR=0.4; 95% CI: 0.2, 0.8). CONCLUSIONS: Although inflammation exists in PD, it may not represent an etiologic factor. Our findings suggest the need for larger studies that measure inflammatory markers before PD onset.
Keywords: Aged; Aged, 80 and over; Albumins; Biomarkers; C-Reactive Protein; Enzyme-Linked Immunosorbent Assay; Female; Fibrinogen; Humans; Incidence; Inflammation; Interleukin-6; Leukocyte Count; Male; Parkinson Disease; Prevalence; Risk Factors; Tumor Necrosis Factor-alpha

Meta-analysis identifies six new susceptibility loci for atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Albert, Christine M; Glazer, Nicole L; Ritchie, Marylyn D; Smith, Albert V; Arking, Dan E; Müller-Nurasyid, Martina; Krijthe, Bouwe P; Lubitz, Steven A; Bis, Joshua C; Chung, Mina K; et al. (Nat Genet, 2012)
Atrial fibrillation is a highly prevalent arrhythmia and a major risk factor for stroke, heart failure and death. We conducted a genome-wide association study (GWAS) in individuals of European ancestry, including 6,707 with and 52,426 without atrial fibrillation. Six new atrial fibrillation susceptibility loci were identified and replicated in an additional sample of individuals of European ancestry, including 5,381 subjects with and 10,030 subjects without atrial fibrillation (P < 5 × 10(-8)). Four of the loci identified in Europeans were further replicated in silico in a GWAS of Japanese individuals, including 843 individuals with and 3,350 individuals without atrial fibrillation. The identified loci implicate candidate genes that encode transcription factors related to cardiopulmonary development, cardiac-expressed ion channels and cell signaling molecules.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Child; Child, Preschool; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Infant, Newborn; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

The natural history of subclinical hypothyroidism in the elderly: the cardiovascular health study. - Somwaru, Lily L; Rariy, Chevon M; Arnold, Alice M; Cappola, Anne R (J Clin Endocrinol Metab, 2012)
CONTEXT: Studies of long-term outcomes of subclinical hypothyroidism have assessed only baseline thyroid function, despite natural transitions to euthyroidism and overt hypothyroidism over time. OBJECTIVE: We provide estimates of persistence, resolution, and progression of subclinical hypothyroidism over 4 yr, stratified by baseline TSH, anti-thyroid peroxidase antibody (TPOAb) status, age, and sex. DESIGN, SETTING, AND PARTICIPANTS: Participants were 3996 U.S. individuals at least 65 yr old enrolled in the Cardiovascular Health Study. Subclinical hypothyroidism was detected at baseline in 459 individuals not taking thyroid medication. MAIN OUTCOME MEASURE: Thyroid function was evaluated at 2 and 4 yr and initiation of thyroid medication annually. Results were stratified by baseline TSH, TPOAb status, age, and sex. RESULTS: Persistence of subclinical hypothyroidism was 56% at 2 and 4 yr. At 2 yr, resolution was more common with a TSH of 4.5-6.9 mU/liter (46 vs. 10% with TSH 7-9.9 mU/liter and 7% with TSH ≥10 mU/liter; P < 0.001) and with TPOAb negativity (48 vs. 15% for positive; P < 0.001). Higher TSH and TPOAb positivity were independently associated with lower likelihood of reversion to euthyroidism (P < 0.05). TSH of 10 mU/liter or higher was independently associated with progression to overt hypothyroidism (P < 0.05). Transitions between euthyroidism and subclinical hypothyroidism were common between 2 and 4 yr. Age and sex did not affect transitions. CONCLUSIONS: Subclinical hypothyroidism persists for 4 yr in just over half of older individuals, with high rates of reversion to euthyroidism in individuals with lower TSH concentrations and TPOAb negativity. Future studies should examine the impact of transitions in thyroid status on clinical outcomes.
Keywords: Age Distribution; Aged; Aged, 80 and over; Autoantibodies; Cardiovascular Diseases; Cohort Studies; Disease Progression; Female; Humans; Hypothyroidism; Iodide Peroxidase; Logistic Models; Longitudinal Studies; Male; Prevalence; Risk Factors; Seroepidemiologic Studies; Severity of Illness Index; Sex Distribution; Thyrotropin

Nonesterified fatty acids and risk of sudden cardiac death in older adults. - Djoussé, Luc; Biggs, Mary L; Ix, Joachim H; Kizer, Jorge R; Lemaitre, Rozenn N; Sotoodehnia, Nona; Zieman, Susan J; Mozaffarian, Dariush; Tracy, Russell P; Mukamal, Kenneth J; Siscovick, David S (Circ Arrhythm Electrophysiol, 2012)
BACKGROUND: Although nonesterified fatty acids (NEFA) have been positively associated with coronary heart disease risk factors, limited and inconsistent data are available on the relation between NEFA and sudden cardiac death. METHODS AND RESULTS: Using a prospective design, we studied 4657 older men and women (mean age, 75 years) from the Cardiovascular Health Study (1992-2006) to evaluate the association between plasma NEFA and the risk of sudden cardiac death in older adults. Plasma concentrations of NEFA were measured using established enzymatic methods, and sudden death was adjudicated using medical records, death certificates, proxy interview, and autopsy reports. We used Cox proportional hazard models to estimate multivariable-adjusted relative risks. During a median follow-up of 10.0 years, 221 new cases of sudden cardiac death occurred. In a multivariable model adjusting for age, sex, race, clinic site, alcohol intake, smoking, prevalent coronary heart disease and heart failure, and self-reported health status, relative risks (95% confidence interval) for sudden cardiac death were 1.0 (ref), 1.15 (0.81-1.64), 1.06 (0.72-1.55), and 0.91 (0.60-1.38) across consecutive quartiles of NEFA concentration. In secondary analyses restricted to the first 5 years of follow-up, we also did not observe a statistically significant association between plasma NEFA and sudden cardiac death. CONCLUSIONS: Our data do not provide evidence for an association between plasma NEFA measured late in life and the risk of sudden cardiac death in older adults.
Keywords: Aged; Aged, 80 and over; Biomarkers; Death, Sudden, Cardiac; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Humans; Incidence; Male; Proportional Hazards Models; Prospective Studies; Retrospective Studies; Risk Factors

Novel circulating fatty acid patterns and risk of cardiovascular disease: the Cardiovascular Health Study. - Imamura, Fumiaki; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Lichtenstein, Alice H; Matthan, Nirupa R; Herrington, David M; Siscovick, David S; Mozaffarian, Dariush (Am J Clin Nutr, 2012)
BACKGROUND: Complex interplays of diet and metabolism influence circulating fatty acids (FAs), possibly constituting FA patterns related to cardiovascular disease (CVD) risk. OBJECTIVES: We aimed to derive FA patterns from circulating FAs, relate the patterns to CVD incidence, and extend the derived patterns to atherosclerosis progression in another independent cohort. DESIGN: We used principal component analysis (PCA) to derive FA patterns from 38 plasma phospholipid FAs in 2972 older adults in the Cardiovascular Health Study (CHS). Identified patterns were evaluated for prospective associations with 14-y incidence of CVD [ischemic heart disease (IHD) or stroke]. In another independent cohort of postmenopausal women with IHD, we evaluated associations of the CHS-derived patterns with 3.2-y progression of angiographically defined coronary atherosclerosis. RESULTS: Three distinct patterns were identified, characterized by higher proportions of trans FAs, de novo lipogenesis (DNL) FAs, and long-chain MUFAs (LCMUFAs). During 32,265 person-years, 780 incident CVD events occurred. The trans FA pattern was associated with higher CVD risk (multivariable-adjusted HR for the highest compared with the lowest quintiles = 1.58; 95% CI: 1.17, 2.12; P-trend = 0.006), primarily attributable to higher risk of stroke (HR: 2.46; 95% CI: 1.54, 3.92; P-trend = 0.005). The DNL and LCMUFA patterns were not associated with CVD incidence or with IHD or stroke (P-trend > 0.11 each). In the second cohort, the trans FA pattern, but not the other 2 patterns, was positively associated with progression of coronary atherosclerosis (P-trend < 0.05). CONCLUSIONS: PCA appears to provide informative circulating FA patterns. A pattern driven mainly by trans FA levels related to greater CVD risk in older adults and coronary atherosclerosis progression in women with IHD.
Keywords: Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Cohort Studies; Coronary Artery Disease; Disease Progression; Female; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Myocardial Ischemia; Principal Component Analysis; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; Trans Fatty Acids; United States

Predicting late-life disability and death by the rate of decline in physical performance measures. - Hirsch, Calvin Hayes; Bůzková, Petra; Robbins, John A; Patel, Kushang V; Newman, Anne B (Age Ageing, 2012)
BACKGROUND: the rate of performance decline may influence the risk of disability or death. METHODS: for 4,182 Cardiovascular Health Study participants, we used multinomial Poisson log-linear models to assess the contribution of physical performance in 1998-99, and the rate of performance change between 1992-93 and 1998-99, to the risk of death or disability in 2005-06 in three domains: mobility, upper-extremity function (UEF) and activities of daily living (ADL). We evaluated performance in finger-tapping, grip strength, stride length, gait speed and chair stands separately and together for each outcome, adjusting for age, gender, race and years of disability in that outcome between 1992-93 and 1998-99. RESULTS: participants' age averaged 79.4 in 1998-99; 1,901 died over 7 years. Compared with the lowest change quintile in stride length, the highest quintile had a 1.32 relative risk (RR) of ADL disability (95% CI: 1.16 -1.96) and a 1.27 RR of death (95% CI: 1.07 -1.51). The highest change quintile for grip strength increased the risk of ADL disability by 35% (95% CI: 1.13 -1.61) and death by 31% (95% CI: 1.16 -1.49), compared with the lowest quintile. The annual change in stride length and grip strength also predicted disability in mobility and UEF. CONCLUSION: performance trajectories independently predict death and disability.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Aging; Disability Evaluation; Disabled Persons; Female; Geriatric Assessment; Hand Strength; Health Surveys; Humans; Linear Models; Male; Mobility Limitation; Mortality; Motor Skills; Predictive Value of Tests; Risk Assessment; Risk Factors; Survival Analysis; Time Factors; United States; Upper Extremity; Walking

Racial differences in risks for first cardiovascular events and noncardiovascular death: the Atherosclerosis Risk in Communities study, the Cardiovascular Health Study, and the Multi-Ethnic Study of Atherosclerosis. - Feinstein, Matthew; Ning, Hongyan; Kang, Joseph; Bertoni, Alain; Carnethon, Mercedes; Lloyd-Jones, Donald M (Circulation, 2012)
BACKGROUND: No studies have compared first cardiovascular disease (CVD) events and non-CVD death between races in a competing risks framework, which examines risks for numerous events simultaneously. METHODS AND RESULTS: We used competing Cox models to estimate hazards for first CVD events and non-CVD death within and between races in 3 multicenter, National Heart, Lung, and Blood Institute-sponsored cohorts. Of 14 569 Atherosclerosis Risk in Communities (ARIC) study participants aged 45 to 64 years with mean follow-up of 10.5 years, 11.6% had CVD and 5.0% had non-CVD death as first events; among 4237 Cardiovascular Health Study (CHS) study participants aged 65 to 84 years and followed for 8.5 years, these figures were 43.2% and 15.7%, respectively. Middle-aged blacks were significantly more likely than whites to experience any CVD as a first event; this disparity disappeared by older adulthood and after adjustment for CVD risk factors. The pattern of results was similar for Multi-Ethnic Study of Atherosclerosis (MESA) participants. Traditional Cox and competing risks models yielded different results for coronary heart disease risk. Black men appeared somewhat more likely than white men to experience coronary heart disease with use of a standard Cox model (hazard ratio 1.06; 95% CI 0.90, 1.26), whereas they appeared less likely than white men to have a first coronary heart disease event with use of a competing risks model (hazard ratio, 0.77; 95% CI, 0.60, 1.00). CONCLUSIONS: CVD affects blacks at an earlier age than whites; this may be attributable in part to elevated CVD risk factor levels among blacks. Racial disparities in first CVD incidence disappear by older adulthood. Competing risks analyses may yield somewhat different results than traditional Cox models and provide a complementary approach to examining risks for first CVD events.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Aged, 80 and over; Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Continental Population Groups; Ethnic Groups; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged; Residence Characteristics; Risk Factors

Retinal microvascular signs and disability in the Cardiovascular Health Study. - Kim, Dae Hyun; Chaves, Paulo H M; Newman, Anne B; Klein, Ronald; Sarnak, Mark J; Newton, Elizabeth; Strotmeyer, Elsa S; Burke, Gregory L; Lipsitz, Lewis A (Arch Ophthalmol, 2012)
OBJECTIVE: To study the associations of retinal microvascular changes, which are associated with systemic conditions and cognitive decline, with disability in performing activities of daily living (ADL). DESIGN: Prospective cohort study of 1487 community-dwelling participants in the Cardiovascular Health Study (mean age, 78 years) who were free of ADL disability and had available data on retinal signs and carotid intima-media thickness at the 1998-1999 visit. Main outcome measures were incident ADL disability, defined as self-reported difficulty in performing any ADL, by the presence of retinal signs and advanced carotid atherosclerosis, defined by carotid intima-media thickness in the 80th percentile or more or 25% or more stenosis, and potential mediation by cerebral microvascular disease on brain imaging or by executive dysfunction, slow gait, and depressive mood, which are symptoms of frontal subcortical dysfunction. RESULTS: During the median follow-up of 3.1 years (maximum, 7.8 years), participants with 2 or more retinal signs had a higher rate of disability than those with fewer than 2 retinal signs (10.1% vs 7.1%; adjusted hazard ratio, 1.45; 95% confidence interval, 1.24-1.69; P < .001). There was no evidence of interaction by advanced carotid atherosclerosis (P > .10). The association seemed to be partially mediated by executive dysfunction, slow gait, and depressive symptoms but not by cerebral microvascular disease on brain imaging. CONCLUSIONS: These results provide further support for the pathophysiologic and prognostic significance of microvascular disease in age-related disability. However, it remains to be determined how to best use retinal photography in clinical risk prediction.
Keywords: Activities of Daily Living; Aged; Carotid Artery Diseases; Cognition Disorders; Diagnostic Techniques, Ophthalmological; Disability Evaluation; Follow-Up Studies; Humans; Hypertension; Incidence; Kaplan-Meier Estimate; Microcirculation; Predictive Value of Tests; Prevalence; Prognosis; Prospective Studies; Retinal Diseases; Risk Factors; Smoking

The risk of infection-related hospitalization with decreased kidney function. - Dalrymple, Lorien S; Katz, Ronit; Kestenbaum, Bryan; de Boer, Ian H; Fried, Linda; Sarnak, Mark J; Shlipak, Michael G (Am J Kidney Dis, 2012)
BACKGROUND: Moderate kidney disease may predispose to infection. We sought to determine whether decreased kidney function, estimated by serum cystatin C level, was associated with the risk of infection-related hospitalization in older individuals. STUDY DESIGN: Cohort study. SETTING & PARTICIPANTS: 5,142 Cardiovascular Health Study (CHS) participants with measured serum creatinine and cystatin C and without estimated glomerular filtration rate (eGFR) <15 mL/min/1.73 m(2) at enrollment. PREDICTOR: The primary exposure of interest was eGFR using serum cystatin C level (eGFR(SCysC)). OUTCOME: Infection-related hospitalizations during a median follow-up of 11.5 years. RESULTS: In adjusted analyses, eGFR(SCysC) categories of 60-89, 45-59, and 15-44 mL/min/1.73 m(2) were associated with 16%, 37%, and 64% greater risk of all-cause infection-related hospitalization, respectively, compared with eGFR(SCysC) ≥90 mL/min/1.73 m(2). When cause-specific infection was examined, eGFR(SCysC) of 15-44 mL/min/1.73 m(2) was associated with an 80% greater risk of pulmonary and 160% greater risk of genitourinary infection compared with eGFR(SCysC) ≥90 mL/min/1.73 m(2). LIMITATIONS: No measures of urinary protein, study limited to principal discharge diagnosis. CONCLUSIONS: Lower kidney function, estimated using cystatin C level, was associated with a linear and graded risk of infection-related hospitalization. These findings highlight that even moderate degrees of decreased kidney function are associated with clinically significant higher risks of serious infection in older individuals.
Keywords: Aged; Cohort Studies; Female; Glomerular Filtration Rate; Hospitalization; Humans; Infection; Kidney; Male; Risk Factors

Risk of intraparenchymal hemorrhage with magnetic resonance imaging-defined leukoaraiosis and brain infarcts. - Folsom, Aaron R; Yatsuya, Hiroshi; Mosley, Thomas H; Psaty, Bruce M; Longstreth, W T (Ann Neurol, 2012)
OBJECTIVE: To determine whether the burden of leukoaraiosis and the number of brain infarcts, defined by magnetic resonance imaging (MRI), are prospectively and independently associated with intraparenchymal hemorrhage (IPH) incidence in a pooled population-based study. METHODS: Among 4,872 participants initially free of clinical stroke in the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study, we assessed white matter grade (range, 0-9), reflecting increasing leukoaraiosis, and brain infarcts using MRI. Over a median of 13 years of follow-up, 71 incident, spontaneous IPH events occurred. RESULTS: After adjustment for other IPH risk factors, the hazard ratios (95% confidence intervals) across white matter grades 0 to 1, 2, 3, and 4 to 9 were 1.00, 1.68 (0.86-3.30), 3.52 (1.80-6.89), and 3.96 (1.90-8.27), respectively (p for trend <0.0001). These hazard ratios were weakened only modestly (p for trend = 0.0003) with adjustment for MRI-defined brain infarcts. The IPH hazard ratios for 0, 1, 2, or ≥3 MRI-defined brain infarcts were 1.00, 1.97 (1.10-3.54), 2.00 (0.83-4.78), and 3.12 (1.31-7.43) (p for trend = 0.002), but these were substantially attenuated when adjusted for white matter grade (p for trend = 0.049). INTERPRETATION: Greater MRI-defined burden of leukoaraiosis is a risk factor for spontaneous IPH. Spontaneous IPH should be added to the growing list of potential poor outcomes in people with leukoaraiosis.
Keywords: Cerebral Infarction; Cohort Studies; Female; Humans; Incidence; Intracranial Hemorrhages; Leukoaraiosis; Magnetic Resonance Imaging; Male; Middle Aged; Risk Factors

Serum 25-hydroxyvitamin D concentration and risk for major clinical disease events in a community-based population of older adults: a cohort study. - de Boer, Ian H; Levin, Gregory; Robinson-Cohen, Cassianne; Biggs, Mary L; Hoofnagle, Andy N; Siscovick, David S; Kestenbaum, Bryan (Ann Intern Med, 2012)
BACKGROUND: Circulating concentrations of 25-hydroxyvitamin D [25-(OH)D] are used to define vitamin D deficiency. Current clinical 25-(OH)D targets based on associations with intermediate markers of bone metabolism may not reflect optimal levels for other chronic diseases and do not account for known seasonal variation in 25-(OH)D concentration. OBJECTIVE: To evaluate the relationship of 25-(OH)D concentration with the incidence of major clinical disease events that are pathophysiologically relevant to vitamin D. DESIGN: Cohort study. SETTING: The Cardiovascular Health Study conducted in 4 U.S. communities. Data from 1992 to 2006 were included in this analysis. PARTICIPANTS: 1621 white older adults. MEASUREMENTS: Serum 25-(OH)D concentration (using a high-performance liquid chromatography-tandem mass spectrometry assay that conforms to National Institute of Standards and Technology reference standards) and associations with time to a composite outcome of incident hip fracture, myocardial infarction, cancer, or death. RESULTS: Over a median 11-year follow-up, the composite outcome occurred in 1018 participants (63%). Defining events included 137 hip fractures, 186 myocardial infarctions, 335 incidences of cancer, and 360 deaths. The association of low 25-(OH)D concentration with risk for the composite outcome varied by season (P = 0.057). A concentration lower than a season-specific Z score of -0.54 best discriminated risk for the composite outcome and was associated with a 24% higher risk in adjusted analyses (95% CI, 9% to 42%). Corresponding season-specific 25-(OH)D concentrations were 43, 50, 61, and 55 nmol/L (17, 20, 24, and 22 ng/mL) in winter, spring, summer, and autumn, respectively. LIMITATION: The observational study was restricted to white participants. CONCLUSION: Threshold concentrations of 25-(OH)D associated with increased risk for relevant clinical disease events center near 50 nmol/L (20 ng/mL). Season-specific targets for 25-(OH)D concentration may be more appropriate than static targets when evaluating health risk. PRIMARY FUNDING SOURCE: National Institutes of Health.
Keywords: Aged; Cause of Death; Female; Follow-Up Studies; Hip Fractures; Humans; Male; Myocardial Infarction; Neoplasms; Proportional Hazards Models; Risk Assessment; Risk Factors; Seasons; United States; Vitamin D; Vitamin D Deficiency

Subclinical thyroid dysfunction and the risk of heart failure events: an individual participant data analysis from 6 prospective cohorts. - Gencer, Bariş; Collet, Tinh-Hai; Virgini, Vanessa; Bauer, Douglas C; Gussekloo, Jacobijn; Cappola, Anne R; Nanchen, David; den Elzen, Wendy P J; Balmer, Philippe; Luben, Robert N; Iacoviello, Massimo; Triggiani, Vincenzo; et al. (Circulation, 2012)
BACKGROUND: American College of Cardiology/American Heart Association guidelines for the diagnosis and management of heart failure recommend investigating exacerbating conditions such as thyroid dysfunction, but without specifying the impact of different thyroid-stimulation hormone (TSH) levels. Limited prospective data exist on the association between subclinical thyroid dysfunction and heart failure events. METHODS AND RESULTS: We performed a pooled analysis of individual participant data using all available prospective cohorts with thyroid function tests and subsequent follow-up of heart failure events. Individual data on 25 390 participants with 216 248 person-years of follow-up were supplied from 6 prospective cohorts in the United States and Europe. Euthyroidism was defined as TSH of 0.45 to 4.49 mIU/L, subclinical hypothyroidism as TSH of 4.5 to 19.9 mIU/L, and subclinical hyperthyroidism as TSH <0.45 mIU/L, the last two with normal free thyroxine levels. Among 25 390 participants, 2068 (8.1%) had subclinical hypothyroidism and 648 (2.6%) had subclinical hyperthyroidism. In age- and sex-adjusted analyses, risks of heart failure events were increased with both higher and lower TSH levels (P for quadratic pattern <0.01); the hazard ratio was 1.01 (95% confidence interval, 0.81-1.26) for TSH of 4.5 to 6.9 mIU/L, 1.65 (95% confidence interval, 0.84-3.23) for TSH of 7.0 to 9.9 mIU/L, 1.86 (95% confidence interval, 1.27-2.72) for TSH of 10.0 to 19.9 mIU/L (P for trend <0.01) and 1.31 (95% confidence interval, 0.88-1.95) for TSH of 0.10 to 0.44 mIU/L and 1.94 (95% confidence interval, 1.01-3.72) for TSH <0.10 mIU/L (P for trend=0.047). Risks remained similar after adjustment for cardiovascular risk factors. CONCLUSION: Risks of heart failure events were increased with both higher and lower TSH levels, particularly for TSH ≥10 and <0.10 mIU/L.
Keywords: Adult; Aged; Aged, 80 and over; Comorbidity; Female; Follow-Up Studies; Heart Failure; Humans; Hypothyroidism; Male; Middle Aged; Prospective Studies; Risk; Risk Factors; Sensitivity and Specificity; Thyrotropin; Thyroxine

Total and high-molecular-weight adiponectin and risk of incident diabetes in older people. - Kizer, Jorge R; Arnold, Alice M; Benkeser, David; Ix, Joachim H; Djoussé, Luc; Zieman, Susan J; Barzilay, Joshua I; Tracy, Russell P; Mantzoros, Christos S; Siscovick, David S; Mukamal, Kenneth J (Diabetes Care, 2012)
OBJECTIVE: To delineate the associations of total adiponectin, high-molecular-weight (HMW) adiponectin, and the HMW-to-total adiponectin ratio with diabetes in older adults. RESEARCH DESIGN AND METHODS: Total and HMW adiponectin were measured in a population-based study of older adults. The relations of total adiponectin, HMW adiponectin, and their ratio with incident diabetes (n = 309) were assessed in 3,802 individuals. RESULTS: Total and HMW adiponectin were highly correlated (r = 0.94). Analysis using cubic splines revealed that the associations between total and HMW adiponectin and new-onset diabetes were not linear. Specifically, after adjustment for confounders, there were similar inverse relationships for total (hazard ratio per SD 0.49 [95% CI 0.39-0.63]) and HMW adiponectin (0.42 [0.32-0.56]) with diabetes up to values of 20 and 10 mg/L, respectively, above which the associations plateaued. These associations persisted after adjustment for potential mediators (blood pressure, lipids, C-reactive protein, and homeostasis model assessment of insulin resistance [HOMA-IR]). There was, however, evidence of interaction by HOMA-IR in the lower range of adiponectin, with stronger inverse associations among insulin-sensitive than insulin-resistant participants. HMW-to-total adiponectin ratio showed a linear adjusted association with outcome, but this was abolished by inclusion of mediating variables. CONCLUSIONS: In this older cohort, increasing concentrations of total and HMW adiponectin were associated with comparably lower risks of diabetes, but these associations leveled off with further increases above concentrations of 20 and 10 mg/L, respectively. The more pronounced risk decreases at the lower range among participants without insulin resistance support a role for adiponectin that is independent of baseline hyperinsulinemia, but this will require further investigation.
Keywords: Adiponectin; Aged; Diabetes Mellitus; Female; Humans; Male; Risk Factors

Trans-fatty acid consumption and heart rate variability in 2 separate cohorts of older and younger adults. - Soares-Miranda, Luisa; Stein, Phyllis K; Imamura, Fumiaki; Sattelmair, Jacob; Lemaitre, Rozenn N; Siscovick, David S; Mota, Jorge; Mozaffarian, Dariush (Circ Arrhythm Electrophysiol, 2012)
BACKGROUND: Trans-fatty acid (TFA) consumption is associated with risk of coronary heart disease, and trans-18:2, but not trans-18:1, in red blood cell membranes has been associated with sudden cardiac arrest. Abnormal heart rate variability (HRV) reflects autonomic dysfunction and predicts cardiac death. Relationships between TFA consumption and HRV remain understudied. We determined whether total TFA consumption, as well as trans-18:1 and trans-18:2 TFA consumption, was independently associated with HRV in 2 independent cohorts in the United States and Portugal. METHODS AND RESULTS: In 2 independent cohorts of older US adults (Cardiovascular Health Study [CHS], age 72±5 years, 1989/1995) and young Portuguese adults (Porto, age 19±2 years, 2008/2010), we assessed habitual TFA intake by food frequency questionnaires in CHS (separately estimating trans-18:1 and trans-18:2) and multiple 24-hour recalls in Porto (estimating total TFA only, which in a subset correlated with circulating trans-18:2 but not trans-18:1, suggesting that we captured the former). HRV was assessed using 24-hour Holters in CHS (n=1076) and repeated short-term (5-minute) ECGs in Porto (n=160). We used multivariate-adjusted linear regression to relate TFA consumption to HRV cross-sectionally (CHS, Porto) and longitudinally (CHS). In CHS, higher trans-18:2 consumption was associated with lower 24-hour SD of all normal-to-normal intervals both cross-sectionally (-12%; 95% CI, -19% to -6%; P=0.001) and longitudinally (-15%; 95% CI, -25% to -4%; P= 0.009) and lower 24-hour SD of 5-minute average N-N intervals and mean of the 5-minute SD of N-N intervals calculated over 24 hours (P<0.05 each). Higher trans-18:1 consumption in CHS was associated with more favorable 24-hour HRV in particular time-domain indices (24-hour SD of all normal-to-normal intervals, SD of 5-minute average N-N intervals, mean of the 5-minute SD of N-N intervals calculated over 24 hours; P<0.05 each). In Porto, each higher SD TFA consumption was associated with 4% lower 5-minute 24-hour SD of all normal-to-normal intervals (95% CI, -8% to -1%; P=0.04) and 7% lower 5-minute square root of the mean of the squares of successive N-N differences (95% CI, -13% to -1%; P=0.04). CONCLUSIONS: Trans-18:2 consumption is associated with specific, less favorable indices of HRV in both older and young adults. Trans-18:1 consumption is associated with more favorable HRV indices in older adults. Our results support the need to investigate potential HRV-related mechanisms, whereby trans-18:2 may increase arrhythmic risk.
Keywords: Adolescent; Age Factors; Aged; Aging; Arrhythmias, Cardiac; Cohort Studies; Cross-Sectional Studies; Dietary Fats; Electrocardiography, Ambulatory; Feeding Behavior; Female; Heart Rate; Humans; Linear Models; Longitudinal Studies; Male; Multivariate Analysis; Portugal; Predictive Value of Tests; Prospective Studies; Risk Assessment; Risk Factors; Surveys and Questionnaires; Trans Fatty Acids; United States; Young Adult

Adiposity and cognitive decline in the cardiovascular health study. - Luchsinger, José A; Biggs, Mary L; Kizer, Jorge R; Barzilay, Joshua; Fitzpatrick, Annette; Newman, Anne; Longstreth, William T; Lopez, Oscar; Siscovick, David; Kuller, Lewis (Neuroepidemiology, 2013)
BACKGROUND: Studies relating adiposity to cognition in the elderly show conflicting results, which may be explained by the choice of adiposity measures. Thus, we studied the longitudinal associations of different adiposity measures, fat mass by bioelectrical impedance analysis, body mass index (BMI) and waist circumference (WC), with cognitive performance in the Cardiovascular Health Study. METHODS: Cognitive performance was assessed with the modified Mini-Mental State Examination, the Digit Symbol Substitution Test, and a composite of both. We used linear mixed models to estimate rates of change in cognitive function scores associated with adiposity measured at baseline. RESULTS: The final sample was comprised of 2,681 women (57.9%) and 1,949 men (42.1%) aged 73 ± 5.2 and 73.9 ± 5.6 years, respectively. Adiposity was associated with slower cognitive decline in most analyses. Results were similar for fat mass, BMI and WC. Higher fat-free mass was also related to slower cognitive decline. Results were similar in analyses excluding persons with cancer, smokers, and persons with short follow-up, poor self-reported health, or persons with cardiovascular disease. CONCLUSIONS: Higher adiposity and higher fat-free mass in the elderly was related to better cognitive performance. This finding was not explained by confounding by preexisting conditions.
Keywords: Adiposity; Aged; Aged, 80 and over; Body Mass Index; Cardiovascular Diseases; Cognition Disorders; Electric Impedance; Female; Humans; Male; Risk Factors; Waist Circumference; Waist-Hip Ratio

Albuminuria is associated with hip fracture risk in older adults: the cardiovascular health study. - Barzilay, J I; Bůžková, P; Chen, Z; de Boer, I H; Carbone, L; Rassouli, N N; Fink, H A; Robbins, J A (Osteoporos Int, 2013)
UNLABELLED: The microcirculation plays an important role in bone health. Here, we examine whether albuminuria, a marker of renal microvascular disease, is associated with the risk of hip fracture in older adults (age, 78 years). We find a small independent association in women but not in men. INTRODUCTION: The microvascular circulation plays an important role in bone physiology. Two studies of middle-aged adults have found that albuminuria (>30 mg albumin/g creatinine), a disorder of the renal microvasculature, is associated with fracture risk. Here, we examine whether albuminuria is related to hip fracture risk and reduced hip bone mineral density (BMD) in older adults with a mean age of 78 years. METHODS: From the Cardiovascular Health Study (41 % male), 3,110 adults with albuminuria testing were followed up for incident hip fracture for up to 9.5 years. BMD was performed in a subset of 1,208 participants. RESULTS: There were 313 hip fractures during follow-up (7.7 % of men; 11.7 % of women). The incidence rate for men, with and without albuminuria, was 1.43 and 0.93/100 person-years of follow-up (p = 0.02); for women, 1.84 and 1.33 (p = 0.04). After adjustment for osteoporosis-related factors, frailty and falling, a doubling of albuminuria was significantly associated with hip fracture risk in women (hazard ratio, 1.12, 95 % CI, 1.001-1.25), but not in men. In the subcohort with BMD measurement, increased urine albumin levels were significantly associated with decreased total hip BMD in men (-0.009 g calcium/cm(2) (-0.017, -0.001); p = 0.04), but not in women. CONCLUSIONS: In older women, albuminuria is associated with a small, but statistically significant, increased risk of hip fracture independent of other explanatory factors. No such risk appears to be present in men, although their total hip BMD is lower in association with albuminuria.
Keywords: Aged; Aged, 80 and over; Albuminuria; Bone Density; Female; Follow-Up Studies; Hip Fractures; Hip Joint; Humans; Incidence; Kaplan-Meier Estimate; Male; Osteoporotic Fractures; Risk Factors; Sex Factors; United States

Association of genome-wide variation with highly sensitive cardiac troponin-T levels in European Americans and Blacks: a meta-analysis from atherosclerosis risk in communities and cardiovascular health studies. - Yu, Bing; Barbalic, Maja; Brautbar, Ariel; Nambi, Vijay; Hoogeveen, Ron C; Tang, Weihong; Mosley, Thomas H; Rotter, Jerome I; deFilippi, Christopher R; O'Donnell, Christopher J; Kathiresan, Sekar; Rice, Ken; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND: High levels of cardiac troponin T, measured by a highly sensitive assay (hs-cTnT), are strongly associated with incident coronary heart disease and heart failure. To date, no large-scale genome-wide association study of hs-cTnT has been reported. We sought to identify novel genetic variants that are associated with hs-cTnT levels. METHODS AND RESULTS: We performed a genome-wide association in 9491 European Americans and 2053 blacks free of coronary heart disease and heart failure from 2 prospective cohorts: the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. Genome-wide association studies were conducted in each study and race stratum. Fixed-effect meta-analyses combined the results of linear regression from 2 cohorts within each race stratum and then across race strata to produce overall estimates and probability values. The meta-analysis identified a significant association at chromosome 8q13 (rs10091374; P=9.06×10(-9)) near the nuclear receptor coactivator 2 (NCOA2) gene. Overexpression of NCOA2 can be detected in myoblasts. An additional analysis using logistic regression and the clinically motivated 99th percentile cut point detected a significant association at 1q32 (rs12564445; P=4.73×10(-8)) in the gene TNNT2, which encodes the cardiac troponin T protein itself. The hs-cTnT-associated single-nucleotide polymorphisms were not associated with coronary heart disease in a large case-control study, but rs12564445 was significantly associated with incident heart failure in Atherosclerosis Risk in Communities Study European Americans (hazard ratio=1.16; P=0.004). CONCLUSIONS: We identified 2 loci, near NCOA2 and in the TNNT2 gene, at which variation was significantly associated with hs-cTnT levels. Further use of the new assay should enable replication of these results.
Keywords: African Continental Ancestry Group; Atherosclerosis; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Nuclear Receptor Coactivator 2; Polymorphism, Single Nucleotide; Prospective Studies; Residence Characteristics; Risk Factors; Troponin T

Associations of plasma phospholipid and dietary alpha linolenic acid with incident atrial fibrillation in older adults: the Cardiovascular Health Study. - Fretts, Amanda M; Mozaffarian, Dariush; Siscovick, David S; Heckbert, Susan R; McKnight, Barbara; King, Irena B; Rimm, Eric B; Psaty, Bruce M; Sacks, Frank M; Song, Xiaoling; Spiegelman, Donna; Lemaitre, Rozenn N (J Am Heart Assoc, 2013)
BACKGROUND: Few studies have examined the relationship of α-linolenic acid (ALA 18:3n-3), an intermediate-chain essential n-3 polyunsaturated fatty acid derived from plants and vegetable oils, with incident atrial fibrillation (AF). METHODS AND RESULTS: The study population included participants from the Cardiovascular Health Study, a community-based longitudinal cohort of adults aged 65 or older, free of prevalent coronary heart disease and atrial fibrillation. We assessed the associations of plasma phospholipid and dietary ALA with incident AF using Cox regression. The biomarker analysis comprised a total of 2899 participants, and the dietary analysis comprised 4337 participants. We found no association of plasma phospholipid ALA and incident AF. Comparing each of the second, third, and fourth quartiles to the lowest quartile, the hazard ratios for AF were 1.11 (95% CI, 0.90 to 1.37), 1.09 (95% CI, 0.88 to 1.35), and 0.92 (95% CI, 0.74 to 1.15), after adjustment for age, sex, race, clinic, education, smoking, alcohol, body mass index, waist circumference, diabetes, heart failure, stroke, treated hypertension, and physical activity (P trend=0.48). When dietary ALA was considered the exposure of interest, results were similar. CONCLUSIONS: Results from this prospective cohort study of older adults indicate no association of plasma phospholipid or dietary ALA and incident AF.
Keywords: Age Factors; Aged; Aged, 80 and over; alpha-Linolenic Acid; Atrial Fibrillation; Biomarkers; Diet; Female; Humans; Incidence; Linear Models; Longitudinal Studies; Male; Nutritional Status; Phospholipids; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Atrial fibrillation and the risk of sudden cardiac death: the atherosclerosis risk in communities study and cardiovascular health study. - Chen, Lin Y; Sotoodehnia, Nona; Bůzková, Petra; Lopez, Faye L; Yee, Laura M; Heckbert, Susan R; Prineas, Ronald; Soliman, Elsayed Z; Adabag, Selcuk; Konety, Suma; Folsom, Aaron R; Siscovick, David; et al. (JAMA Intern Med, 2013)
BACKGROUND: It is unknown whether atrial fibrillation (AF) is associated with an increased risk of sudden cardiac death (SCD) in the general population. This association was examined in 2 population-based cohorts. METHODS: In the Atherosclerosis Risk in Communities (ARIC) Study, we analyzed data from 15 439 participants (baseline age, 45-64 years; 55.2% women; and 26.6% black) from baseline (1987-1989) through December 31, 2001. In the Cardiovascular Health Study (CHS), we analyzed data from 5479 participants (baseline age, ≥65 years; 58.2% women; and 15.4% black) from baseline (first cohort, 1989-1990; second cohort, 1992-1993) through December 31, 2006. The main outcome was physician-adjudicated SCD, defined as death from a sudden, pulseless condition presumed to be due to a ventricular tachyarrhythmia. The secondary outcome was non-SCD (NSCD), defined as coronary heart disease death not meeting SCD criteria. We used Cox proportional hazards models to assess the association between AF and SCD/NSCD, adjusting for baseline demographic and cardiovascular risk factors. RESULTS: In the ARIC Study, 894 AF, 269 SCD, and 233 NSCD events occurred during follow-up (median, 13.1 years). The crude incidence rates of SCD were 2.89 per 1000 person-years (with AF) and 1.30 per 1000 person-years (without AF). The multivariable hazard ratios (HRs) (95% CIs) of AF for SCD and NSCD were 3.26 (2.17-4.91) and 2.43 (1.60-3.71), respectively. In the CHS, 1458 AF, 292 SCD, and 581 NSCD events occurred during follow-up (median, 13.1 years). The crude incidence rates of SCD were 12.00 per 1000 person-years (with AF) and 3.82 per 1000 person-years (without AF). The multivariable HRs (95% CIs) of AF for SCD and NSCD were 2.14 (1.60-2.87) and 3.10 (2.58-3.72), respectively. The meta-analyzed HRs (95% CIs) of AF for SCD and NSCD were 2.47 (1.95-3.13) and 2.98 (2.52-3.53), respectively. CONCLUSIONS: Incident AF is associated with an increased risk of SCD and NSCD in the general population. Additional research to identify predictors of SCD in patients with AF is warranted.
Keywords: Aged; Atrial Fibrillation; Cardiovascular Diseases; Death, Sudden, Cardiac; Demography; Ethnic Groups; Female; Humans; Incidence; Male; Middle Aged; Proportional Hazards Models; Risk Assessment; Risk Factors; Sex Factors; United States

Bidirectional relationship between cognitive function and pneumonia. - Shah, Faraaz Ali; Pike, Francis; Alvarez, Karina; Angus, Derek; Newman, Anne B; Lopez, Oscar; Tate, Judith; Kapur, Vishesh; Wilsdon, Anthony; Krishnan, Jerry A; Hansel, Nadia; Au, David; et al. (Am J Respir Crit Care Med, 2013)
RATIONALE: Relationships between chronic health conditions and acute infections remain poorly understood. Preclinical studies suggest crosstalk between nervous and immune systems. OBJECTIVES: To determine bidirectional relationships between cognition and pneumonia. METHODS: We conducted longitudinal analyses of a population-based cohort over 10 years. We determined whether changes in cognition increase risk of pneumonia hospitalization by trajectory analyses and joint modeling. We then determined whether pneumonia hospitalization increased risk of subsequent dementia using a Cox model with pneumonia as a time-varying covariate. MEASUREMENTS AND MAIN RESULTS: Of the 5,888 participants, 639 (10.9%) were hospitalized with pneumonia at least once. Most participants had normal cognition before pneumonia. Three cognition trajectories were identified: no, minimal, and severe rapid decline. A greater proportion of participants hospitalized with pneumonia were on trajectories of minimal or severe decline before occurrence of pneumonia compared with those never hospitalized with pneumonia (proportion with no, minimal, and severe decline were 67.1%, 22.8%, and 10.0% vs. 76.0%, 19.3%, and 4.6% for participants with and without pneumonia, respectively; P < 0.001). Small subclinical changes in cognition increased risk of pneumonia, even in those with normal cognition and physical function before pneumonia (β = -0.02; P < 0.001). Participants with pneumonia were subsequently at an increased risk of dementia (hazard ratio, 2.24 [95% confidence interval, 1.62-3.11]; P = 0.01). Associations were independent of demographics, health behaviors, other chronic conditions, and physical function. Bidirectional relationship did not vary based on severity of disease, and similar associations were noted for those with severe sepsis and other infections. CONCLUSIONS: A bidirectional relationship exists between pneumonia and cognition and may explain how a single episode of infection in well-appearing older individuals accelerates decline in chronic health conditions and loss of functional independence.
Keywords: Aged; Cognition Disorders; Dementia; Female; Hospitalization; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Pneumonia; Proportional Hazards Models; Risk Factors

Circulating 25-hydroxyvitamin D is associated with insulin resistance cross-sectionally but not longitudinally in older adults: The Cardiovascular Health Study. - Danziger, John; Biggs, Mary L; Niemi, Matt; Ix, Joachim H; Kizer, Jorge R; Djoussé, Luc; de Boer, Ian H; Siscovick, David S; Kestenbaum, Bryan; Mukamal, Kenneth J (Metabolism, 2013)
BACKGROUND: Despite extensive study, the role of vitamin D in insulin resistance and secretion remains unclear. OBJECTIVE: To examine the cross-sectional and longitudinal relationships between 25-hydroxyvitamin D (25(OH)D) concentrations and indices of insulin resistance and secretion in older adults. METHODS AND RESULTS: Among 2134 participants of the Cardiovascular Health Study who were free from cardiovascular disease, we measured serum 25(OH)D concentrations in samples collected in 1992-1993. We examined insulin resistance and secretion using Homeostasis Model Assessment (HOMA) estimates cross-sectionally and among 1469 participants who had repeated HOMA measures four years later (1996-1997). In cross-sectional analysis, each 10 ng/mL increment in 25(OH)D concentration was associated with a 0.09 lower adjusted HOMA-IR [95% CI (-0.17, -0.02), p=0.01]. However, baseline 25(OH)D concentrations were not associated with change in HOMA-IR over 4 years of follow up (p=0.48). 25(OH)D concentrations were not associated with insulin secretion, as determined by HOMA-β, in either cross-sectional or longitudinal analysis. CONCLUSIONS: Circulating 25(OH)D concentrations are associated with lower insulin resistance in cross-sectional but not longitudinal analyses. Whether this reflects residual confounding in cross-sectional analyses or the short-term nature of the relationship between vitamin D and insulin sensitivity will require trials with repeated measures of these factors.
Keywords: Adiposity; Aged; Anthropometry; Cardiovascular Diseases; Cross-Sectional Studies; Exercise; Female; Humans; Hydroxycholecalciferols; Inflammation; Insulin; Insulin Resistance; Longitudinal Studies; Male; Middle Aged; Obesity; Risk Factors; Surveys and Questionnaires

Common carotid intima-media thickness does not add to Framingham risk score in individuals with diabetes mellitus: the USE-IMT initiative. - den Ruijter, H M; Peters, S A E; Groenewegen, K A; Anderson, T J; Britton, A R; Dekker, J M; Engstrom, G; Eijkemans, M J; Evans, G W; de Graaf, J; Grobbee, D E; Hedblad, B; et al. (Diabetologia, 2013)
AIMS/HYPOTHESIS: The aim of this work was to investigate whether measurement of the mean common carotid intima-media thickness (CIMT) improves cardiovascular risk prediction in individuals with diabetes. METHODS: We performed a subanalysis among 4,220 individuals with diabetes in a large ongoing individual participant data meta-analysis involving 56,194 subjects from 17 population-based cohorts worldwide. We first refitted the risk factors of the Framingham heart risk score on the individuals without previous cardiovascular disease (baseline model) and then expanded this model with the mean common CIMT (CIMT model). The absolute 10 year risk for developing a myocardial infarction or stroke was estimated from both models. In individuals with diabetes we compared discrimination and calibration of the two models. Reclassification of individuals with diabetes was based on allocation to another cardiovascular risk category when mean common CIMT was added. RESULTS: During a median follow-up of 8.7 years, 684 first-time cardiovascular events occurred among the population with diabetes. The C statistic was 0.67 for the Framingham model and 0.68 for the CIMT model. The absolute 10 year risk for developing a myocardial infarction or stroke was 16% in both models. There was no net reclassification improvement with the addition of mean common CIMT (1.7%; 95% CI -1.8, 3.8). There were no differences in the results between men and women. CONCLUSIONS/INTERPRETATION: There is no improvement in risk prediction in individuals with diabetes when measurement of the mean common CIMT is added to the Framingham risk score. Therefore, this measurement is not recommended for improving individual cardiovascular risk stratification in individuals with diabetes.
Keywords: Cardiovascular Diseases; Carotid Intima-Media Thickness; Diabetes Mellitus; Humans; Myocardial Infarction; Risk Factors; Stroke

Common genetic loci influencing plasma homocysteine concentrations and their effect on risk of coronary artery disease. - van Meurs, Joyce B J; Paré, Guillaume; Schwartz, Stephen M; Hazra, Aditi; Tanaka, Toshiko; Vermeulen, Sita H; Cotlarciuc, Ioana; Yuan, Xin; Mälarstig, Anders; Bandinelli, Stefania; Bis, Joshua C; Blom, Henk; et al. (Am J Clin Nutr, 2013)
BACKGROUND: The strong observational association between total homocysteine (tHcy) concentrations and risk of coronary artery disease (CAD) and the null associations in the homocysteine-lowering trials have prompted the need to identify genetic variants associated with homocysteine concentrations and risk of CAD. OBJECTIVE: We tested whether common genetic polymorphisms associated with variation in tHcy are also associated with CAD. DESIGN: We conducted a meta-analysis of genome-wide association studies (GWAS) on tHcy concentrations in 44,147 individuals of European descent. Polymorphisms associated with tHcy (P < 10(⁻⁸) were tested for association with CAD in 31,400 cases and 92,927 controls. RESULTS: Common variants at 13 loci, explaining 5.9% of the variation in tHcy, were associated with tHcy concentrations, including 6 novel loci in or near MMACHC (2.1 × 10⁻⁹), SLC17A3 (1.0 × 10⁻⁸), GTPB10 (1.7 × 10⁻⁸), CUBN (7.5 × 10⁻¹⁰), HNF1A (1.2 × 10⁻¹²)), and FUT2 (6.6 × 10⁻⁹), and variants previously reported at or near the MTHFR, MTR, CPS1, MUT, NOX4, DPEP1, and CBS genes. Individuals within the highest 10% of the genotype risk score (GRS) had 3-μmol/L higher mean tHcy concentrations than did those within the lowest 10% of the GRS (P = 1 × 10⁻³⁶). The GRS was not associated with risk of CAD (OR: 1.01; 95% CI: 0.98, 1.04; P = 0.49). CONCLUSIONS: We identified several novel loci that influence plasma tHcy concentrations. Overall, common genetic variants that influence plasma tHcy concentrations are not associated with risk of CAD in white populations, which further refutes the causal relevance of moderately elevated tHcy concentrations and tHcy-related pathways for CAD.
Keywords: Coronary Artery Disease; Genes; Genetic Loci; Genetic Predisposition to Disease; Genotype; Homocysteine; Humans; Polymorphism, Genetic; Risk Factors

Common variants associated with plasma triglycerides and risk for coronary artery disease. - Do, Ron; Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Gao, Chi; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; et al. (Nat Genet, 2013)
Triglycerides are transported in plasma by specific triglyceride-rich lipoproteins; in epidemiological studies, increased triglyceride levels correlate with higher risk for coronary artery disease (CAD). However, it is unclear whether this association reflects causal processes. We used 185 common variants recently mapped for plasma lipids (P < 5 × 10(-8) for each) to examine the role of triglycerides in risk for CAD. First, we highlight loci associated with both low-density lipoprotein cholesterol (LDL-C) and triglyceride levels, and we show that the direction and magnitude of the associations with both traits are factors in determining CAD risk. Second, we consider loci with only a strong association with triglycerides and show that these loci are also associated with CAD. Finally, in a model accounting for effects on LDL-C and/or high-density lipoprotein cholesterol (HDL-C) levels, the strength of a polymorphism's effect on triglyceride levels is correlated with the magnitude of its effect on CAD risk. These results suggest that triglyceride-rich lipoproteins causally influence risk for CAD.
Keywords: Biological Transport; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Humans; Polymorphism, Single Nucleotide; Risk Factors; Triglycerides

Effects of smoking on the genetic risk of obesity: the population architecture using genomics and epidemiology study. - Fesinmeyer, Megan D; North, Kari E; Lim, Unhee; Bůzková, Petra; Crawford, Dana C; Haessler, Jeffrey; Gross, Myron D; Fowke, Jay H; Goodloe, Robert; Love, Shelley-Ann; Graff, Misa; Carlson, Christopher S; et al. (BMC Med Genet, 2013)
BACKGROUND: Although smoking behavior is known to affect body mass index (BMI), the potential for smoking to influence genetic associations with BMI is largely unexplored. METHODS: As part of the 'Population Architecture using Genomics and Epidemiology (PAGE)' Consortium, we investigated interaction between genetic risk factors associated with BMI and smoking for 10 single nucleotide polymorphisms (SNPs) previously identified in genome-wide association studies. We included 6 studies with a total of 56,466 subjects (16,750 African Americans (AA) and 39,716 European Americans (EA)). We assessed effect modification by testing an interaction term for each SNP and smoking (current vs. former/never) in the linear regression and by stratified analyses. RESULTS: We did not observe strong evidence for interactions and only observed two interactions with p-values <0.1: for rs6548238/TMEM18, the risk allele (C) was associated with BMI only among AA females who were former/never smokers (β = 0.018, p = 0.002), vs. current smokers (β = 0.001, p = 0.95, p(interaction) = 0.10). For rs9939609/FTO, the A allele was more strongly associated with BMI among current smoker EA females (β = 0.017, p = 3.5 x 10(-5)), vs. former/never smokers (β = 0.006, p = 0.05, p(interaction) = 0.08). CONCLUSIONS: These analyses provide limited evidence that smoking status may modify genetic effects of previously identified genetic risk factors for BMI. Larger studies are needed to follow up our results. CLINICAL TRIAL REGISTRATION: NCT00000611.
Keywords: Adolescent; Adult; African Americans; Aged; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Mass Index; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Male; Membrane Proteins; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins; Risk Factors; Smoking; Young Adult

Epidemiology and long-term clinical and biologic risk factors for pneumonia in community-dwelling older Americans: analysis of three cohorts. - Yende, Sachin; Alvarez, Karina; Loehr, Laura; Folsom, Aaron R; Newman, Anne B; Weissfeld, Lisa A; Wunderink, Richard G; Kritchevsky, Stephen B; Mukamal, Kenneth J; London, Stephanie J; Harris, Tamara B; Bauer, Doug C; et al. (Chest, 2013)
BACKGROUND: Preventing pneumonia requires better understanding of incidence, mortality, and long-term clinical and biologic risk factors, particularly in younger individuals. METHODS: This was a cohort study in three population-based cohorts of community-dwelling individuals. A derivation cohort (n = 16,260) was used to determine incidence and survival and develop a risk prediction model. The prediction model was validated in two cohorts (n = 8,495). The primary outcome was 10-year risk of pneumonia hospitalization. RESULTS: The crude and age-adjusted incidences of pneumonia were 6.71 and 9.43 cases/1,000 person-years (10-year risk was 6.15%). The 30-day and 1-year mortality were 16.5% and 31.5%. Although age was the most important risk factor (range of crude incidence rates, 1.69-39.13 cases/1,000 person-years for each 5-year increment from 45-85 years), 38% of pneumonia cases occurred in adults < 65 years of age. The 30-day and 1-year mortality were 12.5% and 25.7% in those < 65 years of age. Although most comorbidities were associated with higher risk of pneumonia, reduced lung function was the most important risk factor (relative risk = 6.61 for severe reduction based on FEV1 by spirometry). A clinical risk prediction model based on age, smoking, and lung function predicted 10-year risk (area under curve [AUC] = 0.77 and Hosmer-Lemeshow [HL] C statistic = 0.12). Model discrimination and calibration were similar in the internal validation cohort (AUC = 0.77; HL C statistic, 0.65) but lower in the external validation cohort (AUC = 0.62; HL C statistic, 0.45). The model also calibrated well in blacks and younger adults. C-reactive protein and IL-6 were associated with higher pneumonia risk but did not improve model performance. CONCLUSIONS: Pneumonia hospitalization is common and associated with high mortality, even in younger healthy adults. Long-term risk of pneumonia can be predicted in community-dwelling adults with a simple clinical risk prediction model.
Keywords: Age Factors; Aged; Aged, 80 and over; Community-Acquired Infections; Comorbidity; Female; Follow-Up Studies; Hospitalization; Humans; Incidence; Male; Middle Aged; Pneumonia; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; Survival Rate; Time Factors

Evaluating subject-level incremental values of new markers for risk classification rule. - Cai, T; Tian, L; Lloyd-Jones, D; Wei, L J (Lifetime Data Anal, 2013)
Suppose that we need to classify a population of subjects into several well-defined ordered risk categories for disease prevention or management with their "baseline" risk factors/markers. In this article, we present a systematic approach to identify subjects using their conventional risk factors/markers who would benefit from a new set of risk markers for more accurate classification. Specifically for each subgroup of individuals with the same conventional risk estimate, we present inference procedures for the reclassification and the corresponding correct re-categorization rates with the new markers. We then apply these new tools to analyze the data from the Cardiovascular Health Study sponsored by the US National Heart, Lung, and Blood Institute. We used Framingham risk factors plus the information of baseline anti-hypertensive drug usage to identify adult American women who may benefit from the measurement of a new blood biomarker, CRP, for better risk classification in order to intensify prevention of coronary heart disease for the subsequent 10 years.
Keywords: Aged; Antihypertensive Agents; Biomarkers; Biostatistics; C-Reactive Protein; Confidence Intervals; Coronary Disease; Female; Humans; Risk; Risk Factors; Statistics, Nonparametric; United States

Exploring psychosocial pathways between neighbourhood characteristics and stroke in older adults: the cardiovascular health study. - Yan, Tingjian; Escarce, José J; Liang, Li-Jung; Longstreth, W T; Merkin, Sharon Stein; Ovbiagele, Bruce; Vassar, Stefanie D; Seeman, Teresa; Sarkisian, Catherine; Brown, Arleen F (Age Ageing, 2013)
OBJECTIVES: to investigate whether psychosocial pathways mediate the association between neighbourhood socioeconomic disadvantage and stroke. METHODS: prospective cohort study with a follow-up of 11.5 years. SETTING: the Cardiovascular Health Study, a longitudinal population-based cohort study of older adults ≥65 years. MEASUREMENTS: the primary outcome was adjudicated incident ischaemic stroke. Neighbourhood socioeconomic status (NSES) was measured using a composite of six census-tract variables. Psychosocial factors were assessed with standard measures for depression, social support and social networks. RESULTS: of the 3,834 white participants with no prior stroke, 548 had an incident ischaemic stroke over the 11.5-year follow-up. Among whites, the incident stroke hazard ratio (HR) associated with living in the lowest relative to highest NSES quartile was 1.32 (95% CI = 1.01-1.73), in models adjusted for individual SES. Additional adjustment for psychosocial factors had a minimal effect on hazard of incident stroke (HR = 1.31, CI = 1.00-1.71). Associations between NSES and stroke incidence were not found among African-Americans (n = 785) in either partially or fully adjusted models. CONCLUSIONS: psychosocial factors played a minimal role in mediating the effect of NSES on stroke incidence among white older adults.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Aging; Brain Ischemia; Depression; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Linear Models; Logistic Models; Male; Middle Aged; Proportional Hazards Models; Prospective Studies; Residence Characteristics; Risk Assessment; Risk Factors; Social Support; Socioeconomic Factors; Stroke; Time Factors; United States; Vulnerable Populations

Fatty acid-binding protein 4 and incident heart failure: the Cardiovascular Health Study. - Djoussé, Luc; Bartz, Traci M; Ix, Joachim H; Kochar, Jinesh; Kizer, Jorge R; Gottdiener, John S; Tracy, Russell P; Mozaffarian, Dariush; Siscovick, David S; Mukamal, Kenneth J; Zieman, Susan J (Eur J Heart Fail, 2013)
AIM: To examine the association of plasma fatty acid-binding protein 4 (FABP4) with incident heart failure. METHODS AND RESULTS: In a prospective study of 4179 participants from the Cardiovascular Health Study, we measured plasma FABP4 on blood specimens collected between 1992 and 1993. Incident heart failure was adjudicated by an endpoint committee and we used a Cox proportional hazards model to calculate hazard ratios (HRs) of heart failure. The average age at baseline was 75 years. During a median follow-up of 10.7 years, 1182 cases of incident heart failure occurred. We observed a positive association between FABP4 and heart failure in the minimally adjusted models [HR 1.32, 95% confidence interval (CI) 1.25-1.38 per 1 SD higher FABP4] that was attenuated upon adjustment for potential confounders, mostly kidney function and body mass index (corresponding HR 1.09, 95% CI 1.01-1.17). In a subsample of heart failure cases with available data on LV systolic function, FABP4 was not associated with heart failure with or without preserved LV systolic function. Exclusion of people with unintentional weight loss and self-reported fair/poor health status did not alter the conclusion. CONCLUSION: An elevated plasma concentration of FABP4 was associated with a modestly higher risk of heart failure in older adults in the USA after adjustment for confounding factors.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Fatty Acid-Binding Proteins; Female; Follow-Up Studies; Glomerular Filtration Rate; Heart Failure; Humans; Male; Proportional Hazards Models; Prospective Studies; Risk Factors; United States; Ventricular Function, Left

Fetuin-A, type 2 diabetes, and risk of cardiovascular disease in older adults: the cardiovascular health study. - Jensen, Majken K; Bartz, Traci M; Mukamal, Kenneth J; Djoussé, Luc; Kizer, Jorge R; Tracy, Russell P; Zieman, Susan J; Rimm, Eric B; Siscovick, David S; Shlipak, Michael; Ix, Joachim H (Diabetes Care, 2013)
OBJECTIVE: Fetuin-A, a hepatic secretory protein that simultaneously inhibits arterial calcification and insulin action, is associated with type 2 diabetes, but its association with cardiovascular disease (CVD) is uncertain. Preliminary studies suggest that the association of fetuin-A with CVD might differ among individuals with or without type 2 diabetes. RESEARCH DESIGN AND METHODS: This was a prospective study of 3,810 community-living individuals older than 65 years (511 with type 2 diabetes) and free of CVD in 1992 when fetuin-A levels were measured. Participants were followed-up for incident CVD through June 2008. RESULTS: Mean age was 75 years, and 61% were women; 1,456 participants had an incident CVD event (248 among individuals with type 2 diabetes). The association of fetuin-A with CVD was modified by type 2 diabetes (P interaction = 0.02). Higher fetuin-A was associated with lower CVD risk among persons without type 2 diabetes [hazard ratio per SD 0.1 g/L higher fetuin-A, 0.93 (95% CI, 0.88-0.99)], whereas a trend in the opposite direction was observed among individuals with type 2 diabetes, although it was not statistically significant [1.07 (0.93-1.22)]. Among individuals without type 2 diabetes, similar effect modification was observed by obesity and insulin resistance. Consistently, higher fetuin-A was associated with lower CVD risk only in the subgroups without obesity or with HOMA-IR below the median [0.91 (0.85-0.97) and 0.87 (0.79-0.95), respectively]. CONCLUSIONS: The association of fetuin-A with risk of CVD differs among elderly individuals with and without insulin resistance or type 2 diabetes.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Diabetes Mellitus, Type 2; Female; Fetuins; Humans; Incidence; Longitudinal Studies; Male; Risk Factors

Fibroblast growth factor 23, left ventricular mass, and left ventricular hypertrophy in community-dwelling older adults. - Jovanovich, Anna; Ix, Joachim H; Gottdiener, John; McFann, Kim; Katz, Ronit; Kestenbaum, Bryan; de Boer, Ian H; Sarnak, Mark; Shlipak, Michael G; Mukamal, Kenneth J; Siscovick, David; Chonchol, Michel (Atherosclerosis, 2013)
OBJECTIVES: In chronic kidney disease (CKD), high FGF23 concentrations are associated with left ventricular hypertrophy (LVH), cardiovascular events, and death. The associations of FGF23 with left ventricular mass (LVM) and LVH in the general population and the influence of CKD remains uncertain. METHODS: C-terminal plasma FGF23 concentrations were measured, and LVM and LVH evaluated by echocardiogram among 2255 individuals ≥65 years in the Cardiovascular Health Study. Linear regression analysis adjusting for demographics, cardiovascular, and kidney related risk factors examined the associations of FGF23 concentrations with LVM. Analyses were stratified by CKD status and adjusted linear and logistic regression analysis explored the associations of FGF23 with LVM and LVH. RESULTS: Among the entire cohort, higher FGF23 concentrations were associated with greater LVM in adjusted analyses (β = 6.71 [95% CI 4.35-9.01] g per doubling of FGF23). 32% (n = 624) had CKD (eGFR <60 mL/min/1.73 m(2) and/or urine albumin-to-creatinine ratio >30 mg/g). Associations were stronger among participants with CKD (p interaction = 0.006): LVM β = 9.71 [95% CI 5.86-13.56] g per doubling of FGF23 compared to those without CKD (β = 3.44 [95% CI 0.77, 6.11] g per doubling of FGF23). While there was no significant interaction between FGF23 and CKD for LVH (p interaction = 0.25), the OR (1.46 95% CI [1.20-1.77]) in the CKD group was statistically significant and of larger magnitude than the OR for in the no CKD group (1.12 [95% CI 0.97-1.48]). CONCLUSION: In a large cohort of older community-dwelling adults, higher FGF23 concentrations were associated with greater LVM and LVH with stronger relationships in participants with CKD.
Keywords: Aged; Female; Fibroblast Growth Factors; Heart Ventricles; Humans; Hypertrophy, Left Ventricular; Longitudinal Studies; Male; Renal Insufficiency, Chronic; Risk Factors; Ultrasonography

Genetic risk factors for BMI and obesity in an ethnically diverse population: results from the population architecture using genomics and epidemiology (PAGE) study. - Fesinmeyer, Megan D; North, Kari E; Ritchie, Marylyn D; Lim, Unhee; Franceschini, Nora; Wilkens, Lynne R; Gross, Myron D; Bůzková, Petra; Glenn, Kimberly; Quibrera, P Miguel; Fernandez-Rhodes, Lindsay; Li, Qiong; et al. (Obesity (Silver Spring), 2013)
OBJECTIVE: Several genome-wide association studies (GWAS) have demonstrated that common genetic variants contribute to obesity. However, studies of this complex trait have focused on ancestrally European populations, despite the high prevalence of obesity in some minority groups. DESIGN AND METHODS: As part of the "Population Architecture using Genomics and Epidemiology (PAGE)" Consortium, we investigated the association between 13 GWAS-identified single-nucleotide polymorphisms (SNPs) and BMI and obesity in 69,775 subjects, including 6,149 American Indians, 15,415 African-Americans, 2,438 East Asians, 7,346 Hispanics, 604 Pacific Islanders, and 37,823 European Americans. For the BMI-increasing allele of each SNP, we calculated β coefficients using linear regression (for BMI) and risk estimates using logistic regression (for obesity defined as BMI ≥ 30) followed by fixed-effects meta-analysis to combine results across PAGE sites. Analyses stratified by racial/ethnic group assumed an additive genetic model and were adjusted for age, sex, and current smoking. We defined "replicating SNPs" (in European Americans) and "generalizing SNPs" (in other racial/ethnic groups) as those associated with an allele frequency-specific increase in BMI. RESULTS: By this definition, we replicated 9/13 SNP associations (5 out of 8 loci) in European Americans. We also generalized 8/13 SNP associations (5/8 loci) in East Asians, 7/13 (5/8 loci) in African Americans, 6/13 (4/8 loci) in Hispanics, 5/8 in Pacific Islanders (5/8 loci), and 5/9 (4/8 loci) in American Indians. CONCLUSION: Linkage disequilibrium patterns suggest that tagSNPs selected for European Americans may not adequately tag causal variants in other ancestry groups. Accordingly, fine-mapping in large samples is needed to comprehensively explore these loci in diverse populations.
Keywords: Alleles; Body Mass Index; Ethnic Groups; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Metagenomics; Obesity; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

A genome-wide association study for venous thromboembolism: the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) consortium. - Tang, Weihong; Teichert, Martina; Chasman, Daniel I; Heit, John A; Morange, Pierre-Emmanuel; Li, Guo; Pankratz, Nathan; Leebeek, Frank W; Paré, Guillaume; de Andrade, Mariza; Tzourio, Christophe; Psaty, Bruce M; et al. (Genet Epidemiol, 2013)
Venous thromboembolism (VTE) is a common, heritable disease resulting in high rates of hospitalization and mortality. Yet few associations between VTE and genetic variants, all in the coagulation pathway, have been established. To identify additional genetic determinants of VTE, we conducted a two-stage genome-wide association study (GWAS) among individuals of European ancestry in the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) VTE consortium. The discovery GWAS comprised 1,618 incident VTE cases out of 44,499 participants from six community-based studies. Genotypes for genome-wide single-nucleotide polymorphisms (SNPs) were imputed to approximately 2.5 million SNPs in HapMap and association with VTE assessed using study-design appropriate regression methods. Meta-analysis of these results identified two known loci, in F5 and ABO. Top 1,047 tag SNPs (P ≤ 0.0016) from the discovery GWAS were tested for association in an additional 3,231 cases and 3,536 controls from three case-control studies. In the combined data from these two stages, additional genome-wide significant associations were observed on 4q35 at F11 (top SNP rs4253399, intronic to F11) and on 4q28 at FGG (rs6536024, 9.7 kb from FGG; P < 5.0 × 10(-13) for both). The associations at the FGG locus were not completely explained by previously reported variants. Loci at or near SUSD1 and OTUD7A showed borderline yet novel associations (P < 5.0 × 10(-6) ) and constitute new candidate genes. In conclusion, this large GWAS replicated key genetic associations in F5 and ABO, and confirmed the importance of F11 and FGG loci for VTE. Future studies are warranted to better characterize the associations with F11 and FGG and to replicate the new candidate associations.
Keywords: Aged; Aging; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; Venous Thromboembolism

Height and risk of incident intraparenchymal hemorrhage: Atherosclerosis Risk in Communities and Cardiovascular Health study cohorts. - Smith, Lindsay G; Yatsuya, Hiroshi; Psaty, Bruce M; Longstreth, W T; Folsom, Aaron R (J Stroke Cerebrovasc Dis, 2013)
BACKGROUND: Height is inversely associated with incident coronary disease and total stroke, but few studies have examined the association between height and intraparenchymal hemorrhage (IPH). We hypothesized that height would be inversely associated with incident IPH in the combined cohorts of the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. METHODS: Data on Caucasian and African American participants were used to estimate the association of height at baseline with incident IPH verified by clinician review of medical records and imaging reports. Sex-specific Cox proportional hazards regression models were used to calculate hazard ratios. RESULTS: A total of 20,983 participants initially free of stroke (11,788 women and 9195 men) were followed for an average of 15.9 years (standard deviation [SD] 5.1 years). Incident IPH occurred in 115 women and 73 men. Sex, but not age, race, study, or blood pressure, modified the association (P = .03). After adjustment for risk factors (age, systolic blood pressure, triglycerides, low-density lipoprotein cholesterol, fibrinogen, and race), among women, height was significantly inversely associated with incident IPH (hazard ratio [HR] per SD [6.3 cm] was 0.81; 95% confidence interval [CI] 0.66-0.99; P = .04). The HR for tertile 3 vs 1 in women was 0.63 (95% CI 0.37-1.08). Among men, height was not linearly associated with incident IPH (HR per SD [6.7 cm] was 1.09; 95% CI 0.84-1.40; P = .52). CONCLUSIONS: This large prospective study provides evidence that shorter height may be a risk factor for incident IPH in women.
Keywords: African Americans; Aged; Body Height; Cerebral Hemorrhage; European Continental Ancestry Group; Female; Humans; Incidence; Male; Middle Aged; Multivariate Analysis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Sex Factors; Time Factors; United States

Hemoglobin decline, function, and mortality in the elderly: the cardiovascular health study. - Zakai, Neil A; French, Benjamin; Arnold, Alice M; Newman, Anne B; Fried, Linda F; Robbins, John; Chaves, Paulo; Cushman, Mary (Am J Hematol, 2013)
While anemia is associated with poor functional and mortality outcomes in the elderly, the impact of hemoglobin decline is less studied. We evaluated the determinants and consequences of hemoglobin decline in 3,758 non-anemic participants from the Cardiovascular Health Study, a prospective cohort of community-dwelling elderly ≥65 years old at baseline and followed for up to 16 years. Hemoglobin was measured at baseline and 3 years later and anemia defined by World Health Organization (WHO) criteria. We modeled hemoglobin decline in two ways: (1) per each 1 g/dL decrease in hemoglobin and (2) development of anemia by the WHO criteria. Among participants without baseline anemia, hemoglobin decreased by 0.4 g/dL and 9% developed anemia over 3 years. Baseline increasing age, female sex, diabetes, and kidney disease predicted hemoglobin decline over 3 years. Baseline increasing age, being African-American, and kidney disease predicted anemia development over 3 years. Hemoglobin decline was associated with subsequent worse cognitive function in men and anemia development with subsequent worse cognitive function in women. Both anemia development (HR 1.39, 95% CI 1.15, 1.69) and hemoglobin decline (HR 1.11, 95% CI 1.04, 1.18 per 1 g/dL decrease) predicted subsequent mortality in men and women. Hemoglobin decreases identified a large group of elderly individuals at risk for subsequent adverse outcomes who would not be identified using the WHO anemia criteria. These data may allow clinicians to identify at-risk elderly individuals for early intervention to improve the quality and quantity of life.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Anemia; Diabetes Complications; Female; Follow-Up Studies; Hemoglobins; Humans; Kidney Diseases; Male; Prospective Studies; Quality of Life; Risk Factors; Sex Factors; Survival Rate; Time Factors; World Health Organization

Hypertension and low HDL cholesterol were associated with reduced kidney function across the age spectrum: a collaborative study. - Odden, Michelle C; Tager, Ira B; Gansevoort, Ron T; Bakker, Stephan J L; Fried, Linda F; Newman, Anne B; Katz, Ronit; Satterfield, Suzanne; Harris, Tamara B; Sarnak, Mark J; Siscovick, David; Shlipak, Michael G (Ann Epidemiol, 2013)
PURPOSE: To determine if the associations among established risk factors and reduced kidney function vary by age. METHODS: We pooled cross-sectional data from 14,788 nondiabetics aged 40 to 100 years in 4 studies: Cardiovascular Health Study, Health, Aging, and Body Composition Study, Multi-Ethnic Study of Atherosclerosis, and Prevention of Renal and Vascular End-Stage Disease cohort. RESULTS: Hypertension and low high-density lipoprotein (HDL) cholesterol were associated with reduced cystatin C-based estimated glomerular filtration rate (eGFR) across the age spectrum. In adjusted analyses, hypertension was associated with a 2.3 (95% confidence interval [CI], 0.1, 4.4), 5.1 (95% CI, 4.1, 6.1), and 6.9 (95% CI, 3.0, 10.4) mL/min/1.73 m(2) lower eGFR in participants 40 to 59, 60 to 79, and at least 80 years, respectively (P for interaction < .001). The association of low HDL cholesterol with reduced kidney function was also greater in the older age groups: 4.9 (95% CI, 3.5, 6.3), 7.1 (95% CI, 6.0, 8.3), 8.9 (95% CI, 5.4, 11.9) mL/min/1.73 m(2) (P for interaction < .001). Smoking and obesity were associated with reduced kidney function in participants under 80 years. All estimates of the potential population impact of the risk factors were modest. CONCLUSIONS: Hypertension, obesity, smoking, and low HDL cholesterol are modestly associated with reduced kidney function in nondiabetics. The associations of hypertension and HDL cholesterol with reduced kidney function seem to be stronger in older adults.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Aging; Causality; Cholesterol, LDL; Cohort Studies; Comorbidity; Cross-Sectional Studies; Cystatin C; Female; Humans; Hypertension; Kidney Function Tests; Male; Netherlands; Obesity; Prevalence; Renal Insufficiency, Chronic; Risk Factors; Smoking; United States

Impact of inflammatory biomarkers on relation of high density lipoprotein-cholesterol with incident coronary heart disease: cardiovascular Health Study. - Tehrani, David M; Gardin, Julius M; Yanez, David; Hirsch, Calvin H; Lloyd-Jones, Donald M; Stein, Phyllis K; Wong, Nathan D (Atherosclerosis, 2013)
BACKGROUND: Inflammatory factors and low HDL-C relate to CHD risk, but whether inflammation attenuates any protective association of high HDL-C is unknown. OBJECTIVE: Investigate inflammatory markers' individual and collective impact on the association of HDL-C with incident coronary heart disease (CHD). METHODS: In 3888 older adults without known cardiovascular disease (CVD), we examined if the inflammatory markers C-reactive protein (CRP), interleukin-6 (IL-6), and lipoprotein-associated phospholipase A2 (Lp-PLA₂) modify the relation of HDL-C with CHD. HDL-C, CRP, IL-6, and Lp-PLA₂ values were grouped as using gender-specific tertiles. Also, an inflammation index of z-score sums for CRP, IL-6, and Lp-PLA₂ was categorized into tertiles. We calculated CHD incidence for each HDL-C/inflammation group and performed Cox regression, adjusted for standard CVD risk factors and triglycerides to examine the relationship of combined HDL-C-inflammation groups with incident events. RESULTS: CHD incidence (per 1000 person years) was higher for higher levels of CRP, IL-6, and the index, and lower for higher levels of HDL-C. Compared to high HDL-C/low-inflammation categories (referent), adjusted HRs for incident CHD were increased for those with high HDL-C and high CRP (HR = 1.50, p < 0.01) or highest IL-6 tertile (HR = 1.40, p < 0.05), but not with highest Lp-PLA₂ tertile. Higher CHD incidence was similarly seen for those with intermediate or low HDL-C accompanied by high CRP, high IL-6, or a high inflammatory index. CONCLUSION: The protective relation of high HDL-C for incident CHD appears to be attenuated by greater inflammation.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; African Americans; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, HDL; Coronary Disease; European Continental Ancestry Group; Female; Humans; Incidence; Inflammation; Interleukin-6; Male; Middle Aged; Proportional Hazards Models; Prospective Studies; Risk Factors

Inflammation and sudden cardiac death in a community-based population of older adults: the Cardiovascular Health Study. - Hussein, Ayman A; Gottdiener, John S; Bartz, Traci M; Sotoodehnia, Nona; DeFilippi, Christopher; See, Vincent; Deo, Rajat; Siscovick, David; Stein, Phyllis K; Lloyd-Jones, Donald (Heart Rhythm, 2013)
BACKGROUND: Inflammation is linked to adverse cardiovascular events, but its association with sudden cardiac death (SCD) has been controversial. Older subjects, who are at particular risk for SCD, were underrepresented in previous studies addressing this issue. OBJECTIVE: The purpose of this study was to study the association between inflammation and SCD in a community-based population of older adults. METHODS: In the Cardiovascular Health Study, 5806 and 5382 participants had measurements of C-reactive protein (CRP) and interleukin-6 (IL6), respectively, and were followed for up to 17 years. SCD risk as a function of baseline IL-6 and CRP was assessed in the overall population and in a group of participants without known prevalent cardiac disease. RESULTS: In univariate analyses, both IL-6 (hazard ratio [HR] 1.79 for 1+ log IL-6, 95% confidence interval [CI] 1.50-2.13; 5th vs 1st quintile HR 3.36, 95% CI 2.24-5.05) and CRP (HR 1.31 for 1+ log CRP, 95% CI 1.18-1.45; 5th vs 1st quintile HR 2.00, 95% CI 1.40-2.87) were associated with SCD risk. In covariate-adjusted analyses, accounting for baseline risk factors, incident myocardial infarction, and heart failure, the association with SCD risk persisted for IL-6 (HR 1.26 for 1+ log IL-6, 95% CI 1.02-1.56; 5th vs 1st quintile HR 1.63, 95% CI 1.03-2.56) but was significantly attenuated for CRP (HR 1.13 for 1+ log CRP, 95% CI 1.00-1.28; 5th vs 1st quintile HR 1.34, 95% CI 0.88-2.05). Similar findings were observed in participants without prevalent cardiac disease. CONCLUSION: Greater burden of inflammation, assessed by IL-6 levels, is associated with SCD risk beyond traditional risk factors, incident myocardial infarction, and heart failure.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; Case-Control Studies; Cohort Studies; Death, Sudden, Cardiac; Female; Humans; Inflammation; Interleukin-6; Male; Risk Factors

Insights into the genetic architecture of early stage age-related macular degeneration: a genome-wide association study meta-analysis. - Holliday, Elizabeth G; Smith, Albert V; Cornes, Belinda K; Buitendijk, Gabriëlle H S; Jensen, Richard A; Sim, Xueling; Aspelund, Thor; Aung, Tin; Baird, Paul N; Boerwinkle, Eric; Cheng, Ching Yu; van Duijn, Cornelia M; et al. (PLoS One, 2013)
Genetic factors explain a majority of risk variance for age-related macular degeneration (AMD). While genome-wide association studies (GWAS) for late AMD implicate genes in complement, inflammatory and lipid pathways, the genetic architecture of early AMD has been relatively under studied. We conducted a GWAS meta-analysis of early AMD, including 4,089 individuals with prevalent signs of early AMD (soft drusen and/or retinal pigment epithelial changes) and 20,453 individuals without these signs. For various published late AMD risk loci, we also compared effect sizes between early and late AMD using an additional 484 individuals with prevalent late AMD. GWAS meta-analysis confirmed previously reported association of variants at the complement factor H (CFH) (peak P = 1.5×10(-31)) and age-related maculopathy susceptibility 2 (ARMS2) (P = 4.3×10(-24)) loci, and suggested Apolipoprotein E (ApoE) polymorphisms (rs2075650; P = 1.1×10(-6)) associated with early AMD. Other possible loci that did not reach GWAS significance included variants in the zinc finger protein gene GLI3 (rs2049622; P = 8.9×10(-6)) and upstream of GLI2 (rs6721654; P = 6.5×10(-6)), encoding retinal Sonic hedgehog signalling regulators, and in the tyrosinase (TYR) gene (rs621313; P = 3.5×10(-6)), involved in melanin biosynthesis. For a range of published, late AMD risk loci, estimated effect sizes were significantly lower for early than late AMD. This study confirms the involvement of multiple established AMD risk variants in early AMD, but suggests weaker genetic effects on the risk of early AMD relative to late AMD. Several biological processes were suggested to be potentially specific for early AMD, including pathways regulating RPE cell melanin content and signalling pathways potentially involved in retinal regeneration, generating hypotheses for further investigation.
Keywords: Apolipoproteins E; Complement Factor H; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Kruppel-Like Transcription Factors; Macular Degeneration; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Proteins; Risk Factors; Zinc Finger Protein Gli3

Kidney function and prevalent and incident frailty. - Dalrymple, Lorien S; Katz, Ronit; Rifkin, Dena E; Siscovick, David; Newman, Anne B; Fried, Linda F; Sarnak, Mark J; Odden, Michelle C; Shlipak, Michael G (Clin J Am Soc Nephrol, 2013)
BACKGROUND AND OBJECTIVES: Kidney disease is associated with physiologic changes that may predispose to frailty. This study sought to investigate whether lower levels of kidney function were associated with prevalent or incident frailty in Cardiovascular Health Study (CHS) participants. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: CHS enrolled community-dwelling adults age ≥65 years between 1989-1990 and 1992-1993. To examine prevalent frailty, included were 4150 participants without stroke, Parkinson disease, prescribed medications for Alzheimer disease or depression, or severely impaired cognition. To examine incident frailty, included were a subset of 3459 participants without baseline frailty or development of exclusion criteria during follow-up. The primary predictor was estimated GFR (eGFR) calculated using serum cystatin C (eGFR(cys)). Secondary analyses examined eGFR using serum creatinine (eGFR(SCr)). Outcomes were prevalent frailty and incident frailty at 4 years of follow-up. Frailty was ascertained on the basis of weight loss, exhaustion, weakness, slowness, and low physical activity. RESULTS: The mean age was 75 years and the median eGFR(cys) was 73 ml/min per 1.73 m(2). Among participants with an eGFR(cys) <45 ml/min per 1.73 m(2), 24% had prevalent frailty. In multivariable analysis and compared with eGFR(cys) ≥90 ml/min per 1.73 m(2), eGFR(cys) categories of 45-59 (odds ratio [OR], 1.80; 95% confidence interval [CI], 1.17 to 2.75) and 15-44 (OR, 2.87; 95% CI, 1.72 to 4.77) were associated with higher odds of frailty, whereas 60-75 (OR, 1.14; 95% CI, 0.76 to 1.70) was not. In multivariable analysis, eGFR(cys) categories of 60-75 (incidence rate ratio [IRR], 1.72; 95% CI, 1.07 to 2.75) and 15-44 (IRR, 2.28; 95% CI, 1.23 to 4.22) were associated with higher incidence of frailty whereas 45-59 (IRR, 1.53; 95% CI, 0.90 to 2.60) was not. Lower levels of eGFR(SCr) were not associated with higher risk of prevalent or incident frailty. CONCLUSIONS: In community-dwelling elders, lower eGFR(cys) was associated with a higher risk of prevalent and incident frailty whereas lower eGFR(SCr) was not. These findings highlight the importance of considering non-GFR determinants of kidney function.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Biomarkers; Creatinine; Cross-Sectional Studies; Cystatin C; Fatigue; Female; Frail Elderly; Geriatric Assessment; Glomerular Filtration Rate; Humans; Incidence; Independent Living; Kidney; Kidney Diseases; Logistic Models; Male; Motor Activity; Multivariate Analysis; Muscle Weakness; Odds Ratio; Phenotype; Prevalence; Prospective Studies; Risk Factors; Time Factors; United States; Weight Loss

Lack of associations of ten candidate coronary heart disease risk genetic variants and subclinical atherosclerosis in four US populations: the Population Architecture using Genomics and Epidemiology (PAGE) study. - Zhang, Lili; Bůzková, Petra; Wassel, Christina L; Roman, Mary J; North, Kari E; Crawford, Dana C; Boston, Jonathan; Brown-Gentry, Kristin D; Cole, Shelley A; Deelman, Ewa; Goodloe, Robert; Wilson, Sarah; et al. (Atherosclerosis, 2013)
BACKGROUND: A number of genetic variants have been discovered by recent genome-wide association studies for their associations with clinical coronary heart disease (CHD). However, it is unclear whether these variants are also associated with the development of CHD as measured by subclinical atherosclerosis phenotypes, ankle brachial index (ABI), carotid artery intima-media thickness (cIMT) and carotid plaque. METHODS: Ten CHD risk single nucleotide polymorphisms (SNPs) were genotyped in individuals of European American (EA), African American (AA), American Indian (AI), and Mexican American (MA) ancestry in the Population Architecture using Genomics and Epidemiology (PAGE) study. In each individual study, we performed linear or logistic regression to examine population-specific associations between SNPs and ABI, common and internal cIMT, and plaque. The results from individual studies were meta-analyzed using a fixed effect inverse variance weighted model. RESULTS: None of the ten SNPs was significantly associated with ABI and common or internal cIMT, after Bonferroni correction. In the sample of 13,337 EA, 3809 AA, and 5353 AI individuals with carotid plaque measurement, the GCKR SNP rs780094 was significantly associated with the presence of plaque in AI only (OR = 1.32, 95% confidence interval: 1.17, 1.49, P = 1.08 × 10(-5)), but not in the other populations (P = 0.90 in EA and P = 0.99 in AA). A 9p21 region SNP, rs1333049, was nominally associated with plaque in EA (OR = 1.07, P = 0.02) and in AI (OR = 1.10, P = 0.05). CONCLUSIONS: We identified a significant association between rs780094 and plaque in AI populations, which needs to be replicated in future studies. There was little evidence that the index CHD risk variants identified through genome-wide association studies in EA influence the development of CHD through subclinical atherosclerosis as assessed by cIMT and ABI across ancestries.
Keywords: African Americans; Aged; Ankle Brachial Index; Asymptomatic Diseases; Carotid Artery Diseases; Carotid Intima-Media Thickness; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Indians, North American; Linear Models; Logistic Models; Male; Mexican Americans; Middle Aged; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Predictive Value of Tests; Risk Assessment; Risk Factors; United States

Long-chain monounsaturated Fatty acids and incidence of congestive heart failure in 2 prospective cohorts. - Imamura, Fumiaki; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Steffen, Lyn M; Folsom, Aaron R; Siscovick, David S; Mozaffarian, Dariush (Circulation, 2013)
BACKGROUND: Decades-old animal experiments suggested that dietary long-chain monounsaturated fatty acids (LCMUFAs) caused cardiotoxicity, leading, for example, development of Canola oil (Canadian oil low in erucic acid) from rapeseed. However, potential cardiotoxicity in humans and contemporary dietary sources of LCMUFAs are unknown. METHODS AND RESULTS: We prospectively investigated the associations of plasma phospholipid LCMUFAs (20:1, 22:1, and 24:1), assessed as objective biomarkers of exposure, with incidence congestive heart failure in 2 independent cohorts: 3694 older adults (mean age, 75.2±5.2 years) in the Cardiovascular Health Study (CHS; 1992-2006) and 3577 middle-aged adults (mean age, 54.1±5.8 years) in the Atherosclerosis Risk in Communities Study, Minnesota subcohort (ARIC; 1987-2008). We further examined dietary correlates of circulating LCMUFAs in CHS and ARIC and US dietary sources of LCMUFAs in the 2003-2010 National Health and Nutrition Examination Survey (NHANES). In CHS, 997 congestive heart failure events occurred during 39 238 person-years; in ARIC, 330 events congestive heart failure events occurred during 64 438 person-years. After multivariable adjustment, higher levels of 22:1 and 24:1 were positively associated with greater incident congestive heart failure in both CHS and ARIC; hazard ratios were 1.34 (95% confidence interval, 1.02-1.76) and 1.57 (95% confidence interval, 1.11-2.23) for highest versus lowest quintiles of 22:1, respectively, and 1.75 (95% confidence interval, 1.23-2.50) and 1.92 (95% confidence interval, 1.22-3.03) for 24:1, respectively (P for trend ≤0.03 each). A variety of foods were related to circulating LCMUFAs in CHS and ARIC, consistent with food sources of LCMUFAs in NHANES, including fish, poultry, meats, whole grains, and mustard. CONCLUSIONS: Higher circulating levels of 22:1 and 24:1, with apparently diverse dietary sources, were associated with incident congestive heart failure in 2 independent cohorts, suggesting possible cardiotoxicity of LCMUFAs in humans.
Keywords: Aged; Aged, 80 and over; Cross-Sectional Studies; Dietary Fats; Fatty Acids, Monounsaturated; Feeding Behavior; Female; Heart Failure; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Nutrition Surveys; Prospective Studies; Risk Factors; Stroke

Multiethnic meta-analysis of genome-wide association studies in >100 000 subjects identifies 23 fibrinogen-associated Loci but no strong evidence of a causal association between circulating fibrinogen and cardiovascular disease. - Sabater-Lleal, Maria; Huang, Jie; Chasman, Daniel; Naitza, Silvia; Dehghan, Abbas; Johnson, Andrew D; Teumer, Alexander; Reiner, Alex P; Folkersen, Lasse; Basu, Saonli; Rudnicka, Alicja R; Trompet, Stella; et al. (Circulation, 2013)
BACKGROUND: Estimates of the heritability of plasma fibrinogen concentration, an established predictor of cardiovascular disease, range from 34% to 50%. Genetic variants so far identified by genome-wide association studies explain only a small proportion (<2%) of its variation. METHODS AND RESULTS: We conducted a meta-analysis of 28 genome-wide association studies including >90 000 subjects of European ancestry, the first genome-wide association meta-analysis of fibrinogen levels in 7 studies in blacks totaling 8289 samples, and a genome-wide association study in Hispanics totaling 1366 samples. Evaluation for association of single-nucleotide polymorphisms with clinical outcomes included a total of 40 695 cases and 85 582 controls for coronary artery disease, 4752 cases and 24 030 controls for stroke, and 3208 cases and 46 167 controls for venous thromboembolism. Overall, we identified 24 genome-wide significant (P<5×10(-8)) independent signals in 23 loci, including 15 novel associations, together accounting for 3.7% of plasma fibrinogen variation. Gene-set enrichment analysis highlighted key roles in fibrinogen regulation for the 3 structural fibrinogen genes and pathways related to inflammation, adipocytokines, and thyrotrophin-releasing hormone signaling. Whereas lead single-nucleotide polymorphisms in a few loci were significantly associated with coronary artery disease, the combined effect of all 24 fibrinogen-associated lead single-nucleotide polymorphisms was not significant for coronary artery disease, stroke, or venous thromboembolism. CONCLUSIONS: We identify 23 robustly associated fibrinogen loci, 15 of which are new. Clinical outcome analysis of these loci does not support a causal relationship between circulating levels of fibrinogen and coronary artery disease, stroke, or venous thromboembolism.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; Coronary Artery Disease; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Hispanic Americans; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Venous Thromboembolism; Young Adult

Neighborhood socioeconomic disadvantage and mortality after stroke. - Brown, Arleen F; Liang, Li-Jung; Vassar, Stefanie D; Merkin, Sharon Stein; Longstreth, W T; Ovbiagele, Bruce; Yan, Tingjian; Escarce, José J (Neurology, 2013)
OBJECTIVE: Residence in a socioeconomically disadvantaged community is associated with mortality, but the mechanisms are not well understood. We examined whether socioeconomic features of the residential neighborhood contribute to poststroke mortality and whether neighborhood influences are mediated by traditional behavioral and biologic risk factors. METHODS: We used data from the Cardiovascular Health Study, a multicenter, population-based, longitudinal study of adults ≥65 years. Residential neighborhood disadvantage was measured using neighborhood socioeconomic status (NSES), a composite of 6 census tract variables representing income, education, employment, and wealth. Multilevel Cox proportional hazard models were constructed to determine the association of NSES to mortality after an incident stroke, adjusted for sociodemographic characteristics, stroke type, and behavioral and biologic risk factors. RESULTS: Among the 3,834 participants with no prior stroke at baseline, 806 had a stroke over a mean 11.5 years of follow-up, with 168 (20%) deaths 30 days after stroke and 276 (34%) deaths at 1 year. In models adjusted for demographic characteristics, stroke type, and behavioral and biologic risk factors, mortality hazard 1 year after stroke was significantly higher among residents of neighborhoods with the lowest NSES than those in the highest NSES neighborhoods (hazard ratio 1.77, 95% confidence interval 1.17-2.68). CONCLUSION: Living in a socioeconomically disadvantaged neighborhood is associated with higher mortality hazard at 1 year following an incident stroke. Further work is needed to understand the structural and social characteristics of neighborhoods that may contribute to mortality in the year after a stroke and the pathways through which these characteristics operate.
Keywords: Aged; Female; Humans; Incidence; Kaplan-Meier Estimate; Male; Proportional Hazards Models; Residence Characteristics; Risk Factors; Socioeconomic Factors; Stroke; Vulnerable Populations

Plasma free fatty acids and risk of heart failure: the Cardiovascular Health Study. - Djoussé, Luc; Benkeser, David; Arnold, Alice; Kizer, Jorge R; Zieman, Susan J; Lemaitre, Rozenn N; Tracy, Russell P; Gottdiener, John S; Mozaffarian, Dariush; Siscovick, David S; Mukamal, Kenneth J; Ix, Joachim H (Circ Heart Fail, 2013)
BACKGROUND: Although plasma free fatty acid (FFA) concentrations have been associated with lipotoxicity, apoptosis, and risk of diabetes mellitus and coronary heart disease, it is unclear whether FFA levels are associated with heart failure (HF). METHODS AND RESULTS: To test the hypothesis that plasma concentration of FFAs is positively associated with incident HF, we prospectively analyzed data on 4248 men and women free of HF at baseline and >65 years old from the Cardiovascular Health Study. FFA concentration was measured in duplicate by the Wako enzymatic method. Incident HF was validated by a centralized Events Committee. We used Cox proportional hazards to estimate the hazard ratio of HF per SD of FFAs. During a median follow-up of 10.5 years, a total of 1286 new cases of HF occurred. In a multivariable model adjusting for clinic site, comorbidity, demographic, anthropometric, and lifestyle factors, each SD (0.2 mEq/L) higher plasma FFA was associated with 12% (95% confidence interval, 6%-19%) higher risk of HF. Controlling for time-varying diabetes mellitus and coronary heart disease did not change the results (hazard ratio per SD, 1.16 [95% confidence interval, 1.09-1.23]). CONCLUSIONS: A single measure of plasma FFA obtained later in life is associated with a higher risk of HF in older adults. Additional studies are needed to explore biological mechanisms by which FFAs may influence the risk of HF and determine whether FFAs could serve as a novel pharmacological target for HF prevention.
Keywords: Aged; Aged, 80 and over; Biomarkers; Comorbidity; Fatty Acids, Nonesterified; Female; Heart Failure; Humans; Incidence; Kaplan-Meier Estimate; Linear Models; Male; Multivariate Analysis; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Factors; Time Factors; United States

Post-genome-wide association study challenges for lipid traits: describing age as a modifier of gene-lipid associations in the Population Architecture using Genomics and Epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Franceschini, Nora; Hindorff, Lucia A; Cole, Shelley A; Bůzková, Petra; Schumacher, Fredrick R; Eaton, Charles B; Goodloe, Robert J; Duggan, David J; Haessler, Jeff; Cochran, Barbara; et al. (Ann Hum Genet, 2013)
Numerous common genetic variants that influence plasma high-density lipoprotein cholesterol, low-density lipoprotein cholesterol (LDL-C), and triglyceride distributions have been identified via genome-wide association studies (GWAS). However, whether or not these associations are age-dependent has largely been overlooked. We conducted an association study and meta-analysis in more than 22,000 European Americans between 49 previously identified GWAS variants and the three lipid traits, stratified by age (males: <50 or ≥50 years of age; females: pre- or postmenopausal). For each variant, a test of heterogeneity was performed between the two age strata and significant Phet values were used as evidence of age-specific genetic effects. We identified seven associations in females and eight in males that displayed suggestive heterogeneity by age (Phet < 0.05). The association between rs174547 (FADS1) and LDL-C in males displayed the most evidence for heterogeneity between age groups (Phet = 1.74E-03, I(2) = 89.8), with a significant association in older males (P = 1.39E-06) but not younger males (P = 0.99). However, none of the suggestive modifying effects survived adjustment for multiple testing, highlighting the challenges of identifying modifiers of modest SNP-trait associations despite large sample sizes.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Lipids; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

Prediction and classification of cardiovascular disease risk in older adults with diabetes. - Mukamal, K J; Kizer, J R; Djoussé, L; Ix, J H; Zieman, S; Siscovick, D S; Sibley, C T; Tracy, R P; Arnold, A M (Diabetologia, 2013)
AIMS/HYPOTHESIS: We sought to derive and validate a cardiovascular disease (CVD) prediction algorithm for older adults with diabetes, and evaluate the incremental benefit of adding novel circulating biomarkers and measures of subclinical atherosclerosis. METHODS: As part of the Cardiovascular Health Study (CHS), a population-based cohort of adults aged ≥65 years, we examined the 10 year risk of myocardial infarction, stroke and cardiovascular death in 782 older adults with diabetes, in whom 265 events occurred. We validated predictive models in 843 adults with diabetes, who were followed for 7 years in a second cohort, the Multi-Ethnic Study of Atherosclerosis (MESA); here 71 events occurred. RESULTS: The best fitting standard model included age, smoking, systolic blood pressure, total and HDL-cholesterol, creatinine and the use of glucose-lowering agents; however, this model had a C statistic of 0.64 and poorly classified risk in men. Novel biomarkers did not improve discrimination or classification. The addition of ankle-brachial index, electrocardiographic left ventricular hypertrophy and internal carotid intima-media thickness modestly improved discrimination (C statistic 0.68; p = 0.002) and classification (net reclassification improvement [NRI] 0.12; p = 0.01), mainly in those remaining free of CVD. Results were qualitatively similar in the MESA, with a change in C statistic from 0.65 to 0.68 and an NRI of 0.09 upon inclusion of subclinical disease measures. CONCLUSIONS/INTERPRETATION: Standard clinical risk factors and novel biomarkers poorly discriminate and classify CVD risk in older adults with diabetes. The inclusion of subclinical atherosclerotic measures modestly improves these features, but to develop more robust risk prediction, a better understanding of the pathophysiology and determinants of CVD in this patient group is needed.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Biomarkers; Blood Pressure; Cardiovascular Diseases; Carotid Intima-Media Thickness; Cholesterol, HDL; Diabetes Mellitus; Female; Humans; Male; Myocardial Infarction; Regression Analysis; Risk Factors; Stroke

The QT interval and risk of incident atrial fibrillation. - Mandyam, Mala C; Soliman, Elsayed Z; Alonso, Alvaro; Dewland, Thomas A; Heckbert, Susan R; Vittinghoff, Eric; Cummings, Steven R; Ellinor, Patrick T; Chaitman, Bernard R; Stocke, Karen; Applegate, William B; Arking, Dan E; et al. (Heart Rhythm, 2013)
BACKGROUND: Abnormal atrial repolarization is important in the development of atrial fibrillation (AF), but no direct measurement is available in clinical medicine. OBJECTIVE: To determine whether the QT interval, a marker of ventricular repolarization, could be used to predict incident AF. METHODS: We examined a prolonged QT interval corrected by using the Framingham formula (QT(Fram)) as a predictor of incident AF in the Atherosclerosis Risk in Communities (ARIC) study. The Cardiovascular Health Study (CHS) and Health, Aging, and Body Composition (ABC) study were used for validation. Secondary predictors included QT duration as a continuous variable, a short QT interval, and QT intervals corrected by using other formulas. RESULTS: Among 14,538 ARIC study participants, a prolonged QT(Fram) predicted a roughly 2-fold increased risk of AF (hazard ratio [HR] 2.05; 95% confidence interval [CI] 1.42-2.96; P < .001). No substantive attenuation was observed after adjustment for age, race, sex, study center, body mass index, hypertension, diabetes, coronary disease, and heart failure. The findings were validated in Cardiovascular Health Study and Health, Aging, and Body Composition study and were similar across various QT correction methods. Also in the ARIC study, each 10-ms increase in QT(Fram) was associated with an increased unadjusted (HR 1.14; 95% CI 1.10-1.17; P < .001) and adjusted (HR 1.11; 95% CI 1.07-1.14; P < .001) risk of AF. Findings regarding a short QT interval were inconsistent across cohorts. CONCLUSIONS: A prolonged QT interval is associated with an increased risk of incident AF.
Keywords: Aged; Atrial Fibrillation; Cohort Studies; Electrocardiography; Female; Humans; Incidence; Long QT Syndrome; Male; Middle Aged; Risk Factors

Racial differences in the incidence of and risk factors for atrial fibrillation in older adults: the cardiovascular health study. - Jensen, Paul N; Thacker, Evan L; Dublin, Sascha; Psaty, Bruce M; Heckbert, Susan R (J Am Geriatr Soc, 2013)
This study examined whether different associations between risk factors and atrial fibrillation (AF) according to race could explain the lower incidence of AF in blacks. Baseline risk factor information was obtained from interviews, clinical examinations, and echocardiography in 4,774 white and 911 black Cardiovascular Health Study participants aged 65 and older without a history of AF at baseline in 1989/90 or 1992/93. Incident AF was determined according to hospital discharge diagnosis or annual study electrocardiogram. Cox regression was used to assess associations between risk factors and race and incident AF. During a mean 11.2 years of follow-up, 1,403 whites and 182 blacks had incident AF. Associations between all examined risk factors were similar in both races, except left ventricular posterior wall thickness, which was more strongly associated with AF in blacks (per 0.2 cm, blacks: hazard ratio (HR) = 1.72, 95% confidence interval (CI) = 1.44-2.06; whites: HR = 1.30, 95% CI = 1.18-1.43). Overall, the relative risk of AF was 25% lower in blacks than whites after adjustment for age and sex (HR = 0.75, 95% CI = 0.64-0.87) and 45% lower after adjustment for all considered risk factors (HR = 0.55, 95% CI = 0.35-0.88). Different associations of the considered risk factors and incident AF by race do not explain the lower incidence of AF in blacks.
Keywords: Aged; Atrial Fibrillation; Continental Population Groups; Female; Follow-Up Studies; Humans; Incidence; Male; Prevalence; Risk Assessment; Risk Factors; Stroke; United States

Resequencing and clinical associations of the 9p21.3 region: a comprehensive investigation in the Framingham heart study. - Johnson, Andrew D; Hwang, Shih-Jen; Voorman, Arend; Morrison, Alanna; Peloso, Gina M; Hsu, Yi-Hsiang; Thanassoulis, George; Newton-Cheh, Christopher; Rogers, Ian S; Hoffmann, Udo; Freedman, Jane E; Fox, Caroline S; et al. (Circulation, 2013)
BACKGROUND: 9p21.3 is among the most strongly replicated regions for cardiovascular disease. There are few reports of sequencing the associated 9p21.3 interval. We set out to sequence the 9p21.3 region followed by a comprehensive study of genetic associations with clinical and subclinical cardiovascular disease and its risk factors, as well as with copy number variation and gene expression, in the Framingham Heart Study (FHS). METHODS AND RESULTS: We sequenced 281 individuals (94 with myocardial infarction, 94 with high coronary artery calcium levels, and 93 control subjects free of elevated coronary artery calcium or myocardial infarction), followed by genotyping and association in >7000 additional FHS individuals. We assessed genetic associations with clinical and subclinical cardiovascular disease, risk factor phenotypes, and gene expression levels of the protein-coding genes CDKN2A and CDKN2B and the noncoding gene ANRIL in freshly harvested leukocytes and platelets. Within this large sample, we found strong associations of 9p21.3 variants with increased risk for myocardial infarction, higher coronary artery calcium levels, and larger abdominal aorta diameters and no evidence for association with traditional cardiovascular disease risk factors. No common protein-coding variation, variants in splice donor or acceptor sites, or copy number variation events were observed. By contrast, strong associations were observed between genetic variants and gene expression, particularly for a short isoform of ANRIL and for CDKN2B. CONCLUSIONS: Our thorough genomic characterization of 9p21.3 suggests common variants likely account for observed disease associations and provides further support for the hypothesis that complex regulatory variation affecting ANRIL and CDKN2B gene expression may contribute to increased risk for clinically apparent and subclinical coronary artery disease and aortic disease.
Keywords: Calcinosis; Chromosomes, Human, Pair 9; Coronary Artery Disease; Cyclin-Dependent Kinase Inhibitor p15; Cyclin-Dependent Kinase Inhibitor p16; DNA Copy Number Variations; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genotype; Humans; Longitudinal Studies; Male; Massachusetts; Middle Aged; Myocardial Infarction; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; RNA, Long Noncoding; Sequence Analysis, DNA

Risk factors for hospital admission among older persons with newly diagnosed heart failure: findings from the Cardiovascular Health Study. - Chaudhry, Sarwat I; McAvay, Gail; Chen, Shu; Whitson, Heather; Newman, Anne B; Krumholz, Harlan M; Gill, Thomas M (J Am Coll Cardiol, 2013)
OBJECTIVES: This study sought to identify risk factors for the occurrence of all-cause hospital admissions among older persons after heart failure diagnosis, and to determine whether geriatric conditions would emerge as independent risk factors for admission when evaluated in the context of other relevant clinical data. BACKGROUND: Efforts to reduce costs in heart failure have focused on hospital utilization, yet few studies have examined how geriatric conditions affect the long-term risk for hospital admission after heart failure diagnosis. With the aging of the population with heart failure, geriatric conditions such as slow gait and muscle weakness are becoming increasingly common. METHODS: The study population included participants with a new diagnosis of heart failure in the Cardiovascular Health Study, a longitudinal study of community-living older persons. Data were collected through annual examinations and medical-record reviews. Geriatric conditions assessed were slow gait, muscle weakness (defined as weak grip), cognitive impairment, and depressive symptoms. Anderson-Gill regression modeling was used to determine the predictors of hospital admission after heart failure diagnosis. RESULTS: Of the 758 participants with a new diagnosis of heart failure, the mean rate of hospital admission was 7.9 per 10 person-years (95% CI: 7.4 to 8.4). Independent risk factors for hospital admission included diabetes mellitus (HR: 1.36; 95% CI: 1.13 to 1.64), New York Heart Association functional class III or IV (HR: 1.32; 95% CI: 1.11 to 1.57), chronic kidney disease (HR: 1.32; 95% CI: 1.14 to 1.53), slow gait (HR: 1.28; 95% CI: 1.06 to 1.55), depressed ejection fraction (HR: 1.25; 95% CI: 1.04 to 1.51), depression (HR: 1.23; 95% CI: 1.05 to 1.45), and muscle weakness (HR: 1.19; 95% CI: 1.00 to 1.42). CONCLUSIONS: Geriatric conditions are important, and potentially modifiable, risk factors for hospital admission in heart failure that should be routinely assessed at the time of heart failure diagnosis.
Keywords: Age Factors; Aged; Aged, 80 and over; Comorbidity; Effect Modifier, Epidemiologic; Female; Geriatric Assessment; Health Surveys; Heart Failure; Hospitalization; Humans; Longitudinal Studies; Male; Mental Competency; Risk Assessment; Risk Factors; Severity of Illness Index; Stroke Volume; Time-to-Treatment; United States

Risk factors for type 2 diabetes mellitus preceded by β-cell dysfunction, insulin resistance, or both in older adults: the Cardiovascular Health Study. - Imamura, Fumiaki; Mukamal, Kenneth J; Meigs, James B; Luchsinger, José A; Ix, Joachim H; Siscovick, David S; Mozaffarian, Dariush (Am J Epidemiol, 2013)
Insulin resistance (IR) and pancreatic β-cell dysfunction lead to type 2 diabetes mellitus (DM). We tested whether risk factors would differ for DM that was preceded predominantly by IR, β-cell dysfunction, or both among 4,384 older adults (mean age, 72.7 (standard deviation, 5.6) years) in the Cardiovascular Health Study, which was conducted in North Carolina, California, Maryland, and Pennsylvania (1989-2007). When evaluating established risk factors, we found older age, greater adiposity, higher systolic blood pressure, a lower high-density lipoprotein cholesterol level, a higher triglyceride level, and a lower alcohol intake to be independently associated with greater IR but, conversely, with better β-cell function (P < 0.001). The prospective associations between some risk factors and incident DM varied significantly depending on whether DM was preceded predominantly by IR, β-cell dysfunction, or both. For example, obesity and lower high-density lipoprotein cholesterol levels were positively associated with DM preceded predominantly by IR (hazard ratio (HR) = 5.02, 95% confidence interval (CI): 2.81, 9.00; and HR = 1.97, 95% CI: 1.32, 2.93, respectively), with a significant association with and an insignificant trend toward a lower risk of DM preceded predominantly by β-cell dysfunction (HR = 0.33, 95% CI: 0.14, 0.80; and HR = 0.78, 95% CI: 0.43, 1.39, respectively). In conclusion, among older adults, DM risk factors were differentially associated with DM preceded predominantly by IR or β-cell dysfunction. Biologic and clinical implications of putative subtypes of DM require further investigation.
Keywords: Adiposity; Age Factors; Aged; Aged, 80 and over; Aging; Alcohol Drinking; Blood Pressure; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Humans; Incidence; Insulin Resistance; Insulin-Secreting Cells; Lipids; Male; Prospective Studies; Risk Factors; Socioeconomic Factors; United States

Risk of venous thromboembolism associated with single and combined effects of Factor V Leiden, Prothrombin 20210A and Methylenetethraydrofolate reductase C677T: a meta-analysis involving over 11,000 cases and 21,000 controls. - Simone, Benedetto; De Stefano, Valerio; Leoncini, Emanuele; Zacho, Jeppe; Martinelli, Ida; Emmerich, Joseph; Rossi, Elena; Folsom, Aaron R; Almawi, Wassim Y; Scarabin, Pierre Y; den Heijer, Martin; Cushman, Mary; et al. (Eur J Epidemiol, 2013)
Genetic and environmental factors interact in determining the risk of venous thromboembolism (VTE). The risk associated with the polymorphic variants G1691A of factor V (Factor V Leiden, FVL), G20210A of prothrombin (PT20210A) and C677T of methylentetrahydrofolate reductase (C677T MTHFR) genes has been investigated in many studies. We performed a pooled analysis of case-control and cohort studies investigating in adults the association between each variant and VTE, published on Pubmed, Embase or Google through January 2010. Authors of eligible papers, were invited to provide all available individual data for the pooling. The Odds Ratio (OR) for first VTE associated with each variant, individually and combined with the others, were calculated with a random effect model, in heterozygotes and homozygotes (dominant model for FVL and PT20210A; recessive for C677T MTHFR). We analysed 31 databases, including 11,239 cases and 21,521 controls. No significant association with VTE was found for homozygous C677T MTHFR (OR: 1.38; 95 % confidence intervals [CI]: 0.98-1.93), whereas the risk was increased in carriers of either heterozygous FVL or PT20210 (OR = 4.22; 95 % CI: 3.35-5.32; and OR = 2.79;95 % CI: 2.25-3.46, respectively), in double heterozygotes (OR = 3.42; 95 %CI 1.64-7.13), and in homozygous FVL or PT20210A (OR = 11.45; 95 %CI: 6.79-19.29; and OR: 6.74 (CI 95 % 2.19-20.72), respectively). The stratified analyses showed a stronger effect of FVL on individuals ≤ 45 years (p value for interaction = 0.036) and of PT20210A in women using oral contraceptives (p-value for interaction = 0.045). In this large pooled analysis, inclusive of large studies like MEGA, no effect was found for C677T MTHFR on VTE; FVL and PT20210A were confirmed to be moderate risk factors. Notably, double carriers of the two genetic variants produced an impact on VTE risk significantly increased but weaker than previously thought.
Keywords: Case-Control Studies; Factor V; Genetic Predisposition to Disease; Humans; Methylenetetrahydrofolate Reductase (NADPH2); Prothrombin; Risk Factors; Venous Thromboembolism

Soluble CD14: genomewide association analysis and relationship to cardiovascular risk and mortality in older adults. - Reiner, Alex P; Lange, Ethan M; Jenny, Nancy S; Chaves, Paulo H M; Ellis, Jaclyn; Li, Jin; Walston, Jeremy; Lange, Leslie A; Cushman, Mary; Tracy, Russell P (Arterioscler Thromb Vasc Biol, 2013)
OBJECTIVE: CD14 is a glycosylphosphotidylinositol-anchored membrane glycoprotein expressed on neutrophils and monocytes/macrophages that also circulates as a soluble form (sCD14). Despite the well-recognized role of CD14 in inflammation, relatively little is known about the genetic determinants of sCD14 or the relationship of sCD14 to vascular- and aging-related phenotypes. METHODS AND RESULTS: We measured baseline levels of sCD14 in >5000 European-American and black adults aged 65 years and older from the Cardiovascular Health Study, who were well characterized at baseline for atherosclerotic risk factors and subclinical cardiovascular disease, and who have been followed for clinical cardiovascular disease and mortality outcomes up to 20 years. At baseline, sCD14 generally showed strong positive correlations with traditional cardio-metabolic risk factors and with subclinical measures of vascular disease such as carotid wall thickness and ankle-brachial index (independently of traditional cardiovascular disease risk factors), and was also inversely correlated with body mass index. In genomewide association analyses of sCD14, we (1) confirmed the importance of the CD14 locus on chromosome 5q21 in European-American; (2) identified a novel African ancestry-specific allele of CD14 associated with lower sCD14 in blacks; and (3) identified a putative novel association in European-American of a nonsynonymous variant of PIGC, which encodes an enzyme required for the first step in glycosylphosphotidylinositol anchor biosynthesis. Finally, we show that, like other acute phase inflammatory biomarkers, sCD14 predicts incident cardiovascular disease, and strongly and independently predicts all-cause mortality in older adults. CONCLUSIONS: CD14 independently predicts risk mortality in older adults.
Keywords: African Americans; Age Factors; Aged; Biomarkers; Cardiovascular Diseases; Chromosomes, Human, Pair 5; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Haplotypes; Hexosyltransferases; Humans; Incidence; Inflammation Mediators; Linear Models; Lipopolysaccharide Receptors; Logistic Models; Male; Membrane Proteins; Multivariate Analysis; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Total and high-molecular-weight adiponectin and risk of coronary heart disease and ischemic stroke in older adults. - Kizer, Jorge R; Benkeser, David; Arnold, Alice M; Djoussé, Luc; Zieman, Susan J; Mukamal, Kenneth J; Tracy, Russell P; Mantzoros, Christos S; Siscovick, David S; Gottdiener, John S; Ix, Joachim H (J Clin Endocrinol Metab, 2013)
CONTEXT: Adiponectin is atheroprotective in the laboratory, but prospective studies have shown opposite associations with cardiovascular disease (CVD) in healthy middle-aged populations (protective) and older cohorts (adverse). Whether this relates to different proportions of high-molecular-weight (HMW) adiponectin is unknown. OBJECTIVE: The aim of the study was to test the hypothesis that total adiponectin is directly associated, but HMW adiponectin is inversely related, with CVD in older adults. DESIGN, SETTING, AND PARTICIPANTS: We evaluated 3290 participants free of prevalent CVD in a longitudinal cohort study of U.S. adults aged 65 yr and older. MAIN OUTCOME MEASURES: We measured incident CVD (n = 1291), comprising coronary heart disease and ischemic stroke. RESULTS: Total and HMW adiponectin were tightly correlated (r = 0.94). Cubic splines adjusted for potential confounders revealed that the associations of total and HMW adiponectin with CVD were U-shaped, with inflection points of 20 and 10 mg/liter, respectively. After controlling for potential confounding, levels of total and HMW adiponectin below these cutpoints tended to be inversely associated with incident CVD, driven by their significant or near-significant relations with coronary heart disease [hazard ratio (HR), 0.85 per sd increase; 95% confidence interval (CI), 0.75-96; and HR, 0.87; 95% CI, 0.75-1.01, respectively]. These associations were abrogated by additional inclusion of putative metabolic intermediates. Above these cutpoints, however, both total and HMW adiponectin were significantly directly associated with CVD after adjustment for confounders and, particularly, mediators (HR, 1.20 per sd increase; 95% CI, 1.06-1.35; and HR, 1.12; 95% CI, 1.02-1.24, respectively). CONCLUSION: In community-living elders, total and HMW adiponectin showed similar U-shaped relationships with CVD. The inverse relation in the lower range, but not the direct association at the higher end, disappeared after inclusion of putative intermediates, suggesting that high levels may reflect adverse processes separate from adiponectin's beneficial glycometabolic properties.
Keywords: Adiponectin; Adult; Aged; Aged, 80 and over; Brain Ischemia; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; Coronary Disease; Female; Humans; Male; Molecular Weight; Residence Characteristics; Risk Factors; Stroke

Use of antihypertensive medications and breast cancer risk. - Saltzman, Babette S; Weiss, Noel S; Sieh, Weiva; Fitzpatrick, Annette L; McTiernan, Anne; Daling, Janet R; Li, Christopher I (Cancer Causes Control, 2013)
PURPOSE: Use of specific antihypertensive medications (AHTs) has been hypothesized to increase breast cancer risk, but results across published studies are inconsistent. METHODS: We re-evaluated the relationship between AHT use and breast cancer risk in a prospective cohort of 3,201 women ≥65 years of age at recruitment now with more than double the length of follow-up (12 vs. 5 years) and substantially more breast cancer diagnoses (188 compared with 75 cases). We estimated the association between AHT use overall as well as use of specific formulations (based on data collected annually) and breast cancer risk using multivariate-adjusted Cox regression. RESULTS: Compared with women who reported no use of AHTs, women who had used calcium channel blockers (CCB) within the past two years had a 1.6-fold increased risk of breast cancer (95 % confidence interval (CI): 1.0-2.5), and in particular, recent users of immediate-release CCBs had a 2.4-fold increased risk (95 % CI: 1.3-4.5). Neither ever nor recent use of any other type of AHT was associated with breast cancer risk. CONCLUSIONS: While the observed association between immediate-release CCBs and breast cancer risk is based on a small sample size and needs to be interpreted cautiously, this result is consistent with others in the literature. However, given declines in use of these preparations in favor of sustained-release CCBs, which was not related to risk, the potential clinical and public health impact of this association is limited. This study also adds to the evidence that other commonly used AHTs are not strongly related to breast cancer risk.
Keywords: Aged; Aged, 80 and over; Antihypertensive Agents; Breast Neoplasms; Cohort Studies; Female; Humans; Proportional Hazards Models; Prospective Studies; Risk Factors; United States

Association between the metabolic syndrome, its individual components, and unprovoked venous thromboembolism: results of a patient-level meta-analysis. - Ageno, Walter; Di Minno, Matteo N D; Ay, Cihan; Jang, Moon Ju; Hansen, John-Bjarne; Steffen, Lyn M; Vaya, Amparo; Rattazzi, Marcello; Pabinger, Ingrid; Oh, Doyeun; Di Minno, Giovanni; Braekkan, Sigrid K; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: The metabolic syndrome (MetS) may contribute to the pathogenesis of venous thromboembolism (VTE), but this association requires additional investigation. APPROACH AND RESULTS: We performed a patient-level meta-analysis of case-control and cohort studies that evaluated the role of MetS and risk of unprovoked VTE. For case-control studies, odds ratios and 95% confidence intervals were calculated using logistic regression analysis to estimate the influence of individual variables on the risk of VTE; χ(2) tests for trend were used to investigate the effect of increasing number of components of MetS on the risk of VTE and to explore the influence of abdominal obesity on this relationship. For cohort studies, hazard ratios and 95% confidence interval were calculated using multivariable Cox regression analysis. Six case-control studies were included (908 cases with unprovoked VTE and 1794 controls): in multivariate analysis, MetS was independently associated with VTE (odds ratio, 1.91; 95% confidence interval, 1.57-2.33), and both MetS and abdominal obesity were better predictors of unprovoked VTE than obesity defined by the body mass index. Two prospective cohort studies were included (26,531 subjects and 289 unprovoked VTE events): age, obesity, and abdominal obesity, but not MetS were associated with VTE. CONCLUSIONS: Case-control but not prospective cohort studies support an association between MetS and VTE. Abdominal adiposity is a strong risk factor for VTE.
Keywords: Adult; Aged; Case-Control Studies; Cohort Studies; Female; Humans; Logistic Models; Male; Metabolic Syndrome; Middle Aged; Obesity, Abdominal; Risk Factors; Venous Thromboembolism

Association of a cystatin C gene variant with cystatin C levels, CKD, and risk of incident cardiovascular disease and mortality. - O'Seaghdha, Conall M; Tin, Adrienne; Yang, Qiong; Katz, Ronit; Liu, Yongmei; Harris, Tamara; Astor, Brad; Coresh, Josef; Fox, Caroline S; Kao, W H Linda; Shlipak, Michael G (Am J Kidney Dis, 2014)
BACKGROUND: Carriers of the T allele of the single-nucleotide polymorphism rs13038305 tend to have lower cystatin C levels and higher cystatin C-based estimated glomerular filtration rate (eGFRcys). Adjusting for this genetic effect on cystatin C concentrations may improve GFR estimation, reclassify cases of chronic kidney disease (CKD), and strengthen risk estimates for cardiovascular disease (CVD) and mortality. STUDY DESIGN: Observational. SETTING & POPULATION: 4 population-based cohorts: Atherosclerosis Risk in Communities (ARIC), Cardiovascular Health (CHS), Framingham Heart (FHS), and Health, Aging, and Body Composition (Health ABC) studies. PREDICTORS: We estimated the association of rs13038305 with eGFRcys and serum creatinine-based eGFR (eGFRcr) and performed longitudinal analyses of the associations of eGFRcys with mortality and cardiovascular events following adjustment for rs13038305. OUTCOMES: We assessed reclassification by genotype-adjusted eGFRcys across CKD categories: <45, 45-59, 60-89, and ≥ 90 mL/min/1.73 m(2). We compared mortality and CVD outcomes in those reclassified to a worse eGFRcys category with those unaffected. Results were combined using fixed-effect inverse-variance meta-analysis. RESULTS: In 14,645 participants, each copy of the T allele of rs13038305 (frequency, 21%) was associated with a 6.4% lower cystatin C concentration, 5.5-mL/min/1.73 m(2) higher eGFRcys, and 36% [95% CI, 29%-41%] lower odds of CKD. Associations with CVD (HR, 1.17; 95% CI, 1.14-1.20) and mortality (HR, 1.22; 95% CI, 1.19-1.24) per 10-mL/min/1.73 m(2) lower eGFRcys were similar with or without rs13038305 adjustment. 1,134 (7.7%) participants were reclassified to a worse CKD category following rs13038305 adjustment, and rates of CVD and mortality were higher in individuals who were reclassified. However, the overall net reclassification index was not significant for either outcome, at 0.009 (95% CI, -0.003 to 0.022) for mortality and 0.014 (95% CI, 0.0 to 0.028) for CVD. LIMITATIONS: rs13038305 explains only a small proportion of cystatin C variation. CONCLUSIONS: Statistical adjustment can correct a genetic bias in GFR estimates based on cystatin C in carriers of the T allele of rs13038305 and result in changes in disease classification. However, on a population level, the effects on overall reclassification of CKD status are modest.
Keywords: Aged; Bias; Biomarkers; Cardiovascular Diseases; Creatinine; Cystatin C; Female; Genetic Variation; Glomerular Filtration Rate; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Risk Assessment; Risk Factors; Severity of Illness Index; Statistics as Topic; Survival Rate

Association of kidney disease measures with ischemic versus hemorrhagic strokes: pooled analyses of 4 prospective community-based cohorts. - Mahmoodi, Bakhtawar K; Yatsuya, Hiroshi; Matsushita, Kunihiro; Sang, Yinying; Gottesman, Rebecca F; Astor, Brad C; Woodward, Mark; Longstreth, W T; Psaty, Bruce M; Shlipak, Michael G; Folsom, Aaron R; Gansevoort, Ron T; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Although low glomerular filtration rate (GFR) and albuminuria are associated with increased risk of stroke, few studies compared their contribution to risk of ischemic versus hemorrhagic stroke separately. We contrasted the association of these kidney measures with ischemic versus hemorrhagic stroke. METHODS: We pooled individual participant data from 4 community-based cohorts: 3 from the United States and 1 from The Netherlands. GFR was estimated using both creatinine and cystatin C, and albuminuria was quantified by urinary albumin-to-creatinine ratio (ACR). Associations of estimated GFR and ACR were compared for each stroke type (ischemic versus intraparenchymal hemorrhagic) using study-stratified Cox regression. RESULTS: Among 29,595 participants (mean age, 61 [SD 12.5] years; 46% men; 17% black), 1261 developed stroke (12% hemorrhagic) during 280,549 person-years. Low estimated GFR was significantly associated with increased risk of ischemic stroke, but not hemorrhagic stroke, whereas high ACR was associated with both stroke types. Adjusted hazard ratios for ischemic and hemorrhagic stroke at estimated GFR of 45 (versus 95) mL/min per 1.73 m2 were 1.30 (95% confidence interval, 1.01-1.68) and 0.92 (0.47-1.81), respectively. In contrast, the corresponding hazard ratios for ACR of 300 (versus 5) mg/g were 1.62 (1.27-2.07) for ischemic and 2.57 (1.37-4.83) for hemorrhagic stroke, with significantly stronger association with hemorrhagic stroke (P=0.04). For hemorrhagic stroke, the association of elevated ACR was of similar magnitude as that of elevated systolic blood pressure. CONCLUSIONS: Whereas albuminuria showed significant association with both stroke types, the association of decreased estimated GFR was only significant for ischemic stroke. The strong association of albuminuria with both stroke types warrants clinical attention and further investigations.
Keywords: Aged; Albuminuria; Brain Ischemia; Comorbidity; Female; Glomerular Filtration Rate; Humans; Intracranial Hemorrhages; Kidney Diseases; Male; Middle Aged; Netherlands; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; United States

B-type natriuretic peptide and C-reactive protein in the prediction of atrial fibrillation risk: the CHARGE-AF Consortium of community-based cohort studies. - Sinner, Moritz F; Stepas, Katherine A; Moser, Carlee B; Krijthe, Bouwe P; Aspelund, Thor; Sotoodehnia, Nona; Fontes, João D; Janssens, A Cecile J W; Kronmal, Richard A; Magnani, Jared W; Witteman, Jacqueline C; Chamberlain, Alanna M; et al. (Europace, 2014)
AIMS: B-type natriuretic peptide (BNP) and C-reactive protein (CRP) predict atrial fibrillation (AF) risk. However, their risk stratification abilities in the broad community remain uncertain. We sought to improve risk stratification for AF using biomarker information. METHODS AND RESULTS: We ascertained AF incidence in 18 556 Whites and African Americans from the Atherosclerosis Risk in Communities Study (ARIC, n=10 675), Cardiovascular Health Study (CHS, n = 5043), and Framingham Heart Study (FHS, n = 2838), followed for 5 years (prediction horizon). We added BNP (ARIC/CHS: N-terminal pro-B-type natriuretic peptide; FHS: BNP), CRP, or both to a previously reported AF risk score, and assessed model calibration and predictive ability [C-statistic, integrated discrimination improvement (IDI), and net reclassification improvement (NRI)]. We replicated models in two independent European cohorts: Age, Gene/Environment Susceptibility Reykjavik Study (AGES), n = 4467; Rotterdam Study (RS), n = 3203. B-type natriuretic peptide and CRP were significantly associated with AF incidence (n = 1186): hazard ratio per 1-SD ln-transformed biomarker 1.66 [95% confidence interval (CI), 1.56-1.76], P < 0.0001 and 1.18 (95% CI, 1.11-1.25), P < 0.0001, respectively. Model calibration was sufficient (BNP, χ(2) = 17.0; CRP, χ(2) = 10.5; BNP and CRP, χ(2) = 13.1). B-type natriuretic peptide improved the C-statistic from 0.765 to 0.790, yielded an IDI of 0.027 (95% CI, 0.022-0.032), a relative IDI of 41.5%, and a continuous NRI of 0.389 (95% CI, 0.322-0.455). The predictive ability of CRP was limited (C-statistic increment 0.003). B-type natriuretic peptide consistently improved prediction in AGES and RS. CONCLUSION: B-type natriuretic peptide, not CRP, substantially improved AF risk prediction beyond clinical factors in an independently replicated, heterogeneous population. B-type natriuretic peptide may serve as a benchmark to evaluate novel putative AF risk biomarkers.
Keywords: Aged; Atrial Fibrillation; Biomarkers; C-Reactive Protein; Europe; Female; Humans; Incidence; Male; Natriuretic Peptide, Brain; Peptide Fragments; Predictive Value of Tests; Risk Assessment; Risk Factors; United States

Circulating fibrosis biomarkers and risk of atrial fibrillation: The Cardiovascular Health Study (CHS). - Rosenberg, Michael A; Maziarz, Marlena; Tan, Alex Y; Glazer, Nicole L; Zieman, Susan J; Kizer, Jorge R; Ix, Joachim H; Djoussé, Luc; Siscovick, David S; Heckbert, Susan R; Mukamal, Kenneth J (Am Heart J, 2014)
BACKGROUND: Cardiac fibrosis is thought to play a central role in the pathogenesis of atrial fibrillation (AF). Retrospective studies have suggested that circulating fibrosis biomarkers are associated with AF, but prospective studies are limited. METHODS: We measured circulating levels of 2 fibrosis biomarkers, procollagen type III, N-terminal propeptide (PIIINP) and transforming growth factor β1 among participants of the CHS, a population-based study of older Americans. We used Cox proportional hazards and competing risks models to examine adjusted risk of incident AF over a median follow-up of 8.8 years. RESULTS: Levels of PIIINP were assessed in 2,935 participants, of whom 767 developed AF. Compared with the median PIIINP level (4.45 μg/L), adjusted hazard ratios (95% CIs) were 0.85 (0.72-1.00) at the 10th percentile, 0.93 (0.88-0.99) at the 25th percentile, 1.04 (0.95-1.04) at the 75th percentile, and 1.07 (0.90-1.26) at the 90th. Transforming growth factor β1 levels, assessed in 1,538 participants with 408 cases of incident AF, were not associated with AF risk. CONCLUSION: In older adults, PIIINP levels were associated with risk of incident AF in a complex manner, with an association that appeared to be positive up to median levels but with little relationship beyond that. Further studies are required to confirm and possibly delineate the mechanism for this relationship.
Keywords: Aged; Atrial Fibrillation; Biomarkers; Cardiomyopathies; Electrocardiography; Enzyme-Linked Immunosorbent Assay; Female; Fibrosis; Follow-Up Studies; Humans; Incidence; Male; Peptide Fragments; Procollagen; Prospective Studies; Risk Factors; Time Factors; Transforming Growth Factor beta1; United States

Circulating levels of carboxy‐methyl‐lysine (CML) are associated with hip fracture risk: the Cardiovascular Health Study. - Barzilay, Joshua I; Bůzková, Petra; Zieman, Susan J; Kizer, Jorge R; Djoussé, Luc; Ix, Joachim H; Tracy, Russell P; Siscovick, David S; Cauley, Jane A; Mukamal, Kenneth J (J Bone Miner Res, 2014)
Advanced glycation end products (AGE) in bone tissue are associated with impaired biomechanical properties and increased fracture risk. Here we examine whether serum levels of the AGE carboxy‐methyl‐lysine (CML) are associated with risk of hip fracture.We followed 3373 participants from the Cardiovascular Health Study (age 78 years; range, 68–102 years; 39.8% male) for a median of 9.22 years (range, 0.01–12.07 years). Rates of incident hip fracture were calculated by quartiles of baseline CML levels, and hazard ratios were adjusted for covariates associated with hip fracture risk. A subcohort of 1315 participants had bone mineral density (BMD)measurement. There were 348 hip fractures during follow‐up, with incidence rates of hip fracture by CML quartiles of 0.94, 1.34, 1.18, and 1.69 per 100 participant‐years. The unadjusted hazard ratio of hip fracture increased with each 1 SD increase (189 ng/mL) of CML level (hazard ratio, 1.27; 95% confidence interval [CI], 1.16–1.40]; p<0.001). Sequential adjustment for age, gender, race/ethnicity,body mass index (BMI), smoking, alcohol consumption, prevalent coronary heart disease (CHD), energy expenditure, and estimated glomerular filtration rate (based on cystatin C), moderately attenuated the hazard ratio for fracture (1.17; 95% CI, 1.05–1.31; p=0.006).In the cohort with BMD testing, total hip BMD was not significantly associated with CML levels. We conclude that increasing levels of CML are associated with hip fracture risk in older adults, independent of hip BMD. These results implicate AGE in the pathogenesis of hip fractures.
Keywords: Age Factors; Aged; Female; Follow-Up Studies; Glycation End Products, Advanced; Hip Fractures; Humans; Incidence; Lysine; Male; Prospective Studies; Retrospective Studies; Risk Factors

Circulating omega-6 polyunsaturated fatty acids and total and cause-specific mortality: the Cardiovascular Health Study. - Wu, Jason H Y; Lemaitre, Rozenn N; King, Irena B; Song, Xiaoling; Psaty, Bruce M; Siscovick, David S; Mozaffarian, Dariush (Circulation, 2014)
BACKGROUND: Although omega-6 polyunsaturated fatty acids (n-6 PUFA) have been recommended to reduce coronary heart disease (CHD), controversy remains about benefits versus harms, including concerns over theorized proinflammatory effects of n-6 PUFA. We investigated associations of circulating n-6 PUFA including linoleic acid (the major dietary PUFA), γ-linolenic acid, dihomo-γ-linolenic acid, and arachidonic acid, with total and cause-specific mortality in the Cardiovascular Health Study, a community-based U.S. cohort. METHODS AND RESULTS: Among 2792 participants(aged ≥65 years) free of cardiovascular disease at baseline, plasma phospholipid n-6 PUFA were measured at baseline using standardized methods. All-cause and cause-specific mortality, and total incident CHD and stroke, were assessed and adjudicated centrally. Associations of PUFA with risk were assessed by Cox regression. During 34 291 person-years of follow-up (1992-2010), 1994 deaths occurred (678 cardiovascular deaths), with 427 fatal and 418 nonfatal CHD, and 154 fatal and 399 nonfatal strokes. In multivariable models, higher linoleic acid was associated with lower total mortality, with extreme-quintile hazard ratio =0.87 (P trend=0.005). Lower death was largely attributable to cardiovascular disease causes, especially nonarrhythmic CHD mortality (hazard ratio, 0.51; 95% confidence interval, 0.32-0.82; P trend=0.001). Circulating γ-linolenic acid, dihomo-γ-linolenic acid, and arachidonic acid were not significantly associated with total or cause-specific mortality (eg, for arachidonic acid and CHD death, the extreme-quintile hazard ratio was 0.97; 95% confidence interval, 0.70-1.34; P trend=0.87). Evaluated semiparametrically, linoleic acid showed graded inverse associations with total mortality (P=0.005). There was little evidence that associations of n-6 PUFA with total mortality varied by age, sex, race, or plasma n-3 PUFA. Evaluating both n-6 and n-3 PUFA, lowest risk was evident with highest levels of both. CONCLUSIONS: High circulating linoleic acid, but not other n-6 PUFA, was inversely associated with total and CHD mortality in older adults.
Keywords: Aged; Arachidonic Acid; Biomarkers; Cohort Studies; Coronary Disease; Fatty Acids, Omega-3; Fatty Acids, Omega-6; Fatty Acids, Unsaturated; Female; Follow-Up Studies; Humans; Linoleic Acid; Male; Prospective Studies; Regression Analysis; Risk Factors; Stroke; Survival Rate; United States

Common carotid intima-media thickness measurements do not improve cardiovascular risk prediction in individuals with elevated blood pressure: the USE-IMT collaboration. - Bots, Michiel L; Groenewegen, Karlijn A; Anderson, Todd J; Britton, Annie R; Dekker, Jacqueline M; Engström, Gunnar; Evans, Greg W; de Graaf, Jacqueline; Grobbee, Diederick E; Hedblad, Bo; Hofman, Albert; Holewijn, Suzanne; et al. (Hypertension, 2014)
Carotid intima-media thickness (CIMT) is a marker of cardiovascular risk. It is unclear whether measurement of mean common CIMT improves 10-year risk prediction of first-time myocardial infarction or stroke in individuals with elevated blood pressure. We performed an analysis among individuals with elevated blood pressure (i.e., a systolic blood pressure ≥140 mm Hg and a diastolic blood pressure ≥ 90 mm Hg) in USE-IMT, a large ongoing individual participant data meta-analysis. We refitted the risk factors of the Framingham Risk Score on asymptomatic individuals (baseline model) and expanded this model with mean common CIMT (CIMT model) measurements. From both models, 10-year risks to develop a myocardial infarction or stroke were estimated. In individuals with elevated blood pressure, we compared discrimination and calibration of the 2 models and calculated the net reclassification improvement (NRI). We included 17 254 individuals with elevated blood pressure from 16 studies. During a median follow-up of 9.9 years, 2014 first-time myocardial infarctions or strokes occurred. The C-statistics of the baseline and CIMT models were similar (0.73). NRI with the addition of mean common CIMT was small and not significant (1.4%; 95% confidence intervals, -1.1 to 3.7). In those at intermediate risk (n=5008, 10-year absolute risk of 10% to 20%), the NRI was 5.6% (95% confidence intervals, 1.6-10.4). There is no added value of measurement of mean common CIMT in individuals with elevated blood pressure for improving cardiovascular risk prediction. For those at intermediate risk, the addition of mean common CIMT to an existing cardiovascular risk score is small but statistically significant.
Keywords: Adult; Aged; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Carotid Artery, Common; Carotid Intima-Media Thickness; Cohort Studies; Female; Humans; Hypertension; Male; Meta-Analysis as Topic; Middle Aged; Risk Assessment; Risk Factors

A common SCN5A variant is associated with PR interval and atrial fibrillation among African Americans. - Ilkhanoff, Leonard; Arking, Dan E; Lemaitre, Rozenn N; Alonso, Alvaro; Chen, Lin Y; Durda, Peter; Hesselson, Stephanie E; Kerr, Kathleen F; Magnani, Jared W; Marcus, Gregory M; Schnabel, Renate B; Smith, J Gustav; et al. (J Cardiovasc Electrophysiol, 2014)
OBJECTIVE: We examined the association of rs7626962 (S1103Y) or rs7629265, a variant in high linkage disequilibrium with S1103Y (r(2) = 0.87 - 1), with sudden cardiac death (SCD) and atrial fibrillation (AF) among African Americans. BACKGROUND: The SCN5A missense variant S1103Y has been associated with SCD among African Americans in small case-control studies, but larger population-based studies are needed to validate these findings. The association of this variant with AF has not been fully explored. METHODS: Using genotyping data on over 7,000 African Americans from 5 cohorts (Atherosclerosis Risk in Communities [ARIC], Cleveland Family Study [CFS], Jackson Heart Study [JHS], Multi-Ethnic Study of Atherosclerosis [MESA], Cardiovascular Health Study [CHS]), we examined the association of rs7629265 with electrocardiographic PR, QRS, and QT intervals, and with incident AF and SCD. We examined association of S1103Y (rs7626962) with SCD using a population-based case-control study of SCD Cardiac Arrest Blood Study (CABS). RESULTS: Meta-analyses across 5 cohorts demonstrated that rs7629265 was significantly associated with PR duration (β = -4.1 milliseconds; P = 2.2×10(-6) ), but not significantly associated with QRS or QT intervals. In meta-analyses of prospectively followed ARIC and CHS participants (n = 3,656), rs7629265 was associated with increased AF risk (n = 299 AF cases; HR = 1.74, P = 1.9 × 10(-4) ). By contrast, rs7629265 was not significantly associated with SCD risk in ARIC (n = 83 SCD cases; P = 0.30) or CHS (n = 54 SCD cases; P = 0.47). Similarly, S1103Y was not significantly associated with SCD risk in CABS (n = 225 SCD cases; P = 0.29). CONCLUSION: The common SCN5A variant, rs7629265, is associated with increased AF risk and shorter PR interval among African Americans. In contrast to prior reports, we found no evidence of association of rs7629265 or rs7626962 (S1103Y) with SCD risk in the general population.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Atrial Fibrillation; Case-Control Studies; Cohort Studies; Death, Sudden, Cardiac; Female; Genetic Variation; Humans; Male; Middle Aged; NAV1.5 Voltage-Gated Sodium Channel; Prospective Studies; Risk Factors; Single-Blind Method

Common variation in fatty acid metabolic genes and risk of incident sudden cardiac arrest. - Lemaitre, Rozenn N; Johnson, Catherine O; Hesselson, Stephanie; Sotoodehnia, Nona; Sotoodhenia, Nona; McKnight, Barbara; Sitlani, Colleen M; Rea, Thomas D; King, Irena B; Kwok, Pui-Yan; Mak, Angel; Li, Guo; et al. (Heart Rhythm, 2014)
BACKGROUND: There is limited information on genetic factors associated with sudden cardiac arrest (SCA). OBJECTIVE: To assess the association of common variation in genes in fatty acid pathways with SCA risk. METHODS: We selected 85 candidate genes and 1155 single nucleotide polymorphisms (SNPs) tagging common variation in each gene. We investigated the SNP associations with SCA in a population-based case-control study. Cases (n = 2160) were from a repository of SCA in the greater Seattle area. Controls (n = 2615), frequency-matched on age and sex, were from the same area. We used linear logistic regression to examine SNP associations with SCA. We performed permutation-based p-min tests to account for multiple comparisons within each gene. The SNP associations with a corrected P value of <.05 were then examined in a meta-analysis of these SNP associations in 9 replication studies totaling 2129 SCA cases and 23,833 noncases. RESULTS: Eight SNPs in or near 8 genes were associated with SCA risk in the discovery study, one of which was nominally significant in the replication phase (rs7737692, minor allele frequency 36%, near the LPCAT1 gene). For each copy of the minor allele, rs7737692 was associated with 13% lower SCA risk (95% confidence interval -21% to -5%) in the discovery phase and 9% lower SCA risk (95% confidence interval -16% to -1%) in the replication phase. CONCLUSIONS: While none of the associations reached significance with Bonferroni correction, a common genetic variant near LPCAT1, a gene involved in the remodeling of phospholipids, was nominally associated with incident SCA risk. Further study is needed to validate this observation.
Keywords: 1-Acylglycerophosphocholine O-Acyltransferase; Aged; Algorithms; Alleles; Case-Control Studies; Death, Sudden, Cardiac; Fatty Acids; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Male; Polymorphism, Single Nucleotide; Risk Factors

Coronary heart disease risks associated with high levels of HDL cholesterol. - Wilkins, John T; Ning, Hongyan; Stone, Neil J; Criqui, Michael H; Zhao, Lihui; Greenland, Philip; Lloyd-Jones, Donald M (J Am Heart Assoc, 2014)
BACKGROUND: The association between high-density lipoprotein cholesterol (HDL-C) and coronary heart disease (CHD) events is not well described in individuals with very high levels of HDL-C (>80 mg/dL). METHODS AND RESULTS: Using pooled data from 6 community-based cohorts we examined CHD and total mortality risks across a broad range of HDL-C, including values in excess of 80 mg/dL. We used Cox proportional hazards models with penalized splines to assess multivariable, adjusted, sex-stratified associations of HDL-C with the hazard for CHD events and total mortality, using HDL-C 45 mg/dL and 55 mg/dL as the referent in men and women, respectively. Analyses included 11 515 men and 12 925 women yielding 307 245 person-years of follow-up. In men, the association between HDL-C and CHD events was inverse and linear across most HDL-C values; however at HDL-C values >90 mg/dL there was a plateau effect in the pattern of association. In women, the association between HDL-C and CHD events was inverse and linear across lower values of HDL-C, however at HDL-C values >75 mg/dL there were no further reductions in the hazard ratio point estimates for CHD. In unadjusted models there were increased total mortality risks in men with very high HDL-C, however mortality risks observed in participants with very high HDL-C were attenuated after adjustment for traditional risk factors. CONCLUSIONS: We did not observe further reductions in CHD risk with HDL-C values higher than 90 mg/dL in men and 75 mg/dL in women.
Keywords: Aged; Biomarkers; Cholesterol, HDL; Coronary Disease; Female; Humans; Linear Models; Male; Middle Aged; Multivariate Analysis; Prognosis; Proportional Hazards Models; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation

Development and validation of an ankle brachial index risk model for the prediction of cardiovascular events. - Fowkes, F G R; Murray, G D; Butcher, I; Folsom, A R; Hirsch, A T; Couper, D J; deBacker, G; Kornitzer, M; Newman, A B; Sutton-Tyrrell, K C; Cushman, M; Lee, A J; et al. (Eur J Prev Cardiol, 2014)
BACKGROUND: The ankle brachial index (ABI) is related to risk of cardiovascular events independent of the Framingham risk score (FRS). The aim of this study was to develop and evaluate a risk model for cardiovascular events incorporating the ABI and FRS. DESIGN: An analysis of participant data from 18 cohorts in which 24,375 men and 20,377 women free of coronary heart disease had ABI measured and were followed up for events. METHODS: Subjects were divided into a development and internal validation dataset and an external validation dataset. Two models, comprising FRS and FRS + ABI, were fitted for the primary outcome of major coronary events. RESULTS: In predicting events in the external validation dataset, C-index for the FRS was 0.672 (95% CI 0.599 to 0.737) in men and 0.578 (95% CI 0.492 to 0.661) in women. The FRS + ABI led to a small increase in C-index in men to 0.685 (95% CI 0.612 to 0.749) and large increase in women to 0.690 (95% CI 0.605 to 0.764) with net reclassification improvement (NRI) of 4.3% (95% CI 0.0 to 7.6%, p = 0.050) and 9.6% (95% CI 6.1 to 16.4%, p < 0.001), respectively. Restricting the FRS + ABI model to those with FRS intermediate 10-year risk of 10 to 19% resulted in higher NRI of 15.9% (95% CI 6.1 to 20.6%, p < 0.001) in men and 23.3% (95% CI 13.8 to 62.5%, p = 0.002) in women. However, incorporating ABI in an improved newly fitted risk factor model had a nonsignificant effect: NRI 2.0% (95% CI 2.3 to 4.2%, p = 0.567) in men and 1.1% (95% CI 1.9 to 4.0%, p = 0.483) in women. CONCLUSIONS: An ABI risk model may improve prediction especially in individuals at intermediate risk and when performance of the base risk factor model is modest.
Keywords: Adult; Aged; Aged, 80 and over; Ankle Brachial Index; Cardiovascular Diseases; Europe; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Models, Statistical; Predictive Value of Tests; Prognosis; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Time Factors; United States; Young Adult

Evidence of heterogeneity by race/ethnicity in genetic determinants of QT interval. - Seyerle, Amanda A; Young, Alicia M; Jeff, Janina M; Melton, Phillip E; Jorgensen, Neal W; Lin, Yi; Carty, Cara L; Deelman, Ewa; Heckbert, Susan R; Hindorff, Lucia A; Jackson, Rebecca D; Martin, Lisa W; et al. (Epidemiology, 2014)
BACKGROUND: QT interval (QT) prolongation is an established risk factor for ventricular tachyarrhythmia and sudden cardiac death. Previous genome-wide association studies in populations of the European descent have identified multiple genetic loci that influence QT, but few have examined these loci in ethnically diverse populations. METHODS: Here, we examine the direction, magnitude, and precision of effect sizes for 21 previously reported SNPs from 12 QT loci, in populations of European (n = 16,398), African (n = 5,437), American Indian (n = 5,032), Hispanic (n = 1,143), and Asian (n = 932) descent as part of the Population Architecture using Genomics and Epidemiology (PAGE) study. Estimates obtained from linear regression models stratified by race/ethnicity were combined using inverse-variance weighted meta-analysis. Heterogeneity was evaluated using Cochran's Q test. RESULTS: Of 21 SNPs, 7 showed consistent direction of effect across all 5 populations, and an additional 9 had estimated effects that were consistent across 4 populations. Despite consistent direction of effect, 9 of 16 SNPs had evidence (P < 0.05) of heterogeneity by race/ethnicity. For these 9 SNPs, linkage disequilibrium plots often indicated substantial variation in linkage disequilibrium patterns among the various racial/ethnic groups, as well as possible allelic heterogeneity. CONCLUSIONS: These results emphasize the importance of analyzing racial/ethnic groups separately in genetic studies. Furthermore, they underscore the possible utility of trans-ethnic studies to pinpoint underlying casual variants influencing heritable traits such as QT.
Keywords: Aged; Continental Population Groups; Electrocardiography; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Long QT Syndrome; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

Extreme deep white matter hyperintensity volumes are associated with African American race. - Nyquist, Paul A; Bilgel, Murat S; Gottesman, Rebecca; Yanek, Lisa R; Moy, Taryn F; Becker, Lewis C; Cuzzocreo, Jennifer; Prince, Jerry; Yousem, David M; Becker, Diane M; Kral, Brian G; Vaidya, Dhananjay (Cerebrovasc Dis, 2014)
BACKGROUND: African Americans (AAs) have a higher prevalence of extreme ischemic white matter hyperintensities (WMHs) on magnetic resonance imaging (MRI) than do European Americans (EAs) based on the Cardiovascular Health Study (CHS) score. Ischemic white matter disease, limited to the deep white matter, may be biologically distinct from disease in other regions and may reflect a previously observed trend toward an increased risk of subcortical lacunar infarcts in AAs. We hypothesized that extreme deep WMH volume (DWMV) or periventricular volume (PV) may also have a higher prevalence in AAs. Thus, we studied extreme CHS scores and extreme DWMV and PV in a healthy population enriched for cardiovascular disease risk factors. METHODS: We imaged the brains of 593 subjects who were first-degree relatives of probands with early onset coronary disease prior to 60 years of age. WMHs were manually delineated on 3-tesla cranial MRI by a trained radiology reader; the location and volume of lesions were characterized using automated software. DWMV and PV were measured directly with automated software, and the CHS score was determined by a neuroradiologist. Volumes were characterized as being in the upper 25% versus lower 75% of total lesion volume. Volumes in the upper versus the remaining quartiles were examined for AA versus EA race using multiple logistic regression (generalized estimating equations adjusted for family relatedness) and adjusted for major vascular disease risk factors including age ≥55 years versus <55, sex, current smoking, obesity, hypertension, diabetes and low-density lipoprotein >160 mg/dl. RESULTS: Participants were 58% women and 37% AAs, with a mean age of 51.5 ± 11.0 years (range, 29-74 years). AAs had significantly higher odds of having extreme DWMVs (odds ratio, OR, 1.8; 95% confidence interval, CI, 1.2-2.9; p = 0.0076) independently of age, sex, hypertension and all other risk factors. AAs also had significantly higher odds of having extreme CHS scores ≥3 (OR, 1.3; 95% CI, 1.1-3.6; p = 0.025). Extreme PV was not significantly associated with AA race (OR, 1.3; 95% CI, 0.81-2.1; p = 0.26). CONCLUSIONS: AAs from families with early-onset cardiovascular disease are more likely to have extreme DWMVs (a subclinical form of cerebrovascular disease) and an extreme CHS score, but not extreme PV, independently of age and other cardiovascular disease risk factors. These findings suggest that this AA population is at an increased risk for DWMV and may be at an increased risk for future subcortical stroke. Longitudinal studies are required to see if DWMV is predictive of symptomatic subcortical strokes in this population.
Keywords: Adult; African Americans; Age Factors; Aged; Cerebrovascular Disorders; European Continental Ancestry Group; Female; Humans; Hypertension; Magnetic Resonance Imaging; Male; Middle Aged; Prevalence; Risk Factors; White Matter

Fibroblast growth factor 23, the ankle-brachial index, and incident peripheral artery disease in the Cardiovascular Health Study. - Garimella, Pranav S; Ix, Joachim H; Katz, Ronit; Chonchol, Michel B; Kestenbaum, Bryan R; de Boer, Ian H; Siscovick, David S; Shastri, Shani; Hiramoto, Jade S; Shlipak, Michael G; Sarnak, Mark J (Atherosclerosis, 2014)
BACKGROUND: Fibroblast growth factor 23 (FGF23) has emerged as a novel risk factor for mortality and cardiovascular events. Its association with the ankle-brachial index (ABI) and clinical peripheral artery disease (PAD) is less known. METHODS: Using data (N = 3143) from the Cardiovascular Health Study (CHS), a cohort of community dwelling adults >65 years of age, we analyzed the cross-sectional association of FGF23 with ABI and its association with incident clinical PAD events during 9.8 years of follow up using multinomial logistic regression and Cox proportional hazards models respectively. RESULTS: The prevalence of cardiovascular disease (CVD) and traditional risk factors like diabetes, coronary artery disease, and heart failure increased across higher quartiles of FGF23. Compared to those with ABI of 1.1-1.4, FGF23 per doubling at baseline was associated with prevalent PAD (ABI < 0.9) although this association was attenuated after adjusting for CVD risk factors, and kidney function (OR 0.91, 95% CI 0.76-1.08). FGF23 was not associated with high ABI (>1.4) (OR 1.06, 95% CI 0.75-1.51). Higher FGF23 was associated with incidence of PAD events in unadjusted, demographic adjusted, and CVD risk factor adjusted models (HR 2.26, 95% CI 1.28-3.98; highest versus lowest quartile). The addition of estimated glomerular filtration and urine albumin to creatinine ratio to the model however, attenuated these findings (HR 1.46, 95% CI, 0.79-2.70). CONCLUSIONS: In community dwelling older adults, FGF23 was not associated with baseline low or high ABI or incident PAD events after adjusting for confounding variables. These results suggest that FGF23 may primarily be associated with adverse cardiovascular outcomes through non atherosclerotic mechanisms.
Keywords: Aged; Ankle Brachial Index; Cardiovascular Diseases; Cross-Sectional Studies; Fibroblast Growth Factors; Humans; Incidence; Peripheral Arterial Disease; Risk Factors

Fibroblast growth factor-23 and incident atrial fibrillation: the Multi-Ethnic Study of Atherosclerosis (MESA) and the Cardiovascular Health Study (CHS). - Mathew, Jehu S; Sachs, Michael C; Katz, Ronit; Patton, Kristen K; Heckbert, Susan R; Hoofnagle, Andrew N; Alonso, Alvaro; Chonchol, Michel; Deo, Rajat; Ix, Joachim H; Siscovick, David S; Kestenbaum, Bryan; et al. (Circulation, 2014)
BACKGROUND: Fibroblast growth factor-23 (FGF-23) is a hormone that promotes urinary phosphate excretion and regulates vitamin D metabolism. Circulating FGF-23 concentrations increase markedly in chronic kidney disease and are associated with increased risk of clinical cardiovascular events. FGF-23 may promote atrial fibrillation (AF) by inducing left ventricular hypertrophy and diastolic and left atrial dysfunction. METHODS AND RESULTS: We tested the associations of circulating FGF-23 concentration with incident AF among 6398 participants in the Multi-Ethnic Study of Atherosclerosis (MESA) and 1350 participants in the Cardiovascular Health Study (CHS), all free of clinical cardiovascular disease at baseline. Over a median of 7.7 and 8.0 years of follow-up, we observed 291 and 229 incident AF events in MESA and CHS, respectively. In multivariable Cox proportional hazards models, each 2-fold-higher FGF-23 concentration was associated with a 41% higher risk of incident AF in MESA (hazard ratio, 1.41; 95% confidence interval, 1.13-1.76; P=0.003) and a 30% higher risk of incident AF in CHS (hazard ratio, 1.30; 95% confidence interval, 1.05-1.61; P=0.016) after adjustment for potential confounding characteristics, including kidney disease. Serum phosphate concentration was significantly associated with incident AF in MESA (hazard ratio, 1.15 per 0.5 mg/dL; 95% confidence interval, 1.02-1.31; P=0.023) but not CHS. In MESA, an association of low estimated glomerular filtration rate with incident AF was partially attenuated by adjustment for FGF-23. CONCLUSION: Higher circulating FGF-23 concentration is associated with incident AF and may, in part, explain the link between chronic kidney disease and AF.
Keywords: Aged; Aged, 80 and over; Atrial Fibrillation; Comorbidity; Ethnic Groups; Female; Fibroblast Growth Factor 3; Follow-Up Studies; Glomerular Filtration Rate; Heart Failure; Humans; Hypertrophy, Left Ventricular; Male; Middle Aged; Phosphates; Proportional Hazards Models; Renal Insufficiency, Chronic; Risk Factors; United States; Ventricular Dysfunction, Left; Ventricular Remodeling; Vitamin D

Fibroblast growth factor-23 and the long-term risk of hospital-associated AKI among community-dwelling older individuals. - Brown, Jeremiah R; Katz, Ronit; Ix, Joachim H; de Boer, Ian H; Siscovick, David S; Grams, Morgan E; Shlipak, Michael; Sarnak, Mark J (Clin J Am Soc Nephrol, 2014)
BACKGROUND AND OBJECTIVES: AKI occurs frequently in older persons. Elevated circulating fibroblast growth factor-23 (FGF-23), a known marker of impaired mineral metabolism, may also reflect tubular dysfunction and risk of AKI. This study evaluated FGF-23 as well as traditional markers of kidney disease, namely urine albumin-to-creatinine ratio (UACR) and creatinine-cystatin C estimated GFR (eGFRCrCyC), as risk factors for AKI in elderly individuals. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Plasma FGF-23, UACR, and eGFRCrCyC were measured in 3241 community-dwelling elderly individuals in the Cardiovascular Health Study. Hospitalization for AKI was defined by International Classification of Diseases, Ninth Revision, Clinical Modification codes. Associations of each biomarker with AKI were evaluated using Cox proportional hazards models adjusted for demographics, cardiovascular risk factors, and biomarkers of kidney function. RESULTS: The mean participant age was 78 years; 60% of participants were women and 16% were African American. The median (interquartile range) values of biomarkers were as follows: FGF-23, 70 RU/ml (53, 99); UACR, 8.88 mg/g (4.71, 20.47); and eGFRCrCyC, 71 ml/min per 1.73 m(2) (59, 83). Hospitalized AKI occurred in 119 participants over 10.0 years of median follow-up. In fully adjusted analyses, compared with the lowest quartiles, the highest quartiles of FGF-23 (≥100 RU/ml) and UACR (≥20.9 mg/g) were associated with AKI (FGF-23: hazard ratio [HR], 1.99; 95% confidence interval [95% CI], 1.04 to 3.80; and UACR: HR, 3.35; 95% CI, 1.83 to 6.13). Compared with the highest quartile, the lowest quartile of eGFRCrCyC (<57 ml/min per 1.73 m(2)) was associated with AKI with an HR of 2.15 (95% CI, 1.21 to 3.82). CONCLUSIONS: FGF-23 adjusted for albuminuria, cardiovascular disease risk factors, and baseline eGFR is independently associated with a higher risk of AKI hospitalizations in community-dwelling elderly individuals. Further studies to understand the nature of this association are warranted.
Keywords: Acute Kidney Injury; Age Factors; Aged; Aged, 80 and over; Albuminuria; Biomarkers; Creatinine; Cystatin C; Female; Fibroblast Growth Factors; Glomerular Filtration Rate; Hospitalization; Humans; Independent Living; Kidney; Longitudinal Studies; Male; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Factors; Time Factors

Fibrosis-related biomarkers and incident cardiovascular disease in older adults: the cardiovascular health study. - Agarwal, Isha; Glazer, Nicole L; Barasch, Eddy; Biggs, Mary L; Djoussé, Luc; Fitzpatrick, Annette L; Gottdiener, John S; Ix, Joachim H; Kizer, Jorge R; Rimm, Eric B; Sicovick, David S; Tracy, Russell P; et al. (Circ Arrhythm Electrophysiol, 2014)
BACKGROUND: Fibrotic changes in the heart and arteries have been implicated in a diverse range of cardiovascular diseases (CVD), but whether circulating biomarkers that reflect fibrosis are associated with CVD is unknown. METHODS AND RESULTS: We determined the associations of 2 biomarkers of fibrosis, transforming growth factor- β (TGF-β), and procollagen type III N-terminal propeptide (PIIINP), with incident heart failure, myocardial infarction, and stroke among community-living older adults in the Cardiovascular Health Study. We measured circulating TGF-β (n=1371) and PIIINP (n=2568) from plasma samples collected in 1996 and ascertained events through 2010. Given TGF-β's pleiotropic effects on inflammation and fibrogenesis, we investigated potential effect modification by C-reactive protein in secondary analyses. After adjustment for sociodemographic, clinical, and biochemical risk factors, PIIINP was associated with total CVD (hazard ratio [HR] per SD=1.07; 95% confidence interval [CI], 1.01-1.14) and heart failure (HR per SD=1.08; CI, 1.01-1.16) but not myocardial infarction or stroke. TGF-β was not associated with any CVD outcomes in the full cohort but was associated with total CVD (HR per SD=1.16; CI, 1.02-1.31), heart failure (HR per SD=1.16; CI, 1.01-1.34), and stroke (HR per SD=1.20; CI, 1.01-1.42) among individuals with C-reactive protein above the median, 2.3 mg/L (P interaction <0.05). CONCLUSIONS: Our findings provide large-scale, prospective evidence that circulating biomarkers of fibrosis, measured in community-living individuals late in life, are associated with CVD. Further research on whether TGF-β has a stronger fibrogenic effect in the setting of inflammation is warranted.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; Female; Fibrosis; Heart Failure; Humans; Incidence; Male; Myocardial Infarction; Peptide Fragments; Procollagen; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; Stroke; Time Factors; Transforming Growth Factor beta; United States

Fibrosis-related biomarkers and risk of total and cause-specific mortality: the cardiovascular health study. - Agarwal, Isha; Glazer, Nicole L; Barasch, Eddy; Biggs, Mary L; Djoussé, Luc; Fitzpatrick, Annette L; Gottdiener, John S; Ix, Joachim H; Kizer, Jorge R; Rimm, Eric B; Siscovick, David S; Tracy, Russell P; et al. (Am J Epidemiol, 2014)
Fibrosis has been implicated in diverse diseases of the liver, kidney, lungs, and heart, but its importance as a risk factor for mortality remains unconfirmed. We determined the prospective associations of 2 complementary biomarkers of fibrosis, transforming growth factor-β (TGF-β) and procollagen type III N-terminal propeptide (PIIINP), with total and cause-specific mortality risks among community-living older adults in the Cardiovascular Health Study (1996-2010). We measured circulating TGF-β and PIIINP levels in plasma samples collected in 1996 and ascertained the number of deaths through 2010. Both TGF-β and PIIINP were associated with elevated risks of total and pulmonary mortality after adjustment for sociodemographic, clinical, and biochemical risk factors. For total mortality, the hazard ratios per doubling of TGF-β and PIIINP were 1.09 (95% confidence interval (CI): 1.01, 1.17; P = 0.02) and 1.14 (CI: 1.03, 1.27; P = 0.01), respectively. The corresponding hazard ratios for pulmonary mortality were 1.27 (CI: 1.01, 1.60; P = 0.04) for TGF-β and 1.52 (CI: 1.11, 2.10; P = 0.01) for PIIINP. Associations of TGF-β and PIIINP with total and pulmonary mortality were strongest among individuals with higher C-reactive protein concentrations (P for interaction < 0.05). Our findings provide some of the first large-scale prospective evidence that circulating biomarkers of fibrosis measured late in life are associated with death.
Keywords: Aged; Aged, 80 and over; Biomarkers; Cause of Death; Female; Fibrosis; Follow-Up Studies; Humans; Likelihood Functions; Male; Multivariate Analysis; Peptide Fragments; Procollagen; Proportional Hazards Models; Prospective Studies; Risk Factors; Transforming Growth Factor beta

Genetic determinants of age-related macular degeneration in diverse populations from the PAGE study. - Restrepo, Nicole A; Spencer, Kylee L; Goodloe, Robert; Garrett, Tiana A; Heiss, Gerardo; Bůzková, Petra; Jorgensen, Neal; Jensen, Richard A; Matise, Tara C; Hindorff, Lucia A; Klein, Barbara E K; Klein, Ronald; et al. (Invest Ophthalmol Vis Sci, 2014)
PURPOSE: Substantial progress has been made in identifying susceptibility variants for AMD in European populations; however, few studies have been conducted to understand the role these variants play in AMD risk in diverse populations. The present study aims to examine AMD risk across diverse populations in known and suspected AMD complement factor and lipid-related loci. METHODS: Targeted genotyping was performed across study sites for AMD and lipid trait-associated single nucleotide polymorphism (SNPs). Genetic association tests were performed at individual sites and then meta-analyzed using logistic regression assuming an additive genetic model stratified by self-described race/ethnicity. Participants included cases with early or late AMD and controls with no signs of AMD as determined by fundus photography. Populations included in this study were European Americans, African Americans, Mexican Americans, and Singaporeans from the Population Architecture using Genomics and Epidemiology (PAGE) study. RESULTS: Index variants of AMD, rs1061170 (CFH) and rs10490924 (ARMS2), were associated with AMD at P=3.05×10(-8) and P=6.36×10(-6), respectively, in European Americans. In general, none of the major AMD index variants generalized to our non-European populations with the exception of rs10490924 in Mexican Americans at an uncorrected P value<0.05. Four lipid-associated SNPS (LPL rs328, TRIB1 rs6987702, CETP rs1800775, and KCTD10/MVK rs2338104) were associated with AMD in African Americans and Mexican Americans (P<0.05), but these associations did not survive strict corrections for multiple testing. CONCLUSIONS: While most associations did not generalize in the non-European populations, variants within lipid-related genes were found to be associated with AMD. This study highlights the need for larger well-powered studies in non-European populations.
Keywords: Adult; Aged; Aged, 80 and over; Complement Factor H; DNA; Ethnic Groups; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Macular Degeneration; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Prevalence; Prospective Studies; Proteins; Risk Factors; United States

Genetic variants related to height and risk of atrial fibrillation: the cardiovascular health study. - Rosenberg, Michael A; Kaplan, Robert C; Siscovick, David S; Psaty, Bruce M; Heckbert, Susan R; Newton-Cheh, Christopher; Mukamal, Kenneth J (Am J Epidemiol, 2014)
Increased height is a known independent risk factor for atrial fibrillation (AF). However, whether genetic determinants of height influence risk is uncertain. In this candidate gene study, we examined the association of 209 height-associated single-nucleotide polymorphisms (SNPs) with incident AF in 3,309 persons of European descent from the Cardiovascular Health Study, a prospective cohort study of older adults (aged ≥ 65 years) enrolled in 1989-1990. After a median follow-up period of 13.2 years, 879 participants developed incident AF. The height-associated SNPs together explained approximately 10% of the variation in height (P = 6.0 × 10(-8)). Using an unweighted genetic height score, we found a nonsignificant association with risk of AF (per allele, hazard ratio = 1.01, 95% confidence interval: 1.00, 1.02; P = 0.06). In weighted analyses, we found that genetically predicted height was strongly associated with AF risk (per 10 cm, hazard ratio = 1.30, 95% confidence interval: 1.03, 1.64; P = 0.03). Importantly, for all models, the inclusion of actual height completely attenuated the genetic height effect. Finally, we identified 1 nonsynonymous SNP (rs1046934) that was independently associated with AF and may warrant future study. In conclusion, we found that genetic determinants of height appear to increase the risk of AF, primarily via height itself. This approach of examining SNPs associated with an intermediate phenotype should be considered as a method for identifying novel genetic targets.
Keywords: African Americans; Aged; Atrial Fibrillation; Body Height; Endonucleases; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Male; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk Factors

Genome-wide association study for circulating tissue plasminogen activator levels and functional follow-up implicates endothelial STXBP5 and STX2. - Huang, Jie; Huffman, Jennifer E; Yamakuchi, Munekazu; Yamkauchi, Munekazu; Trompet, Stella; Asselbergs, Folkert W; Sabater-Lleal, Maria; Trégouët, David-Alexandre; Chen, Wei-Min; Smith, Nicholas L; Kleber, Marcus E; Shin, So-Youn; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Tissue plasminogen activator (tPA), a serine protease, catalyzes the conversion of plasminogen to plasmin, the major enzyme responsible for endogenous fibrinolysis. In some populations, elevated plasma levels of tPA have been associated with myocardial infarction and other cardiovascular diseases. We conducted a meta-analysis of genome-wide association studies to identify novel correlates of circulating levels of tPA. APPROACH AND RESULTS: Fourteen cohort studies with tPA measures (N=26 929) contributed to the meta-analysis. Three loci were significantly associated with circulating tPA levels (P<5.0×10(-8)). The first locus is on 6q24.3, with the lead single nucleotide polymorphism (SNP; rs9399599; P=2.9×10(-14)) within STXBP5. The second locus is on 8p11.21. The lead SNP (rs3136739; P=1.3×10(-9)) is intronic to POLB and <200 kb away from the tPA encoding the gene PLAT. We identified a nonsynonymous SNP (rs2020921) in modest linkage disequilibrium with rs3136739 (r(2)=0.50) within exon 5 of PLAT (P=2.0×10(-8)). The third locus is on 12q24.33, with the lead SNP (rs7301826; P=1.0×10(-9)) within intron 7 of STX2. We further found evidence for the association of lead SNPs in STXBP5 and STX2 with expression levels of the respective transcripts. In in vitro cell studies, silencing STXBP5 decreased the release of tPA from vascular endothelial cells, whereas silencing STX2 increased the tPA release. Through an in silico lookup, we found no associations of the 3 lead SNPs with coronary artery disease or stroke. CONCLUSIONS: We identified 3 loci associated with circulating tPA levels, the PLAT region, STXBP5, and STX2. Our functional studies implicate a novel role for STXBP5 and STX2 in regulating tPA release.
Keywords: Aged; Cells, Cultured; Coronary Artery Disease; Endothelial Cells; Europe; Female; Gene Expression Regulation; Gene Silencing; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; R-SNARE Proteins; Risk Factors; Stroke; Syntaxin 1; Tissue Plasminogen Activator; Transfection; United States; Up-Regulation

Genome-wide association study of L-arginine and dimethylarginines reveals novel metabolic pathway for symmetric dimethylarginine. - Lüneburg, Nicole; Lieb, Wolfgang; Zeller, Tanja; Chen, Ming-Huei; Maas, Renke; Carter, Angela M; Xanthakis, Vanessa; Glazer, Nicole L; Schwedhelm, Edzard; Seshadri, Sudha; Ikram, Mohammad Arfan; Longstreth, William T; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Dimethylarginines (DMA) interfere with nitric oxide formation by inhibiting nitric oxide synthase (asymmetrical DMA [ADMA]) and l-arginine uptake into the cell (ADMA and symmetrical DMA [SDMA]). In prospective clinical studies, ADMA has been characterized as a cardiovascular risk marker, whereas SDMA is a novel marker for renal function and associated with all-cause mortality after ischemic stroke. The aim of the current study was to characterize the environmental and genetic contributions to interindividual variability of these biomarkers. METHODS AND RESULTS: This study comprised a genome-wide association analysis of 3 well-characterized population-based cohorts (Framingham Heart Study [FHS; n=2992], Gutenberg Health Study [GHS; n=4354], and Multinational Monitoring of Trends and Determinants in Cardiovascular Disease Study [MONICA]/Cooperative Health Research in the Augsburg Area, Augsburg, Bavaria, Germany [KORA] F3 [n=581]) and identified replicated loci (DDAH1, MED23, Arg1, and AGXT2) associated with the interindividual variability in ADMA, l-arginine, and SDMA. Experimental in silico and in vitro studies confirmed functional significance of the identified AGXT2 variants. Clinical outcome analysis in 384 patients of the Leeds stroke study demonstrated an association between increased plasma levels of SDMA, AGXT2 variants, and various cardiometabolic risk factors. AGXT2 variants were not associated with poststroke survival in the Leeds study or were they associated with incident stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. CONCLUSIONS: These genome-wide association study support the importance of DDAH1 and MED23/Arg1 in regulating ADMA and l-arginine metabolism, respectively, and identify a novel regulatory renal pathway for SDMA by AGXT2. AGXT2 variants might explain part of the pathogenic link between SDMA, renal function, and outcome. An association between AGXT2 variants and stroke is unclear and warrants further investigation.
Keywords: Adult; Aged; Amidohydrolases; Arginine; Binding Sites; Cohort Studies; Female; Genetic Loci; Genome-Wide Association Study; Genotype; HEK293 Cells; Humans; Male; Mediator Complex; Middle Aged; Polymorphism, Single Nucleotide; Protein Structure, Tertiary; Risk Factors; Stroke; Substrate Specificity; Transaminases

Height and risk of sudden cardiac death: the Atherosclerosis Risk in Communities and Cardiovascular Health studies. - Rosenberg, Michael A; Lopez, Faye L; Bůzková, Petra; Adabag, Selcuk; Chen, Lin Y; Sotoodehnia, Nona; Kronmal, Richard A; Siscovick, David S; Alonso, Alvaro; Buxton, Alfred; Folsom, Aaron R; Mukamal, Kenneth J (Ann Epidemiol, 2014)
PURPOSE: Sudden cardiac death (SCD) is an important cause of mortality in the adult population. Height has been associated with cardiac hypertrophy and an increased risk of arrhythmias but also with decreased risk of coronary heart disease, suggesting a complex association with SCD. METHODS: We examined the association of adult height with the risk of physician-adjudicated SCD in two large population-based cohorts: the Cardiovascular Health Study and the Atherosclerosis Risk in Communities study. RESULTS: Over an average follow-up time of 11.7 years in Cardiovascular Health Study, there were 199 (3.6%) cases of SCD among 5556 participants. In Atherosclerosis Risk in Communities study, over 12.6 years, there were 227 (1.5%) cases of SCD among 15,633 participants. In both cohorts, there was a trend toward decreased SCD with taller height. In fixed effects meta-analysis, the pooled hazard ratio per 10 cm of height was 0.84; 95% confidence interval, 0.73-0.98; P = .03. The association of increased height with lower risk of SCD was slightly attenuated after inclusion of risk factors associated with height, such as hypertension and left ventricular hypertrophy. The association appeared stronger among men than women in both cohorts. CONCLUSIONS: In two population-based prospective cohorts of different ages, greater height was associated with lower risk of SCD.
Keywords: Adult; Aged; Atherosclerosis; Body Height; Coronary Disease; Death, Sudden, Cardiac; Female; Humans; Hypertension; Incidence; Male; Middle Aged; Population Surveillance; Prospective Studies; Risk Factors

Heritability of and mortality prediction with a longevity phenotype: the healthy aging index. - Sanders, Jason L; Minster, Ryan L; Barmada, M Michael; Matteini, Amy M; Boudreau, Robert M; Christensen, Kaare; Mayeux, Richard; Borecki, Ingrid B; Zhang, Qunyuan; Perls, Thomas; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Longevity-associated genes may modulate risk for age-related diseases and survival. The Healthy Aging Index (HAI) may be a subphenotype of longevity, which can be constructed in many studies for genetic analysis. We investigated the HAI's association with survival in the Cardiovascular Health Study and heritability in the Long Life Family Study. METHODS: The HAI includes systolic blood pressure, pulmonary vital capacity, creatinine, fasting glucose, and Modified Mini-Mental Status Examination score, each scored 0, 1, or 2 using approximate tertiles and summed from 0 (healthy) to 10 (unhealthy). In Cardiovascular Health Study, the association with mortality and accuracy predicting death were determined with Cox proportional hazards analysis and c-statistics, respectively. In Long Life Family Study, heritability was determined with a variance component-based family analysis using a polygenic model. RESULTS: Cardiovascular Health Study participants with unhealthier index scores (7-10) had 2.62-fold (95% confidence interval: 2.22, 3.10) greater mortality than participants with healthier scores (0-2). The HAI alone predicted death moderately well (c-statistic = 0.643, 95% confidence interval: 0.626, 0.661, p < .0001) and slightly worse than age alone (c-statistic = 0.700, 95% confidence interval: 0.684, 0.717, p < .0001; p < .0001 for comparison of c-statistics). Prediction increased significantly with adjustment for demographics, health behaviors, and clinical comorbidities (c-statistic = 0.780, 95% confidence interval: 0.765, 0.794, p < .0001). In Long Life Family Study, the heritability of the HAI was 0.295 (p < .0001) overall, 0.387 (p < .0001) in probands, and 0.238 (p = .0004) in offspring. CONCLUSION: The HAI should be investigated further as a candidate phenotype for uncovering longevity-associated genes in humans.
Keywords: Aged; Aging; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genotype; Health Behavior; Humans; Longevity; Male; Phenotype; Retrospective Studies; Risk Factors; Survival Rate; United States

Identification of novel genetic Loci associated with thyroid peroxidase antibodies and clinical thyroid disease. - Medici, Marco; Porcu, Eleonora; Pistis, Giorgio; Teumer, Alexander; Brown, Suzanne J; Jensen, Richard A; Rawal, Rajesh; Roef, Greet L; Plantinga, Theo S; Vermeulen, Sita H; Lahti, Jari; Simmonds, Matthew J; et al. (PLoS Genet, 2014)
Autoimmune thyroid diseases (AITD) are common, affecting 2-5% of the general population. Individuals with positive thyroid peroxidase antibodies (TPOAbs) have an increased risk of autoimmune hypothyroidism (Hashimoto's thyroiditis), as well as autoimmune hyperthyroidism (Graves' disease). As the possible causative genes of TPOAbs and AITD remain largely unknown, we performed GWAS meta-analyses in 18,297 individuals for TPOAb-positivity (1769 TPOAb-positives and 16,528 TPOAb-negatives) and in 12,353 individuals for TPOAb serum levels, with replication in 8,990 individuals. Significant associations (P<5×10(-8)) were detected at TPO-rs11675434, ATXN2-rs653178, and BACH2-rs10944479 for TPOAb-positivity, and at TPO-rs11675434, MAGI3-rs1230666, and KALRN-rs2010099 for TPOAb levels. Individual and combined effects (genetic risk scores) of these variants on (subclinical) hypo- and hyperthyroidism, goiter and thyroid cancer were studied. Individuals with a high genetic risk score had, besides an increased risk of TPOAb-positivity (OR: 2.18, 95% CI 1.68-2.81, P = 8.1×10(-8)), a higher risk of increased thyroid-stimulating hormone levels (OR: 1.51, 95% CI 1.26-1.82, P = 2.9×10(-6)), as well as a decreased risk of goiter (OR: 0.77, 95% CI 0.66-0.89, P = 6.5×10(-4)). The MAGI3 and BACH2 variants were associated with an increased risk of hyperthyroidism, which was replicated in an independent cohort of patients with Graves' disease (OR: 1.37, 95% CI 1.22-1.54, P = 1.2×10(-7) and OR: 1.25, 95% CI 1.12-1.39, P = 6.2×10(-5)). The MAGI3 variant was also associated with an increased risk of hypothyroidism (OR: 1.57, 95% CI 1.18-2.10, P = 1.9×10(-3)). This first GWAS meta-analysis for TPOAbs identified five newly associated loci, three of which were also associated with clinical thyroid disease. With these markers we identified a large subgroup in the general population with a substantially increased risk of TPOAbs. The results provide insight into why individuals with thyroid autoimmunity do or do not eventually develop thyroid disease, and these markers may therefore predict which TPOAb-positives are particularly at risk of developing clinical thyroid dysfunction.
Keywords: Autoantibodies; Genetic Loci; Genome-Wide Association Study; Graves Disease; Hashimoto Disease; Humans; Iodide Peroxidase; Risk Factors; Thyroiditis, Autoimmune; Thyrotropin

Incidence of and risk factors for sick sinus syndrome in the general population. - Jensen, Paul N; Gronroos, Noelle N; Chen, Lin Y; Folsom, Aaron R; deFilippi, Chris; Heckbert, Susan R; Alonso, Alvaro (J Am Coll Cardiol, 2014)
BACKGROUND: Little is known about the incidence of and risk factors for sick sinus syndrome (SSS), a common indication for pacemaker implantation. OBJECTIVES: This study sought to describe the epidemiology of SSS. METHODS: This analysis included 20,572 participants (mean baseline age 59 years, 43% male) in the ARIC (Atherosclerosis Risk In Communities) study and the CHS (Cardiovascular Health Study), who at baseline were free of prevalent atrial fibrillation and pacemaker therapy, had a heart rate of ≥ 50 beats/min unless using beta blockers, and were identified as of white or black race. Incident SSS cases were identified by hospital discharge International Classification of Disease-revision 9-Clinical Modification code 427.81 and validated by medical record review. RESULTS: During an average 17 years of follow-up, 291 incident SSS cases were identified (unadjusted rate 0.8 per 1,000 person-years). Incidence increased with age (hazard ratio [HR]: 1.73; 95% confidence interval [CI]: 1.47 to 2.05 per 5-year increment), and blacks had a 41% lower risk of SSS than whites (HR: 0.59; 95% CI: 0.37 to 0.98). Incident SSS was associated with greater baseline body mass index, height, N-terminal pro-B-type natriuretic peptide, and cystatin C, with longer QRS interval, with lower heart rate, and with prevalent hypertension, right bundle branch block, and cardiovascular disease. We project that the annual number of new SSS cases in the United States will increase from 78,000 in 2012 to 172,000 in 2060. CONCLUSIONS: Blacks have a lower risk of SSS than whites, and several cardiovascular risk factors were associated with incident SSS. With the aging of the population, the number of Americans with SSS will increase dramatically over the next 50 years.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Cohort Studies; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Male; Middle Aged; Population Surveillance; Prospective Studies; Risk Factors; Sick Sinus Syndrome

The influence of sex on cardiovascular outcomes associated with diabetes among older black and white adults. - Vimalananda, Varsha G; Biggs, Mary L; Rosenzweig, James L; Carnethon, Mercedes R; Meigs, James B; Thacker, Evan L; Siscovick, David S; Mukamal, Kenneth J (J Diabetes Complications, 2014)
AIMS: It is unknown whether sex differences in the association of diabetes with cardiovascular outcomes vary by race. We examined sex differences in the associations of diabetes with incident congestive heart failure (CHF) and coronary heart disease (CHD) between older black and white adults. METHODS: We analyzed data from the Cardiovascular Health Study (CHS), a prospective cohort study of community-dwelling individuals aged ≥65 from four US counties. We included 4817 participants (476 black women, 279 black men, 2447 white women and 1625 white men). We estimated event rates and multivariate-adjusted hazard ratios for incident CHF, CHD, and all-cause mortality by Cox regression and competing risk analyses. RESULTS: Over a median follow-up of 12.5years, diabetes was more strongly associated with CHF among black women (HR, 2.42 [95% CI, 1.70-3.40]) than black men (1.39 [0.83-2.34]); this finding did not reach statistical significance (P for interaction=0.08). Female sex conferred a higher risk for a composite outcome of CHF and CHD among black participants (2.44 [1.82-3.26]) vs. (1.44 [0.97-2.12]), P for interaction=0.03). There were no significant sex differences in the HRs associated with diabetes for CHF among whites, or for CHD or all-cause mortality among blacks or whites. The three-way interaction between sex, race, and diabetes on risk of cardiovascular outcomes was not significant (P=0.07). CONCLUSIONS: Overall, sex did not modify the cardiovascular risk associated with diabetes among older black or white adults. However, our results suggest that a possible sex interaction among older blacks merits further study.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Aged, 80 and over; Cohort Studies; Coronary Disease; Diabetes Complications; European Continental Ancestry Group; Female; Heart Failure; Humans; Incidence; Longitudinal Studies; Male; Prospective Studies; Regression Analysis; Retrospective Studies; Risk Factors; Sex Factors; Survival Rate

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans. - Ellis, Jaclyn; Lange, Ethan M; Li, Jin; Dupuis, Josée; Baumert, Jens; Walston, Jeremy D; Keating, Brendan J; Durda, Peter; Fox, Ervin R; Palmer, Cameron D; Meng, Yan A; Young, Taylor; et al. (Hum Genet, 2014)
C-reactive protein (CRP) is a heritable biomarker of systemic inflammation and a predictor of cardiovascular disease (CVD). Large-scale genetic association studies for CRP have largely focused on individuals of European descent. We sought to uncover novel genetic variants for CRP in a multiethnic sample using the ITMAT Broad-CARe (IBC) array, a custom 50,000 SNP gene-centric array having dense coverage of over 2,000 candidate CVD genes. We performed analyses on 7,570 African Americans (AA) from the Candidate gene Association Resource (CARe) study and race-combined meta-analyses that included 29,939 additional individuals of European descent from CARe, the Women's Health Initiative (WHI) and KORA studies. We observed array-wide significance (p < 2.2 × 10(-6)) for four loci in AA, three of which have been reported previously in individuals of European descent (IL6R, p = 2.0 × 10(-6); CRP, p = 4.2 × 10(-71); APOE, p = 1.6 × 10(-6)). The fourth significant locus, CD36 (p = 1.6 × 10(-6)), was observed at a functional variant (rs3211938) that is extremely rare in individuals of European descent. We replicated the CD36 finding (p = 1.8 × 10(-5)) in an independent sample of 8,041 AA women from WHI; a meta-analysis combining the CARe and WHI AA results at rs3211938 reached genome-wide significance (p = 1.5 × 10(-10)). In the race-combined meta-analyses, 13 loci reached significance, including ten (CRP, TOMM40/APOE/APOC1, HNF1A, LEPR, GCKR, IL6R, IL1RN, NLRP3, HNF4A and BAZ1B/BCL7B) previously associated with CRP, and one (ARNTL) previously reported to be nominally associated with CRP. Two novel loci were also detected (RPS6KB1, p = 2.0 × 10(-6); CD36, p = 1.4 × 10(-6)). These results highlight both shared and unique genetic risk factors for CRP in AA compared to populations of European descent.
Keywords: Adult; African Americans; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; CD36 Antigens; Female; Genetic Loci; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Humans; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Large-scale meta-analysis of genome-wide association data identifies six new risk loci for Parkinson's disease. - Nalls, Mike A; Pankratz, Nathan; Lill, Christina M; Do, Chuong B; Hernandez, Dena G; Saad, Mohamad; DeStefano, Anita L; Kara, Eleanna; Bras, Jose; Sharma, Manu; Schulte, Claudia; Keller, Margaux F; et al. (Nat Genet, 2014)
We conducted a meta-analysis of Parkinson's disease genome-wide association studies using a common set of 7,893,274 variants across 13,708 cases and 95,282 controls. Twenty-six loci were identified as having genome-wide significant association; these and 6 additional previously reported loci were then tested in an independent set of 5,353 cases and 5,551 controls. Of the 32 tested SNPs, 24 replicated, including 6 newly identified loci. Conditional analyses within loci showed that four loci, including GBA, GAK-DGKQ, SNCA and the HLA region, contain a secondary independent risk variant. In total, we identified and replicated 28 independent risk variants for Parkinson's disease across 24 loci. Although the effect of each individual locus was small, risk profile analysis showed substantial cumulative risk in a comparison of the highest and lowest quintiles of genetic risk (odds ratio (OR) = 3.31, 95% confidence interval (CI) = 2.55-4.30; P = 2 × 10(-16)). We also show six risk loci associated with proximal gene expression or DNA methylation.
Keywords: Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Parkinson Disease; Polymorphism, Single Nucleotide; Risk Factors

Lipoprotein-associated phospholipase A2 and risk of dementia in the Cardiovascular Health Study. - Fitzpatrick, Annette L; Irizarry, Michael C; Cushman, Mary; Jenny, Nancy S; Chi, Gloria C; Koro, Carol (Atherosclerosis, 2014)
OBJECTIVE: To evaluate associations between Lipoprotein-associated phospholipase A2 (Lp-PLA2) mass and activity with risk of dementia and its subtypes. METHODS: Analysis were completed on 3320 participants of the Cardiovascular Health Study (CHS), a population-based longitudinal study of community-dwelling adults age ≥65 years followed for an average of 5.4 years. Baseline serum Lp-PLA2 mass was measured using a sandwich enzyme immunoassay and Lp-PLA2 activity utilized a tritiated-platelet activating factor activity assay. Cox proportional hazards regression assessed the relative risk of incident dementia with higher baseline Lp-PLA2 adjusting for demographics, cardiovascular disease (CVD) and risk factors, inflammation markers and apolipoprotein E (APOE) genotype. RESULTS: Each standard deviation higher Lp-PLA2 mass and activity were related to increased risk of dementia (fully adjusted HR: 1.11 per SD, 95% CI: 1.00-1.24 for mass; HR: 1.12 per SD, 95% CI: 1.00-1.26 for activity). Persons in the highest quartile of Lp-PLA2 mass were 50% more likely to develop dementia than those in the lowest quartile in adjusted models (HR: 1.49; 95% CI: 1.08-2.06). Among dementia subtypes, the risk of AD was increased two-fold in the highest compared to lowest quartile of Lp-PLA2 mass (adjusted HR: 1.98, 95% CI: 1.22-3.21). Results were attenuated in models of mixed dementia and VaD. Lp-PLA2 activity also doubled the risk of mixed dementia in the highest compared to lowest quartile (HR: 2.21, 95% CI: 1.12-4.373). INTERPRETATION: These data support Lp-PLA2 as a risk factor for dementia independent of CVD and its risk factors. Further study is required to clarify the role of Lp-PLA2-related mechanisms in dementia subtypes.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Alzheimer Disease; Dementia; Female; Humans; Male; Risk; Risk Factors

Loss-of-function mutations in APOC3, triglycerides, and coronary disease. - Crosby, Jacy; Peloso, Gina M; Auer, Paul L; Crosslin, David R; Stitziel, Nathan O; Lange, Leslie A; Lu, Yingchang; Tang, Zheng-Zheng; Zhang, He; Hindy, George; Masca, Nicholas; Stirrups, Kathleen; et al. (N Engl J Med, 2014)
BACKGROUND: Plasma triglyceride levels are heritable and are correlated with the risk of coronary heart disease. Sequencing of the protein-coding regions of the human genome (the exome) has the potential to identify rare mutations that have a large effect on phenotype. METHODS: We sequenced the protein-coding regions of 18,666 genes in each of 3734 participants of European or African ancestry in the Exome Sequencing Project. We conducted tests to determine whether rare mutations in coding sequence, individually or in aggregate within a gene, were associated with plasma triglyceride levels. For mutations associated with triglyceride levels, we subsequently evaluated their association with the risk of coronary heart disease in 110,970 persons. RESULTS: An aggregate of rare mutations in the gene encoding apolipoprotein C3 (APOC3) was associated with lower plasma triglyceride levels. Among the four mutations that drove this result, three were loss-of-function mutations: a nonsense mutation (R19X) and two splice-site mutations (IVS2+1G→A and IVS3+1G→T). The fourth was a missense mutation (A43T). Approximately 1 in 150 persons in the study was a heterozygous carrier of at least one of these four mutations. Triglyceride levels in the carriers were 39% lower than levels in noncarriers (P<1×10(-20)), and circulating levels of APOC3 in carriers were 46% lower than levels in noncarriers (P=8×10(-10)). The risk of coronary heart disease among 498 carriers of any rare APOC3 mutation was 40% lower than the risk among 110,472 noncarriers (odds ratio, 0.60; 95% confidence interval, 0.47 to 0.75; P=4×10(-6)). CONCLUSIONS: Rare mutations that disrupt APOC3 function were associated with lower levels of plasma triglycerides and APOC3. Carriers of these mutations were found to have a reduced risk of coronary heart disease. (Funded by the National Heart, Lung, and Blood Institute and others.).
Keywords: African Continental Ancestry Group; Apolipoprotein C-III; Coronary Disease; European Continental Ancestry Group; Exome; Genotype; Heterozygote; Humans; Liver; Mutation; Risk Factors; Sequence Analysis, DNA; Triglycerides

A low-frequency variant in MAPK14 provides mechanistic evidence of a link with myeloperoxidase: a prognostic cardiovascular risk marker. - Waterworth, Dawn M; Li, Li; Scott, Robert; Warren, Liling; Gillson, Christopher; Aponte, Jennifer; Sarov-Blat, Lea; Sprecher, Dennis; Dupuis, Josée; Reiner, Alex; Psaty, Bruce M; Tracy, Russell P; et al. (J Am Heart Assoc, 2014)
BACKGROUND: Genetics can be used to predict drug effects and generate hypotheses around alternative indications. To support Losmapimod, a p38 mitogen-activated protein kinase inhibitor in development for acute coronary syndrome, we characterized gene variation in MAPK11/14 genes by exome sequencing and follow-up genotyping or imputation in participants well-phenotyped for cardiovascular and metabolic traits. METHODS AND RESULTS: Investigation of genetic variation in MAPK11 and MAPK14 genes using additive genetic models in linear or logistic regression with cardiovascular, metabolic, and biomarker phenotypes highlighted an association of RS2859144 in MAPK14 with myeloperoxidase in a dyslipidemic population (Genetic Epidemiology of Metabolic Syndrome Study), P=2.3×10(-6)). This variant (or proxy) was consistently associated with myeloperoxidase in the Framingham Heart Study and Cardiovascular Health Study studies (replication meta-P=0.003), leading to a meta-P value of 9.96×10(-7) in the 3 dyslipidemic groups. The variant or its proxy was then profiled in additional population-based cohorts (up to a total of 58 930 subjects) including Cohorte Lausannoise, Ely, Fenland, European Prospective Investigation of Cancer, London Life Sciences Prospective Population Study, and the Genetics of Obesity Associations study obesity case-control for up to 40 cardiovascular and metabolic traits. Overall analysis identified the same single nucleotide polymorphisms to be nominally associated consistently with glomerular filtration rate (P=0.002) and risk of obesity (body mass index ≥30 kg/m(2), P=0.004). CONCLUSIONS: As myeloperoxidase is a prognostic marker of coronary events, the MAPK14 variant may provide a mechanistic link between p38 map kinase and these events, providing information consistent with current indication of Losmapimod for acute coronary syndrome. If replicated, the association with glomerular filtration rate, along with previous biological findings, also provides support for kidney diseases as alternative indications.
Keywords: Adult; Aged; Cardiovascular Diseases; Dyslipidemias; Exome; Female; Genotype; Humans; Linear Models; Logistic Models; Male; Metabolic Syndrome X; Middle Aged; Mitogen-Activated Protein Kinase 11; Mitogen-Activated Protein Kinase 14; Obesity; Peroxidase; Polymorphism, Single Nucleotide; Prognosis; Risk Factors; Sequence Analysis, DNA

Metabolic syndrome and risk of incident peripheral artery disease: the cardiovascular health study. - Garg, Parveen K; Biggs, Mary L; Carnethon, Mercedes; Ix, Joachim H; Criqui, Michael H; Britton, Kathryn A; Djoussé, Luc; Sutton-Tyrrell, Kim; Newman, Anne B; Cushman, Mary; Mukamal, Kenneth J (Hypertension, 2014)
Prior studies evaluating metabolic syndrome (MetS) and incident peripheral artery disease (PAD) have been limited by use of modified MetS criteria and restriction to clinical PAD end points. We investigated MetS and risk of developing a low ankle-brachial index (ABI) and clinical PAD in the Cardiovascular Health Study, a population-based cohort of adults aged ≥65 years. Participants with MetS met at least 3 of 5 Adult Treatment Panel III criteria. Baseline C-reactive protein-MetS or fibrinogen-MetS were defined as presence of 3 of 6 components, with elevated C-reactive protein (>3 mg/L) or fibrinogen (>341 mg/dL) as a sixth component. Incident low ABI, defined as ABI <0.9 and decline of ≥0.15, was assessed among a subset of 1899 individuals with 2 ABI measurements 6 years apart. Over a median follow-up of 13.7 years, 4632 individuals were followed up for clinical PAD, defined as revascularization or diagnosed claudication. Adult Treatment Panel III MetS was associated with both incident low ABI (risk ratio, 1.26; 95% confidence interval [CI], 1.00-1.58) and clinical PAD (hazard ratio, 1.47; 95% CI, 1.11-1.94). Incorporating C-reactive protein or fibrinogen into Adult Treatment Panel III criteria identified an additional 16% to 20% of individuals as having MetS, and both C-reactive protein-MetS and fibrinogen-MetS were associated with incident low ABI (risk ratio, 1.36; 95% CI, 1.07-1.72 and risk ratio, 1.43; 95% CI, 1.13-1.81, respectively) and clinical PAD (hazard ratio, 1.56; 95% CI, 1.17-2.08 and hazard ratio, 1.55; 95% CI, 1.17-2.07, respectively). Among Adult Treatment Panel III MetS criteria, risk of PAD was most strongly associated with hypertension.
Keywords: Aged; Ankle Brachial Index; C-Reactive Protein; Female; Fibrinogen; Follow-Up Studies; Humans; Incidence; Longitudinal Studies; Male; Metabolic Syndrome; Peripheral Arterial Disease; Prevalence; Risk Factors; Vasculitis

Multilocus genetic risk score associates with ischemic stroke in case-control and prospective cohort studies. - Malik, Rainer; Bevan, Steve; Nalls, Michael A; Holliday, Elizabeth G; Devan, William J; Cheng, Yu-Ching; Ibrahim-Verbaas, Carla A; Verhaaren, Benjamin F J; Bis, Joshua C; Joon, Aron Y; de Stefano, Anita L; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Genome-wide association studies have revealed multiple common variants associated with known risk factors for ischemic stroke (IS). However, their aggregate effect on risk is uncertain. We aimed to generate a multilocus genetic risk score (GRS) for IS based on genome-wide association studies data from clinical-based samples and to establish its external validity in prospective population-based cohorts. METHODS: Three thousand five hundred forty-eight clinic-based IS cases and 6399 controls from the Wellcome Trust Case Control Consortium 2 were used for derivation of the GRS. Subjects from the METASTROKE consortium served as a replication sample. The validation sample consisted of 22 751 participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. We selected variants that had reached genome-wide significance in previous association studies on established risk factors for IS. RESULTS: A combined GRS for atrial fibrillation, coronary artery disease, hypertension, and systolic blood pressure significantly associated with IS both in the case-control samples and in the prospective population-based studies. Subjects in the top quintile of the combined GRS had >2-fold increased risk of IS compared with subjects in the lowest quintile. Addition of the combined GRS to a simple model based on sex significantly improved the prediction of IS in the combined clinic-based samples but not in the population-based studies, and there was no significant improvement in net reclassification. CONCLUSIONS: A multilocus GRS based on common variants for established cardiovascular risk factors was significantly associated with IS both in clinic-based samples and in the general population. However, the improvement in clinical risk prediction was found to be small.
Keywords: Adult; Aged; Aged, 80 and over; Atrial Fibrillation; Blood Pressure; Brain Ischemia; Case-Control Studies; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Multilocus Sequence Typing; Polymorphism, Single Nucleotide; Population; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke

Plasma phospholipid and dietary α-linolenic acid, mortality, CHD and stroke: the Cardiovascular Health Study. - Fretts, Amanda M; Mozaffarian, Dariush; Siscovick, David S; Sitlani, Colleen; Psaty, Bruce M; Rimm, Eric B; Song, Xiaoling; McKnight, Barbara; Spiegelman, Donna; King, Irena B; Lemaitre, Rozenn N (Br J Nutr, 2014)
Previous studies have suggested that long-chain n-3 fatty acids derived from seafood are associated with a lower risk of mortality, CHD and stroke. Whether α-linolenic acid (ALA, 18 : 3n-3), a plant-derived long-chain essential n-3 fatty acid, is associated with a lower risk of these outcomes is unclear. The aim of the present study was to examine the associations of plasma phospholipid and dietary ALA with the risk of mortality, CHD and stroke among older adults who participated in the Cardiovascular Health Study, a cohort study of adults aged ≥ 65 years. A total of 2709 participants were included in the plasma phospholipid ALA analysis and 2583 participants were included in the dietary ALA analysis. Cox regression was used to assess the associations of plasma phospholipid and dietary ALA with the risk of mortality, incident CHD and stroke. In minimally and multivariable-adjusted models, plasma phospholipid ALA was found to be not associated with the risk of mortality, incident CHD or stroke. After adjustment for age, sex, race, enrolment site, education, smoking status, diabetes, BMI, alcohol consumption, treated hypertension and total energy intake, higher dietary ALA intake was found to be associated with a lower risk of total and non-cardiovascular mortality; on comparing the highest quintiles of dietary ALA with the lowest quintiles, the HR for total mortality and non-cardiovascular mortality were found to be 0·73 (95 % CI 0·61, 0·88) and 0·64 (95 % CI 0·52, 0·80), respectively. Dietary ALA was found to be not associated with the risk of cardiovascular mortality, incident CHD or stroke. In conclusion, the results of the present suggest study that dietary ALA, but not plasma phospholipid ALA, is associated with a lower risk of total and non-cardiovascular mortality in older adults.
Keywords: Aged; alpha-Linolenic Acid; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Diet; Female; Humans; Male; Mortality; Phospholipids; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; United States

Plasma phospholipid saturated fatty acids and incident atrial fibrillation: the Cardiovascular Health Study. - Fretts, Amanda M; Mozaffarian, Dariush; Siscovick, David S; Djoussé, Luc; Heckbert, Susan R; King, Irena B; McKnight, Barbara; Sitlani, Colleen; Sacks, Frank M; Song, Xiaoling; Sotoodehnia, Nona; Spiegelman, Donna; et al. (J Am Heart Assoc, 2014)
BACKGROUND: Prior studies suggest that circulating fatty acids may influence the risk of atrial fibrillation (AF), but little is known about the associations of circulating saturated fatty acids with risk of AF. METHODS AND RESULTS: The study population included 2899 participants from the Cardiovascular Health Study, a community-based longitudinal cohort of adults aged 65 years or older in the United States who were free of prevalent coronary heart disease and AF in 1992. Cox regression was used to assess the association of all the long-chain saturated fatty acids-palmitic acid (16:0), stearic acid (18:0), arachidic acid (20:0), behenic acid (22:0), and lignoceric acid (24:0)-with incident AF. During a median of 11.2 years of follow-up, 707 cases of incident AF occurred. After adjustment for other AF risk factors, higher levels of circulating 16:0 were associated with a higher risk of AF (hazard ratio comparing highest and lowest quartiles: 1.48; 95% CI: 1.18, 1.86). In contrast, higher levels of circulating 18:0, 20:0, 22:0, and 24:0 were each associated with a lower risk of AF. The hazard ratios (95% CI) for AF in the top and bottom quartiles were 0.76 (95% CI: 0.61, 0.95) for 18:0; 0.78 (95% CI: 0.63, 0.97) for 20:0; 0.62 (95% CI: 0.50, 0.78) for 22:0; and 0.68 (95% CI: 0.55, 0.85) for 24:0. CONCLUSIONS: Results from this prospective cohort study of older adults demonstrate divergent associations of circulating 16:0 versus longer-chain saturated fatty acids with incident AF, highlighting the need to investigate both determinants of these levels and potential pathways of the observed differential risk.
Keywords: Aged; Aged, 80 and over; Atrial Fibrillation; Eicosanoic Acids; Fatty Acids; Female; Humans; Longitudinal Studies; Male; Palmitic Acid; Phospholipids; Proportional Hazards Models; Prospective Studies; Risk Factors; Stearic Acids; United States

Plasma-free fatty acids, fatty acid-binding protein 4, and mortality in older adults (from the Cardiovascular Health Study). - Miedema, Michael D; Maziarz, Marlena; Biggs, Mary L; Zieman, Susan J; Kizer, Jorge R; Ix, Joachim H; Mozaffarian, Dariush; Tracy, Russell P; Psaty, Bruce M; Siscovick, David S; Mukamal, Kenneth J; Djoussé, Luc (Am J Cardiol, 2014)
Plasma-free fatty acids (FFAs) are largely derived from adipose tissue. Elevated levels of FFA and fatty acid-binding protein 4 (FABP4), a key cytoplasmic chaperone of fatty acids, have been associated with adverse cardiovascular outcomes, but limited data are available on the relation of these biomarkers with cardiovascular and total mortality. We studied 4,707 participants with a mean age of 75 years who had plasma FFA and FABP4 measured in 1992 to 1993 as part of the Cardiovascular Health Study, an observational cohort of community-dwelling older adults. Over a median follow-up of 11.8 years, 3,555 participants died. Cox proportional hazard regression was used to determine the association between FFA, FABP4, and mortality. In fully adjusted models, FFA were associated with dose-dependent significantly higher total mortality (hazard ratio [HR] per SD: 1.14, 95% confidence interval [CI] 1.09 to 1.18), but FABP4 levels were not (HR 1.04, 95% CI 0.98 to 1.09). In a cause-specific mortality analysis, higher concentrations of FFA were associated with significantly higher risk of death because of cardiovascular disease, dementia, infection, and respiratory causes but not cancer or trauma. We did not find evidence of an interaction between FFA and FABP4 (p = 0.45), but FABP4 appeared to be associated with total mortality differentially in men and women (HR 1.17, 95% CI 1.08 to 1.26 for men; HR 1.02, 95% CI 0.96 to 1.07 for women, interaction p value <0.001). In conclusion, in a cohort of community-dwelling older subjects, elevated plasma concentrations of FFA, but not FABP4, were associated with cardiovascular and noncardiovascular mortality.
Keywords: Age Distribution; Age Factors; Aged; Aged, 80 and over; Biomarkers; Cardiovascular Diseases; Cause of Death; Fatty Acid-Binding Proteins; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Health Status; Humans; Male; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; Survival Rate; Time Factors; United States

Predicting stroke through genetic risk functions: the CHARGE Risk Score Project. - Ibrahim-Verbaas, Carla A; Fornage, Myriam; Bis, Joshua C; Choi, Seung Hoan; Psaty, Bruce M; Meigs, James B; Rao, Madhu; Nalls, Mike; Fontes, João D; O'Donnell, Christopher J; Kathiresan, Sekar; Ehret, Georg B; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Beyond the Framingham Stroke Risk Score, prediction of future stroke may improve with a genetic risk score (GRS) based on single-nucleotide polymorphisms associated with stroke and its risk factors. METHODS: The study includes 4 population-based cohorts with 2047 first incident strokes from 22,720 initially stroke-free European origin participants aged ≥55 years, who were followed for up to 20 years. GRSs were constructed with 324 single-nucleotide polymorphisms implicated in stroke and 9 risk factors. The association of the GRS to first incident stroke was tested using Cox regression; the GRS predictive properties were assessed with area under the curve statistics comparing the GRS with age and sex, Framingham Stroke Risk Score models, and reclassification statistics. These analyses were performed per cohort and in a meta-analysis of pooled data. Replication was sought in a case-control study of ischemic stroke. RESULTS: In the meta-analysis, adding the GRS to the Framingham Stroke Risk Score, age and sex model resulted in a significant improvement in discrimination (all stroke: Δjoint area under the curve=0.016, P=2.3×10(-6); ischemic stroke: Δjoint area under the curve=0.021, P=3.7×10(-7)), although the overall area under the curve remained low. In all the studies, there was a highly significantly improved net reclassification index (P<10(-4)). CONCLUSIONS: The single-nucleotide polymorphisms associated with stroke and its risk factors result only in a small improvement in prediction of future stroke compared with the classical epidemiological risk factors for stroke.
Keywords: Age Factors; Aged; Aged, 80 and over; Area Under Curve; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; ROC Curve; Sex Factors; Stroke

Prognostic implications of microvascular and macrovascular abnormalities in older adults: cardiovascular health study. - Kim, Dae Hyun; Grodstein, Francine; Newman, Anne B; Chaves, Paulo H M; Odden, Michelle C; Klein, Ronald; Sarnak, Mark J; Patel, Kushang V; Lipsitz, Lewis A (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Microvascular and macrovascular abnormalities are frequently found on noninvasive tests performed in older adults. Their prognostic implications on disability and life expectancy have not been collectively assessed. METHODS: This prospective study included 2,452 adults (mean age: 79.5 years) with available measures of microvascular (brain, retina, kidney) and macrovascular abnormalities (brain, carotid, coronary, peripheral artery) in the Cardiovascular Health Study. The burden of microvascular and macrovascular abnormalities was examined in relation to total, activity-of-daily-living disability-free, and severe disability-free life expectancies in the next 10 years (1999-2009). RESULTS: At 75 years, individuals with low burden of both abnormalities lived, on average, 8.71 years (95% confidence interval: 8.29, 9.12) of which 7.67 years (7.16, 8.17) were without disability. In comparison, individuals with high burden of both abnormalities had shortest total life expectancy (6.95 years [6.52, 7.37]; p < .001) and disability-free life expectancy (5.60 years [5.10, 6.11]; p < .001). Although total life expectancy was similarly reduced for those with high burden of either type of abnormalities (microvascular: 7.96 years [7.50, 8.42] vs macrovascular: 8.25 years [7.80, 8.70]; p = .10), microvascular abnormalities seemed to have larger impact than macrovascular abnormalities on disability-free life expectancy (6.45 years [5.90, 6.99] vs 6.96 years [6.43, 7.48]; p = .016). These results were consistent for severe disability-free life expectancy and in individuals without clinical cardiovascular disease. CONCLUSIONS: Considering both microvascular and macrovascular abnormalities from multiple noninvasive tests may provide additional prognostic information on how older adults spend their remaining life. Optimal clinical use of this information remains to be determined.
Keywords: Aged; Aged, 80 and over; Aging; Ankle Brachial Index; Disability Evaluation; Electrocardiography; Female; Follow-Up Studies; Forecasting; Humans; Life Expectancy; Magnetic Resonance Imaging; Male; Microcirculation; Prognosis; Prospective Studies; Risk Factors; Vascular Malformations

Racial and regional differences in venous thromboembolism in the United States in 3 cohorts. - Zakai, Neil A; McClure, Leslie A; Judd, Suzanne E; Safford, Monika M; Folsom, Aaron R; Lutsey, Pamela L; Cushman, Mary (Circulation, 2014)
BACKGROUND: Blacks are thought to have a higher risk of venous thromboembolism (VTE) than whites. However, prior studies are limited to administrative databases that lack specific information on VTE risk factors or have limited geographic scope. METHODS AND RESULTS: We ascertained VTE from 3 prospective studies: the Atherosclerosis Risk in Communities Study (ARIC), the Cardiovascular Health Study (CHS), and the Reasons for Geographic and Racial Differences in Stroke study (REGARDS). We tested the association of race with VTE using Cox proportional hazard models adjusted for VTE risk factors. Over 438 090 person-years, 916 incident VTE events (302 in blacks) occurred in 51 149 individuals (17 318 blacks) who were followed up. In risk factor-adjusted models, blacks had a higher rate of VTE than whites in the CHS (hazard ratio, 1.81; 95% confidence interval, 1.20-2.73) but not ARIC (hazard ratio, 1.21; 95% confidence interval, 0.96-1.54). In REGARDS, there was a significant region-by-race interaction (P=0.01): Blacks in the Southeast had a significantly higher rate of VTE than blacks in the rest of the United States (hazard ratio, 1.63; 95% confidence interval, 1.08-2.48) that was not seen in whites (hazard ratio, 0.83; 95% confidence interval, 0.61-1.14). CONCLUSIONS: The association of race with VTE differed in each cohort, which may reflect the different time periods of the studies or different regional rates of VTE. Further studies of environmental and genetic risk factors for VTE are needed to determine which underlie racial and perhaps regional differences in VTE.
Keywords: African Continental Ancestry Group; Aged; Cohort Studies; European Continental Ancestry Group; Female; Humans; Longitudinal Studies; Male; Middle Aged; Prevalence; Proportional Hazards Models; Prospective Studies; Residence Characteristics; Risk Factors; United States; Venous Thromboembolism

Relative risks of chronic kidney disease for mortality and end-stage renal disease across races are similar. - Wen, Chi Pang; Matsushita, Kunihiro; Coresh, Josef; Iseki, Kunitoshi; Islam, Muhammad; Katz, Ronit; McClellan, William; Peralta, Carmen A; Wang, Haiyan; de Zeeuw, Dick; Astor, Brad C; Gansevoort, Ron T; et al. (Kidney Int, 2014)
Some suggest race-specific cutpoints for kidney measures to define and stage chronic kidney disease (CKD), but evidence for race-specific clinical impact is limited. To address this issue, we compared hazard ratios of estimated glomerular filtration rates (eGFR) and albuminuria across races using meta-regression in 1.1 million adults (75% Asians, 21% Whites, and 4% Blacks) from 45 cohorts. Results came mainly from 25 general population cohorts comprising 0.9 million individuals. The associations of lower eGFR and higher albuminuria with mortality and end-stage renal disease (ESRD) were largely similar across races. For example, in Asians, Whites, and Blacks, the adjusted hazard ratios (95% confidence interval) for eGFR 45-59 versus 90-104 ml/min per 1.73 m(2) were 1.3 (1.2-1.3), 1.1 (1.0-1.2), and 1.3 (1.1-1.7) for all-cause mortality, 1.6 (1.5-1.7), 1.4 (1.2-1.7), and 1.4 (0.7-2.9) for cardiovascular mortality, and 27.6 (11.1-68.7), 11.2 (6.0-20.9), and 4.1 (2.2-7.5) for ESRD, respectively. The corresponding hazard ratios for urine albumin-to-creatinine ratio 30-299 mg/g or dipstick 1+ versus an albumin-to-creatinine ratio under 10 or dipstick negative were 1.6 (1.4-1.8), 1.7 (1.5-1.9), and 1.8 (1.7-2.1) for all-cause mortality, 1.7 (1.4-2.0), 1.8 (1.5-2.1), and 2.8 (2.2-3.6) for cardiovascular mortality, and 7.4 (2.0-27.6), 4.0 (2.8-5.9), and 5.6 (3.4-9.2) for ESRD, respectively. Thus, the relative mortality or ESRD risks of lower eGFR and higher albuminuria were largely similar among three major races, supporting similar clinical approach to CKD definition and staging, across races.
Keywords: Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Albuminuria; Asian Continental Ancestry Group; Cardiovascular Diseases; Cohort Studies; Creatinine; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Odds Ratio; Renal Insufficiency, Chronic; Risk Factors

Risk factors for cardiovascular disease across the spectrum of older age: the Cardiovascular Health Study. - Odden, Michelle C; Shlipak, Michael G; Whitson, Heather E; Katz, Ronit; Kearney, Patricia M; deFilippi, Chris; Shastri, Shani; Sarnak, Mark J; Siscovick, David S; Cushman, Mary; Psaty, Bruce M; Newman, Anne B (Atherosclerosis, 2014)
OBJECTIVE: The associations of some risk factors with cardiovascular disease (CVD) are attenuated in older age; whereas others appear robust. The present study aimed to compare CVD risk factors across older age. METHODS: Participants (n = 4883) in the Cardiovascular Health Study free of prevalent CVD, were stratified into three age groups: 65-74, 75-84, 85+ years. Traditional risk factors included systolic blood pressure (BP), LDL-cholesterol, HDL-cholesterol, obesity, and diabetes. Novel risk factors included kidney function, C-reactive protein (CRP), and N-terminal pro-B-type natriuretic peptide (NT pro-BNP). RESULTS: There were 1498 composite CVD events (stroke, myocardial infarction, and cardiovascular death) over 5 years. The associations of high systolic BP and diabetes appeared strongest, though both were attenuated with age (p-values for interaction = 0.01 and 0.002, respectively). The demographic-adjusted hazard ratios (HR) for elevated systolic BP were 1.79 (95% confidence interval: 1.49, 2.15), 1.59 (1.37, 1.85) and 1.10 (0.86, 1.41) in participants aged 65-74, 75-84, 85+, and for diabetes, 2.36 (1.89, 2.95), 1.55 (1.27, 1.89), 1.51 (1.10, 2.09). The novel risk factors had consistent associations with the outcome across the age spectrum; low kidney function: 1.69 (1.31, 2.19), 1.61 (1.36, 1.90), and 1.57 (1.16, 2.14) for 65-74, 75-84, and 85+ years, respectively; elevated CRP: 1.54 (1.28, 1.87), 1.33 (1.13, 1.55), and 1.51 (1.15, 1.97); elevated NT pro-BNP: 2.67 (1.96, 3.64), 2.71 (2.25, 3.27), and 2.18 (1.43, 3.45). CONCLUSIONS: The associations of most traditional risk factors with CVD were minimal in the oldest old, whereas diabetes, eGFR, CRP, and NT pro-BNP were associated with CVD across older age.
Keywords: Aged; Aged, 80 and over; Blood Pressure; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Diabetes Complications; Diabetes Mellitus; Female; Humans; Inflammation; Kidney; Kidney Diseases; Lipids; Male; Natriuretic Peptide, Brain; Obesity; Peptide Fragments; Risk Factors

Separate prediction of intracerebral hemorrhage and ischemic stroke. - Ferket, Bart S; van Kempen, Bob J H; Wieberdink, Renske G; Steyerberg, Ewout W; Koudstaal, Peter J; Hofman, Albert; Shahar, Eyal; Gottesman, Rebecca F; Rosamond, Wayne; Kizer, Jorge R; Kronmal, Richard A; Psaty, Bruce M; et al. (Neurology, 2014)
OBJECTIVES: To develop and validate 10-year cumulative incidence functions of intracerebral hemorrhage (ICH) and ischemic stroke (IS). METHODS: We used data on 27,493 participants from 3 population-based cohort studies: the Atherosclerosis Risk in Communities Study, median age 54 years, 45% male, median follow-up 20.7 years; the Rotterdam Study, median age 68 years, 38% male, median follow-up 14.3 years; and the Cardiovascular Health Study, median age 71 years, 41% male, median follow-up 12.8 years. Among these participants, 325 ICH events, 2,559 IS events, and 9,909 nonstroke deaths occurred. We developed 10-year cumulative incidence functions for ICH and IS using stratified Cox regression and competing risks analysis. Basic models including only established nonlaboratory risk factors were extended with diastolic blood pressure, total cholesterol/high-density lipoprotein cholesterol ratio, body mass index, waist-to-hip ratio, and glomerular filtration rate. The cumulative incidence functions' performances were cross-validated in each cohort separately by Harrell C-statistic and calibration plots. RESULTS: High total cholesterol/high-density lipoprotein cholesterol ratio decreased the ICH rates but increased IS rates (p for difference across stroke types <0.001). For both the ICH and IS models, C statistics increased more by model extension in the Atherosclerosis Risk in Communities and Cardiovascular Health Study cohorts. Improvements in C statistics were reproduced by cross-validation. Models were well calibrated in all cohorts. Correlations between 10-year ICH and IS risks were moderate in each cohort. CONCLUSIONS: We developed and cross-validated cumulative incidence functions for separate prediction of 10-year ICH and IS risk. These functions can be useful to further specify an individual's stroke risk.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Body Mass Index; Brain Ischemia; Cholesterol; Female; Humans; Incidence; Intracranial Hemorrhages; Male; Middle Aged; Models, Statistical; Predictive Value of Tests; Risk Assessment; Risk Factors; Stroke

Shared genetic susceptibility to ischemic stroke and coronary artery disease: a genome-wide analysis of common variants. - Dichgans, Martin; Malik, Rainer; König, Inke R; Rosand, Jonathan; Clarke, Robert; Gretarsdottir, Solveig; Thorleifsson, Gudmar; Mitchell, Braxton D; Assimes, Themistocles L; Levi, Christopher; O'Donnell, Christopher J; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Ischemic stroke (IS) and coronary artery disease (CAD) share several risk factors and each has a substantial heritability. We conducted a genome-wide analysis to evaluate the extent of shared genetic determination of the two diseases. METHODS: Genome-wide association data were obtained from the METASTROKE, Coronary Artery Disease Genome-wide Replication and Meta-analysis (CARDIoGRAM), and Coronary Artery Disease (C4D) Genetics consortia. We first analyzed common variants reaching a nominal threshold of significance (P<0.01) for CAD for their association with IS and vice versa. We then examined specific overlap across phenotypes for variants that reached a high threshold of significance. Finally, we conducted a joint meta-analysis on the combined phenotype of IS or CAD. Corresponding analyses were performed restricted to the 2167 individuals with the ischemic large artery stroke (LAS) subtype. RESULTS: Common variants associated with CAD at P<0.01 were associated with a significant excess risk for IS and for LAS and vice versa. Among the 42 known genome-wide significant loci for CAD, 3 and 5 loci were significantly associated with IS and LAS, respectively. In the joint meta-analyses, 15 loci passed genome-wide significance (P<5×10(-8)) for the combined phenotype of IS or CAD and 17 loci passed genome-wide significance for LAS or CAD. Because these loci had prior evidence for genome-wide significance for CAD, we specifically analyzed the respective signals for IS and LAS and found evidence for association at chr12q24/SH2B3 (PIS=1.62×10(-7)) and ABO (PIS=2.6×10(-4)), as well as at HDAC9 (PLAS=2.32×10(-12)), 9p21 (PLAS=3.70×10(-6)), RAI1-PEMT-RASD1 (PLAS=2.69×10(-5)), EDNRA (PLAS=7.29×10(-4)), and CYP17A1-CNNM2-NT5C2 (PLAS=4.9×10(-4)). CONCLUSIONS: Our results demonstrate substantial overlap in the genetic risk of IS and particularly the LAS subtype with CAD.
Keywords: Brain Ischemia; Coronary Artery Disease; Data Interpretation, Statistical; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk Factors; Stroke

Simple biologically informed inflammatory index of two serum cytokines predicts 10 year all-cause mortality in older adults. - Varadhan, Ravi; Yao, Wenliang; Matteini, Amy; Beamer, Brock A; Xue, Qian-Li; Yang, Huanle; Manwani, Bhavish; Reiner, Alexander; Jenny, Nancy; Parekh, Neel; Fallin, M Daniele; Newman, Anne; et al. (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Individual measurements of inflammation have been utilized to assess adverse outcomes risk in older adults with varying degrees of success. This study was designed to identify biologically informed, aggregate measures of inflammation for optimal risk assessment and to inform further biological study of inflammatory pathways. METHODS: In total, 15 nuclear factor-kappa B-mediated pathway markers of inflammation were first measured in baseline serum samples of 1,155 older participants in the InCHIANTI population. Of these, C-reactive protein, interleukin-1-receptor antagonist, interleukin-6, interleukin-18, and soluble tumor necrosis factor-α receptor-1 were independent predictors of 5-year mortality. These five inflammatory markers were measured in baseline serum samples of 5,600 Cardiovascular Health Study participants. A weighted summary score, the first principal component summary score, and an inflammation index score were developed from these five log-transformed inflammatory markers, and their prediction of 10-year all-cause mortality was evaluated in Cardiovascular Health Study and then validated in InCHIANTI. RESULTS: The inflammation index score that included interleukin-6 and soluble tumor necrosis factor-α receptor-1 was the best predictor of 10-year all-cause mortality in Cardiovascular Health Study, after adjusting for age, sex, education, race, smoking, and body mass index (hazards ratio = 1.62; 95% CI: 1.54, 1.70) compared with all other single and combined measures. The inflammation index score was also the best predictor of mortality in the InCHIANTI validation study (hazards ratio 1.33; 95% CI: 1.17-1.52). Stratification by sex and CVD status further strengthened the association of inflammation index score with mortality. CONCLUSION: A simple additive index of serum interleukin-6 and soluble tumor necrosis factor-α receptor-1 best captures the effect of chronic inflammation on mortality in older adults among the 15 biomarkers measured.
Keywords: Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; Cohort Studies; Female; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-18; Interleukin-6; Longevity; Male; Receptors, Tumor Necrosis Factor, Type I; Risk Factors

Sleep duration does not mediate or modify association of common genetic variants with type 2 diabetes. - Tare, Archana; Lane, Jacqueline M; Cade, Brian E; Grant, Struan F A; Chen, Ting-Hsu; Punjabi, Naresh M; Lauderdale, Diane S; Zee, Phyllis C; Gharib, Sina A; Gottlieb, Daniel J; Scheer, Frank A J L; Redline, Susan; et al. (Diabetologia, 2014)
AIMS/HYPOTHESIS: Short and long sleep duration are associated with increased risk of type 2 diabetes. We aimed to investigate whether genetic variants for fasting glucose or type 2 diabetes associate with short or long sleep duration and whether sleep duration modifies the association of genetic variants with these traits. METHODS: We examined the cross-sectional relationship between self-reported habitual sleep duration and prevalence of type 2 diabetes in individuals of European descent participating in five studies included in the Candidate Gene Association Resource (CARe), totalling 1,474 cases and 8,323 controls. We tested for association of 16 fasting glucose-associated variants, 27 type 2 diabetes-associated variants and aggregate genetic risk scores with continuous and dichotomised (≤5 h or ≥9 h) sleep duration using regression models adjusted for age, sex and BMI. Finally, we tested whether a gene × behaviour interaction of variants with sleep duration had an impact on fasting glucose or type 2 diabetes risk. RESULTS: Short sleep duration was significantly associated with type 2 diabetes in CARe (OR 1.32; 95% CI 1.08, 1.61; p = 0.008). Variants previously associated with fasting glucose or type 2 diabetes and genetic risk scores were not associated with sleep duration. Furthermore, no study-wide significant interaction was observed between sleep duration and these variants on glycaemic traits. Nominal interactions were observed for sleep duration and PPARG rs1801282, CRY2 rs7943320 and HNF1B rs4430796 in influencing risk of type 2 diabetes (p < 0.05). CONCLUSIONS/INTERPRETATION: Our findings suggest that differences in habitual sleep duration do not mediate or modify the relationship between common variants underlying glycaemic traits (including in circadian rhythm genes) and diabetes.
Keywords: Blood Glucose; Body Composition; Body Mass Index; Cross-Sectional Studies; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Fasting; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Glucose Intolerance; Glycated Hemoglobin A; Humans; Insulin Resistance; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Sleep; Surveys and Questionnaires; Time Factors; United States

Subclinical thyroid dysfunction and hip fracture and bone mineral density in older adults: the cardiovascular health study. - Garin, Margaret C; Arnold, Alice M; Lee, Jennifer S; Robbins, John; Cappola, Anne R (J Clin Endocrinol Metab, 2014)
BACKGROUND: Subclinical thyroid dysfunction is common in the elderly, yet its relationship with hip fracture and bone mineral density (BMD) is unclear. OBJECTIVE: We examined the association between endogenous subclinical hyper- and hypothyroidism and hip fracture and BMD in older adults. METHODS: A total of 4936 US individuals 65 years old or older enrolled in the Cardiovascular Health Study and not taking thyroid preparations were included. Analyses of incident hip fracture were performed by thyroid status, over a median follow-up of 12 years. A cross-sectional analysis of thyroid status and BMD was performed in a subset of 1317 participants who had dual-energy x-ray absorptiometry scans. Models were adjusted for risk factors and stratified by sex. RESULTS: No association was found between subclinical hypothyroidism and incident hip fracture compared with euthyroidism, when assessed at a single time point or persisting at two time points, in either women [hazard ratio (HR) 0.91, 95% confidence interval (CI) 0.69-1.20 for a single and HR 0.79, 95% CI 0.52-1.21 for two time points] or men (HR 1.27, 95% CI 0.82-1.95 for a single and HR 1.09, 95% CI 0.57-2.10 for two time points). Likewise, no association was found between subclinical hyperthyroidism and incident hip fracture in either sex (HR 1.11, 95% CI 0.55-2.25 in women and HR 1.78, 95% CI 0.56-5.66 in men). No association was found between subclinical thyroid dysfunction and BMD at the lumbar spine, total hip, or femoral neck sites. CONCLUSIONS: Our data suggest no association between subclinical hypothyroidism or subclinical hyperthyroidism and hip fracture risk or BMD in older men and women. Additional data are needed to improve the precision of estimates for subclinical hyperthyroidism and in men.
Keywords: Absorptiometry, Photon; Aged; Aged, 80 and over; Asymptomatic Diseases; Bone Density; Cardiovascular System; Cohort Studies; Cross-Sectional Studies; Female; Hip Fractures; Humans; Male; Osteoporotic Fractures; Risk Factors; Sex Factors; Thyroid Diseases

Systolic and diastolic blood pressure, incident cardiovascular events, and death in elderly persons: the role of functional limitation in the Cardiovascular Health Study. - Peralta, Carmen A; Katz, Ronit; Newman, Anne B; Psaty, Bruce M; Odden, Michelle C (Hypertension, 2014)
Whether limitation in the ability to perform activities of daily living (ADL) or gait speed can identify elders in whom the association of systolic and diastolic blood pressure (DBP) with cardiovascular events (CVDs) and death differs is unclear. We evaluated whether limitation in ADL or gait speed modifies the association of systolic blood pressure or DBP with incident CVD (n=2358) and death (n=3547) in the Cardiovascular Health Study. Mean age was 78±5 and 21% reported limitation in ≥1 ADL. There were 778 CVD and 1289 deaths over 9 years. Among persons without and those with ADL limitation, systolic blood pressure was associated with incident CVD: hazard ratio [HR] (per 10-mm Hg increase) 1.08 (95% confidence interval, 1.03, 1.13) and 1.06 (0.97, 1.17), respectively. ADL modified the association of DBP with incident CVD. Among those without ADL limitation, DBP was weakly associated with incident CVD, HR 1.04 (0.79, 1.37) for DBP >80, compared with <65 mm Hg. Among those with ADL limitation, DBP was inversely associated with CVD: HR 0.65 (0.44, 0.96) for DBP 66 to 80 mm Hg and HR 0.49 (0.25, 0.94) for DBP >80, compared with DBP ≤65. Among people with ADL limitation, a DBP of 66 to 80 had the lowest risk of death, HR 0.72 (0.57, 0.91), compared with a DBP of ≤65. Associations did not vary by 15-feet walking speed. ADL can identify elders in whom diastolic hypotension is associated with higher cardiovascular risk and death. Functional status, rather than chronologic age alone, should inform design of hypertension trials in elders.
Keywords: Activities of Daily Living; African Continental Ancestry Group; Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Diastole; European Continental Ancestry Group; Female; Follow-Up Studies; Gait; Heart Rate; Humans; Incidence; Longitudinal Studies; Male; Risk Factors; Survival Rate; Systole

Telomere length and the risk of atrial fibrillation: insights into the role of biological versus chronological aging. - Roberts, Jason D; Dewland, Thomas A; Longoria, James; Fitzpatrick, Annette L; Ziv, Elad; Hu, Donglei; Lin, Jue; Glidden, David V; Psaty, Bruce M; Burchard, Esteban G; Blackburn, Elizabeth H; Olgin, Jeffrey E; et al. (Circ Arrhythm Electrophysiol, 2014)
BACKGROUND: Advanced age is the most important risk factor for atrial fibrillation (AF); however, the mechanism remains unknown. Telomeres, regions of DNA that shorten with cell division, are considered reliable markers of biological aging. We sought to examine the association between leukocyte telomere length (LTL) and incident AF in a large population-based cohort using direct LTL measurements and genetic data. To further explore our findings, we compared atrial cell telomere length and LTL in cardiac surgery patients. METHODS AND RESULTS: Mean LTL and the TERT rs2736100 single nucleotide polymorphism were assessed as predictors of incident AF in the Cardiovascular Health Study (CHS). Among the surgical patients, within subject comparison of atrial cell telomere length versus LTL was assessed. Among 1639 CHS participants, we observed no relationship between mean LTL and incident AF before and after adjustment for potential confounders (adjusted hazard ratio, 1.09; 95% confidence interval: 0.92-1.29; P=0.299); chronologic age remained strongly associated with AF in the same model. No association was observed between the TERT rs2736100 single nucleotide polymorphism and incident AF (adjusted hazard ratio: 0.95; 95% confidence interval: 0.88-1.04; P=0.265). In 35 cardiac surgery patients (26 with AF), atrial cell telomere length was longer than LTL (1.19 ± 0.20 versus 1.02 ± 0.25 [T/S ratio], P<0.001), a finding that remained consistent within the AF subgroup. CONCLUSIONS: Our study revealed no evidence of an association between LTL and incident AF and no evidence of relative atrial cell telomere shortening in AF. Chronological aging independent of biological markers of aging is the primary risk factor for AF.
Keywords: Age Factors; Aged; Aging; Atrial Fibrillation; California; Cardiac Surgical Procedures; Cellular Senescence; Cross-Sectional Studies; Female; Genetic Predisposition to Disease; Humans; Incidence; Leukocytes; Male; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Telomerase; Telomere; Time Factors

Testosterone, dihydrotestosterone, and incident cardiovascular disease and mortality in the cardiovascular health study. - Shores, Molly M; Biggs, Mary L; Arnold, Alice M; Smith, Nicholas L; Longstreth, W T; Kizer, Jorge R; Hirsch, Calvin H; Cappola, Anne R; Matsumoto, Alvin M (J Clin Endocrinol Metab, 2014)
CONTEXT: Low testosterone (T) is associated with prevalent cardiovascular disease (CVD) and mortality. DHT, a more potent androgen, may also be associated with CVD and mortality, but few studies have examined this. OBJECTIVE: The study objective was to examine whether T and DHT are risk factors for incident CVD and mortality. DESIGN: In a longitudinal cohort study, we evaluated whether total T, calculated free T (cFT), DHT, and calculated free DHT were associated with incident CVD and mortality in men in the Cardiovascular Health Study (mean age 76, range 66-97 years) who were free of CVD at the time of blood collection. MAIN OUTCOME: The main outcomes were incident CVD and all-cause mortality. RESULTS: Among 1032 men followed for a median of 9 years, 436 incident CVD events and 777 deaths occurred. In models adjusted for cardiovascular risk factors, total T and cFT were not associated with incident CVD or all-cause mortality, whereas DHT and calculated free DHT had curvilinear associations with incident CVD (P < .002 and P = .04, respectively) and all-cause mortality (P < .001 for both). CONCLUSIONS: In a cohort of elderly men, DHT and calculated free DHT were associated with incident CVD and all-cause mortality. Further studies are needed to confirm these results and to clarify the underlying physiologic mechanisms.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cause of Death; Dihydrotestosterone; Humans; Incidence; Longitudinal Studies; Male; Mortality; Residence Characteristics; Risk Factors; Testosterone

Thyroid antibody status, subclinical hypothyroidism, and the risk of coronary heart disease: an individual participant data analysis. - Collet, Tinh-Hai; Bauer, Douglas C; Cappola, Anne R; Asvold, Bjørn O; Weiler, Stefan; Vittinghoff, Eric; Gussekloo, Jacobijn; Bremner, Alexandra; den Elzen, Wendy P J; Maciel, Rui M B; Vanderpump, Mark P J; Cornuz, Jacques; et al. (J Clin Endocrinol Metab, 2014)
CONTEXT: Subclinical hypothyroidism has been associated with increased risk of coronary heart disease (CHD), particularly with thyrotropin levels of 10.0 mIU/L or greater. The measurement of thyroid antibodies helps predict the progression to overt hypothyroidism, but it is unclear whether thyroid autoimmunity independently affects CHD risk. OBJECTIVE: The objective of the study was to compare the CHD risk of subclinical hypothyroidism with and without thyroid peroxidase antibodies (TPOAbs). DATA SOURCES AND STUDY SELECTION: A MEDLINE and EMBASE search from 1950 to 2011 was conducted for prospective cohorts, reporting baseline thyroid function, antibodies, and CHD outcomes. DATA EXTRACTION: Individual data of 38 274 participants from six cohorts for CHD mortality followed up for 460 333 person-years and 33 394 participants from four cohorts for CHD events. DATA SYNTHESIS: Among 38 274 adults (median age 55 y, 63% women), 1691 (4.4%) had subclinical hypothyroidism, of whom 775 (45.8%) had positive TPOAbs. During follow-up, 1436 participants died of CHD and 3285 had CHD events. Compared with euthyroid individuals, age- and gender-adjusted risks of CHD mortality in subclinical hypothyroidism were similar among individuals with and without TPOAbs [hazard ratio (HR) 1.15, 95% confidence interval (CI) 0.87-1.53 vs HR 1.26, CI 1.01-1.58, P for interaction = .62], as were risks of CHD events (HR 1.16, CI 0.87-1.56 vs HR 1.26, CI 1.02-1.56, P for interaction = .65). Risks of CHD mortality and events increased with higher thyrotropin, but within each stratum, risks did not differ by TPOAb status. CONCLUSIONS: CHD risk associated with subclinical hypothyroidism did not differ by TPOAb status, suggesting that biomarkers of thyroid autoimmunity do not add independent prognostic information for CHD outcomes.
Keywords: Adult; Aged; Aged, 80 and over; Autoantibodies; Coronary Disease; Female; Humans; Hypothyroidism; Incidence; Male; Middle Aged; Prevalence; Prognosis; Risk Factors; Seroepidemiologic Studies; Severity of Illness Index; Young Adult

Troponin T, NT-proBNP, and venous thromboembolism: the Longitudinal Investigation of Thromboembolism Etiology (LITE). - Folsom, Aaron R; Lutsey, Pamela L; Nambi, Vijay; deFilippi, Christopher R; Heckbert, Susan R; Cushman, Mary; Ballantyne, Christie M (Vasc Med, 2014)
Increased levels of plasma troponins and natriuretic peptides are markers of cardiac dysfunction associated with increased risk of cardiovascular disease. Little information exists on cardiac dysfunction and occurrence of venous thromboembolism (VTE). In two prospective epidemiological cohorts, we tested the hypothesis that high-sensitivity troponin T (TnT) and N-terminal pro B-type natriuretic peptide (NT-proBNP) are associated positively with VTE occurrence. The Atherosclerosis Risk in Communities (ARIC) study and the Cardiovascular Health Study (CHS) measured plasma TnT and NT-proBNP in 13,719 men or women with no history of venous thrombosis, coronary heart disease, or heart failure and followed them for approximately 10 years for VTE occurrence (n = 348 VTEs). In both ARIC and CHS, TnT was associated positively with incidence of total VTE and provoked VTE, but not with unprovoked VTE: age, race, and sex-adjusted hazard ratios for total VTE in the pooled analysis were 1.00, 0.85, 1.36, 1.51, and 1.98 (p-trend <0.0001) across five categories of TnT. In contrast, the association of NT-proBNP with VTE was positive in ARIC (hazard ratios approximately 2.5-fold for the highest versus lowest NT-proBNP quintiles), but non-existent in CHS.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Biomarkers; Female; Heart Failure; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Prospective Studies; Risk Factors; Troponin T; Venous Thromboembolism

Vitamin D and the risk of dementia and Alzheimer disease. - Littlejohns, Thomas J; Henley, William E; Lang, Iain A; Annweiler, Cedric; Beauchet, Olivier; Chaves, Paulo H M; Fried, Linda; Kestenbaum, Bryan R; Kuller, Lewis H; Langa, Kenneth M; Lopez, Oscar L; Kos, Katarina; et al. (Neurology, 2014)
OBJECTIVE: To determine whether low vitamin D concentrations are associated with an increased risk of incident all-cause dementia and Alzheimer disease. METHODS: One thousand six hundred fifty-eight elderly ambulatory adults free from dementia, cardiovascular disease, and stroke who participated in the US population-based Cardiovascular Health Study between 1992-1993 and 1999 were included. Serum 25-hydroxyvitamin D (25(OH)D) concentrations were determined by liquid chromatography-tandem mass spectrometry from blood samples collected in 1992-1993. Incident all-cause dementia and Alzheimer disease status were assessed during follow-up using National Institute of Neurological and Communicative Disorders and Stroke/Alzheimer's Disease and Related Disorders Association criteria. RESULTS: During a mean follow-up of 5.6 years, 171 participants developed all-cause dementia, including 102 cases of Alzheimer disease. Using Cox proportional hazards models, the multivariate adjusted hazard ratios (95% confidence interval [CI]) for incident all-cause dementia in participants who were severely 25(OH)D deficient (<25 nmol/L) and deficient (≥25 to <50 nmol/L) were 2.25 (95% CI: 1.23-4.13) and 1.53 (95% CI: 1.06-2.21) compared to participants with sufficient concentrations (≥50 nmol/L). The multivariate adjusted hazard ratios for incident Alzheimer disease in participants who were severely 25(OH)D deficient and deficient compared to participants with sufficient concentrations were 2.22 (95% CI: 1.02-4.83) and 1.69 (95% CI: 1.06-2.69). In multivariate adjusted penalized smoothing spline plots, the risk of all-cause dementia and Alzheimer disease markedly increased below a threshold of 50 nmol/L. CONCLUSION: Our results confirm that vitamin D deficiency is associated with a substantially increased risk of all-cause dementia and Alzheimer disease. This adds to the ongoing debate about the role of vitamin D in nonskeletal conditions.
Keywords: Aged; Alzheimer Disease; Dementia; Female; Follow-Up Studies; Humans; Incidence; Male; Proportional Hazards Models; Risk Factors; United States; Vitamin D; Vitamin D Deficiency

What do carotid intima-media thickness and plaque add to the prediction of stroke and cardiovascular disease risk in older adults? The cardiovascular health study. - Gardin, Julius M; Bartz, Traci M; Polak, Joseph F; O'Leary, Daniel H; Wong, Nathan D (J Am Soc Echocardiogr, 2014)
BACKGROUND: The aim of this study was to evaluate whether the addition of ultrasound carotid intima-media thickness (CIMT) measurements and risk categories of plaque help predict incident stroke and cardiovascular disease (CVD) in older adults. METHODS: Carotid ultrasound studies were recorded in the multicenter Cardiovascular Health Study. CVD was defined as coronary heart disease plus heart failure plus stroke. Ten-year risk prediction Cox proportional-hazards models for stroke and CVD were calculated using Cardiovascular Health Study-specific coefficients for Framingham risk score factors. Categories of CIMT and CIMT plus plaque were added to Framingham risk score prediction models, and categorical net reclassification improvement (NRI) and Harrell's c-statistic were calculated. RESULTS: In 4,384 Cardiovascular Health Study participants (61% women, 14% black; mean baseline age, 72 ± 5 years) without CVD at baseline, higher CIMT category and the presence of plaque were both associated with higher incidence rates for stroke and CVD. The addition of CIMT improved the ability of Framingham risk score-type risk models to discriminate cases from noncases of incident stroke and CVD (NRI = 0.062, P = .015, and NRI = 0.027, P < .001, respectively), with no further improvement by adding plaque. For both outcomes, NRI was driven by down-classifying those without incident disease. Although the addition of plaque to CIMT did not result in a significant NRI for either outcome, it was significant among those without incident disease. CONCLUSIONS: In older adults, the addition of CIMT modestly improves 10-year risk prediction for stroke and CVD beyond a traditional risk factor model, mainly by down-classifying risk in those without stroke or CVD; the addition of plaque to CIMT adds no statistical benefit in the overall cohort, although there is evidence of down-classification in those without events.
Keywords: Aged; Cardiovascular Diseases; Carotid Intima-Media Thickness; Carotid Stenosis; Comorbidity; Female; Humans; Incidence; Longitudinal Studies; Male; Reproducibility of Results; Risk Factors; Sensitivity and Specificity; Stroke; Survival Rate

Association between hospitalization for pneumonia and subsequent risk of cardiovascular disease. - Corrales-Medina, Vicente F; Alvarez, Karina N; Weissfeld, Lisa A; Angus, Derek C; Chirinos, Julio A; Chang, Chung-Chou H; Newman, Anne; Loehr, Laura; Folsom, Aaron R; Elkind, Mitchell S; Lyles, Mary F; Kronmal, Richard A; et al. (JAMA, 2015)
IMPORTANCE: The risk of cardiovascular disease (CVD) after infection is poorly understood. OBJECTIVE: To determine whether hospitalization for pneumonia is associated with an increased short-term and long-term risk of CVD. DESIGN, SETTINGS, AND PARTICIPANTS: We examined 2 community-based cohorts: the Cardiovascular Health Study (CHS, n = 5888; enrollment age, ≥65 years; enrollment period, 1989-1994) and the Atherosclerosis Risk in Communities study (ARIC, n = 15,792; enrollment age, 45-64 years; enrollment period, 1987-1989). Participants were followed up through December 31, 2010. We matched each participant hospitalized with pneumonia to 2 controls. Pneumonia cases and controls were followed for occurrence of CVD over 10 years after matching. We estimated hazard ratios (HRs) for CVD at different time intervals, adjusting for demographics, CVD risk factors, subclinical CVD, comorbidities, and functional status. EXPOSURES: Hospitalization for pneumonia. MAIN OUTCOMES AND MEASURES: Incident CVD (myocardial infarction, stroke, and fatal coronary heart disease). RESULTS: Of 591 pneumonia cases in CHS, 206 had CVD events over 10 years after pneumonia hospitalization. CVD risk after pneumonia was highest in the first year. CVD occurred in 54 cases and 6 controls in the first 30 days (HR, 4.07; 95% CI, 2.86-5.27); 11 cases and 9 controls between 31 and 90 days (HR, 2.94; 95% CI, 2.18-3.70); and 22 cases and 55 controls between 91 days and 1 year (HR, 2.10; 95% CI, 1.59-2.60). Additional CVD risk remained elevated into the tenth year, when 4 cases and 12 controls developed CVD (HR, 1.86; 95% CI, 1.18-2.55). In ARIC, of 680 pneumonia cases, 112 had CVD over 10 years after hospitalization. CVD occurred in 4 cases and 3 controls in the first 30 days (HR, 2.38; 95% CI, 1.12-3.63); 4 cases and 0 controls between 31 and 90 days (HR, 2.40; 95% CI, 1.23-3.47); 11 cases and 8 controls between 91 days and 1 year (HR, 2.19; 95% CI, 1.20-3.19); and 8 cases and 7 controls during the second year (HR, 1.88; 95% CI, 1.10-2.66). After the second year, the HRs were no longer statistically significant. CONCLUSIONS AND RELEVANCE: Hospitalization for pneumonia was associated with increased short-term and long-term risk of CVD, suggesting that pneumonia may be a risk factor for CVD.
Keywords: Aged; Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Comorbidity; Female; Hospitalization; Humans; Male; Middle Aged; Pneumonia; Risk Factors

Association between left atrial abnormality on ECG and vascular brain injury on MRI in the Cardiovascular Health Study. - Kamel, Hooman; Bartz, Traci M; Longstreth, W T; Okin, Peter M; Thacker, Evan L; Patton, Kristen K; Stein, Phyllis K; Gottesman, Rebecca F; Heckbert, Susan R; Kronmal, Richard A; Elkind, Mitchell S V; Soliman, Elsayed Z (Stroke, 2015)
BACKGROUND AND PURPOSE: Emerging evidence suggests that atrial disease is associated with vascular brain injury in the absence of atrial fibrillation. METHODS: The Cardiovascular Health Study prospectively enrolled community-dwelling adults aged ≥65 years. Among participants who underwent MRI, we examined associations of ECG left atrial abnormality with brain infarcts and leukoaraiosis. P-wave terminal force in lead V1 was the primary measure of left atrial abnormality; P-wave area and duration were secondary predictors. We excluded participants with atrial fibrillation before or on their index ECG. Primary outcomes were incident infarcts and worsening leukoaraiosis from initial to follow-up scan ≈5 years later. Secondary outcomes were prevalent infarcts and degree of leukoaraiosis on initial MRI. Relative risk (RR) and linear regression models were adjusted for vascular risk factors. RESULTS: Among 3129 participants with ≥1 scan, each SD increase in P-wave terminal force in lead V1 was associated with a 0.05-point (95% confidence interval [CI], 0.0003-0.10) higher baseline white matter grade on a 10-point scale. P-wave terminal force in lead V1 was associated with prevalent infarcts of any type (RR per SD, 1.09; 95% CI, 1.04-1.16) and more so with prevalent nonlacunar infarcts (RR per SD, 1.22; 95% CI, 1.08-1.38). Among 1839 participants with 2 scans, P-wave terminal force in lead V1 was associated with worsening leukoaraiosis (RR per SD, 1.09; 95% CI, 1.01-1.18), but not with incident infarcts (RR per SD, 1.06; 95% CI, 0.93-1.20). Sensitivity analyses adjusting for incident atrial fibrillation found similar results. P-wave area and duration were not associated with outcomes. CONCLUSIONS: ECG left atrial abnormality is associated with vascular brain injury in the absence of documented atrial fibrillation.
Keywords: Aged; Atrial Fibrillation; Brain; Brain Infarction; Cardiovascular Diseases; Cerebrovascular Trauma; Electrocardiography; Female; Heart Atria; Heart Diseases; Humans; Linear Models; Magnetic Resonance Imaging; Male; Middle Aged; Predictive Value of Tests; Prospective Studies; Regression Analysis; Risk Factors; Treatment Outcome

Association of Cardiometabolic Multimorbidity With Mortality. - Di Angelantonio, Emanuele; Kaptoge, Stephen; Wormser, David; Willeit, Peter; Butterworth, Adam S; Bansal, Narinder; O'Keeffe, Linda M; Gao, Pei; Wood, Angela M; Burgess, Stephen; Freitag, Daniel F; Pennells, Lisa; et al. (JAMA, 2015)
IMPORTANCE: The prevalence of cardiometabolic multimorbidity is increasing. OBJECTIVE: To estimate reductions in life expectancy associated with cardiometabolic multimorbidity. DESIGN, SETTING, AND PARTICIPANTS: Age- and sex-adjusted mortality rates and hazard ratios (HRs) were calculated using individual participant data from the Emerging Risk Factors Collaboration (689,300 participants; 91 cohorts; years of baseline surveys: 1960-2007; latest mortality follow-up: April 2013; 128,843 deaths). The HRs from the Emerging Risk Factors Collaboration were compared with those from the UK Biobank (499,808 participants; years of baseline surveys: 2006-2010; latest mortality follow-up: November 2013; 7995 deaths). Cumulative survival was estimated by applying calculated age-specific HRs for mortality to contemporary US age-specific death rates. EXPOSURES: A history of 2 or more of the following: diabetes mellitus, stroke, myocardial infarction (MI). MAIN OUTCOMES AND MEASURES: All-cause mortality and estimated reductions in life expectancy. RESULTS: In participants in the Emerging Risk Factors Collaboration without a history of diabetes, stroke, or MI at baseline (reference group), the all-cause mortality rate adjusted to the age of 60 years was 6.8 per 1000 person-years. Mortality rates per 1000 person-years were 15.6 in participants with a history of diabetes, 16.1 in those with stroke, 16.8 in those with MI, 32.0 in those with both diabetes and MI, 32.5 in those with both diabetes and stroke, 32.8 in those with both stroke and MI, and 59.5 in those with diabetes, stroke, and MI. Compared with the reference group, the HRs for all-cause mortality were 1.9 (95% CI, 1.8-2.0) in participants with a history of diabetes, 2.1 (95% CI, 2.0-2.2) in those with stroke, 2.0 (95% CI, 1.9-2.2) in those with MI, 3.7 (95% CI, 3.3-4.1) in those with both diabetes and MI, 3.8 (95% CI, 3.5-4.2) in those with both diabetes and stroke, 3.5 (95% CI, 3.1-4.0) in those with both stroke and MI, and 6.9 (95% CI, 5.7-8.3) in those with diabetes, stroke, and MI. The HRs from the Emerging Risk Factors Collaboration were similar to those from the more recently recruited UK Biobank. The HRs were little changed after further adjustment for markers of established intermediate pathways (eg, levels of lipids and blood pressure) and lifestyle factors (eg, smoking, diet). At the age of 60 years, a history of any 2 of these conditions was associated with 12 years of reduced life expectancy and a history of all 3 of these conditions was associated with 15 years of reduced life expectancy. CONCLUSIONS AND RELEVANCE: Mortality associated with a history of diabetes, stroke, or MI was similar for each condition. Because any combination of these conditions was associated with multiplicative mortality risk, life expectancy was substantially lower in people with multimorbidity.
Keywords: Adult; Aged; Comorbidity; Diabetes Mellitus; Female; Humans; Life Expectancy; Male; Middle Aged; Mortality; Myocardial Infarction; Risk Factors; Stroke

Association of exome sequences with plasma C-reactive protein levels in >9000 participants. - Schick, Ursula M; Auer, Paul L; Bis, Joshua C; Lin, Honghuang; Wei, Peng; Pankratz, Nathan; Lange, Leslie A; Brody, Jennifer; Stitziel, Nathan O; Kim, Daniel S; Carlson, Christopher S; Fornage, Myriam; et al. (Hum Mol Genet, 2015)
C-reactive protein (CRP) concentration is a heritable systemic marker of inflammation that is associated with cardiovascular disease risk. Genome-wide association studies have identified CRP-associated common variants associated in ∼25 genes. Our aims were to apply exome sequencing to (1) assess whether the candidate loci contain rare coding variants associated with CRP levels and (2) perform an exome-wide search for rare variants in novel genes associated with CRP levels. We exome-sequenced 6050 European-Americans (EAs) and 3109 African-Americans (AAs) from the NHLBI-ESP and the CHARGE consortia, and performed association tests of sequence data with measured CRP levels. In single-variant tests across candidate loci, a novel rare (minor allele frequency = 0.16%) CRP-coding variant (rs77832441-A; p.Thr59Met) was associated with 53% lower mean CRP levels (P = 2.9 × 10(-6)). We replicated the association of rs77832441 in an exome array analysis of 11 414 EAs (P = 3.0 × 10(-15)). Despite a strong effect on CRP levels, rs77832441 was not associated with inflammation-related phenotypes including coronary heart disease. We also found evidence for an AA-specific association of APOE-ε2 rs7214 with higher CRP levels. At the exome-wide significance level (P < 5.0 × 10(-8)), we confirmed associations for reported common variants of HNF1A, CRP, IL6R and TOMM40-APOE. In gene-based tests, a burden of rare/lower frequency variation in CRP in EAs (P ≤ 6.8 × 10(-4)) and in retinoic acid receptor-related orphan receptor α (RORA) in AAs (P = 1.7 × 10(-3)) were associated with CRP levels at the candidate gene level (P < 2.0 × 10(-3)). This inquiry did not elucidate novel genes, but instead demonstrated that variants distributed across the allele frequency spectrum within candidate genes contribute to CRP levels.
Keywords: Adult; African Americans; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Plasma; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors

Atherosclerotic cardiovascular disease in older adults with diabetes mellitus. - Barzilay, Joshua I; Mukamal, Kenneth J; Kizer, Jorge R (Clin Geriatr Med, 2015)
Diabetes mellitus exerts a strong effect on atherosclerotic cardiovascular disease risk into older age (beyond ages 70-74 years). This effect is particularly noticeable with regard to coronary artery disease and cerebral microvascular disease. Thus, diabetes mellitus in older adults deserves the same careful medical attention as it does in middle age.
Keywords: Age Factors; Aged; Coronary Artery Disease; Diabetes Mellitus, Type 2; Female; Humans; Male; Risk Factors; Survival Rate

Cardiovascular and Mortality Outcomes in the Elderly With Impaired Cardiac and Pulmonary Function: The Cardiovascular Health Study (CHS). - Waheed, Salman; Chaves, Paulo H M; Gardin, Julius M; Cao, Jie Jane (J Am Heart Assoc, 2015)
BACKGROUND: Impaired pulmonary function (IPF) and left ventricular systolic dysfunction (LVSD) are prevalent in the elderly and are associated with significant morbidity and mortality. The main objectives of this study were to examine the relative impact and joint association of IPF and LVSD with heart failure, cardiovascular mortality and all-cause mortality, and their impact on risk classification using a continuous net reclassification index. METHODS AND RESULTS: We followed 2342 adults without prevalent cardiovascular disease (mean age, 76 years) from the Cardiovascular Health Study for a median of 12.6 years. LVSD was defined as LV ejection fraction <55%. IPF was defined as: forced expiratory volume in 1 second:forced vital capacity <70%, and predicted forced expiratory volume in 1 second <80%. Outcomes included heart failure hospitalization, cardiovascular mortality, all-cause mortality, and composite outcome. LVSD was detected in 128 subjects (6%), IPF in 441 (19%) and both in 38 (2%). Compared to those without LVSD or IPF, there was a significantly increased cardiovascular risk for groups of LVSD only, IPF only, and LVSD plus IPF, adjusted hazard ratio (95% CI) 2.1 (1.5-3.0), 1.7 (1.4-2.1), and 3.2 (2.0-5.1) for HF; 1.8 (1.2-2.6), 1.4 (1.1-1.8), and 2.8 (1.7-4.7) for cardiovascular mortality; 1.3 (1.0-1.8), 1.7 (1.4-1.9), and 2.1 (1.5-3.0) for all-cause mortality, and 1.6 (1.3-2.1), 1.7 (1.5-1.9), and 2.4 (1.7-3.3) for composite outcome, respectively. Risk classification improved significantly for all outcomes when IPF was added to the adjusted model with LVSD or LVSD to IPF. CONCLUSIONS: While risk of cardiovascular outcomes was the highest among elderly with both LVSD and IPF, risk was comparable between subjects with IPF alone and those with LVSD alone. This observation, combined with improved risk classification by adding IPF to LVSD or LVSD to IPF, underscore the importance of comprehensive heart and lung evaluation in cardiovascular outcome assessment.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Heart Diseases; Heart Failure; Hospitalization; Humans; Kaplan-Meier Estimate; Lung Diseases; Male; Mortality; Prospective Studies; Respiratory Function Tests; Risk Assessment; Risk Factors; Stroke Volume; United States; Ventricular Dysfunction, Left

Coagulation factor XII genetic variation, ex vivo thrombin generation, and stroke risk in the elderly: results from the Cardiovascular Health Study. - Olson, N C; Butenas, S; Lange, L A; Lange, E M; Cushman, M; Jenny, N S; Walston, J; Souto, J C; Soria, J M; Chauhan, G; Debette, S; Longstreth, W T; et al. (J Thromb Haemost, 2015)
BACKGROUND: The relationships of thrombin generation (TG) with cardiovascular disease risk are underevaluated in population-based cohorts. OBJECTIVES: To evaluate the relationships of TG influenced by the contact and tissue factor coagulation pathways ex vivo with common single-nucleotide polymorphisms (SNPs) and incident cardiovascular disease and stroke. PATIENTS/METHODS: We measured peak TG (pTG) in baseline plasma samples of Cardiovascular Health Study participants (n = 5411), both with and without inhibitory anti-factor XIa antibody (pTG/FXIa(-) ). We evaluated their associations with ~ 50 000 SNPs by using the IBCv2 genotyping array, and with incident cardiovascular disease and stroke events over a median follow-up of 13.2 years. RESULTS: The minor allele for an SNP in the FXII gene (F12), rs1801020, was associated with lower pTG in European-Americans (β = - 34.2 ± 3.5 nm; P = 3.3 × 10(-22) ; minor allele frequency [MAF] = 0.23) and African-Americans (β = - 31.1 ± 7.9 nm; P = 9.0 × 10(-5) ; MAF = 0.42). Lower FXIa-independent pTG (pTG/FXIa(-) ) was associated with the F12 rs1801020 minor allele, and higher pTG/FXIa(-) was associated with the ABO SNP rs657152 minor allele (β = 16.3 nm; P = 4.3 × 10(-9) ; MAF = 0.37). The risk factor-adjusted ischemic stroke hazard ratios were 1.09 (95% confidence interval CI 1.01-1.17; P = 0.03) for pTG, 1.06 (95% CI 0.98-1.15; P = 0.17) for pTG/FXIa(-) , and 1.11 (95% CI 1.02-1.21; P = 0.02) for FXIa-dependent pTG (pTG/FXIa(+) ), per one standard deviation increment (n = 834 ischemic strokes). In a multicohort candidate gene analysis, rs1801020 was not associated with incident ischemic stroke (β = - 0.02; standard error = 0.08; P = 0.81). CONCLUSIONS: These results support the importance of contact activation pathway-dependent TG as a risk factor for ischemic stroke, and indicate the importance of F12 SNPs for TG ex vivo and in vivo.
Keywords: African Americans; Age Factors; Aged; Blood Coagulation; Brain Ischemia; European Continental Ancestry Group; Factor XII; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Incidence; Male; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Stroke; Thrombin; Time Factors; United States

Consumption of meat is associated with higher fasting glucose and insulin concentrations regardless of glucose and insulin genetic risk scores: a meta-analysis of 50,345 Caucasians. - Fretts, Amanda M; Follis, Jack L; Nettleton, Jennifer A; Lemaitre, Rozenn N; Ngwa, Julius S; Wojczynski, Mary K; Kalafati, Ioanna Panagiota; Varga, Tibor V; Frazier-Wood, Alexis C; Houston, Denise K; Lahti, Jari; Ericson, Ulrika; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Recent studies suggest that meat intake is associated with diabetes-related phenotypes. However, whether the associations of meat intake and glucose and insulin homeostasis are modified by genes related to glucose and insulin is unknown. OBJECTIVE: We investigated the associations of meat intake and the interaction of meat with genotype on fasting glucose and insulin concentrations in Caucasians free of diabetes mellitus. DESIGN: Fourteen studies that are part of the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium participated in the analysis. Data were provided for up to 50,345 participants. Using linear regression within studies and a fixed-effects meta-analysis across studies, we examined 1) the associations of processed meat and unprocessed red meat intake with fasting glucose and insulin concentrations; and 2) the interactions of processed meat and unprocessed red meat with genetic risk score related to fasting glucose or insulin resistance on fasting glucose and insulin concentrations. RESULTS: Processed meat was associated with higher fasting glucose, and unprocessed red meat was associated with both higher fasting glucose and fasting insulin concentrations after adjustment for potential confounders [not including body mass index (BMI)]. For every additional 50-g serving of processed meat per day, fasting glucose was 0.021 mmol/L (95% CI: 0.011, 0.030 mmol/L) higher. Every additional 100-g serving of unprocessed red meat per day was associated with a 0.037-mmol/L (95% CI: 0.023, 0.051-mmol/L) higher fasting glucose concentration and a 0.049-ln-pmol/L (95% CI: 0.035, 0.063-ln-pmol/L) higher fasting insulin concentration. After additional adjustment for BMI, observed associations were attenuated and no longer statistically significant. The association of processed meat and fasting insulin did not reach statistical significance after correction for multiple comparisons. Observed associations were not modified by genetic loci known to influence fasting glucose or insulin resistance. CONCLUSION: The association of higher fasting glucose and insulin concentrations with meat consumption was not modified by an index of glucose- and insulin-related single-nucleotide polymorphisms. Six of the participating studies are registered at clinicaltrials.gov as NCT0000513 (Atherosclerosis Risk in Communities), NCT00149435 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetics of Lipid Lowering Drugs and Diet Network), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Blood Glucose; Cohort Studies; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hyperglycemia; Hyperinsulinism; Insulin; Insulin Resistance; Insulin-Secreting Cells; Meat; Meat Products; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Contribution of Major Lifestyle Risk Factors for Incident Heart Failure in Older Adults: The Cardiovascular Health Study. - Del Gobbo, Liana C; Kalantarian, Shadi; Imamura, Fumiaki; Lemaitre, Rozenn; Siscovick, David S; Psaty, Bruce M; Mozaffarian, Dariush (JACC Heart Fail, 2015)
OBJECTIVES: The goal of this study was to determine the relative contribution of major lifestyle factors on the development of heart failure (HF) in older adults. BACKGROUND: HF incurs high morbidity, mortality, and health care costs among adults ≥65 years of age, which is the most rapidly growing segment of the U.S. METHODS: We prospectively investigated separate and combined associations of lifestyle risk factors with incident HF (1,380 cases) over 21.5 years among 4,490 men and women in the Cardiovascular Health Study, which is a community-based cohort of older adults. Lifestyle factors included 4 dietary patterns (Alternative Healthy Eating Index, Dietary Approaches to Stop Hypertension, an American Heart Association 2020 dietary goals score, and a Biologic pattern, which was constructed using previous knowledge of cardiovascular disease dietary risk factors), 4 physical activity metrics (exercise intensity, walking pace, energy expended in leisure activity, and walking distance), alcohol intake, smoking, and obesity. RESULTS: No dietary pattern was associated with developing HF (p > 0.05). Walking pace and leisure activity were associated with a 26% and 22% lower risk of HF, respectively (pace >3 mph vs. <2 mph; hazard ratio [HR]: 0.74; 95% confidence interval [CI]: 0.63 to 0.86; leisure activity ≥845 kcal/week vs. <845 kcal/week; HR: 0.78; 95% CI: 0.69 to 0.87). Modest alcohol intake, maintaining a body mass index <30 kg/m(2), and not smoking were also independently associated with a lower risk of HF. Participants with ≥4 healthy lifestyle factors had a 45% (HR: 0.55; 95% CI: 0.42 to 0.74) lower risk of HF. Heterogeneity by age, sex, cardiovascular disease, hypertension medication use, and diabetes was not observed. CONCLUSIONS: Among older U.S. adults, physical activity, modest alcohol intake, avoiding obesity, and not smoking, but not dietary patterns, were associated with a lower risk of HF.
Keywords: Aged; Alcohol Drinking; Cohort Studies; Diet; Female; Heart Failure; Humans; Incidence; Male; Motor Activity; Obesity; Proportional Hazards Models; Prospective Studies; Risk Factors; Sedentary Lifestyle; Smoking; United States

DCAF4, a novel gene associated with leucocyte telomere length. - Mangino, Massimo; Christiansen, Lene; Stone, Rivka; Hunt, Steven C; Horvath, Kent; Eisenberg, Dan T A; Kimura, Masayuki; Petersen, Inge; Kark, Jeremy D; Herbig, Utz; Reiner, Alex P; Benetos, Athanase; et al. (J Med Genet, 2015)
BACKGROUND: Leucocyte telomere length (LTL), which is fashioned by multiple genes, has been linked to a host of human diseases, including sporadic melanoma. A number of genes associated with LTL have already been identified through genome-wide association studies. The main aim of this study was to establish whether DCAF4 (DDB1 and CUL4-associated factor 4) is associated with LTL. In addition, using ingenuity pathway analysis (IPA), we examined whether LTL-associated genes in the general population might partially explain the inherently longer LTL in patients with sporadic melanoma, the risk for which is increased with ultraviolet radiation (UVR). RESULTS: Genome-wide association (GWA) meta-analysis and de novo genotyping of 20 022 individuals revealed a novel association (p=6.4×10(-10)) between LTL and rs2535913, which lies within DCAF4. Notably, eQTL analysis showed that rs2535913 is associated with decline in DCAF4 expressions in both lymphoblastoid cells and sun-exposed skin (p=4.1×10(-3) and 2×10(-3), respectively). Moreover, IPA revealed that LTL-associated genes, derived from GWA meta-analysis (N=9190), are over-represented among genes engaged in melanoma pathways. Meeting increasingly stringent p value thresholds (p<0.05, <0.01, <0.005, <0.001) in the LTL-GWA meta-analysis, these genes were jointly over-represented for melanoma at p values ranging from 1.97×10(-169) to 3.42×10(-24). CONCLUSIONS: We uncovered a new locus associated with LTL in the general population. We also provided preliminary findings that suggest a link of LTL through genetic mechanisms with UVR and melanoma in the general population.
Keywords: Alleles; Carrier Proteins; Gene Expression Regulation; Genome-Wide Association Study; Humans; Leukocytes; Melanoma; Risk Factors; Telomere; Telomere Homeostasis

Development and validation of a model to predict 5-year risk of death without ESRD among older adults with CKD. - Bansal, Nisha; Katz, Ronit; de Boer, Ian H; Peralta, Carmen A; Fried, Linda F; Siscovick, David S; Rifkin, Dena E; Hirsch, Calvin; Cummings, Steven R; Harris, Tamara B; Kritchevsky, Stephen B; Sarnak, Mark J; et al. (Clin J Am Soc Nephrol, 2015)
BACKGROUND AND OBJECTIVES: CKD is associated with mortality. Accurate prediction tools for mortality may guide clinical decision-making, particularly among elderly persons with CKD. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: A prediction equation was developed for 5-year risk of mortality among participants with CKD in the Cardiovascular Health Study. Sixteen candidate predictor variables were explored, which included demographics, physical examination measures, comorbidity, medication use, and kidney function measures (eGFR calculated from serum creatinine and the CKD Epidemiology Collaboration equation and the urine albumin-to-creatinine ratio). Models were developed using Cox regression and evaluated using c statistics. A final parsimonious model was externally validated in an independent cohort of community-living elders with CKD in the Health, Aging, and Body Composition Study. RESULTS: The development cohort included 828 participants who had a mean age of 80 (±5.6) years and an eGFR of 47 (±11) ml/min per 1.73 m(2), and median albumin-to-creatinine ratio of 13 (interquartile range 6-51) mg/g. The validation cohort included 789 participants who had a mean age of 74 (±2.8) years and an eGFR of 50 (±9) ml/min per 1.73 m(2), and median albumin-to-creatinine ratio of 13 (interquartile range 6-42) mg/g. The final model for 5-year mortality risk included age, sex, race, eGFR, urine albumin-to-creatinine ratio, smoking, diabetes mellitus, and history of heart failure and stroke (c statistic=0.72; 95% confidence interval, 0.68 to 0.74). When a point-based system was assigned for each of nine variables in the equation, the estimated risk of death within 5 years ranged from 3.8% among participants with the lowest scores to 83.6% among participants with nine points. The model performed fair in external validation (c statistic=0.69; 95% confidence interval, 0.64 to 0.74). CONCLUSIONS: A simple prediction tool using nine readily available clinical variables can assist in predicting 5-year mortality risk in elderly patients with CKD, which may be useful in counseling patients and guiding clinical decision making.
Keywords: Age Factors; Aged; Aged, 80 and over; Albuminuria; Continental Population Groups; Creatinine; Diabetes Mellitus; Female; Glomerular Filtration Rate; Heart Failure; Humans; Male; Proportional Hazards Models; Regression Analysis; Renal Insufficiency, Chronic; Risk Factors; Sex Factors; Smoking; Stroke

Empirically Derived Trajectories to Dementia Over 15 Years of Follow-up Identified by Using Mixed Membership Models. - Lecci, Fabrizio; Junker, Brian; Kuller, Lewis H; Lopez, Oscar L; Becker, James T (Am J Epidemiol, 2015)
Alzheimer disease is the most common form of dementia in the elderly, and the complex relationships among risk factors produce highly variable natural histories from normal cognition through the prodromal stage of mild cognitive impairment (MCI) to clinical dementia. We used a novel statistical approach, mixed membership trajectory models, to capture the variety of such pathways in 652 participants in the Cardiovascular Health Study Cognition Study over 22 years of follow-up (1992-2014). We identified 3 trajectories: a "healthy" profile with a peak probability of MCI between 95 and 100 years of age and only a 50% probability of dementia by age 100; an "intermediate" profile with a peak probability of MCI between 85 and 90 years of age and progression to dementia between 90 and 95 years; and an "unhealthy" profile with a peak probability of progressing to MCI between ages 75 and 80 years and to dementia between the ages of 80 and 85 years. Hypertension, education, race, and the ϵ4 allele of the apolipoprotein E gene all affected the closeness of an individual to 1 or more of the canonical trajectories. These results provide new insights into the natural history of Alzheimer disease and evidence for a potential difference in the pathophysiology of the development of dementia.
Keywords: Age Distribution; Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Cardiovascular Diseases; Comorbidity; Dementia; Diabetes Mellitus; Disease Progression; Female; Follow-Up Studies; Humans; Magnetic Resonance Imaging; Male; Mild Cognitive Impairment; Neuroimaging; Prevalence; Proportional Hazards Models; Risk Factors; Sex Distribution

Fetuin-A and risk of coronary heart disease: A Mendelian randomization analysis and a pooled analysis of AHSG genetic variants in 7 prospective studies. - Laugsand, Lars E; Ix, Joachim H; Bartz, Traci M; Djoussé, Luc; Kizer, Jorge R; Tracy, Russell P; Dehghan, Abbas; Rexrode, Kathryn; Lopez, Oscar L; Rimm, Eric B; Siscovick, David S; O'Donnell, Christopher J; et al. (Atherosclerosis, 2015)
BACKGROUND AND AIMS: Fetuin-A has a plausible role in the inhibition of arterial calcification, but its association with risk of coronary heart disease (CHD) in the general population is unclear. We used two common genetic variants in the fetuin-A gene (AHSG) that are strongly associated with circulating fetuin-A levels to investigate the associations with risk of CHD and subclinical cardiovascular measures (intima-media thickness, ankle-arm index, and coronary artery calcification). METHODS: Genetic variation and fetuin-A levels were assessed in 3299 community-living individuals (2733 Caucasians and 566 African Americans) 65 years of age or older, free of previous cardiovascular disease, who participated in the Cardiovascular Health Study (CHS) in 1992-1993. RESULTS: Among Caucasians, both rs2248690 and rs4917 were associated with 12% lower fetuin-A concentrations per minor allele (P < 0.0001). The hazard ratios (HRs) per minor allele for incident CHD were 1.12 (95% CI: 1.00-1.26) for rs2248690 and 1.02 (0.91-1.14) for rs4917. Using both genotypes as an instrumental variable for measured fetuin-A, the HRs for one standard deviation increase in genetically determined fetuin-A levels on CHD risk were 0.84 (95% CI: 0.70-1.00) for rs2248690 and 0.97 (95% CI: 0.82-1.14) for rs4917, respectively. However, in CHS neither of the genotypes were associated with subclinical cardiovascular measures and when CHS data were meta-analyzed with data from six other prospective studies (totaling 26,702 Caucasian participants and 3295 CHD cases), the meta-analyzed HRs for incident CHD were 1.12 (0.93-1.34) and 1.06 (0.93-1.20) for rs2248690 and rs4917, respectively (p heterogeneity 0.005 and 0.0048). CONCLUSION: Common variants in the AHSG gene are strongly associated with fetuin-A levels, but their concurrent association with CHD risk in current prospective studies is inconsistent. Further investigation in studies with measured fetuin-A and AHSG variants is needed to clarify the potential causal association of fetuin-A with CHD risk.
Keywords: Aged; Aged, 80 and over; alpha-2-HS-Glycoprotein; Carotid Intima-Media Thickness; Coronary Vessels; Female; Genetic Variation; Genotype; Heart Diseases; Humans; Insulin Resistance; Longitudinal Studies; Male; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Vascular Calcification

Fibroblast growth factor 23 and sudden versus non-sudden cardiac death: the Cardiovascular Health Study. - Deo, Rajat; Katz, Ronit; de Boer, Ian H; Sotoodehnia, Nona; Kestenbaum, Bryan; Mukamal, Kenneth J; Chonchol, Michel; Sarnak, Mark J; Siscovick, David; Shlipak, Michael G; Ix, Joachim H (Am J Kidney Dis, 2015)
BACKGROUND: Elevated fibroblast growth factor 23 (FGF-23) concentrations are associated with greater risk of cardiovascular events and mortality, especially among people with chronic kidney disease (CKD). Because individuals with CKD are at an increased risk of sudden cardiac death (SCD), we sought to understand whether FGF-23 level is a stronger risk factor for SCD versus non-SCD. STUDY DESIGN: Cohort study. SETTING & PARTICIPANTS: 3,244 participants 65 years or older in the community-based Cardiovascular Health Study. PREDICTOR: Plasma FGF-23 concentrations. OUTCOMES: We assessed SCD and non-SCD in these analyses. SCD was adjudicated rigorously and was defined as a sudden pulseless condition of cardiac origin in a previously stable person occurring out of hospital or in the emergency department. MEASUREMENTS: We estimated associations of baseline FGF-23 concentrations with SCD and non-SCD using Cox proportional hazards models after adjustment for demographics, cardiovascular risk factors, comorbid conditions, and kidney function. We also tested whether associations differed by CKD status. RESULTS: During a median follow-up of 8.1 years, there were 118 adjudicated SCD and 570 non-SCD events. After multivariable adjustment for demographics, cardiovascular risk factors, comorbid conditions, and parameters of kidney function, higher FGF-23 concentrations were an independent risk factor for non-SCD (HR [per doubling], 1.17; 95% CI, 1.06-1.30). However, elevated FGF-23 concentrations were not associated independently with SCD (HR [per doubling], 1.07; 95% CI, 0.85-1.35). In stratified analysis by CKD status (36.5% of cohort), doubling of FGF-23 concentrations was associated independently with non-SCD (adjusted HR, 1.26; 95% CI, 1.10-1.45). A similar magnitude of association was observed between FGF-23 level and SCD in the CKD subgroup; however, it was not significant (HR, 1.20; 95% CI, 0.89-1.62). LIMITATIONS: Limited power to detect moderate-sized effects between FGF-23 level and SCD in both the primary and stratified analyses. CONCLUSIONS: In this population-based study, FGF-23 level elevations were associated independently with non-SCD. Among individuals with CKD, the associations between FGF-23 level and SCD and non-SCD were similar.
Keywords: Aged; Aged, 80 and over; Biomarkers; Comorbidity; Death, Sudden, Cardiac; Electrocardiography; Female; Fibroblast Growth Factors; Follow-Up Studies; Heart Arrest; Heart Diseases; Humans; Kaplan-Meier Estimate; Male; Prospective Studies; Renal Insufficiency, Chronic; Risk Factors; Sympathetic Nervous System; United States

Fibrosis-related biomarkers and large and small vessel disease: the Cardiovascular Health Study. - Agarwal, Isha; Arnold, Alice; Glazer, Nicole L; Barasch, Eddy; Djoussé, Luc; Fitzpatrick, Annette L; Gottdiener, John S; Ix, Joachim H; Jensen, Richard A; Kizer, Jorge R; Rimm, Eric B; Siscovick, David S; et al. (Atherosclerosis, 2015)
OBJECTIVE: Fibrosis has been implicated in a number of pathological, organ-based conditions of the liver, kidney, heart, and lungs. The objective of this study was to determine whether biomarkers of fibrosis are associated with vascular disease in the large and/or small vessels. METHODS: We evaluated the associations of two circulating biomarkers of fibrosis, transforming growth factor-β (TGF-β) and procollagen type III N-terminal propeptide (PIIINP), with incident peripheral artery disease (PAD) and subclinical macrovascular (carotid intima-media thickness, flow-mediated vasodilation, ankle-brachial index, retinal vein diameter), and microvascular (retinal artery diameter and retinopathy) disease among older adults in the Cardiovascular Health Study. We measured TGF-β and PIIINP from samples collected in 1996 and ascertained clinical PAD through 2011. Measurements of large and small vessels were collected between 1996 and 1998. RESULTS: After adjustment for sociodemographic, clinical, and biochemical risk factors, TGF-β was associated with incident PAD (hazard ratio [HR] = 1.36 per doubling of TGF-β, 95% confidence interval [CI] = 1.04, 1.78) and retinal venular diameter (1.63 μm per doubling of TGF-β, CI = 0.23, 3.02). PIIINP was not associated with incident PAD, but was associated with carotid intima-media thickness (0.102 mm per doubling of PIIINP, CI = 0.029, 0.174) and impaired brachial artery reactivity (-0.20% change per doubling of PIIINP, CI = -0.39, -0.02). Neither TGF-β nor PIIINP were associated with retinal arteriolar diameter or retinopathy. CONCLUSIONS: Serum concentrations of fibrosis-related biomarkers were associated with several measures of large vessel disease, including incident PAD, but not with small vessel disease. Fibrosis may contribute to large vessel atherosclerosis in older adults.
Keywords: Aged; Ankle Brachial Index; Biomarkers; Brachial Artery; Carotid Artery Diseases; Carotid Intima-Media Thickness; Cross-Sectional Studies; Female; Fibrosis; Humans; Incidence; Male; Peptide Fragments; Peripheral Arterial Disease; Predictive Value of Tests; Procollagen; Prognosis; Prospective Studies; Retinal Diseases; Risk Factors; Transforming Growth Factor beta; United States; Vasodilation

Genes from a translational analysis support a multifactorial nature of white matter hyperintensities. - Lopez, Lorna M; Hill, W David; Harris, Sarah E; Valdes Hernandez, Maria; Munoz Maniega, Susana; Bastin, Mark E; Bailey, Emma; Smith, Colin; McBride, Martin; McClure, John; Graham, Delyth; Dominiczak, Anna; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: White matter hyperintensities (WMH) of presumed vascular origin increase the risk of stroke and dementia. Despite strong WMH heritability, few gene associations have been identified. Relevant experimental models may be informative. METHODS: We tested the associations between genes that were differentially expressed in brains of young spontaneously hypertensive stroke-prone rats and human WMH (using volume and visual score) in 621 subjects from the Lothian Birth Cohort 1936 (LBC1936). We then attempted replication in 9361 subjects from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE). We also tested the subjects from LBC1936 for previous genome-wide WMH associations found in subjects from CHARGE. RESULTS: Of 126 spontaneously hypertensive stroke-prone rat genes, 10 were nominally associated with WMH volume or score in subjects from LBC1936, of which 5 (AFP, ALB, GNAI1, RBM8a, and MRPL18) were associated with both WMH volume and score (P<0.05); 2 of the 10 (XPNPEP1, P=6.7×10(-5); FARP1, P=0.024) plus another spontaneously hypertensive stroke-prone rat gene (USMG5, P=0.00014), on chromosomes 10, 13, and 10 respectively, were associated with WMH in subjects from CHARGE. Gene set enrichment showed significant associations for downregulated spontaneously hypertensive stroke-prone rat genes with WMH in humans. In subjects from LBC1936, we replicated CHARGE's genome-wide WMH associations on chromosomes 17 (TRIM65 and TRIM47) and, for the first time, 1 (PMF1). CONCLUSIONS: Despite not passing multiple testing thresholds individually, these genes collectively are relevant to known WMH associations, proposed WMH mechanisms, or dementia: associations with Alzheimer's disease, late-life depression, ATP production, osmotic regulation, neurodevelopmental abnormalities, and cognitive impairment. If replicated further, they suggest a multifactorial nature for WMH and argue for more consideration of vascular contributions to dementia.
Keywords: Aged; Alzheimer Disease; Animals; Brain; Causality; Dementia; Female; Genome-Wide Association Study; Humans; Leukoencephalopathies; Male; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR; Rats, Wistar; Risk Factors; Translational Medical Research; White Matter

Higher circulating adiponectin levels are associated with increased risk of atrial fibrillation in older adults. - Macheret, Fima; Bartz, Traci M; Djoussé, Luc; Ix, Joachim H; Mukamal, Kenneth J; Zieman, Susan J; Siscovick, David S; Tracy, Russell P; Heckbert, Susan R; Psaty, Bruce M; Kizer, Jorge R (Heart, 2015)
BACKGROUND: Adiponectin has cardioprotective properties, suggesting that lower levels seen in obesity and diabetes could heighten risk of atrial fibrillation (AF). Among older adults, however, higher adiponectin has been linked to greater incidence of adverse outcomes associated with AF, although recent reports have shown this association to be U-shaped. We postulated that higher adiponectin would be linked to increased risk for AF in older adults in a U-shaped manner. METHODS: We examined the associations of total and high-molecular-weight (HMW) adiponectin with incident AF among individuals free of prevalent cardiovascular disease (CVD) participating in a population-based cohort study of older adults (n=3190; age=74±5 years). RESULTS: During median follow-up of 11.4 years, there were 886 incident AF events. Adjusted cubic splines showed a positive and linear association between adiponectin and incident AF. After adjusting for potential confounders, including amino-terminal pro-B-type natriuretic peptide 1-76, the HR (95% CI) for AF per SD increase in total adiponectin was 1.14 (1.05 to 1.24), while that for HMW adiponectin was 1.17 (1.08 to 1.27). Additional adjustment for putative mediators, including subclinical CVD, diabetes, lipids and inflammation, did not significantly affect these estimates. CONCLUSIONS: The present findings demonstrate that higher, not lower, levels of adiponectin are independently associated with increased risk of AF in older adults despite its documented cardiometabolic benefits. Additional work is necessary to determine if adiponectin is a marker of failed counter-regulatory pathways or whether this hormone is directly harmful in the setting of or as a result of advanced age.
Keywords: Adiponectin; Age Factors; Aged; Aged, 80 and over; Aging; Atrial Fibrillation; Biomarkers; Female; Humans; Incidence; Linear Models; Male; Multivariate Analysis; Natriuretic Peptide, Brain; Peptide Fragments; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation

HMG-coenzyme A reductase inhibition, type 2 diabetes, and bodyweight: evidence from genetic analysis and randomised trials. - Swerdlow, Daniel I; Preiss, David; Kuchenbaecker, Karoline B; Holmes, Michael V; Engmann, Jorgen E L; Shah, Tina; Sofat, Reecha; Stender, Stefan; Johnson, Paul C D; Scott, Robert A; Leusink, Maarten; Verweij, Niek; et al. (Lancet, 2015)
BACKGROUND: Statins increase the risk of new-onset type 2 diabetes mellitus. We aimed to assess whether this increase in risk is a consequence of inhibition of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), the intended drug target. METHODS: We used single nucleotide polymorphisms in the HMGCR gene, rs17238484 (for the main analysis) and rs12916 (for a subsidiary analysis) as proxies for HMGCR inhibition by statins. We examined associations of these variants with plasma lipid, glucose, and insulin concentrations; bodyweight; waist circumference; and prevalent and incident type 2 diabetes. Study-specific effect estimates per copy of each LDL-lowering allele were pooled by meta-analysis. These findings were compared with a meta-analysis of new-onset type 2 diabetes and bodyweight change data from randomised trials of statin drugs. The effects of statins in each randomised trial were assessed using meta-analysis. FINDINGS: Data were available for up to 223 463 individuals from 43 genetic studies. Each additional rs17238484-G allele was associated with a mean 0·06 mmol/L (95% CI 0·05-0·07) lower LDL cholesterol and higher body weight (0·30 kg, 0·18-0·43), waist circumference (0·32 cm, 0·16-0·47), plasma insulin concentration (1·62%, 0·53-2·72), and plasma glucose concentration (0·23%, 0·02-0·44). The rs12916 SNP had similar effects on LDL cholesterol, bodyweight, and waist circumference. The rs17238484-G allele seemed to be associated with higher risk of type 2 diabetes (odds ratio [OR] per allele 1·02, 95% CI 1·00-1·05); the rs12916-T allele association was consistent (1·06, 1·03-1·09). In 129 170 individuals in randomised trials, statins lowered LDL cholesterol by 0·92 mmol/L (95% CI 0·18-1·67) at 1-year of follow-up, increased bodyweight by 0·24 kg (95% CI 0·10-0·38 in all trials; 0·33 kg, 95% CI 0·24-0·42 in placebo or standard care controlled trials and -0·15 kg, 95% CI -0·39 to 0·08 in intensive-dose vs moderate-dose trials) at a mean of 4·2 years (range 1·9-6·7) of follow-up, and increased the odds of new-onset type 2 diabetes (OR 1·12, 95% CI 1·06-1·18 in all trials; 1·11, 95% CI 1·03-1·20 in placebo or standard care controlled trials and 1·12, 95% CI 1·04-1·22 in intensive-dose vs moderate dose trials). INTERPRETATION: The increased risk of type 2 diabetes noted with statins is at least partially explained by HMGCR inhibition. FUNDING: The funding sources are cited at the end of the paper.
Keywords: Aged; Body Mass Index; Body Weight; Cholesterol, HDL; Cholesterol, LDL; Diabetes Mellitus, Type 2; Female; Genetic Testing; Humans; Hydroxymethylglutaryl CoA Reductases; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Randomized Controlled Trials as Topic; Risk Factors

Impact of gait speed and instrumental activities of daily living on all-cause mortality in adults ≥65 years with heart failure. - Lo, Alexander X; Donnelly, John P; McGwin, Gerald; Bittner, Vera; Ahmed, Ali; Brown, Cynthia J (Am J Cardiol, 2015)
Mobility and function are important predictors of survival. However, their combined impact on mortality in adults ≥65 years with heart failure (HF) is not well understood. This study examined the role of gait speed and instrumental activities of daily living (IADL) in all-cause mortality in a cohort of 1,119 community-dwelling Cardiovascular Health Study participants ≥65 years with incident HF. Data on HF and mortality were collected through annual examinations or contact during the 10-year follow-up period. Slower gait speed (<0.8 m/s vs ≥0.8 m/s) and IADL impairment (≥1 vs 0 areas of dependence) were determined from baseline and follow-up assessments. A total of 740 (66%) of the 1,119 participants died during the follow-up period. Multivariate Cox proportional hazards models showed that impairments in either gait speed (hazard ratio 1.37, 95% confidence interval 1.10 to 1.70; p = 0.004) or IADL (hazard ratio 1.56, 95% confidence interval 1.29-1.89; p <0.001), measured within 1 year before the diagnosis of incident HF, were independently associated with mortality, adjusting for sociodemographic and clinical characteristics. The combined presence of slower gait speed and IADL impairment was associated with a greater risk of mortality and suggested an additive relation between gait speed and IADL. In conclusion, gait speed and IADL are important risk factors for mortality in adults ≥65 years with HF, but the combined impairments of both gait speed and IADL can have an especially important impact on mortality.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Early Diagnosis; Female; Follow-Up Studies; Gait; Geriatric Assessment; Heart Failure; Humans; Male; Odds Ratio; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Sensitivity and Specificity; Survival Analysis; United States; Walking

Intermediate and long-term risk of new-onset heart failure after hospitalization for pneumonia in elderly adults. - Corrales-Medina, Vicente F; Taljaard, Monica; Yende, Sachin; Kronmal, Richard; Dwivedi, Girish; Newman, Anne B; Elkind, Mitchell S V; Lyles, Mary F; Chirinos, Julio A (Am Heart J, 2015)
BACKGROUND: Pneumonia is associated with high risk of heart failure (HF) in the short term (30 days) postinfection. Whether this association persists beyond this period is unknown. METHODS: We studied 5,613 elderly (≥65 years) adults enrolled in the Cardiovascular Health Study between 1989 and 1994 at 4 US communities. Participants had no clinical diagnosis of HF at enrollment, and they were followed up through December 2010. Hospitalizations for pneumonia were identified using validated International Classification of Disease Ninth Revision codes. A centralized committee adjudicated new-onset HF events. Using Cox regression, we estimated adjusted hazard ratios (HRs) of new-onset HF at different time intervals after hospitalization for pneumonia. RESULTS: A total of 652 participants hospitalized for pneumonia during follow-up were still alive and free of clinical diagnosis of HF by day 30 posthospitalization. Relative to the time of their hospitalization, new-onset HF occurred in 22 cases between 31 and 90 days (HR 6.9, 95% CI 4.46-10.63, P < .001), 14 cases between 91 days and 6 months (HR 3.2, 95% CI 1.88-5.50, P < .001), 20 cases between 6 months and 1 year (HR 2.6, 95% CI 1.64-4.04, P < .001), 76 cases between 1 and 5 years (HR 1.7, 95% CI 1.30-2.12, P < .001), and 71 cases after 5 years (HR 2.0, 95% CI 1.56-2.58, P < .001). Results were robust to sensitivity analyses using stringent definitions of pneumonia and extreme assumptions for potential informative censoring. CONCLUSION: Hospitalization for pneumonia is associated with increased risk of new-onset HF in the intermediate and long term. Studies should characterize the mechanisms of this association in order to prevent HF in elderly pneumonia survivors.
Keywords: Aged; Disease Progression; Female; Follow-Up Studies; Forecasting; Heart Failure; Hospitalization; Humans; Incidence; Inpatients; Male; Patient Readmission; Pneumonia; Proportional Hazards Models; Retrospective Studies; Risk Assessment; Risk Factors; Time Factors

LV Mass as a Predictor of CVD Events in Older Adults With and Without Metabolic Syndrome and Diabetes. - Hoang, Khiet; Zhao, Yanglu; Gardin, Julius M; Carnethon, Mercedes; Mukamal, Ken; Yanez, David; Wong, Nathan D (JACC Cardiovasc Imaging, 2015)
OBJECTIVES: The purpose of this study was to examine the prognostic significance of left ventricular (LV) mass for cardiovascular disease (CVD) events in older adults with and without metabolic syndrome (MetS) and diabetes mellitus (DM). BACKGROUND: MetS and DM are associated with increased CVD risk, but it is unclear in these groups whether subclinical CVD as shown by increased LV mass improves risk prediction compared to standard risk factors in older individuals. METHODS: We studied 3,724 adults (mean 72.4 ± 5.4 years of age, 61.0% female, 4.4% African-American) from the Cardiovascular Health Study who had MetS but not DM or had DM alone or had neither condition. Cox regression was used to examine the association of LV mass, (alone and indexed by height and body surface area [BSA]) as determined by echocardiography, with CVD events, including coronary heart disease (CHD), stroke, heart failure (HF), and CVD death, as well as total mortality. We also assessed the added prediction, discriminative value, and net reclassification improvement (NRI) for clinical utility of LV mass compared to standard risk factors. RESULTS: Over a mean follow-up of 14.2 ± 6.3 years, 2,180 subjects experienced CVD events, including 986 CVD deaths. After adjustment for age, sex and standard risk factors, LV mass was positively associated with CVD events in those with MetS (hazard ratio [HR]: 1.4, p < 0.001) and without MetS (HR: 1.4, p < 0.001), but not DM (HR: 1.0, p = 0.62), with similar findings for LV mass indexed for height or BSA. Adding LV mass to standard risk factors moderately improved the prediction accuracy in the overall sample and MetS group from changes in C-statistics (p < 0.05). Categorical-free net reclassification improvement increased significantly by 17% to 19% in those with MetS. Findings were comparable for CHD, CVD mortality, and total mortality. CONCLUSIONS: LV mass is associated with increased CVD risk and provides modest added prediction and clinical utility compared to standard risk factors in older persons with and without MetS but not with DM.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Comorbidity; Diabetes Mellitus; Female; Heart Ventricles; Humans; Hypertrophy, Left Ventricular; Logistic Models; Male; Metabolic Syndrome X; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Meta-Analysis of Genome-Wide Association Studies Identifies Genetic Risk Factors for Stroke in African Americans. - Carty, Cara L; Keene, Keith L; Cheng, Yu-Ching; Meschia, James F; Chen, Wei-Min; Nalls, Mike; Bis, Joshua C; Kittner, Steven J; Rich, Stephen S; Tajuddin, Salman; Zonderman, Alan B; Evans, Michele K; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: The majority of genome-wide association studies (GWAS) of stroke have focused on European-ancestry populations; however, none has been conducted in African Americans, despite the disproportionately high burden of stroke in this population. The Consortium of Minority Population Genome-Wide Association Studies of Stroke (COMPASS) was established to identify stroke susceptibility loci in minority populations. METHODS: Using METAL, we conducted meta-analyses of GWAS in 14 746 African Americans (1365 ischemic and 1592 total stroke cases) from COMPASS, and tested genetic variants with P<10(-6) for validation in METASTROKE, a consortium of ischemic stroke genetic studies in European-ancestry populations. We also evaluated stroke loci previously identified in European-ancestry populations. RESULTS: The 15q21.3 locus linked with lipid levels and hypertension was associated with total stroke (rs4471613; P=3.9×10(-8)) in African Americans. Nominal associations (P<10(-6)) for total or ischemic stroke were observed for 18 variants in or near genes implicated in cell cycle/mRNA presplicing (PTPRG, CDC5L), platelet function (HPS4), blood-brain barrier permeability (CLDN17), immune response (ELTD1, WDFY4, and IL1F10-IL1RN), and histone modification (HDAC9). Two of these loci achieved nominal significance in METASTROKE: 5q35.2 (P=0.03), and 1p31.1 (P=0.018). Four of 7 previously reported ischemic stroke loci (PITX2, HDAC9, CDKN2A/CDKN2B, and ZFHX3) were nominally associated (P<0.05) with stroke in COMPASS. CONCLUSIONS: We identified a novel genetic variant associated with total stroke in African Americans and found that ischemic stroke loci identified in European-ancestry populations may also be relevant for African Americans. Our findings support investigation of diverse populations to identify and characterize genetic risk factors, and the importance of shared genetic risk across populations.
Keywords: African Americans; Case-Control Studies; Cohort Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors; Stroke

NT-proBNP and troponin T and risk of rapid kidney function decline and incident CKD in elderly adults. - Bansal, Nisha; Katz, Ronit; Dalrymple, Lorien; de Boer, Ian; DeFilippi, Christopher; Kestenbaum, Bryan; Park, Meyeon; Sarnak, Mark; Seliger, Stephen; Shlipak, Michael (Clin J Am Soc Nephrol, 2015)
BACKGROUND AND OBJECTIVES: Elevations in N-terminal pro-B-type natriuretic peptide and high-sensitivity troponin T are associated with poor cardiovascular outcomes. Whether elevations in these cardiac biomarkers are associated with decline in kidney function was evaluated. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: N-terminal pro-B-type natriuretic peptide and troponin T were measured at baseline in 3752 participants free of heart failure in the Cardiovascular Health Study. eGFR was determined from the Chronic Kidney Disease Epidemiology Collaboration equation using serum cystatin C. Rapid decline in kidney function was defined as decline in serum cystatin C eGFR≥30%, and incident CKD was defined as the onset of serum cystatin C eGFR<60 among those without CKD at baseline (n=2786). Cox regression models were used to examine the associations of each biomarker with kidney function decline adjusting for demographics, baseline serum cystatin C eGFR, diabetes, and other CKD risk factors. RESULTS: In total, 503 participants had rapid decline in serum cystatin C eGFR over a mean follow-up time of 6.41 (1.81) years, and 685 participants developed incident CKD over a mean follow-up time of 6.41 (1.74) years. Participants in the highest quartile of N-terminal pro-B-type natriuretic peptide (>237 pg/ml) had an 67% higher risk of rapid decline and 38% higher adjusted risk of incident CKD compared with participants in the lowest quartile (adjusted hazard ratio for serum cystatin C eGFR rapid decline, 1.67; 95% confidence interval, 1.25 to 2.23; hazard ratio for incident CKD, 1.38; 95% confidence interval, 1.08 to 1.76). Participants in the highest category of troponin T (>10.58 pg/ml) had 80% greater risk of rapid decline compared with participants in the lowest category (adjusted hazard ratio, 1.80; 95% confidence interval, 1.35 to 2.40). The association of troponin T with incident CKD was not statistically significant (hazard ratio, 1.17; 95% confidence interval, 0.92 to 1.50). CONCLUSIONS: Elevated N-terminal pro-B-type natriuretic peptide and troponin T are associated with rapid decline of kidney function and incident CKD. Additional studies are needed to evaluate the mechanisms that may explain this association.
Keywords: Age Factors; Aged; Aging; Biomarkers; Cystatin C; Disease Progression; Female; Glomerular Filtration Rate; Humans; Incidence; Kidney; Linear Models; Longitudinal Studies; Male; Natriuretic Peptide, Brain; Peptide Fragments; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Prospective Studies; Renal Insufficiency, Chronic; Risk Factors; Time Factors; Troponin T; United States; Up-Regulation

Older Adults, "Malignant" Left Ventricular Hypertrophy, and Associated Cardiac-Specific Biomarker Phenotypes to Identify the Differential Risk of New-Onset Reduced Versus Preserved Ejection Fraction Heart Failure: CHS (Cardiovascular Health Study). - Seliger, Stephen L; de Lemos, James; Neeland, Ian J; Christenson, Robert; Gottdiener, John; Drazner, Mark H; Berry, Jarett; Sorkin, John; DeFilippi, Christopher (JACC Heart Fail, 2015)
OBJECTIVES: This study hypothesized that biomarkers of subclinical myocardial injury (high-sensitivity cardiac troponin T [hs-cTnT]) and hemodynamic stress (N-terminal pro-B-type natriuretic peptide [NT-proBNP]) would differentiate heart failure (HF) risk among older adults with left ventricular hypertrophy (LVH). BACKGROUND: The natural history of LVH, an important risk factor for HF, is heterogeneous. METHODS: NT-proBNP and hs-cTnT were measured at baseline and after 2 to 3 years in older adults without prior HF or myocardial infarction in the CHS (Cardiovascular Health Study). LVH and left ventricular ejection fraction were determined by echocardiography. HF events were adjudicated over a median of 13.1 years and classified as preserved or reduced left ventricular ejection fraction (heart failure with preserved ejection fraction or heart failure with reduced ejection fraction [HFrEF]). Adjusted risk of HF by LVH and biomarker tertiles, and by LVH and longitudinal increase in each biomarker was estimated using Cox regression. RESULTS: Prevalence of LVH was 12.5% among 2,347 participants with complete measures. Adjusted risk of HF (N = 643 events) was approximately 3.8-fold higher among participants with LVH and in the highest biomarker tertile, compared with those with low biomarker levels without LVH (NT-proBNP, hazard ratio [HR]: 3.78; 95% confidence interval [CI]: 2.78 to 5.15 and hs-cTnT, HR: 3.86; 95% CI: 2.84 to 5.26). The adjusted risk of HFrEF was 7.8 times higher among those with the highest tertile of hs-cTnT and LVH (HR: 7.83; 95% CI: 4.43 to 13.83). Those with LVH and longitudinal increases in hs-cTnT or NT-proBNP were approximately 3-fold more likely to develop HF, primarily HFrEF, compared with those without LVH and with stable biomarkers. CONCLUSIONS: The combination of LVH with greater hs-cTnT or NT-proBNP levels, and their longitudinal increase, identifies older adults at highest risk for symptomatic HF, especially HFrEF. These biomarkers may characterize sub-phenotypes in the transition from LVH to HF and suggest modifiable targets for prevention.
Keywords: Aged; Biomarkers; Echocardiography; Female; Heart Failure; Humans; Hypertrophy, Left Ventricular; Male; Natriuretic Peptide, Brain; Peptide Fragments; Phenotype; Prospective Studies; Risk Factors; Troponin T

Plasma phospholipid very-long-chain saturated fatty acids and incident diabetes in older adults: the Cardiovascular Health Study. - Lemaitre, Rozenn N; Fretts, Amanda M; Sitlani, Colleen M; Biggs, Mary L; Mukamal, Kenneth; King, Irena B; Song, Xiaoling; Djoussé, Luc; Siscovick, David S; McKnight, Barbara; Sotoodehnia, Nona; Kizer, Jorge R; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Circulating saturated fatty acids (SFAs) are integrated biomarkers of diet and metabolism that may influence the pathogenesis of diabetes. In epidemiologic studies, circulating levels of palmitic acid (16:0) are associated with diabetes; however, very-long-chain SFAs (VLSFAs), with 20 or more carbons, differ from palmitic acid in their biological activities, and little is known of the association of circulating VLSFA with diabetes. OBJECTIVE: By using data from the Cardiovascular Health Study, we examined the associations of plasma phospholipid VLSFA levels measured at baseline with subsequent incident diabetes. DESIGN: A total of 3179 older adults, with a mean age of 75 y at study baseline (1992-1993), were followed through 2011. We used multiple proportional hazards regression to examine the associations of arachidic acid (20:0), behenic acid (22:0), and lignoceric acid (24:0) with diabetes. RESULTS: Baseline levels of each VLSFA were cross-sectionally associated with lower triglyceride levels and lower circulating palmitic acid. We identified 284 incident diabetes cases during follow-up. Compared with the lowest quartile, levels of arachidic acid in the highest quartile of the fatty acid distribution were associated with a 47% lower risk of diabetes (95% CI: 23%, 63%; P-trend: <0.001), after adjustment for demographics, lifestyle factors, and clinical conditions. In analogous comparisons, levels of behenic and lignoceric acid were similarly associated with 33% (95% CI: 6%, 53%; P-trend: 0.02) and 37% (95% CI: 11%, 55%; P-trend: 0.01) lower diabetes risk, respectively. Adjustment for triglycerides and palmitic acid attenuated the associations toward the null, and only the association of arachidic acid remained statistically significant (32% lower risk for fourth vs. first quartile; P-trend: 0.04). CONCLUSIONS: These results suggest that circulating VLSFAs are associated with a lower risk of diabetes, and these associations may be mediated by lower triglycerides and palmitic acid. The study highlights the need to distinguish the effects of different SFAs and to explore determinants of circulating VLSFAs. This trial was registered at clinicaltrials.gov as NCT00005133.
Keywords: Aged; Aged, 80 and over; Biomarkers; Cross-Sectional Studies; Diabetes Mellitus; Diet; Eicosanoic Acids; Fatty Acids; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Humans; Incidence; Male; Observational Studies as Topic; Palmitic Acid; Phospholipids; Prospective Studies; Risk Factors; Triglycerides

Potassium and glucose measures in older adults: the Cardiovascular Health Study. - Chatterjee, Ranee; Biggs, Mary L; de Boer, Ian H; Brancati, Frederick L; Svetkey, Laura P; Barzilay, Joshua; Djoussé, Luc; Ix, Joachim H; Kizer, Jorge R; Siscovick, David S; Mozaffarian, Dariush; Edelman, David; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: We sought to determine the impacts of serum and dietary potassium measures on glucose metabolism and diabetes risk in older adults. METHODS: Among participants of the Cardiovascular Health Study, a community-based cohort of older American adults, we examined a) cross-sectional associations between potassium and measures of insulin sensitivity and secretion estimated from oral glucose tolerance tests and b) longitudinal associations of serum and dietary potassium with diabetes risk. RESULTS: Among 4,754 participants aged ≥65 years at baseline, there were 445 cases of incident diabetes during a median follow-up of 12 years. In multivariate models, baseline serum and dietary potassium were both associated with lower insulin sensitivity and greater insulin secretion. Compared with those with a serum potassium ≥4.5 mEq/L, participants with a serum potassium <4.0mEq/L had an adjusted mean difference in Matsuda insulin sensitivity index of -0.18 (-0.39, 0.02). Compared with those in the highest quartile, participants in the lowest quartile of dietary potassium intake had a corresponding adjusted mean difference in Matsuda insulin sensitivity index of -0.61 (-0.94, -0.29). In multivariate models, neither serum nor dietary potassium intake was associated with long-term diabetes risk. CONCLUSIONS: Although we did not identify serum and dietary potassium as risk factors for incident diabetes in older adults, results from cross-sectional analyses suggest that both may be associated with increased insulin resistance. This relationship with insulin resistance needs to be confirmed, and its importance on diabetes risk, cardiovascular risk, and conditions specific to older adults should be determined as well.
Keywords: Aged; Blood Glucose; Cohort Studies; Cross-Sectional Studies; Diabetes Mellitus; Female; Humans; Insulin; Insulin Resistance; Longitudinal Studies; Male; Multivariate Analysis; Potassium; Potassium, Dietary; Risk Factors; United States

Prognostic Significance of High-Sensitivity Cardiac Troponin T Concentrations between the Limit of Blank and Limit of Detection in Community-Dwelling Adults: A Metaanalysis. - Parikh, Ravi H; Seliger, Stephen L; de Lemos, James; Nambi, Vijay; Christenson, Robert; Ayers, Colby; Sun, Wensheng; Gottdiener, John S; Kuller, Lewis H; Ballantyne, Christie; deFilippi, Christopher R (Clin Chem, 2015)
BACKGROUND: There is controversy regarding whether to report concentrations of high-sensitivity cardiac troponin T (hs-cTnT) to the limit of blank (LOB) (3 ng/L) or the limit of detection (LOD) (5 ng/L) of the assay in community-based cohorts. We hypothesized that hs-cTnT concentrations between the LOB and LOD would be associated with poorer cardiovascular outcomes compared to concentrations below the LOB. METHODS: hs-cTnT was analyzed in a total of 10 723 participants from the Cardiovascular Health Study (CHS), Atherosclerosis Risk in Communities (ARIC) study, and Dallas Heart Study (DHS). Participants were divided into 2 groups, those with hs-cTnT concentrations below the limit of blank (LOB) (<3 ng/L) and those with hs-cTnT between the LOB and limit of detection (LOD) (3-4.99 ng/L). Cross-sectional associations with traditional cardiovascular risk factors and cardiac structural measurements, and longitudinal associations with long-term cardiovascular outcomes of incident heart failure and cardiovascular death, were determined. RESULTS: Participants with hs-cTnT between the LOB and LOD for all 3 cohorts were older, more likely to be male, and have a higher burden of cardiovascular risk factors and structural pathology. A metaanalysis of the 3 cohorts showed participants with hs-cTnT between the LOB and LOD were at increased risk of new-onset heart failure (hazard ratio, 1.18; 95% CI, 1.02-1.38) and cardiovascular mortality (hazard ratio, 1.29; 95% CI, 1.06-1.57). CONCLUSIONS: hs-cTnT concentrations between the LOB and LOD (3-4.99 ng/L) are associated with a higher prevalence of traditional risk factors, more cardiac pathology, and worse outcomes than concentrations below the LOB (<3 ng/L).
Keywords: Aged; Atherosclerosis; Biomarkers; Cross-Sectional Studies; Female; Heart Failure; Humans; Independent Living; Limit of Detection; Longitudinal Studies; Male; Middle Aged; Myocardial Infarction; Prognosis; Risk Assessment; Risk Factors; Sex Factors; Troponin T

Prospective association of fatty acids in the de novo lipogenesis pathway with risk of type 2 diabetes: the Cardiovascular Health Study. - Ma, Wenjie; Wu, Jason H Y; Wang, Qianyi; Lemaitre, Rozenn N; Mukamal, Kenneth J; Djoussé, Luc; King, Irena B; Song, Xiaoling; Biggs, Mary L; Delaney, Joseph A; Kizer, Jorge R; Siscovick, David S; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Experimental evidence suggests that hepatic de novo lipogenesis (DNL) affects insulin homeostasis via synthesis of saturated fatty acids (SFAs) and monounsaturated fatty acids (MUFAs). Few prospective studies have used fatty acid biomarkers to assess associations with type 2 diabetes. OBJECTIVES: We investigated associations of major circulating SFAs [palmitic acid (16:0) and stearic acid (18:0)] and MUFA [oleic acid (18:1n-9)] in the DNL pathway with metabolic risk factors and incident diabetes in community-based older U.S. adults in the Cardiovascular Health Study. We secondarily assessed other DNL fatty acid biomarkers [myristic acid (14:0), palmitoleic acid (16:1n-7), 7-hexadecenoic acid (16:1n-9), and vaccenic acid (18:1n-7)] and estimated dietary SFAs and MUFAs. DESIGN: In 3004 participants free of diabetes, plasma phospholipid fatty acids were measured in 1992, and incident diabetes was identified by medication use and blood glucose. Usual diets were assessed by using repeated food-frequency questionnaires. Multivariable linear and Cox regression were used to assess associations with metabolic risk factors and incident diabetes, respectively. RESULTS: At baseline, circulating palmitic acid and stearic acid were positively associated with adiposity, triglycerides, inflammation biomarkers, and insulin resistance (P-trend < 0.01 each), whereas oleic acid showed generally beneficial associations (P-trend < 0.001 each). During 30,763 person-years, 297 incident diabetes cases occurred. With adjustment for demographics and lifestyle, palmitic acid (extreme-quintile HR: 1.89; 95% CI: 1.27, 2.83; P-trend = 0.001) and stearic acid (HR: 1.62; 95% CI: 1.09, 2.41; P-trend = 0.006) were associated with higher diabetes risk, whereas oleic acid was not significantly associated. In secondary analyses, vaccenic acid was inversely associated with diabetes (HR: 0.56; 95% CI: 0.38, 0.83; P-trend = 0.005). Other fatty acid biomarkers and estimated dietary SFAs or MUFAs were not significantly associated with incident diabetes. CONCLUSIONS: In this large prospective cohort, circulating palmitic acid and stearic acid were associated with higher diabetes risk, and vaccenic acid was associated with lower diabetes risk. These results indicate a need for additional investigation of biological mechanisms linking specific fatty acids in the DNL pathway to the pathogenesis of diabetes.
Keywords: Aged; Biomarkers; Cohort Studies; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Follow-Up Studies; Humans; Incidence; Lipogenesis; Liver; Male; Palmitic Acid; Phospholipids; Prevalence; Proportional Hazards Models; Risk Factors; Stearic Acids; United States; Up-Regulation

Prospective study of circulating factor XI and incident venous thromboembolism: The Longitudinal Investigation of Thromboembolism Etiology (LITE). - Folsom, Aaron R; Tang, Weihong; Roetker, Nicholas S; Heckbert, Susan R; Cushman, Mary; Pankow, James S (Am J Hematol, 2015)
Elevated plasma concentrations of coagulation factor XI may increase risk of venous thromboembolism (VTE), but prospective data are limited. We studied prospectively the associations of plasma factor XI and a key F11 genetic variant with incident VTE in whites and African-Americans. We measured factor XI in 16,299 participants, initially free of VTE, in two prospective population cohorts. We also measured the F11 single nucleotide polymorphism rs4241824, which a genome-wide association study had linked to factor XI concentration. During follow-up, we identified 606 VTEs. The age, race, sex, and study-adjusted hazard ratio of VTE increased across factor XI quintiles (P < 0.001 for trend), and the hazard ratio was 1.51 (95% CI 1.16, 1.97) for the highest versus lowest quintile overall, and was 1.42 (95% CI 1.03, 1.95) in whites and 1.72 (95% CI 1.08, 2.73) in African-Americans. In whites, the F11 variant was associated with both factor XI concentration and VTE incidence (1.15-fold greater incidence of VTE per risk allele). In African-Americans, these associations were absent. In conclusion, this cohort study documented that an elevated plasma factor XI concentration is a risk factor for VTE over extended follow-up, not only in whites but also in African-Americans. In whites, the association of the F11 genetic variant with VTE suggests a causal relation, but we did not observe this genetic relation in African-Americans.
Keywords: African Americans; Aged; Alleles; European Continental Ancestry Group; Factor XI; Female; Gene Expression; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk Factors; United States; Venous Thromboembolism

Race/Ethnic Differences in the Associations of the Framingham Risk Factors with Carotid IMT and Cardiovascular Events. - Gijsberts, Crystel M; Groenewegen, Karlijn A; Hoefer, Imo E; Eijkemans, Marinus J C; Asselbergs, Folkert W; Anderson, Todd J; Britton, Annie R; Dekker, Jacqueline M; Engström, Gunnar; Evans, Greg W; de Graaf, Jacqueline; Grobbee, Diederick E; et al. (PLoS One, 2015)
BACKGROUND: Clinical manifestations and outcomes of atherosclerotic disease differ between ethnic groups. In addition, the prevalence of risk factors is substantially different. Primary prevention programs are based on data derived from almost exclusively White people. We investigated how race/ethnic differences modify the associations of established risk factors with atherosclerosis and cardiovascular events. METHODS: We used data from an ongoing individual participant meta-analysis involving 17 population-based cohorts worldwide. We selected 60,211 participants without cardiovascular disease at baseline with available data on ethnicity (White, Black, Asian or Hispanic). We generated a multivariable linear regression model containing risk factors and ethnicity predicting mean common carotid intima-media thickness (CIMT) and a multivariable Cox regression model predicting myocardial infarction or stroke. For each risk factor we assessed how the association with the preclinical and clinical measures of cardiovascular atherosclerotic disease was affected by ethnicity. RESULTS: Ethnicity appeared to significantly modify the associations between risk factors and CIMT and cardiovascular events. The association between age and CIMT was weaker in Blacks and Hispanics. Systolic blood pressure associated more strongly with CIMT in Asians. HDL cholesterol and smoking associated less with CIMT in Blacks. Furthermore, the association of age and total cholesterol levels with the occurrence of cardiovascular events differed between Blacks and Whites. CONCLUSION: The magnitude of associations between risk factors and the presence of atherosclerotic disease differs between race/ethnic groups. These subtle, yet significant differences provide insight in the etiology of cardiovascular disease among race/ethnic groups. These insights aid the race/ethnic-specific implementation of primary prevention.
Keywords: Adult; Age Distribution; Aged; Carotid Artery Diseases; Carotid Intima-Media Thickness; Cholesterol, HDL; Cholesterol, LDL; Comorbidity; Continental Population Groups; Diabetes Mellitus; Dyslipidemias; Ethnic Groups; Female; Follow-Up Studies; Global Health; Humans; Hypertension; Incidence; Linear Models; Male; Middle Aged; Myocardial Infarction; Prevalence; Proportional Hazards Models; Risk Factors; Smoking; Stroke

Serial measures of cardiac troponin T levels by a highly sensitive assay and incident atrial fibrillation in a prospective cohort of ambulatory older adults. - Hussein, Ayman A; Bartz, Traci M; Gottdiener, John S; Sotoodehnia, Nona; Heckbert, Susan R; Lloyd-Jones, Donald; Kizer, Jorge R; Christenson, Robert; Wazni, Oussama; DeFilippi, Christopher (Heart Rhythm, 2015)
BACKGROUND: Various mechanisms in cardiac remodeling related to atrial fibrillation (AF) lead to elevated circulating cardiac troponin levels, but little is known about such elevations upstream to AF onset. OBJECTIVE: The purpose of this study was to study the association between circulating troponin levels as assessed by a highly sensitive cardiac troponin T (hs-cTnT) assay and incident atrial fibrillation (AF). METHODS: In a large prospective cohort of ambulatory older adults [the Cardiovascular Health Study (CHS)], hs-cTnT levels were measured in sera that were collected at enrollment from 4262 participants without AF (2871 with follow-up measurements). Incident AF was identified by electrocardiograms during CHS visits, hospital discharge diagnoses, and Medicare files, including outpatient and physician claims diagnoses. RESULTS: Over median follow-up of 11.2 years (interquartile range 6.1-16.5), 1363 participants (32.0%) developed AF. Higher baseline levels of hs-cTnT were associated with incident AF in covariate-adjusted analyses accounting for demographics, traditional risk factors, and incident heart failure in time-dependent analyzes (hazard ratio for 3rd tertile vs undetectable 1.75, 95% confidence interval 1.48-2.08). This association was statistically significant in analyses that additionally adjusted for biomarkers of inflammation and hemodynamic strain (hazard ratio for 3rd tertile vs undetectable 1.38, 95% confidence interval 1.16-1.65). Significant associations were also found when hs-cTnT levels were treated as a continuous variable and when examining change from baseline of hs-cTnT levels and incident AF. CONCLUSION: The findings show a significant association of circulating troponin levels in ambulatory older adults with incident AF beyond that of traditional risk factors, incident heart failure, and biomarkers of inflammation and hemodynamic strain.
Keywords: Aged; Atrial Fibrillation; Biomarkers; Electrocardiography; Female; Heart Failure; Humans; Incidence; Longitudinal Studies; Male; Outpatients; Risk Assessment; Risk Factors; Statistics as Topic; Troponin T; United States

Subclinical Hypothyroidism and the Risk of Stroke Events and Fatal Stroke: An Individual Participant Data Analysis. - Chaker, Layal; Baumgartner, Christine; den Elzen, Wendy P J; Ikram, M Arfan; Blum, Manuel R; Collet, Tinh-Hai; Bakker, Stephan J L; Dehghan, Abbas; Drechsler, Christiane; Luben, Robert N; Hofman, Albert; Portegies, Marileen L P; et al. (J Clin Endocrinol Metab, 2015)
OBJECTIVE: The objective was to determine the risk of stroke associated with subclinical hypothyroidism. DATA SOURCES AND STUDY SELECTION: Published prospective cohort studies were identified through a systematic search through November 2013 without restrictions in several databases. Unpublished studies were identified through the Thyroid Studies Collaboration. We collected individual participant data on thyroid function and stroke outcome. Euthyroidism was defined as TSH levels of 0.45-4.49 mIU/L, and subclinical hypothyroidism was defined as TSH levels of 4.5-19.9 mIU/L with normal T4 levels. DATA EXTRACTION AND SYNTHESIS: We collected individual participant data on 47 573 adults (3451 subclinical hypothyroidism) from 17 cohorts and followed up from 1972-2014 (489 192 person-years). Age- and sex-adjusted pooled hazard ratios (HRs) for participants with subclinical hypothyroidism compared to euthyroidism were 1.05 (95% confidence interval [CI], 0.91-1.21) for stroke events (combined fatal and nonfatal stroke) and 1.07 (95% CI, 0.80-1.42) for fatal stroke. Stratified by age, the HR for stroke events was 3.32 (95% CI, 1.25-8.80) for individuals aged 18-49 years. There was an increased risk of fatal stroke in the age groups 18-49 and 50-64 years, with a HR of 4.22 (95% CI, 1.08-16.55) and 2.86 (95% CI, 1.31-6.26), respectively (p trend 0.04). We found no increased risk for those 65-79 years old (HR, 1.00; 95% CI, 0.86-1.18) or ≥ 80 years old (HR, 1.31; 95% CI, 0.79-2.18). There was a pattern of increased risk of fatal stroke with higher TSH concentrations. CONCLUSIONS: Although no overall effect of subclinical hypothyroidism on stroke could be demonstrated, an increased risk in subjects younger than 65 years and those with higher TSH concentrations was observed.
Keywords: Adult; Asymptomatic Diseases; Female; Humans; Hypothyroidism; Incidence; Male; Risk Factors; Stroke; Thyrotropin

Subclinical thyroid dysfunction and fracture risk: a meta-analysis. - Blum, Manuel R; Bauer, Douglas C; Collet, Tinh-Hai; Fink, Howard A; Cappola, Anne R; da Costa, Bruno R; Wirth, Christina D; Peeters, Robin P; Asvold, Bjørn O; den Elzen, Wendy P J; Luben, Robert N; Imaizumi, Misa; et al. (JAMA, 2015)
IMPORTANCE: Associations between subclinical thyroid dysfunction and fractures are unclear and clinical trials are lacking. OBJECTIVE: To assess the association of subclinical thyroid dysfunction with hip, nonspine, spine, or any fractures. DATA SOURCES AND STUDY SELECTION: The databases of MEDLINE and EMBASE (inception to March 26, 2015) were searched without language restrictions for prospective cohort studies with thyroid function data and subsequent fractures. DATA EXTRACTION: Individual participant data were obtained from 13 prospective cohorts in the United States, Europe, Australia, and Japan. Levels of thyroid function were defined as euthyroidism (thyroid-stimulating hormone [TSH], 0.45-4.49 mIU/L), subclinical hyperthyroidism (TSH <0.45 mIU/L), and subclinical hypothyroidism (TSH ≥4.50-19.99 mIU/L) with normal thyroxine concentrations. MAIN OUTCOME AND MEASURES: The primary outcome was hip fracture. Any fractures, nonspine fractures, and clinical spine fractures were secondary outcomes. RESULTS: Among 70,298 participants, 4092 (5.8%) had subclinical hypothyroidism and 2219 (3.2%) had subclinical hyperthyroidism. During 762,401 person-years of follow-up, hip fracture occurred in 2975 participants (4.6%; 12 studies), any fracture in 2528 participants (9.0%; 8 studies), nonspine fracture in 2018 participants (8.4%; 8 studies), and spine fracture in 296 participants (1.3%; 6 studies). In age- and sex-adjusted analyses, the hazard ratio (HR) for subclinical hyperthyroidism vs euthyroidism was 1.36 for hip fracture (95% CI, 1.13-1.64; 146 events in 2082 participants vs 2534 in 56,471); for any fracture, HR was 1.28 (95% CI, 1.06-1.53; 121 events in 888 participants vs 2203 in 25,901); for nonspine fracture, HR was 1.16 (95% CI, 0.95-1.41; 107 events in 946 participants vs 1745 in 21,722); and for spine fracture, HR was 1.51 (95% CI, 0.93-2.45; 17 events in 732 participants vs 255 in 20,328). Lower TSH was associated with higher fracture rates: for TSH of less than 0.10 mIU/L, HR was 1.61 for hip fracture (95% CI, 1.21-2.15; 47 events in 510 participants); for any fracture, HR was 1.98 (95% CI, 1.41-2.78; 44 events in 212 participants); for nonspine fracture, HR was 1.61 (95% CI, 0.96-2.71; 32 events in 185 participants); and for spine fracture, HR was 3.57 (95% CI, 1.88-6.78; 8 events in 162 participants). Risks were similar after adjustment for other fracture risk factors. Endogenous subclinical hyperthyroidism (excluding thyroid medication users) was associated with HRs of 1.52 (95% CI, 1.19-1.93) for hip fracture, 1.42 (95% CI, 1.16-1.74) for any fracture, and 1.74 (95% CI, 1.01-2.99) for spine fracture. No association was found between subclinical hypothyroidism and fracture risk. CONCLUSIONS AND RELEVANCE: Subclinical hyperthyroidism was associated with an increased risk of hip and other fractures, particularly among those with TSH levels of less than 0.10 mIU/L and those with endogenous subclinical hyperthyroidism. Further study is needed to determine whether treating subclinical hyperthyroidism can prevent fractures.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Female; Fractures, Bone; Hip Fractures; Humans; Hyperthyroidism; Hypothyroidism; Male; Middle Aged; Risk Factors; Spinal Fractures; Thyrotropin; Young Adult

Variation in resting heart rate over 4 years and the risks of myocardial infarction and death among older adults. - Floyd, James S; Sitlani, Colleen M; Wiggins, Kerri L; Wallace, Erin; Suchy-Dicey, Astrid; Abbasi, Siddique A; Carnethon, Mercedes R; Siscovick, David S; Sotoodehnia, Nona; Heckbert, Susan R; McKnight, Barbara; Rice, Kenneth M; et al. (Heart, 2015)
OBJECTIVE: Resting heart rate (RHR) is an established predictor of myocardial infarction (MI) and mortality, but the relationship between variation in RHR over a period of several years and health outcomes is unclear. We evaluated the relationship between long-term variation in RHR and the risks of incident MI and mortality among older adults. METHODS: 1991 subjects without cardiovascular disease from the Cardiovascular Health Study were included. RHR was taken from resting ECGs at the first five annual study visits. RHR mean, trend and variation were estimated with linear regression. Subjects were followed for incident MI and death until December 2010. HRs for RHR mean, trend and variation are reported for differences of 10 bpm, 2 bpm/year and 2 bpm, respectively. RESULTS: 262 subjects had an incident MI event (13%) and 1326 died (67%) during 12 years of median follow-up. In primary analyses adjusted for cardiovascular risk factors, RHR mean (HR 1.12; 95% CI 1.05 to 1.20) and variation (HR 1.08; 95% CI 1.03 to 1.13) were associated with the risk of death while trend was not. None of the RHR variables were significantly associated with the risk of incident MI events; however, CIs were wide and the MI associations with RHR variables were not significantly different from the mortality associations. Adjusting for additional variables did not affect estimates, and there were no significant interactions with sex. CONCLUSIONS: Variation in RHR over a period of several years represents a potential predictor of long-term mortality among older persons free of cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Cause of Death; Electrocardiography; Female; Follow-Up Studies; Heart Rate; Humans; Incidence; Linear Models; Male; Myocardial Infarction; Outcome Assessment (Health Care); Prognosis; Proportional Hazards Models; Prospective Studies; Rest; Risk Factors; Time; Washington

Ventricular Ectopy as a Predictor of Heart Failure and Death. - Dukes, Jonathan W; Dewland, Thomas A; Vittinghoff, Eric; Mandyam, Mala C; Heckbert, Susan R; Siscovick, David S; Stein, Phyllis K; Psaty, Bruce M; Sotoodehnia, Nona; Gottdiener, John S; Marcus, Gregory M (J Am Coll Cardiol, 2015)
BACKGROUND: Studies of patients presenting for catheter ablation suggest that premature ventricular contractions (PVCs) are a modifiable risk factor for congestive heart failure (CHF). The relationship among PVC frequency, incident CHF, and mortality in the general population remains unknown. OBJECTIVES: The goal of this study was to determine whether PVC frequency ascertained using a 24-h Holter monitor is a predictor of a decrease in the left ventricular ejection fraction (LVEF), incident CHF, and death in a population-based cohort. METHODS: We studied 1,139 Cardiovascular Health Study (CHS) participants who were randomly assigned to 24-h ambulatory electrocardiography (Holter) monitoring and who had a normal LVEF and no history of CHF. PVC frequency was quantified using Holter studies, and LVEF was measured from baseline and 5-year echocardiograms. Participants were followed for incident CHF and death. RESULTS: Those in the upper quartile versus the lowest quartile of PVC frequency had a multivariable-adjusted, 3-fold greater odds of a 5-year decrease in LVEF (odds ratio [OR]: 3.10; 95% confidence interval [CI]: 1.42 to 6.77; p = 0.005), a 48% increased risk of incident CHF (HR: 1.48; 95% CI: 1.08 to 2.04; p = 0.02), and a 31% increased risk of death (HR: 1.31; 95% CI: 1.06 to 1.63; p = 0.01) during a median follow-up of >13 years. Similar statistically significant results were observed for PVCs analyzed as a continuous variable. The specificity for the 15-year risk of CHF exceeded 90% when PVCs included at least 0.7% of ventricular beats. The population-level risk for incident CHF attributed to PVCs was 8.1% (95% CI: 1.2% to 14.9%). CONCLUSIONS: In a population-based sample, a higher frequency of PVCs was associated with a decrease in LVEF, an increase in incident CHF, and increased mortality. Because of the capacity to prevent PVCs through medical or ablation therapy, PVCs may represent a modifiable risk factor for CHF and death.
Keywords: Aged; Catheter Ablation; Echocardiography; Electrocardiography, Ambulatory; Female; Forecasting; Heart Failure; Humans; Male; Risk Factors; Stroke Volume; Ventricular Premature Complexes

APOL1 Genotype, Kidney and Cardiovascular Disease, and Death in Older Adults. - Mukamal, Kenneth J; Tremaglio, Joseph; Friedman, David J; Ix, Joachim H; Kuller, Lewis H; Tracy, Russell P; Pollak, Martin R (Arterioscler Thromb Vasc Biol, 2016)
OBJECTIVE: We sought to evaluate the cardiovascular impact of coding variants in the apolipoprotein L1 gene APOL1 that protect against trypanosome infection but have been associated with kidney disease among African Americans. APPROACH AND RESULTS: As part of the Cardiovascular Health Study, a population-based cohort of Americans aged ≥65 years, we genotyped APOL1 polymorphisms rs73885319 and rs71785153 and examined kidney function, subclinical atherosclerosis, and incident cardiovascular disease and death over 13 years of follow-up among 91 African Americans with 2 risk alleles, 707 other African Americans, and 4964 white participants. The high-risk genotype with 2 risk alleles was associated with 2-fold higher levels of albuminuria and lower ankle-brachial indices but similar carotid intima-media thickness among African Americans. Median survival among high-risk African Americans was 9.9 years (95% confidence interval [CI], 8.7-11.9), compared with 13.6 years (95% CI, 12.5-14.3) among other African Americans and 13.3 years (95% CI, 13.0-13.6) among whites (P=0.03). The high-risk genotype was also associated with increased risk for incident myocardial infarction (adjusted hazard ratio 1.8; 95% CI, 1.1-3.0) and mortality (adjusted hazard ratio 1.3; 95% CI 1.0-1.7). Albuminuria and risk for myocardial infarction and mortality were nearly identical between African Americans with 0 to 1 risk alleles and whites. CONCLUSIONS: APOL1 genotype is associated with albuminuria, subclinical atherosclerosis, incident myocardial infarction, and mortality in older African Americans. African Americans without 2 risk alleles do not differ significantly in risk of myocardial infarction or mortality from whites. APOL1 trypanolytic variants may account for a substantial proportion of the excess risk of chronic disease in African Americans.
Keywords: African Americans; Age Factors; Aged; Albuminuria; Apolipoproteins; Atherosclerosis; Cardiovascular Diseases; Cause of Death; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Health Status Disparities; Heterozygote; Homozygote; Humans; Incidence; Kaplan-Meier Estimate; Kidney Diseases; Lipoproteins, HDL; Male; Myocardial Infarction; Phenotype; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Associations of insulin resistance, inflammation and liver synthetic function with very low-density lipoprotein: The Cardiovascular Health Study. - Jiang, Z Gordon; de Boer, Ian H; Mackey, Rachel H; Jensen, Majken K; Lai, Michelle; Robson, Simon C; Tracy, Russell; Kuller, Lewis H; Mukamal, Kenneth J (Metabolism, 2016)
INTRODUCTION: Production of very low-density lipoprotein (VLDL) is increased in states of metabolic syndrome, leading to hypertriglyceridemia. However, metabolic syndrome is often associated with non-alcoholic fatty liver disease, which leads to liver fibrosis and inflammation that may decrease VLDL production. In this study, we aim to determine the interactive impact on VLDL profiles from insulin resistance, impairment in liver synthetic function and inflammation. METHODS: We examined cross-sectional associations of insulin sensitivity, inflammation, and liver synthetic function with VLDL particle (VLDL-P) concentration and size among 1,850 older adults in the Cardiovascular Health Study. RESULTS: Indices for high insulin sensitivity and low liver synthetic function were associated with lower concentrations of VLDL-P. In addition, insulin resistance preferentially increased concentration of large VLDL and was associated with mean VLDL size. Indices for inflammation however demonstrated a nonlinear relationship with both VLDL-P concentration and VLDL size. When mutually adjusted, one standard deviation (SD) increment in Matsuda index and C-reactive protein (CRP) were associated with 4.9 nmol/L (-8.2 to -1.5, p=0.005) and 6.3 nmol/L (-11.0 to -1.6, p=0.009) lower VLDL-P concentration respectively. In contrast, one-SD increment in factor VII, a marker for liver synthetic function, was associated with 16.9 nmol/L (12.6-21.2, p<0.001) higher VLDL-P concentration. Furthermore, a one-SD increment in the Matsuda index was associated with 1.1 nm (-2.0 to -0.3, p=0.006) smaller mean VLDL size, whereas CRP and factor VII were not associated with VLDL size. CONCLUSION: Insulin sensitivity, inflammation and markers for liver synthetic function differentially impact VLDL-P concentration and VLDL size. These results underscore the complex effects of insulin resistance and its complications on VLDL production.
Keywords: Aged; Aged, 80 and over; C-Reactive Protein; Cross-Sectional Studies; Factor VII; Female; Humans; Inflammation; Insulin Resistance; Lipoproteins, VLDL; Liver; Liver Function Tests; Male; Risk Factors; Socioeconomic Factors

Associations of Plasma Phospholipid SFAs with Total and Cause-Specific Mortality in Older Adults Differ According to SFA Chain Length. - Fretts, Amanda M; Mozaffarian, Dariush; Siscovick, David S; King, Irena B; McKnight, Barbara; Psaty, Bruce M; Rimm, Eric B; Sitlani, Colleen; Sacks, Frank M; Song, Xiaoling; Sotoodehnia, Nona; Spiegelman, Donna; et al. (J Nutr, 2016)
BACKGROUND: Not much is known about the relations of circulating saturated fatty acids (SFAs), which are influenced by both metabolic and dietary determinants, with total and cause-specific mortality. OBJECTIVE: We examined the associations of plasma phospholipid SFAs with total and cause-specific mortality among 3941 older adults from the Cardiovascular Health Study, a population-based prospective study of adults aged ≥65 y who were followed from 1992 through 2011. METHODS: The relations of total and cause-specific mortality with plasma phospholipid palmitic acid (16:0), stearic acid (18:0), arachidic acid (20:0), behenic acid (22:0), and lignoceric acid (24:0) were assessed using Cox proportional hazards models. RESULTS: During 45,450 person-years of follow-up, 3134 deaths occurred. Higher concentrations of the plasma phospholipid SFAs 18:0, 22:0, and 24:0 were associated with a lower risk of total mortality [multivariable-adjusted HRs (95% CIs)] for the top compared with the bottom quintile: 0.85 (0.75, 0.95) for 18:0; 0.85 (0.75, 0.95) for 22:0; and 0.80 (0.71, 0.90) for 24:0. In contrast, plasma 16:0 concentrations in the highest quintile were associated with a higher risk of total mortality compared with concentrations in the lowest quintile [1.25 (1.11, 1.41)]. We also found no association of plasma phospholipid 20:0 with total mortality. CONCLUSIONS: These findings suggest that the associations of plasma phospholipid SFAs with the risk of death differ according to SFA chain length and support future studies to better characterize the determinants of circulating SFAs and to explore the mechanisms underlying these relations.
Keywords: Aged; Aged, 80 and over; Cause of Death; Diet; Dietary Fats; Eicosanoic Acids; Fatty Acids; Female; Humans; Male; Mortality; Palmitic Acid; Phospholipids; Prospective Studies; Risk Factors; Stearic Acids

Fibroblast Growth Factor-23 and Frailty in Elderly Community-Dwelling Individuals: The Cardiovascular Health Study. - Beben, Tomasz; Ix, Joachim H; Shlipak, Michael G; Sarnak, Mark J; Fried, Linda F; Hoofnagle, Andrew N; Chonchol, Michel; Kestenbaum, Bryan R; de Boer, Ian H; Rifkin, Dena E (J Am Geriatr Soc, 2016)
OBJECTIVES: To evaluate whether fibroblast growth factor 23 (FGF-23) is related to frailty and to characterize the nature of their joint association with mortality. DESIGN: Cross-sectional analysis for frailty and longitudinal cohort analysis for mortality. SETTING: Cardiovascular Health Study. PARTICIPANTS: Community-dwelling individuals (N = 2,977; mean age 77.9 ± 4.7, 40% male, 83% white). MEASUREMENTS: The predictor was serum FGF-23 concentration (C-terminal enzyme-linked immunosorbent assay), and the outcomes were frailty status (determined according to frailty phenotype criteria of weight loss, weakness, exhaustion, slowness, and low physical activity) and mortality. Multinomial logistic regression was used to assess the cross-sectional association between FGF-23 and frailty and prefrailty, adjusting for demographic characteristics, cardiovascular disease and risk factors, and kidney markers. Proportional hazards Cox proportional hazards regression was used to assess the association between FGF-23, frailty, and all-cause mortality. RESULTS: Mean estimated glomerular filtration rate (eGFR) was 64 ± 17 mL/min per 1.73 m(2) . Median FGF-23 was 70.3 RU/mL (interquartile range 53.4-99.2); 52% were prefrail, and 13% were frail. After multivariate adjustment, each doubling in FGF-23 concentration was associated with 38% (95% confidence interval (CI) = 17-62%) higher odds of frailty than of nonfrailty and 16% (95% CI = 3-30%) higher odds of prefrailty. FGF-23 (hazard ratio (HR) = 1.16, 95% CI = 1.10-1.23) and frailty (HR = 1.82, 95% CI = 1.57-2.12) were independently associated with mortality, but neither association was meaningfully attenuated when adjusted for the other. CONCLUSION: In a large cohort of older adults, higher FGF-23 was independently associated with prevalent frailty and prefrailty. FGF-23 and frailty were independent and additive risk factors for mortality. FGF-23 may be a marker for functional outcomes.
Keywords: Aged; Anthropometry; Biomarkers; Cardiovascular Diseases; Cross-Sectional Studies; Enzyme-Linked Immunosorbent Assay; Female; Fibroblast Growth Factors; Frail Elderly; Glomerular Filtration Rate; Humans; Independent Living; Longitudinal Studies; Male; Phenotype; Risk Factors; Surveys and Questionnaires

Gait Speed Predicts Incident Disability: A Pooled Analysis. - Perera, Subashan; Patel, Kushang V; Rosano, Caterina; Rubin, Susan M; Satterfield, Suzanne; Harris, Tamara; Ensrud, Kristine; Orwoll, Eric; Lee, Christine G; Chandler, Julie M; Newman, Anne B; Cauley, Jane A; et al. (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND: Functional independence with aging is an important goal for individuals and society. Simple prognostic indicators can inform health promotion and care planning, but evidence is limited by heterogeneity in measures of function. METHODS: We performed a pooled analysis of data from seven studies of 27,220 community-dwelling older adults aged 65 or older with baseline gait speed, followed for disability and mortality. Outcomes were incident inability or dependence on another person in bathing or dressing; and difficulty walking ¼ - ½ mile or climbing 10 steps within 3 years. RESULTS: Participants with faster baseline gait had lower rates of incident disability. In subgroups (defined by 0.2 m/s-wide intervals from <0.4 to ≥ 1.4 m/s) with increasingly greater gait speed, 3-year rates of bathing or dressing dependence trended from 10% to 1% in men, and from 15% to 1% in women, while mobility difficulty trended from 47% to 4% in men and 40% to 6% in women. The age-adjusted relative risk ratio per 0.1 m/s greater speed for bathing or dressing dependence in men was 0.68 (0.57-0.81) and in women: 0.74 (0.66-0.82); for mobility difficulty, men: 0.75 (0.68-0.82), women: 0.73 (0.67-0.80). Results were similar for combined disability and mortality. Effects were largely consistent across subgroups based on age, gender, race, body mass index, prior hospitalization, and selected chronic conditions. In the presence of multiple other risk factors for disability, gait speed significantly increased the area under the receiver operator characteristic curve. CONCLUSION: In older adults, gait speed predicts 3 year incidence of bathing or dressing dependence, mobility difficulty, and a composite outcome of disability and mortality.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cohort Studies; Disability Evaluation; Disabled Persons; Female; Gait; Geriatric Assessment; Humans; Independent Living; Male; Mobility Limitation; Predictive Value of Tests; Prognosis; Psychomotor Performance; Risk Assessment; Risk Factors; ROC Curve; Survival Analysis; United States

Lipoprotein-Associated Phospholipase A2 and Incident Peripheral Arterial Disease in Older Adults: The Cardiovascular Health Study. - Garg, Parveen K; Arnold, Alice M; Hinckley Stukovsky, Karen D; Koro, Carol; Jenny, Nancy S; Mukamal, Kenneth J; Criqui, Michael H; Furberg, Curt D; Newman, Anne B; Cushman, Mary (Arterioscler Thromb Vasc Biol, 2016)
OBJECTIVE: Although prior studies report a relationship between elevated lipoprotein-associated phospholipase A2 (Lp-PLA2) and incident cardiovascular disease, the prospective association of Lp-PLA2 with incident peripheral arterial disease (PAD) has not been studied. We investigated the association between Lp-PLA2 mass and activity and the risk of developing clinical PAD and low ankle-brachial index (ABI). APPROACH AND RESULTS: Among Cardiovascular Health Study participants, a population-based cohort of 5888 adults aged ≥65 years enrolled in 1989 to 1990, Lp-PLA2 mass and activity were measured in 4537 individuals without baseline PAD. Clinical PAD, defined as leg artery revascularization or diagnosed claudication, was ascertained through 2011. Incident low ABI, defined as ABI <0.9 and decline of ≥0.15, was assessed among 3537 individuals who had an ABI >0.9 at baseline and a second ABI measurement 3 or 6 years later. Analyses were adjusted for demographics, cholesterol, smoking, comorbidities, and C-reactive protein. Each standard deviation increment in Lp-PLA2 mass (117 ng/mL) was associated with a higher risk of developing clinical PAD (hazard ratio 1.28; 95% confidence interval 1.13, 1.45) and incident low ABI (odds ratio 1.16; 95% confidence interval 1.00, 1.33). Results per standard deviation increment in Lp-PLA2 activity (13 nmol/min per mL) were similar for clinical PAD (hazard ratio 1.24; 95% confidence interval 1.07, 1.44) and low ABI (odds ratio 1.28; 95% confidence interval 1.09, 1.50). CONCLUSIONS: Higher Lp-PLA2 mass and activity were associated with development of both incident clinical PAD and low ABI. Future studies are needed to determine whether pharmacological inhibition of Lp-PLA2 reduces the incidence of PAD.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Age Factors; Aged; Aging; Ankle Brachial Index; Biomarkers; Chi-Square Distribution; Female; Humans; Incidence; Inflammation Mediators; Logistic Models; Male; Odds Ratio; Peripheral Arterial Disease; Prognosis; Proportional Hazards Models; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation

Relations of Postload and Fasting Glucose With Incident Cardiovascular Disease and Mortality Late in Life: The Cardiovascular Health Study. - Brutsaert, Erika F; Shitole, Sanyog; Biggs, Mary Lou; Mukamal, Kenneth J; deBoer, Ian H; Thacker, Evan L; Barzilay, Joshua I; Djoussé, Luc; Ix, Joachim H; Smith, Nicholas L; Kaplan, Robert C; Siscovick, David S; et al. (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND: Older adults have a high prevalence of postload hyperglycemia. Postload glucose has shown more robust associations with cardiovascular disease (CVD) and death than fasting glucose, but data in the oldest old are sparse. METHODS: Fasting and 2-hour postload glucose were measured in community-dwelling older adults, mean age 78, at the 1996-1997 follow-up visit of the Cardiovascular Health Study. We evaluated their associations with atherosclerotic CVD (ASCVD) and mortality using standard Cox regression and competing-risks analyses and assessed improvement in prediction-model discrimination with the c-statistic. RESULTS: Among 2,394 participants without treated diabetes and available data on glycemic measures, there were 579 ASCVD events and 1,698 deaths during median follow-up of 11.2 years. In fully adjusted models, both fasting and 2-hour glucose were associated with ASCVD (HR per SD, 1.13 [1.03-1.25] and 1.17 [1.07-1.28], respectively) and all-cause mortality (HR 1.12 [1.07-1.18] and 1.14 [1.08-1.20]). After mutual adjustment, however, the associations for fasting glucose with both outcomes were abolished, but those for postload glucose were largely unchanged. Consistent findings were observed for ASCVD in competing-risks models. CONCLUSION: In adults surviving to advanced old age, postload glucose was associated with ASCVD and mortality independently of fasting glucose, but fasting glucose was not associated with these outcomes independently of postload glucose. These findings affirm the robust association of postload glucose with ASCVD and death late in life.
Keywords: Aged; Aging; Blood Glucose; Cardiovascular Diseases; Fasting; Female; Follow-Up Studies; Glucose; Glucose Tolerance Test; Health Surveys; Humans; Incidence; Male; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Survival Rate; United States

Risk of dementia and death in the long-term follow-up of the Pittsburgh Cardiovascular Health Study-Cognition Study. - Kuller, Lewis H; Lopez, Oscar L; Becker, James T; Chang, Yuefang; Newman, Anne B (Alzheimers Dement, 2016)
INTRODUCTION: Increasing life expectancy has resulted in a larger population of older individuals at risk of dementia. METHODS: The Cardiovascular Health Study-Cognition Study followed 532 participants from 1998-99 (mean age 79) to 2013 (mean age 93) for death and dementia. RESULTS: Risk of death was determined by extent of coronary artery calcium, high-sensitivity cardiac troponin, brain natriuretic peptide, and white matter grade. Significant predictors of dementia were age, apolipoprotein-E4, vocabulary raw score, hippocampal volume, ventricular size, cognitive performance, and number of blocks walked. By 2013, 160 of 532 were alive, including 19 cognitively normal. Those with normal cognition had higher grade education, better cognition test scores, greater hippocampal volume, faster gait speed, and number of blocks walked as compared with survivors who were demented. DISCUSSION: Few survived free of dementia and disability. Prevention and delay of cognitive decline for this older population is an imperative.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Apolipoprotein E4; Brain; Cardiovascular Diseases; Cognition; Dementia; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Pennsylvania; Risk Factors; Walking

Spousal Associations Between Frailty and Depressive Symptoms: Longitudinal Findings from the Cardiovascular Health Study. - Monin, Joan; Doyle, Margaret; Levy, Becca; Schulz, Richard; Fried, Terri; Kershaw, Trace (J Am Geriatr Soc, 2016)
OBJECTIVES: To determine whether older adult spouses' frailty states and depressive symptoms are interrelated over time. DESIGN: Longitudinal, dyadic path analysis using the Actor-Partner Interdependence Model. SETTING: Data were from baseline (1989-90), Wave 3 (1992-93), and Wave 7 (1996-97), all waves in which frailty and depressive symptoms were measured, of the Cardiovascular Health Study (CHS), a multisite, longitudinal, observational study of risk factors for cardiovascular disease in adults aged 65 and older. PARTICIPANTS: Spouses in 1,260 community-dwelling married couples. MEASUREMENTS: Frailty was measured using the CHS criteria, categorized as nonfrail, prefrail, or frail. Depressive symptoms were measured using the 10-item Center for Epidemiologic Studies Depression Scale. RESULTS: Within individuals (actor effects), greater frailty predicted greater subsequent depressive symptoms, and greater depressive symptoms predicted greater subsequent frailty. Between spouses (partner effects), an individual's greater frailty predicted the spouse's greater frailty, and an individual's greater depressive symptoms predicted the spouse's greater depressive symptoms. CONCLUSION: Frailty and depressive symptoms are interrelated in older adult spouses. For older couples, interventions to prevent or treat frailty and depression that focus on couples may be more effective than those that focus on individuals.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Depression; Female; Frail Elderly; Humans; Longitudinal Studies; Male; Risk Factors; Spouses; United States

Study of Cardiovascular Health Outcomes in the Era of Claims Data: The Cardiovascular Health Study. - Psaty, Bruce M; Delaney, Joseph A; Arnold, Alice M; Curtis, Lesley H; Fitzpatrick, Annette L; Heckbert, Susan R; McKnight, Barbara; Ives, Diane; Gottdiener, John S; Kuller, Lewis H; Longstreth, W T (Circulation, 2016)
BACKGROUND: Increasingly, the diagnostic codes from administrative claims data are being used as clinical outcomes. METHODS AND RESULTS: Data from the Cardiovascular Health Study (CHS) were used to compare event rates and risk factor associations between adjudicated hospitalized cardiovascular events and claims-based methods of defining events. The outcomes of myocardial infarction (MI), stroke, and heart failure were defined in 3 ways: the CHS adjudicated event (CHS[adj]), selected International Classification of Diseases, Ninth Edition diagnostic codes only in the primary position for Medicare claims data from the Center for Medicare & Medicaid Services (CMS[1st]), and the same selected diagnostic codes in any position (CMS[any]). Conventional claims-based methods of defining events had high positive predictive values but low sensitivities. For instance, the positive predictive value of International Classification of Diseases, Ninth Edition code 410.x1 for a new acute MI in the first position was 90.6%, but this code identified only 53.8% of incident MIs. The observed event rates for CMS[1st] were low. For MI, the incidence was 14.9 events per 1000 person-years for CHS[adj] MI, 8.6 for CMS[1st] MI, and 12.2 for CMS[any] MI. In general, cardiovascular disease risk factor associations were similar across the 3 methods of defining events. Indeed, traditional cardiovascular disease risk factors were also associated with all first hospitalizations not resulting from an MI. CONCLUSIONS: The use of diagnostic codes from claims data as clinical events, especially when restricted to primary diagnoses, leads to an underestimation of event rates. Additionally, claims-based events data represent a composite end point that includes the outcome of interest and selected (misclassified) nonevent hospitalizations.
Keywords: Blood Glucose; Cardiovascular Diseases; Female; Follow-Up Studies; Health Surveys; Hospitalization; Hospitals, Veterans; Humans; Insurance Claim Review; International Classification of Diseases; Lipids; Male; Managed Care Programs; Medicare; Risk Factors; Sampling Studies; Treatment Outcome; United States

Subclinical Cardiovascular Disease and Death, Dementia, and Coronary Heart Disease in Patients 80+ Years. - Kuller, Lewis H; Lopez, Oscar L; Mackey, Rachel H; Rosano, Caterina; Edmundowicz, Daniel; Becker, James T; Newman, Anne B (J Am Coll Cardiol, 2016)
BACKGROUND: The successful prevention and treatment of coronary heart disease (CHD) and stroke has resulted in a substantial increase in longevity, with subsequent growth in the population of older people at risk for dementia. OBJECTIVES: The authors evaluated the relationship of coronary and other peripheral atherosclerosis to risk of death, dementia, and CHD in the very elderly. Because the extent of vascular disease differs substantially between men and women, sex- and race-specific analyses were included, with a specific focus on women with low coronary artery calcium (CAC) Agatston scores. METHODS: We evaluated the relationship between measures of subclinical cardiovascular disease (CAC, carotid intimal medial thickness, stenosis, and ankle brachial index) and risk of dementia, CHD, and total mortality in 532 participants of the Cardiovascular Health Study-Cognition Study from 1998/1999 (mean age, 80 years) to 2012/2013 (mean age, 93 years). RESULTS: Thirty-six percent of participants had CAC scores >400. Women and African-Americans had lower CAC scores. Few men had low CAC scores. CAC score and number of coronary calcifications were directly related to age-adjusted total mortality and CHD. The age-specific incidence of dementia was higher than for CHD. Only about 25% of deaths were caused by CHD and 16% by dementia. Approximately 64% of those who died had a prior diagnosis of dementia. White women with low CAC scores had a significantly decreased incidence of dementia. CONCLUSIONS: In subjects 80+ years of age, there is a greater incidence of dementia than of CHD. CAC, as a marker of atherosclerosis, is a determinant of mortality, and risk of CHD and myocardial infarction. White women with low CAC scores had a significantly decreased risk of dementia. A very important unanswered question, especially in the very elderly, is whether prevention of atherosclerosis and its complications is associated with less Alzheimer disease pathology and dementia. (Cardiovascular Health Study [CHS]; NCT00005133).
Keywords: Age Factors; Aged, 80 and over; Cause of Death; Coronary Artery Disease; Dementia; Female; Humans; Incidence; Male; Pennsylvania; Retrospective Studies; Risk Factors; Survival Rate

Association of Diabetic Macular Edema and Proliferative Diabetic Retinopathy With Cardiovascular Disease: A Systematic Review and Meta-analysis. - Xie, Jing; Ikram, M Kamran; Cotch, Mary Frances; Klein, Barbara; Varma, Rohit; Shaw, Jonathan E; Klein, Ronald; Mitchell, Paul; Lamoureux, Ecosse L; Wong, Tien Yin (JAMA Ophthalmol, 2017)
Importance: Previous studies on the relationship between diabetic retinopathy (DR) and cardiovascular disease (CVD) focused on the early stages of DR. Understanding whether patients with type 2 diabetes and severe stages of DR (diabetic macular edema [DME] and proliferative diabetic retinopathy [PDR]) have a higher risk of CVD will allow physicians to more effectively counsel patients. Objective: To examine the association of severe stages of DR (DME and PDR) with incident CVD in patients with type 2 diabetes. Data Sources: English-language publications were reviewed for articles evaluating the relationship of DR and CVD in MEDLINE, EMBASE, Current Contents, and the Cochrane Library from inception (January 1, 1950) to December 31, 2014, using the search terms diabetic retinopathy OR macular edema AND stroke OR cerebrovascular disease OR coronary artery disease OR heart failure OR myocardial infarction OR angina pectoris OR acute coronary syndrome OR coronary artery disease OR cardiomyopathy. Study Selection: Among 656 studies screened for eligibility, 7604 individuals were included from 8 prospective population-based studies with data on photographic-based DR grading, follow-up visits, and well-defined incident CVD end point. Data Extraction and Synthesis: Two independent reviewers conducted a systematic search of the 4 databases, and a single pooled database was developed. Incidence rate ratios (IRRs) were estimated for patients with DME, PDR, and vision-threatening DR, compared with persons without these conditions, by using individual participant data followed by a standard inverse-variance meta-analysis (2-step analysis). The review and analyses were performed from January 1, 2009, to January 1, 2017. Main Outcome and Measures: Incident CVD, including coronary heart disease, stroke, or death from cardiovascular causes. Results: Among 7604 patients with type 2 diabetes, the prevalence of DME was 4.6% and PDR, 7.4%. After a mean follow-up of 5.9 years (range, 3.2-10.1 years), 1203 incident CVD events, including 916 coronary heart disease cases, were reported. Persons with DME or PDR were more likely to have incident CVD (IRR, 1.39; 95% CI, 1.16-1.67) and fatal CVD (IRR, 2.33; 95% CI, 1.49-3.67) compared with those without DME or PDR. Conclusions and Relevance: Patients with type 2 diabetes and DME or PDR have an increased risk of incident CVD, which suggests that these persons should be followed up more closely to prevent CVD.
Keywords: Cardiovascular Diseases; Diabetic Retinopathy; Global Health; Humans; Incidence; Macular Edema; Risk Factors

Blood Pressure and Heart Rate Measures Associated With Increased Risk of Covert Brain Infarction and Worsening Leukoaraiosis in Older Adults. - Leung, Lester Y; Bartz, Traci M; Rice, Kenneth; Floyd, James; Psaty, Bruce; Gutierrez, Jose; Longstreth, W T; Mukamal, Kenneth J (Arterioscler Thromb Vasc Biol, 2017)
OBJECTIVE: In people without previous stroke, covert findings on serial magnetic resonance imaging (MRI) of incident brain infarcts and worsening leukoaraiosis are associated with increased risk for ischemic stroke and dementia. We evaluated whether various measures of blood pressure (BP) and heart rate are associated with these MRI findings. APPROACH AND RESULTS: In the CHS (Cardiovascular Health Study), a longitudinal cohort study of older adults, we used relative risk regression to assess the associations of mean, variability, and trend in systolic BP, diastolic BP, and heart rate measured at 4 annual clinic visits between 2 brain MRIs with incident covert brain infarction and worsening white matter grade (using a 10-point scale to characterize leukoaraiosis). We included participants who had both brain MRIs, no stroke before the follow-up MRI, and no change in antihypertensive medication status during follow-up. Among 878 eligible participants, incident covert brain infarction occurred in 15% and worsening white matter grade in 27%. Mean systolic BP was associated with increased risk for incident covert brain infarction (relative risk per 10 mm Hg, 1.28; 95% confidence interval, 1.12-1.47), and mean diastolic BP was associated with increased risk for worsening white matter grade (relative risk per 10 mm Hg, 1.45; 95% confidence interval, 1.24-1.69). These findings persisted in secondary and sensitivity analyses. CONCLUSIONS: Elevated mean systolic BP is associated with increased risk for covert brain infarction, and elevated mean diastolic BP is associated with increased risk for worsening leukoaraiosis. These findings reinforce the importance of hypertension in the development of silent cerebrovascular diseases, but the pathophysiologic relationships to BP for each may differ.
Keywords: Age Factors; Aged; Antihypertensive Agents; Blood Pressure; Cerebral Infarction; Disease Progression; Female; Heart Rate; Humans; Hypertension; Incidence; Leukoaraiosis; Longitudinal Studies; Magnetic Resonance Imaging; Male; Prospective Studies; Pulsatile Flow; Risk Factors; Time Factors; United States

Exome-wide association study of plasma lipids in >300,000 individuals. - Liu, Dajiang J; Peloso, Gina M; Yu, Haojie; Butterworth, Adam S; Wang, Xiao; Mahajan, Anubha; Saleheen, Danish; Emdin, Connor; Alam, Dewan; Alves, Alexessander Couto; Amouyel, Philippe; Di Angelantonio, Emanuele; et al. (Nat Genet, 2017)
We screened variants on an exome-focused genotyping array in >300,000 participants (replication in >280,000 participants) and identified 444 independent variants in 250 loci significantly associated with total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C), and/or triglycerides (TG). At two loci (JAK2 and A1CF), experimental analysis in mice showed lipid changes consistent with the human data. We also found that: (i) beta-thalassemia trait carriers displayed lower TC and were protected from coronary artery disease (CAD); (ii) excluding the CETP locus, there was not a predictable relationship between plasma HDL-C and risk for age-related macular degeneration; (iii) only some mechanisms of lowering LDL-C appeared to increase risk for type 2 diabetes (T2D); and (iv) TG-lowering alleles involved in hepatic production of TG-rich lipoproteins (TM6SF2 and PNPLA3) tracked with higher liver fat, higher risk for T2D, and lower risk for CAD, whereas TG-lowering alleles involved in peripheral lipolysis (LPL and ANGPTL4) had no effect on liver fat but decreased risks for both T2D and CAD.
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipids; Macular Degeneration; Phenotype; Risk Factors

Factors Associated With Ischemic Stroke Survival and Recovery in Older Adults. - Winovich, Divya Thekkethala; Longstreth, William T; Arnold, Alice M; Varadhan, Ravi; Zeki Al Hazzouri, Adina; Cushman, Mary; Newman, Anne B; Odden, Michelle C (Stroke, 2017)
BACKGROUND AND PURPOSE: Little is known about factors that predispose older adults to poor recovery after a stroke. In this study, we sought to evaluate prestroke measures of frailty and related factors as markers of vulnerability to poor outcomes after ischemic stroke. METHODS: In participants aged 65 to 99 years with incident ischemic strokes from the Cardiovascular Health Study, we evaluated the association of several risk factors (frailty, frailty components, C-reactive protein, interleukin-6, and cystatin C) assessed before stroke with stroke outcomes of survival, cognitive decline (≥5 points on Modified Mini-Mental State Examination), and activities of daily living decline (increase in limitations). RESULTS: Among 717 participants with incident ischemic stroke with survival data, slow walking speed, low grip strength, and cystatin C were independently associated with shorter survival. Among participants <80 years of age, frailty and interleukin-6 were also associated with shorter survival. Among 509 participants with recovery data, slow walking speed, and low grip strength were associated with both cognitive and activities of daily living decline poststroke. C-reactive protein and interleukin-6 were associated with poststroke cognitive decline among men only. Frailty status was associated with activities of daily living decline among women only. CONCLUSIONS: Markers of physical function-walking speed and grip strength-were consistently associated with survival and recovery after ischemic stroke. Inflammation, kidney function, and frailty also seemed to be determinants of survival and recovery after an ischemic stroke. These markers of vulnerability may identify targets for differing pre and poststroke medical management and rehabilitation among older adults at risk of poor stroke outcomes.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Brain Ischemia; Cohort Studies; Female; Follow-Up Studies; Frail Elderly; Humans; Male; Recovery of Function; Risk Factors; Stroke; Survival Rate

Fibroblast Growth Factor 23, Mineral Metabolism, and Adiposity in Normal Kidney Function. - Zaheer, Sarah; de Boer, Ian H; Allison, Matthew; Brown, Jenifer M; Psaty, Bruce M; Robinson-Cohen, Cassianne; Michos, Erin D; Ix, Joachim H; Kestenbaum, Bryan; Siscovick, David; Vaidya, Anand (J Clin Endocrinol Metab, 2017)
Context: Obesity is associated with poor bone mineralization and quality. Fibroblast growth factor 23 (FGF23) plays an important role in skeletal physiology. Objective: To test hypothesis that greater adiposity results in higher FGF23 levels among individuals with normal estimated glomerular filtration rate (eGFR). Design, Setting, Participants: Cross-sectional analyses among participants with eGFR ≥60 mL/min/1.73m2. We assessed the association between crude [body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR); n = 5610] and refined (abdominal adipose tissue area by computed tomography; n = 1313) measures of adiposity and FGF23 using multivariable linear regression. Main Outcome Measure: Serum FGF23. Results: FGF23 was higher across BMI categories (BMI <25: 37.7; BMI 25 to 29.99: 38.7; BMI 30 to 39.99: 39.8; BMI ≥40: 40.9 pg/mL, unadjusted P trend < 0.0001). The association between BMI and FGF23 was independent of known confounders of FGF23 (adjusted β = +7.2% higher FGF23 per 10 kg/m2; P < 0.0001). Similar results were observed using WC and WHR. Abdominal adipose tissue area was also independently associated with higher FGF23 (P < 0.01). Notably, the positive associations between FGF23 and adiposity were observed despite the fact that eGFR did not decline and serum phosphate levels did not increase with adiposity. Conclusion: In a large cohort with normal kidney function, adiposity was associated with higher FGF23 levels independent of known confounders, including eGFR and phosphate. Further studies are needed to evaluate the causes of higher FGF23 in settings of greater adiposity and the potential impact on skeletal health.
Keywords: Adiposity; Aged; Aged, 80 and over; Cross-Sectional Studies; Female; Fibroblast Growth Factors; Glomerular Filtration Rate; Humans; Kidney; Male; Middle Aged; Minerals; Renal Insufficiency, Chronic; Risk Factors

Low-Frequency Synonymous Coding Variation in CYP2R1 Has Large Effects on Vitamin D Levels and Risk of Multiple Sclerosis. - Manousaki, Despoina; Dudding, Tom; Haworth, Simon; Hsu, Yi-Hsiang; Liu, Ching-Ti; Medina-Gómez, Carolina; Voortman, Trudy; van der Velde, Nathalie; Melhus, Håkan; Robinson-Cohen, Cassianne; Cousminer, Diana L; Nethander, Maria; et al. (Am J Hum Genet, 2017)
Vitamin D insufficiency is common, correctable, and influenced by genetic factors, and it has been associated with risk of several diseases. We sought to identify low-frequency genetic variants that strongly increase the risk of vitamin D insufficiency and tested their effect on risk of multiple sclerosis, a disease influenced by low vitamin D concentrations. We used whole-genome sequencing data from 2,619 individuals through the UK10K program and deep-imputation data from 39,655 individuals genotyped genome-wide. Meta-analysis of the summary statistics from 19 cohorts identified in CYP2R1 the low-frequency (minor allele frequency = 2.5%) synonymous coding variant g.14900931G>A (p.Asp120Asp) (rs117913124[A]), which conferred a large effect on 25-hydroxyvitamin D (25OHD) levels (-0.43 SD of standardized natural log-transformed 25OHD per A allele; p value = 1.5 × 10(-88)). The effect on 25OHD was four times larger and independent of the effect of a previously described common variant near CYP2R1. By analyzing 8,711 individuals, we showed that heterozygote carriers of this low-frequency variant have an increased risk of vitamin D insufficiency (odds ratio [OR] = 2.2, 95% confidence interval [CI] = 1.78-2.78, p = 1.26 × 10(-12)). Individuals carrying one copy of this variant also had increased odds of multiple sclerosis (OR = 1.4, 95% CI = 1.19-1.64, p = 2.63 × 10(-5)) in a sample of 5,927 case and 5,599 control subjects. In conclusion, we describe a low-frequency CYP2R1 coding variant that exerts the largest effect upon 25OHD levels identified to date in the general European population and implicates vitamin D in the etiology of multiple sclerosis.
Keywords: Cholestanetriol 26-Monooxygenase; Cytochrome P450 Family 2; Gene Frequency; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Multiple Sclerosis; Polymorphism, Single Nucleotide; Risk Factors; Vitamin D; Vitamin D Deficiency

Omega-3 Fatty Acids and Incident Ischemic Stroke and Its Atherothrombotic and Cardioembolic Subtypes in 3 US Cohorts. - Saber, Hamidreza; Yakoob, Mohammad Yawar; Shi, Peilin; Longstreth, W T; Lemaitre, Rozenn N; Siscovick, David; Rexrode, Kathryn M; Willett, Walter C; Mozaffarian, Dariush (Stroke, 2017)
BACKGROUND AND PURPOSE: The associations of individual long-chain n-3 polyunsaturated fatty acids with incident ischemic stroke and its main subtypes are not well established. We aimed to investigate prospectively the relationship of circulating eicosapentaenoic acid, docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA) with risk of total ischemic, atherothrombotic, and cardioembolic stroke. METHODS: We measured circulating phospholipid fatty acids at baseline in 3 separate US cohorts: CHS (Cardiovascular Health Study), NHS (Nurses' Health Study), and HPFS (Health Professionals Follow-Up Study). Ischemic strokes were prospectively adjudicated and classified into atherothrombotic (large- and small-vessel infarctions) or cardioembolic by imaging studies and medical records. Risk according to fatty acid levels was assessed using Cox proportional hazards (CHS) or conditional logistic regression (NHS, HPFS) according to study design. Cohort findings were pooled using fixed-effects meta-analysis. RESULTS: A total of 953 incident ischemic strokes were identified (408 atherothrombotic, 256 cardioembolic, and 289 undetermined subtypes) during median follow-up of 11.2 years (CHS) and 8.3 years (pooled, NHS and HPFS). After multivariable adjustment, lower risk of total ischemic stroke was seen with higher DPA (highest versus lowest quartiles; pooled hazard ratio [HR], 0.74; 95% confidence interval [CI], 0.58-0.92) and DHA (HR, 0.80; 95% CI, 0.64-1.00) but not eicosapentaenoic acid (HR, 0.94; 95% CI, 0.77-1.19). DHA was associated with lower risk of atherothrombotic stroke (HR, 0.53; 95% CI, 0.34-0.83) and DPA with lower risk of cardioembolic stroke (HR, 0.58; 95% CI, 0.37-0.92). Findings in each individual cohort were consistent with pooled results. CONCLUSIONS: In 3 large US cohorts, higher circulating levels of DHA were inversely associated with incident atherothrombotic stroke and DPA with cardioembolic stroke. These novel findings suggest differential pathways of benefit for DHA, DPA, and eicosapentaenoic acid.
Keywords: Adult; Aged; Aged, 80 and over; Biomarkers; Brain Ischemia; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Incidence; Intracranial Arteriosclerosis; Intracranial Embolism; Intracranial Thrombosis; Male; Middle Aged; Prospective Studies; Random Allocation; Risk Factors; Stroke; United States

Phenotype-Specific Association of Single-Nucleotide Polymorphisms with Heart Failure and Preserved Ejection Fraction: a Genome-Wide Association Analysis of the Cardiovascular Health Study. - Kao, David P; Stevens, Laura M; Hinterberg, Michael A; Görg, Carsten (J Cardiovasc Transl Res, 2017)
Little is known about genetics of heart failure with preserved ejection fraction (HFpEF) in part because of the many comorbidities in this population. To identify single-nucleotide polymorphisms (SNPs) associated with HFpEF, we analyzed phenotypic and genotypic data from the Cardiovascular Health Study, which profiled patients using a 50,000 SNP array. Results were explored using novel SNP- and gene-centric tools. We performed analyses to determine whether some SNPs were relevant only in certain phenotypes. Among 3804 patients, 7 clinical factors and 9 SNPs were significantly associated with HFpEF; the most notable of which was rs6996224, a SNP associated with transforming growth factor-beta receptor 3. Most SNPs were associated with HFpEF only in the absence of a clinical predictor. Significant SNPs represented genes involved in myocyte proliferation, transforming growth factor-beta/erbB signaling, and extracellular matrix formation. These findings suggest that genetic factors may be more important in some phenotypes than others.
Keywords: Aged; Computational Biology; Databases, Genetic; European Continental Ancestry Group; Female; Gene Expression Profiling; Genetic Markers; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Failure; Humans; Male; Oligonucleotide Array Sequence Analysis; Phenotype; Polymorphism, Single Nucleotide; Predictive Value of Tests; Prognosis; Proteoglycans; Receptors, Transforming Growth Factor beta; Risk Assessment; Risk Factors; Stroke Volume; United States

Thyroid Function Within the Normal Range, Subclinical Hypothyroidism, and the Risk of Atrial Fibrillation. - Baumgartner, Christine; da Costa, Bruno R; Collet, Tinh-Hai; Feller, Martin; Floriani, Carmen; Bauer, Douglas C; Cappola, Anne R; Heckbert, Susan R; Ceresini, Graziano; Gussekloo, Jacobijn; den Elzen, Wendy P J; Peeters, Robin P; et al. (Circulation, 2017)
BACKGROUND: Atrial fibrillation (AF) is a highly prevalent disorder leading to heart failure, stroke, and death. Enhanced understanding of modifiable risk factors may yield opportunities for prevention. The risk of AF is increased in subclinical hyperthyroidism, but it is uncertain whether variations in thyroid function within the normal range or subclinical hypothyroidism are also associated with AF. METHODS: We conducted a systematic review and obtained individual participant data from prospective cohort studies that measured thyroid function at baseline and assessed incident AF. Studies were identified from MEDLINE and EMBASE databases from inception to July 27, 2016. The euthyroid state was defined as thyroid-stimulating hormone (TSH) 0.45 to 4.49 mIU/L, and subclinical hypothyroidism as TSH 4.5 to 19.9 mIU/L with free thyroxine (fT4) levels within reference range. The association of TSH levels in the euthyroid and subclinical hypothyroid range with incident AF was examined by using Cox proportional hazards models. In euthyroid participants, we additionally examined the association between fT4 levels and incident AF. RESULTS: Of 30 085 participants from 11 cohorts (278 955 person-years of follow-up), 1958 (6.5%) had subclinical hypothyroidism and 2574 individuals (8.6%) developed AF during follow-up. TSH at baseline was not significantly associated with incident AF in euthyroid participants or those with subclinical hypothyroidism. Higher fT4 levels at baseline in euthyroid individuals were associated with increased AF risk in age- and sex-adjusted analyses (hazard ratio, 1.45; 95% confidence interval, 1.26-1.66, for the highest quartile versus the lowest quartile of fT4; P for trend ≤0.001 across quartiles). Estimates did not substantially differ after further adjustment for preexisting cardiovascular disease. CONCLUSIONS: In euthyroid individuals, higher circulating fT4 levels, but not TSH levels, are associated with increased risk of incident AF.
Keywords: Adult; Aged; Aged, 80 and over; Asymptomatic Diseases; Atrial Fibrillation; Biomarkers; Chi-Square Distribution; Female; Humans; Hypothyroidism; Incidence; Male; Middle Aged; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Assessment; Risk Factors; Thyroid Function Tests; Thyroid Gland; Thyrotropin; Thyroxine; Time Factors; Young Adult

Visit-to-Visit Blood Pressure Variability and Mortality and Cardiovascular Outcomes Among Older Adults: The Health, Aging, and Body Composition Study. - Wu, Chenkai; Shlipak, Michael G; Stawski, Robert S; Peralta, Carmen A; Psaty, Bruce M; Harris, Tamara B; Satterfield, Suzanne; Shiroma, Eric J; Newman, Anne B; Odden, Michelle C (Am J Hypertens, 2017)
BACKGROUND: Level of blood pressure (BP) is strongly associated with cardiovascular (CV) events and mortality. However, it is questionable whether mean BP can fully capture BP-related vascular risk. Increasing attention has been given to the value of visit-to-visit BP variability. METHODS: We examined the association of visit-to-visit BP variability with mortality, incident myocardial infarction (MI), and incident stroke among 1,877 well-functioning elders in the Health, Aging, and Body Composition Study. We defined visit-to-visit diastolic BP (DBP) and systolic BP (SBP) variability as the root-mean-square error of person-specific linear regression of BP as a function of time. Alternatively, we counted the number of considerable BP increases and decreases (separately; 10mm Hg for DBP and 20mm Hg for SBP) between consecutive visits for each individual. RESULTS: Over an average follow-up of 8.5 years, 623 deaths (207 from CV disease), 153 MIs, and 156 strokes occurred. The median visit-to-visit DBP and SBP variability was 4.96 mmHg and 8.53 mmHg, respectively. After multivariable adjustment, visit-to-visit DBP variability was related to higher all-cause (hazard ratio (HR) = 1.18 per 1 SD, 95% confidence interval (CI) = 1.01-1.37) and CV mortality (HR = 1.35, 95% CI = 1.05-1.73). Additionally, individuals having more considerable decreases of DBP (≥10mm Hg between 2 consecutive visits) had higher risk of all-cause (HR = 1.13, 95% CI = 0.99-1.28) and CV mortality (HR = 1.30, 95% CI = 1.05-1.61); considerable increases of SBP (≥20mm Hg) were associated with higher risk of all-cause (HR = 1.18, 95% CI = 1.03-1.36) and CV mortality (HR = 1.37, 95% CI = 1.08-1.74). CONCLUSIONS: Visit-to-visit DBP variability and considerable changes in DBP and SBP were risk factors for mortality in the elderly.
Keywords: Aged; Aging; Blood Pressure; Blood Pressure Determination; Body Composition; California; Cohort Studies; Female; Health Status; Humans; Hypertension; Incidence; Longitudinal Studies; Male; Myocardial Infarction; Office Visits; Prognosis; Retrospective Studies; Risk Factors; Stroke; Survival Rate

Association between subclinical thyroid dysfunction and change in bone mineral density in prospective cohorts. - Segna, D; Bauer, D C; Feller, M; Schneider, C; Fink, H A; Aubert, C E; Collet, T-H; da Costa, B R; Fischer, K; Peeters, R P; Cappola, A R; Blum, M R; et al. (J Intern Med, 2018)
BACKGROUND: Subclinical hyperthyroidism (SHyper) has been associated with increased risk of hip and other fractures, but the linking mechanisms remain unclear. OBJECTIVE: To investigate the association between subclinical thyroid dysfunction and bone loss. METHODS: Individual participant data analysis was performed after a systematic literature search in MEDLINE/EMBASE (1946-2016). Two reviewers independently screened and selected prospective cohorts providing baseline thyroid status and serial bone mineral density (BMD) measurements. We classified thyroid status as euthyroidism (thyroid-stimulating hormone [TSH] 0.45-4.49 mIU/L), SHyper (TSH < 0.45 mIU/L) and subclinical hypothyroidism (SHypo, TSH ≥ 4.50-19.99 mIU/L) both with normal free thyroxine levels. Our primary outcome was annualized percentage BMD change (%ΔBMD) from serial dual X-ray absorptiometry scans of the femoral neck, total hip and lumbar spine, obtained from multivariable regression in a random-effects two-step approach. RESULTS: Amongst 5458 individuals (median age 72 years, 49.1% women) from six prospective cohorts, 451 (8.3%) had SHypo and 284 (5.2%) had SHyper. During 36 569 person-years of follow-up, those with SHyper had a greater annual bone loss at the femoral neck versus euthyroidism: %ΔBMD = -0.18 (95% CI: -0.34, -0.02; I2 = 0%), with a nonstatistically significant pattern at the total hip: %ΔBMD = -0.14 (95% CI: -0.38, 0.10; I2 = 53%), but not at the lumbar spine: %ΔBMD = 0.03 (95% CI: -0.30, 0.36; I2 = 25%); especially participants with TSH < 0.10 mIU/L showed an increased bone loss in the femoral neck (%Δ BMD = -0.59; [95% CI: -0.99, -0.19]) and total hip region (%ΔBMD = -0.46 [95% CI: -1.05, -0.13]). In contrast, SHypo was not associated with bone loss at any site. CONCLUSION: Amongst adults, SHyper was associated with increased femoral neck bone loss, potentially contributing to the increased fracture risk.
Keywords: Aged; Asymptomatic Diseases; Bone Density; Female; Fractures, Bone; Humans; Hyperthyroidism; Hypothyroidism; Male; Risk Factors

GWAS and colocalization analyses implicate carotid intima-media thickness and carotid plaque loci in cardiovascular outcomes. - Franceschini, Nora; Giambartolomei, Claudia; de Vries, Paul S; Finan, Chris; Bis, Joshua C; Huntley, Rachael P; Lovering, Ruth C; Tajuddin, Salman M; Winkler, Thomas W; Graff, Misa; Kavousi, Maryam; Dale, Caroline; et al. (Nat Commun, 2018)
Carotid artery intima media thickness (cIMT) and carotid plaque are measures of subclinical atherosclerosis associated with ischemic stroke and coronary heart disease (CHD). Here, we undertake meta-analyses of genome-wide association studies (GWAS) in 71,128 individuals for cIMT, and 48,434 individuals for carotid plaque traits. We identify eight novel susceptibility loci for cIMT, one independent association at the previously-identified PINX1 locus, and one novel locus for carotid plaque. Colocalization analysis with nearby vascular expression quantitative loci (cis-eQTLs) derived from arterial wall and metabolic tissues obtained from patients with CHD identifies candidate genes at two potentially additional loci, ADAMTS9 and LOXL4. LD score regression reveals significant genetic correlations between cIMT and plaque traits, and both cIMT and plaque with CHD, any stroke subtype and ischemic stroke. Our study provides insights into genes and tissue-specific regulatory mechanisms linking atherosclerosis both to its functional genomic origins and its clinical consequences in humans.
Keywords: ADAMTS9 Protein; Amino Acid Oxidoreductases; Carotid Intima-Media Thickness; Coronary Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lod Score; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

Metabolic Clusters and Outcomes in Older Adults: The Cardiovascular Health Study. - Mukamal, Kenneth J; Siscovick, David S; de Boer, Ian H; Ix, Joachim H; Kizer, Jorge R; Djoussé, Luc; Fitzpatrick, Annette L; Tracy, Russell P; Boyko, Edward J; Kahn, Steven E; Arnold, Alice M (J Am Geriatr Soc, 2018)
BACKGROUND/OBJECTIVES: Few studies have the requisite phenotypic information to define metabolic patterns that may inform our understanding of the pathophysiology and consequences of diabetes in older adults. We sought to characterize clusters of older adults on the basis of shared metabolic features. DESIGN: Population-based prospective cohort study. SETTING: Four U.S. Cardiovascular Health Study field centers. PARTICIPANTS: Individuals aged 65 and older taking no glucose-lowering agents (N = 2,231). MEASUREMENTS: K-means cluster analysis of 11 metabolic parameters (fasting and postload serum glucose and plasma insulin, fasting C-peptide, body mass index, C-reactive protein (CRP), estimated glomerular filtration rate (eGFR), albuminuria, carboxymethyl lysine (an advanced glycation end-product), procollagen III N-terminal propeptide (a fibrotic marker)) and their associations with incident cardiovascular disease, diabetes, disability, and mortality over 8 to 14.5 years of follow-up and with measures of subclinical cardiovascular disease. RESULTS: A 6-cluster solution provided robust differentiation into distinct, identifiable clusters. Cluster A (n = 739) had the lowest glucose and insulin and highest eGFR and the lowest rates of all outcomes. Cluster B (n = 419) had high glucose and insulin and intermediate rates of most outcomes. Cluster C (n = 118) had the highest insulin. Cluster D (n = 129) had the highest glucose with much lower insulin. Cluster E (n = 314) had the lowest eGFR and highest albuminuria. Cluster F (n = 512) had the highest CRP. Rates of CVD, mortality, and subclinical atherosclerosis were highest in clusters C, D, and E and were similar to rates in participants with treated diabetes. Incidence of disability was highest in Cluster C. CONCLUSION: Clustering according to metabolic parameters identifies distinct phenotypes that are strongly associated with clinical and functional outcomes, even at advanced age.
Keywords: Aged; Aged, 80 and over; Blood Glucose; C-Reactive Protein; Cardiovascular Diseases; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Incidence; Insulin; Longitudinal Studies; Male; Prospective Studies; Risk Factors; United States

Predictive value for cardiovascular events of common carotid intima media thickness and its rate of change in individuals at high cardiovascular risk - Results from the PROG-IMT collaboration. - Lorenz, Matthias W; Gao, Lu; Ziegelbauer, Kathrin; Norata, Giuseppe Danilo; Empana, Jean Philippe; Schmidtmann, Irene; Lin, Hung-Ju; McLachlan, Stela; Bokemark, Lena; Ronkainen, Kimmo; Amato, Mauro; Schminke, Ulf; et al. (PLoS One, 2018)
AIMS: Carotid intima media thickness (CIMT) predicts cardiovascular (CVD) events, but the predictive value of CIMT change is debated. We assessed the relation between CIMT change and events in individuals at high cardiovascular risk. METHODS AND RESULTS: From 31 cohorts with two CIMT scans (total n = 89070) on average 3.6 years apart and clinical follow-up, subcohorts were drawn: (A) individuals with at least 3 cardiovascular risk factors without previous CVD events, (B) individuals with carotid plaques without previous CVD events, and (C) individuals with previous CVD events. Cox regression models were fit to estimate the hazard ratio (HR) of the combined endpoint (myocardial infarction, stroke or vascular death) per standard deviation (SD) of CIMT change, adjusted for CVD risk factors. These HRs were pooled across studies. In groups A, B and C we observed 3483, 2845 and 1165 endpoint events, respectively. Average common CIMT was 0.79mm (SD 0.16mm), and annual common CIMT change was 0.01mm (SD 0.07mm), both in group A. The pooled HR per SD of annual common CIMT change (0.02 to 0.43mm) was 0.99 (95% confidence interval: 0.95-1.02) in group A, 0.98 (0.93-1.04) in group B, and 0.95 (0.89-1.04) in group C. The HR per SD of common CIMT (average of the first and the second CIMT scan, 0.09 to 0.75mm) was 1.15 (1.07-1.23) in group A, 1.13 (1.05-1.22) in group B, and 1.12 (1.05-1.20) in group C. CONCLUSIONS: We confirm that common CIMT is associated with future CVD events in individuals at high risk. CIMT change does not relate to future event risk in high-risk individuals.
Keywords: Aged; Cardiovascular Diseases; Carotid Intima-Media Thickness; Female; Humans; Intersectoral Collaboration; Male; Middle Aged; Prognosis; Risk Factors

Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group. - Irvin, Marguerite R; Sitlani, Colleen M; Floyd, James S; Psaty, Bruce M; Bis, Joshua C; Wiggins, Kerri L; Whitsel, Eric A; Stürmer, Til; Stewart, James; Raffield, Laura; Sun, Fangui; Liu, Ching-Ti; et al. (Am J Hypertens, 2019)
BACKGROUND: Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described. METHODS: We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931, nAA = 228). Both a normotensive control group and a treatment-responsive control group were considered in separate analyses. Normotensive controls were untreated (nEA = 14,210, nAA = 2,480) and had systolic BP/diastolic BP < 140/90 mm Hg. Treatment-responsive controls (nEA = 5,266, nAA = 1,817) had BP at goal (<140/90 mm Hg), while treated with one antihypertensive medication class. Individual cohorts used logistic regression with adjustment for age, sex, study site, and principal components for ancestry to examine the association of single-nucleotide polymorphisms with case-control status. Inverse variance-weighted fixed-effects meta-analyses were carried out using METAL. RESULTS: The known hypertension locus, CASZ1, was a top finding among EAs (P = 1.1 × 10-8) and in the race-combined analysis (P = 1.5 × 10-9) using the normotensive control group (rs12046278, odds ratio = 0.71 (95% confidence interval: 0.6-0.8)). Single-nucleotide polymorphisms in this locus were robustly replicated in the Million Veterans Program (MVP) study in consideration of a treatment-responsive control group. There were no statistically significant findings for the discovery analyses including treatment-responsive controls. CONCLUSION: This genomic discovery effort for aTRH identified CASZ1 as an aTRH risk locus.
Keywords: Aged; Antihypertensive Agents; Black or African American; Blood Pressure; Case-Control Studies; DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; DNA-Binding Proteins; Drug Resistance; Dystrophin-Associated Proteins; Europe; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Myosin Heavy Chains; Myosin Type V; Neuropeptides; Pharmacogenetics; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors; Transcription Factors; United States; White People

Genomewide Association Study of Statin-Induced Myopathy in Patients Recruited Using the UK Clinical Practice Research Datalink. - Carr, Daniel F; Francis, Ben; Jorgensen, Andrea L; Zhang, Eunice; Chinoy, Hector; Heckbert, Susan R; Bis, Joshua C; Brody, Jennifer A; Floyd, James S; Psaty, Bruce M; Molokhia, Mariam; Lapeyre-Mestre, Maryse; et al. (Clin Pharmacol Ther, 2019)
Statins can be associated with myopathy. We have undertaken a genomewide association study (GWAS) to discover and validate genetic risk factors for statin-induced myopathy in a "real-world" setting. One hundred thirty-five patients with statin myopathy recruited via the UK Clinical Practice Research Datalink were genotyped using the Illumina OmniExpress Exome version 1.0 Bead Chip and compared with the Wellcome Trust Case-Control Consortium (n = 2,501). Nominally statistically significant single nucleotide polymorphism (SNP) signals in the GWAS (P < 5 × 10 ) were further evaluated in several independent cohorts (comprising 332 cases and 449 drug-tolerant controls). Only one (rs4149056/c.521C>T in the SLCO1B1 gene) SNP was genomewide significant in the severe myopathy (creatine kinase > 10 × upper limit of normal or rhabdomyolysis) group (P = 2.55 × 10 ; odds ratio 5.15; 95% confidence interval 3.13-8.45). The association with SLCO1B1 was present for several statins and replicated in the independent validation cohorts. The data highlight the role of SLCO1B1 c.521C>T SNP as a replicable genetic risk factor for statin myopathy. No other novel genetic risk factors with a similar effect size were identified.
Keywords: Adverse Drug Reaction Reporting Systems; Case-Control Studies; Databases, Factual; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Liver-Specific Organic Anion Transporter 1; Muscular Diseases; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk Factors; Severity of Illness Index; United Kingdom

Chronic obstructive pulmonary disease and related phenotypes: polygenic risk scores in population-based and case-control cohorts. - Moll, Matthew; Sakornsakolpat, Phuwanat; Shrine, Nick; Hobbs, Brian D; DeMeo, Dawn L; John, Catherine; Guyatt, Anna L; McGeachie, Michael J; Gharib, Sina A; Obeidat, Ma'en; Lahousse, Lies; Wijnant, Sara R A; et al. (Lancet Respir Med, 2020)
BACKGROUND: Genetic factors influence chronic obstructive pulmonary disease (COPD) risk, but the individual variants that have been identified have small effects. We hypothesised that a polygenic risk score using additional variants would predict COPD and associated phenotypes. METHODS: We constructed a polygenic risk score using a genome-wide association study of lung function (FEV and FEV/forced vital capacity [FVC]) from the UK Biobank and SpiroMeta. We tested this polygenic risk score in nine cohorts of multiple ethnicities for an association with moderate-to-severe COPD (defined as FEV/FVC <0·7 and FEV <80% of predicted). Associations were tested using logistic regression models, adjusting for age, sex, height, smoking pack-years, and principal components of genetic ancestry. We assessed predictive performance of models by area under the curve. In a subset of studies, we also studied quantitative and qualitative CT imaging phenotypes that reflect parenchymal and airway pathology, and patterns of reduced lung growth. FINDINGS: The polygenic risk score was associated with COPD in European (odds ratio [OR] per SD 1·81 [95% CI 1·74-1·88] and non-European (1·42 [1·34-1·51]) populations. Compared with the first decile, the tenth decile of the polygenic risk score was associated with COPD, with an OR of 7·99 (6·56-9·72) in European ancestry and 4·83 (3·45-6·77) in non-European ancestry cohorts. The polygenic risk score was superior to previously described genetic risk scores and, when combined with clinical risk factors (ie, age, sex, and smoking pack-years), showed improved prediction for COPD compared with a model comprising clinical risk factors alone (AUC 0·80 [0·79-0·81] vs 0·76 [0·75-0·76]). The polygenic risk score was associated with CT imaging phenotypes, including wall area percent, quantitative and qualitative measures of emphysema, local histogram emphysema patterns, and destructive emphysema subtypes. The polygenic risk score was associated with a reduced lung growth pattern. INTERPRETATION: A risk score comprised of genetic variants can identify a small subset of individuals at markedly increased risk for moderate-to-severe COPD, emphysema subtypes associated with cigarette smoking, and patterns of reduced lung growth. FUNDING: US National Institutes of Health, Wellcome Trust.
Keywords: Adult; Case-Control Studies; Cohort Studies; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Phenotype; Pulmonary Disease, Chronic Obstructive; Risk Factors; Vital Capacity

Metabolites Associated with Walking Ability Among the Oldest Old from the CHS All Stars Study. - Marron, Megan M; Wendell, Stacy G; Boudreau, Robert M; Clish, Clary B; Santanasto, Adam J; Tseng, George C; Zmuda, Joseph M; Newman, Anne B (J Gerontol A Biol Sci Med Sci, 2020)
BACKGROUND: Low walking ability is highly prevalent with advancing age and predicts major health outcomes. Metabolomics may help to better characterize differences in walking ability among older adults, providing insight into potentially altered molecular processes underlying age-related decline in functioning. We sought to identify metabolites and metabolic pathways associated with high versus low walking ability among 120 participants ages 79-95 from the CHS All Stars study. METHODS: Using a nested case-control design, 60 randomly selected participants with low walking ability were matched one-to-one on age, gender, race, and fasting time with 60 participants with high walking ability. High versus low walking ability was defined as being in the best versus worst tertiles for both gait speed (≥0.9 vs <0.7 m/s) and the Walking Ability Index (7-9 vs 0-1). Using liquid chromatography-mass spectrometry, 569 metabolites were identified in overnight-fasting plasma. RESULTS: Ninety-six metabolites were associated with walking ability, where 24% were triacylglycerols. Triacylglycerols that were higher among those with high walking ability consisted mostly of polyunsaturated fatty acids, whereas triacylglycerols that were lower among those with high walking ability consisted mostly of saturated or monounsaturated fatty acids. Body composition partly explained associations between some metabolites and walking ability. Proline and arginine metabolism was a top pathway associated with walking ability. CONCLUSION: These results may partly reflect pathways of modifiable risk factors, including excess dietary lipids and lack of physical activity, contributing to obesity and further alterations in metabolic pathways that lead to age-related decline in walking ability in this older adult cohort.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Female; Geriatric Assessment; Humans; Male; Metabolomics; Risk Factors; Walking; Walking Speed

Performance of the Pooled Cohort Equations to Estimate Atherosclerotic Cardiovascular Disease Risk by Body Mass Index. - Khera, Rohan; Pandey, Ambarish; Ayers, Colby R; Carnethon, Mercedes R; Greenland, Philip; Ndumele, Chiadi E; Nambi, Vijay; Seliger, Stephen L; Chaves, Paulo H M; Safford, Monika M; Cushman, Mary; Xanthakis, Vanessa; et al. (JAMA Netw Open, 2020)
Importance: Obesity is a global health challenge and a risk factor for atherosclerotic cardiovascular disease (ASVCD). Performance of the pooled cohort equations (PCE) for ASCVD risk by body mass index (BMI; calculated as weight in kilograms divided by height in meters squared) is unknown. Objective: To assess performance of the PCE across clinical BMI categories. Design, Setting, and Participants: This cohort study used pooled individual-level data from 8 community-based, prospective, longitudinal cohort studies with 10-year ASCVD event follow-up from 1996 to 2016. We included all adults ages 40 to 79 years without baseline ASCVD or statin use, resulting in a sample size of 37 311 participants. Data were analyzed from August 2017 to July 2020. Exposures: Participant BMI category: underweight (<18.5), normal weight (18.5 to <25), overweight (25 to <30), mild obesity (30 to <35), and moderate to severe obesity (≥35). Main Outcomes and Measures: Discrimination (Harrell C statistic) and calibration (Nam-D'Agostino χ2 goodness-of-fit test) of the PCE across BMI categories. Improvement in discrimination and net reclassification with addition of BMI, waist circumference, and high-sensitivity C-reactive protein (hsCRP) to the PCE. Results: Among 37 311 participants (mean [SD] age, 58.6 [11.8] years; 21 897 [58.7%] women), 380 604 person-years of follow-up were conducted. Mean (SD) baseline BMI was 29.0 (6.2), and 360 individuals (1.0%) were in the underweight category, 9937 individuals (26.6%) were in the normal weight category, 13 601 individuals (36.4%) were in the overweight category, 7783 individuals (20.9%) were in the mild obesity category, and 5630 individuals (15.1%) were in the moderate to severe obesity category. Median (interquartile range [IQR]) 10-year estimated ASCVD risk was 7.1% (2.5%-15.4%), and 3709 individuals (9.9%) developed ASCVD over a median (IQR) 10.8 [8.5-12.6] years. The PCE overestimated ASCVD risk in the overall cohort (estimated/observed [E/O] risk ratio, 1.22; 95% CI, 1.18-1.26) and across all BMI categories except the underweight category. Calibration was better near the clinical decision threshold in all BMI groups but worse among individuals with moderate or severe obesity (E/O risk ratio, 1.36; 95% CI, 1.25-1.47) and among those with the highest estimated ASCVD risk ≥20%. The PCE C statistic overall was 0.760 (95% CI, 0.753-0.767), with lower discrimination in the moderate or severe obesity group (C statistic, 0.742; 95% CI, 0.721-0.763) compared with the normal-range BMI group (C statistic, 0.785; 95% CI, 0.772-0.798). Waist circumference (hazard ratio, 1.07 per 1-SD increase; 95% CI, 1.03-1.11) and hsCRP (hazard ratio, 1.07 per 1-SD increase; 95% CI, 1.05-1.09), but not BMI, were associated with increased ASCVD risk when added to the PCE. However, these factors did not improve model performance (C statistic, 0.760; 95% CI, 0.753-0.767) with or without added metrics. Conclusions and Relevance: These findings suggest that the PCE had acceptable model discrimination and were well calibrated at clinical decision thresholds but overestimated risk of ASCVD for individuals in overweight and obese categories, particularly individuals with high estimated risk. Incorporation of the usual clinical measures of obesity did not improve risk estimation of the PCE. Future research is needed to determine whether incorporation of alternative high-risk obesity markers (eg, weight trajectory or measures of visceral or ectopic fat) into the PCE may improve risk prediction.
Keywords: Adult; Aged; Body Mass Index; Cardiovascular Diseases; Cohort Studies; Correlation of Data; Female; Humans; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors

Pre-diabetes, diabetes and predictors of incident angina among older women and men in the Cardiovascular Health Study. - Mathenge, Njambi; Fan, Wenjun; Wong, Nathan D; Hirsch, Calvin; Delaney, Chris Joseph; Amsterdam, Ezra A; Koch, Bruce; Calara, Rico; Gardin, Julius M (Diab Vasc Dis Res, 2020)
Diabetes mellitus and angina pectoris are important conditions in older persons. The utility of pre-diabetes mellitus, diabetes mellitus and other risk factors as predictors of incident angina pectoris among older adults has not been characterized. We examined incident angina pectoris rates by sex and diabetes mellitus status in 4511 adults aged ⩾65 years without coronary heart disease at baseline from the Cardiovascular Health Study. Cox regression examined predictors of incident angina pectoris, including pre-diabetes mellitus or diabetes mellitus adjusted for sociodemographic characteristics and other risk factors, over 12.2 ± 6.9 years of follow-up. Overall, 39.1% of participants had pre-diabetes mellitus, 14.0% had diabetes mellitus and 532 (11.8%) had incident angina pectoris. Incident angina pectoris rates per 1000 person-years in those with neither condition, pre-diabetes mellitus, and diabetes mellitus were 7.9, 9.0 and 12.3 in women and 10.3, 11.2 and 14.5 in men, respectively. Pre-diabetes mellitus and diabetes mellitus were not independently associated with incident AP; however, key predictors of AP were male sex, low-density lipoprotein-cholesterol, triglycerides, systolic blood pressure, antihypertensive medication and difficulty performing at least one instrumental activity of daily living (all  < 0.05 to  < 0.01). In our cohort of older adult participants, while the incidence of AP is greater in those with diabetes mellitus, neither diabetes mellitus nor pre-diabetes mellitus independently predicted incident angina pectoris.
Keywords: Age Factors; Aged; Angina Pectoris; Diabetes Mellitus; Female; Humans; Incidence; Male; Prediabetic State; Prognosis; Prospective Studies; Risk Assessment; Risk Factors; Sex Factors; Time Factors; United States

Associations of Body Mass Index and Waist Circumference in Young Adulthood with Later Life Incident Diabetes. - Nair, Nandini; Vittinghoff, Eric; Pletcher, Mark J; Oelsner, Elizabeth C; Allen, Norrina B; Ndumele, Chiadi E; West, Nancy A; Strotmeyer, Elsa S; Mukamal, Kenneth J; Siscovick, David S; Biggs, Mary L; Laferrère, Blandine; et al. (J Clin Endocrinol Metab, 2021)
CONTEXT: The independent contribution of young adult exposure to overweight and obesity to later-life incident diabetes is not well studied. OBJECTIVE: To assess the associations of exposures to elevated body mass index (BMI) and waist circumference (WC) in young adulthood (ages 18-39 years) with incident diabetes later in life (≥40 years). DESIGN: Pooled data from 6 US prospective cohorts (Atherosclerosis Risk in Communities Study, Cardiovascular Risk Development in Young Adults Study, Cardiovascular Health Study, (4) Framingham Heart Study Offspring Cohort, (5) Health, Aging and Body Composition Study, and (6) Multi-Ethnic Study of Atherosclerosis. SETTING: Population-based cohort studies. PARTICIPANTS: 30 780 participants (56.1% female, 69.8% non-Hispanic white) without a diagnosis of diabetes by age 40. INTERVENTIONS: We imputed BMI and WC trajectories from age 18 for every participant and estimated time-weighted average exposures to BMI or WC during young adulthood and later life. MAIN OUTCOME MEASURE(S): Incident diabetes defined as fasting glucose ≥126 mg/dL, nonfasting glucose ≥200 mg/dL, or use of diabetes medications. RESULTS: During a 9-year median follow-up, 4323 participants developed incident diabetes. Young adult BMI and WC were associated with later-life incident diabetes after controlling for later-life exposures [hazard ratios (HR) 1.99 for BMI ≥ 30 kg/m2 and 2.13 for WC > 88cm (women)/>102cm (men) compared to normal ranges]. Young adult homeostatic model of insulin resistance mediated 49% and 44% of the association between BMI and WC with later-life incident diabetes. High-density lipoproteins and triglycerides mediated a smaller proportion of these associations. CONCLUSIONS: Elevated BMI and WC during young adulthood were independently associated with later-life incident diabetes. Insulin resistance may be a key mediator.
Keywords: Adolescent; Adult; Biomarkers; Body Mass Index; Diabetes Mellitus; Female; Follow-Up Studies; Humans; Male; Obesity; Overweight; Prognosis; Prospective Studies; Risk Factors; United States; Waist Circumference; Young Adult

Blood n-3 fatty acid levels and total and cause-specific mortality from 17 prospective studies. - Harris, William S; Tintle, Nathan L; Imamura, Fumiaki; Qian, Frank; Korat, Andres V Ardisson; Marklund, Matti; Djoussé, Luc; Bassett, Julie K; Carmichael, Pierre-Hugues; Chen, Yun-Yu; Hirakawa, Yoichiro; Küpers, Leanne K; et al. (Nat Commun, 2021)
The health effects of omega-3 fatty acids have been controversial. Here we report the results of a de novo pooled analysis conducted with data from 17 prospective cohort studies examining the associations between blood omega-3 fatty acid levels and risk for all-cause mortality. Over a median of 16 years of follow-up, 15,720 deaths occurred among 42,466 individuals. We found that, after multivariable adjustment for relevant risk factors, risk for death from all causes was significantly lower (by 15-18%, at least p < 0.003) in the highest vs the lowest quintile for circulating long chain (20-22 carbon) omega-3 fatty acids (eicosapentaenoic, docosapentaenoic, and docosahexaenoic acids). Similar relationships were seen for death from cardiovascular disease, cancer and other causes. No associations were seen with the 18-carbon omega-3, alpha-linolenic acid. These findings suggest that higher circulating levels of marine n-3 PUFA are associated with a lower risk of premature death.
Keywords: Aged; Aged, 80 and over; Cause of Death; Fatty Acids, Omega-3; Female; Follow-Up Studies; Humans; Male; Middle Aged; Mortality, Premature; Prospective Studies; Protective Factors; Risk Factors

Cardiovascular Risk Factors Across the Life Course and Cognitive Decline: A Pooled Cohort Study. - Yaffe, Kristine; Vittinghoff, Eric; Hoang, Tina; Matthews, Karen; Golden, Sherita H; Zeki Al Hazzouri, Adina (Neurology, 2021)
OBJECTIVE: Cardiovascular risk factors (CVRFs) are associated with increased risk of cognitive decline, but little is known about how early adult CVRFs and those across the life course might influence late-life cognition. To test the hypothesis that CVRFs across the adult life course are associated with late-life cognitive changes, we pooled data from 4 prospective cohorts (n = 15,001, ages 18-95). METHODS: We imputed trajectories of body mass index (BMI), fasting glucose (FG), systolic blood pressure (SBP), and total cholesterol (TC) for older adults. We used linear mixed models to determine the association of early adult, midlife, and late-life CVRFs with late-life decline on global cognition (Modified Mini-Mental State Examination [3MS]) and processing speed (Digit Symbol Substitution Test [DSST]), adjusting for demographics, education, and cohort. RESULTS: Elevated BMI, FG, and SBP (but not TC) at each time period were associated with greater late-life decline. Early life CVRFs were associated with the greatest change, an approximate doubling of mean 10-year decline (an additional 3-4 points for 3MS or DSST). Late-life CVRFs were associated with declines in early late life (<80 years) but with gains in very late life (≥80 years). After adjusting for CVRF exposures at all time periods, the associations for early adult and late-life CVRFs persisted. CONCLUSIONS: We found that imputed CVRFs across the life course, especially in early adulthood, were associated with greater late-life cognitive decline. Our results suggest that CVRF treatment in early adulthood could benefit late-life cognition, but that treatment in very late life may not be as helpful for these outcomes.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Aging; Blood Pressure; Cardiovascular Diseases; Cognition; Cognitive Dysfunction; Cohort Studies; Female; Heart Disease Risk Factors; Humans; Hypertension; Male; Middle Aged; Risk Factors; Young Adult

Depressive Symptoms Imputed Across the Life Course Are Associated with Cognitive Impairment and Cognitive Decline. - Brenowitz, Willa D; Zeki Al Hazzouri, Adina; Vittinghoff, Eric; Golden, Sherita H; Fitzpatrick, Annette L; Yaffe, Kristine (J Alzheimers Dis, 2021)
BACKGROUND: Depressive symptoms may increase risk for dementia, but findings are controversial because late-life depression may be a prodromal dementia symptom. Life course data on depression and dementia risk may clarify this association; however, data is limited. OBJECTIVE: To impute adult depressive symptoms trajectories across adult life stages and estimate the association with cognitive impairment and decline. METHODS: Using a pooled study of 4 prospective cohorts (ages 20-89), we imputed adult life course depressive symptoms trajectories based on Center for Epidemiologic Studies Depression Scale-10 (CESD-10) and calculated time-weighted averages for early adulthood (ages 20-49), mid-life (ages 50-69), and late-life (ages 70-89) for 6,122 older participants. Adjusted pooled logistic and mixed-effects models estimated associations of imputed depressive symptoms with two cognitive outcomes: cognitive impairment defined by established criteria and a composite cognitive score. RESULTS: In separate models, elevated depressive symptoms in each life stage were associated with cognitive outcomes: early adulthood OR for cognitive impairment = 1.59 (95%CI: 1.35,1.87); mid-life OR = 1.94 (95%CI:1.16, 3.26); and late-life OR = 1.77 (95%CI:1.42, 2.21). When adjusted for depressive symptoms in the other life-stages, elevated depressive symptoms in early adulthood (OR = 1.73; 95%CI: 1.42,2.11) and late-life (OR = 1.43; 95%CI: 1.08,1.89) remained associated with cognitive impairment and were also associated with faster rates of cognitive decline (p < 0.05). CONCLUSION: Imputing depressive symptom trajectories from pooled cohorts may help expand data across the life course. Our findings suggest early adulthood depressive symptoms may be a risk factor for cognitive impairment independent of mid- or late-life depressive symptoms.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; Cohort Studies; Dementia; Depression; Female; Humans; Male; Middle Aged; Prodromal Symptoms; Risk Factors

Egg consumption, overall diet quality, and risk of type 2 diabetes and coronary heart disease: A pooling project of US prospective cohorts. - Djoussé, Luc; Zhou, Guohai; McClelland, Robyn L; Ma, Nanxun; Zhou, Xia; Kabagambe, Edmond K; Talegawkar, Sameera A; Judd, Suzanne E; Biggs, Mary L; Fitzpatrick, Annette L; Clark, Cheryl R; Gagnon, David R; et al. (Clin Nutr, 2021)
BACKGROUND AND AIMS: Data on the relation of egg consumption with risk of type 2 diabetes (T2D) and coronary heart disease (CHD) are limited and inconsistent. Few studies have controlled for overall dietary patterns in egg-T2D or egg-CHD analyses, and it is unclear whether any observed elevated risks of T2D and CHD with frequent egg consumption is real or due to confounding by dietary habits. We tested the hypothesis that frequent egg consumption is associated with a higher risk of T2D and CHD risk after adjustment for overall dietary patterns among adults. DESIGN: We used prospective cohort design to complete time-to-event analyses. METHODS: We pooled de novo, harmonized, individual-level analyses from nine US cohorts (n = 103,811). Cox regression was used to estimate hazard ratios separately in each cohort adjusting for age, ethnicity, body mass index (BMI), exercise, smoking, alcohol intake, and dietary patterns. We pooled cohort-specific results using an inverse-variance weighted method to estimate summary relative risks. RESULTS: Median age ranged from 25 to 72 years. Median egg consumption was 1 egg per week in most of the cohorts. While egg consumption up to one per week was not associated with T2D risk, consumption of ≥2 eggs per week was associated with elevated risk [27% elevated risk of T2D comparing 7+ eggs/week with none (95% CI: 16%-37%)]. There was little evidence for heterogeneity across cohorts and we observed similar conclusions when stratified by BMI. Overall, egg consumption was not associated with the risk of CHD. However, in a sensitivity analysis, there was a 30% higher risk of CHD (95% CI: 3%-56%) restricted to older adults consuming 5-6 eggs/week. CONCLUSIONS: Our data showed an elevated risk of T2D with egg consumption of ≥2 eggs per week but not with <2 eggs/week. While there was no overall association of egg consumption with CHD risk, the elevated CHD observed with consumption of 5-6 eggs/week in older cohorts merits further investigation.
Keywords: Adult; Aged; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; Diet; Eggs; Humans; Middle Aged; Prospective Studies; Risk Factors; United States

Serum Nonesterified Fatty Acids and Incident Stroke: The CHS. - Huang, Neil K; Biggs, Mary L; Matthan, Nirupa R; Djoussé, Luc; Longstreth, W T; Mukamal, Kenneth J; Siscovick, David S; Lichtenstein, Alice H (J Am Heart Assoc, 2021)
Background Significant associations between total nonesterified fatty acid (NEFA) concentrations and incident stroke have been reported in some prospective cohort studies. We evaluated the associations between incident stroke and serum concentrations of nonesterified saturated, monounsaturated, polyunsaturated, and fatty acids. Methods and Results CHS (Cardiovascular Health Study) participants (N=2028) who were free of stroke at baseline (1996-1997) and had an archived fasting serum sample were included in this study. A total of 35 NEFAs were quantified using gas chromatography. Cox proportional hazards regression models were used to evaluate associations of 5 subclasses (nonesterified saturated, monounsaturated, omega (n)-6 polyunsaturated, n-3 polyunsaturated, and fatty acids) of NEFAs and individual NEFAs with incident stroke. Sensitivity analysis was conducted by excluding cases with hemorrhagic stroke (n=45). A total of 338 cases of incident stroke occurred during the median 10.5-year follow-up period. Total n-3 (hazard ratio [HR], 0.77 [95% CI, 0.61-0.97]) and n-6 (HR, 1.32 [95% CI, 1.01-1.73]) subclasses of NEFA were negatively and positively associated with incident stroke, respectively. Among individual NEFAs, dihomo-γ-linolenic acid (20:3n-6) was associated with higher risk (HR, 1.29 [95% CI, 1.02-1.63]), whereas -7-hexadecenoic acid (16:1n-9) and arachidonic acid (20:4n-6) were associated with a lower risk (HR, 0.67 [95% CI, 0.47-0.97]; HR, 0.81 [95% CI. 0.65-1.00], respectively) of incident stroke per standard deviation increment. After the exclusion of cases with hemorrhagic stroke, these associations did not remain significant. Conclusions A total of 2 NEFA subclasses and 3 individual NEFAs were associated with incident stroke. Of these, the NEFA n-3 subclass and dihomo-γ-linolenic acid are diet derived and may be potential biomarkers for total stroke risk.
Keywords: 8,11,14-Eicosatrienoic Acid; Fatty Acids, Nonesterified; Fatty Acids, Omega-3; Hemorrhagic Stroke; Humans; Prospective Studies; Risk Factors; Stroke; Trans Fatty Acids

Serum Non-Esterified Fatty Acids, Carotid Artery Intima-Media Thickness and Flow-Mediated Dilation in Older Adults: The Cardiovascular Health Study (CHS). - Huang, Neil K; Bůzková, Petra; Matthan, Nirupa R; Djoussé, Luc; Kizer, Jorge R; Mukamal, Kenneth J; Polak, Joseph F; Lichtenstein, Alice H (Nutrients, 2021)
Elevated common carotid artery intima-media thickness (carotid IMT) and diminished flow-mediated dilation (FMD) are early subclinical indicators of atherosclerosis. Serum total non-esterified fatty acid (NEFA) concentrations have been positively associated with subclinical atherosclerosis. The relations between individual NEFA, carotid IMT and FMD have as yet to be assessed. We investigated the associations between fasting serum individual NEFA, carotid IMT and FMD among Cardiovascular Health Study (CHS) participants with ( = 255 for carotid IMT, 301 for FMD) or without ( = 1314 for carotid IMT, 1462 for FMD) known atherosclerotic cardiovascular disease (ASCVD). Using archived samples (fasting) collected from 1996-1997 (baseline), 35 individual NEFAs were measured using gas chromatography. Carotid IMT and estimated plaque thickness (mean of maximum internal carotid IMT) were determined in 1998-1999. FMD was measured in 1997-1998. Linear regression adjusted by the Holm-Bonferroni method was used to assess relations between individual NEFA, carotid IMT and FMD. In multivariable adjusted linear regression models per SD increment, the non-esterified fatty acid conjugated linoleic acid (-18:2 CLA) was positively associated with carotid IMT [β (95% CI): 44.8 (19.2, 70.4), = 0.025] among participants with, but not without, ASCVD [2.16 (-6.74, 11.5), = 1.000]. Non-esterified -palmitoleic acid (16:1n-7) was positively associated with FMD [19.7 (8.34, 31.0), = 0.024] among participants without, but not with ASCVD. No significant associations between NEFAs and estimated plaque thickness were observed. In older adults, serum non-esterified CLA and palmitoleic acid were positively associated with carotid IMT and FMD, respectively, suggesting potential modifiable biomarkers for arteriopathy.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Biomarkers; Brachial Artery; Carotid Artery, Common; Carotid Intima-Media Thickness; Dilatation; Fatty Acids, Monounsaturated; Fatty Acids, Nonesterified; Female; Humans; Linoleic Acid; Male; Regional Blood Flow; Risk Factors; Ultrasonography

Supplemental Association of Clonal Hematopoiesis With Incident Heart Failure. - Yu, Bing; Roberts, Mary B; Raffield, Laura M; Zekavat, Seyedeh Maryam; Nguyen, Ngoc Quynh H; Biggs, Mary L; Brown, Michael R; Griffin, Gabriel; Desai, Pinkal; Correa, Adolfo; Morrison, Alanna C; Shah, Amil M; et al. (J Am Coll Cardiol, 2021)
BACKGROUND: Age-related clonal hematopoiesis of indeterminate potential (CHIP), defined as clonally expanded leukemogenic sequence variations (particularly in DNMT3A, TET2, ASXL1, and JAK2) in asymptomatic individuals, is associated with cardiovascular events, including recurrent heart failure (HF). OBJECTIVES: This study sought to evaluate whether CHIP is associated with incident HF. METHODS: CHIP status was obtained from whole exome or genome sequencing of blood DNA in participants without prevalent HF or hematological malignancy from 5 cohorts. Cox proportional hazards models were performed within each cohort, adjusting for demographic and clinical risk factors, followed by fixed-effect meta-analyses. Large CHIP clones (defined as variant allele frequency >10%), HF with or without baseline coronary heart disease, and left ventricular ejection fraction were evaluated in secondary analyses. RESULTS: Of 56,597 individuals (59% women, mean age 58 years at baseline), 3,406 (6%) had CHIP, and 4,694 developed HF (8.3%) over up to 20 years of follow-up. CHIP was prospectively associated with a 25% increased risk of HF in meta-analysis (hazard ratio: 1.25; 95% confidence interval: 1.13-1.38) with consistent associations across cohorts. ASXL1, TET2, and JAK2 sequence variations were each associated with an increased risk of HF, whereas DNMT3A sequence variations were not associated with HF. Secondary analyses suggested large CHIP was associated with a greater risk of HF (hazard ratio: 1.29; 95% confidence interval: 1.15-1.44), and the associations for CHIP on HF with and without prior coronary heart disease were homogenous. ASXL1 sequence variations were associated with reduced left ventricular ejection fraction. CONCLUSIONS: CHIP, particularly sequence variations in ASXL1, TET2, and JAK2, represents a new risk factor for HF.
Keywords: Aged; Clonal Hematopoiesis; Correlation of Data; Demography; DNA-Binding Proteins; Female; Heart Failure; Humans; Janus Kinase 2; Male; Middle Aged; Mutation; Proportional Hazards Models; Proto-Oncogene Proteins; Repressor Proteins; Risk Factors; Stroke Volume; Ventricular Dysfunction, Left; Whole Exome Sequencing

Diabetes Status Modifies the Association Between Different Measures of Obesity and Heart Failure Risk Among Older Adults: A Pooled Analysis of Community-Based NHLBI Cohorts. - Patel, Kershaw V; Segar, Matthew W; Lavie, Carl J; Kondamudi, Nitin; Neeland, Ian J; Almandoz, Jaime P; Martin, Corby K; Carbone, Salvatore; Butler, Javed; Powell-Wiley, Tiffany M; Pandey, Ambarish (Circulation, 2022)
BACKGROUND: Obesity and diabetes are associated with a higher risk of heart failure (HF). The interrelationships between different measures of adiposity-overall obesity, central obesity, fat mass (FM)-and diabetes status for HF risk are not well-established. METHODS: Participant-level data from the ARIC study (Atherosclerosis Risk in Communities; visit 5) and the CHS (Cardiovascular Health Study; visit 1) cohorts were obtained from the National Heart, Lung, and Blood Institute Biologic Specimen and Data Repository Information Coordinating Center, harmonized, and pooled for the present analysis, excluding individuals with prevalent HF. FM was estimated in all participants using established anthropometric prediction equations additionally validated using the bioelectrical impedance-based FM in the ARIC subgroup. Incident HF events on follow-up were captured across both cohorts using similar adjudication methods. Multivariable-adjusted Fine-Gray models were created to evaluate the associations of body mass index (BMI), waist circumference (WC), and FM with risk of HF in the overall cohort as well as among those with versus without diabetes at baseline. The population attributable risk of overall obesity (BMI≥30 kg/m), abdominal obesity (WC>88 and 102 cm in women and men, respectively), and high FM (above sex-specific median) for incident HF was evaluated among participants with and without diabetes. RESULTS: The study included 10 387 participants (52.9% ARIC; 25.1% diabetes; median age, 74 years). The correlation between predicted and bioelectrical impedance-based FM was high (=0.90; n=5038). During a 5-year follow-up, 447 participants developed HF (4.3%). Higher levels of each adiposity measure were significantly associated with higher HF risk (hazard ratio [95% CI] per 1 SD higher BMI=1.15 [1.05, 1.27], WC=1.22 [1.10, 1.36]; FM=1.13 [1.02, 1.25]). A significant interaction was noted between diabetes status and measures of BMI ( interaction=0.04) and WC ( interaction=0.004) for the risk of HF. In stratified analysis, higher measures of each adiposity parameter were significantly associated with higher HF risk in individuals with diabetes (hazard ratio [95% CI] per 1 SD higher BMI=1.29 [1.14-1.47]; WC=1.48 [1.29-1.70]; FM=1.25 [1.09-1.43]) but not those without diabetes, including participants with prediabetes and euglycemia. The population attributable risk percentage of overall obesity, abdominal obesity, and high FM for incident HF was higher among participants with diabetes (12.8%, 29.9%, and 13.7%, respectively) versus those without diabetes (≤1% for each). CONCLUSIONS: Higher BMI, WC, and FM are strongly associated with greater risk of HF among older adults, particularly among those with prevalent diabetes.
Keywords: Aged; Cohort Studies; Diabetes Mellitus; Female; Heart Failure; Humans; Male; National Heart, Lung, and Blood Institute (U.S.); Obesity; Risk Factors; United States

Dietary Meat, Trimethylamine N-Oxide-Related Metabolites, and Incident Cardiovascular Disease Among Older Adults: The Cardiovascular Health Study. - Wang, Meng; Wang, Zeneng; Lee, Yujin; Lai, Heidi T M; de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Fretts, Amanda; Sotoodehnia, Nona; Budoff, Matthew; DiDonato, Joseph A; McKnight, Barbara; Tang, W H Wilson; et al. (Arterioscler Thromb Vasc Biol, 2022)
BACKGROUND: Effects of animal source foods (ASF) on atherosclerotic cardiovascular disease (ASCVD) and underlying mechanisms remain controversial. We investigated prospective associations of different ASF with incident ASCVD and potential mediation by gut microbiota-generated trimethylamine N-oxide, its L-carnitine-derived intermediates γ-butyrobetaine and crotonobetaine, and traditional ASCVD risk pathways. METHODS: Among 3931 participants from a community-based US cohort aged 65+ years, ASF intakes and trimethylamine N-oxide-related metabolites were measured serially over time. Incident ASCVD (myocardial infarction, fatal coronary heart disease, stroke, other atherosclerotic death) was adjudicated over 12.5 years median follow-up. Cox proportional hazards models with time-varying exposures and covariates examined ASF-ASCVD associations; and additive hazard models, mediation proportions by different risk pathways. RESULTS: After multivariable-adjustment, higher intakes of unprocessed red meat, total meat, and total ASF associated with higher ASCVD risk, with hazard ratios (95% CI) per interquintile range of 1.15 (1.01-1.30), 1.22 (1.07-1.39), and 1.18 (1.03-1.34), respectively. Trimethylamine N-oxide-related metabolites together significantly mediated these associations, with mediation proportions (95% CI) of 10.6% (1.0-114.5), 7.8% (1.0-32.7), and 9.2% (2.2-44.5), respectively. Processed meat intake associated with a nonsignificant trend toward higher ASCVD (1.11 [0.98-1.25]); intakes of fish, poultry, and eggs were not significantly associated. Among other risk pathways, blood glucose, insulin, and C-reactive protein, but not blood pressure or blood cholesterol, each significantly mediated the total meat-ASCVD association. CONCLUSIONS: In this large, community-based cohort, higher meat intake associated with incident ASCVD, partly mediated by microbiota-derived metabolites of L-carnitine, abundant in red meat. These novel findings support biochemical links between dietary meat, gut microbiome pathways, and ASCVD.
Keywords: Animals; Atherosclerosis; Cardiovascular Diseases; Carnitine; Humans; Meat; Methylamines; Risk Factors

Epilepsy, Vascular Risk Factors, and Cognitive Decline in Older Adults: The Cardiovascular Health Study. - Choi, Hyunmi; Elkind, Mitchell S V; Longstreth, W T; Boehme, Amelia K; Hafen, Rebekah; Hoyt, Emma J; Thacker, Evan L (Neurology, 2022)
BACKGROUND AND OBJECTIVES: Recent studies have shown that global cognitive ability tends to decline faster over time in older adults (≥65 years) with epilepsy compared with older adults without epilepsy. Scarce data exist about the role of vascular risk factors (VRFs) on cognitive course in epilepsy. We assessed whether the associations of individual VRFs with cognitive trajectory differed depending on the presence of prevalent epilepsy. METHODS: The Cardiovascular Health Study is a population-based longitudinal cohort study of 5,888 US adults aged ≥65 years. Cognitive function was assessed annually with modified Mini-Mental State Examination (3MS; global cognitive ability) and Digit Symbol Substitution Test (DSST; information processing speed). We used linear mixed models to estimate the individual and joint associations of epilepsy and VRFs with cognitive decline by modeling epilepsy × VRF interactions one by one, each adjusted for all other VRFs considered, including demographics, health behaviors, clinical characteristics, and comorbid diagnoses. From these models, we estimated excess mean cognitive decline due to interaction of epilepsy with each VRF. RESULTS: We observed excess mean decline in global cognitive ability (3MS) due to interactions of epilepsy with hypertension (6.6 points greater mean 8-year decline than expected if no interaction; 95% CI 1.3-12.0) and with abstaining from alcohol (5.8 points greater than expected; 95% CI 0.3-11.3). We also observed excess mean decline in information processing speed (DSST) due to interactions of epilepsy with prior stroke (18.1 points greater mean 9-year decline than expected; 95% CI 7.6-28.5), with abstaining from alcohol (6.1 points greater than expected; 95% CI 2.5-9.8), and with higher triglyceride levels (2.4 points greater than expected per SD; 95% CI 0.4-4.3). DISCUSSION: Associations of some VRFs with cognitive decline in older adults are stronger in the presence of epilepsy, suggesting a need for greater attention to vascular protection for preserving brain health in older adults with epilepsy.
Keywords: Aged; Cognition; Cognitive Dysfunction; Epilepsy; Humans; Longitudinal Studies; Neuropsychological Tests; Risk Factors

Intake and Sources of Dietary Fiber, Inflammation, and Cardiovascular Disease in Older US Adults. - Shivakoti, Rupak; Biggs, Mary L; Djoussé, Luc; Durda, Peter Jon; Kizer, Jorge R; Psaty, Bruce; Reiner, Alex P; Tracy, Russell P; Siscovick, David; Mukamal, Kenneth J (JAMA Netw Open, 2022)
Importance: Higher intake of dietary fiber has been associated with lower inflammation, but whether there are differences in this association by source of dietary fiber (ie, cereal, vegetable, or fruit) has not been studied to date. Objectives: To evaluate the associations of total fiber intake and source (ie, cereal, vegetable, and fruit fiber intake) with inflammation and to evaluate whether inflammation mediates the inverse association between dietary fiber intake and cardiovascular disease (CVD). Design, Setting, and Participants: At the baseline visit (1989-1990) of 4125 adults aged 65 years or older in an ongoing US cohort study, dietary intake was assessed by a food frequency questionnaire among study participants without prevalent CVD (stroke and myocardial infarction) at enrollment. Inflammation was assessed from blood samples collected at baseline with immunoassays for markers of inflammation. Multivariable linear regression models tested the association of dietary fiber intake with inflammation. Also assessed was whether each inflammatory marker and its composite derived from principal component analysis mediated the association of baseline cereal fiber intake with development of CVD (stroke, myocardial infarction, and atherosclerotic cardiovascular death) through June 2015. Data from June 1, 1989, through June 30, 2015, were analyzed. Exposures: Total fiber intake and sources of fiber (cereal, vegetable, and fruit). Main Outcomes and Measures: Systemic markers of inflammation. Cardiovascular disease was the outcome in the mediation analysis. Results: Of 4125 individuals, 0.1% (n = 3) were Asian or Pacific Islander, 4.4% (n = 183) were Black, 0.3% (n = 12) were Native American, 95.0% (n = 3918) were White, and 0.2% (n = 9) were classified as other. Among these 4125 individuals (2473 women [60%]; mean [SD] age, 72.6 [5.5] years; 183 Black individuals [4.4%]; and 3942 individuals of other races and ethnicitites [95.6%] [ie, race and ethnicity other than Black, self-classified by participant]), an increase in total fiber intake of 5 g/d was associated with significantly lower concentrations of C-reactive protein (adjusted mean difference, -0.05 SD; 95% CI, -0.08 to -0.01 SD; P = .007) and interleukin 1 receptor antagonist (adjusted mean difference, -0.04 SD; 95% CI, -0.07 to -0.01 SD; P < .02) but with higher concentrations of soluble CD163 (adjusted mean difference, 0.05 SD; 95% CI, 0.02-0.09 SD; P = .005). Among fiber sources, only cereal fiber was consistently associated with lower inflammation. Similarly, cereal fiber intake was associated with lower CVD incidence (adjusted hazard ratio, 0.90; 95% CI, 0.81-1.00; 1941 incident cases). The proportion of the observed association of cereal fiber with CVD mediated by inflammatory markers ranged from 1.5% for interleukin 18 to 14.2% for C-reactive protein, and 16.1% for their primary principal component. Conclusions and Relevance: Results of this study suggest that cereal fiber intake was associated with lower levels of various inflammatory markers and lower risk of CVD and that inflammation mediated approximately one-sixth of the association between cereal fiber intake and CVD.
Keywords: Adult; Aged; Cardiovascular Diseases; Cohort Studies; Dietary Fiber; Female; Humans; Inflammation; Middle Aged; Risk Factors

Large-scale genome-wide association study of coronary artery disease in genetically diverse populations. - Tcheandjieu, Catherine; Zhu, Xiang; Hilliard, Austin T; Clarke, Shoa L; Napolioni, Valerio; Ma, Shining; Lee, Kyung Min; Fang, Huaying; Chen, Fei; Lu, Yingchang; Tsao, Noah L; Raghavan, Sridharan; et al. (Nat Med, 2022)
We report a genome-wide association study (GWAS) of coronary artery disease (CAD) incorporating nearly a quarter of a million cases, in which existing studies are integrated with data from cohorts of white, Black and Hispanic individuals from the Million Veteran Program. We document near equivalent heritability of CAD across multiple ancestral groups, identify 95 novel loci, including nine on the X chromosome, detect eight loci of genome-wide significance in Black and Hispanic individuals, and demonstrate that two common haplotypes at the 9p21 locus are responsible for risk stratification in all populations except those of African origin, in which these haplotypes are virtually absent. Moreover, in the largest GWAS for angiographically derived coronary atherosclerosis performed to date, we find 15 loci of genome-wide significance that robustly overlap with established loci for clinical CAD. Phenome-wide association analyses of novel loci and polygenic risk scores (PRSs) augment signals related to insulin resistance, extend pleiotropic associations of these loci to include smoking and family history, and precisely document the markedly reduced transferability of existing PRSs to Black individuals. Downstream integrative analyses reinforce the critical roles of vascular endothelial, fibroblast, and smooth muscle cells in CAD susceptibility, but also point to a shared biology between atherosclerosis and oncogenesis. This study highlights the value of diverse populations in further characterizing the genetic architecture of CAD.
Keywords: Coronary Artery Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

Lung function impairment and risk of incident heart failure: the NHLBI Pooled Cohorts Study. - Eckhardt, Christina M; Balte, Pallavi P; Barr, Robert Graham; Bertoni, Alain G; Bhatt, Surya P; Cuttica, Michael; Cassano, Patricia A; Chaves, Paolo; Couper, David; Jacobs, David R; Kalhan, Ravi; Kronmal, Richard; et al. (Eur Heart J, 2022)
AIMS: The aim is to evaluate associations of lung function impairment with risk of incident heart failure (HF). METHODS AND RESULTS: Data were pooled across eight US population-based cohorts that enrolled participants from 1987 to 2004. Participants with self-reported baseline cardiovascular disease were excluded. Spirometry was used to define obstructive [forced expiratory volume in 1 s/forced vital capacity (FEV1/FVC) <0.70] or restrictive (FEV1/FVC ≥0.70, FVC <80%) lung physiology. The incident HF was defined as hospitalization or death caused by HF. In a sub-set, HF events were sub-classified as HF with reduced ejection fraction (HFrEF; EF <50%) or preserved EF (HFpEF; EF ≥50%). The Fine-Gray proportional sub-distribution hazards models were adjusted for sociodemographic factors, smoking, and cardiovascular risk factors. In models of incident HF sub-types, HFrEF, HFpEF, and non-HF mortality were treated as competing risks. Among 31 677 adults, there were 3344 incident HF events over a median follow-up of 21.0 years. Of 2066 classifiable HF events, 1030 were classified as HFrEF and 1036 as HFpEF. Obstructive [adjusted hazard ratio (HR) 1.17, 95% confidence interval (CI) 1.07-1.27] and restrictive physiology (adjusted HR 1.43, 95% CI 1.27-1.62) were associated with incident HF. Obstructive and restrictive ventilatory defects were associated with HFpEF but not HFrEF. The magnitude of the association between restrictive physiology and HFpEF was similar to associations with hypertension, diabetes, and smoking. CONCLUSION: Lung function impairment was associated with increased risk of incident HF, and particularly incident HFpEF, independent of and to a similar extent as major known cardiovascular risk factors.
Keywords: Adult; Heart Failure; Hospitalization; Humans; Lung; National Heart, Lung, and Blood Institute (U.S.); Prognosis; Risk Factors; Stroke Volume; United States

Multi-ancestry genetic study of type 2 diabetes highlights the power of diverse populations for discovery and translation. - Mahajan, Anubha; Spracklen, Cassandra N; Zhang, Weihua; Ng, Maggie C Y; Petty, Lauren E; Kitajima, Hidetoshi; Yu, Grace Z; Rüeger, Sina; Speidel, Leo; Kim, Young Jin; Horikoshi, Momoko; Mercader, Josep M; et al. (Nat Genet, 2022)
We assembled an ancestrally diverse collection of genome-wide association studies (GWAS) of type 2 diabetes (T2D) in 180,834 affected individuals and 1,159,055 controls (48.9% non-European descent) through the Diabetes Meta-Analysis of Trans-Ethnic association studies (DIAMANTE) Consortium. Multi-ancestry GWAS meta-analysis identified 237 loci attaining stringent genome-wide significance (P < 5 × 10), which were delineated to 338 distinct association signals. Fine-mapping of these signals was enhanced by the increased sample size and expanded population diversity of the multi-ancestry meta-analysis, which localized 54.4% of T2D associations to a single variant with >50% posterior probability. This improved fine-mapping enabled systematic assessment of candidate causal genes and molecular mechanisms through which T2D associations are mediated, laying the foundations for functional investigations. Multi-ancestry genetic risk scores enhanced transferability of T2D prediction across diverse populations. Our study provides a step toward more effective clinical translation of T2D GWAS to improve global health for all, irrespective of genetic background.
Keywords: Diabetes Mellitus, Type 2; Ethnicity; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

A multi-ethnic polygenic risk score is associated with hypertension prevalence and progression throughout adulthood. - Kurniansyah, Nuzulul; Goodman, Matthew O; Kelly, Tanika N; Elfassy, Tali; Wiggins, Kerri L; Bis, Joshua C; Guo, Xiuqing; Palmas, Walter; Taylor, Kent D; Lin, Henry J; Haessler, Jeffrey; Gao, Yan; et al. (Nat Commun, 2022)
In a multi-stage analysis of 52,436 individuals aged 17-90 across diverse cohorts and biobanks, we train, test, and evaluate a polygenic risk score (PRS) for hypertension risk and progression. The PRS is trained using genome-wide association studies (GWAS) for systolic, diastolic blood pressure, and hypertension, respectively. For each trait, PRS is selected by optimizing the coefficient of variation (CV) across estimated effect sizes from multiple potential PRS using the same GWAS, after which the 3 trait-specific PRSs are combined via an unweighted sum called "PRSsum", forming the HTN-PRS. The HTN-PRS is associated with both prevalent and incident hypertension at 4-6 years of follow up. This association is further confirmed in age-stratified analysis. In an independent biobank of 40,201 individuals, the HTN-PRS is confirmed to be predictive of increased risk for coronary artery disease, ischemic stroke, type 2 diabetes, and chronic kidney disease.
Keywords: Adult; Diabetes Mellitus, Type 2; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Multifactorial Inheritance; Prevalence; Risk Factors

Plasma Levels of Advanced Glycation Endproducts and Risk of Cardiovascular Events: Findings From 2 Prospective Cohorts. - Lamprea-Montealegre, Julio A; Arnold, Alice M; McClelland, Robyn L; Mukamal, Kenneth J; Djoussé, Luc; Biggs, Mary L; Siscovick, David S; Tracy, Russell P; Beisswenger, Paul J; Psaty, Bruce M; Ix, Joachim H; Kizer, Jorge R (J Am Heart Assoc, 2022)
Background Advanced glycation endproducts (AGEs) have been linked to cardiovascular disease (CVD) in cohorts with and without diabetes. Data are lacking on prospective associations of various α-dicarbonyl-derived AGEs and incident CVD in the general population. We tested the hypothesis that major plasma AGEs are associated with new-onset CVD in 2 population-based cohorts of differing age and comorbidities. Methods and Results Analyses involved a random subcohort (n=466) from the Cardiovascular Health Study and a case-cohort sample (n=1631) from the Multi-Ethnic Study of Atherosclerosis. Five AGEs and 2 oxidative products were measured by liquid chromatography tandem mass spectrometry. Associations with CVD (myocardial infarction and stroke) were evaluated with Cox regression. Participants in the Cardiovascular Health Study were older than the Multi-Ethnic Study of Atherosclerosis, and had more comorbidities, along with higher levels of all AGEs. During median follow-up of 11 years, 439 participants in the Multi-Ethnic Study of Atherosclerosis and 200 in the Cardiovascular Health Study developed CVD. After multivariable adjustment, carboxymethyl-lysine, 3-deoxyglucosone hydroimidazolones and a summary variable of all measured AGEs (principal component 1) were significantly associated with incident CVD in the Cardiovascular Health Study (HRs [95% CI]: 1.20 [1.01, 1.42], 1.45 [1.23, 1.72], and 1.29 [1.06, 1.56], respectively), but not the Multi-Ethnic Study of Atherosclerosis. Oxidative products were not associated with CVD in either cohort. Conclusions We found α-dicarbonyl-derived AGEs to be associated with CVD in an older cohort, but not in a healthier middle-aged/older cohort. Our results suggest that AGEs may exert detrimental cardiovascular effects only under conditions of marked dicarbonyl and oxidative stress. Further investigation of α-dicarbonyl derivatives could lead to potential new strategies for CVD prevention in high-risk older populations.
Keywords: Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Glycation End Products, Advanced; Humans; Middle Aged; Risk Factors

Pooled Cohort Probability Score for Subclinical Airflow Obstruction. - Bhatt, Surya P; Balte, Pallavi P; Schwartz, Joseph E; Jaeger, Byron C; Cassano, Patricia A; Chaves, Paulo H; Couper, David; Jacobs, David R; Kalhan, Ravi; Kaplan, Robert; Lloyd-Jones, Donald; Newman, Anne B; et al. (Ann Am Thorac Soc, 2022)
Early detection of chronic obstructive pulmonary disease (COPD) is a public health priority. Airflow obstruction is the single most important risk factor for adverse COPD outcomes, but spirometry is not routinely recommended for screening. To describe the burden of subclinical airflow obstruction (SAO) and to develop a probability score for SAO to inform potential detection and prevention programs. Lung function and clinical data were harmonized and pooled across nine U.S. general population cohorts. Adults with respiratory symptoms, inhaler use, or prior diagnosis of COPD or asthma were excluded. A probability score for prevalent SAO (forced expiratory volume in 1 second/forced vital capacity < 0.70) was developed via hierarchical group-lasso regularization from clinical variables in strata of sex and smoking status, and its discriminative accuracy for SAO was assessed in the pooled cohort as well as in an external validation cohort (NHANES [National Health and Nutrition Examination Survey] 2011-2012). Incident hospitalizations and deaths due to COPD (respiratory events) were defined by adjudication or administrative criteria in four of nine cohorts. Of 33,546 participants (mean age 52 yr, 54% female, 44% non-Hispanic White), 4,424 (13.2%) had prevalent SAO. The incidence of respiratory events ( = 14,024) was threefold higher in participants with SAO versus those without (152 vs. 39 events/10,000 person-years). The probability score, which was based on six commonly available variables (age, sex, race and/or ethnicity, body mass index, smoking status, and smoking pack-years) was well calibrated and showed excellent discrimination in both the testing sample (C-statistic, 0.81; 95% confidence interval [CI], 0.80-0.82) and in NHANES (C-statistic, 0.83; 95% CI, 0.80-0.86). Among participants with predicted probabilities ⩾ 15%, 3.2 would need to undergo spirometry to detect one case of SAO. Adults with SAO demonstrate excess respiratory hospitalization and mortality. A probability score for SAO using commonly available clinical risk factors may be suitable for targeting screening and primary prevention strategies.
Keywords: Adult; Female; Forced Expiratory Volume; Humans; Lung; Male; Middle Aged; Nutrition Surveys; Pulmonary Disease, Chronic Obstructive; Risk Factors; Spirometry; Vital Capacity

Trimethylamine N-oxide and hip fracture and bone mineral density in older adults: The cardiovascular health study. - Elam, Rachel E; Bůzková, Petra; Barzilay, Joshua I; Wang, Zeneng; Nemet, Ina; Budoff, Matthew J; Cauley, Jane A; Fink, Howard A; Lee, Yujin; Robbins, John A; Wang, Meng; Hazen, Stanley L; et al. (Bone, 2022)
CONTEXT: Gut microbiota-derived metabolite trimethylamine N-oxide (TMAO) may adversely affect bone by inducing oxidative stress. Whether this translates into increased fracture risk in older adults is uncertain. OBJECTIVE: Determine the associations of plasma TMAO with hip fracture and bone mineral density (BMD) in older adults. DESIGN AND SETTING: Cox hazard models and linear regression stratified by sex examined the associations of TMAO with hip fracture and BMD in the longitudinal cohort of the Cardiovascular Health Study. PARTICIPANTS: 5019 U.S. adults aged ≥65 years. EXPOSURE: Plasma TMAO. MAIN OUTCOME MEASURES: Incident hip fractures; total hip BMD dual x-ray absorptiometry in a subset (n = 1400). RESULTS: Six hundred sixty-six incident hip fractures occurred during up to 26 years of follow-up (67,574 person-years). After multivariable adjustment, TMAO was not significantly associated with hip fracture (women: hazard ratio (HR) [95% confidence interval (CI)] of 1.00[0.92,1.09] per TMAO doubling; men: 1.12[0.95,1.33]). TMAO was also not associated with total hip BMD (women: BMD difference [95% CI] of 0.42 g/cm*100 [-0.34,1.17] per TMAO doubling; men: 0.19[-1.04,1.42]). In exploratory analyses, we found an interaction between body mass index (BMI) and the association of TMAO with hip fracture (P < 0.01). Higher TMAO was significantly associated with risk of hip fracture in adults with overweight or obesity (BMI ≥ 25) (HR [95% CI]:1.17[1.05,1.31]), but not normal or underweight. CONCLUSIONS: Among older US men and women, TMAO was not significantly associated with risk of hip fracture or BMD overall. Exploratory analyses suggested a significant association between higher TMAO and hip fracture when BMI was elevated, which merits further study.
Keywords: Absorptiometry, Photon; Aged; Bone Density; Female; Hip Fractures; Humans; Male; Methylamines; Risk Factors

Association between 5-year change in cardiovascular risk and the incidence of atherosclerotic cardiovascular diseases: a multi-cohort study. - Yi, Jiayi; Wang, Lili; Guo, Xinli; Ren, Xiangpeng (J Transl Med, 2023)
BACKGROUND: The influence of the historical cardiovascular risk status on future risk of atherosclerotic cardiovascular disease (ASCVD) is poorly understood. We aimed to investigate the association between 5-year changes in cardiovascular risk and ASCVD incidence. METHODS: We analyzed pooled data from seven community-based prospective cohort studies with up to 20 years of follow-up data. The study populations included White or Black participants aged 40-75 years without prevalent ASCVD. Cardiovascular risk was assessed using the pooled cohort equation and was categorized into non-high (< 20%) or high risk (≥ 20%). Changes in cardiovascular disease (CVD) risk over a 5-year interval were recorded. The main outcome was incident ASCVD. RESULTS: Among 11,026 participants (mean [SD] age, 60.0 [8.1] years), 4272 (38.7%) were female and 3127 (28.4%) were Black. During a median follow-up period of 9.9 years, 2560 (23.2%) ASCVD events occurred. In comparison with individuals showing a consistently high CVD risk, participants whose CVD risk changed from non-high to high (hazard ratio [HR], 0.67; 95% confidence interval [CI] 0.59-0.77) or high to non-high (HR, 0.57; 95% CI 0.41-0.80) and those with a consistently non-high risk (HR, 0.33; 95% CI 0.29-0.37) had a lower risk of incident ASCVD. In comparison with individuals showing a consistently non-high CVD risk, participants whose CVD risk changed from high to non-high (HR, 1.74; 95% CI 1.26-2.41) or from non-high to high risk (HR, 2.04; 95% CI 1.84-2.27) and those with a consistently high risk (HR 3.03; 95% CI 2.69-3.42) also showed an increased risk of incident ASCVD. CONCLUSIONS: Individuals with the same current CVD risk status but different historical CVD risks exhibited varying risks of future ASCVD incidents. Dynamic risk evaluation may enable more accurate cardiovascular risk stratification, and decision-making regarding preventive interventions should take the historical risk status into account.
Keywords: Atherosclerosis; Cardiovascular Diseases; Cohort Studies; Female; Heart Disease Risk Factors; Humans; Incidence; Male; Middle Aged; Prospective Studies; Risk Factors

Association of covert brain infarcts and white matter hyperintensities with risk of hip fracture in older adults: the Cardiovascular Health Study. - Sheets, Kerry M; Bůzková, Petra; Chen, Zhao; Carbone, Laura D; Cauley, Jane A; Barzilay, Joshua I; Starks, Jamie L; Miller, Lindsay M; Fink, Howard A (Osteoporos Int, 2023)
UNLABELLED: Covert brain infarcts and white matter hyperintensities (WMHs), incidental markers of brain microvascular disease commonly seen on brain MRIs in older adults, have been associated with falls and lower bone mineral density. We found covert infarcts and WMHs may also be associated with an increased risk of future hip fracture. INTRODUCTION: To determine whether covert infarcts and white matter hyperintensities (WMHs) are associated with increased risk of incident hip fracture. METHODS: A prospective cohort of 3373 community-dwelling adults aged ≥ 65 years enrolled in the Cardiovascular Health Study with a brain MRI (1992-1993) was analyzed. Covert infarcts were categorized by number of infarcts and largest infarct size. WMH burden was assessed by radiologists and graded qualitatively from 0 (no WMHs) to 9 (extensive). RESULTS: Participants had 465 incident hip fractures during a mean follow-up of 12.8 years. The demographic-adjusted hazard of incident hip fracture was 32% higher among participants with ≥ 1 covert infarct compared to those without infarcts (hazard ratio (HR) 1.32; 95% CI, 1.08-1.62). The hazard of incident hip fracture was similar after further adjustment for medications and medical history (HR = 1.34; 95% CI, 1.08-1.65), but attenuated following additional adjustment for functional status, frailty, and falls (HR = 1.25; 95% CI, 0.99-1.57). Fully adjusted hazard of incident hip fracture per increase in infarct number was 1.10 (95% CI, 0.98-1.23); risk in individuals whose largest infarct was ≥ 20 mm versus 3 to < 20 mm was similar. Compared with WMH grades 0-1, the demographic-adjusted hazard of hip fracture was 1.34 (95% CI, 1.09-1.66) and 1.83 (95% CI, 1.37-2.46), respectively, for WMH grades 2-3 and 4-9. The hazard was similar following adjustment for medications and medical history (grades 2-3: HR = 1.32; 95% CI, 1.05-1.64; grades 4-9: HR = 1.69; 95% CI, 1.23-2.30), but attenuated following additional adjustment for functional status, frailty, and falls (grades 2-3: HR = 1.24; 95% CI, 0.98-1.56; grades 4-9: HR = 1.34; 95% CI, 0.95-1.90). CONCLUSION: Older, community-dwelling adults with covert infarcts or WMHs may be at increased risk of hip fracture.
Keywords: Aged; Brain Infarction; Frailty; Hip Fractures; Humans; Prospective Studies; Risk Factors; White Matter

Association of Obesity With Cognitive Decline in Black and White Americans. - Quaye, Emmanuel; Galecki, Andrzej T; Tilton, Nicholas; Whitney, Rachael; Briceño, Emily M; Elkind, Mitchell S V; Fitzpatrick, Annette L; Gottesman, Rebecca F; Griswold, Michael; Gross, Alden L; Heckbert, Susan R; Hughes, Timothy M; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: There are disparities in the prevalence of obesity by race, and the relationship between obesity and cognitive decline is unclear. The objective of this study was to determine whether obesity is independently associated with cognitive decline and whether the association between obesity and cognitive decline differs in Black and White adults. We hypothesized that obesity is associated with greater cognitive decline compared with normal weight and that the effect of obesity on cognitive decline is more pronounced in Black adults compared with their White counterparts. METHODS: We pooled data from 28,867 participants free of stroke and dementia (mean, SD: age 61 [10.7] years at the first cognitive assessment, 55% female, 24% Black, and 29% obese) from 6 cohorts. The primary outcome was the annual change in global cognition. We performed linear mixed-effects models with and without time-varying cumulative mean systolic blood pressure (SBP) and fasting plasma glucose (FPG). Global cognition was set to a t-score metric (mean 50, SD 10) at a participant's first cognitive assessment; a 1-point difference represents a 0.1 SD difference in global cognition across the 6 cohorts. The median follow-up was 6.5 years (25th percentile, 75th percentile: 5.03, 20.15). RESULTS: Obese participants had lower baseline global cognition than normal-weight participants (difference in intercepts, -0.36 [95% CI, -0.46 to -0.17]; < 0.001). This difference in baseline global cognition was attenuated but was borderline significant after accounting for SBP and FPG (adjusted differences in intercepts, -0.19 [95% CI, -0.39 to 0.002]; = 0.05). There was no difference in the rate of decline in global cognition between obese and normal-weight participants (difference in slope, 0.009 points/year [95% CI, -0.009 to 0.03]; = 0.32). After accounting for SBP and FPG, obese participants had a slower decline in global cognition (adjusted difference in slope, 0.03 points/year slower [95% CI, 0.01 to 0.05]; < 0.001). There was no evidence that race modified the association between body mass index and global cognitive decline ( = 0.34). DISCUSSION: These results suggest that obesity is associated with lower initial cognitive scores and may potentially attenuate declines in cognition after accounting for BP and FPG.
Keywords: Aged; Black or African American; Cognition; Cognitive Dysfunction; Female; Humans; Male; Middle Aged; Obesity; Risk Factors; United States; White

Association of omega 3 polyunsaturated fatty acids with incident chronic kidney disease: pooled analysis of 19 cohorts. - Ong, Kwok Leung; Marklund, Matti; Huang, Liping; Rye, Kerry-Anne; Hui, Nicholas; Pan, Xiong-Fei; Rebholz, Casey M; Kim, Hyunju; Steffen, Lyn M; van Westing, Anniek C; Geleijnse, Johanna M; Hoogeveen, Ellen K; et al. (BMJ, 2023)
OBJECTIVE: To assess the prospective associations of circulating levels of omega 3 polyunsaturated fatty acid (n-3 PUFA) biomarkers (including plant derived α linolenic acid and seafood derived eicosapentaenoic acid, docosapentaenoic acid, and docosahexaenoic acid) with incident chronic kidney disease (CKD). DESIGN: Pooled analysis. DATA SOURCES: A consortium of 19 studies from 12 countries identified up to May 2020. STUDY SELECTION: Prospective studies with measured n-3 PUFA biomarker data and incident CKD based on estimated glomerular filtration rate. DATA EXTRACTION AND SYNTHESIS: Each participating cohort conducted de novo analysis with prespecified and consistent exposures, outcomes, covariates, and models. The results were pooled across cohorts using inverse variance weighted meta-analysis. MAIN OUTCOME MEASURES: Primary outcome of incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m. In a sensitivity analysis, incident CKD was defined as new onset estimated glomerular filtration rate <60 mL/min/1.73 m and <75% of baseline rate. RESULTS: 25 570 participants were included in the primary outcome analysis and 4944 (19.3%) developed incident CKD during follow-up (weighted median 11.3 years). In multivariable adjusted models, higher levels of total seafood n-3 PUFAs were associated with a lower incident CKD risk (relative risk per interquintile range 0.92, 95% confidence interval 0.86 to 0.98; P=0.009, I=9.9%). In categorical analyses, participants with total seafood n-3 PUFA level in the highest fifth had 13% lower risk of incident CKD compared with those in the lowest fifth (0.87, 0.80 to 0.96; P=0.005, I=0.0%). Plant derived α linolenic acid levels were not associated with incident CKD (1.00, 0.94 to 1.06; P=0.94, I=5.8%). Similar results were obtained in the sensitivity analysis. The association appeared consistent across subgroups by age (≥60 <60 years), estimated glomerular filtration rate (60-89 ≥90 mL/min/1.73 m), hypertension, diabetes, and coronary heart disease at baseline. CONCLUSIONS: Higher seafood derived n-3 PUFA levels were associated with lower risk of incident CKD, although this association was not found for plant derived n-3 PUFAs. These results support a favourable role for seafood derived n-3 PUFAs in preventing CKD.
Keywords: alpha-Linolenic Acid; Fatty Acids, Omega-3; Fatty Acids, Unsaturated; Humans; Middle Aged; Prospective Studies; Renal Insufficiency, Chronic; Risk Factors

CHARGE-AF: A Useful Score For Atrial Fibrillation Prediction? - Goudis, Christos; Daios, Stylianos; Dimitriadis, Fotios; Liu, Tong (Curr Cardiol Rev, 2023)
Atrial fibrillation (AF) is the commonest arrhythmia in clinical practice and is associated with increased morbidity and mortality. Various predictive scores for new-onset AF have been proposed, but so far, none have been widely used in clinical practice. CHARGE-AF score was developed from a pooled diverse population from three large cohorts (Atherosclerosis Risk in Communities study, Cardiovascular Health Study and Framingham Heart Study). A simple 5-year predictive model includes the variables of age, race, height, weight, systolic and diastolic blood pressure, current smoking, use of antihypertensive medication, diabetes mellitus, history of myocardial infarction and heart failure. Recent studies report that the CHARGE-AF score has good discrimination for incident AF and seems to be a promising prediction model for this arrhythmia. New screening tools (smartphone apps, smartwatches) are rapidly developing for AF detection. Therefore, the wide application of the CHARGE-AF score in clinical practice and the upcoming usage of mobile health technologies and smartwatches may result in better AF prediction and adequate stroke prevention, especially in high-risk patients.
Keywords: Atherosclerosis; Atrial Fibrillation; Heart Failure; Humans; Incidence; Myocardial Infarction; Risk Assessment; Risk Factors

CogDrisk, ANU-ADRI, CAIDE, and LIBRA Risk Scores for Estimating Dementia Risk. - Huque, Md Hamidul; Kootar, Scherazad; Eramudugolla, Ranmalee; Han, S Duke; Carlson, Michelle C; Lopez, Oscar L; Bennett, David A; Peters, Ruth; Anstey, Kaarin J (JAMA Netw Open, 2023)
IMPORTANCE: While the Australian National University-Alzheimer Disease Risk Index (ANU-ADRI), Cardiovascular Risk Factors, Aging, and Dementia (CAIDE), and Lifestyle for Brain Health (LIBRA) dementia risk tools have been widely used, a large body of new evidence has emerged since their publication. Recently, Cognitive Health and Dementia Risk Index (CogDrisk) and CogDrisk for Alzheimer disease (CogDrisk-AD) risk tools have been developed for the assessment of dementia and AD risk, respectively, using contemporary evidence; comparison of the relative performance of these risk tools is limited. OBJECTIVE: To evaluate the performance of CogDrisk, ANU-ADRI, CAIDE, LIBRA, and modified LIBRA (LIBRA with age and sex estimates from ANU-ADRI) in estimating dementia and AD risks (with CogDrisk-AD and ANU-ADRI). DESIGN, SETTING, AND PARTICIPANTS: This population-based cohort study obtained data from the Rush Memory and Aging Project (MAP), the Cardiovascular Health Study Cognition Study (CHS-CS), and the Health and Retirement Study-Aging, Demographics and Memory Study (HRS-ADAMS). Participants who were free of dementia at baseline were included. The factors were component variables in the risk tools that included self-reported baseline demographics, medical risk factors, and lifestyle habits. The study was conducted between November 2021 and March 2023, and statistical analysis was performed from January to June 2023. MAIN OUTCOMES AND MEASURES: Risk scores were calculated based on available factors in each of these cohorts. Area under the receiver operating characteristic curve (AUC) was calculated to measure the performance of each risk score. Multiple imputation was used to assess whether missing data may have affected estimates for dementia risk. RESULTS: Among the 6107 participants in 3 validation cohorts included for this study, 2184 participants without dementia at baseline were available from MAP (mean [SD] age, 80.0 [7.6] years; 1606 [73.5%] female), 548 participants without dementia at baseline were available from HRS-ADAMS (mean [SD] age, 79.5 [6.3] years; 288 [52.5%] female), and 3375 participants without dementia at baseline were available from CHS-CS (mean [SD] age, 74.8 [4.9] years; 1994 [59.1%] female). In all 3 cohorts, a similar AUC for dementia was obtained using CogDrisk, ANU-ADRI, and modified LIBRA (MAP cohort: CogDrisk AUC, 0.65 [95% CI, 0.61-0.69]; ANU-ADRI AUC, 0.65 [95% CI, 0.61-0.69]; modified LIBRA AUC, 0.65 [95% CI, 0.61-0.69]; HRS-ADAMS cohort: CogDrisk AUC, 0.75 [95% CI, 0.71-0.79]; ANU-ADRI AUC, 0.74 [95% CI, 0.70-0.78]; modified LIBRA AUC, 0.75 [95% CI, 0.71-0.79]; CHS-CS cohort: CogDrisk AUC, 0.70 [95% CI, 0.67-0.72]; ANU-ADRI AUC, 0.69 [95% CI, 0.66-0.72]; modified LIBRA AUC, 0.70 [95% CI, 0.68-0.73]). The CAIDE and LIBRA also provided similar but lower AUCs than the 3 aforementioned tools (eg, MAP cohort: CAIDE AUC, 0.50 [95% CI, 0.46-0.54]; LIBRA AUC, 0.53 [95% CI, 0.48-0.57]). The performance of CogDrisk-AD and ANU-ADRI in estimating AD risks was also similar. CONCLUSIONS AND RELEVANCE: CogDrisk and CogDrisk-AD performed similarly to ANU-ADRI in estimating dementia and AD risks. These results suggest that CogDrisk and CogDrisk-AD, with a greater range of modifiable risk factors compared with other risk tools in this study, may be more informative for risk reduction.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Australia; Cohort Studies; Female; Heart Disease Risk Factors; Humans; Male; Risk Factors

Evaluating the use of blood pressure polygenic risk scores across race/ethnic background groups. - Kurniansyah, Nuzulul; Goodman, Matthew O; Khan, Alyna T; Wang, Jiongming; Feofanova, Elena; Bis, Joshua C; Wiggins, Kerri L; Huffman, Jennifer E; Kelly, Tanika; Elfassy, Tali; Guo, Xiuqing; Palmas, Walter; et al. (Nat Commun, 2023)
We assess performance and limitations of polygenic risk scores (PRSs) for multiple blood pressure (BP) phenotypes in diverse population groups. We compare "clumping-and-thresholding" (PRSice2) and LD-based (LDPred2) methods to construct PRSs from each of multiple GWAS, as well as multi-PRS approaches that sum PRSs with and without weights, including PRS-CSx. We use datasets from the MGB Biobank, TOPMed study, UK biobank, and from All of Us to train, assess, and validate PRSs in groups defined by self-reported race/ethnic background (Asian, Black, Hispanic/Latino, and White). For both SBP and DBP, the PRS-CSx based PRS, constructed as a weighted sum of PRSs developed from multiple independent GWAS, perform best across all race/ethnic backgrounds. Stratified analysis in All of Us shows that PRSs are better predictive of BP in females compared to males, individuals without obesity, and middle-aged (40-60 years) compared to older and younger individuals.
Keywords: Blood Pressure; Ethnicity; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Multifactorial Inheritance; Population Health; Risk Factors

Genetic architecture of spatial electrical biomarkers for cardiac arrhythmia and relationship with cardiovascular disease. - Young, William J; Haessler, Jeffrey; Benjamins, Jan-Walter; Repetto, Linda; Yao, Jie; Isaacs, Aaron; Harper, Andrew R; Ramirez, Julia; Garnier, Sophie; Van Duijvenboden, Stefan; Baldassari, Antoine R; Concas, Maria Pina; et al. (Nat Commun, 2023)
The 3-dimensional spatial and 2-dimensional frontal QRS-T angles are measures derived from the vectorcardiogram. They are independent risk predictors for arrhythmia, but the underlying biology is unknown. Using multi-ancestry genome-wide association studies we identify 61 (58 previously unreported) loci for the spatial QRS-T angle (N = 118,780) and 11 for the frontal QRS-T angle (N = 159,715). Seven out of the 61 spatial QRS-T angle loci have not been reported for other electrocardiographic measures. Enrichments are observed in pathways related to cardiac and vascular development, muscle contraction, and hypertrophy. Pairwise genome-wide association studies with classical ECG traits identify shared genetic influences with PR interval and QRS duration. Phenome-wide scanning indicate associations with atrial fibrillation, atrioventricular block and arterial embolism and genetically determined QRS-T angle measures are associated with fascicular and bundle branch block (and also atrioventricular block for the frontal QRS-T angle). We identify potential biology involved in the QRS-T angle and their genetic relationships with cardiovascular traits and diseases, may inform future research and risk prediction.
Keywords: Arrhythmias, Cardiac; Atrioventricular Block; Biomarkers; Cardiovascular Diseases; Electrocardiography; Genome-Wide Association Study; Humans; Risk Factors

High-risk carotid plaques and incident ischemic stroke in patients with atrial fibrillation in the Cardiovascular Health Study. - Noubiap, Jean Jacques; Thomas, Gijo; Kamtchum-Tatuene, Joseph; Middeldorp, Melissa E; Sanders, Prashanthan (Eur J Neurol, 2023)
BACKGROUND AND PURPOSE: Whether carotid artery disease could improve stroke risk stratification tools in patients with atrial fibrillation (AF) remains uncertain. This study was undertaken to investigate the risk of ischemic stroke associated with occlusive and nonocclusive carotid atherosclerotic disease in patients with AF in the prospective population-based Cardiovascular Health Study. METHODS: We included participants aged ≥65 years with AF. We used multivariable Cox regression analysis to explore the risk of ischemic stroke associated with the percentage of carotid stenosis, plaque irregularity, echogenicity, and vulnerability (markedly irregular, ulcerated, or hypoechoic plaques). RESULTS: A total of 1398 participants were included (55.2% female, 61.7% aged 65-74 years). The maximum carotid stenosis was <50%, 50%-99%, and 100% in 94.5%, 5%, and 0.5% of participants, respectively. High-risk plaques based on echogenicity and plaque irregularity were found in 25.6% and 8.9% of participants, respectively. After a median follow-up of 10.9 years (interquartile range = 7.5-15.6), 298 ischemic strokes were recorded. There was no difference in the incidence of ischemic stroke according to the degree of carotid artery stenosis (p = 0.44), plaque echogenicity (low vs. high risk, p = 0.68), plaque irregularity (low vs. high risk, p = 0.55), and plaque vulnerability (p = 0.86). The CHA₂DS₂-VASc score was associated with an increased risk of ischemic stroke (adjusted hazard ratio = 1.28, 95% confidence interval = 1.18-1.40, p < 0.001). Both maximum grade of stenosis and plaque vulnerability were not associated with incident ischemic stroke (all p > 0.05). CONCLUSIONS: Neither the degree of carotid stenosis nor the presence of vulnerable plaques was associated with incident ischemic stroke in this cohort of individuals with AF. This suggests that carotid disease was probably not a significant contributor to ischemic stroke in this population.
Keywords: Atrial Fibrillation; Carotid Artery Diseases; Carotid Stenosis; Female; Humans; Ischemic Stroke; Male; Plaque, Atherosclerotic; Prospective Studies; Risk Factors; Stroke

Plasma Trimethylamine--Oxide and Incident Ischemic Stroke: The Cardiovascular Health Study and the Multi-Ethnic Study of Atherosclerosis. - Lemaitre, Rozenn N; Jensen, Paul N; Wang, Zeneng; Fretts, Amanda M; Sitlani, Colleen M; Nemet, Ina; Sotoodehnia, Nona; de Oliveira Otto, Marcia C; Zhu, Weifei; Budoff, Matt; Longstreth, W T; Psaty, Bruce M; et al. (J Am Heart Assoc, 2023)
Background The association of circulating trimethylamine--oxide (TMAO) with stroke has received limited attention. To address this gap, we examined the associations of serial measures of plasma TMAO with incident ischemic stroke. Methods and Results We used a prospective cohort design with data pooled from 2 cohorts. The settings were the CHS (Cardiovascular Health Study), a cohort of older adults, and the MESA (Multi-Ethnic Study of Atherosclerosis), both in the United States. We measured plasma concentrations of TMAO at baseline and again during the follow-up using high-performance liquid chromatography and mass spectrometry. We assessed the association of plasma TMAO with incident ischemic stroke using proportional hazards regression adjusted for risk factors. The combined cohorts included 11 785 participants without a history of stroke, on average 73 (CHS) and 62 (MESA) years old at baseline, including 60% (CHS) and 53% (MESA) women. We identified 1031 total incident ischemic strokes during a median 15-year follow-up in the combined cohorts. In multivariable analyses, TMAO was significantly associated with incident ischemic stroke risk (hazard ratios comparing a doubling of TMAO: 1.11 [1.03-1.18], =0.004). The association was linear over the range of TMAO concentrations and appeared restricted to those without diagnosed coronary heart disease. An association with hemorrhagic stroke was not found. Conclusions Plasma TMAO levels are associated with incident ischemic stroke in a diverse population. Registration URL: https://www.clinicaltrials.gov. Unique identifier: NCT00005133.
Keywords: Aged; Atherosclerosis; Female; Humans; Ischemic Stroke; Methylamines; Oxides; Prospective Studies; Risk Factors; Stroke; United States

A proteomic analysis of atrial fibrillation in a prospective longitudinal cohort (AGES-Reykjavik study). - Jonmundsson, Thorarinn; Steindorsdottir, Anna E; Austin, Thomas R; Frick, Elisabet A; Axelsson, Gisli T; Launer, Lenore; Psaty, Bruce M; Loureiro, Joseph; Orth, Anthony P; Aspelund, Thor; Emilsson, Valur; Floyd, James S; et al. (Europace, 2023)
AIMS: Atrial fibrillation (AF) is associated with high risk of comorbidities and mortality. Our aim was to examine causal and predictive relationships between 4137 serum proteins and incident AF in the prospective population-based Age, Gene/Environment Susceptibility-Reykjavik (AGES-Reykjavik) study. METHODS AND RESULTS: The study included 4765 participants, of whom 1172 developed AF. Cox proportional hazards regression models were fitted for 4137 baseline protein measurements adjusting for known risk factors. Protein associations were tested for replication in the Cardiovascular Health Study (CHS). Causal relationships were examined in a bidirectional, two-sample Mendelian randomization analysis. The time-dependent area under the receiver operating characteristic curve (AUC)-statistic was examined as protein levels and an AF-polygenic risk score (PRS) were added to clinical risk models. The proteomic signature of incident AF consisted of 76 proteins, of which 63 (83%) were novel and 29 (38%) were replicated in CHS. The signature included both N-terminal prohormone of brain natriuretic peptide (NT-proBNP)-dependent (e.g. CHST15, ATP1B1, and SVEP1) and independent components (e.g. ASPN, AKR1B, and LAMA1/LAMB1/LAMC1). Nine causal candidates were identified (TAGLN, WARS, CHST15, CHMP3, COL15A1, DUSP13, MANBA, QSOX2, and SRL). The reverse causal analysis suggested that most AF-associated proteins were affected by the genetic liability to AF. N-terminal prohormone of brain natriuretic peptide improved the prediction of incident AF events close to baseline with further improvements gained by the AF-PRS at all time points. CONCLUSION: The AF proteomic signature includes biologically relevant proteins, some of which may be causal. It mainly reflects an NT-proBNP-dependent consequence of the genetic liability to AF. N-terminal prohormone of brain natriuretic peptide is a promising marker for incident AF in the short term, but risk assessment incorporating a PRS may improve long-term risk assessment.
Keywords: Atrial Fibrillation; Biomarkers; Endosomal Sorting Complexes Required for Transport; Humans; Natriuretic Peptide, Brain; Oxidoreductases Acting on Sulfur Group Donors; Peptide Fragments; Prognosis; Prospective Studies; Proteomics; Risk Factors

Association of serum levels of phenylalanine and tyrosine with hip fractures and frailty in older adults: The cardiovascular health study. - Carbone, Laura; Bůzková, Petra; Robbins, John A; Fink, Howard A; Barzilay, Joshua I; Elam, Rachel E; Isales, Carlos (Arch Osteoporos, 2024)
UNLABELLED: This study examined if the amino acids phenylalanine or tyrosine contribute to risk of hip fracture or frailty in older adults. We determined that neither phenylalanine nor tyrosine are important predictors of hip fracture or frailty. We suggest advice on protein intake for skeletal health consider specific amino acid composition. PURPOSE: Protein is essential for skeletal health, but the specific amino acid compositions of protein may have differential associations with fracture risk. The aim of this study was to determine the association of serum levels of the aromatic amino acids phenylalanine and tyrosine with risk for incident hip fractures over twelve years of follow-up and cross sectional associations with frailty. METHODS: We included 131 older men and women from the Cardiovascular Health Study (CHS) who sustained a hip fracture over twelve years of follow-up and 131 men and women without an incident hip fracture over this same period of time. 42% of this cohort were men and 95% were Caucasian. Weighted multivariable Cox hazards molecules were used to estimate the hazard ratios (HR) and 95% confidence intervals (CI) of incident hip fracture associated with a one standard deviation (SD) higher serum level of phenylalanine or tyrosine. Relative risk regression was used to determine the cross-sectional association of these amino acids with Freid's frailty index. RESULTS: Neither serum levels of phenylalanine (HR 0.85 (95% CI 0.62-1.16) or tyrosine (HR 0.82 (95% CI 0.62-1.1) were significantly associated with incident hip fractures or cross sectionally with frailty (frail compared with prefrail/not frail) (HR 0.92 (95% CI 0.48-1.76) and HR (0.86 (95% CI 0.46-1.61) respectively. CONCLUSION: Phenylalanine and tyrosine are not significant contributors to hip fractures or frailty in older men and women.
Keywords: Aged; Aged, 80 and over; Cross-Sectional Studies; Female; Frail Elderly; Frailty; Hip Fractures; Humans; Male; Phenylalanine; Risk Factors; Tyrosine

Associations between toxicity-weighted concentrations and dementia risk: Results from the Cardiovascular Health Cognition Study. - Crane, Breanna M; Moored, Kyle D; Donahue, Patrick T; Corrigan, Anne E; Curriero, Frank C; Shields, Timothy M; Desjardins, Michael R; Richards, Emily A; Rosso, Andrea L; Lovasi, Gina S; Odden, Michelle C; Lopez, Oscar L; et al. (Sci Total Environ, 2024)
BACKGROUND: Air pollution is a modifiable risk factor for dementia. Yet, studies on specific sources of air pollution (i.e., toxic chemical emissions from industrial facilities) and dementia risk are scarce. We examined associations between toxicity-weighted concentrations of industrial pollution and dementia outcomes among a large, multi-site cohort of older adults. METHODS: Participants (n = 2770) were ≥ 65 years old (Mean = 75.3, SD = 5.1 years) from the Cardiovascular Health Cognition Study (1992-1999). Toxicity-weighted concentrations were estimated using the Risk Screening Environmental Indicator (RSEI) model which incorporates total reported chemical emissions with toxicity, fate, and transport models. Estimates were aggregated to participants' baseline census tract, averaged across 1988-1992, and log2-transformed. Dementia status was clinically adjudicated in 1998-1999 and categorized by subtype (Alzheimer's, vascular, mixed). We assessed whether RSEI-estimated toxicity-weighted concentrations were associated with 1) odds of prevalent dementia and 2) incident dementia risk by subtype. RESULTS: After adjusting for individual and census-tract level covariates, a doubling in toxicity-weighted concentrations was associated with 9 % higher odds of prevalent dementia (OR = 1.09, 95 % CI: 1.00, 1.19). In discrete-time survival models, each doubling in toxicity-weighted concentrations was associated with a 16 % greater hazard of vascular dementia (HR = 1.16, 95 % CI: 1.01, 1.34) but was not significantly associated with all-cause, Alzheimer's disease, or mixed dementia (p's > 0.05). DISCUSSION: Living in regions with higher toxicity-weighted concentrations was associated with higher odds of prevalent dementia and a higher risk of incident vascular dementia in this large, community-based cohort of older adults. These findings support the need for additional studies to examine whether toxic chemical emissions from industrial and federal facilities may be a modifiable target for dementia prevention.
Keywords: Aged; Aged, 80 and over; Air Pollutants; Air Pollution; Dementia; Environmental Exposure; Female; Humans; Male; Risk Factors

Cumulative Systolic Blood Pressure and Incident Stroke Type Variation by Race and Ethnicity. - Johnson, Kimson E; Li, Hanyu; Zhang, Min; Springer, Mellanie V; Galecki, Andrzej T; Whitney, Rachael T; Gottesman, Rebecca F; Hayward, Rodney A; Sidney, Stephen; Elkind, Mitchell S V; Longstreth, W T; Heckbert, Susan R; et al. (JAMA Netw Open, 2024)
IMPORTANCE: Stroke risk varies by systolic blood pressure (SBP), race, and ethnicity. The association between cumulative mean SBP and incident stroke type is unclear, and whether this association differs by race and ethnicity remains unknown. OBJECTIVE: To examine the association between cumulative mean SBP and first incident stroke among 3 major stroke types-ischemic stroke (IS), intracerebral hemorrhage (ICH), and subarachnoid hemorrhage (SAH)-and explore how these associations vary by race and ethnicity. DESIGN, SETTING, AND PARTICIPANTS: Individual participant data from 6 US longitudinal cohorts (January 1, 1971, to December 31, 2019) were pooled. The analysis was performed from January 1, 2022, to January 2, 2024. The median follow-up was 21.6 (IQR, 13.6-31.8) years. EXPOSURE: Time-dependent cumulative mean SBP. MAIN OUTCOMES AND MEASURES: The primary outcome was time from baseline visit to first incident stroke. Secondary outcomes consisted of time to first incident IS, ICH, and SAH. RESULTS: Among 40 016 participants, 38 167 who were 18 years or older at baseline with no history of stroke and at least 1 SBP measurement before the first incident stroke were included in the analysis. Of these, 54.0% were women; 25.0% were Black, 8.9% were Hispanic of any race, and 66.2% were White. The mean (SD) age at baseline was 53.4 (17.0) years and the mean (SD) SBP at baseline was 136.9 (20.4) mm Hg. A 10-mm Hg higher cumulative mean SBP was associated with a higher risk of overall stroke (hazard ratio [HR], 1.20 [95% CI, 1.18-1.23]), IS (HR, 1.20 [95% CI, 1.17-1.22]), and ICH (HR, 1.31 [95% CI, 1.25-1.38]) but not SAH (HR, 1.13 [95% CI, 0.99-1.29]; P = .06). Compared with White participants, Black participants had a higher risk of IS (HR, 1.20 [95% CI, 1.09-1.33]) and ICH (HR, 1.67 [95% CI, 1.30-2.13]) and Hispanic participants of any race had a higher risk of SAH (HR, 3.81 [95% CI, 1.29-11.22]). There was no consistent evidence that race and ethnicity modified the association of cumulative mean SBP with first incident stroke and stroke type. CONCLUSIONS AND RELEVANCE: The findings of this cohort study suggest that cumulative mean SBP was associated with incident stroke type, but the associations did not differ by race and ethnicity. Culturally informed stroke prevention programs should address modifiable risk factors such as SBP along with social determinants of health and structural inequities in society.
Keywords: Adult; Aged; Black or African American; Blood Pressure; Cerebral Hemorrhage; Ethnicity; Female; Hispanic or Latino; Humans; Hypertension; Incidence; Ischemic Stroke; Longitudinal Studies; Male; Middle Aged; Racial Groups; Risk Factors; Stroke; Subarachnoid Hemorrhage; United States; White; White People

Development and Validation of the American Heart Association's PREVENT Equations. - Khan, Sadiya S; Matsushita, Kunihiro; Sang, Yingying; Ballew, Shoshana H; Grams, Morgan E; Surapaneni, Aditya; Blaha, Michael J; Carson, April P; Chang, Alexander R; Ciemins, Elizabeth; Go, Alan S; Gutierrez, Orlando M; et al. (Circulation, 2024)
BACKGROUND: Multivariable equations are recommended by primary prevention guidelines to assess absolute risk of cardiovascular disease (CVD). However, current equations have several limitations. Therefore, we developed and validated the American Heart Association Predicting Risk of CVD EVENTs (PREVENT) equations among US adults 30 to 79 years of age without known CVD. METHODS: The derivation sample included individual-level participant data from 25 data sets (N=3 281 919) between 1992 and 2017. The primary outcome was CVD (atherosclerotic CVD and heart failure). Predictors included traditional risk factors (smoking status, systolic blood pressure, cholesterol, antihypertensive or statin use, and diabetes) and estimated glomerular filtration rate. Models were sex-specific, race-free, developed on the age scale, and adjusted for competing risk of non-CVD death. Analyses were conducted in each data set and meta-analyzed. Discrimination was assessed using the Harrell C-statistic. Calibration was calculated as the slope of the observed versus predicted risk by decile. Additional equations to predict each CVD subtype (atherosclerotic CVD and heart failure) and include optional predictors (urine albumin-to-creatinine ratio and hemoglobin A1c), and social deprivation index were also developed. External validation was performed in 3 330 085 participants from 21 additional data sets. RESULTS: Among 6 612 004 adults included, mean±SD age was 53±12 years, and 56% were women. Over a mean±SD follow-up of 4.8±3.1 years, there were 211 515 incident total CVD events. The median C-statistics in external validation for CVD were 0.794 (interquartile interval, 0.763-0.809) in female and 0.757 (0.727-0.778) in male participants. The calibration slopes were 1.03 (interquartile interval, 0.81-1.16) and 0.94 (0.81-1.13) among female and male participants, respectively. Similar estimates for discrimination and calibration were observed for atherosclerotic CVD- and heart failure-specific models. The improvement in discrimination was small but statistically significant when urine albumin-to-creatinine ratio, hemoglobin A1c, and social deprivation index were added together to the base model to total CVD (ΔC-statistic [interquartile interval] 0.004 [0.004-0.005] and 0.005 [0.004-0.007] among female and male participants, respectively). Calibration improved significantly when the urine albumin-to-creatinine ratio was added to the base model among those with marked albuminuria (>300 mg/g; 1.05 [0.84-1.20] versus 1.39 [1.14-1.65]; =0.01). CONCLUSIONS: PREVENT equations accurately and precisely predicted risk for incident CVD and CVD subtypes in a large, diverse, and contemporary sample of US adults by using routinely available clinical variables.
Keywords: Adult; Aged; Albumins; American Heart Association; Atherosclerosis; Cardiovascular Diseases; Creatinine; Female; Glycated Hemoglobin; Heart Failure; Humans; Male; Middle Aged; Risk Assessment; Risk Factors

Genetic Complexities of Cerebral Small Vessel Disease, Blood Pressure, and Dementia. - Sargurupremraj, Muralidharan; Soumaré, Aïcha; Bis, Joshua C; Surakka, Ida; Jürgenson, Tuuli; Joly, Pierre; Knol, Maria J; Wang, Ruiqi; Yang, Qiong; Satizabal, Claudia L; Gudjonsson, Alexander; Mishra, Aniket; et al. (JAMA Netw Open, 2024)
IMPORTANCE: Vascular disease is a treatable contributor to dementia risk, but the role of specific markers remains unclear, making prevention strategies uncertain. OBJECTIVE: To investigate the causal association between white matter hyperintensity (WMH) burden, clinical stroke, blood pressure (BP), and dementia risk, while accounting for potential epidemiologic biases. DESIGN, SETTING, AND PARTICIPANTS: This study first examined the association of genetically determined WMH burden, stroke, and BP levels with Alzheimer disease (AD) in a 2-sample mendelian randomization (2SMR) framework. Second, using population-based studies (1979-2018) with prospective dementia surveillance, the genetic association of WMH, stroke, and BP with incident all-cause dementia was examined. Data analysis was performed from July 26, 2020, through July 24, 2022. EXPOSURES: Genetically determined WMH burden and BP levels, as well as genetic liability to stroke derived from genome-wide association studies (GWASs) in European ancestry populations. MAIN OUTCOMES AND MEASURES: The association of genetic instruments for WMH, stroke, and BP with dementia was studied using GWASs of AD (defined clinically and additionally meta-analyzed including both clinically diagnosed AD and AD defined based on parental history [AD-meta]) for 2SMR and incident all-cause dementia for longitudinal analyses. RESULTS: In 2SMR (summary statistics-based) analyses using AD GWASs with up to 75 024 AD cases (mean [SD] age at AD onset, 75.5 [4.4] years; 56.9% women), larger WMH burden showed evidence for a causal association with increased risk of AD (odds ratio [OR], 1.43; 95% CI, 1.10-1.86; P = .007, per unit increase in WMH risk alleles) and AD-meta (OR, 1.19; 95% CI, 1.06-1.34; P = .008), after accounting for pulse pressure for the former. Blood pressure traits showed evidence for a protective association with AD, with evidence for confounding by shared genetic instruments. In the longitudinal (individual-level data) analyses involving 10 699 incident all-cause dementia cases (mean [SD] age at dementia diagnosis, 74.4 [9.1] years; 55.4% women), no significant association was observed between larger WMH burden and incident all-cause dementia (hazard ratio [HR], 1.02; 95% CI, 1.00-1.04; P = .07). Although all exposures were associated with mortality, with the strongest association observed for systolic BP (HR, 1.04; 95% CI, 1.03-1.06; P = 1.9 × 10-14), there was no evidence for selective survival bias during follow-up using illness-death models. In secondary analyses using polygenic scores, the association of genetic liability to stroke, but not genetically determined WMH, with dementia outcomes was attenuated after adjusting for interim stroke. CONCLUSIONS: These findings suggest that WMH is a primary vascular factor associated with dementia risk, emphasizing its significance in preventive strategies for dementia. Future studies are warranted to examine whether this finding can be generalized to non-European populations.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Blood Pressure; Cerebral Small Vessel Diseases; Dementia; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Mendelian Randomization Analysis; Prospective Studies; Risk Factors; Stroke

High Throughput Plasma Proteomics and Risk of Heart Failure and Frailty in Late Life. - Ramonfaur, Diego; Buckley, Leo F; Arthur, Victoria; Yang, Yimin; Claggett, Brian L; Ndumele, Chiadi E; Walker, Keenan A; Austin, Thomas; Odden, Michelle C; Floyd, James S; Sanders-van Wijk, Sandra; Njoroge, Joyce; et al. (JAMA Cardiol, 2024)
IMPORTANCE: Heart failure (HF) and frailty frequently coexist and may share a common pathobiology, although the underlying mechanisms remain unclear. Understanding these mechanisms may provide guidance for preventing and treating both conditions. OBJECTIVE: To identify shared pathways between incident HF and frailty in late life using large-scale proteomics. DESIGN, SETTING, AND PARTICIPANTS: In this cohort study, 4877 aptamers (Somascan v4) were measured among participants in the community-based longitudinal Atherosclerosis Risk In Communities (ARIC) cohort study at visit 3 (V3; 1993-1995; n = 10 638) and at visit 5 (V5; 2011-2013; n = 3908). Analyses were externally replicated among 3189 participants in the Cardiovascular Health Study (CHS). Data analysis was conducted from February 2022 to June 2023. EXPOSURES: Protein aptamers, measured at study V3 and V5. MAIN OUTCOMES AND MEASURES: Outcomes assessed included incident HF hospitalization after V3 and after V5, prevalent frailty at V5, and incident frailty between V5 and visit 6 (V6; 2016-2017; n = 4131). Frailty was assessed using the Fried criteria. Analyses were adjusted for age, gender, race, field center, hypertension, diabetes, smoking status, body mass index, estimated glomerular filtration rate, prevalent coronary heart disease, prevalent atrial fibrillation, and history of myocardial infarction. Mendelian randomization (MR) analysis was performed to assess potential causal effects of candidate proteins on HF and frailty. RESULTS: A total of 4877 protein aptamers were measured among 10 638 participants at V3 (mean [SD] age, 60 [6] years; 4886 [46%] men). Overall, 286 proteins were associated with incident HF after V3 (822 events; P < 1.0 × 10-5), 83 of which were also associated with incident after V5 (336 events; P < 1.7 × 10-4). Among HF-free participants at V5 (n = 3908; mean [SD] age, 75 [5] years; 1861 [42%] men), 48 of 83 HF-associated proteins were associated with prevalent frailty (223 cases; P < 6.0 × 10-4), 18 of which were also associated with incident frailty at V6 (152 cases; P < 1.0 × 10-3). These proteins enriched fibrosis and inflammation pathways and demonstrated stronger associations with incident HF with preserved ejection fraction (HFpEF) than HF with reduced ejection fraction. All 18 proteins were associated with both prevalent frailty and incident HF in CHS. MR identified potential causal effects of several proteins on frailty and HF. CONCLUSIONS AND RELEVANCE: In this study, the proteins associated with risk of HF and frailty enrich for pathways related to inflammation and fibrosis as well as risk of HFpEF. Several of these proteins could potentially contribute to the shared pathophysiology of frailty and HF.
Keywords: Aged; Biomarkers; Female; Frailty; Heart Failure; Humans; Incidence; Male; Middle Aged; Proteomics; Risk Factors

Large-Scale Proteomics Identifies Novel Biomarkers and Circulating Risk Factors for Aortic Stenosis. - Shelbaya, Khaled; Arthur, Victoria; Yang, Yimin; Dorbala, Pranav; Buckley, Leo; Claggett, Brian; Skali, Hicham; Dufresne, Line; Yang, Ta-Yu; Engert, James C; Thanassoulis, George; Floyd, James; et al. (J Am Coll Cardiol, 2024)
BACKGROUND: Limited data exist regarding risk factors for aortic stenosis (AS). The plasma proteome is a promising phenotype for discovery of novel biomarkers and potentially causative mechanisms. OBJECTIVES: The aim of this study was to discover novel biomarkers with potentially causal associations with AS. METHODS: We measured 4,877 plasma proteins (SomaScan aptamer-affinity assay) among ARIC (Atherosclerosis Risk In Communities) study participants in mid-life (visit 3 [V3]; n = 11,430; age 60 ± 6 years) and in late-life (V5; n = 4,899; age 76 ± 5 years). We identified proteins cross-sectionally associated with aortic valve (AV) peak velocity (AVmax) and dimensionless index by echocardiography at V5 and with incident AV-related hospitalization after V3 with the use of multivariable linear and Cox proportional hazard regression. We assessed associations of candidate proteins with changes in AVmax over 6 years and with AV calcification with the use of cardiac computed tomography, replicated analysis in an independent sample, performed Mendelian randomization, and evaluated gene expression in explanted human AV tissue. RESULTS: Fifty-two proteins cross-sectionally were associated with AVmax and dimensionless index at V5 and with risk of incident AV-related hospitalization after V3. Among 3,413 participants in the Cardiovascular Health Study, 6 of those proteins were significantly associated with adjudicated moderate or severe AS, including matrix metalloproteinase 12 (MMP12), complement C1q tumor necrosis factor-related protein 1 (C1QTNF1), and growth differentiation factor-15. MMP12 was also associated with greater increase in AVmax over 6 years, greater degree of AV calcification, and greater expression in calcific compared with normal or fibrotic AV tissue. C1QTNF1 had consistent potential causal effects on both AS and AVmax according to Mendelian randomization analysis. CONCLUSIONS: These findings identify MMP12 as a potential novel circulating biomarker of AS risk and C1QTNF1 as a new putative target to prevent AS progression.
Keywords: Aged; Aged, 80 and over; Aortic Valve; Aortic Valve Stenosis; Biomarkers; Calcinosis; Humans; Matrix Metalloproteinase 12; Middle Aged; Proteomics; Risk Factors

Machine learning models for predicting blood pressure phenotypes by combining multiple polygenic risk scores. - Hrytsenko, Yana; Shea, Benjamin; Elgart, Michael; Kurniansyah, Nuzulul; Lyons, Genevieve; Morrison, Alanna C; Carson, April P; Haring, Bernhard; Mitchell, Braxton D; Psaty, Bruce M; Jaeger, Byron C; Gu, C Charles; et al. (Sci Rep, 2024)
We construct non-linear machine learning (ML) prediction models for systolic and diastolic blood pressure (SBP, DBP) using demographic and clinical variables and polygenic risk scores (PRSs). We developed a two-model ensemble, consisting of a baseline model, where prediction is based on demographic and clinical variables only, and a genetic model, where we also include PRSs. We evaluate the use of a linear versus a non-linear model at both the baseline and the genetic model levels and assess the improvement in performance when incorporating multiple PRSs. We report the ensemble model's performance as percentage variance explained (PVE) on a held-out test dataset. A non-linear baseline model improved the PVEs from 28.1 to 30.1% (SBP) and 14.3% to 17.4% (DBP) compared with a linear baseline model. Including seven PRSs in the genetic model computed based on the largest available GWAS of SBP/DBP improved the genetic model PVE from 4.8 to 5.1% (SBP) and 4.7 to 5% (DBP) compared to using a single PRS. Adding additional 14 PRSs computed based on two independent GWASs further increased the genetic model PVE to 6.3% (SBP) and 5.7% (DBP). PVE differed across self-reported race/ethnicity groups, with primarily all non-White groups benefitting from the inclusion of additional PRSs. In summary, non-linear ML models improves BP prediction in models incorporating diverse populations.
Keywords: Blood Pressure; Female; Genetic Predisposition to Disease; Genetic Risk Score; Genome-Wide Association Study; Humans; Hypertension; Machine Learning; Male; Middle Aged; Models, Genetic; Multifactorial Inheritance; Phenotype; Risk Factors

Role of Polyunsaturated Fat in Modifying Cardiovascular Risk Associated With Family History of Cardiovascular Disease: Pooled De Novo Results From 15 Observational Studies. - Laguzzi, Federica; Åkesson, Agneta; Marklund, Matti; Qian, Frank; Gigante, Bruna; Bartz, Traci M; Bassett, Julie K; Birukov, Anna; Campos, Hannia; Hirakawa, Yoichiro; Imamura, Fumiaki; Jäger, Susanne; et al. (Circulation, 2024)
BACKGROUND: It is unknown whether dietary intake of polyunsaturated fatty acids (PUFA) modifies the cardiovascular disease (CVD) risk associated with a family history of CVD. We assessed interactions between biomarkers of low PUFA intake and a family history in relation to long-term CVD risk in a large consortium. METHODS: Blood and tissue PUFA data from 40 885 CVD-free adults were assessed. PUFA levels ≤25th percentile were considered to reflect low intake of linoleic, alpha-linolenic, and eicosapentaenoic/docosahexaenoic acids (EPA/DHA). Family history was defined as having ≥1 first-degree relative who experienced a CVD event. Relative risks with 95% CI of CVD were estimated using Cox regression and meta-analyzed. Interactions were assessed by analyzing product terms and calculating relative excess risk due to interaction. RESULTS: After multivariable adjustments, a significant interaction between low EPA/DHA and family history was observed (product term pooled RR, 1.09 [95% CI, 1.02-1.16]; =0.01). The pooled relative risk of CVD associated with the combined exposure to low EPA/DHA, and family history was 1.41 (95% CI, 1.30-1.54), whereas it was 1.25 (95% CI, 1.16-1.33) for family history alone and 1.06 (95% CI, 0.98-1.14) for EPA/DHA alone, compared with those with neither exposure. The relative excess risk due to interaction results indicated no interactions. CONCLUSIONS: A significant interaction between biomarkers of low EPA/DHA intake, but not the other PUFA, and a family history was observed. This novel finding might suggest a need to emphasize the benefit of consuming oily fish for individuals with a family history of CVD.
Keywords: Animals; Biomarkers; Cardiovascular Diseases; Docosahexaenoic Acids; Fatty Acids, Omega-3; Risk Factors

Trimethylamine -Oxide and Related Gut Microbe-Derived Metabolites and Incident Heart Failure Development in Community-Based Populations. - Tang, W H Wilson; Lemaitre, Rozenn N; Jensen, Paul N; Wang, Meng; Wang, Zeneng; Li, Xinmin S; Nemet, Ina; Lee, Yujin; Lai, Heidi T M; de Oliveira Otto, Marcia C; Fretts, Amanda M; Sotoodehnia, Nona; et al. (Circ Heart Fail, 2024)
BACKGROUND: Growing evidence indicates that trimethylamine -oxide, a gut microbial metabolite of dietary choline and carnitine, promotes both cardiovascular disease and chronic kidney disease risk. It remains unclear how circulating concentrations of trimethylamine -oxide and its related dietary and gut microbe-derived metabolites (choline, betaine, carnitine, γ-butyrobetaine, and crotonobetaine) affect incident heart failure (HF). METHODS: We evaluated 11 768 participants from the Cardiovascular Health Study and the Multi-Ethnic Study of Atherosclerosis with serial measures of metabolites. Cox proportional hazard models were used to examine the associations between metabolites and incident HF, adjusted for cardiovascular disease risk factors. RESULTS: In all, 2102 cases of HF occurred over a median follow-up of 15.9 years. After adjusting for traditional risk factors, higher concentrations of trimethylamine -oxide (hazard ratio, 1.15 [95% CI, 1.09-1.20]; <0.001), choline (hazard ratio, 1.44 [95% CI, 1.26-1.64]; <0.001), and crotonobetaine (hazard ratio, 1.24 [95% CI, 1.16-1.32]; <0.001) were associated with increased risk for incident HF. After further adjustment for renal function (potential confounder or mediator), these associations did not reach Bonferroni-corrected statistical significance (=0.01, 0.049, and 0.006, respectively). Betaine and carnitine were nominally associated with a higher incidence of HF (<0.05). In exploratory analyses, results were similar for subtypes of HF based on left ventricular ejection fraction, and associations appeared generally stronger among Black and Hispanic/Latino versus White adults, although there were no interactions for any metabolites with race. CONCLUSIONS: In this pooled analysis of 2 well-phenotyped, diverse, community-based cohorts, circulating concentrations of gut microbe-derived metabolites such as trimethylamine -oxide, choline, and crotonobetaine were independently associated with a higher risk of developing HF. REGISTRATION: URL: https://www.clinicaltrials.gov/; Unique identifiers: NCT00005133 and NCT00005487.
Keywords: Aged; Aged, 80 and over; Betaine; Biomarkers; Carnitine; Choline; Female; Gastrointestinal Microbiome; Heart Failure; Humans; Incidence; Male; Methylamines; Middle Aged; Risk Factors; United States

Association Between Cigarette Smoking and Subclinical Markers of Cardiovascular Harm. - Yao, Zhiqi; Tasdighi, Erfan; Dardari, Zeina A; Jha, Kunal K; Osuji, Ngozi; Rajan, Tanuja; Boakye, Ellen; Rodriguez, Carlos J; Matsushita, Kunihiro; Simonsick, Eleanor M; Lima, João A C; Widome, Rachel; et al. (J Am Coll Cardiol, 2025)
BACKGROUND: Cigarette smoking is a strong risk factor for cardiovascular harm. OBJECTIVES: The study sought to explore the detailed relationships between smoking intensity, pack-years, and time since cessation with inflammation, thrombosis, and subclinical atherosclerosis markers of cardiovascular harm. METHODS: We included 182,364 participants (mean age 58.2 years, 69.0% female) from 22 cohorts of the Cross Cohort Collaboration with self-reported smoking status, including smoking intensity and/or pack-years, and concurrent subclinical marker measurements. Markers were categorized into 3 domains: inflammation (high-sensitivity C-reactive protein, interleukin-6, glycoprotein acetylation), thrombosis (fibrinogen, D-dimer), and subclinical atherosclerosis (coronary artery calcium, carotid intima-media thickness, carotid plaque, and ankle-brachial index). Utilizing multivariate regression models and restricted cubic splines, we assessed associations of smoking status, intensity, pack-years, time since cessation, and subclinical markers. RESULTS: A total of 15.3% of participants currently smoke (mean 16.7 cigarettes/day, mean 30.0 pack-years), and 34.6% of participants formerly smoked (median 19.0 years since quitting, mean 22.4 pack-years). Participants with a history of smoking showed higher levels of all subclinical markers compared with those who have never smoked, with stronger associations observed in those currently smoke. Among participants who currently smoke, smoking intensity showed a clear dose-response relationship with all markers, except for D-dimer, specifically with incremental 1% to 9% higher levels of subclinical markers per 10 cigarettes. After 20 cigarettes, the patterns appeared to plateau for blood markers, while they continued to increase for atherosclerosis markers. Among those who have ever smoked, robust dose-response relationships were observed for pack-years with all subclinical markers, with incremental 1% to 9% higher levels per 10 pack-years. The dose-response effects persisted after 20 pack-years for all markers, though with a milder slope. Among participants who smoked formerly, there were substantially lower levels of biomarkers with longer time since quitting, and most markers were not different compared with those who have never smoked by 30 years, except for the coronary artery calcium score, which remained 19% higher even beyond quitting after 30 years. CONCLUSIONS: Smoking-relevant parameters show strong and dose-response relationships across 3 domains of subclinical markers of cardiovascular harm. The sensitivity of the tested subclinical markers to small increments in cigarette exposure suggests potential value in the regulation of new and existing tobacco products.
Keywords: Aged; Atherosclerosis; Biomarkers; Cardiovascular Diseases; Carotid Intima-Media Thickness; Cigarette Smoking; Cohort Studies; Female; Humans; Male; Middle Aged; Risk Factors

Cardiac Troponins and Cardiovascular Disease Risk Prediction: An Individual-Participant-Data Meta-Analysis. - Shah, Anoop S V; Keene, Spencer J; Pennells, Lisa; Kaptoge, Stephen; Kimenai, Dorien M; Walker, Matthew; Halley, Julianne D; Rocha, Sara; Hoogeveen, Ron C; Gudnason, Vilmundur; Bakker, Stephan J L; Wannamethee, Sasiwarang G; et al. (J Am Coll Cardiol, 2025)
BACKGROUND: The extent to which high-sensitivity cardiac troponin can predict cardiovascular disease (CVD) is uncertain. OBJECTIVES: We aimed to quantify the potential advantage of adding information on cardiac troponins to conventional risk factors in the prevention of CVD. METHODS: We meta-analyzed individual-participant data from 15 cohorts, comprising 62,150 participants without prior CVD. We calculated HRs, measures of risk discrimination, and reclassification after adding cardiac troponin T (cTnT) or I (cTnI) to conventional risk factors. The primary outcome was first-onset CVD (ie, coronary heart disease or stroke). We then modeled the implications of initiating statin therapy using incidence rates from 2.1 million individuals from the United Kingdom. RESULTS: Among participants with cTnT or cTnI measurements, 8,133 and 3,749 incident CVD events occurred during a median follow-up of 11.8 and 9.8 years, respectively. HRs for CVD per 1-SD higher concentration were 1.31 (95% CI: 1.25-1.37) for cTnT and 1.26 (95% CI: 1.19-1.33) for cTnI. Addition of cTnT or cTnI to conventional risk factors was associated with C-index increases of 0.015 (95% CI: 0.012-0.018) and 0.012 (95% CI: 0.009-0.015) and continuous net reclassification improvements of 6% and 5% in cases and 22% and 17% in noncases. One additional CVD event would be prevented for every 408 and 473 individuals screened based on statin therapy in those whose CVD risk is reclassified from intermediate to high risk after cTnT or cTnI measurement, respectively. CONCLUSIONS: Measurement of cardiac troponin results in a modest improvement in the prediction of first-onset CVD that may translate into population health benefits if used at scale.
Keywords: Biomarkers; Cardiovascular Diseases; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Risk Assessment; Risk Factors; Troponin I; Troponin T

Cardiovascular Risk Factors and Genetic Risk in Transthyretin V142I Carriers. - Shetty, Naman S; Gaonkar, Mokshad; Pampana, Akhil; Patel, Nirav; Morrison, Alanna C; Reiner, Alexander P; Carson, April P; Yu, Bing; Psaty, Bruce M; Kooperberg, Charles; Fatkin, Diane; Boerwinkle, Eric; et al. (JACC Heart Fail, 2025)
BACKGROUND: Nearly 3% to 4% of Black individuals in the United States carry the transthyretin V142I variant, which increases their risk of heart failure. However, the role of cardiovascular (CV) risk factors (RFs) in influencing the risk of clinical outcomes among V142I variant carriers is unknown. OBJECTIVES: This study aimed to assess the impact of CV RFs on the risk of heart failure in V142I carriers. METHODS: This study included self-identified Black individuals without prevalent heart failure from 6 TOPMed (Trans-Omics for Precision Medicine) cohorts, the REGARDS (Reasons for Geographic And Racial Differences in Stroke) study, and the All of Us Research Program. The cohort was stratified based on the V142I genotype and the number of CV RFs (hypertension, diabetes, obesity, and hypercholesterolemia). Adjusted Cox models were used to assess the association of heart failure with the V142I genotype and CV RF profile, taking noncarriers with a favorable CV RF profile as reference. RESULTS: The cross-sectional analysis, including 1,625 V142I carriers among 48,365 Black individuals, found that the prevalence of CV RFs did not vary by V142I carrier status. In the longitudinal analysis, there were 587 (3.2%) V142I carriers among 18,407 Black individuals (median age: 60 years [Q1-Q3: 52-68 years], 63.0% female). Among carriers, the heart failure risk was attenuated with a favorable (0 or 1 RF) CV RF profile (adjusted HR: 2.26; 95% CI: 1.58-3.23) compared with an unfavorable (3 or 4 RFs) CV RF profile (adjusted HR: 4.14; 95% CI: 2.79-6.14). CONCLUSIONS: A favorable CV RF profile lowers but does not abrogate V142I variant-associated heart failure risk. This study highlights the importance of having a favorable CV RF profile among V142I carriers for risk reduction of heart failure.
Keywords: Aged; Black or African American; Cardiovascular Diseases; Cross-Sectional Studies; Diabetes Mellitus; Female; Genotype; Heart Disease Risk Factors; Heart Failure; Heterozygote; Humans; Hypercholesterolemia; Hypertension; Male; Middle Aged; Obesity; Prealbumin; Risk Factors; United States

Circulating non-esterified fatty acids, risk of dementia and cognitive decline: The cardiovascular health study and multi-ethnic study of atherosclerosis. - Moseholm, Kristine F; Jensen, Majken K; Bůzková, Petra; Aroner, Sarah A; Fitzpatrick, Annette L; Longstreth, W T; Lopez, Oscar; Siscovick, David S; Kizer, Jorge R; Ix, Joachim H; Hughes, Timothy M; Hayden, Kathleen M; et al. (Neurobiol Aging, 2025)
Circulating non-esterified fatty acids (NEFAs) have toxic effects on a variety of organs central to cardiometabolic disease and can cross the blood-brain barrier. Whether NEFAs associate with cognitive decline or dementia remains unknown. Circulating total NEFA levels were measured in 3242 participants without dementia among older adults of the Cardiovascular Health Study (CHS) and related to adjudicated dementia over 6 years (n = 456 cases) and annually assessed cognitive decline. For confirmation, we related circulating NEFAs to cognition assessed 10 years later among 4361 participants in the Multi-Ethnic Study of Atherosclerosis (MESA). In CHS participants, each SD higher NEFA levels were associated with a hazard ratio (HR) for all-cause dementia of 1.11 (95 % CI: 1.01; 1.22). Baseline NEFA levels were also associated with more rapid decline in cognition over 6 years of follow-up. In MESA, circulating NEFA measurements were associated with lower cognitive scores measured 10 years later.'
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognitive Dysfunction; Cohort Studies; Dementia; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Humans; Male; Middle Aged; Risk; Risk Factors

Low Lung Function Is Associated with High Population Attributable Fraction for Cardiovascular Mortality. - Bhatt, Surya P; Wu, Chaoqi; Sun, Yifei; Balte, Pallavi P; Schwartz, Joseph E; Divo, Miguel J; Jaeger, Byron C; Chaves, Paulo H; Couper, David; Jacobs, David R; Lloyd-Jones, Donald; Kalhan, Ravi; et al. (Ann Am Thorac Soc, 2025)
Chronic lung diseases are associated with increased risk of mortality due to coronary heart disease (CHD). Nonetheless, the population attributable fraction (PAF) of lung function impairment relative to other established cardiovascular risk factors is unclear. To evaluate the PAF of low lung function for CHD mortality We harmonized and pooled lung function and clinical data across eight U.S. general population cohorts. Impaired lung function was defined as forced expiratory volume in 1 second (FEV) and/or forced vital capacity ≤ 95% predicted on baseline spirometry. The association between CHD mortality and risk factors was assessed using cause-specific proportional hazards and Fine-Gray proportional subdistribution hazard models, treating non-CHD mortality as a competing risk. Models were adjusted for lung function as well as age, sex, race/ethnicity, educational attainment, body mass index, smoking status, pack-years of smoking, diabetes mellitus, high-density lipoprotein, and high low-density lipoprotein (≥130 mg/dl). PAF was calculated as the relative change in the average absolute risk of 10-year CHD mortality by elimination of lung function lower than 95% predicted. Among 35,143 participants, 1,844 of 13,174 (14.0%) deaths were due to CHD. Compared with percentage predicted FEV (FEVpp) > 95%, the subdistribution adjusted hazard ratio for low FEVpp was 1.30 (95% confidence interval, 1.18-1.44). The PAF for FEVpp ≤ 95% was 12%, ranking low FEV third on the list of PAF for CHD mortality, after hypertension and diabetes. Low FEVpp ranked second in the subgroup of active smokers (PAF 14%), after hypertension. Low lung function, even in the range considered clinically normal, ranks high on the list of attributable risk factors for CHD mortality and should be considered in cardiovascular risk stratification.
Keywords: Adult; Aged; Coronary Disease; Female; Forced Expiratory Volume; Humans; Lung; Lung Diseases; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Smoking; Spirometry; United States; Vital Capacity

Meta-analysis of genome-wide associations and polygenic risk prediction for atrial fibrillation in more than 180,000 cases. - Roselli, Carolina; Surakka, Ida; Olesen, Morten S; Sveinbjornsson, Gardar; Marston, Nicholas A; Choi, Seung Hoan; Holm, Hilma; Chaffin, Mark; Gudbjartsson, Daniel; Hill, Matthew C; Aegisdottir, Hildur; Albert, Christine M; et al. (Nat Genet, 2025)
Atrial fibrillation (AF) is the most common heart rhythm abnormality and is a leading cause of heart failure and stroke. This large-scale meta-analysis of genome-wide association studies increased the power to detect single-nucleotide variant associations and found more than 350 AF-associated genetic loci. We identified candidate genes related to muscle contractility, cardiac muscle development and cell-cell communication at 139 loci. Furthermore, we assayed chromatin accessibility using assay for transposase-accessible chromatin with sequencing and histone H3 lysine 4 trimethylation in stem cell-derived atrial cardiomyocytes. We observed a marked increase in chromatin accessibility for our sentinel variants and prioritized genes in atrial cardiomyocytes. Finally, a polygenic risk score (PRS) based on our updated effect estimates improved AF risk prediction compared to the CHARGE-AF clinical risk score and a previously reported PRS for AF. The doubling of known risk loci will facilitate a greater understanding of the pathways underlying AF.
Keywords: Atrial Fibrillation; Chromatin; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Multifactorial Inheritance; Myocytes, Cardiac; Polymorphism, Single Nucleotide; Risk Factors

Selected social and lifestyle correlates of brain health markers: the Cross-Cohort Collaboration Consortium. - Grasset, Leslie; Bis, Joshua C; Frenzel, Stefan; Kojis, Daniel; Simino, Jeannette; Yaqub, Amber; Beiser, Alexa; Berr, Claudine; Bressler, Jan; Bülow, Robin; DeCarli, Charles S; Fohner, Alison E; et al. (Alzheimers Dement, 2025)
INTRODUCTION: To investigate the associations of education level, marital status, and physical activity with dementia risk and brain MRI markers. METHODS: Data from six community-based samples from the Cross-Cohort Collaboration Consortium were analyzed. Self-reported education level, marital status, and physical activity at age 60 to 75 years were harmonized. Subsamples of participants with brain MRI markers at time of exposure were selected. Associations with dementia risk and cross-sectional MRI markers were meta-analyzed. RESULTS: Higher education level was associated with lower dementia risk (hazard ratio [HR] = 0.65, 95% confidence interval [CI] = 0.59; 0.72 vs low level) but not significantly with brain MRI markers. Compared with being unmarried, being married was only associated with higher total brain and hippocampal volumes. Being physically active was associated with lower dementia risk (HR = 0.73, 95% CI = 0.52; 1.04), as well as larger total brain volume and smaller white matter hyperintensity volume. DISCUSSION: This study provides further evidence regarding the contribution of education level and physical activity to dementia resilience. HIGHLIGHTS: Education level, marital status, and physical activity are thought to contribute to resilience against ADRD. We used random-effects meta-analysis to summarize results from six community-based samples from the CCC. In this cross-cohort meta-analysis, higher education level and being physically active were associated with lower risk of dementia. In cross-sectional analyses, being married was associated with larger TBV and HV, while being physically active was associated with larger TBV and lower WMHV.
Keywords: Aged; Brain; Cohort Studies; Cross-Sectional Studies; Dementia; Educational Status; Exercise; Female; Humans; Life Style; Magnetic Resonance Imaging; Male; Marital Status; Middle Aged; Risk Factors

Sequencing in over 50,000 cases identifies coding and structural variation underlying atrial fibrillation risk. - Choi, Seung Hoan; Jurgens, Sean J; Xiao, Ling; Hill, Matthew C; Haggerty, Christopher M; Sveinbjörnsson, Garðar; Morrill, Valerie N; Marston, Nicholas A; Weng, Lu-Chen; Pirruccello, James P; Arnar, David O; Gudbjartsson, Daniel Fannar; et al. (Nat Genet, 2025)
Atrial fibrillation (AF) is a prevalent and morbid abnormality of the heart rhythm with a strong genetic component. Here, we meta-analyzed genome and exome sequencing data from 36 studies that included 52,416 AF cases and 277,762 controls. In burden tests of rare coding variation, we identified novel associations between AF and the genes MYBPC3, LMNA, PKP2, FAM189A2 and KDM5B. We further identified associations between AF and rare structural variants owing to deletions in CTNNA3 and duplications of GATA4. We broadly replicated our findings in independent samples from MyCode, deCODE and UK Biobank. Finally, we found that CRISPR knockout of KDM5B in stem-cell-derived atrial cardiomyocytes led to a shortening of the action potential duration and widespread transcriptomic dysregulation of genes relevant to atrial homeostasis and conduction. Our results highlight the contribution of rare coding and structural variants to AF, including genetic links between AF and cardiomyopathies, and expand our understanding of the rare variant architecture for this common arrhythmia.
Keywords: Atrial Fibrillation; Case-Control Studies; Exome Sequencing; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Myocytes, Cardiac; Risk Factors